Temporary Territories and Persistent Places: A Bioarchaeological Evaluation of the Association between Monumentality and Territoriality for Foraging Societies of the Prehistoric Ohio Valley - Seidel, Andrew Colin; Carr, Christopher; Stojanowski, Christopher M; Buikstra, Jane E; Aguilera, Miguel (Temporary Territories and Persistent Places: A Bioarchaeological Evaluation of the Association between Monumentality and Territoriality for Foraging Societies of the Prehistoric Ohio Valley)
Federal legislation prioritizes the repatriation of culturally unidentifiable human remains to federally-recognized Indian tribes that are linked geographically to the region from which the remains were removed. Such linkages are typically based on a Eurocentric notion of the exclusive use and occupancy of an area of land - a space-based approach to land use. Contemporary collaborations between anthropologists and indigenous communities suggest, however, that indigenous patterns of land use are better characterized as place-based and are therefore more complex and fluid than is reflected in current legislation. Despite these insights, space-based approaches remain common within archaeology. One example is the inference of territorial behavior from the presence of monuments within the archaeological record. Drawing on osteological and mortuary data derived from a sample of Adena mounds located in northern Kentucky, this dissertation adopts a place-based approach in order to evaluate the archaeological association between monumentality and territoriality. The relative amounts of skeletal and phenotypic variability present at various spatial scales are quantified and compared and the degree to which mortuary and phenotypic data exhibit spatial structure consistent with the expectations of an isolation-by-distance model is assessed. Results indicate that, while burial samples derived from some mounds exhibit amounts of phenotypic variability that are consistent with the expectations of a territorial model, data from other mounds suggest that multiple groups participated in their construction. Further, the general absence of spatial structure within the phenotypic data suggests that the individuals interred in these mounds are perhaps better characterized as representing an integrated regional population rather than localized groups. Untested archaeological inferences of territoriality may therefore mischaracterize regional population dynamics. In addition, these results suggest that the prioritization criteria for the repatriation of culturally unidentifiable human remains may merit revision.
Doctoral Dissertation Anthropology 2019
Keywords: Adena; Archaeology; Biodistance; Kentucky; Mortuary Practices; Physical anthropology

Controls on the Respiration of Ancient Carbon Draining From Permafrost Soils Into Sunlit Arctic Surface Waters - Rieb, E. C.; Polik, C. A.; Ward, C. P.; Kling, G. W.; Cory, R. M. (Journal of Geophysical Research: Biogeosciences, 2024)
The thawing of ancient organic carbon stored in arctic permafrost soils, and its oxidation to carbon dioxide (CO2, a greenhouse gas), is predicted to amplify global warming. However, the extent to which organic carbon in thawing permafrost soils will be released as CO2 is uncertain. A critical unknown is the extent to which dissolved organic carbon (DOC) from thawing permafrost soils is respired to CO2 by microbes upon export of freshly thawed DOC to both dark bottom waters and sunlit surface waters. In this study, we quantified the radiocarbon age and 13C composition of CO2 produced by microbial respiration of DOC that was leached from permafrost soils and either kept in the dark or exposed to ultraviolet and visible wavelengths of light. We show that permafrost DOC most labile to microbial respiration was as old or older (ages 4,000–11,000 a BP) and more 13C-depleted than the bulk DOC in both dark and light-exposed treatments, likely indicating respiration of old, 13C-depleted lignin and lipid fractions of the permafrost DOC pool. Light exposure either increased, decreased, or had no effect on the magnitude of microbial respiration of old permafrost DOC relative to respiration in the dark, depending on both the extent of DOC oxidation during exposure to light and the wavelength of light. Together, these findings suggest that photochemical changes affecting the lability of permafrost DOC during sunlight exposure are an important control on the magnitude of microbial respiration of permafrost DOC in arctic surface waters.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2023JG007853
Keywords: Arctic; dissolved organic carbon; permafrost; photochemistry; radiocarbon; respiration

Evaluating middle to late Holocene climate variability from δ18O of aquatic invertebrate remains in southwestern Greenland - Edgerton, Briana A.; Axford, Yarrow; Chipman, Melissa L. (Quaternary Science Reviews, 2024)
Holocene paleotemperature records from ice-free margins of Greenland suggest spatiotemporal heterogeneity in the timing of key climate transitions following retreat of the Greenland Ice Sheet. However, the paucity of high-resolution climate records from this region limits our understanding of the timing, spatial variation, and drivers of Holocene climate variability. Here, we present a middle to late Holocene climate reconstruction based on δ18O of aquatic invertebrate (chironomid and cladoceran) remains and sediment geochemistry from lake sediments to elucidate millennial to submillennial-scale drivers of climate in southwestern Greenland. We establish that our site, Arrowhead Lake, is a through-flowing basin with an integrated signal of annual meteoric water with no evidence of significant evaporative enrichment. Core sediment geochemistry captures the transition from minerogenic-dominated to organic-rich sediments ∼8 cal ka BP. Chitin-based δ18O measurements of both chironomid head capsules and ephippia exhibit similar temporal variability through the record, broadly decreasing from 8.2 cal ka BP to present, concurrent with decreasing summer insolation and regional Neoglacial cooling. A simplified assumption that temperature is the sole driver of changes in isotopes of precipitation yields an estimated average temperature change from the middle to late Holocene at Arrowhead Lake of 2.1–3.0 °C, comparable to existing estimates of middle to late Holocene temperature decline in western Greenland. Depleted δ18O values after 3.3 cal ka BP correspond to the onset of Neoglacial cooling and independent evidence for a slowdown of the West Greenland Current, and suggests that both temperature and sea-ice variability were important controls on isotopic variability at this site. Highly depleted isotopic values at 8.2 cal ka BP followed by high isotopic variability in the early part of the middle Holocene suggests that our record may capture regional 8.2 ka cooling. This new isotope record provides insight into climate influences during the middle and late Holocene along the western Greenland margin that are important for understanding how ongoing melt of the Greenland Ice Sheet and amplified warming in the Arctic may impact the climate system.
Keywords: Chitin; Greenland; Holocene; paleoclimatology; Stable isotopes; δO

Updated chronology for Peoria Silt (loess) accumulation in Illinois and western Indiana from radiocarbon dating of terrestrial gastropod shells - Grimley, David A.; Loope, Henry M.; Jacobs, Peter M.; Nash, T. Andrew; Dendy, Sarah N.; Conroy, Jessica L.; Curry, B. Brandon (Quaternary Research, 2024)
Based on calibrated radiocarbon ages of terrestrial gastropod shells (Succineidae, Discus, Stenotrema, Webbhelix), the chronology of Peoria Silt (loess) deposition in the Central Lowlands is updated. These taxa provide reliable ages (within ~0.2 ka), based on historical shell dating, shell-organic age comparisons, and stratigraphic consistency. A compilation of 53 new and 36 published Peoria Silt shell ages (calibrated), from 12 localities, date from 30.0 to 17.4 ka. Proximal (fossiliferous) loess from 10 sections had mean loess accumulation rates of 0.6–2.2 mm/yr. Study sites along the upper Mississippi, Illinois, to mid-Mississippi, and Ohio-Wabash Valleys suggest Peoria loess accumulated from ~27 to 15 ka, ~29 to 18 ka, and ~30 to 18 ka, respectively. The cessation age for Peoria Silt, based on surface extrapolations, is ~1–6 ka earlier than some prior Illinois estimates, even assuming slower loess accumulation in the modern solum. Younger loess in northwestern Illinois likely reflects, in part, Superior and Des Moines Lobe glacial-meltwater sediment, and Iowan Erosion Surface inputs to the upper Mississippi Valley, after the Lake Michigan Lobe receded. Furthermore, stronger winds, drier conditions, and reduced vegetation cover in valley deflation areas may have favored higher accumulation rates and later loess deposition in northwestern relative to southeastern areas.
Keywords: chronology; Illinois; Indiana; Kentucky; Last Glacial; Loess; Peoria Silt; radiocarbon; Succineidae; Wisconsin Episode

Comparability of Radiocarbon Measurements in Dissolved Inorganic Carbon of Seawater Produced at ETH-Zurich - Castrillejo, Maxi; Hansman, Roberta L.; Graven, Heather D.; Lester, Joanna G.; Bollhalder, Silvia; Kündig, Kayley; Wacker, Lukas (Radiocarbon, 2023)
Radiocarbon observations (Δ14C) in dissolved inorganic carbon (DIC) of seawater provide useful information about ocean carbon cycling and ocean circulation. To deliver high-quality observations, the Laboratory of Ion Beam Physics (LIP) at ETH-Zurich developed a new simplified method allowing the rapid analysis of radiocarbon in DIC of small seawater samples, which is continually assessed by following internal quality controls. However, a comparison with externally produced 14C measurements to better establish an equivalency between methods was still missing. Here, we make the first intercomparison with the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility based on 14 duplicate seawater samples collected in 2020. We also compare with prior deep-water observations from the 1970s to 1990s. The results show a very good agreement in both comparisons. The mean Δ14C of 12 duplicate samples measured by LIP and NOSAMS were statistically identical within one sigma uncertainty while two other duplicate samples agreed within two sigma. Based on this small number of duplicate samples, LIP values appear to be slightly lower than the NOSAMS values, but more measurements will be needed for confirmation. We also comment on storage and preservation techniques used in this study, including the freezing of samples collected in foil bags.
Publisher: Cambridge University Press
Keywords: 14C; comparison; DIC; dissolved inorganic carbon; radiocarbon; SEAWATER

Comparing the isotopic and molecular composition of dissolved organic carbon between the oligotrophic South China Sea and the adjacent North Pacific Ocean: Signals of biodegradation, conservative mixing, and terrestrial input - Jiang, Peng; Chen, Hongmei; Liu, Zhanfei; Li, Xiaolin (Marine Chemistry, 2023)
The cycling of oceanic dissolved organic carbon (DOC) is a crucial component of the global carbon cycle, yet the identification of sources and the mechanisms of its molecular transformation remain poorly understood. This study compared the isotopic and molecular composition of DOC between the oligotrophic South China Sea (SCS) and the adjacent North Pacific Ocean (NPO), and traced both its allochthonous and autochthonous sources as well as its dynamic cycling processes. DOC was collected through solid-phase extraction (SPE) from water samples of both the SCS and NPO. Carbon content, isotopic ratios, and high-resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) measurements revealed that SPE-DOC contained both labile and refractory fractions. According to our mass balance model, the labile fraction of SPE-DOC exhibited a decline from 11.5 to 12.6 μM in surface waters to a negligible concentration below 1000 m. Conversely, the refractory fraction of SPE-RDOC maintained a relatively consistent value, ranging from 12.7 to 19.0 μM across the entire water column. The vertical distribution patterns of the molecular composition and carbon isotopic ratios jointly indicated that the DOC distributions are shaped by distinct biological and physical processes within different biogeochemical realms of the water column. The production and transformation of the relatively labile DOC fractions were the dominant processes in the epipelagic and mesopelagic zones (upper 1000 m). The extent of diapycnal mixing between the SCS and NPO explained the different vertical distributions of refractory DOC molecules in the bathypelagic oceans. The molecular indices of polyphenol compounds, aromaticity, double bond saturation state, terrestrial mass peaks, and δ13C ratios of SPE-DOC indicated contributions from terrestrial sources, likely riverine input, in the SCS. This study sheds light on the molecular evidence of DOC sources, as well as their transformation and conservative mixing processes along the overturning circulation in marginal seas.
Keywords: carbon isotopes; dissolved organic carbon; FT-ICR-MS; North pacific ocean; radiocarbon; south china sea

Earthquake-enhanced dissolved carbon cycles in ultra-deep ocean sediments - Chu, Mengfan; Bao, Rui; Strasser, Michael; Ikehara, Ken; Everest, Jez; Maeda, Lena; Hochmuth, Katharina; Xu, Li; McNichol, Ann; Bellanova, Piero; Rasbury, Troy; Kölling, Martin; et al. (Nature Communications, 2023)
Hadal trenches are unique geological and ecological systems located along subduction zones. Earthquake-triggered turbidites act as efficient transport pathways of organic carbon (OC), yet remineralization and transformation of OC in these systems are not comprehensively understood. Here we measure concentrations and stable- and radiocarbon isotope signatures of dissolved organic and inorganic carbon (DOC, DIC) in the subsurface sediment interstitial water along the Japan Trench axis collected during the IODP Expedition 386. We find accumulation and aging of DOC and DIC in the subsurface sediments, which we interpret as enhanced production of labile dissolved carbon owing to earthquake-triggered turbidites, which supports intensive microbial methanogenesis in the trench sediments. The residual dissolved carbon accumulates in deep subsurface sediments and may continue to fuel the deep biosphere. Tectonic events can therefore enhance carbon accumulation and stimulate carbon transformation in plate convergent trench systems, which may accelerate carbon export into the subduction zones., Earthquakes enhance dissolved carbon production and fuel the microbial activities in hadal trench subsurface sediments, and ultimately strengthen carbon accumulation and transformation in the subduction zones.

Independent age estimates resolve the controversy of ancient human footprints at White Sands - Pigati, Jeffrey S.; Springer, Kathleen B.; Honke, Jeffrey S.; Wahl, David; Champagne, Marie R.; ZIMMERMAN, SUSAN R. H.; Gray, Harrison J.; Santucci, Vincent L.; Odess, Daniel; Bustos, David; Bennett, Matthew R. (Science, 2023)
Human footprints at White Sands National Park, New Mexico, USA, reportedly date to between ~23,000 and 21,000 years ago according to radiocarbon dating of seeds from the aquatic plant Ruppia cirrhosa. These ages remain controversial because of potential old carbon reservoir effects that could compromise their accuracy. We present new calibrated 14C ages of terrestrial pollen collected from the same stratigraphic horizons as those of the Ruppia seeds, along with optically stimulated luminescence ages of sediments from within the human footprint–bearing sequence, to evaluate the veracity of the seed ages. The results show that the chronologic framework originally established for the White Sands footprints is robust and reaffirm that humans were present in North America during the Last Glacial Maximum.
Publisher: American Association for the Advancement of Science

Lake Dynamics Modulate the Air Temperature Variability Recorded by Sedimentary Aquatic Biomarkers: A Holocene Case Study From Western Greenland - Cluett, A. A.; Thomas, E. K.; McKay, N. P.; Cowling, O. C.; Castañeda, I. S.; Morrill, C. (Journal of Geophysical Research: Biogeosciences, 2023)
Quantitative temperature reconstructions from lacustrine organic geochemical proxies including branched glycerol dialkyl glycerol tetraethers (brGDGTs) and alkenones provide key constraints on past continental climates. However, estimation of air temperatures from proxies can be impacted by non-stationarity in the relationships between seasonal air and water temperatures, a factor not yet examined in strongly seasonal high-latitude settings. We pair downcore analyses of brGDGTs and alkenones measured on the same samples through the Holocene with forward-modeled proxy values based on thermodynamic lake model simulations for a western Greenland lake. The measured brGDGT distributions suggest that stable autochthonous (aquatic) production overpowers allochthonous inputs for most samples, justifying the use of the lake model to interpret temperature-driven changes. Conventional calibration of alkenones (detected only after 5.5 thousand years BP) suggests substantially larger temperature variations than conventional calibration of brGDGTs. Comparison of proxy measurements to forward-modeled values suggests variations in brGDGT distributions monotonically reflect multi-decadal summer air temperatures changes, although the length of the ice-free season dampens the influence of air temperatures on water temperatures. Drivers of alkenone variability remain less clear; potential influences include small changes in the seasonality of proxy production or biases toward specific years, both underlain by non-linearity in water-air temperature sensitivity during relevant seasonal windows. We demonstrate that implied temperature variability can differ substantially between proxies because of differences in air-water temperature sensitivity during windows of proxy synthesis without necessitating threshold behavior in the lake or local climate, and recommend that future studies incorporate lake modeling to constrain this uncertainty.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022JG007106
Keywords: Alkenone; Arctic; biogeochemical proxies; brGDGT; data-model comparison; proxy system modeling

New insights on black carbon in pelagic Atlantic sediments - St.Laurent, Kari; Cantwell, Mark; Lohmann, Rainer (Marine Chemistry, 2023)
Black carbon (BC) is ubiquitous in pelagic sediments and presumed to have an older radiocarbon age due to long ocean residence times and pre-aging in terrestrial soils. Here, we analyzed sediments from five regions in the subtropical Atlantic Ocean to quantify the black carbon fraction of the total organic carbon pool. Black carbon, derived from the chemothermal oxidation method, comprised between 17 ± 6% of the sedimentary organic carbon in the Northwest Argentina Basin and 65 ± 18% in the Amazon Delta. Black carbon sediment accumulation rates were six times greater in the Sierra Leone Rise (8.4 ± 4.1 mg cm−2 kyr−1) compared to the remote Northwest Argentina Basin (1.3 ± 0.4 mg cm−2 kyr−1), possibly due to enhanced regional atmospheric deposition from annual African grassland fires. The radiocarbon age for BC from subtropical Atlantic sediments were more modern compared to the bulk total organic carbon, and BC source was apportioned as biomass burning byproducts from their stable carbon isotopic signatures and characteristic ratios of polycyclic aromatic hydrocarbons. This study demonstrated that subtropical Atlantic Ocean sediments serve as an important sink for young BC.
Keywords: Atlantic Ocean; BLACK CARBON; Polycyclic aromatic hydrocarbons; radiocarbon; sediments

Organic carbon and planktic foraminifera radiocarbon derived Holocene sediment accumulation rates in the northern slopes of the Gulf of Mexico - Schwing, Patrick; Chanton, Jeffrey; Bosman, Samantha; Brooks, Gregg; Larson, Rebekka A.; Romero, Isabel; Diercks, Arne (Deep Sea Research Part I: Oceanographic Research Papers, 2023)
In the context of climate regulation and anthropogenic waste detoxification (e.g. oil spills), estimates of deep ocean sedimentation and carbon sequestration are of the utmost importance. Radiocarbon (14C) is a common radioisotope that can be used to establish millennial scale sediment accumulation rates. The objectives of this study were to: 1) establish ages for co-occurring total organic carbon (TOC) and planktic foraminifera (carbonate) in the northeastern Gulf of Mexico (GoM), 2) use these ages to estimate accumulation rates independently, 3) identify any evidence of redistribution, and 4) examine any offset between TOC and carbonate 14C ages as a tool to potentially identify selective TOC transport. Sediment samples were collected in May 2018 from the RV Point Sur using an Ocean Instruments MC-800 multi corer. Radiocarbon measurements of both planktic foraminifera and TOC subsamples were made at the National Ocean Science Accelerator Mass Spectrometry Facility (NOSAMS). Radiocarbon ages, calibrated using the OxCal 4.4, ranged from recent to 6407 BP. Linear (LAR: 4–24 cm/kyr) and mass accumulation rates (MAR: 1.5–11.5 g/cm2/kyr) were generally consistent with those reported by other recent studies in the GoM. At two sites, C14 ages decreased from the surface to the second sampling increment which was consistent with sediment redistribution. The TOC-carbonate offsets, which are indicative of lateral advection and organic matter aging, were lower than those found in the majority of other regions, which was consistent with less lateral transport or a more oligotrophic setting. The magnitude in radiocarbon age offsets with depth could potentially be used as a relative aging or transport assessment tool in areas with little resuspension.
Keywords: accumulation rates; Foraminifera; Gulf of Mexico; radiocarbon; Radiogeochemistry

Sequential thermal analysis of complex organic mixtures: Procedural standards and improved CO2 purification capacity - Hanke, Ulrich M.; Gagnon, Alan R.; Reddy, Christopher M.; Gaylord, Mary C. Lardie; Cruz, Anne J.; Galy, Valier; Hansman, Roberta L.; Kurz, Mark D. (Radiocarbon, 2023)
Sequential thermal analysis allows for deconvoluting the refractory nature and complexity of carbon mixtures embedded in mineral matrices for subsequent offline stable carbon and radiocarbon (14C) isotope analyses. Originally developed to separate Holocene from more ancient sedimentary organic matter to improve dating of marine sediments, the Ramped Pyrolysis and Oxidation (RPO) apparatus, or informally, the “dirt burner” is now used to address pressing questions in the broad field of biogeochemistry. The growing interest in the community now necessitates improved handling and procedures for routine analyses of difficult sample types. Here we report on advances in CO2 purification during sample processing, modifications to the instrumentation at the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility, and introduce sodium bicarbonate procedural standards with differing natural abundance 14C signatures for blank assessment. Measurements from different environmental samples are used to compare the procedure to the different generations of sequential thermal analyses. With this study, we aim to improve the standardization of the procedures and prepare this instrumentation for innovations in online stable carbon isotopes and direct AMS-interface measurements in the future.
Publisher: Cambridge University Press
Keywords: chemical analysis; dirt burner; full oxidation (FOX) mode; Radiocarbon dating; ramped pyrolysis oxidation

Styles and rates of mesophotic reef accretion on a Caribbean insular slope - Sherman, Clark E.; Carlo, Milton; Tuohy, Evan; Adey, Walter H. (Coral Reefs, 2023)
Structural framework is fundamental to the concept of a coral-algal reef. However, our current understanding of reef framework is based largely upon studies of relatively shallow systems that formed at water depths of less than 30 m. There is comparatively limited information on deeper, mesophotic reef frameworks. Short drill cores collected at depths of ~ 50 m on the steep insular slope of southwest Puerto Rico allow for documentation of the composition and accretion rates of mesophotic reef framework. Framework is dominated by platy agariciid corals (Agaricia spp.) and autochthonous micrite (automicrite) with calcareous algae, corallines and peyssonnelids, forming a secondary component. Conspicuously, well-lithified automicrite constitutes a major structural and volumetric component of the framework. It is composed of magnesian calcite and displays irregular clotted, peloidal and fenestral fabrics, consistent with in situ formation. Radiocarbon ages of corals and automicrite indicate that they have formed recently (< 4 ka) and coevally in their current setting over a period of relative environmental stability. The steep slope gradient and associated dynamic oceanographic conditions may allow for extensive automicrite formation. Mesophotic reef accretion is occurring on the steep slope, though at slow rates of ~ 0.3 m ka−1.
Keywords: Autochthonous micrite (automicrite); Mesophotic coral ecosystem; Reef accretion; Reef framework

A Tropical Cocktail of Organic Matter Sources: Variability in Supraglacial and Glacier Outflow Dissolved Organic Matter Composition and Age Across the Ecuadorian Andes - Holt, Amy D.; Kellerman, Anne M.; Battin, Tom. I.; McKenna, Amy M.; Hood, Eran; Andino, Patricio; Crespo-Pérez, Verónica; Peter, Hannes; Schön, Martina; De Staercke, Vincent; Styllas, Michail; Tolosano, Matteo; et al. (Journal of Geophysical Research: Biogeosciences, 2023)
The biogeochemistry of rapidly retreating Andean glaciers is poorly understood, and Ecuadorian glacier dissolved organic matter (DOM) composition is unknown. This study examined molecular composition and carbon isotopes of DOM from supraglacial and outflow streams (n = 5 and 14, respectively) across five ice capped volcanoes in Ecuador. Compositional metrics were paired with streamwater isotope analyses (δ18O) to assess if outflow DOM composition was associated with regional precipitation gradients and thus an atmospheric origin of glacier DOM. Ecuadorian glacier outflows exported ancient, biolabile dissolved organic carbon (DOC), and DOM contained a high relative abundance (RA) of aliphatic and peptide-like compounds (≥27%RA). Outflows were consistently more depleted in Δ14C-DOC (i.e., older) compared to supraglacial streams (mean −195.2 and −61.3‰ respectively), perhaps due to integration of spatially heterogenous and variably aged DOM pools across the supraglacial environment, or incorporation of aged subglacial OM as runoff was routed to the outflow. Across Ecuador, Δ14C-DOC enrichment was associated with decreased aromaticity of DOM, due to increased contributions of organic matter (OM) from microbial processes or atmospheric deposition of recently fixed and subsequently degraded OM (e.g., biomass burning byproducts). There was a regional gradient between glacier outflow DOM composition and streamwater δ18O, suggesting covariation between regional precipitation gradients and the DOM exported from glacier outflows. Ultimately, this highlights that atmospheric deposition may exert a control on glacier outflow DOM composition, suggesting regional air circulation patterns and precipitation sources in part determine the origins and quality of OM exported from glacier environments.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022JG007188
Keywords: cryosphere; dissolved organic carbon; Dissolved organic matter; Ecuador; FT-ICR MS; glaciers; δ13C-DOC; Δ14C-DOC

Baobabs at the edge: 90-year dynamics of climate variability, growth, resilience, and evolutionary legacy effects - Mayne, Diana H.; Karimi, Nisa; Cruywagen, Elsie M.; Cole, Patrick; Goodall, Victoria (Frontiers in Forests and Global Change, 2022)
Climate variability and resilience remain gaps in tree research, challenged by the interacting factors in climate change, long-term resilience and the influence of evolutionary legacy effects. In a multidisciplinary approach using 90-year (1930–2020) climate-growth data, we investigated the dynamics of climate variability on growth and resilience of the tropical African baobab (Adansonia digitata) at the range edge in climate-variable, southeast Africa. The main driver of climate variability, ENSO (El Niño-Southern Oscillation), triggered 83% of droughts exacerbated by positive Indian Ocean Dipole (pIOD) events. Growth over 90 years was positively correlated with maximum temperature and increased after the 1976–1977 Global Warming Shift. The influence of warming was compromised by climate variability and extreme events. Although growth is a measure of adaptive capacity, accelerated growth over the past 20 years contrasted with dehydration, canopy dieback and a novel Didymella pathogen. Resilience was contingent on high genetic diversity (polyploidy and heterozygosity) and Neotropical legacy effects of stem water storage and longevity trade-offs of low growth, recruitment and reproduction. The evolution of resprouting in disturbed, fire-prone ecosystems and bark regeneration increased recovery from disturbance. As resource opportunists, baobabs adopted a fast-slow survival strategy. Rainfall and warming enhanced growth while low and variable rainfall favoured a conservative, low growth-higher survival strategy. Low rainfall, climate extremes and topography increased mortality risk. Mortality was higher at lower elevations on site and regionally. Low growth may conserve the baobab in climate warming but the southern hemisphere tropics is one of two identified global hotspots with amplified hot years. The heightened disturbance predicted from increased climate variability, hot droughts and landfalling tropical cyclones magnifies mortality risk for “Africa’s favourite tree.”

Black carbon and organic carbon dataset over the Third Pole - Kang, Shichang; Zhang, Yulan; Chen, Pengfei; Guo, Junming; Zhang, Qianggong; Cong, Zhiyuan; Kaspari, Susan; Tripathee, Lekhendra; Gao, Tanguang; Niu, Hewen; Zhong, Xinyue; Chen, Xintong; et al. (Earth System Science Data, 2022)
Abstract. The Tibetan Plateau and its surroundings, also known as the Third Pole, play an important role in the global and regional climate and hydrological cycle. Carbonaceous aerosols (CAs), including black carbon (BC) and organic carbon (OC), can directly or indirectly absorb and scatter solar radiation and change the energy balance on the Earth. CAs, along with the other atmospheric pollutants (e.g., mercury), can be frequently transported over long distances into the inland Tibetan Plateau. During the last decades, a coordinated monitoring network and research program named “Atmospheric Pollution and Cryospheric Changes” (APCC) has been gradually set up and continuously operated within the Third Pole regions to investigate the linkage between atmospheric pollutants and cryospheric changes. This paper presents a systematic dataset of BC, OC, water-soluble organic carbon (WSOC), and water-insoluble organic carbon (WIOC) from aerosols (20 stations), glaciers (17 glaciers, including samples from surface snow and ice, snow pits, and 2 ice cores), snow cover (2 stations continuously observed and 138 locations surveyed once), precipitation (6 stations), and lake sediment cores (7 lakes) collected across the Third Pole, based on the APCC program. These data were created based on online (in situ) and laboratory measurements. High-resolution (daily scale) atmospheric-equivalent BC concentrations were obtained by using an Aethalometer (AE-33) in the Mt. Everest (Qomolangma) region, which can provide new insight into the mechanism of BC transportation over the Himalayas. Spatial distributions of BC, OC, WSOC, and WIOC from aerosols, glaciers, snow cover, and precipitation indicated different features among the different regions of the Third Pole, which were mostly influenced by emission sources, transport pathways, and deposition processes. Historical records of BC from ice cores and lake sediment cores revealed the strength of the impacts of human activity since the Industrial Revolution. BC isotopes from glaciers and aerosols identified the relative contributions of biomass and fossil fuel combustion to BC deposition on the Third Pole. Mass absorption cross sections of BC and WSOC from aerosol, glaciers, snow cover, and precipitation samples were also provided. This updated dataset is released to the scientific communities focusing on atmospheric science, cryospheric science, hydrology, climatology, and environmental science. The related datasets are presented in the form of excel files. BC and OC datasets over the Third Pole are available to download from the National Cryosphere Desert Data Center (https://doi.org/10.12072/ncdc.NIEER.db0114.2021; Kang and Zhang, 2021).

Carbon Accumulation, Flux, and Fate in Stordalen Mire, a Permafrost Peatland in Transition - Holmes, M. E.; Crill, P. M.; Burnett, W. C.; McCalley, C. K.; Wilson, R. M.; Frolking, S.; Chang, K.‐Y.; Riley, W. J.; Varner, R. K.; Hodgkins, S. B.; McNichol, A. P.; Saleska, S. R.; et al. (Global Biogeochemical Cycles, 2022)
Stordalen Mire is a peatland in the discontinuous permafrost zone in arctic Sweden that exhibits a habitat gradient from permafrost palsa, to Sphagnum bog underlain by permafrost, to Eriophorum‐dominated fully thawed fen. We used three independent approaches to evaluate the annual, multi‐decadal, and millennial apparent carbon accumulation rates (aCAR) across this gradient: seven years of direct semi‐continuous measurement of CO2 and CH4 exchange, and 21 core profiles for 210Pb and 14C peat dating. Year‐round chamber measurements indicated net carbon balance of −13 ± 8, −49 ± 15, and −91 ± 43 g C m−2 y−1 for the years 2012–2018 in palsa, bog, and fen, respectively. Methane emission offset 2%, 7%, and 17% of the CO2 uptake rate across this gradient. Recent aCAR indicates higher C accumulation rates in surface peats in the palsa and bog compared to current CO2 fluxes, but these assessments are more similar in the fen. aCAR increased from low millennial‐scale levels (17–29 g C m−2 y−1) to moderate aCAR of the past century (72–81 g C m−2 y−1) to higher recent aCAR of 90–147 g C m−2 y−1. Recent permafrost collapse, greater inundation and vegetation response has made the landscape a stronger CO2 sink, but this CO2 sink is increasingly offset by rising CH4 emissions, dominated by modern carbon as determined by 14C. The higher CH4 emissions result in higher net CO2‐equivalent emissions, indicating that radiative forcing of this mire and similar permafrost ecosystems will exert a warming influence on future climate. Stordalen Mire, a permafrost peatland, has become a stronger carbon sink due to shifts in vegetation and inundation accompanying thaw This stronger carbon sink is offset by an increase in methane emission, resulting in higher net CO2‐equivalent emissions Analysis of respiration products indicates that methane emission from the fen and bog are dominated by modern carbon Stordalen Mire, a permafrost peatland, has become a stronger carbon sink due to shifts in vegetation and inundation accompanying thaw This stronger carbon sink is offset by an increase in methane emission, resulting in higher net CO2‐equivalent emissions Analysis of respiration products indicates that methane emission from the fen and bog are dominated by modern carbon

Comparing paleo-oxygenation proxies (benthic foraminiferal surface porosity, I/Ca, authigenic uranium) on modern sediments and the glacial Arabian Sea - Lu, Wanyi; Wang, Yi; Oppo, Delia W.; Nielsen, Sune G.; Costa, Kassandra M. (Geochimica et Cosmochimica Acta, 2022)
Oceanic oxygen reconstructions of the last glacial period are needed to understand the mechanisms of glacial deep ocean carbon storage and to validate climate model simulations. However, existing bottom-water oxygen (BWO) reconstructions are ambiguous due to limitations of each paleo-BWO proxy. Here we present data on three proxies for BWO: benthic foraminiferal surface porosity, benthic foraminiferal iodine/calcium (I/Ca), and authigenic uranium (aU), from globally distributed core-top samples, and we evaluate the potential advantages and limitations of these BWO proxies on global and regional scales. All three proxies are most sensitive to changes at relatively low BWO concentrations (<∼50 µmol/kg). Data from globally-distributed core tops confirm that foraminiferal surface porosity is correlated with BWO between 0 and 100 µmol/kg. Our analysis further confirms that benthic surface porosity is predominantly controlled directly by BWO rather than other potential functionalities of surface pores such as organic carbon uptake and respiratory CO2 release. Low benthic I/Ca can identify low BWO (<50 µmol/kg), whereas higher benthic I/Ca values are not associated with specific BWO, possibly due to additional dependence of I/Ca on temperature, salinity, carbonate ion concentration, or water mass mixing at higher BWO. The relationship between aU and BWO is regionally dependent. In the Arabian Sea, variable aU enrichments occur only within the Oxygen Minimum Zone (OMZ), driven by high export production and organic matter fluxes to the sediment. Finally, we combine foraminiferal surface porosity, I/Ca and aU to generate the first quantitative glacial-Holocene BWO reconstructions using a sediment core taken from within the modern Arabian Sea OMZ. All three proxies consistently suggest BWO < 50 μmol/kg in the shallow Arabian Sea during the last ∼30 kyr, with relatively higher BWO during the glacial period than the Holocene. A comparison with the benthic carbon isotope gradient proxy (Δδ13C) confirms that Δδ13C over-estimates BWO in low-oxygen settings possibly due to sediment diagenesis impacts. Our study provides new insights on the merits and limitations of these BWO proxies and confirms the importance of multi-proxy reconstructions for more reliable paleo-BWO estimates.
Keywords: 13 Climate Action

The giant 1960 tsunami in the context of a 6000‐year record of paleotsunamis and coastal evolution in south‐central Chile - Matos‐Llavona, Pedro I.; Ely, Lisa L.; MacInnes, Breanyn; Dura, Tina; Cisternas, Marco A.; Bourgeois, Joanne; Bruce, David; DePaolis, Jessica; Dolcimascolo, Alexander; Horton, Benjamin P.; Melnick, Daniel; Nelson, Alan R.; et al. (Earth Surface Processes and Landforms, 2022)
The tsunami associated with the giant 9.5 Mw 1960 Chile earthquake deposited an extensive sand layer above organic‐rich soils near Queule (39.3°S, 73.2°W), south‐central Chile. Using the 1960 tsunami deposits, together with eye‐witness observations and numerical simulations of tsunami inundation, we tested the tsunami inundation sensitivity of the site to different earthquake slip distributions. Stratigraphically below the 1960 deposit are two additional widespread sand layers interpreted as tsunami deposits with maximum ages of 4960–4520 and 5930–5740 cal BP. This >4500‐year gap of tsunami deposits preserved in the stratigraphic record is inconsistent with written and geological records of large tsunamis in south‐central Chile in 1575, 1837, and possibly 1737. We explain this discrepancy by: (1) poor preservation of tsunami deposits due to reduced accommodation space from relative sea‐level fall during the late Holocene; (2) recently evolved coastal geomorphology that increased sediment availability for tsunami deposit formation in 1960; and/or (3) the possibility that the 1960 tsunami was significantly larger at this particular location than other tsunamis in the past >4500 years. Our research illustrates the complexities of reconstructing a complete stratigraphic record of past tsunamis from a single site for tsunami hazard assessment. The coastal geomorphology near Queule, Chile preserves evidence of the giant Mw 9.51960 Chile earthquake and two buried paleotsunami deposits within the last 6000 years. Using the 1960 tsunami deposits, eye‐witness observations, and numerical simulations of tsunami inundation, we tested the sensitivity of the site to different earthquake slip distributions. We consider the role of coastal geomorphic evolution, sea‐level history, and tsunami magnitude in the preservation of paleotsunami depositional records.

Glacial isostatic adjustment near the center of the former Patagonian Ice Sheet (48°S) during the last 16.5 kyr - Troch, Matthias; Bertrand, Sébastien; Lange, Carina B.; Cárdenas, Paola; Arz, Helge; Pantoja-Gutiérrez, Silvio; De Pol-Holz, Ricardo; Kilian, Rolf (Quaternary Science Reviews, 2022)
Our understanding of glacial isostatic rebound across Patagonia is highly limited, despite its importance to constrain past ice volume estimates and better comprehend relative sea-level variations. With this in mind, our research objective is to reconstruct the magnitude and rate of Late Glacial and Holocene glacial isostatic adjustment near the center of the former Patagonian Ice Sheet. We focus on Larenas Bay (48°S; 1.26 km2), which is connected to Baker Channel through a shallow (7.4 m) and narrow (ca. 150 m across) inlet, and hence has the potential to record periods of basin isolation and marine ingression. The paleoenvironmental evolution of the bay was investigated through a sedimentological analysis of a 9.2 m long radiocarbon-dated sediment core covering the last 16.8 kyr. Salinity indicators, including diatom paleoecology, alkenone concentrations and CaCO3 content, were used to reconstruct the bay's connectivity to the fjord. Results indicate that Larenas Bay was a marine environment before 16.5 cal kyr BP and after 9.1 cal kyr BP, but that it was disconnected from Baker Channel in-between. We infer that the postglacial rebound started before 16.5 cal kyr BP and that it outpaced global sea-level rise until slightly before 9.1 cal kyr BP. During the Late Glacial and early Holocene, the center of the former Patagonian Ice Sheet experienced an absolute uplift of ca. 96 m, at an average rate of 1.3 cm/yr. During the remainder of the Holocene, glacial isostatic adjustment continued (ca. 20 m), but at a slower average pace of 0.2 cm/yr. Comparisons between multi-millennial variations in the salinity indicators and existing records of global sea-level rise suggest that the glacial isostatic adjustment rate also fluctuated within these time intervals, likely in response to glacier dynamics. More specifically, most of the glacial isostatic adjustment registered between 16.5 – 9.1 cal kyr BP seems to have occurred before meltwater pulse 1A (14.5 – 14.0 kyr BP). Likewise, it appears that the highest glacial isostatic rebound rates of the last 9.1 kyr occurred during the late Holocene, most likely in response to glacier recession from their Neoglacial maxima. This implies a relatively rapid response of the local solid earth to ice unloading, which agrees with independent modelling studies investigating contemporary uplift. We conclude that the center of the former Patagonian Ice Sheet experienced a glacial isostatic adjustment of ca. 116 m over the last 16.5 kyr, and that >80% occurred during the Late Glacial and early Holocene.

Iberian hydroclimate variability and the Azores High during the last 1200 years: evidence from proxy records and climate model simulations - Thatcher, Diana L.; Wanamaker, A. D.; Denniston, R. F.; Ummenhofer, C. C.; Asmerom, Y.; Polyak, V. J.; Cresswell-Clay, N.; Hasiuk, F.; Haws, J.; Gillikin, D. P. (Climate Dynamics, 2022)
The state of the atmospheric circulation and the associated hydroclimate in the North Atlantic during the last millennium remain the subject of considerable debate in both proxy- and model-based studies. Of particular interest in the Iberian region is the Azores High (AH) system, the southern node of the North Atlantic Oscillation (NAO), an atmospheric dipole closely tied to regional hydroclimate. Hydroclimate-sensitive proxy reconstructions from this region offer some insights into atmospheric dynamics, but large spatiotemporal gaps in these data inhibit a robust evaluation of hydroclimate variability. In this study, we present a continuous, sub-decadally-resolved composite stalagmite carbon isotopic record from three partially overlapping stalagmites from Buraca Gloriosa (BG) cave, western Portugal, situated within the center of the AH, that preserves evidence of regional hydroclimate variability from approximately 800 CE to the present. Chronologies are derived from U/Th dating and annual laminae. Stalagmite carbon isotopic values primarily reflect the amount of effective moisture and reveal generally dry conditions during the Medieval Climate Anomaly (MCA; 850–1250 CE) and Modern Climate/Industrial Era (1850 CE-present), and wetter conditions during the Little Ice Age (LIA; 1400–1850 CE). Multidecadal to centennial variability in the BG record and state-of-the-art last millennium climate model simulations show considerable coherence with precipitation-sensitive records from Spain and Morocco that, like BG, are strongly influenced by the intensity, size, and location of the AH. Model-proxy synthesis suggests that western Portugal was persistently dry during much of the MCA consistent with other NAO reconstructions; however, even considering age uncertainties, the apparent timing in the transition from a relatively dry MCA to a wetter LIA is spatially variable and confirms the non-stationary behavior of the AH system indicated by model output.
Keywords: Azores High; Hydroclimate; last millennium; Last Millennium Ensemble; Paleoclimate; Stalagmite

In-phase millennial-scale glacier changes in the tropics and North Atlantic regions during the HoloceneAbstract - Jomelli, V.; Swingedouw, D.; Vuille, M.; Favier, V.; Goehring, B.; Shakun, J.; Braucher, R.; Schimmelpfennig, I.; Menviel, L.; Rabatel, A.; Martin, L. C. P.; Blard, P.-H.; et al. (Nature Communications, 2022)
Based on new and published cosmic-ray exposure chronologies, we show that glacier extent in the tropical Andes and the north Atlantic regions (TANAR) varied in-phase on millennial timescales during the Holocene, distinct from other regions. Glaciers experienced an early Holocene maximum extent, followed by a strong mid-Holocene retreat and a re-advance in the late Holocene. We further explore the potential forcing of TANAR glacier variations using transient climate simulations. Since the Atlantic Meridional Overturning Circulation (AMOC) evolution is poorly represented in these transient simulations, we develop a semi-empirical model to estimate the “AMOC-corrected” temperature and precipitation footprint at regional scales. We show that variations in the AMOC strength during the Holocene are consistent with the observed glacier changes. Our findings highlight the need to better constrain past AMOC behavior, as it may be an important driver of TANAR glacier variations during the Holocene, superimposed on other forcing mechanisms.

Large fluxes of continental-shelf-borne dissolved organic carbon in the East China Sea and the Yellow Sea - Han, Heejun; Na, Taehee; Cho, Hyung-Mi; Kim, Guebuem; Hwang, Jeomshik (Marine Chemistry, 2022)
Fluxes of dissolved organic carbon (DOC) from continental shelves to the ocean may play a critical role in marine carbon cycling and budget. However, these fluxes have been poorly constrained because complicated biogeochemical reactions of riverine, atmospheric, and marine organic carbon occur in continental shelf-waters. We used multiple tracers of DOC such as stable- and radiocarbon isotope ratios of DOC, fluorescent properties of dissolved organic matter (FDOM), and 228Ra as a water age tracer to investigate the sources and fluxes of DOC in the northwest Pacific continental margin of the East China Sea and the Yellow Sea. Here, we show that there are significant additional (excess) supplies of DOC in the central Yellow Sea relative to the Changjiang (Yangtze River) source, based on these tracers. The marine δ13C signature (−21.1 ± 1.1‰) and the radiocarbon age (2000 ± 400 yr) of DOC suggest that the additional DOC (Δ14DOC = −44‰) is supplied from a combination of newly produced DOC and the degradation of particulate as well as sedimentary organic matter. The flux of this additional DOC produced in the continental shelf of the East China Sea to the open ocean is estimated to be ~1.9 ± 0.8 Tg C yr−1, which is comparable to that from the Changjiang discharge. Our study implies that the fluxes of continental shelf-borne DOC may be important globally and should be considered in estimating global DOC budgets in the marine environment.

Mangrove Peat Radiocarbon Ages From Snipe and Swan Key, FL - Khan, Nicole S; Toth, Lauren T; Moyer, Ryan P; Shaw, Jaimie E; Capar, Paulina; Kemp, Andrew C; Engelhart, Simon E; Horton, Benjamin P (U.S. Geological Survey, 2022)
In 2016, researchers collected cores of mangrove peat from two islands in the Florida Keys: Snipe Key (24.679°N, 81.653°W) and Swan Key (25.349N, 80.251W) (Fig. 1). This data release contains the radiocarbon ages and associated data for peat samples analyzed throughout the two cores. These data were used by Khan and others (in preparation) to reconstruct the millennial-scale sea level variability of the two locations.
Medium: csv,xlsx Type: dataset
Keywords: core analysis; push coring; Radiometric Dating

Organic carbon burial by river meandering partially offsets bank erosion carbon fluxes in a discontinuous permafrost floodplain - Douglas, Madison M.; Li, Gen K.; Fischer, Woodward W.; Rowland, Joel C.; Kemeny, Preston C.; West, A. Joshua; Schwenk, Jon; Piliouras, Anastasia P.; Chadwick, Austin J.; Lamb, Michael P. (Earth Surface Dynamics, 2022)
Arctic river systems erode permafrost in their banks and mobilize particulate organic carbon (OC). Meandering rivers can entrain particulate OC from permafrost many meters below the depth of annual thaw, potentially enabling the production of greenhouse gases. However, the amount and fate of permafrost OC that is mobilized by river erosion is uncertain. To constrain OC fluxes due to riverbank erosion and deposition, we collected riverbank and floodplain sediment samples along the Koyukuk River, which meanders through discontinuous permafrost in the Yukon River watershed, Alaska, USA, with an average migration rate of 0.52 m yr−1. We measured sediment total OC (TOC) content, radiocarbon activity, water content, bulk density, grain size, and floodplain stratigraphy. Radiocarbon activity and TOC content were higher in samples dominated by silt as compared to sand, which we used to map OC content onto floodplain stratigraphy and estimate carbon fluxes due to river meandering. Results showed that the Koyukuk River erodes and re-deposits a substantial flux of OC each year due to its depth and high migration rate, generating a combined OC flux of a similar magnitude to the floodplain net ecological productivity. However, sediment being eroded from cutbanks and deposited as point bars had similar OC stocks (mean ± 1 SD of 125.3±13.1 kg OC m−2 in cutbanks versus 114.0±15.7 kg OC m−2 in point bars) whether or not the banks contained permafrost. We also observed radiocarbon-depleted biospheric OC in both cutbanks and permafrost-free point bars. These results indicate that a substantial fraction of aged biospheric OC that is liberated from floodplains by bank erosion is subsequently re-deposited in point bars rather than being oxidized. The process of aging, erosion, and re-deposition of floodplain organic material may be intrinsic to river–floodplain dynamics, regardless of permafrost content.

Over a third of groundwater in USA public-supply aquifers is Anthropocene-age and susceptible to surface contamination - Jurgens, Bryant C.; Faulkner, Kirsten; McMahon, Peter B.; Hunt, Andrew G.; Casile, Gerolamo; Young, Megan B.; Belitz, Kenneth (Communications Earth & Environment, 2022)
The distribution of groundwater age is useful for evaluating the susceptibility and sustainability of groundwater resources. Here, we compute the aquifer-scale cumulative distribution function to characterize the age distribution for 21 Principal Aquifers that account for ~80% of public-supply pumping in the United States. The aquifer-scale cumulative distribution function for each Principal Aquifer was derived from an ensemble of modeled age distributions (~60 samples per aquifer) based on multiple tracers: tritium, tritiogenic helium-3, sulfur hexafluoride, chlorofluorocarbons, carbon-14, and radiogenic helium-4. Nationally, the groundwater is 38% Anthropocene (since 1953), 34% Holocene (75 – 11,800 years ago), and 28% Pleistocene (>11,800 years ago). The Anthropocene fraction ranges from <5 to 100%, indicating a wide range in susceptibility to land-surface contamination. The Pleistocene fraction of groundwater exceeds 50% in 7 eastern aquifers that are predominately confined. The Holocene fraction of groundwater exceeds 50% in 5 western aquifers that are predominately unconfined. The sustainability of pumping from these Principal Aquifers depends on rates of recharge and release of groundwater stored in fine-grained layers.
Keywords: Environmental impact; hydrology; Sustainability

Queen triggerfish Balistes vetula: Validation of otolith-based age, growth, and longevity estimates via application of bomb radiocarbon - Shervette, Virginia R.; Rivera Hernández, Jesús M. (PLOS ONE, 2022)
Ensuring the accuracy of age estimation in fisheries science through validation is an essential step in managing species for long-term sustainable harvest. The current study used Δ14 C in direct validation of age estimation for queen triggerfish Balistes vetula and conclusively documented that triggerfish sagittal otoliths provide more accurate and precise age estimates relative to dorsal spines. Caribbean fish samples (n = 2045) ranged in size from 67-473 mm fork length (FL); 23 fish from waters of the southeastern U.S. (SEUS) Atlantic coast ranged in size from 355-525 mm FL. Otolith-based age estimates from Caribbean fish range from 0-23 y, dorsal spine-based age estimates ranged from 1-14 y. Otolith-based age estimates for fish from the SEUS ranged from 8-40 y. Growth function estimates from otoliths in the current study (L∞ = 444, K = 0.13, t0 = -1.12) differed from spined-derived estimates in the literature. Our work indicates that previously reported maximum ages for Balistes species based on spine-derived age estimates may underestimate longevity of these species since queen triggerfish otolith-based ageing extended maximum known age for the species by nearly three-fold (14 y from spines versus 40 y from otoliths). Future research seeking to document age and growth population parameters of Balistes species should strongly consider incorporating otolith-based ageing in the research design.

Relative sea-level change in South Florida during the past ~5000 years - Khan, Nicole S.; Ashe, Erica; Moyer, Ryan P.; Kemp, Andrew C.; Engelhart, Simon E.; Brain, Matthew J.; Toth, Lauren T.; Chappel, Amanda; Christie, Margaret; Kopp, Robert E.; Horton, Benjamin P. (Global and Planetary Change, 2022)
A paucity of detailed relative sea-level (RSL) reconstructions from low latitudes hinders efforts to understand the global, regional, and local processes that cause RSL change. We reconstruct RSL change during the past ~5 ka using cores of mangrove peat at two sites (Snipe Key and Swan Key) in the Florida Keys. Remote sensing and field surveys established the relationship between peat-forming mangroves and tidal elevation in South Florida. Core chronologies are developed from age-depth models applied to 72 radiocarbon dates (39 mangrove wood macrofossils and 33 fine-fraction bulk peat). RSL rose 3.7 m at Snipe Key and 5.0 m at Swan Key in the past 5 ka, with both sites recording the fastest century-scale rate of RSL rise since ~1900 CE (~2.1 mm/a). We demonstrate that it is feasible to produce near-continuous reconstructions of RSL from mangrove peat in regions with a microtidal regime and accommodation space created by millennial-scale RSL rise. Decomposition of RSL trends from a network of reconstructions across South Florida using a spatio-temporal model suggests that Snipe Key was representative of regional RSL trends, but Swan Key was influenced by an additional local-scale process acting over at least the past five millennia. Geotechnical analysis of modern and buried mangrove peat indicates that sediment compaction is not the local-scale process responsible for the exaggerated RSL rise at Swan Key. The substantial difference in RSL between two nearby sites highlights the critical need for within-region replication of RSL reconstructions to avoid misattribution of sea-level trends, which could also have implications for geophysical modeling studies using RSL data for model tuning and validation.
Keywords: Holocene; mangrove; Proxy reconstruction; Reproducibility; sea level

Relative sea-level data preclude major late Holocene ice-mass change in Pine Island Bay - Braddock, Scott; Hall, Brenda L.; Johnson, Joanne S.; Balco, Greg; Spoth, Meghan; Whitehouse, Pippa L.; Campbell, Seth; Goehring, Brent M.; Rood, Dylan H.; Woodward, John (Nature Geoscience, 2022)
The rapidly retreating Thwaites and Pine Island glaciers together dominate present-day ice loss from the West Antarctic Ice Sheet and are implicated in runaway deglaciation scenarios. Knowledge of whether these glaciers were substantially smaller in the mid-Holocene and subsequently recovered to their present extents is important for assessing whether current ice recession is irreversible. Here we reconstruct relative sea-level change from radiocarbon-dated raised beaches at sites immediately seawards of these glaciers, allowing us to examine the response of the earth to loading and unloading of ice in the Amundsen Sea region. We find that relative sea level fell steadily over the past 5.5 kyr without rate changes that would characterize large-scale ice re-expansion. Moreover, current bedrock uplift rates are an order of magnitude greater than the rate of long-term relative sea-level fall, suggesting a change in regional crustal unloading and implying that the present deglaciation may be unprecedented in the past 5.5 kyr. While we cannot preclude minor grounding-line fluctuations, our data are explained most easily by early Holocene deglaciation followed by relatively stable ice positions until recent times and imply that Thwaites and Pine Island glaciers have not been substantially smaller than present during the past 5.5 kyr.

Review article: Existing and potential evidence for Holocene grounding line retreat and readvance in Antarctica - Johnson, Joanne S.; Venturelli, Ryan A.; Balco, Greg; Allen, Claire S.; Braddock, Scott; Campbell, Seth; Goehring, Brent M.; Hall, Brenda L.; Neff, Peter D.; Nichols, Keir A.; Rood, Dylan H.; Thomas, Elizabeth R.; et al. (The Cryosphere, 2022)
Widespread existing geological records from above the modern ice sheet surface and outboard of the current ice margin show that the Antarctic Ice Sheet (AIS) was much more extensive at the Last Glacial Maximum (∼20 ka) than at present. However, whether it was ever smaller than present during the last few millennia, and (if so) by how much, is known only for a few locations because direct evidence lies within or beneath the ice sheet, which is challenging to access. Here, we describe how retreat and readvance (henceforth “readvance”) of AIS grounding lines during the Holocene could be detected and quantified using subglacial bedrock, subglacial sediments, marine sediment cores, relative sea-level (RSL) records, geodetic observations, radar data, and ice cores. Of these, only subglacial bedrock and subglacial sediments can provide direct evidence for readvance. Marine archives are of limited utility because readvance commonly covers evidence of earlier retreat. Nevertheless, stratigraphic transitions documenting change in environment may provide support for direct evidence from subglacial records, as can the presence of transgressions in RSL records, and isostatic subsidence. With independent age control, ice structure revealed by radar can be used to infer past changes in ice flow and geometry, and therefore potential readvance. Since ice cores capture changes in surface mass balance, elevation, and atmospheric and oceanic circulation that are known to drive grounding line migration, they also have potential for identifying readvance. A multidisciplinary approach is likely to provide the strongest evidence for or against a smaller-than-present AIS in the Holocene.
Publisher: Copernicus GmbH

Revised marine reservoir offset (ΔR) values for molluscs and marine mammals from Arctic North America - Pieńkowski, Anna J.; Coulthard, Roy D.; Furze, Mark F. A. (Boreas, 2022)
Appropriate marine–terrestrial reservoir offset (ΔR) values are essential for accurate calibration of marine radiocarbon dates. However, ΔR values are only valid for the specific calibration curve that their calculation is based on. Here, we present revised ΔR values for the Marine20 calibration curve from Arctic North America, based on previously published 14C dates on pre-bomb live-collected marine molluscs (n = 124) and cetaceans (beluga whales; tooth dentine; n = 12), and bowhead whale–driftwood age comparisons from the same glacio-isostatically uplifted shorelines (n = 18). Molluscan-based ΔR are: Chukchi/Beaufort sea coasts, 265±116 14C years; NW Canadian Arctic Archipelago, 188±91 14C years; NE Baffin Island, 81±18 14C years; SE Baffin Island, 14±58 14C years; Hudson Strait, −73±64 14C years; Ungava Bay, 0±86 14C years; Foxe Basin, 175±89 14C years; Hudson Bay, −21±72 14C years; James Bay, 209±114 14C years; West Greenland, −93±111 14C years. Species-specific marine mammal ΔR terms are 107±59 14C years for beluga and 24±58 14C years for bowheads. Our revised ΔR values are applicable for as long as the same broad oceanographic conditions (circulation, ventilation) have persisted, i.e. through the Holocene. While molluscan values are applicable to other marine carbonate (e.g. foraminifera), cetacean ΔR are valid only for the species they were calculated for and should not be applied to other marine mammals. Importantly, the ΔR terms calculated here are only valid for Marine20 and should not be used with earlier or later calibration curves.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bor.12606

BOMB-PRODUCED RADIOCARBON ACROSS THE SOUTH PACIFIC GYRE—A NEW RECORD FROM AMERICAN SAMOA WITH UTILITY FOR FISHERIES SCIENCEABSTRACT - Andrews, Allen H; Prouty, Nancy G; Cheriton, Olivia M (Radiocarbon, 2021)
Coral skeletal structures can provide a robust record of nuclear bomb produced 14C with valuable insight into air-sea exchange processes and water movement with applications to fisheries science. To expand these records in the South Pacific, a coral core from Tutuila Island, American Samoa was dated with density band counting covering a 59-yr period (1953–2012). Seasonal signals in elemental ratios (Sr/Ca and Ba/Ca) and stable carbon (δ13C) values across the coral core corroborated the well-defined annual band structure and highlighted an ocean climate shift from the 1997–1998 El Niño. The American Samoa coral 14C measurements were consistent with other regional records but included some notable differences across the South Pacific Gyre (SPG) at Fiji, Rarotonga, and Easter Island that can be attributed to decadal ocean climate cycles, surface residence times and proximity to the South Equatorial Current. An analysis of the post-peak 14C decline associated with each coral record indicated 14C levels are beginning to merge for the SPG. This observation, coupled with otolith measurements from American Samoa, reinforces the perspective that bomb 14C dating can be performed on fishes and other marine organisms of the region using the post-peak 14C decline to properly inform fisheries management in the South Pacific.

Carbon Isotopic and Lithologic Constraints on the Sources and Cycling of Inorganic Carbon in Four Large Rivers in China: Yangtze, Yellow, Pearl, and Heilongjiang - Shan, Sen; Luo, Chunle; Qi, Yuanzhi; Cai, Wei‐Jun; Sun, Shuwen; Fan, Di; Wang, Xuchen (Journal of Geophysical Research: Biogeosciences, 2021)
Transport of terrigenous carbon by rivers has been affected extensively by climate change and anthropogenic activities in China over the last few decades. Here, we present results on carbon isotopes (C-13, C-14) of dissolved and particulate inorganic carbon (DIC and PIC) and combined with major lithologic ions measured in the four largest rivers in China, namely, the Yangtze, Yellow, Pearl, and Heilongjiang rivers, to reveal the sources and transport of terrigenous inorganic carbon in the rivers. The DIC concentrations showed large variations in the four rivers and ranged from 253 to 3,122 mu M. The Yangtze, Yellow and Pearl rivers transported high DIC contents that had low Delta C-14 values of millennium-aged DIC and very old PIC; however, the Heilongjiang River presented a lower DIC concentration with much younger C-14 ages than the global average (1,100 mu M). The strong correlations between the DIC isotope values and major lithological ions (Ca2+ and Mg2+) suggest that chemical weathering played important but variable roles in controlling the production and fate of DIC in the rivers. Using dual isotopes and the MixSIAR model, we calculated that the chemical weathering of carbonate rocks contributed 95 +/- 5% of the riverine DIC to the headwater of the Yangtze River while silicate rock weathering and riverine organic matter respiration contributed 62 +/- 25% and 5 +/- 5% of the DIC in the middle and lower reaches of the river, respectively. In contrast, chemical weathering of silicate rocks contributed the dominant fraction of DIC in the Yellow (55 +/- 17%), Pearl (61 +/- 20%) and Heilongjiang (83 +/- 29%) rivers.
Keywords: Carbon cycle; Chemical weathering; inorganic carbon in large rivers; radiocarbon; stable carbon isotope

Coal fly ash is a major carbon flux in the Chang Jiang (Yangtze River) basin - Li, Gen K.; Fischer, Woodward W.; Lamb, Michael P.; West, A. Joshua; Zhang, Ting; Galy, Valier; Wang, Xingchen Tony; Li, Shilei; Qiu, Hongrui; Li, Gaojun; Zhao, Liang; Chen, Jun; et al. (Proceedings of the National Academy of Sciences, 2021)
Fly ash-the residuum of coal burning-contains a considerable amount of fossilized particulate organic carbon (FOCash) that remains after high-temperature combustion. Fly ash leaks into natural environments and participates in the contemporary carbon cycle, but its reactivity and flux remained poorly understood. We characterized FOCash in the Chang Jiang (Yangtze River) basin, China, and quantified the riverine FOCash fluxes. Using Raman spectral analysis, ramped pyrolysis oxidation, and chemical oxidation, we found that FOCash is highly recalcitrant and unreactive, whereas shale-derived FOC (FOCrock) was much more labile and easily oxidized. By combining mass balance calculations and other estimates of fly ash input to rivers, we estimated that the flux of FOCash carried by the Chang Jiang was 0.21 to 0.42 Mt C center dot y-1 in 2007 to 2008-an amount equivalent to 37 to 72% of the total riverine FOC export. We attributed such high flux to the combination of increasing coal combustion that enhances FOCash production and the massive construction of dams in the basin that reduces the flux of FOCrock eroded from upstream mountainous areas. Using global ash data, a first-order estimate suggests that FOCash makes up to 16% of the present-day global riverine FOC flux to the oceans. This reflects a substantial impact of anthropogenic activities on the fluxes and burial of fossil organic carbon that has been made less reactive than the rocks from which it was derived.

Compound-specific radiocarbon reveals sources and land–sea transport of polycyclic aromatic hydrocarbons in an urban estuary - Ya, Miaolei; Wu, Yuling; Xu, Li; Li, Yongyu; Chen, Hanzhe; Wang, Xinhong (Water Research, 2021)
As typical chemical indicators of the Anthropocene, polycyclic aromatic hydrocarbons (PAHs) and their environmental behavior in urban estuaries can reveal the influence of anthropogenic activities on coastal zones worldwide. In contrast to conventional approaches based on concentration datasets, we provide a compound-specific radiocarbon ( 14 C) perspective to quantitatively evaluate the sources and land–sea transport of PAHs in an estuarine–coastal surficial sedimentary system impacted by anthropogenic activities and coastal currents. Compound-specific 14 C of PAHs and their 14 C end-member mixing models showed that 67 −73% of fluoranthene and pyrene and 76 −80% of five- and six-ring PAHs in the Jiulong River Estuary (JRE, China) originated from fossil fuels (e.g., coal, oil spill, and petroleum-related emissions). In the adjacent Western Taiwan Strait (WTS), the contributions of fossil fuel to these PAH groups were higher at 74 −79% and 84 −87%, respectively. Furthermore, as a significant biomarker for source al- location of terrigenous organic matter, perylene, a typical five-ring PAH, and its land–sea transport from the basin through the JRE and finally to the WTS was quantitatively evaluated based on the 14 C transport models. In the JRE, fluvial erosions and anthropogenic emissions affected the 14 C signature of perylene ( 14 C perylene , -535 ±5 ‰ ) with contributions of > 38% and < 62%, respectively. From the JRE to the WTS, the decreased 14 C perylene (-735 ±4 ‰ ) could be attributed to the long–range transport of “ocean current- driven” perylene (-919 ±53 ‰ ) with a contribution of 53 ±8%. This compound-specific 14 C approach and PAH transport model help provide a valuable reference for accurately quantifying land–sea transport and burial of organic pollutants in estuarine–coastal sedimentary systems.

Enhanced iceberg discharge in the western North Atlantic during all Heinrich events of the last glaciation - Zhou, Yuxin; McManus, Jerry F.; Jacobel, Allison W.; Costa, Kassandra M.; Wang, Shouyi; Alvarez Caraveo, Blanca (Earth and Planetary Science Letters, 2021)
A series of catastrophic iceberg and meltwater discharges to the North Atlantic, termed Heinrich events, punctuated the last ice age. During Heinrich events, coarse terrigenous debris released from the drifting icebergs was preserved in deep-sea sediments, serving as an indicator of iceberg passage. Quantifying the vertical flux of ice-rafted debris (IRD) in open-ocean settings can resolve questions regarding the timing and spatial variation in ice sheet calving intensity. In this study, 230Thxs-based IRD flux throughout the last glacial period was measured in a deep-sea sediment core from the western North Atlantic, and complemented by data spanning 0-32 ka from a sediment core in the Labrador Sea. The cores were recovered from sites downstream from Hudson Strait, a likely conduit for icebergs calving from the Laurentide ice sheet (LIS). We compare our results with equivalent existing data from the eastern North Atlantic and show that the two cores in our study have higher IRD fluxes during all Heinrich events, notably including events H3 (∼31 ka) and H6 (∼60 ka). This study demonstrates that the LIS played a role in all Heinrich events, and raises the likelihood that a single mechanism can account for the genesis of these events.
Keywords: Heinrich event; IRD flux; thorium normalization; western north atlantic

Evidence of humans in North America during the Last Glacial Maximum - Bennett, Matthew R.; Bustos, David; Pigati, Jeffrey S.; Springer, Kathleen B.; Urban, Thomas M.; Holliday, Vance T.; Reynolds, Sally C.; Budka, Marcin; Honke, Jeffrey S.; Hudson, Adam M.; Fenerty, Brendan; Connelly, Clare; et al. (Science, 2021)
Archaeologists and researchers in allied fields have long sought to understand human colonization of North America. Questions remain about when and how people migrated, where they originated, and how their arrival affected the established fauna and landscape. Here, we present evidence from excavated surfaces in White Sands National Park (New Mexico, United States), where multiple in situ human footprints are stratigraphically constrained and bracketed by seed layers that yield calibrated radiocarbon ages between ~23 and 21 thousand years ago. These findings confirm the presence of humans in North America during the Last Glacial Maximum, adding evidence to the antiquity of human colonization of the Americas and providing a temporal range extension for the coexistence of early inhabitants and Pleistocene megafauna.
Publisher: American Association for the Advancement of Science

A FRAMEWORK FOR TRANSDISCIPLINARY RADIOCARBON RESEARCH: USE OF NATURAL-LEVEL AND ELEVATED-LEVEL -14- C IN ANTARCTIC FIELD RESEARCHABSTRACT - Venturelli, Ryan A; Vick-Majors, Trista J; Collins, Billy; Gagnon, Alan; Kasic, Kathy; Kurz, Mark D; Li, Wei; Priscu, John; Roberts, Mark; Rosenheim, Brad E (Radiocarbon, 2021)
Radiocarbon (C-14) is an isotopic tracer used to address a wide range of scientific research questions. However, contamination by elevated levels of C-14 is deleterious to natural-level laboratory workspaces and accelerator mass spectrometer facilities designed to precisely measure small amounts of C-14. The risk of contaminating materials and facilities intended for natural-level C-14 with elevated-level C-14-labeled materials has dictated near complete separation of research groups practicing profoundly different measurements. Such separation can hinder transdisciplinary research initiatives, especially in remote and isolated field locations where both natural-level and elevated-level radiocarbon applications may be useful. This paper outlines the successful collaboration between researchers making natural-level C-14 measurements and researchers using C-14-labeled materials during a subglacial drilling project in West Antarctica (SALSA 2018-2019). Our strict operating protocol allowed us to successfully carry out C-14 labeling experiments within close quarters at our remote field camp without contaminating samples of sediment and water intended for natural level C-14 measurements. Here we present our collaborative protocol for maintaining natural level C-14 cleanliness as a framework for future transdisciplinary radiocarbon collaborations.
Keywords: AMS; contamination; LEUCINE; radiocarbon

Inverted channel variations identified on a distal portion of a bajada in the central Atacama Desert, Chile - Williams, Rebecca M.E.; Irwin, Rossman P.; Noe Dobrea, Eldar Z.; Howard, Alan D.; Dietrich, William E.; Cawley, J.C. (Geomorphology, 2021)
In deserts, the interplay between occasional fluvial events and persistent aeolian erosion can form composite modern and relict surfaces, especially on the distal portion of alluvial fans. There, relief inversion of alluvial deposits by differential erosion can form longitudinal ridges. We identified two distinct ridge types formed by relief inversion on converging alluvial fans in the hyperarid Chilean Atacama Desert. Although they are co-located and similar in scale, the ridge types have different ages and formation histories that apparently correspond to minor paleoclimate variations. Gravel-armored ridges are remnants of deflated alluvial deposits with a bimodal sediment distribution (gravel and sand) dated to a minor pluvial phase at the end of the Late Pleistocene (similar to 12 kyr). In contrast, younger (similar to 9 kyr) sulfate-capped ridges formed during a minor arid phase with evaporite deposition in a pre-existing channel that armored the underlying deposits. Collectively, inverted channels at Salar de Llamara resulted from multiple episodes of surface overland flow and standing water spanning several thousand years. Based on ridge relief and age, the minimum long-term deflation rate is 0.1-0.2 m/kyr, driven primarily by wind erosion. This case study is an example of the equifinality concept whereby different processes lead to similar landforms. The complex history of the two ridge types can only be generally constrained in remotely sensed data. In situ observations are required to discern the specifics of the aqueous history, including the flow type, magnitude, sequence, and paleoenvironment. These findings have relevance for interpreting similar landforms on Mars.

Limited Presence of Permafrost Dissolved Organic Matter in the Kolyma River, Siberia Revealed by Ramped Oxidation - Rogers, Jennifer A.; Galy, Valier; Kellerman, Anne M.; Chanton, Jeffrey P.; Zimov, Nikita; Spencer, Robert G. M. (Journal of Geophysical Research: Biogeosciences, 2021)

Long-term cultural eutrophication in White and Walden Ponds (Concord, Massachusetts, USA), Thoreau's lakes of light - Stager, J. Curt; Harvey, Lydia; Chimileski, Scott (Lake and Reservoir Management, 2021)
Two historically important ponds in the vicinity of Boston, MA, were subjected to a comparative paleolimnological investigation of the timing and causes of eutrophication trends in each. The remarkable clarity of White Pond during the early 19th century led Henry David Thoreau to compare it favorably to nearby Walden Pond, but during the 20th century water quality in both ponds declined. Sediment core studies show that cultural eutrophication began at Walden during the 1930s, but no long-term sediment records have been available for White Pond, which makes it more difficult to determine the history and causes of eutrophication there. Here we use microfossil and geochemical analyses of sediment cores to show that major changes in the diatom community of White Pond began around 1900, when fish stocking commenced and soil erosion due to land use in the watershed increased, and that the trend intensified around 1960 and 1990. We also describe efforts to mitigate eutrophication at White Pond, highlight the ecological importance of benthic vegetation in nutrient cycling, and suggest that threats to water quality in both of these ponds will likely increase due to anticipated climatic changes in the region.
Keywords: diatoms; eutrophication; paleolimnology; reclamation; Thoreau; Walden

The Preservation of Climate‐Driven Landslide Dams in Western Oregon - Struble, William T.; Roering, Joshua J.; Burns, William J.; Calhoun, Nancy C.; Wetherell, Logan R.; Black, Bryan A. (Journal of Geophysical Research: Earth Surface, 2021)
Bedrock landsliding, including the formation of landslide dams, is a predominant geomorphic process in steep landscapes. Clarifying the importance of hydrologic and seismic mechanisms for triggering deep-seated landslides remains an ongoing effort, and formulation of geomorphic metrics that predict dam preservation is crucial for quantifying secondary landslide hazards. Here, we identify >200 landslide-dammed lakes in western Oregon and utilize dendrochronology and enhanced C-14 dating ("wiggle matching") of "ghost forests" to establish slope failure timing at 20 sites. Our dated landslide dataset reveals bedrock landsliding has been common since the last Cascadia Subduction Zone earthquake in January 1700 AD. Our study does not reveal landslides that date to 1700 AD. Rather, we observe temporal clustering of at least four landslides in the winter of 1889/1890 AD, coincident with a series of atmospheric rivers that generated one of the largest regionally recorded floods. We use topographic and field analyses to assess the relation between dam preservation and topographic characteristics of the impounded valleys. In contrast to previous studies, we do not observe systematic scaling between dam size and upstream drainage area, though dam stability indices for our sites correspond with "stable" dams elsewhere. Notably, we observe that dams are preferentially preserved at drainage areas of similar to 1.5 to 13 km(2) and valley widths of similar to 25 to 80 m, which may reflect the reduced downstream influence of debris flows and the accumulation of mature conifer trees upstream from landslide-dammed lake outlets. We suggest that wood accumulation upstream of landslide dams tempers large stream discharges, thus inhibiting dam incision.

Radiocarbon dates, charcoal, and polycyclic aromatic hydrocarbon (PAH) data from Great Dismal Swamp Sites GDS-519 and GDS-520 - Willard, Debra A; Jones, Miriam C; Vachula, Richard S; Balascio, Nicholas L; Canuel, Elizabeth A (U.S. Geological Survey, 2021)
Sediment cores were collected in Great Dismal Swamp National Wildlife Refuge in November, 2017 to advance understanding of climate- and land-management driven changes in vegetation, hydrology, and fire regimes. Radiocarbon dates were obtained from samples in two cores (GDS-519-3-21-2017 and GDS-520-3-21-2017) to generate age models for the cores. Bulk sediment samples, charcoal, plant macrofossils, and pollen residue were selected at the USGS in Reston, Virginia and submitted to Beta Analytic, Inc. and the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) laboratories for radiocarbon dating. Those laboratories provided both radiocarbon ages and stable carbon isotope (delta 13C) results, which can be used to generate calibrated ages. Bulk density was measured for each core at the USGS in Reston, Virginia. Cores were sectioned at 1-cm increments. One cubic centimeter of wet sediment was extracted from each 1-cm increment downcore and weighed. Samples were subsequently dried at 100 degrees C for at least 24 hours to obtain dry weights, and bulk density was calculated by dividing original 1-cc volume by the dry weight. Polycyclic aromatic hydrocarbons (PAHs) and sedimentary charcoal were analyzed at the Virginia Institute of Marine Science at Gloucester Point, Virginia. PAH analysis began with freeze-drying of samples and extraction of their lipid contents using a Dionex 350 Accelerated Solvent Extractor (9:1; dicholoromethane:methanol). Total lipid extracts were separated into three fractions using silica gel columns and eluents of increasing polarity (F1: hexane, F2: 25% toluene in hexane, F3: methanol). Combined F1 and F2 fractions were analyzed to quantify PAHs using an Agilent 7890A gas chromatograph coupled with a 5975C mass selective detector (GC-MSD). The GC was equipped with a DB-5MS capillary column (30 m length; 320 micrometres outer diameter; 0.25 micrometres film thickness), which was heated using the following temperature program: 16 degrees C/minute to 150 degrees C and 5 degrees C/minute to 300 degrees C. Flow rate was 1.1 mL/minute. Individual PAH abundances were quantified using select ion monitoring mode (SIM) and relative to an external calibration curve constructed with a PAH calibration standard (Sigma-Aldrich CRM47940). Sixteen PAHs were quantified: naphthalene (Na), acenaphthylene (Ayl), acenaphthene (Ace), anthracene (An), phenanthrene (Phe), fluoranthene (Fla), pyrene (Py), benz[a]anthracene (Ba), chrysene (Ch), retene (Ret), benzo[k]fluoranthene (BkF), benzo[a]pyrene (BaP), benzo[b]fluoranthene (BbF), benzo[g,h,i]perylene (Bghi), dibenzo[a,h]anthracene (DiAn), and ideno[1,2,3-cd]pyrene (IP). PAH accumulation rates were quantified using the dry sediment concentration of PAHs and the age-depth model of the sediment cores. Sedimentary charcoal analysis followed a modified version of standard methodologies for isolating and identifying sedimentary charcoal particles. Dried sediment samples were weighed and then subjected to a light chemical treatment (1:1, by volume mixture of 1M sodium hexametaphosphate solution and 2% sodium hypochlorite solution) for 24 hours, in accordance with standard methods (Vachula et al., 2019, 2018). Samples were washed over two nested sieves (63 micrometre and 125 micrometre mesh sizes) to isolate an intermediate size fraction (63-125 micrometres), in which charcoal particles were enumerated using a dissection microscope and gridded petri dishes. Charcoal accumulation rates were quantified using the numeric concentration of charcoal particles, the bulk density of the sediments, and the age-depth model of the sediment cores. References Vachula, R.S., Russell, J.M., Huang, Y. and Richter, N., 2018. Assessing the spatial fidelity of sedimentary charcoal size fractions as fire history proxies with a high-resolution sediment record and historical data. Palaeogeography, Palaeoclimatology, Palaeoecology, 508, pp.166-175. Vachula, R.S., Russell, J.M. and Huang, Y., 2019. Climate exceeded human management as the dominant control of fire at the regional scale in California's Sierra Nevada. Environmental Research Letters, 14(10), p.104011.
Keywords: Climatology

Revisiting the marine reservoir age in Baja California continental margin sediments using 14C and 210Pb dating - Treinen-Crespo, Christina; Barbara, Loïc; Villaescusa, Julio A.; Schmidt, Sabine; Pearson, Ann; Carriquiry, José D. (Quaternary Geochronology, 2021)
Knowledge of the Marine Reservoir Effect (MRE) correction is fundamental in palaeoceanographic research to establish an accurate age-depth model for marine sedimentary records. However, during the last decades different MRE corrections have been applied in inconsistent ways for the same locality and same sediment cores, at Soledad Basin, Baja California, Mexico, creating confusion about the proper correction value of the marine reservoir effect (Delta R) to be applied. In contrast with the empirical approach previously used for assessing the Delta R value in Soledad Basin, in this study we applied an analytical approach based on the concurrent application of AMS-14C and 210Pbxs dating techniques made on sedimentary total organic carbon and foraminifera to determine new regional Delta R values from newly collected sediment cores from this site. Our results from Soledad Basin show a Delta R of 206 +/- 32 years for foraminifera and 706 +/- 42 years for organic carbon. Modeled ages using these results, and compared with those previously applied for the basin, highlight the relevance of the correct use of the local reservoir age as it can generate an offset of approximately 150 years if the other published Delta R were used. These differences can shift core chronologies by several decades and thus yield significant errors in palaeoceanographic reconstructions, which will be important to remedy in future work.

Towards a precise timing of groundwater use in the lower Yellow River area during the late Bronze age: Bayesian inference from the radiocarbon ages of ancient water wells at the Liang'ercun site, north China - Yu, Shi-Yong; Chen, Xuexiang; Fang, Zhen; Liu, Xiuling; Li, Ming; Guo, Junfeng (Quaternary Geochronology, 2021)
Keywords: Geography; Multidisciplinary; Physical Geosciences

An abrupt cooling event recorded around 73 kyr in western South Atlantic - Camillo, Edmundo; Quadros, Juliana P.; Santarosa, Ana Cláudia A.; Costa, Karen B.; Toledo, Felipe A.L. (Quaternary International, 2020)
This paper presents the record of sea surface temperature and planktonic foraminifera cold species for the last 130 kyr of a deep sea marine piston core (GL-854) from western South Atlantic. Our data shows a prominent and consistent feature around 73 kyr when an abrupt drop in sea surface temperature, both artificial neural network and oxygen isotope-based, was recorded. Additionally, our oxygen isotope curve presents a positive excursion and two cold-water planktonic foraminifera (Globoconella inflata and Neogloboquadrina incompta) remarkably increased their abundances. The benthic oxygen isotope record did not indicate any change while planktonic indicators were intensely disturbed. This cooling episode should be explained by a strong and abrupt mechanism able to promptly affect the surface ocean but not the deep ocean. It seems to be one of the coldest intervals during the last 130 kyr. Here, we discuss some hypothesis for this abrupt cooling recorded in the South Atlantic, including the speculative climatic impact of Toba super-eruption.
Keywords: Artificial neural network; C. pelagicus; G. inflata N. incompta; Oxygen isotope record; planktonic foraminifera; Toba volcano

Arctic amplification of global warming strengthened by sunlight oxidation of permafrost carbon to CO2 - Bowen, J. C.; Ward, C. P.; Kling, G. W.; Cory, R. M. (Geophysical Research Letters, 2020)
Once thawed, up to 15% of the ∼1,000 Pg of organic carbon (C) in arctic permafrost soils may be oxidized to carbon dioxide (CO2) by 2100, amplifying climate change. However, predictions of this amplification strength ignore the oxidation of permafrost C to CO2 in surface waters (photomineralization). We characterized the wavelength dependence of permafrost dissolved organic carbon (DOC) photomineralization and demonstrate that iron catalyzes photomineralization of old DOC (4,000-6,300 a BP) derived from soil lignin and tannin. Rates of CO2 production from photomineralization of permafrost DOC are two-fold higher than for modern DOC. Given that model predictions of future net loss of ecosystem C from thawing permafrost do not include the loss of CO2 to the atmosphere from DOC photomineralization, current predictions of an average of 208 Pg C loss by 2299 may be too low by ~14%.

Arsenic contamination of Bangladesh aquifers exacerbated by clay layers - Mihajlov, Ivan; Mozumder, M. Rajib H.; Bostick, Benjamín C.; Stute, Martin; Mailloux, Brian J.; Knappett, Peter S. K.; Choudhury, Imtiaz; Ahmed, Kazi Matin; Schlosser, Peter; van Geen, Alexander (Nature Communications, 2020)
Confining clay layers typically protect groundwater aquifers against downward intrusion of contaminants. In the context of groundwater arsenic in Bangladesh, we challenge this notion here by showing that organic carbon drawn from a clay layer into a low-arsenic pre-Holocene (>12 kyr-old) aquifer promotes the reductive dissolution of iron oxides and the release of arsenic. The finding explains a steady rise in arsenic concentrations in a pre-Holocene aquifer below such a clay layer and the repeated failure of a structurally sound community well. Tritium measurements indicate that groundwater from the affected depth interval (40–50 m) was recharged >60 years ago. Deeper (55–65 m) groundwater in the same pre-Holocene aquifer was recharged only 10–50 years ago but is still low in arsenic. Proximity to a confining clay layer that expels organic carbon as an indirect response to groundwater pumping, rather than directly accelerated recharge, caused arsenic contamination of this pre-Holocene aquifer.

Asian summer monsoon influence on chemical weathering and sediment provenance determined by clay mineral analysis from the Indus Submarine Canyon - Li, Yuting; Clift, Peter D.; Murray, Richard W.; Exnicios, Elise; Ireland, Thomas; Böning, Philipp (Quaternary Research, 2020)
Clay minerals from the Indus Canyon and eastern clinoform since ~12 ka are uniformly rich in smectite and illite, similar to those from the Holocene Indus flood plains. A systematic enrichment of smectite in the proximal delta compared to the canyon and eastern clinoform argues for preferential capture of smectite close to the river mouth since ~12 ka. There is a rapid shift to a more smectite-rich assemblage in the canyon and eastern clinoform after ~5 ka. This change is probably caused by a change in sediment source, with less direct flux from the Himalaya and more erosion of older, weathered, smectite-rich sediment from the Indus River flood plains, driven by incision of the Indus and its tributaries into the floodplain as summer monsoon rains weakened. This influx of smectite is consistent with lower kaolinite/smectite values since ~5 ka. The onset of large-scale agricultural activities since ~5 ka, especially starting with the Harappan Civilization, may also have enhanced incision and erosion of floodplain sediments over the same time period. This study reports for the first time how monsoon strength variations since ~12 ka affected the clay mineral assemblages and sediment provenance in a major submarine canyon.
Keywords: Clay minerals; Holocene; monsoon; Provenance; Reworking; Submarine canyon

Biomass-Derived Provenance Dominates Glacial Surface Organic Carbon in the Western HimalayaBiomass-Derived Provenance Dominates Glacial Surface Organic Carbon in the Western Himalaya - Nizam, Sarwar; Sen, Indra S.; Vinoj, Velu; Galy, Valier; Selby, David; Azam, Mohammad F.; Pandey, Satyendra K.; Creaser, Robert A.; Agarwal, Avinash K.; Singh, Akhilendra P.; Bizimis, Michael (Environmental Science & Technology, 2020)
The origin, transport pathway, and spatial variability of total organic carbon (OC) in the western Himalayan glaciers are poorly understood compared to those of black carbon (BC) and dust, but it is critically important to evaluate the climatic role of OC in the region. By applying the distribution of OC activation energy; C-14 activity; and radiogenic isotopes of Pb-208/Pb-204, (207)pb/(204)pb and (206)pb/Pb-204 in glacial debris and atmospheric particulate matter (PM10 size fraction), we demonstrate that 98.3 +/- 1.6 and 1.7 +/- 1.6% of OC in western Himalayan glaciers are derived from biomass and petrogenic sources, respectively. The (delta C-13 and N/C composition indicates that the biomass is a complex mixture of C3 vegetation and autochthonous photoautotrophic input modified by heterotrophic microbial activity. The data set reveals that the studied western Himalayan glacier has negligible contributions from fossil-fuel- derived particles, which contrasts to the central and eastern Himalayan glaciers that have significant contributions from fossil fuel sources. We show that this spatial variability of OC sources relates to regional differences in air mass transport pathways and precipitation regimes over the Himalaya. Moreover, our observation suggests that biomass-derived carbon could be the only primary driver of carbon-induced glacier melting in the western Himalaya.
Keywords: MASS BALANCES; AEROSOLS; ALBEDO REDUCTION; ATMOSPHERIC LEAD; BLACK CARBON; DUST TRANSPOR; isotopic composition; PB; SNOW ALBEDO; TIBETAN PLATEAU

Carbon Cycling in the World's Deepest Blue Hole - Yao, P.; Wang, X. C.; Bianchi, T. S.; Yang, Z. S.; Fu, L.; Zhang, X. H.; Chen, L.; Zhao, B.; Morrison, E. S.; Shields, M. R.; Liu, Y. N.; Bi, N. S.; et al. (Journal of Geophysical Research: Biogeosciences, 2020)
Blue holes are unique geomorphological features with steep biogeochemical gradients and distinctive microbial communities. Carbon cycling in blue holes, however, remains poorly understood. Here we describe potential mechanisms of dissolved carbon cycling in the world's deepest blue hole, the Yongle Blue Hole (YBH), which was recently discovered in the South China Sea. In the YBH, we found some of the lowest concentrations (e.g., 22 μM) and oldest ages (e.g., 6,810 years before present) of dissolved organic carbon, as well as the highest concentrations (e.g., 3,090 μM) and the oldest ages (e.g., 8,270 years before present) of dissolved inorganic carbon observed in oceanic waters. Sharp gradients of dissolved oxygen, H2S, and CH4 and changes in bacterially mediated sulfur cycling with depth indicated that sulfur‐ and/or methane‐based metabolisms are closely linked to carbon cycling in the YBH. Our results showed that the YBH is a unique and easily accessible natural laboratory for examining carbon cycling in anoxic systems, which has potential for understanding carbon dynamics in both paleo and modern oceans—particularly in the context of global change.
Keywords: anoxia; carbon cycling; dissolved carbon; radiocarbon; sulfur cycling; Yongle blue hole

Carbon isotope forensics for methane source identification - Coffin, Richard; Mueller, James (Remediation Journal, 2020)
Methane (CH4) in ecosystems originates from ancient petroleum formed deep within the earth and/or via microbial fermentation of organic carbon and subsequent reduction of carbon dioxide (CO2). Given the complexity of different ecosystems, origins of CH4 present can be difficult to determine. This issue was realized in a situation where an antimethanogenic in situ chemical reduction (ISCR) remedial amendment containing organic carbon plus zero‐valent iron was applied to treat chlorinated solvents in groundwater at a former dry cleaner facility. The technology rapidly and effectively reduced the concentration of tetrachloroethene in groundwater thus meeting project goals without the stoichiometric accumulation of catabolites such as trichloroethene (TCE), cis‐1,2‐dichloroethene, or vinyl chloride and without excessive methanogenesis (e.g., <2 mg/L) in the treated area. However, approximately 9 months after treatment, increased levels of CH4 (from 5 to 10 mg/L) were observed downgradient from the treated area. The applied remedial amendment contained approximately 60% (weight basis) fermentation organic carbon and was therefore a potential source of this CH4. However, there was <500 mg/L total organic carbon in groundwater emanating from the upgradient treatment area which was unlikely sufficient to produce that much CH4. Moreover, the soil gas also contained benzene, toluene, ethylbenzene, and xylenes and other gasoline constituents. These data suggested that the presence of three gasoline/diesel underground storage tanks that were previously closed in place with no active remediation performed could be the source of elevated CH4. Thirdly, there were sewer lines, utilities, multiple gasoline stations, and industrial activities in the immediate area. With an initial assumption that CH4 source(s) could include the ISCR amendment over stimulation of production, gasoline sourced CH4 from nearby leaking lines, or sewage from local fractured pipes, carbon isotope analyses—radiocarbon (Δ14C) and stable carbon (δ13C)—were coupled with CH4 and CO2 concentration data from groundwater samples to determine the origin of respired carbon. The δ13C range for carbon sources respired in the process would be approximately −26.5‰ to −33.0‰ for the ISCR amendment and total petroleum hydrocarbons (TPH) residuals, respectively. Δ14C is approximately 0‰ and −999‰ for the ISCR amendment (young carbon) and TPH (old carbon), respectively. The isotopic signature of respired gasses confirmed that elevated CH4 downgradient of the treated area originated primarily from sewer gasses (or fermentation of liquids released from sewer lines). This study provides an overview of the capability to apply carbon isotope geochemistry to confirmation of remedial protocols and sources of anthropogenic carbon pools that conclusively identify the origin of CH4 in a complex ecosystem undergoing a remedial action.

Clumped Isotopes Link Older Carbon Substrates With Slower Rates of Methanogenesis in Northern Lakes - Douglas, Peter M. J.; Gonzalez Moguel, Regina; Walter Anthony, Katey M.; Wik, Martin; Crill, Patrick M.; Dawson, Katherine S.; Smith, Derek A.; Yanay, Ella; Lloyd, Max K.; Stolper, Daniel A.; Eiler, John M.; Sessions, Alex L. (Geophysical Research Letters, 2020)
The release of long‐stored carbon from thawed permafrost could fuel increased methanogenesis in northern lakes, but it remains unclear whether old carbon substrates released from permafrost are metabolized as rapidly by methanogenic microbial communities as recently produced organic carbon. Here, we apply methane (CH4) clumped isotope (Δ18) and 14C measurements to test whether rates of methanogenesis are related to carbon substrate age. Results from culture experiments indicate that Δ18 values are negatively correlated with CH4 production rate. Measurements of ebullition samples from thermokarst lakes in Alaska and glacial lakes in Sweden indicate strong negative correlations between CH4 Δ18 and the fraction modern carbon. These correlations imply that CH4 derived from older carbon substrates is produced relatively slowly. Relative rates of methanogenesis, as inferred from Δ18 values, are not positively correlated with CH4 flux estimates, highlighting the likely importance of environmental variables other than CH4 production rates in controlling ebullition fluxes.
Keywords: clumped isotopes; ebullition flux; lakes; methane; permafrost; radiocarbon

Efficient preservation of young terrestrial organic carbon in sandy turbidity-current depositsAbstract - Hage, S.; Galy, V.V.; Cartigny, M.J.B.; Acikalin, S.; Clare, M.A.; Gröcke, D.R.; Hilton, R.G.; Hunt, J.E.; Lintern, D.G.; McGhee, C.A.; Parsons, D.R.; Stacey, C.D.; et al. (Geology, 2020)
Burial of terrestrial biospheric particulate organic carbon in marine sediments removes CO2 from the atmosphere, regulating climate over geologic time scales. Rivers deliver terrestrial organic carbon to the sea, while turbidity currents transport river sediment further offshore. Previous studies have suggested that most organic carbon resides in muddy marine sediment. However, turbidity currents can carry a significant component of coarser sediment, which is commonly assumed to be organic carbon poor. Here, using data from a Canadian fjord, we show that young woody debris can be rapidly buried in sandy layers of turbidity current deposits (turbidites). These layers have organic carbon contents 10× higher than the overlying mud layer, and overall, woody debris makes up >70% of the organic carbon preserved in the deposits. Burial of woody debris in sands overlain by mud caps reduces their exposure to oxygen, increasing organic carbon burial efficiency. Sandy turbidity current channels are common in fjords and the deep sea; hence we suggest that previous global organic carbon burial budgets may have been underestimated.

Groundwater as a major source of dissolved organic matter to Arctic coastal waters - Connolly, Craig T.; Cardenas, M. Bayani; Burkart, Greta A.; Spencer, Robert G. M.; McClelland, James W. (Nature Communications, 2020)
Groundwater is projected to become an increasing source of freshwater and nutrients to the Arctic Ocean as permafrost thaws, yet few studies have quantified groundwater inputs to Arctic coastal waters under contemporary conditions. New measurements along the Alaska Beaufort Sea coast show that dissolved organic carbon and nitrogen (DOC and DON) concentrations in supra-permafrost groundwater (SPGW) near the land-sea interface are up to two orders of magnitude higher than in rivers. This dissolved organic matter (DOM) is sourced from readily leachable organic matter in surface soils and deeper centuries-to millennia-old soils that extend into thawing permafrost. SPGW delivers approximately 400–2100 m3 of freshwater, 14–71 kg of DOC, and 1–4 kg of DON to the coastal ocean per km of shoreline per day during late summer. These substantial fluxes are expected to increase as massive stocks of frozen organic matter in permafrost are liberated in a warming Arctic.

High dissolved organic radiocarbon in precipitation during winter and its implication on the carbon cycle - Cha, Ji-Yeon; Lee, Seung-Cheol; Lee, Eun-Ju; Go, Minjung; Dasari, Kishore Babu; Yim, Yong-Hyeon; Oh, Neung-Hwan (Science of The Total Environment, 2020)
Radiocarbon (14C) analysis is a powerful tool for tracing carbon in the global carbon cycle. Precipitation is a component of the global carbon cycle through which dissolved organic carbon (DOC) enters terrestrial and aquatic ecosystems from the atmosphere. In previous studies, the Δ14C of DOC in rain or snow was negative indicating an input of relatively old organic carbon including fossil fuels, with only a few positive values up to +108‰ showing the signal of recent photosynthesis. However, here we report surprisingly high Δ14C-DOC in bulk precipitation, more than 1000‰ in Seoul, South Korea, especially when the Northwesterly wind blows during winter. In contrast, Δ14C of particulate organic carbon (POC) in bulk precipitation was negative, indicating that the sources of POC and DOC were different. Although the sources of the high Δ14C-DOC are not clear and future studies on them are required, the relatively high Δ14C-DOC in a nearby headwater stream suggests that precipitation DOC has the potential to affect the local carbon cycle, and that stream DOC derived from terrestrial ecosystems could be older than previously thought. The analysis of Δ14C-DOC of precipitation in many other locations is necessary to understand how long carbon stays in terrestrial ecosystems.

Holocene earthquake history and slip rate of the southern Teton fault, Wyoming, USAAbstract - DuRoss, Christopher B.; Gold, Ryan D.; Briggs, Richard W.; Delano, Jaime E.; Ostenaa, Dean A.; Zellman, Mark S.; Cholewinski, Nicole; Wittke, Seth J.; Mahan, Shannon A. (GSA Bulletin, 2020)
The 72-km-long Teton normal fault bounds the eastern base of the Teton Range in northwestern Wyoming, USA. Although geomorphic surfaces along the fault record latest Pleistocene to Holocene fault movement, the postglacial earthquake history of the fault has remained enigmatic. We excavated a paleoseismic trench at the Buffalo Bowl site along the southernmost part of the fault to determine its Holocene rupture history and slip rate. At the site, ∼6.3 m of displacement postdates an early Holocene (ca. 10.5 ka) alluvial-fan surface. We document evidence of three surface-faulting earthquakes based on packages of scarp-derived colluvium that postdate the alluvial-fan units. Bayesian modeling of radiocarbon and luminescence ages yields earthquake times of ca. 9.9 ka, ca. 7.1 ka, and ca. 4.6 ka, forming the longest, most complete paleoseismic record of the Teton fault. We integrate these data with a displaced deglacial surface 4 km NE at Granite Canyon to calculate a postglacial to mid-Holocene (14.4–4.6 ka) slip rate of ∼1.1 mm/yr. Our analysis also suggests that the postglacial to early Holocene (14.4–9.9 ka) slip rate exceeds the Holocene (9.9–4.6 ka) rate by a factor of ∼2 (maximum of 3); however, a uniform rate for the fault is possible considering the 95% slip-rate errors. The ∼5 k.y. elapsed time since the last rupture of the southernmost Teton fault implies a current slip deficit of ∼4–5 m, which is possibly explained by spatially/temporally incomplete paleoseismic data, irregular earthquake recurrence, and/or variable per-event displacement. Our study emphasizes the importance of minimizing slip-rate uncertainties by integrating paleoseismic and geomorphic data sets and capturing multiple earthquake cycles.

The Hooskanaden Landslide: historic and recent surge behavior of an active earthflow on the Oregon Coast - Alberti, Stefano; Senogles, Andrew; Kingen, Kara; Booth, Adam; Castro, Pete; DeKoekkoek, Jill; Glover-Cutter, Kira; Mohney, Curran; Olsen, Michael; Leshchinsky, Ben (Landslides, 2020)
This paper presents an analysis of the Hooskanaden Landslide, an earthflow, which experienced a dramatic surge event beginning on February 24, 2019, closing US Highway 101 near mile point 343.5 for nearly 2 weeks. This ~ 1 km long surge event resulted in horizontal displacements of up to 45 m and uplift of 6 m at the toe located on a gravel beach adjacent to the Pacific Ocean. The Hooskanaden Landslide, likely active since the eighteenth century, exhibits regular activity with a recurrence interval of major surge events of approximately every 20 years, transitioning from slow to relatively rapid velocities. During the 2019 event, maximum displacement rates of approximately 60 cm/h were observed, slowly decreasing to 15 cm/h for a sustained period of approximately 2 weeks before the eventual return to baseline conditions (< 0.02 cm/h).

Identifying the Greatest Earthquakes of the Past 2000 Years at the Nehalem River Estuary, Northern Oregon Coast, USA - Nelson, Alan R.; Hawkes, Andrea D.; Sawai, Yuki; Engelhart, Simon E.; Witter, Rob; Grant-Walter, Wendy C.; Bradley, Lee-Ann; Dura, Tina; Cahill, Niamh; Horton, Ben (Open Quaternary, 2020)
We infer a history of three great megathrust earthquakes during the past 2000 years at the Nehalem River estuary based on the lateral extent of sharp (≤3 mm) peat-mud stratigraphic contacts in cores and outcrops, coseismic subsidence as interpreted from fossil diatom assemblages and reconstructed with foraminiferal assemblages using a Bayesian transfer function, and regional correlation of 14C-modeled ages for the times of subsidence. A subsidence contact from 1700 CE (contact A), sometimes overlain by tsunami-deposited sand, can be traced over distances of 7 km. Contacts B and D, which record subsidence during two earlier megathrust earthquakes, are much less extensive but are traced across a 700-m by 270-m tidal marsh. Although some other Cascadia studies report evidence for an earthquake between contacts B and D, our lack of extensive evidence for such an earthquake may result from the complexities of preserving identifiable evidence of it in the rapidly shifting shoreline environments of the lower river and bay. Ages (95% intervals) and subsidence for contacts are: A, 1700 CE (1.1 ± 0.5 m); B, 942–764 cal a BP (0.7 ± 0.4 m and 1.0 m ± 0.4 m); and D, 1568–1361 cal a BP (1.0 m ± 0.4 m). Comparisons of contact subsidence and the degree of overlap of their modeled ages with ages for other Cascadia sites are consistent with megathrust ruptures many hundreds of kilometers long. But these data cannot conclusively distinguish among different types or lengths of ruptures recorded by the three great earthquake contacts at the Nehalem River estuary.
Keywords: Bayesian transfer function; Cascadia subduction zone; Coseismic subsidence; earthquake hazards; Paleoseismology; salt-marsh stratigraphy; Sea-level changes; tidal foraminifera and diatoms

Influences of upper Floridan aquifer waters on radiocarbon in the otoliths of gray snapper (Lutjanus griseus) in the Gulf of Mexico - Andrews, Allen H; Barnett, Beverly K; Chanton, Jeffrey P; Thornton, Laura A; Allman, Robert J (Radiocarbon, 2020)
The otoliths (ear stones) of fishes are commonly used to describe the age and growth of marine and freshwater fishes. These non-skeletal structures are fortuitous in their utility by being composed of mostly inorganic carbonate that is inert through the life of the fish. This conserved record functions like an environmental chronometer and bomb-produced radiocarbon — a 14C signal created by atmospheric testing of thermonuclear devices — can be used as a time-specific marker in validating fish age. However, complications from the hydrogeology of nearshore marine environments can complicate 14C levels, as was the case with gray snapper (Lutjanus griseus) along the Gulf of Mexico coast of Florida. Radiocarbon of these nearshore waters is influenced by freshwater input from the karst topography of the Upper Floridan Aquifer-estuarine waters that are 14C-depleted from surface and groundwater inputs. Some gray snapper likely recruited to this kind of environment where 14C levels were depleted in the earliest otolith growth, although age was validated for individuals that were not exposed to 14C-depleted waters to an age of at least 25 years with support for a 30-year lifespan.

Insolation and greenhouse gases drove Holocene winter and spring warming in Arctic Alaska - Longo, William M.; Huang, Yongsong; Russell, James M.; Morrill, Carrie; Daniels, William C.; Giblin, Anne E.; Crowther, Josue (Quaternary Science Reviews, 2020)
Global surface temperature changes and their drivers during the Holocene Epoch remain controversial. Syntheses of proxy data indicate that global mean annual temperature declined from the mid-Holocene until the Pre-industrial Era, a trend linked to decreasing Northern Hemisphere summer insolation. In contrast, global climate models simulate increasing mean annual temperatures driven by retreating ice sheets and increasing greenhouse gas concentrations. This proxy-model disagreement may originate from a warm season bias in Northern Hemisphere proxy reconstructions, highlighting the need for new proxies that quantify cold season temperature, especially in Arctic regions that were devoid of continental ice sheets during the Holocene. Here, we present a new 16,000-year winter-spring temperature reconstruction derived from the unsaturation ratio of alkenones (U-3(7)K) in a continuous sedimentary sequence from Lake E5, northern Alaska. We employ a thermodynamic lake model to convert alkenone-inferred lake temperatures into winter-spring air temperature anomalies and we contextualize our proxy reconstruction with climate model output from the region. Our reconstruction shows that winter-spring temperatures warmed rapidly during the deglaciation at 16 and 14 thousand years before present and continued to warm gradually throughout the middle and late Holocene (0.12-0.28 degrees C/thousand years) in concert with regional sea surface temperature and sea ice records. Our results are consistent with climate model simulations and we attribute Holocene warming to rising winter-spring insolation, radiative forcing from rising greenhouse gas concentrations and regional feedbacks. Our reconstructed cold season warming equaled or exceeded summer cooling according to a regional synthesis of temperature records, suggesting that seasonal biases in temperature reconstructions may account for proxy-model disagreements in Holocene temperature trends from Eastern Beringia. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Alkenone; Beringia; Continental biomarkers; Holocene; North America; paleoclimatology; paleolimnology; Proxy data-model comparison; seasonality; Temperature reconstruction

Late glacial and Holocene paleoenvironments in the midcontinent United States, inferred from Geneva Lake leaf wax, ostracode valve, and bulk sediment chemistry - Puleo, Peter J.K.; Axford, Yarrow; McFarlin, Jamie M.; Curry, B. Brandon; Barklage, Mitchell; Osburn, Magdalena R. (Quaternary Science Reviews, 2020)
Geneva Lake in Wisconsin, USA, is > 20,000 years old and contains a 30-m thick lacustrine sediment record of mid-continent North American climate and environmental change. Here we describe a sediment record from Geneva Lake spanning the past 14,500 years. From scanning X-ray fluorescence, organic C and N concentrations and isotopes, X-ray diffraction, magnetic susceptibility, and grain size of bulk sediments, we infer changes in sediment sources over time including: abrupt decline in inputs of remobilized loess ∼13,400 cal yr BP followed by a gradual transition to organic-rich marl deposition by ∼10,400 cal yr BP as the landscape stabilized following a period of permafrost thaw and vegetation development; deposition of a minerogenic unit at ∼8,200 cal yr BP that may record enhanced eolian activity during the widespread “8.2 ka event; ” and elevated zinc, lead, and arsenic from human activities following regional industrialization. Within the Holocene marl, we also use isotopic (δ18O and δ13C) and trace metal ratio (Sr/Ca and Mg/Ca) analyses of ostracode valves paired with concentrations and hydrogen isotopic composition (δ2H) of leaf wax n-alkanes to infer climate and hydrological change. Groundwater had a large but declining influence on lake water chemistry from 11,800 to 9,700 cal yr BP, precluding inferences of regional climate from our lacustrine proxies during this period. δ2H values of terrestrial n-C29 alkanes show little variability from 9,700 to present, indicating the average isotopic composition of local precipitation was relatively stable, reflecting stable condensation temperatures and source. In contrast, a gradual trend towards more δ18O- and δ2H-depleted lake water and lower lake water Sr/Ca from 9700 cal yr BP to present suggest decreasing evaporation of lake water and increasing precipitation amounts throughout the Holocene and resulting shorter lake water residence times. Lake water Mg/Ca variations over the past 9,700 years broadly parallel regional pollen-based reconstructions of summer temperatures. Neither Mg/Ca nor terrestrial leaf wax δ2H suggest long-term directional shifts in temperature at this site through the middle to late Holocene, as climate became wetter. It appears that precipitation isotopes did not track local temperatures on millennial timescales in this part of mid-continent North America through the Holocene, and instead may have covaried with changes in Northern Hemisphere latitudinal temperature gradients driven by large Arctic temperature changes.
Keywords: Holocene; Inorganic geochemistry; Loess; North America; Organic geochemistry; paleoclimatology; paleolimnology; Pleistocene; sedimentology; Stable isotopes

A late Holocene subfossil Atlantic white cedar tree-ring chronology from the northeastern United States - Pearl, Jessie K.; Anchukaitis, Kevin J.; Donnelly, Jeffrey P.; Pearson, Charlotte; Pederson, Neil; Lardie Gaylord, Mary C.; McNichol, Ann P.; Cook, Edward R.; Zimmermann, George L. (Quaternary Science Reviews, 2020)
Tree-rings provide precise annually dated climate information, but their application can be limited by the relatively short lifespan of many trees. To overcome this limitation, tree-ring records can be extended over longer time periods by connecting living trees with older “sub-fossil” trees, which can provide information on longer timescales throughout the Holocene. These long chronologies are proxy records of past climate, provide precise chronological information for extreme events, and give insight into the range of natural climate variability prior to the instrumental period. In the densely populated northeastern United States, few tree-ring records are longer than 500 years, and there are no millennial-length tree-ring chronologies for the region. Here, we use a combination of standard dendrochronological and radiocarbon techniques, including use of the 774 CE radiocarbon excursion, to generate an absolutely dated 2500 year-long tree ring record from living, archaeological, and subfossil Atlantic white cedar (Chamaecyparis thyoides) found in the coastal northeastern United States. Our chronology demonstrates the potential to develop multi-millennial Chamaecyparis thyoides tree-ring records to address previously unanswered questions regarding late Holocene hydroclimate, extreme events, and temperature variability in New England.
Keywords: coastal; Geomorphology; Holocene; North America; paleoclimatology; radiogenic isotopes; Tree-rings

Life history of northern Gulf of Mexico Warsaw grouper Hyporthodus nigritus inferred from otolith radiocarbon analysis - Barnett, Beverly K.; Chanton, Jeffrey P.; Ahrens, Robert; Thornton, Laura; Patterson, William F. (PLOS ONE, 2020)
Warsaw grouper, Hyporthodus nigritus, is a western Atlantic Ocean species typically found at depths between 55 and 525 m. It is listed as a species of concern by the U.S. National Marine Fisheries Service and as near threatened by the International Union for the Conservation of Nature. However, little information exists on the species’ life history in the northern Gulf of Mexico (nGOM) and its stock status in that region is currently unknown. Age of nGOM Warsaw grouper was investigated via opaque zone counts in otolith thin sections (max age = 61 y), and then the bomb 14C chronometer was employed to validate the accuracy of age estimates. Otolith cores (n = 14) were analyzed with accelerator mass spectrometry and resulting Δ14C values overlain on a loess regression computed for a regional coral and known-age red snapper Δ14C time series. Residual analysis between predicted Δ14C values from the loess regression versus Warsaw grouper otolith core Δ14C values indicated no significant difference in the two data series. Therefore, the accuracy of otolith-based aging was validated, which enabled growth and longevity estimates to be made for nGOM Warsaw grouper. Dissolved inorganic carbon (DIC) Δ14C values collected from the nGOM support the inference that juvenile Warsaw grouper occur in shelf waters (<200 m) since DIC Δ14C values in this depth range are enriched in 14C and similar to the Δ14C values from otolith cores. A Bayesian model was fit to fishery-dependent age composition data and produced von Bertalanffy growth function parameters of L1 = 1,533 mm, k = 0.14 y-1, and t0 = 1.82 y. Fishing mortality also was estimated in the model, which resulted in a ratio of fishing to natural mortality of 5.1:1. Overall, study results indicate Warsaw grouper is a long-lived species that is estimated to have experienced significant overfishing in the nGOM, with the age of most landed fish being <10 y.

Minimum limiting deglacial ages for the out-of-phase Saginaw Lobe of the Laurentide Ice Sheet using optically stimulated luminescence (OSL) and radiocarbon methods - Fisher, Timothy G.; Dziekan, Mitchell R.; McDonald, Jennifer; Lepper, Kenneth; Loope, Henry M.; McCarthy, Francine M.G.; Curry, B. Brandon (Quaternary Research, 2020)
Twenty-four new optically stimulated luminescence (OSL) and radiocarbon ages from sediment cores in nine lakes associated with the Shipshewana and Sturgis moraines in northern Indiana and southern Michigan estimate when recession of the Saginaw Lobe of the Laurentide Ice Sheet was underway in the southern Great Lakes region, USA. Average OSL ages of 23.4 ± 2.2 ka for the Shipshewana Moraine and 19.7 ± 2.2 ka for the Sturgis Moraine are considered minimum limiting deglacial ages for these recessional moraines. The much younger radiocarbon ages are consistent with other regional radiocarbon ages from lakes, and record climate amelioration around ~16.5 cal ka BP. Early recession of the interlobate Saginaw Lobe was well underway by 23.4 ± 2.2 ka, when the adjacent Lake Michigan and Huron-Erie lobes were a few hundred kilometers farther south and near their maximum southerly limits. The results provide the first time constraints when sediment from the Lake Michigan and Huron-Erie lobes began filling the accommodation space left by the Saginaw Lobe. The difference between the oldest radiocarbon and OSL age is 7400 yr for the Shipshewana Moraine and 3400 yr for the Sturgis Moraine.
Keywords: Deglaciation; Lake sediment cores; OSL dating; Radiocarbon lag; Saginaw Lobe; Sturgis Moraine

Neotectonic and Paleoseismic Analysis of the Northwest Extent of Holocene Surface Deformation along the Meers Fault, OklahomaABSTRACT - Hornsby, Kristofer T.; Streig, Ashley R.; Bennett, Scott E. K.; Chang, Jefferson C.; Mahan, Shannon (Bulletin of the Seismological Society of America, 2020)
The Meers fault (Oklahoma) is one of few seismogenic structures with evidence for Holocene surface rupture in the stable continental region of North America. The 37-kilometer-long southeast section of the full 54-kilometer-long Meers fault is interpreted to be Holocene active. The 17-kilometer-long northwest section is considered Quaternary active, but not Holocene active.We reevaluate surface expression and earthquake timing of the northwest Meers fault to improve seismic source characterization.We use airborne light detection and ranging and historical stereo paired aerial photos to evaluate the fault scarp and local fault zone geomorphology. In the northwest, complex surface deformation includes fault splays, subtle monoclinal warping, and a minor change in fault strike. We interpret that the along strike transition from surface faulting on the southeast Meers fault to surface folding on the northwest Meers fault occurs at the lithologic contact between Permian Post Oak conglomerate and Hennessey shale. We excavated a paleoseismic trench to evaluate the timing of surface-deforming earthquakes on the northwest section of the fault. The excavation revealed weathered Permian Hennessey shale and an ∼1–2-meter-thick veneer of Holocene alluvial deposits that were progressively deformed during two surface-folding earthquakes likely related to blind fault rupture beneath the site. Repeated onlapping to overlapping stratigraphic sequences and associated unconformities are intimately related to folding events along the monocline. OxCal paleoearthquake age modeling indicates that earthquakes occurred 4704–3109 yr B.P. and 5955–4744 yr B.P., and that part of the northwest section of the Meers fault is Holocene active. We find the Holocene-active section of the Meers fault should be lengthened 6.1 km to the northwest, to a total Holocene-active fault length of 43 km. Empirical scaling relationships between surface rupture length and magnitude reveal that the fault could generate an Mw 7.0 earthquake.

“New” cyanobacterial blooms are not new: two centuries of lake production are related to ice cover and land use - Ewing, Holly A.; Weathers, Kathleen C.; Cottingham, Kathryn L.; Leavitt, Peter R.; Greer, Meredith L.; Carey, Cayelan C.; Steele, Bethel G.; Fiorillo, Alyeska U.; Sowles, John P. (Ecosphere, 2020)
Recent cyanobacterial blooms in otherwise unproductive lakes may be warning signs of impending eutrophication in lakes important for recreation and drinking water, but little is known of their historical precedence or mechanisms of regulation. Here, we examined long-term sedimentary records of both general and taxon-specific trophic proxies from seven lakes of varying productivity in the northeastern United States to investigate their relationship to historical in-lake, watershed, and climatic drivers of trophic status. Analysis of fossil pigments (carotenoids and chlorophylls) revealed variable patterns of past primary production across lakes over two centuries despite broadly similar changes in regional climate and land use. Sediment abundance of the cyanobacteriumGloeotrichia,a large, toxic, nitrogen-fixing taxon common in recent blooms in this region, revealed that this was not a new taxon in the phytoplankton communities but rather had been present for centuries. Histories ofGloeotrichiaabundance differed strikingly across lakes and were not consistently associated with most other sediment proxies of trophic status. Changes in ice cover most often coincided with changes in fossil pigments, and changes in watershed land use were often related to changes inGloeotrichiaabundance, although no single climatic or land-use factor was associated with proxy changes across all seven lakes. The degree to which changes in lake sediment records co-occurred with changes in the timing of ice-out or agricultural land use was negatively correlated with the ratio of watershed area to lake area. Thus, both climate and land management appeared to play key roles in regulation of primary production in these lakes, although the manner in which these factors influenced lakes was mediated by catchment morphometry. Improved understanding of the past interactions between climate change, land use, landscape setting, and water quality underscores the complexity of mechanisms regulating lake and cyanobacterial production and highlights the necessity of considering these interactions-rather than searching for a singular mechanism-when evaluating the causes of ongoing changes in low-nutrient lakes.
Keywords: agriculture; basin morphometry; Cyanobacteria; eutrophication; Gloeotrichia; ice-out; land use; Maine; New Hampshire; paleoecology; Sediment chemistry; watershed

Origin of Groundwater Arsenic in a Rural Pleistocene Aquifer in Bangladesh Depressurized by Distal Municipal Pumping - Mozumder, M. R. H.; Michael, H. A.; Mihajlov, I.; Khan, M. R.; Knappett, P. S. K.; Bostick, B. C.; Mailloux, B. J.; Ahmed, K. M.; Choudhury, I.; Koffman, T.; Ellis, T.; Whaley‐Martin, K.; et al. (Water Resources Research, 2020)
Across South Asia, millions of villagers have reduced their exposure to high‐arsenic (As) groundwater by switching to low‐As wells. Isotopic tracers and flow modeling are used in this study to understand the groundwater flow system of a semi‐confined aquifer of Pleistocene (>10 kyr) age in Bangladesh that is generally low in As but has been perturbed by massive pumping at a distance of about 25 km for the municipal water supply of Dhaka. A 10‐ to 15‐m‐thick clay aquitard caps much of the intermediate aquifer (>40‐ to 90‐m depth) in the 3‐km2 study area, with some interruptions by younger channel sand deposits indicative of river scouring. Hydraulic heads in the intermediate aquifer below the clay‐capped areas are 1–2 m lower than in the high‐As shallow aquifer above the clay layer. In contrast, similar heads in the shallow and intermediate aquifer are observed where the clay layer is missing. The head distribution suggests a pattern of downward flow through interruptions in the aquitard and lateral advection from the sandy areas to the confined portion of the aquifer. The interpreted flow system is consistent with 3H‐3He ages, stable isotope data, and groundwater flow modeling. Lateral flow could explain an association of elevated As with high methane concentrations within layers of gray sand below certain clay‐capped portions of the Pleistocene aquifer. An influx of dissolved organic carbon from the clay layer itself leading to a reduction of initially orange sands has also likely contributed to the rise of As.
Keywords: Arsenic; Dhaka Bangladesh; groundwater pumping; modeling

Permafrost Hydrology Drives the Assimilation of Old Carbon by Stream Food Webs in the Arctic - O’Donnell, Jonathan A.; Carey, Michael P.; Koch, Joshua C.; Xu, Xiaomei; Poulin, Brett A.; Walker, Jennifer; Zimmerman, Christian E. (Ecosystems, 2020)
Permafrost thaw in the Arctic is mobilizing old carbon (C) from soils to aquatic ecosystems and the atmosphere. Little is known, however, about the assimilation of old C by aquatic food webs in Arctic watersheds. Here, we used C isotopes (δ13C, Δ14C) to quantify C assimilation by biota across 12 streams in arctic Alaska. Streams spanned watersheds with varying permafrost hydrology, from ice-poor bedrock to ice-rich loess (that is, yedoma). We measured isotopic content of (1) C sources including dissolved organic C (DOC), dissolved inorganic C (DIC), and soil C, and (2) stream biota, including benthic biofilm and macroinvertebrates, and resident fish species (Arctic Grayling (Thymallus arcticus) and Dolly Varden (Salvelinus malma)). Findings document the assimilation of old C by stream biota, with depleted Δ14C values observed at multiple trophic levels, including benthic biofilm (14C ages = 5255 to 265 years before present (y BP)), macroinvertebrates (4490 y BP to modern), and fish (3195 y BP to modern). Mixing model results indicate that DOC and DIC contribute to benthic biofilm composition, with relative contributions differing across streams draining ice-poor and ice-rich terrain. DOC originates primarily from old terrestrial C sources, including deep peat horizons (39–47%; 530 y BP) and near-surface permafrost (12–19%; 5490 y BP). DOC also accounts for approximately half of fish isotopic composition. Analyses suggest that as the contribution of old C to fish increases, fish growth and nutritional status decline. We anticipate increases in old DOC delivery to streams under projected warming, which may further alter food web function in Arctic watersheds.

Provenance of terrigenous sediments in the central Bay of Bengal and its relationship to climate changes since 25 ka - Li, Jingrui; Liu, Shengfa; Shi, Xuefa; Chen, Min-Te; Zhang, Hui; Zhu, Aimei; Cui, Jingjing; Khokiattiwong, Somkiat; Kornkanitnan, Narumol (Progress in Earth and Planetary Science, 2020)
Lithogenic grain-size, geochemical elements of core sediments from the central Bay of Bengal (BoB) were analyzed to identify sediment provenance and explore the regional “source-sink” processes since 25 ka. Based on the geochemical compositions of core BoB-88, relative contributions of three end-member sources (Himalayan, Myanmar, Indian Peninsula) were calculated and support the general understanding that Himalayan sources were dominant since the last glacial period, which could reach 70% on average in our study. However, sediments from the Indian Peninsula and Myanmar also contributed nonnegligible materials to the central BoB since 25 ka, especially the former shows an obvious increase since 7.5 ka, which was neglected in the previous studies. To trace the sedimentary processes of different provenance terrigenous materials and reveal their response to climate changes, four typical stages with obvious provenance percent variation, including the Last Glacial Maximum period (LGM), Heinrich 1 (H1), Early Holocene Climate Optimum (EHCO), and mid-late Holocene period, were highlighted and discussed. Sea-level change played a dominant role in the glacial-interglacial scale by controlling the transition of deposition center between the shelf/subaquatic delta and the Bengal Fan, especially for sediment from the Himalayan source, exerting influence on contributions from different provenance end-members between the Holocene and the last glacial period. The opposite directions of the southwest and northeast monsoon current in the BoB have a significant influence on the transfer of the Indian Peninsula and Myanmar materials to the studied core, which led to an increase of up to 11% than the average of the Indian Peninsula and a decrease of up to 9% than the average of the Myanmar source during the Holocene. The balance between sea level (limited transport to the deep sea) and ISM (improved erosion production and output to the BoB) during the mid-late Holocene period maintained the stability of Himalayan source percent. Due to the control of the ISM variations, the Himalayan source showed a decrease of up to 20% and 21% than average during the LGM and H1 period, respectively, and an increase of up to 14% than average during the EHCO. The Myanmar source exhibited fluctuations around the average value during the LGM period, but an obvious increase of up to 21% during the H1 period and a decrease up to 8% during the EHCO, while the Indian Peninsula source percent showed little variations during the LGM and H1, but a decrease of up to 6% during the EHCO. Obvious 1/4 processional and millennial periodic changes (5.0 kyr and 1.1 kyr) of contribution proportions from three end-members provide additional evidences for the climate control on the regional source-sink processes and proved the controlled mechanisms of the orbital parameters and possible influence from the solar activity on millennial scales.

A refined age calibrated paleosecular variation and relative paleointensity stack for the NW Barents Sea: Implication for geomagnetic field behavior during the Holocene - Caricchi, C.; Sagnotti, L.; Campuzano, S.A.; Lucchi, R.G.; MacrÌ, P.; Rebesco, M.; Camerlenghi, A. (Quaternary Science Reviews, 2020)
Reconstruction of Paleomagnetic Secular Variation (PSV) of the geomagnetic field is fundamental both to assess geodynamo models and to obtain age constraints for rocks, sediments and archaeological material. We present refined age-calibrated Holocene PSV and relative paleointensity (RPI) stack curves derived from Arctic marine sediments (Northwestern Barents Sea). The Holocene sections of four sedimentary cores were correlated on the basis of paleomagnetic trends and age models, and stacked. The resultant composite PSV and RPI Holocene records (NBS stack) and the reconstructed Holocene Virtual Geomagnetic Pole (VGP) path were evaluated in comparison with the most recent paleomagnetic stack curves and geomagnetic field models. The data indicate that during the Holocene time, the VGPs moved within the superficial projection of the inner core tangent cylinder, with the exception of short time intervals around 5600 and 3200 cal yr BP when VGPs extended to lower latitudes. These deviations might reflect regional geomagnetic features, such as persistent geomagnetic flux lobes at core-mantle boundary. Our data confirm that the large VGP shift observed around 5600 cal yr BP is the result of an increased radial magnetic field at the core-mantle boundary over North America, whilst the VGP shift around 3200 cal yr BP represents a major swing to middle latitudes toward the Middle East and might be associated to a regional high paleointensity peak, known as Levantine Iron Age Anomaly (LIAA).
Keywords: Arctic region; Barents Sea; Geomagnetic paleosecular variation; Holocene; marine sediment cores; Paleomagnetism; Relative paleointensity

Resolving sea ice dynamics in the north-western Ross Sea during the last 2.6 ka: From seasonal to millennial timescales - Tesi, T.; Belt, S.T.; Gariboldi, K.; Muschitiello, F.; Smik, L.; Finocchiaro, F.; Giglio, F.; Colizza, E.; Gazzurra, G.; Giordano, P.; Morigi, C.; Capotondi, L.; et al. (Quaternary Science Reviews, 2020)
Time-series analyses of satellite images reveal that sea ice extent in the Ross Sea has experienced significant changes over the last 40 years, likely triggered by large-scale atmospheric anomalies. However, resolving how sea ice in the Ross Sea has changed over longer timeframes has until now remained more elusive. Here we used a laminated sediment piston core (14.6 m) collected from the Edisto inlet (Western Ross Sea) to reconstruct fast ice dynamics over the last 2.6 ka. Our goal was to first understand the climate expression of selected well-defined sediment laminae and then use these characteristics for reconstructing past sea ice behaviour across the whole sedimentary sequence. We used the recently established sea ice diatom biomarker proxy IPSO25 in combination with diatom census counts and bulk analyses. Analyses performed on a suite of discrete laminae revealed statistically significant differences between dark and light laminae reflecting different depositional conditions. Based on their respective biogeochemical fingerprints, we infer that dark laminae accumulated during sea ice thaws in early summer. Under these conditions, laminae contain relatively high concentrations of IPSO25 and display an enriched δ13C composition for the bulk organic matter (OM). While diatom assemblages in dark laminae are relatively homogenous, as the thaw continues later in the summer, Corethron pennatum becomes the dominant diatom species, resulting in the formation of light laminae characterized by low IPSO25 concentrations. Since C. pennatum can migrate vertically through the water column to uptake nutrients and avoid competition in oligotrophic waters, its high concentration likely reflects stratified and ice-free surface waters typical of late summer. Down-core trends show that the correlation between sediment brightness and geochemical fingerprint (i.e., IPSO25 and δ13C) holds throughout the record. Based on the knowledge gained at lamina level, our down-core high-resolution reconstruction shows that the summer fast ice coverage changed dramatically during the late Holocene. Specifically, we conclude that the Edisto inlet experienced regular early summer opening between 2.6 ka, and ca. 0.7 ka, after which, coastal fast ice persisted during summer months and ice-free conditions became less frequent. Comparison with previous regional ice core data suggests that the sudden cooling recorded over the Victoria Land Coast region since 0.7 ka might potentially explain our observation of persistent summer fast ice in the Western Ross Sea. Our study has shown that multi-proxy data derived from laminated sediments can provide hitherto unknown detail regarding past summer sea ice dynamics in coastal Antarctic regions.
Keywords: Fast ice; IPSO25; Laminated sediments; Ross Sea; Sea ice

Sedimentary evidence of prehistoric distant‐source tsunamis in the Hawaiian Islands - La Selle, SeanPaul; Richmond, Bruce M.; Jaffe, Bruce E.; Nelson, Alan R.; Griswold, Frances R.; Arcos, Maria E. M.; Chagué, Catherine; Bishop, James M.; Bellanova, Piero; Kane, Haunani H.; Lunghino, Brent D.; Gelfenbaum, Guy (Sedimentology, 2020)
Over the past 200 years of written records, the Hawaiian Islands have experienced tens of tsunamis generated by earthquakes in the subduction zones of the Pacific ‘Ring of Fire’ (for example, Alaska–Aleutian, Kuril–Kamchatka, Chile and Japan). Mapping and dating anomalous beds of sand and silt deposited by tsunamis in low‐lying areas along Pacific coasts, even those distant from subduction zones, is critical for assessing tsunami hazard throughout the Pacific basin. This study searched for evidence of tsunami inundation using stratigraphic and sedimentological analyses of potential tsunami deposits beneath present and former Hawaiian wetlands, coastal lagoons, and river floodplains. Coastal wetland sites on the islands of Hawai΄i, Maui, O΄ahu and Kaua΄i were selected based on historical tsunami runup, numerical inundation modelling, proximity to sandy source sediments, degree of historical wetland disturbance, and breadth of prior geological and archaeological investigations. Sand beds containing marine calcareous sediment within peaty and/or muddy wetland deposits on the north and north‐eastern shores of Kaua΄i, O΄ahu and Hawai΄i were interpreted as tsunami deposits. At some sites, deposits of the 1946 and 1957 Aleutian tsunamis are analogues for deeper, older probable tsunami deposits. Radiocarbon‐based age models date sand beds from three sites to ca 700 to 500 cal yr bp, which overlaps ages for tsunami deposits in the eastern Aleutian Islands that record a local subduction zone earthquake. The overlapping modelled ages for tsunami deposits at the study sites support a plausible correlation with an eastern Aleutian earthquake source for a large prehistoric tsunami in the Hawaiian Islands.
Keywords: Aleutians; deposit; distant source; extreme events; Hawai΄i; palaeotsunami

The southern Gulf of Mexico: A baseline radiocarbon isoscape of surface sediments and isotopic excursions at depth - Bosman, Samantha H.; Schwing, Patrick T.; Larson, Rebekka A.; Wildermann, Natalie E.; Brooks, Gregg R.; Romero, Isabel C.; Sanchez-Cabeza, Joan-Albert; Ruiz-Fernández, Ana Carolina; Machain-Castillo, Maria Luisa; Gracia, Adolfo; Escobar-Briones, Elva; Murawski, Steven A.; et al. (PLOS ONE, 2020)
The southern Gulf of Mexico (sGoM) is home to an extensive oil recovery and development infrastructure. In addition, the basin harbors sites of submarine hydrocarbon seepage and receives terrestrial inputs from bordering rivers. We used stable carbon, nitrogen, and radiocarbon analyses of bulk sediment organic matter to define the current baseline isoscapes of surface sediments in the sGoM and determined which factors might influence them. These baseline surface isoscapes will be useful for accessing future environmental impacts. We also examined the region for influence of hydrocarbon deposition in the sedimentary record that might be associated with hydrocarbon recovery, spillage and seepage, as was found in the northern Gulf of Mexico (nGoM) following the Deepwater Horizon (DWH) oil spill in 2010. In 1979, the sGoM experienced a major oil spill, Ixtoc 1. Surface sediment δ13C values ranged from -22.4‰ to -19.9‰, while Δ14C values ranged from -337.1‰ to -69.2‰. Sediment δ15N values ranged from 2.8‰ to 7.2‰, while the %C on a carbonate-free basis ranged in value of 0.65% to 3.89% and %N ranged in value of 0.09% to 0.49%. Spatial trends for δ13C and Δ14C were driven by water depth and distance from the coastline, while spatial trends for δ15N were driven by location (latitude and longitude). Location and distance from the coastline were significantly correlated with %C and %N. At depth in two of twenty (10%) core profiles, we found negative δ13C and Δ14C excursions from baseline values in bulk sedimentary organic material, consistent with either oil-residue deposition or terrestrial inputs, but likely the latter. We then used 210Pb dating on those two profiles to determine the time in which the excursion-containing horizons were deposited. Despite the large spill in 1979, no evidence of hydrocarbon residue remained in the sediments from this specific time period.
Keywords: Gulf of Mexico; hydrocarbons; Oil spills; Oils; Petroleum; Sediment

Spatial and temporal variability in Mediterranean climate over the last millennium from vermetid isotope records and CMIP5/PMIP3 models - Amitai, Yael; Yam, Ruth; Montagna, Paolo; Devoti, Saverio; Correa, Matthias López; Shemesh, Aldo (Global and Planetary Change, 2020)
Stable isotope compositions of oxygen (delta O-18) and carbon (delta C-1(3)) of the aragonite skeleton of the reef-building gastropod Dendropoma petreaum provide high-resolution records of the Mediterranean climate over the last millennium. In particular, the isotopic composition of vermetid cores collected from the west and east Mediterranean reveals that the different regions have had distinct thermal and primary production behaviors throughout the last millennium. The rate of warming in the recent Industrial Period is variable among the different regions of the Mediterranean Sea. The delta O-18-derived Sea Surface Temperature (SST) anomalies show that the Eastern Mediterranean surface temperature is increasing much more rapidly than in the Western Mediterranean. Additionally, the signals of the Little Ice Age and of the Medieval Climate Anomaly are more apparent in the western and in the central Mediterranean while they are almost absent in the eastern Mediterranean. We aim to reconcile the SST temporal and spatial pattern with the variability of the North Atlantic Oscillation (NAO) and the South Asian Monsoon (SAM) climate systems by analyzing coupled atmosphere-ocean models from the CMIP5/PMIP3 projects that simulate the global climate of the past 1000 years. We show that even though the NAO is more dominant in the western Mediterranean SST, its latitudinal movement, on a centennial time scale, is evident in the eastern Mediterranean SST signal. We also discuss the Atlantic water inflow role in the observed similarities of the surface productivity signals and the Suess effect that prevail the Industrial Period signal in all regions of the Mediterranean.

Analysis of multiple cosmogenic nuclides constrains Laurentide Ice Sheet history and process on Mt. Mansfield, Vermont's highest peak - Corbett, Lee B.; Bierman, Paul R.; Wright, Stephen F.; Shakun, Jeremy D.; Davis, P. Thompson; Goehring, Brent M.; Halsted, Christopher T.; Koester, Alexandria J.; Caffee, Marc W.; Zimmerman, Susan R. (Quaternary Science Reviews, 2019)
Constraining glacial history and process on Mt Mansfield, the highest peak in Vermont (1339 m a.s.l.), provides insight into how the Laurentide Ice Sheet shaped the underlying landscape, when latest Pleistocene ice retreated, and how upland and lowland glacial histories relate. Here, we quantify in situ cosmogenic 10Be in 20 bedrock and boulder surfaces, as well as in situ cosmogenic 14C in three of those surfaces, to assess subglacial erosion and exposure history. Isotopic concentrations indicate that Mt. Mansfield's lower elevations (∼400–1200 m a.s.l.) were deeply eroded by at least several meters during the last glaciation and then deglaciated rapidly; 10Be ages across this elevation span are indistinguishable and average 13.9 ± 0.6 ka (n = 15), suggesting that 800 m of ice thinning occurred within at most about a millennium. Conversely, the higher elevations (>1200 m a.s.l.) preserve a more complex geomorphic history. Mt. Mansfield's summit surfaces contain 10Be from previous periods of exposure, indicating that the mountaintop landscapes were likely preserved beneath cold-based, weakly-erosive glacial ice. Exposure ages from the shorter-lived isotope, 14C, are younger (9.7 and 11.7 ka), suggesting that Mt. Mansfield's summit was covered until the early Holocene, perhaps by snowfields, ice carapaces, and/or till. Our findings, in context of previous work, suggest that thinning Laurentide ice flowed through the valleys for at most hundreds of years following deglaciation of the uplands, but that the summit remained shielded by ice or sediment for millennia after the valleys became ice-free.
Keywords: Cosmogenic isotopes; erosion; Geochronology; Glaciation; Last glacial maximum; North America; Pleistocene

Annual radiocarbon measurements in a century-old European beech tree (Fagus sylvatica) from coastal northeastern North America - Gaylord, Mary C. Lardie; Longworth, Brett E.; Murphy, Keelan; Cobb, Caroline; McNichol, Ann P. (NUCLEAR INSTRUMENTS & METHODS IN PHYSICS RESEARCH SECTION B-BEAM INTERACTIONS WITH MATERIALS AND ATOMS, 2019)
Radiocarbon (C-14) concentrations of annual tree rings from an European beech tree (Fagus sylvatica) from Woods Hole, MA, USA were analyzed at National Ocean Sciences Accelerator Mass Spectrometry facility (NOSAMS) to construct a C-14 bomb curve record from northeastern North America. The C-14 concentration rises from a pre bomb (1895-1955) average of Fraction Modern ((FC)-C-14) = 0.9764 to a peak of 1.8639 in 1964. After 1964, (FC)-C-14 gradually decreases to 1.0611 in 2014. The annual tree-ring radiocarbon content agrees with the atmospheric radiocarbon content of the Northern Hemisphere and is very similar to the radiocarbon concentration of a red oak (Quercus rubra) tree located in Bear Mountain State Park in New York, USA. Infra-annual tree-ring pairs did not produce evidence of a seasonal effect on the radiocarbon concentration, but there were few samples and more study is warranted.

Bigmouth Buffalo Ictiobus cyprinellus sets freshwater teleost record as improved age analysis reveals centenarian longevity - Lackmann, Alec R.; Andrews, Allen H.; Butler, Malcolm G.; Bielak-Lackmann, Ewelina S.; Clark, Mark E. (Communications Biology, 2019)
Understanding the age structure and population dynamics of harvested species is crucial for sustainability, especially in fisheries. The Bigmouth Buffalo (Ictiobus cyprinellus) is a fish endemic to the Mississippi and Hudson Bay drainages. A valued food-fish for centuries, they are now a prized sportfish as night bowfishing has become a million-dollar industry in the past decade. All harvest is virtually unregulated and unstudied, and Bigmouth Buffalo are declining while little is known about their biology. Using thin-sectioned otoliths and bomb-radiocarbon dating, we find Bigmouth Buffalo can reach 112 years of age, more than quadrupling previous longevity estimates, making this the oldest known freshwater teleost (~12,000 species). We document numerous populations that are comprised largely (85-90%) of individuals over 80 years old, suggesting long-term recruitment failure since dam construction in the 1930s. Our findings indicate Bigmouth Buffalo require urgent attention, while other understudied fishes may be threatened by similar ecological neglect.
Keywords: Ageing; Conservation biology; Freshwater ecology; Ichthyology

CO2-dependent carbon isotope fractionation in Archaea, Part II: The marine water column - Hurley, Sarah J.; Close, Hilary G.; Elling, Felix J.; Jasper, Claire E.; Gospodinova, Kalina; McNichol, Ann P.; Pearson, Ann (GEOCHIMICA ET COSMOCHIMICA ACTA, 2019)
Stable carbon isotope ratios of archaeal glycerol dibiphytanyl glycerol tetraether (GDGT) lipids have been proposed as a proxy to infer past changes in the carbon isotope composition (delta C-13) of dissolved inorganic carbon (DIC). The premise for paleo-delta C-13(DIC) reconstructions from GDGTs is based on observations of relatively constant delta C-13(GDGT) values in recent depositional environments. Marine Thaumarchaeota, thought to be the dominant source of GDGTs to marine sediments, fix inorganic carbon using the 3-hydroxypropionate/4-hydroxybutyrate (3HP/4HB) pathway, which is specific to HCO3- as the substrate. Bicarbonate-dependent autotrophy has been the basis for predicting that the stable carbon isotopic composition of GDGTs (delta C-13(GDGT)) should vary in parallel with water column delta C-13(DIC) values, because HCO3- is by far the dominant fraction of DIC in modern seawater. However, this relationship has never been systematically tested. Here we examine the carbon isotopic composition of GDGTs from four water column profiles in the Southwest and Equatorial Atlantic Ocean. Values of delta C-13(GDGT) increase with depth in the water column, in contrast to the characteristic decrease in delta C-13(DIC) values. These divergent trends imply a decrease in the observed total biosynthetic isotope effect (epsilon(Ar)) with depth, i.e., the offset between delta(13)(DIC) and delta C-13(GDGT) is not constant. Instead, we find that values of epsilon(Ar) specifically correlate with oceanographic variables associated with extent of organic remineralization, decreasing as CO2 concentration increases. This observed relationship is consistent in both magnitude and direction with the results of an isotope flux-balance model for Thaumarchaeota that suggests epsilon(Ar) should be sensitive to growth rate (mu) and CO2 availability under conditions of atmospheric pCO(2) < 4 times the pre-anthropogenic Holocene level. Further tests of the sensitivity of epsilon(Ar) to u and CO2 in the modern marine environment will be essential to exploring the potential for a new, archaeal lipid-derived pCO(2) paleobarometer. (C) 2019 Elsevier Ltd. All rights reserved.

Coupled ocean and atmospheric changes during Greenland stadial 1 in southwestern Europe - Naughton, F.; Costas, S.; Gomes, S.D.; Desprat, S.; Rodrigues, T.; Sanchez Goñi, M.F.; Renssen, H.; Trigo, R.; Bronk-Ramsey, C.; Oliveira, D.; Salgueiro, E.; Voelker, A.H.L.; et al. (Quaternary Science Reviews, 2019)
Paleoclimate reconstructions suggest that the complex variability within the Greenland stadial 1 (GS-1) over western Europe was governed by coupled ocean and atmospheric changes. However, few works from the North Atlantic mid-latitudes document both the GS-1 onset and its termination, which are often considered as single abrupt transition events. Here, we present a direct comparison between marine (alkenone-based sea surface temperatures) and terrestrial (pollen) data, at very high resolution (28 years mean), from the southwestern Iberian shelf record D13882. Our results reveal a rather complex climatic period with internally changing conditions. The GS-1 onset (GS-1a: 12890-12720 yr BP) is marked by a progressive cooling and drying; GS-1b (12720-12390 yr BP) is the coldest and driest phase; GS-1c (12390-12030 yr BP) is marked by a progressive warming and increase in moisture conditions; GS-1 termination (GS-1d: 12030-11770 yr BP) is marked by rapid switches between cool wet, cold dry and cool wet conditions. Although hydroclimate response was very unsteady throughout the GS-1 and in particular during its termination phase, the persistence of an open temperate and Mediterranean forest in southwestern Iberia during the entire episode suggests that at least some moisture was delivered via the Westerlies. We propose coupled ocean and atmospheric mechanisms to reproduce these scenaria. Changes in the strength of the Atlantic Meridional Overturning Circulation (AMOC) as well as variations in the North Atlantic sea-ice growth have favoured the displacement of the polar jet stream's latitudinal position and contributed to a complex spatial pattern and strength of the Westerlies across western Europe.
Keywords: Climate variability; Greenland stadial; Iberian margin; Jet stream; Moisture availability; North Atlantic; Paleoclimate; Westerlies; Younger Dryas Complex

Discovery of an Extensive Deep-Sea Fossil Serpulid Reef Associated With a Cold Seep, Santa Monica Basin, CaliforniaTable_1.docx - Georgieva, Magdalena N.; Paull, Charles K.; Little, Crispin T. S.; McGann, Mary; Sahy, Diana; Condon, Daniel; Lundsten, Lonny; Pewsey, Jack; Caress, David W.; Vrijenhoek, Robert C. (Frontiers in Marine Science, 2019)
Multibeam bathymetric mapping of the Santa Monica Basin in the eastern Pacific has revealed the existence of a number of elevated bathymetric features, or mounds, harboring cold seep communities. During 2013–2014, mounds at ∼600 m water depth were observed for the first time and sampled by Monterey Bay Aquarium Research Institute’s ROV Doc Ricketts. Active cold seeps were found, but surprisingly one of these mounds was characterized by massive deposits composed of fossil serpulid worm tubes (Annelida: Serpulidae) exhibiting various states of mineralization by authigenic carbonate. No living serpulids with equivalent tube morphologies were found at the site; hence the mound was termed “Fossil Hill.” In the present study, the identity of the fossil serpulids and associated fossil community, the ages of fossils and authigenic carbonates, the formation of the fossil serpulid aggregation, and the geological structure of the mound are explored. Results indicate that the tubes were most likely made by a deep-sea serpulid lineage, with radiocarbon dating suggesting that they have a very recent origin during the Late Pleistocene, specifically to the Last Glacial Maximum ∼20,000 years ago. Additional U-Th analyses of authigenic carbonates mostly corroborate the radiocarbon dates, and also indicate that seepage was occurring while the tubes were being formed. We also document similar, older deposits along the approximate trajectory of the San Pedro Basin Fault. We suggest that the serpulid tube facies formed in situ, and that the vast aggregation of these tubes at Fossil Hill is likely due to a combination of optimal physical environmental conditions and chemosynthetic production, which may have been particularly intense as a result of sea-level lowstand during the Last Glacial Maximum.

Evidence for frequent, large tsunamis spanning locked and creeping parts of the Aleutian megathrust - Witter, Rob; Briggs, Rich; Engelhart, Simon E.; Gelfenbaum, Guy; Koehler, Rich D.; Nelson, Alan; Selle, SeanPaul La; Corbett, Reide; Wallace, Kristi (GSA Bulletin, 2019)
At the eastern end of the 1957 Andreanof Islands, Alaska, USA, moment magnitude 8.6 earthquake rupture, Driftwood Bay (Umnak Island) and Stardust Bay (Sedanka Island) lie along presently locked and creeping parts of the Aleutian megathrust, respectively, based on satellite geodesy onshore. Both bays, located 200 km apart, face the Aleutian trench and harbor coastal evidence for tsunami inundation in 1957. Here we describe the evidence at Driftwood Bay, including eight sheets of landward-fining, normally-graded marine sand that extend up to 375 m inland and 23 m above mean tide level. Drift logs that corroborate historical accounts of 1957 tsunami runup on Umnak Island’s Pacific coast overlie the youngest sand sheet, which 137Cs activity shows was deposited in the decade before 1963. The older sand sheets probably record tsunamis prior to 1957 because an emergent coastal terrace lacks evidence for storm-wave erosion and overwash since ca. 2 ka. Comparisons of the Driftwood Bay and Stardust Bay tsunami histories suggest that at least twice in the past 1700 years inundation occurred at one site but not the other. In contrast, Bayesian age-depth modeling suggests that the two bays may record five tsunamis like the 1957 tsunami, generated by earthquake ruptures that spanned the presently locked and creeping parts of the Aleutian megathrust. However, serial tsunamis occurring within days to centuries cannot be precluded. Our findings imply 164–257-year recurrence intervals for large eastern Aleutian tsunamis and challenge the notion that creeping parts of the megathrust, inferred from geodesy onshore, pose lower earthquake and tsunami hazards than locked areas.

Examining Coastal Dynamics and Archaeological Site Evidence at a Drowned Cirque Basin Influenced by Earthquakes and Little Ice Age Glaciation - Maio, Christopher V.; Crowell, Aron L.; Sullivan, Richard M.; Buzard, Richard M.; Whitley, Matthew A.; Bogardus, Reyce C.; Wit, Cary W. de (Journal of Coastal Research, 2019)
This study contributes baseline information regarding the framework geology, drivers of coastal change, and archaeological record along the fjord-indented coastlines of southcentral Alaska. Field data were collected in July 2015 from James Lagoon, a 30-m-deep drowned cirque valley adjacent to McCarty Fjord in the Nuka Bay region of Kenai Fjords National Park. A 1790 CE terminal moraine deposited by McCarty Glacier extends across the cirque opening and delimits the lagoon. Acoustic surveys of the lagoon reveal bedrock overlain by deltaic, lacustrine, and marine facies containing beds that indicate past submarine landslides. Lagoon and marsh sediment cores contain coarse sand horizons interbedded with silt and peat, evidence of repeated low-frequency, high-intensity events. The largest of the event beds in the marine cores occurs near the surface and is likely associated with the 1964 Great Alaska Earthquake (moment magnitude 9.2). Trees killed during the 1964 earthquake fringe the coastline and indicate ∼2 m of coseismic subsidence. Radiocarbon ages of five exposed subfossil stumps indicate two pre-1964 subsidence events occurring between 1710 and 1789 and 1078 and 1125 median probability calendar year CE (cal CE). A Sugpiaq culture archaeological site dated to 1565 cal CE existed on the western shore of James Lagoon in the interval between these two events, possibly for proximity to an ice floe harbor seal rookery at McCarty Glacier. Archaeological site elevation above mean high water at James Lagoon and around Nuka Bay is inversely related to the extent of cumulative site erosion caused by coastal submergence during the last two great earthquakes. These combined findings lay the groundwork for future research and provide context to ongoing coastal hazards and their effects on cultural resources.

A fluvially derived flood deposit dating to the Kamikaze typhoons near Nagasaki, Japan - Ladlow, Caroline; Woodruff, Jonathan D.; Cook, Timothy L.; Baranes, Hannah; Kanamaru, Kinuyo (Natural Hazards, 2019)
Previous studies in western Kyushu revealed prominent marine-derived flood deposits that date to the late thirteenth-century and are interpreted to be a result of two legendary typhoons linked to the failed Mongol invasions of Japan in 1274 and 1281. The regional persistence and prominence of sediments dating to these “Kamikaze” typhoon events (meaning divine wind) raise questions about the origins of these late thirteenth-century deposits. This is due in part to uncertainty in distinguishing between tsunami and storm-induced deposition. To provide additional insight into the true cause of prominent late thirteenth-century flood deposits in western Kyushu, we present a detailed assessment of an additional event deposit dating to the late thirteenth-century from Lake Kawahara near Nagasaki, Japan. This particular deposit thickens landward towards the primary river flowing into Lake Kawahara and exhibits anomalously low Sr/Ti ratios that are consistent with a fluvial rather than a marine sediment source. When combined with previous flood reconstructions, results support the occurrence of an extreme, late thirteenth-century event that was associated with both intense marine- and river-derived flooding. Results therefore contribute to a growing line of evidence for the Kamikaze typhoons resulting in widespread flooding in the region, rather than the late thirteenth-century deposit being associated with a significant tsunami impact to western Kyushu.

Four Major Holocene Earthquakes on the Reelfoot Fault Recorded by Sackungen in the New Madrid Seismic Zone, USA - Gold, Ryan D.; DuRoss, Christopher B.; Delano, Jaime E.; Jibson, Randall W.; Briggs, Richard W.; Mahan, Shannon A.; Williams, Robert A.; Corbett, D. Reide (Journal of Geophysical Research: Solid Earth, 2019)
Three sequences of well‐documented, major ~M7+ earthquakes (1811–1812, ~1450, and ~900 CE) in the New Madrid seismic zone, USA, contribute significantly to seismic hazard in the region. However, it is unknown whether this <550‐year recurrence interval has been constant throughout the Holocene given limited geomorphic evidence of prior earthquakes. We extend the record of paleoearthquakes along the Reelfoot fault via investigation of ridgetop gravitational failure features, interpreted as sackungen. The sackungen occur in bluffs along the eastern margin of the Mississippi River floodplain and are concentrated near (<15 km) the southwest dipping Reelfoot reverse fault. A paleoseismic trench excavated across sackungen at the Paw Paw site exposed four packages of colluvial sediment that postdate 30‐ to 11‐ka Peoria Loess. We interpret the colluvial packages to have been deposited following episodic failure of the sackungen as a result of strong ground motions from the following sequence of earthquakes: event 4, 1640 ± 1730 BCE; event 3, 270 ± 670 CE; event 2, 1430 ± 380 CE; and event 1, 1810 ± 50 CE (2 sigma). Event timing corresponds to previously documented earthquakes and represents the longest archive of paleoearthquakes on the Reelfoot fault. If the trenched sackungen record all major Reelfoot fault earthquakes, our observations in combination with prior investigations indicate a period of quiescence from at least 11 to 4.4 ka, followed by four major seismic events culminating in the 1811–1812 CE sequence. This clustered earthquake recurrence pattern helps place bounds on seismic hazard and geodynamic models in the New Madrid seismic zone.

Holocene and Last Interglacial climate of the Faroe Islands from sedimentary plant wax hydrogen and carbon isotopes - Curtin, Lorelei; D'Andrea, William J.; Balascio, Nicholas; Pugsley, Genevieve; de Wet, Gregory; Bradley, Raymond (Quaternary Science Reviews, 2019)
The Last Interglacial period (LIG) is Earth's most recent globally warm period and is analogous in some ways to projected future global warming. However, questions remain regarding the state of the climate during the LIG in the North Atlantic, a region that is extremely sensitive to changes in oceanic and atmospheric circulation. Here, we present hydrogen and carbon isotope (δD and δ13C) records from a suite of plant wax biomarkers preserved in Holocene and LIG lacustrine sediments from the North Atlantic Faroe Islands and interpret them as qualitative proxies for temperature and hydroclimate variability. These data are used to directly compare LIG and Holocene climate using the same proxy approaches from the same terrestrial location. Measuring multiple isotopes on multiple types of waxes elucidates the sources of homologous plant waxes. We deduce that the δD values of long-chain n-alkanes (C27–C33) and mid-chain n-alkanes (C23–C25) in these sedimentary archives reflect leaf water and lake water δD values, respectively, while the δD values for both long-chain (C28–C30) and mid-chain n-alkanoic acids (C24–C26) primarily represent lake water δD values. Plant wax-inferred δD values of precipitation during the early Holocene (10,100 to 8,200  cal  yr BP) are ∼35‰ more positive than late Holocene values, and decline over the Holocene. δD-inferred hydrologic change and δ13C -inferred plant water use efficiency both indicate that the Faroe Islands became drier throughout the Holocene. Comparison with measurements from LIG plant waxes indicates that late LIG in the Faroe Islands was hydrologically similar to the early-to mid-Holocene (8,200 to 4,000  cal  yr BP), with enriched precipitation isotopes and reduced evapotranspiration indicating a warmer, wetter environment.
Keywords: Holocene; interglacial; North Atlantic; Organic geochemistry; paleoclimatology; Stable isotopes

Holocene paleodepositional changes reflected in the sedimentary microbiome of the Black Sea - More, Kuldeep D.; Giosan, Liviu; Grice, Kliti; Coolen, Marco J. L. (Geobiology, 2019)
Subsurface microbial communities are generally thought to be structured through in situ environmental conditions such as the availability of electron acceptors and donors and porosity, but recent studies suggest that the vertical distribution of a subset of subseafloor microbial taxa, which were present at the time of deposition, were selected by the paleodepositional environment. However, additional highly resolved temporal records of subsurface microbiomes and paired paleoenvironmental reconstructions are needed to justify this claim. Here, we performed a highly resolved shotgun metagenomics survey to study the taxonomic and functional diversity of the subsurface microbiome in Holocene sediments underlying the permanently stratified and anoxic Black Sea. Obligate aerobic bacteria made the largest contribution to the observed shifts in microbial communities associated with known Holocene climate stages and transitions. This suggests that the aerobic fraction of the subseafloor microbiome was seeded from the water column and did not undergo post-depositional selection. In contrast, obligate and facultative anaerobic bacteria showed the most significant response to the establishment of modern-day environmental conditions 5.2 ka ago that led to a major shift in planktonic communities and in the type of sequestered organic matter available for microbial degradation. No significant shift in the subseafloor microbiome was observed as a result of environmental changes that occurred shortly after the marine reconnection, 9 ka ago. This supports the general view that the marine reconnection was a gradual process. We conclude that a high-resolution analysis of downcore changes in the subseafloor microbiome can provide detailed insights into paleoenvironmental conditions and biogeochemical processes that occurred at the time of deposition.
Keywords: geomicrobiology; palaeo-environment; paleoecology; sedimentary metagenomes; subsurface microbiome; sulfur cycle.

Holocene sea-level variability from Chesapeake Bay Tidal Marshes, USA - Cronin, Thomas M; Clevenger, Megan K; Tibert, Neil E; Prescott, Tammy; Toomey, Michael; Hubeny, J Bradford; Abbott, Mark B; Seidenstein, Julia; Whitworth, Hannah; Fisher, Sam; Wondolowski, Nick; Ruefer, Anna (The Holocene, 2019)
We reconstructed the last 10,000 years of Holocene relative sea-level rise (RSLR) from sediment core records near Chesapeake Bay, eastern United States, including new marsh records from the Potomac and Rappahannock Rivers, Virginia. Results show mean RSLR rates of 2.6 mm yr−1 from 10 to 8 kilo-annum (ka) due to combined final ice-sheet melting during deglaciation and glacio-isostatic adjustment (GIA subsidence). Mean RSLR rates from ~6 ka to present were 1.4 mm yr−1 due mainly to GIA, consistent with other East Coast marsh records and geophysical models. However, a progressively slower mean rate (<1.0 mm yr−1) characterized the last 1000 years when a multi-century-long period of tidal marsh development occurred during the ‘Medieval Climate Anomaly’ (MCA) and ‘Little Ice Age’ (LIA) in the Chesapeake Bay region and other East Coast marshes. This decrease was most likely due to climatic and glaciological processes and, correcting for GIA, represents a fall in global mean sea level (GMSL) near the end of Holocene Neoglacial cooling. These pre-historical climate- and GIA-driven Chesapeake Bay sea-level changes contrast sharply with those based on Chesapeake Bay tide-gauge rates (3.1–4.5 mm yr−1) (back to 1903). After subtracting the GIA subsidence component, these rates can be attributed to long-term (millennial) global factors of accelerated ocean thermal expansion (~1.0 mm yr−1) and mass loss from alpine glaciers and Greenland and Antarctic Ice Sheets (1.5–2.0 mm yr−1).
Keywords: chesapeake bay; Foraminifera; Holocene; sea level; tidal marsh; US East Coast

Illuminating microbial species‐specific effects on organic matter remineralization in marine sediments - Mahmoudi, Nagissa; Enke, Tim N.; Beaupré, Steven R.; Teske, Andreas P.; Cordero, Otto X.; Pearson, Ann (Environmental Microbiology, 2019)

Laser ablation–accelerator mass spectrometry reveals complete bomb 14C signal in an otolith with confirmation of 60-year longevity for red snapper (Lutjanus campechanus) - Andrews, Allen H.; Yeman, Christiane; Welte, Caroline; Hattendorf, Bodo; Wacker, Lukas; Christl, Marcus (Marine and Freshwater Research, 2019)
Bomb-produced14C has been used to make valid estimates of age for various marine organisms for 25 years, but fish ages that lead to birth years earlier than the period of increase in14C lose their time specificity. As a result, bomb14Cdating is limited to a minimum age from the last year of prebomb levels because the temporal variation in14C in the marine surface layer is negligible for decades before c. 1958. The longevity of red snapper (Lutjanus campechanus) in the Gulf of Mexico remains unresolved despite various forms of support for ages near 50–60 years. Although the age and growth of red snapper have been verified or validated to a limited extent, some scepticism remains about longevity estimates that exceed30 years. In this study, red snapper otoliths were analysed for14C using a novel laser ablation–accelerator mass spectrometry technique to provide a continuousrecordof14C uptake. This approach provided a basis for age validation that extends beyond the normal limits of bomb14C dating with confirmation of a 60-year longevity for red snapper in the Gulf of Mexico.
Keywords: Age validation; Carbon-14; Gulf of Mexico; Lutjanidae; radiocarbon.

Legacy sediment storage in New England river valleys: Anthropogenic processes in a postglacial landscape - Johnson, Kaitlin M.; Snyder, Noah P.; Castle, Stephanie; Hopkins, Austin J.; Waltner, Mason; Merritts, Dorothy J.; Walter, Robert C. (Geomorphology, 2019)
Legacy sediment associated with erosion from land clearing is a common feature in river valleys of the unglaciated Mid-Atlantic Piedmont region. Here, we quantify the volume of legacy sediment storage in three watersheds in New England, a formerly glaciated region with similar history and intensity of forest clearing and milldam construction during the seventeenth to nineteenth centuries. We combine field observations of bank stratigraphy, radiocarbon dating, and mapping of terraces and floodplains using lidar digital elevation models and other GIS datasets. The 68 km2 South River watershed in western Massachusetts exhibits the most extensive evidence for legacy sediment storage. We visited 18 historic dam sites in the watershed and found field evidence for up to 2.2 m of fine sand and silt legacy sediment storage at 14 of the sites. In the 555 km2 Sheepscot River watershed in coastal Maine, we visited 13 historic dam sites and found likely legacy sediment up to 2.3 m thick at six of the dams. In the 171 km2 upper Charles River watershed in eastern Massachusetts, we investigated 14 dam sites, and found legacy sediment up to 1.8 m thick at two of them. Stratigraphically, we identified the base of fine-grained legacy sediment from a change to much coarser grain size (gravel at most sites) or to glacial lacustrine or marine deposits. Along the Sheepscot River, we observed cut timbers underlying historic sediment at several locations, likely associated with sawmill activities. Only at the Charles River were we able to radiocarbon date the underlying gravel layer (1281–1391 calibrated CE). At no site did we find a buried organic-rich Holocene soil, in contrast to the field relations commonly observed in the Mid-Atlantic region. We use lidar elevation data to map planar terrace extents in each watershed, estimate thickness of remaining legacy sediment found stored behind breached or removed milldams, and estimate volumes of remaining legacy sediment storage in valley bottoms for entire watersheds. The maximum volume of stored legacy sediment estimated for the South, Sheepscot, and upper Charles watersheds is 2.5 × 106 m3, 3.7 × 106 m3, and 2.6 × 104 m3, respectively. These volumes of legacy sediment can be translated to an equivalent thickness of soil eroded from each watershed: 37 mm, 7 mm, and 0.2 mm, respectively. We attribute the variation in presence and thickness of legacy sediment at the New England sites to the existence or absence of upstream sediment supply in the form of thick glacial deposits and to sinks such as lakes and wetlands along valley bottoms. Of the three study watersheds, the South River has the most extensive glacial sediments, fewest sinks, and the most legacy sediment in storage along the river corridor.
Keywords: Anthropogenic sediment; Legacy sedimen; Milldams

Mapping Isotopic and Dissolved Organic Matter Baselines in Waters and Sediments of the Gulf of Mexico - Chanton, Jeffrey P.; Jaggi, Aprami; Radović, Jagoš R.; Rosenheim, Brad E.; Walker, Brett D.; Larter, Stephen R.; Rogers, Kelsey; Bosman, Samantha; Oldenburg, Thomas B. P. (Springer International Publishing, 2019)
The Deepwater Horizon oil spill released petroleum hydrocarbons that were depleted in δ13C and Δ14C at depth into the Gulf of Mexico. Stable-carbon and radiocarbon isotopic values and high-resolution mass spectrometry were used to follow the distributions of this petroleum and to track its transformation into petrocarbon, a term used to describe crude oil or transformed crude oil following biodegradation, weathering, oxygenation, or loss of lighter components. The term petrocarbon includes oil- or methane-derived carbon assimilated or incorporated into microbial biomass or into the food web as well as degraded and undegraded petroleum constituents. Here we report (1) the increase in the relative abundance of oxygen-containing carbon compounds making up the dissolved organic matter (DOM) with increasing depth through the water column, indicating the biodegradation of DOM as it was transported to depth in the water column, (2) the finding of 14C depletion in DOM indicating petrocarbon inputs, and (3) the decrease and subsequent increase of 14C in the isotopic composition of sinking particles indicating the capture of petrocarbon in sediment traps. In addition, we discuss the 14C depletion of this material once it is sedimented to the seafloor and the implications for oil spill budgets of seafloor petrocarbon deposition.
Keywords: Dissolved organic matter; FTICR-MS; Gulf baselines; High-resolution mass spectrometry; organic carbon; radiocarbon; Ramped pyrolysis; Sediment organic matter

Mid-late Holocene rainfall variation in Taiwan: A high-resolution multi-proxy record unravels the dual influence of the Asian monsoon and ENSO - Chen, Jinxia; Li, Tiegang; Nan, Qingyun; Shi, Xuefa; Liu, Yanguang; Jiang, Bo; Zou, Jianjun; Selvaraj, Kandasamy; Li, Dongling; Li, ChuanShun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2019)
Taiwan is particularly sensitive to changes in monsoonal precipitation and to typhoon-induced heavy precipitation events, however, rainfall variability in Taiwan on centennial and millennial time scales during the Holocene has not been well understood. This study describes mid-Holocene rainfall features of Taiwan based on pollen, total organic carbon (TOC), total nitrogen (TN), and C/N ratio records of core MD05-2908. The step-wise increase in sedimentation rate, fern spore percentage and concentration, TOC content, and C/N ratio suggests an increasing terrestrial material supply due to the intensified rainfall in Taiwan since 6800 cal. yr BP. This rainfall pattern shows an inverse pattern to the decreasing East Asian summer monsoon (EASM) strength represented by the multi-proxy records from North China. Variation of the East Asian summer circulation and associated moisture transport may account for the long-term rainfall changes in Taiwan. Superimposed on this trend, we interpreted three prominent rainfall changes, which focus on the periods of 6800–6600, 1090–880 and 490–190 cal. yr BP. These centennial time scale rainfall variations in our records are linked to the intensity of El-Niño Southern Oscillations.
Keywords: C/N ratio; Fern spore; La Niña; Okinawa Trough; tropical cyclone

The Mighty Susquehanna—Extreme Floods in Eastern North America During the Past Two Millennia - Toomey, Michael; Cantwell, Meagan; Colman, Steven; Cronin, Thomas; Donnelly, Jeffrey; Giosan, Liviu; Heil, Clifford; Korty, Robert; Marot, Marci; Willard, Debra (Geophysical Research Letters, 2019)
The hazards posed by infrequent major floods to communities along the Susquehanna River and the ecological health of Chesapeake Bay remain largely unconstrained due to the short length of streamgage records. Here we develop a history of high‐flow events on the Susquehanna River during the late Holocene from flood deposits contained in MD99‐2209, a sediment core recovered in 26 m of water from Chesapeake Bay near Annapolis, Maryland, United States. We identify coarse‐grained deposits left by Hurricane Agnes (1972) and the Great Flood of 1936, as well as during three intervals that predate instrumental flood records (~1800–1500, 1300–1100, and 400–0 CE). Comparison to sedimentary proxy data (pollen and ostracode Mg/Ca ratios) from the same core site indicates that prehistoric flooding on the Susquehanna often accompanied cooler‐than‐usual winter/spring temperatures near Chesapeake Bay—typical of negative phases of the North Atlantic Oscillation and conditions thought to foster hurricane landfalls along the East Coast.

Petrocarbon evolution: Ramped pyrolysis/oxidation and isotopic studies of contaminated oil sediments from the Deepwater Horizon oil spill in the Gulf of Mexico - Rogers, Kelsey L.; Bosman, Samantha H.; Lardie-Gaylord, Mary; McNichol, Ann; Rosenheim, Brad E.; Montoya, Joseph P.; Chanton, Jeffrey P. (PLOS ONE, 2019)
Hydrocarbons released during the Deepwater Horizon (DWH) oil spill weathered due to exposure to oxygen, light, and microbes. During weathering, the hydrocarbons' reactivity and lability was altered, but it remained identifiable as "petrocarbon" due to its retention of the distinctive isotope signatures (C-14 and C-13) of petroleum. Relative to the initial estimates of the quantity of oil-residue deposited in Gulf sediments based on 2010-2011 data, the overall coverage and quantity of the fossil carbon on the seafloor has been attenuated. To analyze recovery of oil contaminated deep-sea sediments in the northern Gulf of Mexico we tracked the carbon isotopic composition (C-13 and C-14, radiocarbon) of bulk sedimentary organic carbon through time at 4 sites. Using ramped pyrolysis/oxidation, we determined the thermochemical stability of sediment organic matter at 5 sites, two of these in time series. There were clear differences between crude oil (which decomposed at a lower temperature during ramped oxidation), natural hydrocarbon seep sediment (decomposing at a higher temperature; Delta C-14 = -189 parts per thousand) and our control site (decomposing at a moderate temperature; Delta C-14 = -189 parts per thousand), in both the stability (ability to withstand ramped temperatures in oxic conditions) and carbon isotope signatures. We observed recovery toward our control site bulk Delta C-14 composition at sites further from the wellhead in similar to 4 years, whereas sites in closer proximity had longer recovery times. The thermographs also indicated temporal changes in the composition of contaminated sediment, with shifts towards higher temperature CO2 evolution over time at a site near the wellhead, and loss of higher temperature CO2 peaks at a more distant site.
Keywords: C-14 ANALYSES; MARINE SNOW; degradation; fractionation; organic-matter; POLYCYCLIC AROMATIC-HYDROCARBONS; MICROBIAL COMMUNITY RESPONSE; radiocarbon; STABLE CARBON; surface sediments

Salt marsh ecosystem restructuring enhances elevation resilience and carbon storage during accelerating relative sea-level rise - Gonneea, Meagan Eagle; Maio, Christopher V.; Kroeger, Kevin D.; Hawkes, Andrea D.; Mora, Jordan; Sullivan, Richard; Madsen, Stephanie; Buzard, Richard M.; Cahill, Niamh; Donnelly, Jeffrey P. (Estuarine, Coastal and Shelf Science, 2019)
Salt marshes respond to sea-level rise through a series of complex and dynamic bio-physical feedbacks. In this study, we found that sea-level rise triggered salt marsh habitat restructuring, with the associated vegetation changes enhancing salt marsh elevation resilience. A continuous record of marsh elevation relative to sea level that includes reconstruction of high-resolution, sub-decadal, marsh elevation over the past century, coupled with a lower-resolution 1500-year record, revealed that relative sea-level rose 1.5 ± 0.4 m, following local glacial isostatic adjustment (1.2 mm/yr). As sea-level rise has rapidly accelerated, the high marsh zone dropped 11 cm within the tidal frame since 1932, leading to greater inundation and a shift to flood- and salt-tolerant low marsh species. Once the marsh platform fell to the elevation favored by low-marsh Spartina alterniflora, the elevation stabilized relative to sea level. Currently low marsh accretion keeps pace with sea-level rise, while present day high marsh zones that have not transitioned to low marsh have a vertical accretion deficit. Greater biomass productivity, and an expanding subsurface accommodation space favorable for salt marsh organic matter preservation, provide a positive feed-back between sea-level rise and marsh platform elevation. Carbon storage was 46 ± 28 g C/m2/yr from 550 to 1800 CE, increasing to 129 ± 50 g C/m2/yr in the last decade. Enhanced carbon storage is controlled by vertical accretion rates, rather than soil carbon density, and is a direct response to anthropogenic eustatic sea-level rise, ultimately providing a negative feedback on climate warming.
Keywords: 14-Carbon; accretion; Carbon storage; Elevation; Salt marsh; Sea level index point; sea-level rise

Sea Level Rise Explains Changing Carbon Accumulation Rates in a Salt Marsh Over the Past Two Millennia - McTigue, Nathan; Davis, Jenny; Rodriguez, Antonio B.; McKee, Brent; Atencio, Anna; Currin, Carolyn (Journal of Geophysical Research: Biogeosciences, 2019)
High rates of carbon burial observed in wetland sediments have garnered attention as a potential “natural fix” to reduce the concentration of carbon dioxide (CO2) in Earth's atmosphere. A carbon accumulation rate (CAR) can be determined through various methods that integrate a carbon stock over different time periods, ranging from decades to millennia. Our goal was to assess how CAR changed over the lifespan of a salt marsh. We applied a geochronology to a series of salt marsh cores using both 14C and 210Pb markers to calculate CARs that were integrated between 35 and 2,460 years before present. CAR was 39 g C·m−2·year−1 when integrated over millennia but was upward of 148 g C·m−2·year−1 for the past century. We present additional evidence to account for this variability by linking it to changes in relative sea level rise (RSLR), where higher rates of RSLR were associated with higher CARs. Thus, the CAR calculated for a wetland should integrate timescales that capture the influence of contemporary RSLR. Therefore, caution should be exercised not to utilize a CAR calculated over inappropriately short or long timescales as a current assessment or forecasting tool for the climate change mitigation potential of a wetland.
Keywords: Carbon storage; Geochronology; Salt marsh; sea‐level rise

Sea-level, monsoonal, and anthropogenic impacts on the millennial-scale variability of siliciclastic sediment input into the western Philippine sea since 27 ka - Xu, Zhaokai; Li, Tiegang; Clift, Peter D.; Wan, Shiming; Lim, Dhongil; Chang, Fengming; Sun, Rongtao (Journal of Asian Earth Sciences, 2019)
Multiproxy records from Core MD06-3054 in the western Philippine Sea and published results from the nearby Core MD06-3052, which are both located at the northern margin of the Western Pacific Warm Pool (WPWP), provide precise reconstructions and evidence for the potential controls on continental erosion and weathering intensities in Luzon. These data also constrain sediment source-to-sink processes in the sea since 27 ka at the millennial scale. We demonstrate that the siliciclastic fraction is derived from Luzon volcanic rocks and eolian dust from mainland Asia. Stronger physical erosion and chemical weathering generally occurred during the last glaciation, Heinrich Event 1, the Younger Dryas, and the period from 10.3 to 11.3 ka. In contrast, the Bølling-Allerød was characterized by weaker physical erosion and chemical weathering. During the last glaciation, Heinrich Event 1, and the Younger Dryas, the lower sea level led to enhanced erosion and weathering of the exposed shelf sediments. In contrast, the weaker physical erosion and chemical weathering that occurred during the Bølling-Allerød and the Holocene, except after 2.1 ka, are closely correlated with the higher sea level. The stronger physical erosion and chemical weathering at 10.3–11.3 ka may be derived from the reworking of older sediments during the time of a strengthening summer monsoon. Furthermore, enhanced human activity since 2.1 ka has become the dominant control on erosion in Luzon. Rapid weathering changes in the WPWP during the last deglaciation highlight the high variability in local controls at low latitudes during these periods and the potential influence of controls at high latitudes.

Sources of carbon to suspended particulate organic matter in the northern Gulf of Mexico - Rogers, Kelsey L.; Bosman, Samantha H.; Weber, Sarah; Magen, Cedric; Montoya, Joseph P.; Chanton, Jeffrey P. (Elem Sci Anth, 2019)
Suspended particulate organic carbon (POCsusp) in the Gulf of Mexico is unique compared to other seas and oceans. In addition to surface primary production, isotopic analysis indicates that microbial cycling of oil and riverine inputs are primary sources of carbon to POCsusp in the Gulf. To characterize POCsusp from seep sites and non-seep north central Gulf (NCG) sites potentially affected by the Deepwater Horizon (DWH) spill, we analyzed 277 and 123 samples for δ13C and Δ1C signatures, respectively. Depth, partitioned into euphotic (300 m), was the main driver of spatial δ13C differences, with deep depths exhibiting 13C depletion. Both deep depths and proximity to sources of natural seepage resulted in 14C depletion. A two-endmember mixing model based on Δ14C indicated that sources to POCsusp were 14–29% fossil carbon at NCG sites and 19–57% at seep sites, with the balance being modern surface production. A six-component Bayesian mixing model MixSIAR, using both 13C and 14C, suggested that riverine inputs were an important carbon source to POCsusp contributing 34–46%. The influence of seeps was localized. Below the euphotic zone at seep sites, 46 ± 5% (n = 9) of the carbon in POCsusp was derived from environmentally degraded, transformed oil; away from seeps, transformed oil contributed 15 ± 4% (n = 39). We hypothesized that, at NCG sites removed from hydrocarbon seep sources, isotopic signatures would be depleted following the spill and then shift towards background-like enriched values over time. At deep depths we observed decreasing Δ14C signatures in POCsusp from 2010 to 2012, followed by isotopic enrichment from 2012 to 2014 and a subsequent recovery rate of 159‰ per year, consistent with this hypothesis and with biodegraded material from DWH hydrocarbons contributing to POCsusp.

Temporal deconvolution of vascular plant-derived fatty acids exported from terrestrial watersheds - Vonk, Jorien E.; Drenzek, Nicholas J.; Hughen, Konrad A.; Stanley, Rachel H.R.; McIntyre, Cameron; çon, Daniel B.; Giosan, Liviu; Southon, John R.; Santos, Guaciara M.; Druffel, Ellen R.M.; Andersson, August A.; öld, Martin; et al. (Geochimica et Cosmochimica Acta, 2019)
Relatively little is known about the amount of time that lapses between the photosynthetic fixation of carbon by vascular land plants and its incorporation into the marine sedimentary record, yet the dynamics of terrestrial carbon sequestration have important implications for the carbon cycle. Vascular plant carbon may encounter multiple potential intermediate storage pools and transport trajectories, and the age of vascular plant carbon accumulating in marine sediments will reflect these different pre-depositional histories. Here, we examine down-core C-14 profiles of higher plant leaf wax-derived fatty acids isolated from high fidelity sedimentary sequences spanning the so-called "bomb-spike", and encompassing a ca. 60-degree latitudinal gradient from tropical (Cariaco Basin), temperate (Saanich Inlet), and polar (Mackenzie Delta) watersheds to constrain integrated vascular plant carbon storage/transport times ("residence times"). Using a modeling framework, we find that, in addition to a "young" (conditionally defined as < 50 y) carbon pool, an old pool of compounds comprises 49 to 78 % of the fractional contribution of organic carbon (OC) and exhibits variable ages reflective of the environmental setting. For the Mackenzie Delta sediments, we find a mean age of the old pool of 28 ky (+/- 9.4, standard deviation), indicating extensive pre-aging in permafrost soils, whereas the old pools in Saanich Inlet and Cariaco Basin sediments are younger, 7.9 (+/- 5.0) and 2.4 (+/- 0.50) to 3.2 (+/- 0.54) ky, respectively, indicating less protracted storage in terrestrial reservoirs. The "young" pool showed clear annual contributions for Saanich Inlet and Mackenzie Delta sediments (comprising 24% and 16% of this pool, respectively), likely reflecting episodic transport of OC from steep hillside slopes surrounding Saanich Inlet and annual spring flood deposition in the Mackenzie Delta, respectively. Contributions of 5-10 year old OC to the Cariaco Basin show a short delay of OC inflow, potentially related to transport time to the offshore basin. Modeling results also indicate that the Mackenzie Delta has an influx of young but decadal material (20-30 years of age), pointing to the presence of an intermediate reservoir. Overall, these results show that a significant fraction of vascular plant C undergoes pre-aging in terrestrial reservoirs prior to accumulation in deltaic and marine sediments. The age distribution, reflecting both storage and transport times, likely depends on landscape-specific factors such as local topography, hydrographic characteristics, and mean annual temperature of the catchment, all of which affect the degree of soil buildup and preservation. We show that catchment-specific carbon residence times across landscapes can vary by an order of magnitude, with important implications both for carbon cycle studies and for the interpretation of molecular terrestrial paleoclimate records preserved in sedimentary sequences.
Keywords: british-columbia; CARIACO BASIN; compound-specific radiocarbon; MACKENZIE DELTA; marine-sediments; odp leg 169s; saanich inlet; SANTA-MONICA BASIN; SOIL ORGANIC-MATTER; TROPICAL VEGETATION

Thermal oxidation of carbon in organic matter rich volcanic soils: insights into SOC age differentiation and mineral stabilization - Grant, Katherine E.; Galy, Valier V.; Chadwick, Oliver A.; Derry, Louis A. (Biogeochemistry, 2019)
Radiocarbon ages and thermal stability measurements can be used to estimate the stability of soil organic carbon (OC). Soil OC is a complex reservoir that contains a range of compounds with different sources, reactivities, and residence times. This heterogeneity can shift bulk radiocarbon values and impact assessment of OC stability and turnover in soils. Four soil horizons (Oa, Bhs, Bs, Bg) were sampled from highly weathered 350 ka Pololu basaltic volcanics on the Island of Hawaii and analyzed by Ramped PyrOX (RPO) in both the pyrolysis (PY) and oxidation (OX) modes to separate a complex mixture of OC into thermally defined fractions. Fractions were characterized for carbon stable isotope and radiocarbon composition. PY and OX modes yielded similar results. Bulk radiocarbon measurements were modern in the Oa horizon (Fm = 1.013) and got progressively older with depth: the Bg horizon had an Fm value of 0.73. Activation energy distributions (p(E)) calculated using the ‘rampedpyrox’ model yielded consistent mean E values of 140 kJ mol−1 below the Oa horizon. The ‘rampedpyrox’ model outputs showed a mostly bimodal distribution in the p(E) below the Oa, with a primary peak at 135 kJ mol−1 and a secondary peak at 148 kJ mol−1, while the Oa was dominated by a single, higher E peak at 157 kJ mol−1. We suggest that mineral-carbon interaction, either through mineral surface-OC or metal-OC interactions, is the stabilization mechanism contributing to the observed mean E of 140 kJ mol−1 below the Oa horizon. In the Oa horizon, within individual RPO analyses, radiocarbon ages in the individual thermal fractions were indistinguishable (p > 0.1). The flat age distributions indicate there is no relationship between age and thermal stability (E) in the upper horizon (> 25 cm). Deeper in the soil profile higher µEf values were associated with older radiocarbon ages, with slopes progressively steepening with depth. In the deepest (Bg) horizon, there was the largest, yet modest change in Fm of 0.06 (626 radiocarbon years), indicating that older OC is slightly more thermally stable.

The Utility of Stable and Radioisotopes in Fish Tissues as Biogeochemical Tracers of Marine Oil Spill Food Web Effects - Patterson III, William F.; Chanton, Jeffery P.; Hollander, David J.; Goddard, Ethan A.; Barnett, Beverly K.; Tarnecki, Joseph H. (Springer International Publishing, 2019)
Direct exposure to petroleum compounds was widely reported for a variety of taxa following the DWH. Evidence of exposure ranged from oiling of skin, shells, or feathers, depending on the taxa, to observation of ingested oil in small translucent, invertebrates, to biomarkers of petroleum compounds within an organism’s tissues, such as PAHs in the hepatopancreas of invertebrates or the liver of fishes, or metabolic products of PAH catabolism in the bile of various vertebrate taxa. Development of natural biogeochemical tracers to examine indirect effects, especially over long (months to years) time scales, can be much more problematic. In this chapter, we describe the utility of employing stable isotopes and radioisotopes to 1) examine whether food web effects can be inferred from shifts in stable isotope values measured in vertebrate taxa; 2) examine the assimilation and trophic transfer of petrocarbon in marine food webs; and, 3) serve as long-term biogeochemical tracers either of petrocarbon assimilation or trophic shifts that are indicative of food web effects of marine oil spills. Data and analyses are largely drawn from DWH-related studies but with broader implications to marine oil spills in general.
Keywords: Petrocarbon; radiocarbon; Reef fish; Stable isotopes

Active Ooid Growth Driven By Sediment Transport in a High-Energy Shoal, Little Ambergris Cay, Turks and Caicos Islands - Trower, Elizabeth J.; Cantine, Marjorie D.; Gomes, Maya L.; Grotzinger, John P.; Knoll, Andrew H.; Lamb, Michael P.; Lingappa, Usha; O'Reilly, Shane S.; Present, Theodore M.; Stein, Nathan; Strauss, Justin V.; Fischer, Woodward W. (Journal of Sedimentary Research, 2018)
Ooids are a common component of carbonate successions of all ages and present significant potential as paleoenvironmental proxies, if the mechanisms that control their formation and growth can be understood quantitatively. There are a number of hypotheses about the controls on ooid growth, each offering different ideas on where and how ooids accrete and what role, if any, sediment transport and abrasion might play. These hypotheses have not been well tested in the field, largely due to the inherent challenges of tracking individual grains over long timescales. This study presents a detailed field test of ooid-growth hypotheses on Little Ambergris Cay in the Turks and Caicos Islands, British Overseas Territories. This field site is characterized by westward net sediment transport from waves driven by persistent easterly trade winds. This configuration makes it possible to track changes in ooid properties along their transport path as a proxy for changes in time. Ooid size, shape, and radiocarbon age were compared along this path to determine in which environments ooids are growing or abrading. Ooid surface textures, petrographic fabrics, stable-isotope compositions (δ13C, δ18O, and δ34S), lipid geochemistry, and genetic data were compared to characterize mechanisms of precipitation and degradation and to determine the relative contributions of abiotic (e.g., abiotic precipitation, physical abrasion) and biologically influenced processes (e.g., biologically mediated precipitation, fabric destruction through microbial microboring and micritization) to grain size and character. A convergence of evidence shows that active ooid growth occurs along the transport path in a high-energy shoal environment characterized by frequent suspended-load transport: median ooid size increases by more than 100 μm and bulk radiocarbon ages decrease by 360 yr westward along the ∼ 20 km length of the shoal crest. Lipid and 16S rRNA data highlight a spatial disconnect between the environments with the most extensive biofilm colonization and environments with active ooid growth. Stable-isotope compositions are indistinguishable among samples, and are consistent with abiotic precipitation of aragonite from seawater. Westward increases in ooid sphericity and the abundance of well-polished ooids illustrate that ooids experience subequal amounts of growth and abrasion—in favor of net growth—as they are transported along the shoal crest. Overall, these results demonstrate that, in the Ambergris system, the mechanism of ooid growth is dominantly abiotic and the loci of ooid growth is determined by both carbonate saturation and sediment transport mode. Microbes play a largely destructive, rather than constructive, role in ooid size and fabric.

Along-slope variations in sediment lithofacies and depositional processes since the Last Glacial Maximum on the northeast Baffin margin, Canada - Jenner, K.A.; Campbell, D.C.; Piper, D.J.W. (Marine Geology, 2018)
Twelve piston cores were used to characterize late Quaternary lithofacies, depositional processes and deglacial history along the Baffin Bay slope between Lancaster Sound and Home Bay. Core investigations show four distinct laterally correlatable lithofacies along the slope – basal and upper diamicton, laminated red brown mud, tan carbonate gravelly, sandy mud and bioturbated brown mud. Basal diamicton largely represents glacigenic debris flow deposits during a glacial advance from Baffin Island at ~25 cal ka. The distribution and character of laminated red brown mud suggests a lateral supply to Baffin Bay slope from ice-proximal meltwater plumes and turbidity currents sourced in glacial ice from both Baffin Bay shelf and Home Bay between 41.5 cal ka to ~14.2 cal ka. An upper diamicton records a lesser, localized glacial advance that ended at about 14.2 cal ka. Tan carbonate mud events represent ice-rafted, enhanced detrital carbonate delivery to the slope between ~25 cal ka and ~11 cal ka. A gradual thinning of these events, from northern to southern Baffin Bay, corroborates a northern Baffin Bay, Lancaster Sound or Nares Strait iceberg source. Proglacial facies seaward of Home Bay contain beds with slightly elevated detrital carbonate that may represent the distal edge of carbonate ice-rafted from Lancaster Sound. Baffin Bay is a type example of a polar glacial basin in which direct glacial supply predominates over the effects of glacial meltwater. As a result, axial supply from the large ice streams north of Baffin Bay (particularly Lancaster Sound) is dominant in the Baffin Bay basin and lateral supply from smaller ice streams on Baffin Island predominates on the NE Baffin Slope.
Keywords: Baffin Bay; Glacigenic debris flow; Late Quaternary; lithofacies; stratigraphy; Tan carbonate events

Ancient water wells reveal a prolonged drought in the lower Yellow River area about 2800 years ago - Yu, Shiyong; Chen, Xuexiang; Liu, Xiuling; Fang, Zhen; Guo, Junfeng; Zhan, Senyang; Fang, Hui; Chen, Fahu (Science Bulletin, 2018)
Given that the Holocene is the most recent interglacial period that has spurred the development of modern societies, scrutinizing climate changes during this period may provide a knowledge base for better understanding the rise and fall of ancient civilizations. However, our knowledge about the mechanism of millennial-scale climate variability particularly in the absence of major continental ice sheets during the second half of the Holocene remains highly uncertain. Although cold spells manifested as the Bond events have been widely reported in the North Atlantic sector during the mid-to-late Holocene, it is not clear whether or not there is a global expression of these events. Therefore, well-tuned far-field proxy records are indispensable to pinpoint the geographical extent of these climate events. Here we show evidence from ancient water wells in North China for a prolonged drought corresponding to a period of pervasive cooling in the North Atlantic region lasting from about 800 to 550 before the Common Era (BCE). Inferred climatic conditions using a conceptual hydrological model, in line with other proxy records, support the hypothesis of the Sun-climate link probably through the complex ocean-atmospheric interactions in the tropical oceans. Our finding suggests that water well construction represented a major technical invention in human history, which greatly improved the resilience against the depletion of surface water at times when arid climate prevailed. The linked climatic and societal changes demonstrated here can serve as a historical analogue for the socio-economic response to potentially large climate changes in the future.

Bathyal records of enhanced silicate erosion and weathering on the exposed Luzon shelf during glacial lowstands and their significance for atmospheric CO2 sink - Xu, Zhaokai; Li, Tiegang; Clift, Peter D.; Wan, Shiming; Qiu, Xiaohua; Lim, Dhongil (Chemical Geology, 2018)
We present a new high-resolution multiproxy data set of mass accumulation rates, Sr-Nd isotopes, as well as major and trace elements for the siliciclastic sediment fraction from International Marine Global Change Study Core MD06-3052, located on the continental slope of the western Philippine Sea. We integrate our new data with published grain sizes and sea surface temperatures from the same core, as well as with Equatorial Pacific sea level, and East Asian summer monsoon precipitation, in order to constrain at high-resolution changes in physical erosion and chemical weathering intensities on Luzon, and sediment source-to-sink processes. We assess the potential significance of chemical weathering of arc silicates in regulating global atmospheric CO2 since 156 kyr BP. Sr-Nd isotopes show that the siliciclastic sediments were dominantly sourced from volcanic rocks exposed on Luzon (~ 68–100%), with a lesser contribution from Asian dust (~ 0–32%). Different indices indicate that stronger physical erosion and chemical weathering occurred during Marine Isotope Stage (MIS) 6 (130–156 kyr BP), as well as in the latter stage of MIS 3 and MIS 2 (14–40 kyr BP). The large sea-level lowstands and associated significant exposure of continental shelf in the western Philippine Sea during these two cold periods should favor physical erosion and chemical weathering of unconsolidated sediments on the exposed shelf. Furthermore, we notice the relatively good coherence between chemical weathering intensities on Luzon and global atmospheric CO2 concentrations over these cold intervals. We suggest that strengthening of chemical weathering of silicates on Luzon and other tropical arcs (within 20° of the Equator) during the Quaternary glacial sea-level lowstands may significantly contribute to the lowering of atmospheric CO2 concentrations during ice ages. We estimate that a significant fraction, up to ~ 16% (i.e., ~ 8 ppmv), of all atmospheric CO2 ultimately sequestered by silicate weathering may be processed through an area corresponding to only ~ 1% of the exorheic drainage area worldwide.
Keywords: Atmospheric CO2 concentration; Chemical weathering; East Asian summer monsoon; sea level; Western Philippine Sea

Data Constraints on Glacial Atlantic Water Mass Geometry and Properties - Oppo, Delia W.; Gebbie, Geoffrey; Huang, Kuo‐Fang; Curry, William B.; Marchitto, Thomas M.; Pietro, Kathryn R. (Paleoceanography and Paleoclimatology, 2018)
The chemical composition of benthic foraminifera from marine sediment cores provides information on how glacial subsurface water properties differed from modern, but separating the influence of changes in the origin and end‐member properties of subsurface water from changes in flows and mixing is challenging. Spatial gaps in coverage of glacial data add to the uncertainty. Here we present new data from cores collected from the Demerara Rise in the western tropical North Atlantic, including cores from the modern tropical phosphate maximum at Antarctic Intermediate Water (AAIW) depths. The results suggest lower phosphate concentration and higher carbonate saturation state within the phosphate maximum than modern despite similar carbon isotope values, consistent with less accumulation of respired nutrients and carbon, and reduced air‐sea gas exchange in source waters to the region. An inversion of new and published glacial data confirms these inferences and further suggests that lower preformed nutrients in AAIW, and partial replacement of this still relatively high‐nutrient AAIW with nutrient‐depleted, carbonate‐rich waters sourced from the region of the modern‐day northern subtropics, also contributed to the observed changes. The results suggest that glacial preformed and remineralized phosphate were lower throughout the upper Atlantic, but deep phosphate concentration was higher. The inversion, which relies on the fidelity of the paleoceanographic data, suggests that the partial replacement of North Atlantic sourced deep water by Southern Ocean Water was largely responsible for the apparent deep North Atlantic phosphate increase, rather than greater remineralization.

Decreased sedimentation efficiency of petro- and non-petro-carbon caused by a dispersant for Macondo surrogate oil in a mesocosm simulating a coastal microbial community - Xu, Chen; Zhang, Saijin; Beaver, Morgan; Wozniak, Andrew; Obeid, Wassim; Lin, Youmin; Wade, Terry L.; Schwehr, Kathleen A.; Lin, Peng; Sun, Luni; Hatcher, Patrick G.; Chin, Wei-Chun; et al. (Marine Chemistry, 2018)
Large amounts of mucous-rich oil-containing marine snow formed in surface waters adjacent to the Deepwater Horizon spill. This marine oil snow (MOS) was implicated in oil delivery to the seafloor. Whether the use of chemical dispersants increased or decreased MOS sedimentation remains controversial. We conducted mesocosm experiments testing the effects of oil and oil plus a dispersant on MOS formation and sedimentation, in coastal seawater. The four treatments used were a surrogate Macondo oil water accommodated fraction (“WAF”), two concentrations of chemically-enhanced WAF (“CEWAF” and diluted CEWAF, “DCEWAF”) containing a dispersant and oil, and Controls (no additions). Based on radiocarbon and 13C NMR results, the presence of dispersants enhanced the amounts of petro-carbon being incorporated into the sinking oil-carrying aggregates (aka MOS). However, most of the chemically-dispersed oil preferentially partitioned into the colloidal and suspended particulate fractions rather than into the rapidly forming MOS. Thus the oil and non-petro-carbon sedimentation efficiency in treatments with a dispersant was much lower, compared to those in the Control and WAF treatments, during the four-day mesocosm experiment. Formation of MOS and its subsequent sinking sequestered the oil in two stages: first via terrestrial-derived detritus containing humic compounds, and subsequently via freshly produced material, such as exopolymeric substances produced by phytoplankton and bacteria.

Dual-Isotope Constraints on Seasonally Resolved Source Fingerprinting of Black Carbon Aerosols in Sites of the Four Emission Hot Spot Regions of China - Fang, Wenzheng; Du, Ke; Andersson, August; Xing, Zhenyu; Cho, Chaeyoon; Kim, Sang-Woo; Deng, Junjun; Gustafsson, Örjan (Journal of Geophysical Research: Atmospheres, 2018)
Despite much recent efforts, the emission sources of black carbon (BC) aerosols―central input to understanding and predicting environmental and climate impact―remain highly uncertain. Here we present observational δ13C/Δ14C‐based constraints on the sources of BC aerosols over the four seasons in each of the four key hot spot emission regions of China: Beijing‐Tianjin‐Hebei (BTH‐Wuqing; where Wuqing is the sampling location), Yangtze River Delta (YRD‐Haining), Pearl River Delta (PRD‐Zhongshan), and Sichuan Basin (SC‐Deyang). Overall, BC loadings were highest in winter, yet elevated loadings were also observed in other seasons, for example, spring at SC‐Deyang and fall at PRD‐Zhongshan. Annually, the dominant BC sources were coal (50 ± 20%) for BTH‐Wuqing, liquid fossil for YRD‐Haining (46 ± 8%) and PRD‐Zhongshan (48 ± 18%), whereas liquid fossil (42 ± 17%) and biomass burning (41 ± 14%) equally affected SC‐Deyang. There is also different but distinct seasonalities in BC sources for the different sites. As an example, for BTH‐Wuqing coal burning increased from summer to winter, while summer and spring BTH‐Wuqing were more influenced by liquid fossil. In contrast, for YRD‐Haining, the relative importance of emission sources was more constant over the year. These quantitative observational constraints on source‐seasonality of BC aerosols in receptor sites located in China's four key economic zones highlight that regulatory control on BC aerosol emissions from different fuels should consider both seasonal and regional variations. Our results also suggest that models on estimates of BC‐induced climate and air quality should consider variations over both regional and seasonal scales.
Keywords: aerosol; BLACK CARBON; carbon isotope; china; emission sources; seasonality

Early Holocene sea level in the Canadian Beaufort Sea constrained by radiocarbon dates from a deep borehole in the Mackenzie Trough, Arctic Canada - O'Regan, Matt; Coxall, Helen; Hill, Philip; Hilton, Robert; Muschitiello, Francesco; Swärd, Henrik (Boreas, 2018)
Deglacial and Holocene relative sea level (RSL) in the Canadian Beaufort Sea was influenced by the timing and extent of glacial ice in the Mackenzie River corridor and adjacent coastal plains. Considerable evidence indicates extensive ice cover in this region of northwestern Canada during the Late Wisconsinan. However, no absolute ages exist to constrain maximum RSL lowering before the late Holocene (4.2–0 ka). In 1984, the Geological Survey of Canada drilled an 81.5‐m‐deep borehole in the western Mackenzie Trough at 45 m water depth (MTW01). The lower 52.5 m of the borehole was interpreted as a deltaic progradational sequence deposited during a period of rising sea level. The upper 29 m was described as foraminifer‐bearing marine sediments deposited after transgression of the site, when RSL rose above ~−74 m. Here, we present radiocarbon measurements from MTW01, acquired from benthic foraminifera, mollusc fragments and particulate organic carbon in the >63 μm fraction (POC>63 μm) in an attempt to constrain the chronology of sediments within this borehole and date the timing of transgression. The deepest carbonate macrofossil was acquired from 8 m above the transgressive surface (equivalent to 21 m b.s.l.), where mollusc fragments returned a date of 9400 +180–260 cal. a BP (2σ). This provides the oldest constraint on Holocene sea‐level lowering in the region, and implies that transgression at this site occurred prior to the early Holocene. Ages obtained from the lower 52.5 m of the borehole are limited to POC>63 μm samples. These indicate that progradational sediments were deposited rapidly after 24 820 +390–380 cal. a BP (2σ). Due to the incorporation of older reworked organic matter, the actual age of progradation is likely to be younger, occurring after Late Wisconsinan glacial ice retreated from the coast.

The Ephemeral Signature of Permafrost Carbon in an Arctic Fluvial Network - Drake, Travis W.; Guillemette, François; Hemingway, Jordon D.; Chanton, Jeffery P.; Podgorski, David C.; Zimov, Nikita S.; Spencer, Robert G. M. (Journal of Geophysical Research: Biogeosciences, 2018)
Arctic fluvial networks process, outgas, and transport significant quantities of terrestrial organic carbon (C), particularly dissolved organic carbon (DOC). The proportion of permafrost C in these fluxes, however, is poorly constrained. A primary obstacle to the quantification of permafrost‐derived DOC is that it is rapidly respired without leaving a unique tracer of its presence. In this study, we investigated the production of bacterial respiratory carbon dioxide (CO2; measured as dissolved inorganic carbon; DIC) during maximum late‐summer thaw in sites spanning a fluvial network (Kolyma Basin, Siberia) to assess whether the biodegradation of permafrost DOC could be detected by the presence of a persistent aged (14C‐depleted) signature on the DIC pool. Using Keeling plot interpretation of DIC produced in bioincubations of river water, we show that bacteria respire varying sources of DOC moving downstream through the fluvial network. Respiration of permafrost (production of aged CO2) was only detected in heavily permafrost thaw influenced sites. In nonpermafrost thaw impacted sites, ambient DIC was modern (14C‐enriched), but rather than precluding the respiration of permafrost OC upstream, we suggest that 14C‐depleted DIC is overwhelmed by modern DIC. Investigation of dissolved organic matter composition via Fourier transform ion cyclotron resonance mass spectrometry highlighted that elevated levels of aliphatic and nitrogen‐containing compounds were associated with the production of aged DIC, providing molecular‐level insight as to why permafrost‐derived dissolved organic matter is rapidly respired. Overall, results from this study demonstrate the difficulty of tracing inputs of a highly reactive substrate to systems with diverse organic matter sources.

Faunal and stable isotopic analyses of benthic foraminifera from the Southeast Seep on Kimki Ridge offshore southern California, USA - McGann, Mary; Conrad, James E. (Deep Sea Research Part II: Topical Studies in Oceanography, 2018)
We investigated the benthic foraminiferal faunal and stable carbon and oxygen isotopic composition of a 15-cm push core (NA075-092b) obtained on a Telepresence-Enabled cruise to the Southeast Seep on Kimki Ridge offshore southern California. The seep core was taken at a depth of 973 m in the vicinity of a Beggiatoa bacterial mat and vesicomyid clams (Calyptogena) and compared to previously published data of living assemblages from ~ 714 m, four reference cores obtained at ~ 1030 m, and another one at 739 m. All of the reference sites are also from the Inner Continental Borderland but with no evidence of methane seepage. No endemic species were found at the seep site and most of the taxa recovered there have been reported previously from other seep or low oxygen environments. Q- and R-mode cluster analyses clearly illustrated differences in the faunal assemblages of the seep and non-seep sites. The living assemblage at Southeast Seep was characterized by abundant Takayanagia delicata, Cassidulina translucens, and Spiroplectammina biformis, whereas the non-seep San Pedro Basin reference assemblage was comprised primarily of Chilostomella oolina and Globobulimina pacifica. Density and species richness were lower at the seep site compared to the non-seep site, reflecting the harsher living conditions there. The dead assemblage at the seep site was dominated by Gyroidina turgida compared to Cassidulina translucens at the ~ 1030 m non-seep site and Cassidulina translucens, Pseudoparrella pacifica, and Takayanagia delicata at the 739 m non-seep site. Density was three times lower at Southeast Seep than at the non-seep sites of comparable water depth but species richness was ~ 30% higher. Stable carbon isotopic values were considerably depleted in the seep samples compared to the non-seep samples, with a progression from lightest to heaviest average δ13C values evident at the seep site reflecting microhabitat preference and vital effect: the deep infaunal species of Globobulimina, the shallow infaunal species Uvigerina peregrina, the epifaunal species Cibicidoides wuellerstorfi, and the shallow infaunal but aragonite-shelled species Hoeglundina elegans. The δ13C values downcore among each benthic species indicates ongoing fluid seepage through at least the last 3800 cal yr B.P. at Southeast Seep. Besides the continual local seepage, evidence from δ13C values of planktic foraminifera in the seep core suggest two pulses of methane (at 3000 and 3700 cal yr B.P.) were released that were large enough to influence much of the water column. Paired benthic and planktic foraminiferal stable oxygen isotope records provide evidence that there were no paleoenvironmental changes such as increased bottom-water temperature or changes in oxygen isotopic composition of bottom and pore waters during this 3800-year record to induce the methane releases. Instead, Southeast Seep appears to be the result of local faulting providing pathways for fluid to flow to the seafloor at a fault stepover or transpressional bend in the regional strike-slip system.
Keywords: Beggiatoa; benthic foraminifera; Calyptogena; Kimki Ridge; Santa Catalina Basin; Southeast Seep; Southern California; stable carbon isotopes

Fifty-five-year longevity for the largest member of the family Sparidae: the endemic red steenbras Petrus rupestris from South Africa - Andrews, AH; Smale, MJ; Cowley, PD; Chang, N (African Journal of Marine Science, 2018)
A previous study that explored the age and growth of red steenbras Petrus rupestris (Valenciennes, 1830), a large sparid (family Sparidae, seabreams or porgies) endemic to South Africa and reported to approach 2 m in length, provided estimates as a moderately slow-growing species with a maximum age near 30 years. The stock is considered collapsed and a fishing moratorium was imposed in 2012, resulting in this species being assessed as Endangered by the IUCN. One consideration in addressing population status is validation of life-history traits. In this study, estimates of age for red steenbras from thin-sectioned otoliths were reassessed visually in terms of both the original ages and revised estimates using a different age-reading pattern. The revised ages exceeded the original ages by up to 30 years, with a maximum estimated age of 55 years from a well-defined otolith section that provided a basis for the revised age-reading procedure. Bomb radiocarbon (14C) dating revealed there was an offset in the timing of the 14C rise on the Agulhas Bank that, when coupled with considerations for regional oceanography, provided support for the revised age-reading pattern and an estimated longevity that exceeds 50 years. These findings were further supported by the fortuitous recapture of a tagged red steenbras that was at liberty for 22 years.
Keywords: Age validation; bomb radiocarbon dating; Carbon-14; copper steenbras; endangered species; fishery closure; otoliths

Fossil Fuel Combustion Emission From South Asia Influences Precipitation Dissolved Organic Carbon Reaching the Remote Tibetan Plateau: Isotopic and Molecular Evidence - Li, Chaoliu; Chen, Pengfei; Kang, Shichang; Yan, Fangping; Tripathee, Lekhendra; Wu, Guangjian; Qu, Bin; Sillanpää, Mika; Yang, Di; Dittmar, Thorsten; Stubbins, Aron; Raymond, Peter A. (Journal of Geophysical Research: Atmospheres, 2018)
The dissolved organic carbon in precipitation (water‐soluble organic carbon, WSOC) can provide a carbon subsidy to receiving ecosystems. The concentrations, isotopic signatures (δ13C/Δ14C), and molecular signatures (transform ion cyclotron mass spectrometry) of WSOC being delivered to Nam Co—a remote site on the inland Tibetan Plateau (TP)—were compared to those of WSOC in the snowpack, and in wet deposition from urban cities fringing the TP. The average WSOC concentration at Nam Co (1.0 ± 0.9 mg C L−1) was lower than for the large cities (1.6 to 2.3 mg C L−1) but higher than in the snowpack samples (0.26 ± 0.09 mg C L−1). Based upon radiocarbon data, it is estimated that 15 ± 6% of Nam Co WSOC was fossil derived, increasing to 20 ± 8% for snowpack WSOC, 29 ± 4% for Lhasa WSOC, and 34 ± 8% for the three cities. Transform ion cyclotron mass spectrometry results revealed that the abundance of dissolved black carbon and sulfur‐containing molecules of WSOC increased in the order Nam Co < snow pack < urban. The enrichment in 14C and depletion in dissolved black carbon and sulfurous organic molecules of Nam Co WSOC was suggestive of low, but still detectable inputs of fossil‐derived organics to WSOC on the remote TP. Backward air mass trajectories for the precipitation events at Nam Co suggested that the fossil fuel contributions to WSOC in Nam Co region originated mainly from South Asia. This study provides novel radiocarbon age, chemistry, and source evidence that anthropogenic WSOC is delivered to the remote TP, one of the most remote regions on Earth.

On the Holocene evolution of the Ayeyawady megadelta - Giosan, Liviu; Naing, Thet; Min Tun, Myo; Clift, Peter D.; Filip, Florin; Constantinescu, Stefan; Khonde, Nitesh; Blusztajn, Jerzy; Buylaert, Jan-Pieter; Stevens, Thomas; Thwin, Swe (Earth Surface Dynamics, 2018)
The Ayeyawady delta is the last Asian megadelta whose evolution has remained essentially unexplored so far. Unlike most other deltas across the world, the Ayeyawady has not yet been affected by dam construction, providing a unique view on largely natural deltaic processes benefiting from abundant sediment loads affected by tectonics and monsoon hydroclimate. To alleviate the information gap and provide a baseline for future work, here we provide a first model for the Holocene development of this megadelta based on drill core sediments collected in 2016 and 2017, dated with radiocarbon and optically stimulated luminescence, together with a reevaluation of published maps, charts and scientific literature. Altogether, these data indicate that Ayeyawady is a mud-dominated delta with tidal and wave influences. The sediment-rich Ayeyawady River built meander belt alluvial ridges with avulsive characters. A more advanced coast in the western half of the delta (i.e., the Pathein lobe) was probably favored by the more western location of the early course of the river. Radiogenic isotopic fingerprinting of the sediment suggests that the Pathein lobe coast does not receive significant sediment from neighboring rivers. However, the eastern region of the delta (i.e., Yangon lobe) is offset inland and extends east into the mudflats of the Sittaung estuary. Wave-built beach ridge construction during the late Holocene, similar to several other deltas across the Indian monsoon domain, suggests a common climatic control on monsoonal delta morphodynamics through variability in discharge, changes in wave climate or both. Correlation of the delta morphological and stratigraphic architecture information on land with the shelf bathymetry, as well as its tectonic, sedimentary and hydrodynamic characteristics, provides insight on the peculiar growth style of the Ayeyawady delta. The offset between the western Pathein lobe and the eastern deltaic coast appears to be driven by tectonic–hydrodynamic feedbacks as the extensionally lowered shelf block of the Gulf of Mottama amplifies tidal currents relative to the western part of the shelf. This situation probably activates a perennial shear front between the two regions that acts as a leaky energy fence. Just as importantly, the strong currents in the Gulf of Mottama act as an offshore-directed tidal pump that helps build the deep mid-shelf Mottama clinoform with mixed sediments from the Ayeyawady, Sittaung and Thanlwin rivers. The highly energetic tidal, wind and wave regime of the northern Andaman Sea thus exports most sediment offshore despite the large load of the Ayeyawady River.

The Impact of Aquifer Flushing on Groundwater Arsenic Across a 35‐km Transect Perpendicular to the Upper Brahmaputra River in Assam, India - Choudhury, R.; Nath, B.; Khan, M. R.; Mahanta, C.; Ellis, T.; Geen, A. (Water Resources Research, 2018)
Well testing in the floodplain of the Brahmaputra River in Golaghat and Jorhat districts of Assam, India, shows that groundwater arsenic (As) concentrations increase with distance from the river. To establish the origin of this pattern, an additional 900 wells <60‐m deep were tested for As and nine sites were drilled along a 35‐km transect perpendicular to the river. The field data show no relation between groundwater As concentrations ranging from <1 to 660 μg/L along the transect and (a) As concentrations of <1–5 mg/kg in cuttings of aquifer sand recovered while drilling or (b) the degree of reduction of iron oxides in these cuttings. The drilling indicates, however, a marked increase in the thickness of a clay layer capping the aquifer starting from <1–5 m near the river to over 60 m at the most distant site toward the base of the Naga foothills. Organic radiocarbon ages of 18–46 kyr obtained from all but one of 13 clay samples indicate pre‐Holocene deposition of the underlying sands across the entire transect. Radiocarbon ages of dissolved inorganic carbon of 0.2, 4.7, and 17.8 kyr were measured in groundwater from three monitoring wells installed to 30–60‐m depth at distances of 10, 20, and 40 km from the river, respectively. A conceptual groundwater flow model consistent with monitored heads and groundwater ages suggests that thick clay layers capping the aquifer further from the river inhibited flushing of the aquifer and, as a result, preserved higher As levels in groundwater.
Keywords: aquifer flushing; Arsenic; groundwater; South Asia

Isotopic composition of sinking particles: Oil effects, recovery andbaselines in the Gulf of Mexico, 2010–2015 - Chanton, Jeffrey P.; Giering, Sarah L. C.; Bosman, Samantha H.; Rogers, Kelsey L.; Sweet, Julia; Asper, Vernon L.; Diercks, Arne R.; Passow, Uta (Elem Sci Anth, 2018)
The extensive release of oil during the 2010 Deepwater Horizon spill in the northern Gulf of Mexico perturbed the pelagic ecosystem and associated sinking material. To gauge the recovery and post-spill baseline sources, we measured Δ14C, δ13C and δ34S of sinking particles near the spill site and at a reference site and natural seep site. Particulates were collected August 2010–April 2016 in sediment traps moored at sites with depths of 1160–1660 m. Near the spill site, changes in Δ14C indicated a 3-year recovery period, while δ34S indicated 1–2 years, which agreed with estimates of 1–2 years based on hydrocarbon composition. Under post-spill baseline conditions, carbon inputs to sinking particulates in the northern Gulf were dominated by surface marine production (80–85%) and riverine inputs (15–20%). Near the spill site, Δ14C values were depleted in October 2010 (–140 to –80‰), increasing systematically by 0.07 ± 0.02‰ day–1 until July 2013 when values reached –3.2 ± 31.0‰. This Δ14C baseline was similar to particulates at the reference site (3.8 ± 31.1‰). At both sites, δ13C values stayed constant throughout the study period (–21.9 ± 0.5‰ and –21.9 ± 0.9‰, respectively). δ34S near the spill site was depleted (7.4 ± 3.1‰) during October 2010–September 2011, but enriched (16.9 ± 2.0‰) and similar to the reference site (16.2 ± 3.1‰) during November 2012–April 2015. At the seep site, Δ14C values were –21.7 ± 45.7‰ except during August 2012–January 2013 when a significant Δ14C depletion of –109.0 ± 29.1‰ was observed. We interpret this depletion period, also observed in δ13C data, as caused by the incorporation of naturally seeped oil into sinking particles. Determination of post-spill baselines for these isotopic signatures allows for evaluation of anthropogenic inputs in future.
Keywords: Deep Water Horizon Oil Spill; Gulf of Mexico; isotopes; radiocarbon; sediment trap; sinking particulates

Late Holocene paleoceanography in the Chukchi and Beaufort Seas, Arctic Ocean, based on benthic foraminifera and ostracodes - Seidenstein, Julia L.; Cronin, Thomas M.; Gemery, Laura; Keigwin, Lloyd D.; Pearce, Christof; Jakobsson, Martin; Coxall, Helen K.; Wei, Emily A.; Driscoll, Neal W. (arktos, 2018)
Calcareous microfossil assemblages in late Holocene sediments from the western Arctic continental shelf provide an important baseline for evaluating the impacts of today’s changing Arctic oceanography. This study compares 14C-dated late Holocene microfaunal assemblages of sediment cores SWERUS-L2-2-PC1, 2-MC4 and 2-KL1 (57 mwd), which record the last 4200 years in the Herald Canyon (Chukchi Sea shelf), and HLY1302-JPC-32, GGC-30, MC-29 (60 mwd), which record the last 3000 years in the Beaufort Sea shelf off the coast of Canada. Foraminiferal and ostracode assemblages are typical of Arctic continental shelf environments with annual sea-ice cover and show relatively small changes in terms of variability of dominant species. Important microfaunal changes in the Beaufort site include a spike in Spiroplectammina biformis coinciding with a decrease in Cassidulina reniforme in the last few centuries suggesting an increase of Pacific Water influence and decreased sea-ice. There is low-amplitude centennial-scale variability in proportions of benthic foraminiferal species, such as C. reniforme. In addition to these species, Cassidulina teretis s.l., Elphidium excavatum clavatum and Stainforthia feylingi are also common at this site. At the Herald Canyon site in the last few centuries, C. reniforme peaks around 150 years BP and then decreases while Spiroplectammina earlandi spikes and Acanthocythereis dunelmensis decreases also suggesting an increase in Pacific Water influence and decreased sea-ice at this site. This site also includes Buccella spp. and Elphidium excavatum clavatum. Differences in benthic foraminifera and ostracode species dominance between the two sites may be due to a greater influence of Pacific Water in the Chukchi shelf, compared to the more distal Beaufort shelf, which is also affected by the Beaufort Gyre and the Mackenzie River.

Linear decline in red snapper (Lutjanus campechanus) otolith Δ14C extends the utility of the bomb radiocarbon chronometer for fish age validation in the Northern Gulf of Mexico - Barnett, Beverly K; Thornton, Laura; Allman, Robert; Chanton, Jeffrey P; Patterson, William F (ICES Journal of Marine Science, 2018)
Radiocarbon (D14C) was analyzed in northern Gulf of Mexico (nGOM) red snapper (Lutjanus campechanus) otolith cores (n¼23), otolith edge samples (n¼12), and whole age-0 otoliths (n¼9), with edge samples and whole age-0 otoliths constituting known-age samples. There was no significant difference in the linear relationship of D14C versus year of formation between regional corals and known-age otolith samples, and a linear regression fit to the combined data from 1980 to 2015 extends the utility of the bomb radiocarbon chronometer for age validation. The entire regional coral and known-age otolith data set (1940 to 2015) was then utilized as a reference series to validate otolith-derived red snapper age estimates for cored otolith samples. A loess regression was fit to the reference data and then the sum of squared residuals (SSR) was computed from predicted versus observed birth years for cored adult otolith samples. This process was then repeated for ages biased 61–4 years. Ages with no bias applied had the lowest SSR, thus validating red snapper age estimates and demonstrating the utility of the combined regional coral and known-age red snapper otolith D14C time series for age validation of nGOM marine fishes.
Keywords: Age validation; otoliths; radiocarbon; red snapper

A long-term decrease in the persistence of soil carbon caused by ancient Maya land use - Douglas, Peter M. J.; Pagani, Mark; Eglinton, Timothy I.; Brenner, Mark; Curtis, Jason H.; Breckenridge, Andy; Johnston, Kevin (Nature Geoscience, 2018)
The long-term effects of deforestation on tropical forest soil carbon reservoirs are important for estimating the consequences of land use on the global carbon cycle, but are poorly understood. The Maya Lowlands of Mexico and Guatemala provide a unique opportunity to assess this question, given the widespread deforestation by the ancient Maya that began ~4,000 years ago. Here, we compare radiocarbon ages of plant waxes and macrofossils in sediment cores from three lakes in the Maya Lowlands to record past changes in the mean soil transit time of plant waxes (MTTwax). MTTwax indicates the average age of plant waxes that are transported from soils to lake sediments, and comparison of radiocarbon data from soils and lake sediments within the same catchment indicates that MTTwax reflects the age of carbon in deep soils. All three sediment cores showed a decrease in MTTwax, ranging from 2,300 to 800 years, over the past 3,500 years. This decrease in MTTwax, indicating shorter storage times for carbon in lake catchment soils, is associated with evidence for ancient Maya deforestation. MTTwax never recovered to pre-deforestation values, despite subsequent reforestation, implying that current tropical deforestation will have long-lasting effects on soil carbon sinks.

Menardiiform planktonic foraminifera stratigraphy from Middle Pleistocene to Holocene in the Western South Atlantic - Costa, Karen Badaraco; Camillo Jr, Edmundo; Santarosa, Ana Cláudia Aoki; Iwai, Fabiane Sayuri; Quadros, Juliana Pereira de; Leipnitz, Itamar Ivo; Toledo, Felipe Antonio de Lima (REVISTA BRASILEIRA DE PALEONTOLOGIA, 2018)
We studied the Middle Pleistocene to Holocene menardiiform planktonic foraminifera (MPF) stratigraphy in six continuous deep-sea sediment cores recovered from the Brazilian continental slope to evaluate its use in climatic characterization and as a reliable biostratigraphic tool in the western South Atlantic. For this purpose, an important issue was to construct a robust local biochronological framework for the past 772 ky in the western South Atlantic (Santos Basin). The oxygen isotope chronostratigraphic control allowed us to recalibrate the MPF events in the Santos Basin and identify diachronous bioevents. The bio-horizons found in the Santos Basin, such as the V/W and T/U (bio)zone boundaries, were found in a different chronostratigraphic position compared to previous studies. Results indicate that typical cyclic disappearances and reappearances of the MPF are not synchronous throughout the Atlantic Ocean and should not be employed for ‘climatic zonation’. This asynchronous evidence also provides information on the timing of the mechanisms responsible for the proliferation of these species throughout the Atlantic Ocean. Therefore, we strongly recommend that a local biochronological framework should be used for inter-basin comparisons and also accumulation rate estimates, both for paleoclimatic studies and continental slope geohazard assessment. © 2018, Sociedade Brasileira de Paleontologia. All rights reserved.

Microbial oxidation of lithospheric organic carbon in rapidly eroding tropical mountain soils - Hemingway, Jordon D.; Hilton, Robert G.; Hovius, Niels; Eglinton, Timothy I.; Haghipour, Negar; Wacker, Lukas; Chen, Meng-Chiang; Galy, Valier V. (Science, 2018)
Lithospheric organic carbon (“petrogenic”; OCpetro) is oxidized during exhumation and subsequent erosion of mountain ranges. This process is a considerable source of carbon dioxide (CO2) to the atmosphere over geologic time scales, but the mechanisms that govern oxidation rates in mountain landscapes are poorly constrained. We demonstrate that, on average, 67 ± 11% of the OCpetro initially present in bedrock exhumed from the tropical, rapidly eroding Central Range of Taiwan is oxidized in soils, leading to CO2 emissions of 6.1 to 18.6 metric tons of carbon per square kilometer per year. The molecular and isotopic evolution of bulk OC and lipid biomarkers during soil formation reveals that OCpetro remineralization is microbially mediated. Rapid oxidation in mountain soils drives CO2 emission fluxes that increase with erosion rate, thereby counteracting CO2 drawdown by silicate weathering and biospheric OC burial.

Paleomagnetism and rock magnetism from sediments along a continental shelf-to-slope transect in the NW Barents Sea: Implications for geomagnetic and depositional changes during the past 15 thousand years - Caricchi, C.; Lucchi, R.G.; Sagnotti, L.; MacrÌ, P.; Morigi, C.; Melis, R.; Caffau, M.; Rebesco, M.; Hanebuth, T.J.J. (Global and Planetary Change, 2018)
Paleomagnetic and rock magnetic data were measured on glaciomarine silty-clay successions along an E-W sediment-core transect across the continental shelf and slope of the Kveithola paleo-ice stream system (south of Svalbard, north-western Barents Sea), representing a stratigraphic interval spanning the last deglaciation and the Holocene. The records indicate that magnetite is the main magnetic mineral and that magnetic minerals are distinctly less abundant on the shelf than at the continental slope. The paleomagnetic properties allow for the reconstruction of a well-defined characteristic remanent magnetization (ChRM) throughout the sedimentary successions. The stratigraphic trends of rock magnetic and paleomagnetic parameters are used for a shelf-slope core correlation and sediment facies analysis is applied for depositional processes reconstruction. The new paleomagnetic records compare to the PSV and RPI variation predicted for the core sites by a simulation using the global geomagnetic field variation models SHA.DIF.14k and CALS7K.2 and closest PSV and RPI regional stack curves. The elaborated dataset, corroborated by available 14C ages, provides a fundamental chronological framework to constrain the coupling of shelf-slope sedimentary processes and environmental changes in the NW Barents Sea region during and after deglaciation.
Keywords: Barents Sea; Kveithola glacial trough; Paleomagnetism; Rock magnetism

The Potential Impact of Hydrocarbons on Mussels in Port au Port Bay, Newfoundland - Cook, Melissa C.; May, Adam; Kohl, Lucas; Van Biesen, Geert; Parrish, Christopher C.; Morrill, Penny L. (Elsevier, 2018)
Since 2012, the scallop fishery in Port au Port Bay, Newfoundland, Canada has experienced a drastic decline, while no decline was observed in adjacent St. George's Bay. Local fishermen have raised concerns about an abandoned oil exploration well in the Port au Port Bay. This study investigated the potential impact of petroleum hydrocarbons on sediments and blue mussels [Mytilus edulis] (a proxy organism for scallops) in the area. Sediments from both bays were characterized for their hydrocarbons and compared to potential petroleum hydrocarbon sources. Mussels were analysed for health indices and their 14C content. The results showed that the concentration of hydrocarbons found in the sediments of the fishing ground was within the range of unpolluted marine sediments and that the hydrocarbons present were likely from a mixture of sources. The health indices of the mussels in Port au Port Bay were similar to the health indices of mussels in St. George's Bay and the 14C content of the mussels from both bays was modern. These data suggest that the Port au Port fishing ground was not solely contaminated from crude oil leaking from an oil exploration well, that the mussels were not contaminated with petroleum hydrocarbons, and that Port au Port mussels were just as healthy as the mussels of St. George's Bay. Therefore, whatever caused the scallop decline was most likely scallop- and bay-specific. During this study a fast and efficient method for extracting petroleum hydrocarbons from sediment using accelerated solvent extraction with integrated silica gel was developed.
Keywords: Health indices; Hydrocarbon contamination; Mussels; Petroleum; Scallops

Quaternary Glaciation of the Great Lakes Region: Process, Landforms, Sediments, and ChronologyMinimum age of the Mapleton, Tully, and Labrador Hollow moraines indicates correlation with the Port Huron Phase in central New York State - Kehew, Alan E.; Curry, B. Brandon; Kozlowski, Andrew L.; Bird, Brian C.; Lowell, Thomas V.; Smith, Colby A.; Feranec, Robert S.; Graham, Brandon Lars (Geological Society of America, 2018)
The glaciated terrain along the northern edge of the Appalachian Plateau in the eastern Finger Lakes of central New York has long been recognized as an important location for meltwater routing and for proglacial lake development in the Great Lakes region. Despite recognition of multiple ice margins formed by the Ontario Lobe of the Laurentide ice sheet during the late Wisconsinan, numerical age control of several margins has been elusive, particularly in regard to regional readvances of the Port Bruce (ca. 16,980–18,000 cal [calibrated] yr B.P.) and Port Huron (ca. 14,300– 16,000 cal yr B.P.) Phases. Utilizing light detection and ranging (LiDAR) terrain models in the eastern Finger Lakes area, we identified and described the Mapleton, Tully, and Labrador Hollow moraines. Associated ice-marginal landforms include push moraines, fans, and hummocky topography. In places, these features intrude into the northern heads of through valleys. Coring of three basins directly associated with these landforms yielded more than 20 samples of boreal tree needles and twigs, and Dryas leaves. Accelerated mass spectrometry (AMS) radiocarbon assay results indicate that poststadial lacustrine sedimentation began at ca. 15,000 cal yr B.P., consistent with ages of the Port Huron Phase.

Radiocarbon and Stable Isotope Evidence for Changes in Sediment Mixing in the North Pacific over the Past 30 kyrAbstract - Costa, Kassandra M; McManus, Jerry F; Anderson, Robert F (Radiocarbon, 2018)
Deep-sea sediment mixing by bioturbation is ubiquitous on the seafloor, and it can be an important influence on the fidelity of paleoceanographic records. Bioturbation can be difficult to quantify, especially in the past, but diffusive models based on radioactive tracer profiles have provided a relatively successful approach. However, a singular, constant mixing regime is unlikely to prevail in a region where dynamic oceanographic changes in the bottom water environment are a consequence of paleoclimatic variability. In this study, foraminiferal stable isotopes, radiocarbon (14C) dating, and 230Th fluxes are utilized to understand the sediment mixing history in the easternmost region of the North Pacific. In the uppermost sediment, a 12,000-yr offset between planktonic foraminifera species N. incompta and G. bulloides is observed that coincides with age plateaus at 2000–2500 yr for N. incompta and 15,000–16,000 yr for G. bulloides despite coincident glacial-interglacial shifts in δ18O of benthic species. These age plateaus, particularly for G. bulloides, are a result of changing foraminiferal abundance related to assemblage shifts and carbonate preservation changes since the last glacial period, providing a window into the extent of mixing in the past. The 14C and stable isotope results can be simulated using an iterative model that couples these changes in foraminiferal abundance with variability in mixing depth over time. The best-fit model output suggests that the deepest, or most intense, mixing of the past 30,000 yr (30 kyr) may have occurred during the Holocene. Even though changes in mixing affect the 14C and δ18O of planktonic species that have dramatically varying abundance, substantial age control is nevertheless provided by δ18O measurements on the more consistently abundant benthic foraminifera Uvigerina, thus allowing the construction of a reliable chronology for these cores.
Keywords: bioturbation; north pacific; radiocarbon; Stable isotopes

Radiocarbon, Cesium-137, Grain Size, and X-ray Fluorescence Data for Tsunami Geology Investigation, Driftwood Bay, Umnak Island, Alaska (2018) - Witter, Rob; Gelfenbaum, Guy; Corbett, Reide; Tam, Angela; La Selle, SeanPaul (Alaska Science Center, U.S. Geological Survey, 2018)
These files provide the complete data release for the paper entitled, "Frequent large tsunamis spanned locked/creeping parts of the Aleutian megathrust." The data set consists of nine tables that include radiocarbon dates, cesium-137 activity, grain size measurements, and scanning X-ray fluorescence element intensity counts.

Rapid precipitation changes in the tropical West Pacific linked to North Atlantic climate forcing during the last deglaciation - Xiong, Zhifang; Li, Tiegang; Chang, Fengming; Algeo, Thomas J.; Clift, Peter D.; Bretschneider, Lisa; Lu, Zhengyao; Zhu, Xiao; Frank, Martin; Sauer, Peter E.; Jiang, FuQing; Wan, Shiming; et al. (Quaternary Science Reviews, 2018)
The cause of rapid hydrological changes in the tropical West Pacific during the last deglaciation remains controversial. In order to test whether these changes were triggered by abrupt climate change events in the North Atlantic Ocean, variations in precipitation during the last deglaciation (18-10 ka) were extracted from proxy records of chemical weathering and terrigenous input in the western Philippine Sea (WPS). The evolution of chemical weathering and terrigenous input since 27 ka was reconstructed using the chemical index of alteration (CIA), elemental ratios (K/Al, TOC/TN and Ti/Ca), δ13Corg, terrigenous fraction abundance and flux data from International Marine Global Change Study Program (IMAGES) core MD06-3054 collected on the upper continental slope of eastern Luzon (northern Philippines). Sediment deposited during the Last Glacial Maximum (LGM) shows weathering equal to or slightly greater than Holocene sediment in the WPS. This unusual state of chemical weathering, which is inconsistent with lower air temperatures and decreased precipitation in Luzon during the LGM, may be due to reworking of poorly consolidated sediments on the eastern Luzon continental shelf during the LGM sea-level lowstand. Rapid changes in chemical weathering, characterized by higher intensity during the Heinrich event 1 (H1) and Younger Dryas (YD) and lower intensity during the Bølling-Allerød (B/A), were linked to rapid variations in precipitation in the WPS during the last deglaciation. The higher terrigenous inputs during the LGM relative to those of the Holocene were controlled by sea-level changes rather than precipitation. The terrigenous inputs show a long-term decline during the last deglaciation, punctuated by brief spikes during the H1 and YD related to sea-level rises and rapid precipitation changes in the WPS, respectively. The proxy records of chemical weathering and terrigenous input from eastern Luzon suggest high rainfall during the H1 and YD events, consistent with inferred rainfall patterns based on Fe/Ca records from offshore Mindanao. Rapid precipitation changes in the WPS did not coincide with migrations of the Intertropical Convergence Zone (ITCZ) but, rather, were related to state shifts of the El Niño-Southern Oscillation (ENSO) during the last deglaciation. Based on proxy records and modeling results, we argue that the Atlantic meridional overturning circulation (AMOC) controlled rapid precipitation changes in the tropical West Pacific through zonal shifts of ENSO or meridional migration of the ITCZ during the last deglaciation. Our findings highlight the dominant role of the North Atlantic Ocean in the tropical hydrologic cycle during the last deglaciation.
Keywords: AMOC; Chemical weathering; enso; ITCZ; Terrigenous input; Western Philippine Sea

Relative sea-level change in Newfoundland, Canada during the past ∼3000 years - Kemp, Andrew C.; Wright, Alexander J.; Edwards, Robin J.; Barnett, Robert L.; Brain, Matthew J.; Kopp, Robert E.; Cahill, Niamh; Horton, Benjamin P.; Charman, Dan J.; Hawkes, Andrea D.; Hill, Troy D.; van de Plassche, Orson (Quaternary Science Reviews, 2018)
Several processes contributing to coastal relative sea-level (RSL) change in the North Atlantic Ocean are observed and/or predicted to have distinctive spatial expressions that vary by latitude. To expand the latitudinal range of RSL records spanning the past ∼3000 years and the likelihood of recognizing the characteristic fingerprints of these processes, we reconstructed RSL at two sites (Big River and Placentia) in Newfoundland from salt-marsh sediment. Bayesian transfer functions established the height of former sea level from preserved assemblages of foraminifera and testate amoebae. Age-depth models constrained by radiocarbon dates and chronohorizons estimated the timing of sediment deposition. During the past ∼3000 years, RSL rose by ∼3.0 m at Big River and by ∼1.5 m at Placentia. A locally calibrated geotechnical model showed that post-depositional lowering through sediment compaction was minimal. To isolate and quantify contributions to RSL from global, regional linear, regional non-linear, and local-scale processes, we decomposed the new reconstructions (and those in an expanded, global database) using a spatio-temporal statistical model. The global component confirms that 20th century sea-level rise occurred at the fastest, century-scale rate in over 3000 years (P > 0.999). Distinguishing the contributions from local and regional non-linear processes is made challenging by a sparse network of reconstructions. However, only a small contribution from local-scale processes is necessary to reconcile RSL reconstructions and modeled RSL trends. We identified three latitudinally-organized groups of sites that share coherent regional non-linear trends and indicate that dynamic redistribution of ocean mass by currents and/or winds was likely an important driver of sea-level change in the North Atlantic Ocean during the past ∼3000 years.

Remobilization of old permafrost carbon to Chukchi Sea sediments during the end of the last deglaciation - Martens, Jannik; Wild, Birgit; Pearce, Christof; Tesi, Tommaso; Andersson, August; Broder, Lisa; O’Regan, Matt; Jakobsson, Martin; Sköld, Martin; Gemery, Laura; Cronin, Thomas M.; Semiletov, Igor; et al. (Global Biogeochemical Cycles, 2018)
Climate warming is expected to destabilize permafrost carbon (PF‐C) by thaw‐erosion and deepening of the seasonally thawed active layer and thereby promote PF‐C mineralization to CO2 and CH4. A similar PF‐C remobilization might have contributed to the increase in atmospheric CO2 during deglacial warming after the last glacial maximum. Using carbon isotopes and terrestrial biomarkers (Δ14C, δ13C, and lignin phenols), this study quantifies deposition of terrestrial carbon originating from permafrost in sediments from the Chukchi Sea (core SWERUS‐L2‐4‐PC1). The sediment core reconstructs remobilization of permafrost carbon during the late Allerød warm period starting at 13,000 cal years before present (BP), the Younger Dryas, and the early Holocene warming until 11,000 cal years BP and compares this period with the late Holocene, from 3,650 years BP until present. Dual‐carbon‐isotope‐based source apportionment demonstrates that Ice Complex Deposit—ice‐ and carbon‐rich permafrost from the late Pleistocene (also referred to as Yedoma)—was the dominant source of organic carbon (66 ± 8%; mean ± standard deviation) to sediments during the end of the deglaciation, with fluxes more than twice as high (8.0 ± 4.6 g·m−2·year−1) as in the late Holocene (3.1 ± 1.0 g·m−2·year−1). These results are consistent with late deglacial PF‐C remobilization observed in a Laptev Sea record, yet in contrast with PF‐C sources, which at that location were dominated by active layer material from the Lena River watershed. Release of dormant PF‐C from erosion of coastal permafrost during the end of the last deglaciation indicates vulnerability of Ice Complex Deposit in response to future warming and sea level changes.
Keywords: carbon isotope; climate change feedback; coastal erosion; Deglaciation; past carbon cycling; permafrost

Residential Coal Combustion as a Source of Levoglucosan in ChinaResidential Coal Combustion as a Source of Levoglucosan in China - Yan, Caiqing; Zheng, Mei; Sullivan, Amy P.; Shen, Guofeng; Chen, Yingjun; Wang, Shuxiao; Zhao, Bin; Cai, Siyi; Desyaterik, Yury; Li, Xiaoying; Zhou, Tian; Gustafsson, Örjan; et al. (Environmental Science & Technology, 2018)
Levoglucosan (LG) has been widely identified as a specific marker for biomass burning (BB) sources and frequently utilized in estimating the BB contribution to atmospheric fine particles all over the world. However, this study provides direct evidence to show that coal combustion (CC) is also a source of LG, especially in the wintertime in Northern China, based on both source testing and ambient measurement. Our results show that low-temperature residential CC could emit LG with emission factors (EF) ranging from 0.3 to 15.9 mg kg–1. Ratios of LG to its isomers, mannosan and galactosan, differ between CC and BB emissions, and the wintertime ratios in Beijing ambient PM2.5 and source-specific tracers including carbon isotopic signatures all indicated a significant contribution from CC to ambient levoglucosan in winter in Beijing. The results suggest that LG cannot be used as a distinct source marker for biomass burning in special cases such as some cities in the northern China, where coal is still widely used in the residential and industrial sectors. Biomass burning sources could be overestimated, although such an over-estimation could vary spatially and temporally.

Seafloor fluid seeps on Kimki Ridge, offshore southern California: Links to active strike-slip faulting - Conrad, James E.; Prouty, Nancy G.; Walton, Maureen A.L.; Kluesner, Jared W.; Maier, Katherine L.; McGann, Mary; Brothers, Daniel S.; Roland, Emily C.; Dartnell, Peter (Deep Sea Research Part II: Topical Studies in Oceanography, 2018)
The Kimki Ridge fluid seeps are located in western Catalina Basin about 60 km southwest of the southern California mainland and at a water depth of approximately 1100 m. Multichannel seismic reflection profiles collected by the U.S. Geological Survey (USGS) in 2014 show acoustic transparency within the Kimki Ridge, suggesting the possibility of fluid seeps and possible sub-seafloor fluid pathways. Subsequent multibeam bathymetric and backscatter intensity data collected during a cooperative University of Washington/USGS cruise in early 2016 show subtle seafloor buildups with high acoustic backscatter (reflectivity) in three places along Kimki Ridge, supporting the existence of fluid seepage. A Remotely Operated Vehicle (ROV) dive, conducted as part of the Nautilus Exploration Program, took place in August 2016 to confirm the presence of these previously unknown seeps and document their characteristics as well as those of any associated biological communities. Two of the three seeps were explored by ROV, and showed abundant evidence of fluid seepage, including characteristic algal mats, chemosynthetic clams, and authigenic carbonate formation. The seeps are comprised of carbonate buildups 1–3 m thick and 300–500 m across. Within these areas, we interpret broad crater-like depressions 30–50 m across and 1–2 m deep to be individual seep vents. The seep areas appear to be broad zones of diffuse seepage that support chemosynthetic biologic communities; however, active venting was not observed. Geochemical analyses of rock samples collected from the seeps indicate microbially driven anaerobic oxidation of methane at or near the sediment water interface. Seismic-reflection profiles show chimney-like fluid pathways along the limbs and in the axis of the fold forming Kimki Ridge, and evidence of methane in shallow sediments can be traced into the adjacent Catalina Basin. A system of closely spaced faults located at the axis of the Kimki Ridge anticline may serve as pathways to allow fluid flow to the seafloor. Our data are consistent with other studies that suggest that transpression is an important component in the formation and localization of fluid seeps in a strike-slip setting, implying that seep formation may be a common occurrence at fault stepovers or transpressional bends in strike-slip systems.
Keywords: California Inner Continental Borderland; E/V Nautilus; Faulting; methane; Seepages

Tropical peatland carbon storage linked to global latitudinal trends in peat recalcitrance - Hodgkins, Suzanne B.; Richardson, Curtis J.; Dommain, René; Wang, Hongjun; Glaser, Paul H.; Verbeke, Brittany; Winkler, B. Rose; Cobb, Alexander R.; Rich, Virginia I.; Missilmani, Malak; Flanagan, Neal; Ho, Mengchi; et al. (Nature Communications, 2018)
Peatlands represent large terrestrial carbon banks. Given that most peat accumulates in boreal regions, where low temperatures and water saturation preserve organic matter, the existence of peat in (sub)tropical regions remains enigmatic. Here we examined peat and plant chemistry across a latitudinal transect from the Arctic to the tropics. Near-surface low-latitude peat has lower carbohydrate and greater aromatic content than near-surface high-latitude peat, creating a reduced oxidation state and resulting recalcitrance. This recalcitrance allows peat to persist in the (sub)tropics despite warm temperatures. Because we observed similar declines in carbohydrate content with depth in high-latitude peat, our data explain recent field-scale deep peat warming experiments in which catotelm (deeper) peat remained stable despite temperature increases up to 9 °C. We suggest that high-latitude deep peat reservoirs may be stabilized in the face of climate change by their ultimately lower carbohydrate and higher aromatic composition, similar to tropical peats.

Using Stable and Radiocarbon Analyses as a Forensic Tool to Find Evidence of Oil in the Particulates of the Water Column and on the Seafloor Following the 2010 Gulf of Mexico Oil Spill - Bosman, Samantha H.; Chanton, Jeffrey P.; Rogers, Kelsey L. (Elsevier, 2018)
Over 600 million liters of oil and copious amounts of methane were released into the Gulf of Mexico between April 20, 2010 and July 15, 2010. We used stable and radiocarbon analyses as a forensic tool to trace these hydrocarbons from the Deepwater Horizon (DwH) well into suspended particulate organic carbon (POCsusp), sinking particulate organic carbon (POCsink), and sedimentary organic carbon on the seafloor. POCsusp samples were considerably depleted both in δ13C and Δ14C relative to surface production, with δ13C and Δ14C values as low as −37.2‰ and −618‰, respectively. POCsink time series data revealed a modern Δ14C value due to a large diatom bloom in early September 2010, but values became depleted as oil contaminated particles continued to descend in the water column until the end of the year. Sediment cores collected in the vicinity of the DwH wellhead revealed evidence of oil contamination in the surface layer (0–1 cm), as indicated by a depletion in Δ14C values compared to the layers below the surface. In addition to providing evidence of oil contamination using stable and radiocarbon analyses, our study was consistent with the existence of a pathway by which spilled oil was deposited onto the seafloor.
Keywords: Deepwater Horizon; isotopes; methane; Petrocarbon; POCsin; POCsusp; Sediment

3000 Years of Human Subsistence and Estuarine Resource Exploitation on the Rhode River Estuary, Chesapeake Bay, Maryland - Rick, Torben C.; Reeder-Myers, Leslie A.; Carr, Michael J.; Hines, Anson H. (Journal of the North Atlantic, 2017)
Chesapeake Bay is home to highly productive marine ecosystems that were a key part of Native American subsistence for millennia. Despite a number of archaeological projects focused on Chesapeake Bay prehistory, key questions remain about the nature of human use of the estuary through time and across space. Recent work at 7 shell middens on the Rhode River Estuary, MD, provides insight into human subsistence and estuarine res ource exploitation from ∼3200 years ago through the mid-19th century. This is an important diachronic sequence of coastal land use and subsistence for the Chesapeake and helps fill a gap in our understanding of coastal adaptations along North America's Atlantic Coast. Despite climate change, fluctuating sea levels, and the likely appearance of maize agriculture in the area ∼1000 years ago, Native American exploitation of oysters and estuarine resources remained fairly consistent across the Early to Late Woodland. These data stand in contrast to the mid-1800s assemblage, which was likely deposited by 19th-century Euro-Americans and contains overall larger oysters perhaps obtained from deeper waters that may not have been a focus of Native American harvest. When placed in the context of other regional data, our analysis illustrates the value of shell middens for helping understand human subsistence strategies and the historical ecol ogy of the North American Atlantic Coast.

The 3.6 ka Aniakchak tephra in the Arctic Ocean: a constraint on the Holocene radiocarbon reservoir age in the Chukchi Sea - Pearce, Christof; Varhelyi, Aron; Wastegård, Stefan; Muschitiello, Francesco; Barrientos, Natalia; O'Regan, Matt; Cronin, Thomas M.; Gemery, Laura; Semiletov, Igor; Backman, Jan; Jakobsson, Martin (Climate of the Past, 2017)
The caldera-forming eruption of the Aniakchak volcano in the Aleutian Range on the Alaskan Peninsula at 3.6 cal kyr BP was one of the largest Holocene eruptions worldwide. The resulting ash is found as a visible sediment layer in several Alaskan sites and as a cryptotephra on Newfoundland and Greenland. This large geographic distribution, combined with the fact that the eruption is relatively well constrained in time using radiocarbon dating of lake sediments and annual layer counts in ice cores, makes it an excellent stratigraphic marker for dating and correlating mid–late Holocene sediment and paleoclimate records. This study presents the outcome of a targeted search for the Aniakchak tephra in a marine sediment core from the Arctic Ocean, namely Core SWERUS-L2-2-PC1 (2PC), raised from 57 m water depth in Herald Canyon, western Chukchi Sea. High concentrations of tephra shards, with a geochemical signature matching that of Aniakchak ash, were observed across a more than 1.5 m long sediment sequence. Since the primary input of volcanic ash is through atmospheric transport, and assuming that bioturbation can account for mixing up to ca. 10 cm of the marine sediment deposited at the coring site, the broad signal is interpreted as sustained reworking at the sediment source input. The isochron is therefore placed at the base of the sudden increase in tephra concentrations rather than at the maximum concentration. This interpretation of major reworking is strengthened by analysis of grain size distribution which points to ice rafting as an important secondary transport mechanism of volcanic ash. Combined with radiocarbon dates on mollusks in the same sediment core, the volcanic marker is used to calculate a marine radiocarbon reservoir age offset ΔR = 477 ± 60 years. This relatively high value may be explained by the major influence of typically "carbon-old" Pacific waters, and it agrees well with recent estimates of ΔR along the northwest Alaskan coast, possibly indicating stable oceanographic conditions during the second half of the Holocene. Our use of a volcanic absolute age marker to obtain the marine reservoir age offset is the first of its kind in the Arctic Ocean and provides an important framework for improving chronologies and correlating marine sediment archives in this region. Core 2PC has a high sediment accumulation rate averaging 200 cm kyr throughout the last 4000 years, and the chronology presented here provides a solid base for high-resolution reconstructions of late Holocene climate and ocean variability in the Chukchi Sea.

Age Constraints on Gulf of Mexico Deep Water Ventilation as Determined by 14C MeasurementsAbstract - Chapman, Piers; DiMarco, Steven F; Key, Robert M; Previti, Connie; Yvon-Lewis, Shari (Radiocarbon, 2017)
While the exchange of water through Yucatan Strait is reasonably well known, the age of the deep water in both the Caribbean Sea and Gulf of Mexico is not. We recently measured the radiocarbon (14C) concentrations in deep water in the Gulf of Mexico from a line of stations along 90°30′W. The mean apparent age of water below 900 m, the depth of the Florida Strait sill, was found to be about 740 yr relative to the 1950 14C standard. Depending on how the corrections for biological activity in the upper water are applied, this converts to a “true” age of between 231 ± 28 and 293 ± 74 yr. These ages agree with a previous estimate of the age of the deep water in the Gulf of Mexico based on heat flows, put upper limits on the age of the deep water in the Caribbean Sea, and provide constraints on modelers for the return of deep water from the Gulf of Mexico to the Caribbean. This might be important in the event of a future deep water oil or other chemical spill in the region.
Keywords: Gulf of Mexico; radiocarbon AMS dating; water

Analysis of piston cores and high-resolution sub-bottom profiler data, Baffin Bay slope, Nunavut - Campbell, D C; Jenner, K A; Higgins, J; Piper, D J W (2017)
Preface This Open File report summarizes a set of 20 piston cores, up to 822 cm long, taken from the continental slope of Baffin Bay, Canada, in water depths between 833 and 1715 m. It provides down-core lithostratigraphy, physical properties measurements, core photography and core X-radiography, in addition to high-resolution seismic data over most core sites, selected grain size data and portable X-ray fluorescence data. Preliminary along-slope correlation between cores and AMS radiocarbon ages are also provided. Further information on these cores is available through the Expedition Database at http://ed.gdr.nrcan.gc.ca/index_e.php Acknowledgments We thank Dan Meagher, Jesse Sherwin and Meaghan MacQuarrie for assistance with core processing and core logging and Jessica Parkinson and Simon Poirier for core data compilation. Owen Brown completed grain size analyses and Linda Fan assisted with these analyses and plotted the grain size data.We also thank Kate Jarrett for assistance with core subsampling.

Biogeochemical properties of sinking particles in the southwestern part of the East Sea (Japan Sea) - Minkyoung Kim; Jeomshik Hwang; TaeKeun Rho; Tongsup Lee; Dong-Jin Kang; Kyung-Il Chang; Suyun Noh; HuiTae Joo; Jung Hyun Kwak; Chang-Keun Kang; Kyung-Ryul Kim (Journal of Marine Systems, 2017)
Abstract This study investigates the biological pump system in the East Sea (Japan Sea) by conducting an analysis of the total particle flux, biogenic material composition, and carbon isotope ratios of sinking particles. The samples were collected for one year starting from March 2011 using time-series sediment traps deployed at depths of 1040 m and 2280 m on bottom-tethered mooring at Station \{EC1\} (37.33°N, 131.45°E; 2300 m water depth) in the Ulleung Basin (UB), southwestern part of the East Sea. The temporal variation in the particulate organic carbon (POC) flux at 1000 m shows a good relationship with the primary production in the corresponding surface water. The ratio of \{POC\} flux at 1000 m to satellite-based primary production in the corresponding region in the \{UB\} was   3%, which is comparable to the values of 2 to 5% estimated from previous studies of other part of the East Sea. The lithogenic material accounted for > 17% of the sinking particles at 1000 m and for a larger fraction of 40 to 60% at 2280 m. The radiocarbon contents of the sinking \{POC\} at both trap depths imply the additional supply of aged POC, with a much greater contribution at 2280 m. Overall, the particle flux in the deep interior of the East Sea appears to be controlled by the supply of complex sources, including aeolian input, the lateral supply of resuspended sediments, and biological production in the surface water.
Keywords: East Sea (Japan Sea)

Biological and physical controls on the flux and characteristics of sinking particles on the Northwest Atlantic margin - Hwang, Jeomshik; Manganini, Steven J.; Park, JongJin; çon, Daniel B.; Toole, John M.; Eglinton, Timothy I. (Journal of Geophysical Research: Oceans, 2017)
Biogenic matter characteristics and radiocarbon contents of organic carbon (OC) were examined on sinking particle samples intercepted at three nominal depths of 1000 m, 2000 m, and 3000 m (similar to 50 m above the seafloor) during a 3 year sediment trap program on the New England slope in the Northwest Atlantic. We have sought to characterize the sources of sinking particles in the context of vertical export of biogenic particles from the overlying water column and lateral supply of resuspended sediment particles from adjacent margin sediments. High aluminum (Al) abundances and low OC radiocarbon contents indicated contributions from resuspended sediment which was greatest at 3000 m but also significant at shallower depths. The benthic source (i.e., laterally supplied resuspended sediment) of opal appears negligible based on the absence of a correlation with Al fluxes. In comparison, CaCO3 fluxes at 3000 m showed a positive correlation with Al fluxes. Benthic sources accounted for 42 similar to 63% of the sinking particle flux based on radiocarbon mass balance and the relationship between Al flux and CaCO3 flux. Episodic pulses of Al at 3000 m were significantly correlated with the near-bottom current at a nearby hydrographic mooring site, implying the importance of current variability in lateral particle transport. However, Al fluxes at 1000 m and 2000 m were coherent but differed from those at 3000 m, implying more than one mode of lateral supply of particles in the water column.

Climate and environmental changes for the past 44 ka clarified by pollen and algae composition in the Ulleung Basin, East Sea (Japan Sea) - Jinxia Chen; Yanguang Liu; Xuefa Shi; Bong-Chool Suk; Jianjun Zou; Zhengquan Yao (Quaternary International, 2017)
Abstract The pollen and algae records derived from core KCES-1 in the East Sea (Japan Sea) reveal vegetation and climate changes during the past 44 ka. From 44 to 36 cal ka BP, forest vegetation in the coastal regions of Ulleung Basin was composed predominantly of subalpine conifer forest, open grassland covered the exposed continental shelves, indicating a cool and dry climate. During the period of 36–28.3 cal ka BP, a warmer and wetter climate caused the contraction of subalpine conifer forest in the coastal regions of Ulleung Basin, and the expansion of marsh in the exposed continental shelves. From 28.3 to 17.6 cal ka BP, the sea-level decline restricted the herbs pollen originates in the exposed shelf of East China Sea and Yellow Sea inflow into the East Sea (Japan Sea), and caused the reduction of herbs pollen in the site location. During the time interval of 17.6–15.1 cal ka BP, a great expansion of subalpine conifer forest can be regarded as the consequence of enhanced East Asian winter monsoon (EAWM). The obvious increase in temperate deciduous broadleaved trees, spores and algae can be attributable to the rising of sea level and the warming of climate from 15.1 to 12.1 cal ka BP. During the period of 12.1 to 5.3 cal ka BP, broadleaved taxa increased, especially during the time period of 9.5–5.3 cal ka BP, evergreen broadleaved trees pollen reach the highest values throughout the core, as a result of the Holocene climate optimum condition. Vegetation changes controlled by humid impacts occurred at the late Holocene, as indicated by an increase in Pinus pollen.
Keywords: East Sea (Japan Sea)

The De Long Trough: a newly discovered glacial trough on the East Siberian continental margin - O'Regan, Matt; Backman, Jan; Barrientos, Natalia; Cronin, Thomas M.; Gemery, Laura; Kirchner, Nina; Mayer, Larry A.; Nilsson, Johan; Noormets, Riko; Pearce, Christof; Semiletov, Igor; Stranne, Christian; et al. (Climate of the Past, 2017)
Ice sheets extending over parts of the East Siberian continental shelf have been proposed for the last glacial period and during the larger Pleistocene glaciations. The sparse data available over this sector of the Arctic Ocean have left the timing, extent and even existence of these ice sheets largely unresolved. Here we present new geophysical mapping and sediment coring data from the East Siberian shelf and slope collected during the 2014 SWERUS-C3 expedition (SWERUS-C3: Swedish – Russian – US Arctic Ocean Investigation of Climate-Cryosphere-Carbon Interactions). The multibeam bathymetry and chirp sub-bottom profiles reveal a set of glacial landforms that include grounding zone formations along the outer continental shelf, seaward of which lies a  >  65 m thick sequence of glacio-genic debris flows. The glacial landforms are interpreted to lie at the seaward end of a glacial trough – the first to be reported on the East Siberian margin, here referred to as the De Long Trough because of its location due north of the De Long Islands. Stratigraphy and dating of sediment cores show that a drape of acoustically laminated sediments covering the glacial deposits is older than ∼ 50 cal kyr BP. This provides direct evidence for extensive glacial activity on the Siberian shelf that predates the Last Glacial Maximum and most likely occurred during the Saalian (Marine Isotope Stage (MIS) 6).

The deep distributions of helium isotopes, radiocarbon, and noble gases along the U.S. GEOTRACES East Pacific Zonal Transect (GP16) - W. J. Jenkins; Dempsey E. Lott III; Christopher R. German; Kevin L. Cahill; Joanne Goudreau; Brett Longworth (Marine Chemistry, 2017)
Abstract We report the deep distributions of noble gases, helium isotopes, and radiocarbon measured during the U.S. \{GEOTRACES\} \{GP16\} East Pacific Zonal Transect between 152 and 77°W at 12–15°S in the South Pacific. The dominant feature is an intense tongue of hydrothermal effluent that extends > 4000 km westward from the East Pacific Rise (EPR) at   2500 m depth. The patterns reveal significant “downstream” variations in water mass structure, advection, and mixing that belie the simple perception of a continuous plume extending westward from the EPR. For example, one feature observed at 120°W, 14°S has tracer signatures that are consistent with a water mass originating from an area as much as 2000 km south of this section, suggesting a quasi-permanent northward flow on the western flank of the EPR. Helium isotope variations in the plume show a uniquely high 3He/4He source in the tongue compared with typical mid-ocean ridge basalts (MORB), consistent with the anomalously high ratios observed in \{MORB\} glasses from the \{EPR\} segment just south of this transect. The water column data also reveal that the background 3He/4He east of the \{EPR\} is significantly lower than values characteristic of MORB, suggesting an additional, more geographically distributed radiogenic 4He flux of order 107 mol/y into the deep Pacific. In the western end of the section, incoming bottom waters have relatively less hydrothermal hydrothermal helium, more radiocarbon, and more oxygen, as well as negative saturation anomalies for the heavy noble gases (Ar, Kr, and Xe). During the basin-scale upwelling of this water, diapycnal mixing serves to erase these negative anomalies. The relative magnitudes of the increases for the heavy noble gases (Ar, Kr, and Xe) are quantitatively consistent with this process. This leads us to estimate the relatively smaller effects on He and Ne saturations, which range from near zero to 0.2% and 0.3% respectively. With this information, we are able to refine our estimates of the magnitude of 3He and 4He excesses and the absolute 3He/4He ratio of non-atmospheric helium introduced into deep Pacific waters.

Deglacial sea level history of the East Siberian Sea and Chukchi Sea margins - Cronin, Thomas M.; O'Regan, Matt; Pearce, Christof; Gemery, Laura; Toomey, Michael; Semiletov, Igor; Jakobsson, Martin (Climate of the Past, 2017)
Deglacial (12.8–10.7 ka) sea level history on the East Siberian continental shelf and upper continental slope was reconstructed using new geophysical records and sediment cores taken during Leg 2 of the 2014 SWERUS-C3 expedition. The focus of this study is two cores from Herald Canyon, piston core SWERUS-L2-4-PC1 (4-PC1) and multicore SWERUS-L2-4-MC1 (4-MC1), and a gravity core from an East Siberian Sea transect, SWERUS-L2-20-GC1 (20-GC1). Cores 4-PC1 and 20-GC were taken at 120 and 115 m of modern water depth, respectively, only a few meters above the global last glacial maximum (LGM;  ∼  24 kiloannum or ka) minimum sea level of  ∼  125–130 meters below sea level (m b.s.l.). Using calibrated radiocarbon ages mainly on molluscs for chronology and the ecology of benthic foraminifera and ostracode species to estimate paleodepths, the data reveal a dominance of river-proximal species during the early part of the Younger Dryas event (YD, Greenland Stadial GS-1) followed by a rise in river-intermediate species in the late Younger Dryas or the early Holocene (Preboreal) period. A rapid relative sea level rise beginning at roughly 11.4 to 10.8 ka ( ∼  400 cm of core depth) is indicated by a sharp faunal change and unconformity or condensed zone of sedimentation. Regional sea level at this time was about 108 m b.s.l. at the 4-PC1 site and 102 m b.s.l. at 20-GC1. Regional sea level near the end of the YD was up to 42–47 m lower than predicted by geophysical models corrected for glacio-isostatic adjustment. This discrepancy could be explained by delayed isostatic adjustment caused by a greater volume and/or geographical extent of glacial-age land ice and/or ice shelves in the western Arctic Ocean and adjacent Siberian land areas.

Deglaciation and ice shelf development at the northeast margin of the Laurentide Ice Sheet during the Younger Dryas chronozone - Furze, Mark F. A.; ńkowski, Anna J.; McNeely, Morgan A.; Bennett, Robbie; Cage, Alix G. (Boreas, 2017)
Core 2011804-0010 from easternmost Lancaster Sound provides important insights into deglacial timing and style at the marine margin of the NE Laurentide Ice Sheet (LIS). Spanning 13.2–11.0 cal. ka BP and investigated for ice-rafted debris (IRD), foraminifera, biogenic silica and total organic carbon, the stratigraphy comprises a lithofacies progression from proximal grounding line and sub-ice shelf environments to open glaciomarine deposition; a sequence similar to deposits from Antarctic ice shelves. These results are the first marine evidence of a former ice shelf in the eastern Northwest Passage and are consistent with a preceding phase of ice streaming in eastern Lancaster Sound. Initial glacial float-off and retreat occurred >13.2 cal. ka BP, followed by formation of an extensive deglacial ice shelf during the Younger Dryas, which acted to stabilize the retreating margin of the NE LIS until 12.5 cal. ka BP. IRD analyses of sub-ice shelf facies indicate initial high input from source areas on northern Baffin Island delivered to Lancaster Sound by a tributary ice stream in Admiralty Inlet. After ice shelf break-up, Bylot Island became the dominant source area. Foraminifera are dominated by characteristic ice-proximal glaciomarine benthics (Cassidulina reniforme, Elphidium excavatum f. clavata), complemented by advected Atlantic water (Cassidulina neoteretis, Neogloboquadrina pachyderma) and enhanced current indicators (Lobatula lobatula). The biostratigraphy further supports the ice shelf model, with advection of sparse faunas beneath the ice shelf, followed by increased productivity under open water glaciomarine conditions. The absence of Holocene sediments in the core suggests that the uppermost deposits were removed, most likely due to mass transport resulting from the site's proximity to modern tidewater glacier margins. Collectively, this study presents important new constraints on the deglacial behaviour of the NE Laurentide Ice Sheet, with implications for past ice sheet stability, ice-rafted sediment delivery, and ice−ocean interactions in this complex archipelago setting.

The distribution and utility of sea-level indicators in Eurasian sub-Arctic salt marshes (White Sea, Russia) - Kemp, Andrew C.; Horton, Benjamin P.; Nikitina, Daria; Vane, Christopher H.; Potapova, Marina; Weber-Bruya, Elizabeth; Culver, Stephen J.; Repkina, Tatyana; Hill, David F. (Boreas, 2017)
In support of efforts to reconstruct relative sea level (RSL), we investigated the utility of foraminifera, diatoms and bulk‐sediment geochemistry (δ13C, C:N and parameters measured by Rock‐Eval pyrolysis) as sea‐level indicators in Eurasian sub‐Arctic salt marshes. At three salt marshes (<15 km apart) in Dvina Bay (White Sea, Russia), we collected surface sediment samples along transects from subtidal to Taiga forest environments. Foraminifera at all sites formed bipartite assemblages, where elevations below mean high higher water (MHHW) were dominated by Miliammina spp. and elevations between MHHW and the highest occurrence of foraminifera were dominated by Jadammina macrescens and Balticammina pseudomacrescens. Five high‐diversity groups of diatoms were identified and they displayed pronounced variability amongst the study sites. Bulk‐sediment geochemistry recognized two groups (clastic‐dominated environments below MHHW and organic‐rich environments above MHHW). As one group included subtidal elevations and the other included supratidal elevations, we conclude that the measured geochemical parameters are not stand‐alone sea‐level indicators. Core JT2012 captured a regressive sediment succession of clastic, tidal‐flat sediment overlain by salt‐marsh organic silt and freshwater peat. The salt‐marsh sediment accumulated at 2804±52 years before present and preserved foraminifera (Jadammina macrescens and Balticammina pseudomacrescens) with good analogy to modern assemblages indicating that RSL was +2.60±0.47 m at this time. Diatoms confirm that marine influence decreased through time, but the lack of analogy between modern and core assemblages limited their utility as sea‐level indicators. Geochemical parameters also indicate a reduction in marine influence through time. We conclude that RSL reconstructions derived from salt‐marsh sediment preserved beneath Eurasian sub‐Arctic peatlands can provide valuable insight into the spatio‐temporal evolution of the Fennoscandian and Eurasian ice sheets.

Erosion of modern terrestrial organic matter as a major component of sediments in fjords - Cui, Xingqian; Bianchi, Thomas S.; Savage, Candida (Geophysical Research Letters, 2017)
Fjords have recently been recognized as “hot spots” of carbon burial. In this study, we investigated organic carbon (OC) and biomarker radiocarbon values in fjord sediments from New Zealand. Our results showed that OC was mostly modern with the most aged OC in middle reaches of fjords, likely related to hydrodynamic sorting and inputs along adjacent slopes. Radiocarbon ages of sedimentary OC increased from north-to-south, consistent with the Fiordland regional gradients of lower fjord slopes and less rainfall. Our biomarker results suggested that lignin and long-chain fatty acids were preferentially linked with fresh terrestrial debris and degraded soil, respectively, likely due to their chemical and physical properties. Finally, we propose that fjords are a significant sink of modern OC, in contrast to large lowland coastal systems as a major sink of preaged OC. Overall, this study indicated that radiocarbon techniques are critical in investigating carbon dynamics in coastal systems.

Evidence for coseismic subsidence events in a southern California coastal saltmarsh - Leeper, Robert; Rhodes, Brady; Kirby, Matthew; Scharer, Katherine; Carlin, Joseph; Hemphill-Haley, Eileen; Avnaim-Katav, Simona; MacDonald, Glen; Starratt, Scott; Aranda, Angela (Scientific Reports, 2017)
Paleoenvironmental records from a southern California coastal saltmarsh reveal evidence for repeated late Holocene coseismic subsidence events. Field analysis of sediment gouge cores established discrete lithostratigraphic units extend across the wetland. Detailed sediment analyses reveal abrupt changes in lithology, percent total organic matter, grain size, and magnetic susceptibility. Microfossil analyses indicate that predominantly freshwater deposits bury relic intertidal deposits at three distinct depths. Radiocarbon dating indicates that the three burial events occurred in the last 2000 calendar years. Two of the three events are contemporaneous with large-magnitude paleoearthquakes along the Newport-Inglewood/Rose Canyon fault system. From these data, we infer that during large magnitude earthquakes a step-over along the fault zone results in the vertical displacement of an approximately 5-km2 area that is consistent with the footprint of an estuary identified in pre-development maps. These findings provide insight on the evolution of the saltmarsh, coseismic deformation and earthquake recurrence in a wide area of southern California, and sensitive habitat already threatened by eustatic sea level rise.
Keywords: Geomorphology; Natural hazards; Structural geology; tectonics

Extended late Holocene relative sea-level histories for North Carolina, \{USA\} - Andrew C. Kemp; Jessica J. Kegel; Stephen J. Culver; Donald C. Barber; David J. Mallinson; Eduardo Leorri; Christopher E. Bernhardt; Niamh Cahill; Stanley R. Riggs; Anna L. Woodson; Ryan P. Mulligan; Benjamin P. Horton (Quaternary Science Reviews, 2017)
Abstract We produced ∼3000-year long relative sea-level (RSL) histories for two sites in North Carolina (USA) using foraminifera preserved in new and existing cores of dated salt-marsh sediment. At Cedar Island, \{RSL\} rose by ∼2.4 m during the past ∼3000 years compared to ∼3.3 m at Roanoke Island. This spatial difference arises primarily from differential \{GIA\} that caused late Holocene \{RSL\} rise to be 0.1–0.2 mm/yr faster at Roanoke Island than at Cedar Island. However, a non-linear difference in \{RSL\} between the two study regions (particularly from ∼0 \{CE\} to ∼1250 CE) indicates that additional local- to regional-scale processes drove centennial-scale \{RSL\} change in North Carolina. Therefore, the Cedar Island and Roanoke Island records should be considered as independent of one another. Between-site differences on sub-millennial timescales cannot be adequately explained by non-stationary tides, sediment compaction, or local sediment dynamics. We propose that a period of accelerating \{RSL\} rise from ∼600 \{CE\} to 1100 \{CE\} that is present at Roanoke Island (and other sites north of Cape Hatteras at least as far as Connecticut), but absent at Cedar Island (and other sites south of Cape Hatteras at least as far as northeastern Florida) is a local-to regional-scale effect of dynamic ocean and/or atmospheric circulation.
Keywords: Salt marsh

Extreme waves in the British Virgin Islands during the last centuries before 1500 CE - Atwater, Brian F.; ten Brink, Uri S.; Cescon, Anna Lisa; Feuillet, Nathalie; Fuentes, Zamara; Halley, Robert B.; ñez, Carlos; Reinhardt, Eduard G.; Roger, Jean H.; Sawai, Yuki; Spiske, Michaela; Tuttle, Martitia P.; et al. (Geosphere, 2017)
Extraordinary marine inundation scattered clasts southward on the island of Anegada, 120 km south of the Puerto Rico Trench, sometime between 1200 and 1480 calibrated years (cal yr) CE. Many of these clasts were likely derived from a fringing reef and from the sandy flat that separates the reef from the island’s north shore. The scattered clasts include no fewer than 200 coral boulders, mapped herein for the first time and mainly found hundreds of meters inland. Many of these are complete colonies of the brain coral Diploria strigosa. Other coral species represented include Orbicella (formerly Montastraea) annularis, Porites astreoides, and Acropora palmata. Associated bioclastic carbonate sand locally contains articulated cobble-size valves of the lucine Codakia orbicularis and entire conch shells of Strombus gigas, mollusks that still inhabit the sandy shallows between the island’s north shore and a fringing reef beyond. italicmbricated limestone slabs are clustered near some of the coral boulders. In addition, fields of scattered limestone boulders and cobbles near sea level extend mainly southward from limestone sources as much as 1 km inland. Radiocarbon ages have been obtained from 27 coral clasts, 8 lucine valves, and 3 conch shells. All these additional ages predate 1500 cal yr CE, all but 2 are in the range 1000–1500 cal yr CE, and 16 of 22 brain coral ages cluster in the range 1200–1480 cal yr CE. The event marked by these coral and mollusk clasts likely occurred in the last centuries before Columbus (before 1492 CE). The pre-Columbian deposits surpass Anegada’s previously reported evidence for extreme waves in post-Columbian time. The coarsest of the modern storm deposits consist of coral rubble that lines the north shore and sandy fans on the south shore; neither of these storm deposits extends more than 50 m inland. More extensive overwash, perhaps by the 1755 Lisbon tsunami, is marked primarily by a sheet of sand and shells found mainly below sea level beneath the floors of modern salt ponds. This sheet extends more than 1 km southward from the north shore and dates to the interval 1650–1800 cal yr CE. Unlike the pre-Columbian deposits, it lacks coarse clasts from the reef or reef flat; its shell assemblage is instead dominated by cerithid gastropods that were merely stirred up from a marine pond in the island’s interior. In their inland extent and clustered pre-Columbian ages, the coral clasts and associated deposits suggest extreme waves unrivaled in recent millennia at Anegada. Bioclastic sand coats limestone 4 m above sea level in areas 0.7 and 1.3 km from the north shore. A coral boulder of nearly 1 m3 is 3 km from the north shore by way of an unvegetated path near sea level. As currently understood, the extreme flooding evidenced by these and other clasts represents either an extraordinary storm or a tsunami of nearby origin. The storm would need to have produced tsunami-like bores similar to those of 2013 Typhoon Haiyan in the Philippines. Normal faults and a thrust fault provide nearby tsunami sources along the eastern Puerto Rico Trench.

Greenhouse gas balance over thaw-freeze cycles in discontinuous zone permafrost - Wilson, R. M.; Fitzhugh, L.; Whiting, G. J.; Frolking, S.; Harrison, M. D.; Dimova, N.; Burnett, W. C.; Chanton, J. P. (Journal of Geophysical Research: Biogeosciences, 2017)
Peat in the discontinuous permafrost zone contains a globally significant reservoir of carbon that has undergone multiple permafrost-thaw cycles since the end of the mid-Holocene (~3700 years before present). Periods of thaw increase C decomposition rates which leads to the release of CO2 and CH4 to the atmosphere creating potential climate feedback. To determine the magnitude and direction of such feedback, we measured CO2 and CH4 emissions and modeled C accumulation rates and radiative fluxes from measurements of two radioactive tracers with differing lifetimes to describe the C balance of the peatland over multiple permafrost-thaw cycles since the initiation of permafrost at the site. At thaw features, the balance between increased primary production and higher CH4 emission stimulated by warmer temperatures and wetter conditions favors C sequestration and enhanced peat accumulation. Flux measurements suggest that frozen plateaus may intermittently (order of years to decades) act as CO2 sources depending on temperature and net ecosystem respiration rates, but modeling results suggest that—despite brief periods of net C loss to the atmosphere at the initiation of thaw—integrated over millennia, these sites have acted as net C sinks via peat accumulation. In greenhouse gas terms, the transition from frozen permafrost to thawed wetland is accompanied by increasing CO2 uptake that is partially offset by increasing CH4 emissions. In the short-term (decadal time scale) the net effect of this transition is likely enhanced warming via increased radiative C emissions, while in the long-term (centuries) net C deposition provides a negative feedback to climate warming.

A high resolution record of rare earth element compositional changes from the mud deposit on the inner shelf of the East China Sea: Implications for paleoenvironmental changes - Mi, Beibei; Liu, Shengfa; Shi, Xuefa; Li, Xiaoyan; Pan, Hui-Juan; Chen, Min-Te; Wang, Xuchen (Quaternary International, 2017)
A paleoenvironmental reconstruction of the East China Sea (ECS) is presented using rare earth element (REE) analysis of sediments from Core MZ02, which was retrieved from the inner continental shelf's mud area. The analytic results show that the total REEs in the fine sediment vary between 137.76 μg/g and 231.53 μg/g with an average value of 187.69 μg/g. Obvious changes were found during the process of sedimentation. By comparing with the REE compositions from the potential provenances, the ratios of (La/Sm)ucc and (Gd/Yb)ucc revealed that the sediments were mainly derived from river detrital outputs of the Changjiang (Yangtze River), Minjiang and mountainous rivers from western Taiwan Island. The contributions of terrestrial materials from these three main provenances were controlled by sea level change and the Taiwan Warm Current (TWC)-Chinese Coastal Current (CCC) system, which is mainly driven by the East Asian monsoon. The high sedimentation rate during the transgression period between the late Pleistocene and early Holocene (13000–9800 a B.P.) was caused by a well-proportioned mixed provenance from Changjiang, western Taiwanese rivers and Minjiang sediments, due to the lower sea level and the location of the foreshore-nearshore face. Because of the stronger sediment reworking and erosion at the shelf edge during the early Holocene (9800–7300 a B.P.), the strengthening summer East Asian monsoon transported the Minjiang and western Taiwanese river material northeastward, and it became the main sediment source for fine sediments in the shallow sea region of the ECS, while the Changjiang provided a relatively minor amount of detrital sediment to the shelf. The increasing strength of the TWC might have played an important role in sediment dispersal and deposition on the ECS inner shelf during the period 7300–3500 a B.P., thus mountainous river material became the dominant sediment on the shelf of the ECS. Furthermore, the results indicate that the East Asian monsoon and the weakening of the TWC were linked to an abrupt increase in Changjiang-derived terrigenous detritus material since 3500 a B.P.; the source and sink pattern during this period is consistent with the modern sedimentation environment.
Keywords: East China Sea; Mud deposit; Paleoenvironmental; Provenance; Rare earth element; Sediment

Holocene sea ice variability driven by wind and polynya efficiency in the Ross Sea - Mezgec, K.; Stenni, B.; Crosta, X.; Masson-Delmotte, V.; Baroni, C.; Braida, M.; Ciardini, V.; Colizza, E.; Melis, R.; Salvatore, M. C.; Severi, M.; Scarchilli, C.; et al. (Nature Communications, 2017)
The causes of the recent increase in Antarctic sea ice extent, characterised by large regional contrasts and decadal variations, remain unclear. In the Ross Sea, where such a sea ice increase is reported, 50% of the sea ice is produced within wind-sustained latent-heat polynyas. Combining information from marine diatom records and sea salt sodium and water isotope ice core records, we here document contrasting patterns in sea ice variations between coastal and open sea areas in Western Ross Sea over the current interglacial period. Since about 3600 years before present, an increase in the efficiency of regional latent-heat polynyas resulted in more coastal sea ice, while sea ice extent decreased overall. These past changes coincide with remarkable optima or minima in the abundances of penguins, silverfish and seal remains, confirming the high sensitivity of marine ecosystems to environmental and especially coastal sea ice conditions.

Insights of Pb isotopic signature into the historical evolution and sources of Pb contamination in a sediment core of the southwestern Iberian Atlantic shelf - Mário Mil-Homens; Carlos Vale; Pedro Brito; Filipa Naughton; Teresa Drago; Joana Raimundo; Bárbara Anes; Sabine Schmidt; Miguel Caetano (Science of The Total Environment, 2017)
Abstract Stable Pb isotopic ratios and concentrations of Al, Cu and Pb were measured in a 5 m long sediment core (VC2B) retrieved at 96 m water depth in the southwestern Iberian Atlantic shelf. Five phases during the last 9.5 kyrs were identified, two of them (Roman Period and modern mining) marked by a decrease of 206Pb/207Pb ratios reflecting additional inputs of Pb derived from mining activities. The Roman Period was also characterized by high 208Pb/206Pb ratios suggesting the exploitation of the outcropping portion of the orebody intensely weathered when compared with the other formations later mined. The shift of 208Pb/206Pb ratios towards linearity took approximately 1.0 kyrs, which may mirror the time of environmental recovery from the impact of Roman mining activities. The application of a mixing model allowed the quantification of the contribution associated with anthropogenic mining activities to the shelf sediments. The maximum values of Pb contamination occurred in the 20th century. This study gives direct evidence of Pb and Cu exploitation over the last 2000 years. The stable Pb isotopic signatures point to legacy of mining activities that are still the prevailing metal source recorded in the southwestern Iberian Atlantic shelf sediments.
Keywords: Environment recovery

Insights of Pb isotopic signature into the historical evolution and sources of Pb contamination in a sediment core of the southwestern Iberian Atlantic shelf - Mil-Homens, ário; Vale, Carlos; Brito, Pedro; Naughton, Filipa; Drago, Teresa; Raimundo, Joana; Anes, árbara; Schmidt, Sabine; Caetano, Miguel (Science of The Total Environment, 2017)
Stable Pb isotopic ratios and concentrations of Al, Cu and Pb were measured in a 5 m long sediment core (VC2B) retrieved at 96 m water depth in the southwestern Iberian Atlantic shelf. Five phases during the last 9.5 kyrs were identified, two of them (Roman Period and modern mining) marked by a decrease of Pb-206/Pb-207 ratios reflecting additional inputs of Pb derived from mining activities. The Roman Period was also characterized by high Pb-208/Pb-206 ratios suggesting the exploitation of the outcropping portion of the orebody intensely weathered when compared with the other formations later mined. The shift of Pb-208/Pb-206 ratios towards linearity took approximately 1.0 kyrs, which may mirror the time of environmental recovery from the impact of Roman mining activities. The application of a mixing model allowed the quantification of the contribution associated with anthropogenic mining activities to the shelf sediments. The maximum values of Pb contamination occurred in the 20th century. This study gives direct evidence of Pb and Cu exploitation over the last 2000 years. The stable Pb isotopic signatures point to legacy of mining activities that are still the prevailing metal source recorded in the southwestern Iberian Atlantic shelf sediments.
Keywords: Environment recovery; Marine sediments; Pb isotopes; Roman and modem mining activities; Southwestern Iberian shelf; Temporal evolution

Investigation of Late Pleistocene and Holocene Activity in the San Gregorio Fault Zone on the Continental Slope North of Monterey Canyon, Offshore Central California - Maier, Katherine L.; Paull, Charles K.; Brothers, Daniel S.; Caress, David W.; McGann, Mary; Lundsten, Eve M.; Anderson, Krystle; Gwiazda, Roberto (Bulletin of the Seismological Society of America, 2017)
We provide an extensive high‐resolution geophysical, sediment core, and radiocarbon dataset to address late Pleistocene and Holocene fault activity of the San Gregorio fault zone (SGFZ), offshore central California. The SGFZ occurs primarily offshore in the San Andreas fault system and has been accommodating dextral strike‐slip motion between the Pacific and North American plates since the mid‐Miocene. Our study focuses on the SGFZ where it has been mapped through the continental slope north of Monterey Canyon. From 2009 to 2015, the Monterey Bay Aquarium Research Institute collected high‐resolution multibeam bathymetry and chirp sub‐bottom profiles using an autonomous underwater vehicle (AUV). Targeted samples were collected using a remotely operated vehicle (ROV) to provide radiocarbon age constraints. We integrate the high‐resolution geophysical data with radiocarbon dates to reveal Pleistocene seismic horizons vertically offset less than 5 m on nearly vertical faults. These faults are buried by continuous reflections deposited after ∼17.5  ka and likely following erosion during the last sea‐level lowstand ∼21  ka⁠, bracketing the age of faulting to ∼32–21  ka⁠. Clearly faulted horizons are only detected in a small area where mass wasting exhumed older strata to within ∼25  m of the seafloor. The lack of clearly faulted Holocene deposits and possible highly distributed faulting in the study area are consistent with previous interpretations that late Pleistocene and Holocene activity along the SGFZ may decrease to the south. This study illustrates the complexity of the SGFZ, offshore central California, and demonstrates the utility of very high‐resolution data from combined AUV (geophysical)–ROV (seabed sampling) surveys in offshore studies of fault activity.

Large-scale response of the Eastern Mediterranean thermohaline circulation to African monsoon intensification during sapropel S1 formation - T. Tesi; A. Asioli; D. Minisini; V. Maselli; G. Dalla Valle; F. Gamberi; L. Langone; A. Cattaneo; P. Montagna; F. Trincardi (Quaternary Science Reviews, 2017)
Abstract The formation of Eastern Mediterranean sapropels has periodically occurred during intensification of northern hemisphere monsoon precipitation over North Africa. However, the large-scale response of the Eastern Mediterranean thermohaline circulation during these monsoon-fuelled freshening episodes is poorly constrained. Here, we investigate the formation of the youngest sapropel (S1) along an across-slope transect in the Adriatic Sea. Foraminifera-based oxygen index, redox-sensitive elements and biogeochemical parameters reveal – for the first time – that the Adriatic \{S1\} was synchronous with the deposition of south-eastern Mediterranean \{S1\} beds. Proxies of paleo thermohaline currents indicate that the bottom-hugging North Adriatic Dense Water (NAdDW) suddenly decreased at the sapropel onset simultaneously with the maximum freshening of the Levantine Sea during the African Humid Period. We conclude that the lack of the “salty” Levantine Intermediate Water hampered the preconditioning of the northern Adriatic waters necessary for the \{NAdDW\} formation prior to the winter cooling. Consequently, a weak \{NAdDW\} limited in turn the Eastern Mediterranean Deep Water (EMDWAdriatic) formation with important consequences for the ventilation of the Ionian basin as well. Our results highlight the importance of the Adriatic for the deep water ventilation and the interdependence among the major eastern Mediterranean water masses whose destabilization exerted first-order control on \{S1\} deposition.
Keywords: Thermohaline circulation

Local and regional wildfire activity in central Maine (USA) during the past 900 years - Miller, Daniel R.; Castañeda, Isla S.; Bradley, Raymond S.; MacDonald, Dana (Journal of Paleolimnology, 2017)
Climatic and environmental change has a direct effect on wildfire frequencies and distributions throughout many regions of the world. Reconstructions from natural archives such as lake sediments can extend temporally limited historical records of regional wildfire activity over longer timescales through sedimentary charcoal analysis or examining polycyclic aromatic hydrocarbon (PAH) concentrations. To date, little work has been completed on sedimentary PAH distributions from lacustrine records in the Northeastern United States, making it difficult to assess how accurately PAHs trace fire activity in the region, the spatial scope of the signal (local vs. regional), or if certain compounds do a more adequate job of tracking fire than others. In this study, we examine PAHs and macrocharcoal from a varved sedimentary record from Basin Pond, Fayette, Maine (USA). We find that a drastic increase in the concentrations of 12 measured PAHs occurred during the nineteenth to twentieth centuries due to industrialization of the region. Additionally, elevated concentrations of the PAH retene were found to be coeval with known large-scale regional wildfire events that occurred in 1761–1762, 1825, and 1947 (A.D.). We used the ratio of the PAHs retene and chrysene to infer differences in biomass burning versus anthropogenic combustion sources because retene is associated with conifer resin whereas chrysene is associated with fossil fuel burning. Our new Basin Pond PAH records, along with a local signal of fire occurrence from charcoal analysis, offers the prospect of using this multi-proxy approach as a method for examining long-term wildfire frequency at both the local and regional scale in the Northeastern US.

Millennial mode of variability of sea ice conditions in the Okhotsk Sea during the last glaciation (MIS 4–MIS 2) - Vasilenko, Yuriy P.; Gorbarenko, Sergey A.; Bosin, Aleksandr A.; Shi, Xue-fa; Chen, Min-Te; Zou, Jian-jun; Liu, Yan-guang; Artemova, Antonina V.; Yanchenko, Elena A.; Savenko, Mikhail P. (Quaternary International, 2017)
Coarse fraction (CF) content, grain-size distribution, roundness of CF, gravels and pebbles, and examination of surface of pebbles were studied in core LV28-44-4, recovered from the eastern Okhotsk Sea (OS). The age model of the studied core was based on the AMS 14C data, tephrochronology, δ18O benthic foraminifera record, and correlation of peaks of productivity proxies with long-lasted Dansgaard-Oeschger (DO) interstadials. The results show that sea ice was the main transport agent for CF (ice-rafted debris, IRD) in the eastern OS. Published mineralogical studies of clastic material of the OS indicated that the coast of western Kamchatka was the main source of IRD in the eastern OS. We found 19 peaks of IRD, which mostly coincided with DO stadials. The distribution of CF indicates a different pattern of IRD supply during MIS 4, 3, and 2. Comparison of IRD records in the eastern and central parts of the OS allow us to reconstruct millennial changes in ice and wind modes for MIS 4–MIS 2. Significant strengthening of northeastern and eastern winds during DOSs of MIS 3 and of northern and north-western winds during MIS 2 were observed.
Keywords: Ice mode; Ice-rafted debris; Millennial-scale variation; Okhotsk Sea; Wind mode

More reducing bottom-water redox conditions during the Last Glacial Maximum in the southern Challenger Deep (Mariana Trench, western Pacific) driven by enhanced productivity - Min Luo; Thomas J. Algeo; Hongpeng Tong; Joris Gieskes; Linying Chen; Xuefa Shi; Duofu Chen (Deep Sea Research Part II: Topical Studies in Oceanography, 2017)
Abstract The modern southern Mariana Trench is characterized by oligotrophic surface waters, resulting in low primary productivity and well-oxygenated bottom waters. This study investigates changes in the redox conditions of bottom waters in the southern Mariana Trench during the Last Glacial Maximum (LGM) and their potential causes. We measured major, trace, and rare earth elements (REE) in three gravity cores (GC03, GC04, and GC05) and one box core (BC11) retrieved from the southern Challenger Deep at water depths from 5289 to 7118 m. The upper sediment layers of both \{GC05\} and \{BC11\} are dominated by valve fragments of the giant diatom Ethmodiscus rex, forming laminated diatom mats (LDMs). 14C-AMS dates of bulk organic matter show that the \{LDMs\} accumulated between 18.4 and 21.8 kyr B.P., corresponding to the LGM. Modest enrichments of U and Mo along with weak or absent Ce anomalies in the \{LDM\} point to suboxic conditions during the LGM. In contrast, non-LDM samples exhibit little to no enrichment of redox-sensitive elements as well as negative Ce anomalies, indicating deposition under oxic bottom-water conditions. The Ce anomalies are considered valid proxies for bottom-water redox conditions because \{REE\} signatures were acquired in the early diagenetic environment, as indicated by strong P-REE correlations and middle-REE enrichment associated with early diagenetic cycling of Fe-Mn oxyhydroxides in the sediment column followed by capture of the \{REE\} signal by biogenic and/or authigenic apatite. We postulate that the more reducing bottom-water conditions during the \{LGM\} were linked to increased primary productivity induced by enhanced Asian dust input. As shown in earlier studies, the increased primary productivity associated with Ethmodiscus rex blooms in the eastern Philippine Sea played a significant role in capturing atmospheric \{CO2\} during the LGM. Consequently, the magnitude of atmospheric \{CO2\} sequestration by giant diatom blooms during the \{LGM\} may have been greater than previously envisaged.
Keywords: Laminated diatom mats

Open-File ReportOpen-File ReportDeepwater Program: Lophelia II, continuing ecological research on deep-sea corals and deep-reef habitats in the Gulf of Mexico - Demopoulos, Amanda W.J.; Ross, Steve W.; Kellogg, Christina A.; Morrison, Cheryl L.; Nizinski, Martha S.; Prouty, Nancy G.; Bourque, Jill R.; Galkiewicz, Julie P.; Gray, Michael A.; Springmann, Marcus J.; Coykendall, D. Katharine; Miller, Andrew; et al. (2017)
The deep sea is a rich environment composed of diverse habitat types. While deep-sea coral habitats have been discovered within each ocean basin, knowledge about the ecology of these habitats and associated inhabitants continues to grow. This report presents information and results from the Lophelia II project that examined deep-sea coral habitats in the Gulf of Mexico. The Lophelia II project focused on Lophelia pertusa habitats along the continental slope, at depths ranging from 300 to 1,000 meters. The chapters are authored by several scientists from the U.S. Geological Survey, National Oceanic and Atmospheric Administration, University of North Carolina Wilmington, and Florida State University who examined the community ecology (from microbes to fishes), deep-sea coral age, growth, and reproduction, and population connectivity of deep-sea corals and inhabitants. Data from these studies are presented in the chapters and appendixes of the report as well as in journal publications. This study was conducted by the Ecosystems Mission Area of the U.S. Geological Survey to meet information needs identified by the Bureau of Ocean Energy Management.

Permafrost Organic Carbon Mobilization From the Watershed to the Colville River Delta: Evidence From 14C Ramped Pyrolysis and Lignin Biomarkers - Zhang, Xiaowen; Bianchi, Thomas S.; Cui, Xingqian; Rosenheim, Brad E.; Ping, Chien‐Lu; Hanna, Andrea J. M.; Kanevskiy, Mikhail; Schreiner, Kathryn M.; Allison, Mead A. (Geophysical Research Letters, 2017)
The deposition of terrestrial‐derived permafrost particulate organic carbon (POC) has been recorded in major Arctic river deltas. However, associated transport pathways of permafrost POC from the watershed to the coast have not been well constrained. Here we utilized a combination of ramped pyrolysis‐oxidation radiocarbon analysis (RPO 14C) along with lignin biomarkers, to track the linkages between soils and river and delta sediments. Surface and deep soils showed distinct RPO thermographs which may be related to degradation and organo‐mineral interaction. Soil material in the bed load of the river channel was mostly derived from deep old permafrost. Both surface and deep soils were transported and deposited to the coast. Hydrodynamic sorting and barrier island protection played important roles in terrestrial‐derived permafrost POC deposition near the coast. On a large scale, ice processes (e.g., ice gauging and strudel scour) and ocean currents controlled the transport and distribution of permafrost POC on the Beaufort Shelf.
Keywords: Arctic; carbon cycling; Colville River; Lignin; permafrost; pyrolysis

Pleistocene iceberg dynamics on the west Svalbard margin: Evidence from bathymetric and sub-bottom profiler data - Fang Zhao; Timothy A. Minshull; Anya J. Crocker; Julian A. Dowdeswell; Shiguo Wu; Simon M. Soryal (Quaternary Science Reviews, 2017)
Abstract Large icebergs leave evidence of their drift via ploughing of the seabed, thereby providing a geological record of episodes of calving from thick ice sheets. We interpret large-scale curvilinear depressions on the western Svalbard margin as ploughmarks produced by the keels of icebergs that grounded on the seafloor as they drifted through this area. Iceberg ploughmarks were identified at modern water depths between 300 m and 1000 m and in two distinct stratigraphic units. Combining data from sediment cores with seismic stratigraphy from sub-bottom profiler data suggests that the ploughmarks developed in two phases: (1) during Marine Isotope Stage (MIS) 6; and (2) during \{MIS\} 2, indicating the presence of large drifting icebergs on the western Svalbard margin during both the Late Saalian and Late Weichselian glaciations. Sediment-core data along the western Svalbard margin indicate a sharp increase in mass-transported sediments dated at 23.7 ± 0.2 ka, consistent with the \{MIS\} 2 age of the younger iceberg-ploughed surface. The ploughmarks are oriented in two main directions: SW-NE and S-N. S-N oriented ploughmarks, which shallow to the north, indicate iceberg drift from the south with a SW–NE component marking the zone of splitting of the West Spitsbergen Current (WSC) into the Yermak Slope Current (YSC) and North Spitsbergen Current (NSC). Large \{MIS\} 6 and \{MIS\} 2 icebergs most likely had an Arctic Ocean source. We suggest that these icebergs probably left the Arctic Ocean southward through Fram Strait and circulated within the Norwegian-Greenland Sea before being transported northwards along the Svalbard margin by the WSC. An additional likely source of icebergs to the western Svalbard margin during \{MIS\} 2 was the ice-sheet terminating in the western Barents Sea, from which icebergs drifted northward.
Keywords: Pleistocene

Proceedings of the International Ocean Discovery ProgramExpedition 357 methods - Früh-Green, G.L.; Orcutt, B.N.; Green, S.L.; Cotterill, C.; Morgan, S.; Akizawa, N.; Bayrakci, G.; Behrmann, J.-H.; Boschi, C.; Brazleton, W.J.; Cannat, M.; Dunkel, K.G.; et al. (International Ocean Discovery Program, 2017)

Reconstructing Common Era relative sea-level change on the Gulf Coast of Florida - Gerlach, Matthew J.; Engelhart, Simon E.; Kemp, Andrew C.; Moyer, Ryan P.; Smoak, Joseph M.; Bernhardt, Christopher E.; Cahill, Niamh (Marine Geology, 2017)
To address a paucity of Common Era data in the Gulf of Mexico, we reconstructed ~ 1.1 m of relative sea-level (RSL) rise over the past ~ 2000 years at Little Manatee River (Gulf Coast of Florida, USA). We applied a regional-scale foraminiferal transfer function to fossil assemblages preserved in a core of salt-marsh peat and organic silt that was dated using radiocarbon and recognition of pollution, 137Cs and pollen chronohorizons. Our proxy reconstruction was combined with tide-gauge data from four nearby sites spanning 1913–2014 CE. Application of an Errors-in-Variables Integrated Gaussian Process (EIV-IGP) model to the combined proxy and instrumental dataset demonstrates that RSL fell from ~ 350 to 100 BCE, before rising continuously to present. This initial RSL fall was likely the result of local-scale processes (e.g., silting up of a tidal flat or shallow sub-tidal shoal) as salt-marsh development at the site began. Since ~ 0 CE, we consider the reconstruction to be representative of regional-scale RSL trends. We removed a linear rate of 0.3 mm/yr from the RSL record using the EIV-IGP model to estimate climate-driven sea-level trends and to facilitate comparison among sites. This analysis demonstrates that since ~ 0 CE sea level did not deviate significantly from zero until accelerating continuously from ~ 1500 CE to present. Sea level was rising at 1.33 mm/yr in 1900 CE and accelerated until 2014 CE when a rate of 2.02 mm/yr was attained, which is the fastest, century-scale trend in the ~ 2000-year record. Comparison to existing reconstructions from the Gulf coast of Louisiana and the Atlantic coast of northern Florida reveal similar sea-level histories at all three sites. We explored the influence of compaction and fluvial processes on our reconstruction and concluded that compaction was likely insignificant. Fluvial processes were also likely insignificant, but further proxy evidence is needed to fully test this hypothesis. Our results indicate that no significant Common Era sea-level changes took place on the Gulf and southeastern Atlantic U.S. coasts until the onset of modern sea-level rise in the late 19th century.

Records of continental slope sediment flow morphodynamic responses to gradient and active faulting from integrated AUV and ROV data, offshore Palos Verdes, southern California Borderland - Maier, Katherine L.; Brothers, Daniel S.; Paull, Charles K.; McGann, Mary; Caress, David W.; Conrad, James E. (Marine Geology, 2017)
Variations in seabed gradient are widely acknowledged to influence deep-water deposition, but are often difficult to measure in sufficient detail from both modern and ancient examples. On the continental slope offshore Los Angeles, California, autonomous underwater vehicle, remotely operated vehicle, and shipboard methods were used to collect a dense grid of high-resolution multibeam bathymetry, chirp sub-bottom profiles, and targeted sediment core samples that demonstrate the influence of seafloor gradient on sediment accumulation, depositional environment, grain size of deposits, and seafloor morphology. In this setting, restraining and releasing bends along the active right-lateral Palos Verdes Fault create and maintain variations in seafloor gradient. Holocene down-slope flows appear to have been generated by slope failure, primarily on the uppermost slope (~ 100–200 m water depth). Turbidity currents created a low relief (< 10 m) channel, up-slope migrating sediment waves (λ = ~ 100 m, h ≤ 2 m), and a series of depocenters that have accumulated up to 4 m of Holocene sediment. Sediment waves increase in wavelength and decrease in wave height with decreasing gradient. Integrated analysis of high-resolution datasets provides quantification of morphodynamic sensitivity to seafloor gradients acting throughout deep-water depositional systems. These results help to bridge gaps in scale between existing deep-sea and experimental datasets and may provide constraints for future numerical modeling studies.
Keywords: Deep-water channel; Gradient; Holocene; Sediment waves; Turbidite Fault

Relative sea-level trends in New York City during the past 1500 years - Kemp, Andrew C; Hill, Troy D; Vane, Christopher H; Cahill, Niamh; Orton, Philip M; Talke, Stefan A; Parnell, Andrew C; Sanborn, Kelsey; Hartig, Ellen K (The Holocene, 2017)
New York City (NYC) is threatened by 21st-century relative sea-level (RSL) rise because it will experience a trend that exceeds the global mean and has high concentrations of low-lying infrastructure and socioeconomic activity. To provide a long-term context for anticipated trends, we reconstructed RSL change during the past ~1500 years using a core of salt-marsh sediment from Pelham Bay in The Bronx. Foraminifera and bulk-sediment δ13C values were used as sea-level indicators. The history of sediment accumulation was established by radiocarbon dating and recognition of pollution and land-use trends of known age in down-core elemental, isotopic, and pollen profiles. The reconstruction was generated within a Bayesian hierarchical model to accommodate multiple proxies and to provide a unified statistical framework for quantifying uncertainty. We show that RSL in NYC rose by ~1.70 m since ~575 CE (including ~0.38 m since 1850 CE). The rate of RSL rise increased markedly at 1812–1913 CE from ~1.0 to ~2.5 mm/yr, which coincides with other reconstructions along the US Atlantic coast. We investigated the possible influence of tidal-range change in Long Island Sound on our reconstruction using a regional tidal model, and we demonstrate that this effect was likely small. However, future tidal-range change could exacerbate the impacts of RSL rise in communities bordering Long Island Sound. The current rate of RSL rise is the fastest that NYC has experienced for >1500 years, and its ongoing acceleration suggests that projections of 21st-century local RSL rise will be realized.
Keywords: Bayesian transfer function; carbon isotope; Foraminifera; Salt marsh; sedimentation; The Bronx

Seasonal variability in the source and composition of particulate matter in the depositional zone of Baltimore Canyon, U.S. Mid-Atlantic Bight - Prouty, N.G.; Mienis, F.; Campbell-Swarzenski, P.; Roark, E.B.; Davies, A.J.; Robertson, C.M.; Duineveld, G.; Ross, S.W.; Rhode, M.; Demopoulos, A.W.J. (Deep Sea Research Part I: Oceanographic Research Papers, 2017)
Submarine canyons are often hotspots of biomass due to enhanced productivity and funneling of organic matter of marine and terrestrial origin. However, most deep-sea canyons remain poorly studied in terms of their role as conduits of terrestrial and marine particles. A multi-tracer geochemical investigation of particles collected yearlong by a sediment trap in Baltimore Canyon on the US Mid-Atlantic Bight (MAB) revealed temporal variability in source, transport, and fate of particulate matter. Both organic biomarker composition (sterol and n-alkanes) and bulk characteristics (δ13C, Δ14C, Chl-a) suggest that while on average the annual contribution of terrestrial and marine organic matter sources are similar, 42% and 52% respectively, marine sources dominate. Elevated Chlorophyll-a and sterol concentrations during the spring sampling period highlight a seasonal influx of relatively fresh phytodetritus. In addition, the contemporaneous increase in the particle reactive micronutrients cadmium (Cd) and molybdenum (Mo) in the spring suggest increased scavenging, aggregation, and sinking of phytodetrital biomass in response to enhanced surface production within the nutricline. While tidally driven currents within the canyon resuspend sediment between 200 and 600 m, resulting in the formation of a nepheloid layer rich in lithogenic material, near-bed sediment remobilization in the canyon depositional zone was minimal. Instead, vertical transport and lateral transport across the continental margin were the dominant processes driving seasonal input of particulate matter. In turn, seasonal variability in deposited particulate organic matter is likely linked to benthic faunal composition and ecosystem scale carbon cycling.
Keywords: Deep-sea ecosystems; Geochemical analyses; organic matter; sediment trap; Submarine canyons

Siberian Arctic black carbon sources constrained by model and observation - Winiger, Patrik; Andersson, August; Eckhardt, Sabine; Stohl, Andreas; Semiletov, Igor P.; Dudarev, Oleg V.; Charkin, Alexander; Shakhova, Natalia; Klimont, Zbigniew; Heyes, Chris; Gustafsson, Örjan (Proceedings of the National Academy of Sciences, 2017)
Black carbon (BC) in haze and deposited on snow and ice can have strong effects on the radiative balance of the Arctic. There is a geographic bias in Arctic BC studies toward the Atlantic sector, with lack of observational constraints for the extensive Russian Siberian Arctic, spanning nearly half of the circum-Arctic. Here, 2 y of observations at Tiksi (East Siberian Arctic) establish a strong seasonality in both BC concentrations (8 ng⋅m−3 to 302 ng⋅m−3) and dual-isotope–constrained sources (19 to 73% contribution from biomass burning). Comparisons between observations and a dispersion model, coupled to an anthropogenic emissions inventory and a fire emissions inventory, give mixed results. In the European Arctic, this model has proven to simulate BC concentrations and source contributions well. However, the model is less successful in reproducing BC concentrations and sources for the Russian Arctic. Using a Bayesian approach, we show that, in contrast to earlier studies, contributions from gas flaring (6%), power plants (9%), and open fires (12%) are relatively small, with the major sources instead being domestic (35%) and transport (38%). The observation-based evaluation of reported emissions identifies errors in spatial allocation of BC sources in the inventory and highlights the importance of improving emission distribution and source attribution, to develop reliable mitigation strategies for efficient reduction of BC impact on the Russian Arctic, one of the fastest-warming regions on Earth.
Keywords: Arctic haze; atmospheric transport modeling; carbon isotopes; Climate change; emission inventory

Subduction zone slip variability during the last millennium, south-central Chile - Dura, Tina; Horton, Benjamin P.; Cisternas, Marco; Ely, Lisa L.; Hong, Isabel; Nelson, Alan R.; Wesson, Robert L.; Pilarczyk, Jessica E.; Parnell, Andrew C.; Nikitina, Daria (Quaternary Science Reviews, 2017)
The Arauco Peninsula (37°-38°S) in south-central Chile has been proposed as a possible barrier to the along-strike propagation of megathrust ruptures, separating historical earthquakes to the south (1960 AD 1837, 1737, and 1575) and north (2010 AD, 1835, 1751, 1657, and 1570) of the peninsula. However, the 2010 (Mw 8.8) earthquake propagated into the Arauco Peninsula, re-rupturing part of the megathrust that had ruptured only 50 years earlier during the largest subduction zone earthquake in the instrumental record (Mw 9.5). To better understand long-term slip variability in the Arauco Peninsula region, we analyzed four coastal sedimentary sections from two sites (Tirúa, 38.3°S and Quidico, 38.1°S) located within the overlap of the 2010 and 1960 ruptures to reconstruct a ∼600-year record of coseismic land-level change and tsunami inundation. Stratigraphic, lithologic, and diatom results show variable coseismic land-level change coincident with tsunami inundation of the Tirúa and Quidico marshes that is consistent with regional historical accounts of coseismic subsidence during earthquakes along the Valdivia portion of the subduction zone (1960 AD and 1575) and coseismic uplift during earthquakes along the Maule portion of the subduction zone (2010 AD, 1835, 1751). In addition, we document variable coseismic land-level change associated with three new prehistoric earthquakes and accompanying tsunamis in 1470–1570 AD, 1425–1455, and 270–410. The mixed record of coseismic subsidence and uplift that we document illustrates the variability of down-dip and lateral slip distribution at the overlap of the 2010 and 1960 ruptures, showing that ruptures have repeatedly propagated into, but not through the Arauco Peninsula and suggesting the area has persisted as a long-term impediment to slip through at least seven of the last megathrust earthquakes (∼600 years).
Keywords: Coastal hazards; Coastal paleoseismology; Diatom paleoecology; Prehistoric earthquakes; Subduction zone segmentation; Tsunami Deposits

Tropical Pacific climate variability over the last 6000 years as recorded in Bainbridge Crater Lake, Galápagos - Thompson, Diane M.; Conroy, Jessica L.; Collins, Aaron; Hlohowskyj, Stephan R.; Overpeck, Jonathan T.; Riedinger-Whitmore, Melanie; Cole, Julia E.; Bush, Mark B.; Whitney, H.; Corley, Timothy L.; Kannan, Miriam Steinitz (Paleoceanography, 2017)
Finely laminated sediments within Bainbridge Crater Lake, Galápagos, provide a record of El Niño–Southern Oscillation (ENSO) events over the Holocene. Despite the importance of this sediment record, hypotheses for how climate variability is preserved in the lake sediments have not been tested. Here we present results of long‐term monitoring of the local climate and limnology and a revised interpretation of the sediment record. Brown‐green, organic‐rich, siliciclastic laminae reflect warm, wet conditions typical of El Niño events, whereas carbonate and gypsum precipitate during cool, dry La Niña events and persistent dry periods, respectively. Applying this new interpretation, we find that ENSO events of both phases were generally less frequent during the mid‐Holocene (~6100–4000 calendar years B.P.) relative to the last ~1500 calendar years. Abundant carbonate laminations between 3500 and 3000 calendar years B.P. imply that conditions in the Galápagos region were cool and dry during this period when the tropical Pacific E‐W sea surface temperature (SST) gradient likely strengthened. The frequency of El Niño and La Niña events then intensified dramatically around 1750–2000 calendar years B.P., consistent with a weaker SST gradient and an increased frequency of ENSO events in other regional records. This strong interannual variability persisted until ~700 calendar years B.P., when ENSO‐related variability at the lake decreased as the SST gradient strengthened. Persistent, dry conditions then dominated between 300 and 50 calendar years B.P. (A.D. 1650–1900, ± ~100 years), whereas wetter conditions and frequent El Niño events dominated in the most recent century.
Keywords: Climate variability; El Niño–Southern Oscillation(ENSO); Galápagos archipelago; mid‐Holocene; monitoring; tropical Pacific Ocean

Utility of salt-marsh foraminifera, testate amoebae and bulk-sediment δ13C values as sea-level indicators in Newfoundland, Canada - Kemp, Andrew C.; Wright, Alexander J.; Barnett, Robert L.; Hawkes, Andrea D.; Charman, Dan J.; Sameshima, Colby; King, Alexandra N.; Mooney, Hailey C.; Edwards, Robin J.; Horton, Benjamin P.; van de Plassche, Orson (Marine Micropaleontology, 2017)
We investigated the utility of foraminifera, testate amoebae and bulk-sediment δ13C measurements for reconstructing Holocene relative sea level from sequences of salt-marsh sediment in Newfoundland, Canada. Modern, surface sediment was collected along transects from low to supra-tidal elevations in eastern (at Placentia) and western (at Hynes Brook and Big River) Newfoundland. Consistent with previous work, low-diversity assemblages of foraminifera display an almost binary division into a higher salt-marsh assemblage dominated by Jadammina macrescens and Balticammina pseudomacrescens and a lower salt-marsh assemblage comprised of Miliammina fusca. This pattern and composition resembles those identified at other high latitude sites with cool climates and confirms that foraminifera are sea-level indicators. The lowest occurrence of testate amoebae was at approximately mean higher high water. The composition of high salt-marsh testate amoebae assemblages (Centropyxis cassis type, Trinema spp., Tracheleuglypha dentata type, and Euglypha spp.) in Newfoundland was similar to elsewhere in the North Atlantic, but preservation bias favors removal of species with idiosomic tests over those with xenosomic tests. The mixed high salt-marsh plant community in Newfoundland results in bulk surface-sediment δ13C values that are typical of C3 plants, making them indistinguishable from freshwater sediment. Therefore we propose that the utility of this proxy for reconstructing RSL in eastern North America is restricted to the coastline between Chesapeake Bay and southern Nova Scotia. Using a simple, multi-proxy approach to establish that samples in three radiocarbon-dated sediment cores formed between the lowest occurrence of testate amoebae and the highest occurrence of foraminifera, we generated three example late Holocene sea-level index points at Hynes Brook.

Vulnerability of Coral Reefs to Bioerosion From Land‐Based Sources of Pollution - Prouty, Nancy G.; Cohen, Anne; Yates, Kimberly K.; Storlazzi, Curt D.; Swarzenski, Peter W.; White, Darla (Journal of Geophysical Research: Oceans, 2017)
Ocean acidification (OA), the gradual decline in ocean pH and [ urn:x-wiley:21699275:media:jgrc22505:jgrc22505-math-0001] caused by rising levels of atmospheric CO2, poses a significant threat to coral reef ecosystems, depressing rates of calcium carbonate (CaCO3) production, and enhancing rates of bioerosion and dissolution. As ocean pH and [ urn:x-wiley:21699275:media:jgrc22505:jgrc22505-math-0002] decline globally, there is increasing emphasis on managing local stressors that can exacerbate the vulnerability of coral reefs to the effects of OA. We show that sustained, nutrient rich, lower pH submarine groundwater discharging onto nearshore coral reefs off west Maui lowers the pH of seawater and exposes corals to nitrate concentrations 50 times higher than ambient. Rates of coral calcification are substantially decreased, and rates of bioerosion are orders of magnitude higher than those observed in coral cores collected in the Pacific under equivalent low pH conditions but living in oligotrophic waters. Heavier coral nitrogen isotope (δ15N) values pinpoint not only site‐specific eutrophication, but also a sewage nitrogen source enriched in 15N. Our results show that eutrophication of reef seawater by land‐based sources of pollution can magnify the effects of OA through nutrient driven‐bioerosion. These conditions could contribute to the collapse of coastal coral reef ecosystems sooner than current projections predict based only on ocean acidification.
Keywords: aragonite saturation; bioerosion; coral reefs; nutrients; submarine groundwater; Wastewater

What on Earth Have We Been Burning? Deciphering Sedimentary Records of Pyrogenic CarbonWhat on Earth Have We Been Burning? Deciphering Sedimentary Records of Pyrogenic Carbon - Hanke, Ulrich M.; Reddy, Christopher M.; Braun, Ana L. L.; Coppola, Alysha I.; Haghipour, Negar; McIntyre, Cameron P.; Wacker, Lukas; Xu, Li; McNichol, Ann P.; Abiven, Samuel; Schmidt, Michael W. I.; Eglinton, Timothy I. (Environmental Science & Technology, 2017)
Humans have interacted with fire for thousands of years, yet the utilization of fossil fuels marked the beginning of a new era. Ubiquitous in the environment, pyrogenic carbon (PyC) arises from incomplete combustion of biomass and fossil fuels, forming a continuum of condensed aromatic structures. Here, we develop and evaluate 14C records for two complementary PyC molecular markers, benzene polycarboxylic acids (BPCAs) and polycyclic aromatic hydrocarbons (PAHs), preserved in aquatic sediments from a suburban and a remote catchment in the United States (U.S.) from the mid-1700s to 1998. Results show that the majority of PyC stems from local sources and is transferred to aquatic sedimentary archives on subdecadal to millennial time scales. Whereas a small portion stems from near-contemporaneous production and sedimentation, the majority of PyC (∼90%) experiences delayed transmission due to “preaging” on millennial time scales in catchment soils prior to its ultimate deposition. BPCAs (soot) and PAHs (precursors of soot) trace fossil fuel-derived PyC. Both markers parallel historical records of the consumption of fossil fuels in the U.S., yet never account for more than 19% total PyC. This study demonstrates that isotopic characterization of multiple tracers is necessary to constrain histories and inventories of PyC and that sequestration of PyC can markedly lag its production.

10Be dating reveals early-middle Holocene age of the Drygalski Moraines in central West Greenland - Sandra L. Cronauer; Jason P. Briner; Samuel E. Kelley; Susan R.H. Zimmerman; Mathieu Morlighem (Quaternary Science Reviews, 2016)
Abstract We reconstruct the history of the Greenland Ice Sheet margin on the Nuussuaq Peninsula in central West Greenland through the Holocene using lake sediment analysis and cosmogenic 10Be exposure dating of the prominent Drygalski Moraines. Erratics perched on bedrock outboard of the Drygalski Moraines constrain local deglaciation to ∼9.9 ± 0.6 ka (n = 2). Three Drygalski Moraine crests yield mean 10Be ages of 8.6 ± 0.4 ka (n = 2), 8.5 ± 0.2 ka (n = 3), and 7.6 ± 0.1 ka (n = 2) from outer to inner. Perched erratics between the inner two moraines average 7.8 ± 0.1 ka (n = 2) and are consistent with the moraine ages. Sediments from a proglacial lake with a catchment area extending an estimated 2 km beneath (inland of) the present ice sheet terminus constrain an ice sheet minimum extent from 5.4 ka to 0.6 ka. The moraine chronology paired with the lake sediment stratigraphy reveals that the ice margin likely remained within ∼2 km of its present position from ∼9.9 to 5.4 ka. This unexpected early Holocene stability, preceded by rapid ice retreat and followed by minimum ice extent between ∼5.4 and 0.6 ka, contrasts with many records of early Holocene warmth and the Northern Hemisphere summer insolation maximum. We suggest ice margin stability may instead be tied to adjacent ocean temperatures, which reached an optimum in the middle Holocene.
Special Issue: \{PAST\} Gateways (Palaeo-Arctic Spatial and Temporal Gateways)
Keywords: Holocene

The AD 1755 tsunami deposits onshore and offshore of Algarve (south Portugal): Sediment transport interpretations based on the study of Foraminifera assemblages - Maria Quintela; Pedro J.M. Costa; Francisco Fatela; Teresa Drago; Natalia Hoska; César Andrade; Maria C. Freitas (Quaternary International, 2016)
Abstract Tsunamis are amongst the most catastrophic natural hazards affecting worldwide coastal areas. Their impacts are recorded in the geological archives and its study provides crucial insights into the dynamics and intensity of these events. The accurate establishment of return periods can also be derived using sedimentological data. Onshore tsunami deposits have been extensively described over recent years through the application of a wide range of sedimentological proxies, including micropalaeontological analysis. In this work, the identification of palaeotsunami evidence, in both the onshore and offshore sedimentary record of south Portugal, was performed, relying mostly on the study of Foraminifera assemblages. Three onshore trenches and one offshore core were analyzed and imprints of the \{AD\} 1755 tsunami were observed based in the identification of allochthonous foraminiferal species, increase in the number of broken/abraded tests and its correlation with coarser mean grain size. This was possible after micropalaeontological environmental characterization of both low-energy onshore and offshore present-day sedimentation regimes. In the onshore record, three distinct sediment transport phases were differentiated within the tsunamigenic unit. The basal phase portraying the initial inundation represented by the dominance of marine Foraminifera species in a highly diverse assemblage. The higher energetic character of this phase was also reflected in the identification of the highest number of broken/abraded tests. The intermediate phase reflects an unspecified number of inundation and backwash pulses that were recognized based in the well-balanced presence of estuarine (brackish) and marine species, the sharp decrease in the diversity index and in the number of broken/abraded tests. The final phase recorded in the tsunamigenic unit registers the imprint of the last relevant backwash which was identified based on the dominance of estuarine (brackish) fauna. The overlying unit is dominated by tidal marsh species, demonstrating the start of the coastal system recovery phase. In the offshore record, it was possible to identify 2 distinct historical tsunami events (AD 1755 and \{AD\} 1969). This was achieved through the identification of significant increases in coastal Foraminifera species coupled with the presence of coarser layers. This interpretation was sustained by indirect age-estimation methods (radiocarbon and 210Pb) that ascribed compatible ages to the historical tsunami events. The results obtained in this study stress the relevance and innovative character of this onshore and offshore multiproxy approach in the recognition and understanding of tsunami events.
QuicklakeH Special Issue: Rapidly changing large lakes and human response
Keywords: Portugal

Age of the Mt. Ortles ice cores, the Tyrolean Iceman and glaciation of the highest summit of South Tyrol since the Northern Hemisphere Climatic Optimum - Gabrielli, Paolo; Barbante, Carlo; Bertagna, Giuliano; ó, Michele; Binder, Daniel; Carton, Alberto; Carturan, Luca; Cazorzi, Federico; Cozzi, Giulio; Dalla Fontana, Giancarlo; Davis, Mary; De Blasi, Fabrizio; et al. (The Cryosphere, 2016)
In 2011 four ice cores were extracted from the summit of Alto dell’Ortles (3859 m), the highest glacier of South Tyrol in the Italian Alps. This drilling site is located only 37 km southwest from where the Tyrolean Iceman, ∼5.3 kyrs old, was discovered emerging from the ablating ice field of Tisenjoch (3210 m, near the Italian–Austrian border) in 1991. The excellent preservation of this mummy suggested that the Tyrolean Iceman was continuously embedded in prehistoric ice and that additional ancient ice was likely preserved elsewhere in South Tyrol. Dating of the ice cores from Alto dell’Ortles based on 210Pb, tritium, beta activity and 14C determinations, combined with an empirical model (COPRA), provides evidence for a chronologically ordered ice stratigraphy from the modern glacier surface down to the bottom ice layers with an age of ∼7 kyrs, which confirms the hypothesis. Our results indicate that the drilling site has continuously been glaciated on frozen bedrock since ∼7 kyrs BP. Absence of older ice on the highest glacier of South Tyrol is consistent with the removal of basal ice from bedrock during the Northern Hemisphere Climatic Optimum (6–9 kyrs BP), the warmest interval in the European Alps during the Holocene. Borehole inclinometric measurements of the current glacier flow combined with surface ground penetration radar (GPR) measurements indicate that, due to the sustained atmospheric warming since the 1980s, an acceleration of the glacier Alto dell’Ortles flow has just recently begun. Given the stratigraphic chronological continuity of the Mt. Ortles cores over millennia, it can be argued that this behaviour has been unprecedented at this location since the Northern Hemisphere Climatic Optimum.

Biospheric and petrogenic organic carbon flux along southeast Alaska - Xingqian Cui; Thomas S. Bianchi; John M. Jaeger; Richard W. Smith (Earth and Planetary Science Letters, 2016)
Abstract Holocene fjords store ca. 11–12% of the total organic carbon (OC) buried in marine sediments with fjords along southeast (SE) Alaska possibly storing half of this \{OC\} (Smith et al., 2015). However, the respective burial of biospheric (OCbio) and petrogenic \{OC\} (OCpetro) remains poorly constrained, particularly across glaciated versus non-glaciated systems. Here, we use surface sediment samples to quantify the sources and burial of sedimentary \{OC\} along \{SE\} Alaska fjord-coastal systems, and conduct a latitudinal comparison across a suite of fjords and river-coastal systems with distinctive \{OC\} sources. Our results for \{SE\} Alaska show that surface sediments in northern fjords (north of Icy Strait) with headwater glaciers are dominated by OCpetro, in contrast to marine and terrestrially-derived fresh \{OC\} in non-glaciated southern fjords. Along the continental shelf of the Gulf of Alaska, terrestrial \{OC\} is exported from rivers. Using end-member mixing models, we determine that glaciated fjords have significantly higher burial rates of \{OCpetro\} ( ∼ 1.1 × 10 3   g \{OC\}   m − 2 yr − 1 ) than non-glaciated fjords and other coastal systems, making \{SE\} Alaska potentially the largest sink of \{OCpetro\} in North America. In contrast, non-glaciated fjords in \{SE\} Alaska are effective in burying marine \{OC\} (OCbio-mari) (13–82 g  \{OC\}   m − 2 yr − 1 ). Globally, \{OC\} in fjord sediments are comprised of a mixture of \{OCpetro\} and fresh OCbio, in contrast to the pre-aged \{OC\} from floodplain river-coastal systems. We find that there may be a general latitudinal trend in the role of fjords in processing OC, where high-latitude temperate glacial fjords (e.g., Yakutat Bay, \{SE\} Alaska) rebury \{OCpetro\} and non-glacial mid-latitude fjords (e.g., Doubtful Sound, Fiordland) sequester \{CO2\} from phytoplankton and/or temperate forests. Overall, we propose that fjords are effective in sequestering \{OCbio\} and re-burying OCpetro. Based on our study, we hypothesize that climate change will have a semi-predictable impact on fjords' \{OC\} cycling in the near future.
Keywords: glaciers

Bomb Radiocarbon and the Hawaiian Archipelago: Coral, Otoliths, and SeawaterAbstract - Andrews, Allen H; Siciliano, Daria; Potts, Donald C; DeMartini, Edward E; Covarrubias, Stephannie (Radiocarbon, 2016)
Corals of the Hawaiian Archipelago are well situated in the North Pacific Gyre (NPG) to record how bomb-produced radiocarbon has been sequestered and transported by the sea. While this signal can be traced accurately through time in reef-building corals and used to infer oceanographic processes and determine the ages of marine organisms, a comprehensive and validated record has been lacking for the Hawaiian Archipelago. In this study, a coral core from Kure Atoll in the northwestern Hawaiian Islands was used to create a high-resolution bomb 14C record for the years 1939–2002, and was then used with other 14C measurements in fish otoliths and seawater to explore differences and similarities in the bomb 14C signal throughout the Hawaiian Archipelago. The Kure Atoll sample series produced a well-defined bomb 14C curve that, with some exceptions, was similar to other coral 14C records from the Hawaiian Archipelago. Subtle differences in the coral 14C records across the region may be explained by the large-scale ocean circulation patterns and decadal cycles of the NPG. The most rapid increase of 14C, in the 1950s and 1960s, showed similar timing across the Hawaiian Archipelago and provides a robust basis for use of bomb 14C dating to obtain high-precision age determinations of marine organisms. Reference otoliths of juvenile fish demonstrated the use of the post-peak 14C decline period as a viable reference in the age validation of younger and more recently collected fishes, and effectively extended the utility of bomb 14C dating to the latest 30 yr.

Bomb-produced radiocarbon in the western tropical Pacific Ocean: Guam coral reveals operation-specific signals from the Pacific Proving Grounds - Andrews, A.H.; Asami, Ryuji; Iryu, Yasufumi; Kobayashi, Donald R.; Camacho, Frank (JOURNAL OF GEOPHYSICAL RESEARCH-OCEANS, 2016)
High-resolution radiocarbon (C-14) analyses on a coral core extracted from Guam, a western tropical Pacific island, revealed a series of early bomb-produced C-14 spikes. The typical marine bomb C-14 signal-phase lagged and attenuated relative to atmospheric records-is present in the coral and is consistent with other regional coral records. However, C-14 levels well above what can be attributed to air-sea diffusion alone punctuate this pattern. This anomaly was observed in other Indo-Pacific coral records, but the Guam record is unmatched in magnitude and temporal resolution. The Guam coral Delta C-14 record provided three spikes in 1954-1955, 1956-1957, and 1958-1959 that are superimposed on a normal C-14 record. Relative to mean prebomb levels, the first peak rises an incredible similar to 700 parts per thousand and remained elevated for similar to 1.2 years. A follow up assay with finer resolution increased the peak by similar to 300 parts per thousand. Subsequent spikes were less intense with a rise of similar to 35 and similar to 70 parts per thousand. Each can be linked to thermonuclear testing in the Pacific Proving Grounds at Bikini and Enewetak atolls in Operations Castle (1954), Redwing (1956), and Hardtack I (1958). These C-14 signals can be explained by vaporization of coral reef material in the nuclear fireball, coupled with neutron activation of atmospheric nitrogen (C-14 production), and subsequent absorption of (CO2)-C-14 to form particulate carbonates of close-in fallout. The lag time in reaching Guam and other coral records abroad was tied to ocean surface currents and modeling provided validation of C-14 arrival observations.

Complex coastal change in response to autogenic basin infilling: An example from a sub-tropical Holocene strandplain - Hein, Christopher J.; FitzGerald, Duncan M.; de Souza, Luis H. P.; Georgiou, Ioannis Y.; Buynevich, Ilya V.; Klein, Antonio H. da F.; de Menezes, ão Thadeu; Cleary, William J.; Scolaro, Thelma L. (Sedimentology, 2016)
Thick bay-fill sequences that often culminate in strandplain development serve as important sedimentary archives of land–ocean interaction, although distinguishing between internal and external forcings is an ongoing challenge. This study employs sediment cores, ground-penetrating radar surveys, radiocarbon dates, palaeogeographic reconstructions and hydrodynamic modelling to explore the role of autogenic processes – notably a reduction in wave energy in response to coastal embayment infilling – in coastal evolution and shoreline morphodynamics. Following a regional 2 to 4 m highstand at ca 5·8 ka, the 75 km2 Tijucas Strandplain in southern Brazil built from fluvial sediments deposited into a semi-enclosed bay. Holocene regressive deposits are underlain by fluvial sands and a Pleistocene transgressive–regressive sequence, and backed by a highstand barrier-island. The strandplain is immediately underlain by 5 to 16 m of seaward-thickening, fluvially derived, Holocene-age, basin-fill mud. Several trends are observed from the landward (oldest) to the seaward (youngest) sections of the strandplain: (i) the upper shoreface and foreshore become finer and thinner and shift from sand-dominated to mud-dominated; (ii) beachface slopes decrease from >11° to ca 7°; and (iii) progradation rates increase from 0·4 to 1·8 m yr−1. Hydrodynamic modelling demonstrates a correlation between progressive shoaling of Tijucas Bay driven by sea-level fall and sediment infilling and a decrease in onshore wave-energy transport from 18 to 4 kW m−1. The combination of allogenic (sediment supply, falling relative sea-level and geology) and autogenic (decrease in wave energy due to bay shoaling) processes drove the development of a regressive system with characteristics that are rare, if not unique, in the Holocene and rock records. These findings demonstrate the complexities in architecture styles of highstand and regressive systems tracts. Furthermore, this article highlights the diverse internal and external processes and feedbacks responsible for the development of these intricate marginal marine sedimentary systems.

Controls on the stratigraphic framework and paleoenvironmental change within a Holocene estuarine system: Pamlico Sound, North Carolina, USA - Nicholas Zaremba; David J. Mallinson; Eduardo Leorri; Stephen Culver; Stanley Riggs; Ryan Mulligan; Eric Horsman; Siddhartha Mitra (Marine Geology, 2016)
Abstract This study examines the Holocene stratigraphic record and paleoenvironmental evolution of a large estuarine system, at high temporal and spatial resolution, in the context of changing climate, sea level, and hydrodynamics. New data are used to examine two time periods of increased marine influence within Pamlico Sound in northeastern North Carolina interpreted to be the result of extensive barrier island segmentation synchronous with periods of rapid climate change during the late Holocene. The study reveals the controls on the stratigraphic development and the highly dynamic character of the coastal system in response to climate, and sea-level change as it interacts with paleotopography. These findings can be used to inform projections of future environmental changes. Estuarine waters occupied paleovalleys in the Pamlico Sound region as early as ca. 7500 cal \{BP\} and Pleistocene interfluves separated the paleovalleys from the Atlantic Ocean until ca. 5500 cal BP, when they were flooded by rising sealevel forming the broad, shallow Pamlico Sound. Initial barrier islands and shoals likely formed sometime between 5500 and 5000 cal BP, providing the geomorphic setting for continued estuarine conditions behind the barriers. At ca. 4000 cal BP, an increase in marine influence and sand content is detected in multiple cores, and is correlated to seismic data within the Pamlico Sound basin. This change is interpreted to be the result of increased segmentation of barrier islands (thus a greater number of inlets, or wider inlets), which is consistent with a rapid transgression seen in other areas of the U.S. east coast. The segmentation may have been partially facilitated by a rapid increase in lagoonal area and tidal prism by overtopping of interfluves. Greater barrier island continuity is evident from 3500 to 1200 cal BP, as indicated by muddy deposits with low brackish estuarine foraminiferal assemblages. At ca. 1200 cal BP, seismic, sedimentological and micropaleontological data suggest an increase in wave and current energy and marine influence throughout southeastern Pamlico Sound. These changes are interpreted to represent extensive segmentation of the barrier islands during the Medieval Climate Anomaly (MCA). Since ca. 500 cal BP, the Pamlico Sound system has returned to a more restricted state, as inlets have closed. Currently only three major inlets segment the Outer Banks, the barrier island system fronting Pamlico Sound, but warming climate and increasing rates of sea-level rise suggest that another episode of barrier island segmentation began about a half century ago and appears that it may extend into the near future.
Keywords: Coastal geology

Distribution, provenance and early diagenesis of major and trace metals in sediment cores from the Mandovi estuary, western India - A. Prajith; V. Purnachandra Rao; P. Chakraborty (Estuarine, Coastal and Shelf Science, 2016)
Abstract Major elements and trace metals were analyzed in four sediment cores recovered along a transect in the Mandovi estuary for their distribution, provenance and early diagenesis. The sediments were clayey silts in cores from the upper/lower estuary and sand-dominated in cores from the middle estuary/bay. Organic carbon (OC) content varied from 0.5 to 4%, with higher values in fine-grained sediments. The mean Fe and Mn contents of sediments from the upper/middle estuary were 3–5 times and 8–13 times, respectively higher than the reference sediment (RS) from the same estuary. The mean Fe and Mn contents of sediments from the lower estuary/bay were close to the RS. Strong inter-metal correlation among Ti, V, Cr and Zr in all the cores indicated their contribution from a common source, probably the laterites from hinterland. Trace metals were more enriched in fine-grained sediments than in sand-dominated sediments. Early diagenetic control on the redistribution of metal is evident in core sediments from the middle estuary to Bay. The distribution of Mo, U and Pb followed that of Fe and Mn in the upper estuary and \{OC\} in the lower estuary/bay. Our results indicated strong anthropogenic contribution of metals from ore deposits in the upper/middle estuary. The Mn and Cr contents of sediment in the upper/middle estuary and Fe in the middle estuary were highly enriched suggestive of ‘significant pollution signal’. More trace metals from the middle estuary were moderately enriched. Speciation studies showed Mn and Pb occurred abundantly in non-residual phases. High Mn content and its high percentage in exchangeable and reductive phases indicate that it was susceptible to be mobilized. However, Fe, Cu and Ni occurred abundantly in residual phases and less percentage of them were expected to be bio-available.
Keywords: Western India

Footprint of roman and modern mining activities in a sediment core from the southwestern Iberian Atlantic shelf - Mário Mil-Homens; Carlos Vale; Filipa Naughton; Pedro Brito; Teresa Drago; Bárbara Anes; Joana Raimundo; Sabine Schmidt; Miguel Caetano (Science of The Total Environment, 2016)
Abstract A 5-m long sediment core (VC2B), retrieved in the Southwestern Iberian Atlantic shelf, at 96 m water depth, was used to assess major changes in climate and human activities during the last 9.7 kyrs. Analytical measurements included sedimentological (mean grain size, and the contents of sand, silt and clay), geochemical (major, minor, trace and rare earth elements; REEs) and chronological (210Pb and 14C) parameters. Two episodes of increment of fine-grained particles, occurring at 3050 \{BCE\} and 1350 CE, suggest the retreat of the coast line to the present level and the beginning of a wetter phase associated with the “Little Ice Age”. The North American Shale Composite (NASC)-normalized REE-pattern detected in the shelf is similar to that found in the Guadiana estuarine sediments. The possibility of this estuary as a contributor to the sediment load deposited in the adjacent coastal zone was indicated. Trace elements were significantly correlated with Al until 1850 CE, pointing that grain-size rules its distribution in sediments. The depth variation of As, Cu and Pb enrichment factors relative to background values shows two periods of intense human activity that can be mainly linked to mining: (i) across the Roman Period, marked by low enrichments; and (ii) starting on the second half of the 19th century until nowadays with significantly increased enrichments, especially of Pb and Cu. In addition to As, Cu and Pb, this period is also marked by high enrichments of Hg and Zn. Despite the decrease/closure of sulphide massive deposits mining exploitation (e.g., São Domingos, Las Herrerias) during the second half of the 20th century, results showed ongoing input of Pb, Cu, As, Hg and Zn to coastal sediments. Thus, the legacy of contamination by these elements, mainly from leaching of slags and tailings, and remobilization/reworking of contaminated estuarine sediments, is still recorded in marine sediments.
Keywords: mining activities; Rare earth elements

Indus Basin sediment provenance constrained using garnet geochemistry - Anwar Alizai; Peter D. Clift; John Still (Journal of Asian Earth Sciences, 2016)
Abstract The chemical and mineralogical diversity of western Himalayan rivers is the result of each of them draining different tectonic and lithologic units, whose character is partly transferred to the sediments carried by those rivers. Garnet geochemistry was employed to discriminate provenance in the Indus River system. We characterized the geochemistry of garnet sediment grains from the modern Indus and all its major tributaries, as well as the related but ephemeral Ghaggar-Hakra River and dune sand from the Thar Desert. Garnet geochemistry displays a unique signature for the Himalayan rivers on the east of the Indus drainage compared to those in the western drainage. The trunk Indus remains distinct because of the dominant arc-type pyrope-garnet derived from Kohistan and the Karakoram. The Jhellum, which lies just east of the modern Indus has modest concentrations of arc-type pyrope garnets, which are more depleted in the other eastern tributaries. Their presence in the Jhellum reflects recycling of trunk Indus garnets through the Miocene Siwalik Group foreland sedimentary rocks. The Thar Desert dune sample contains significant numbers of grains similar to those in the trunk Indus, likely reworked by monsoon winds from the SW. Our data further indicate the presence of a Himalayan river channel east of the present Indus, close to the delta, in the Nara River valley during the middle Holocene. Sands from this channel cannot be distinguished from the Indus on the basis of their garnet geochemistry alone but we favour their sedimentation from an Indus channel rather than reworking of desert sands by another stream. The garnet geochemistry shows some potential as a provenance tool, but cannot be used alone to uniquely discriminate Indus Basin provenance.
Keywords: Provenance

Late Quaternary fingerprints of precession and sea level variation over the past 35 kyr as revealed by sea surface temperature and upwelling records from the Indian Ocean near southernmost Sumatra - Ziye Li; Xuefa Shi; Min-Te Chen; Houjie Wang; Shengfa Liu; Jian Xu; Haiyan Long; Rainer Arief Troa; Rina Zuraida; Eko Triarso (Quaternary International, 2016)
Abstract We report high-resolution paleoclimatic reconstructions using isotope, alkenone sea surface temperature (SST), productivity, and terrigenous proxy variations over the past 35 kyr from core SO184-10043 (07°18.57′S, 105°03.53′E) in the eastern tropical Indian Ocean offshore of southernmost (S) Sumatra. The core was retrieved at 2171 m water depth, from the monsoon driven seasonal upwelling area off southernmost Sumatra. Our paleoclimatic reconstructions show that an enhanced marine productivity was closely linked to strengthening of coastal upwelling during the increases of boreal summer insolation and associated southeastern (SE) monsoon strength, with pronounced semi-precession cycles (∼11 kyr). In contrast, our record of alkenone \{SSTs\} shows glacial to interglacial, a sea-level variation, but this fluctuates at dominant precession cycles (∼21 kyr). We also observed four \{SST\} “plateaus” with relatively warmer hydrographic stability in our records over the past 35 kyr: 32-27 ka, 24-20 ka, 17-12 ka, and 9-4 ka. The time scale of each plateau is ∼4-6 kyr. Our study indicates that since the last glacial maximum (LGM), the sea level rise has been responsible for the Sunda shelf flooding and the Indonesian Throughflow (ITF) from the South China Sea (SCS) to the eastern Indian Ocean, leaving a dominant fingerprint of a glacial to interglacial increase in \{SSTs\} since ∼9.5 ka We further argue that the a most recent centennial to millennial scale cooling at ∼3.5 ka observed in our \{SST\} record is a widespread event in the tropical Pacific, which has implications for advancing our understanding of the climate dynamics of the tropical oceans at these time scales.
Keywords: Quaternary

Methane emissions proportional to permafrost carbon thawed in Arctic lakes since the 1950s - Walter Anthony, Katey; Daanen, Ronald; Anthony, Peter; Schneider von Deimling, Thomas; Ping, Chien-Lu; Chanton, Jeffrey P.; Grosse, Guido (Nature Geoscience, 2016)
Permafrost thaw exposes previously frozen soil organic matter to microbial decomposition. This process generates methane and carbon dioxide, and thereby fuels a positive feedback process that leads to further warming and thaw1. Despite widespread permafrost degradation during the past ~40 years2, 3, 4, the degree to which permafrost thaw may be contributing to a feedback between warming and thaw in recent decades is not well understood. Radiocarbon evidence of modern emissions of ancient permafrost carbon is also sparse5. Here we combine radiocarbon dating of lake bubble trace-gas methane (113 measurements) and soil organic carbon (289 measurements) for lakes in Alaska, Canada, Sweden and Siberia with numerical modelling of thaw and remote sensing of thermokarst shore expansion. Methane emissions from thermokarst areas of lakes that have expanded over the past 60 years were directly proportional to the mass of soil carbon inputs to the lakes from the erosion of thawing permafrost. Radiocarbon dating indicates that methane age from lakes is nearly identical to the age of permafrost soil carbon thawing around them. Based on this evidence of landscape-scale permafrost carbon feedback, we estimate that 0.2 to 2.5 Pg permafrost carbon was released as methane and carbon dioxide in thermokarst expansion zones of pan-Arctic lakes during the past 60 years.
Keywords: Carbon cycle; Climate change; Cryospheric science

Micropaleontologic record of Pliocene and Quaternary paleoenvironments in the southern Albemarle Embayment, North Carolina, U.S.A - Stephen J. Culver; Kathleen M. Farrell; David J. Mallinson; Debra A. Willard; Benjamin P. Horton; Stanley R. Riggs; E. Robert Thieler; John F. Wehmiller; Peter R. Parham; Jessica Pierson Moore; Scott W. Snyder; Caroline Hillier (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract The Albemarle Embayment, a Cenozoic depositional basin on the Atlantic coast of the USA, is an ideal setting to understand the temporal and spatial variation of eustatic sea-level fluctuations, glacio-hydro-isostasy, tectonics, subsidence, environments and sedimentation patterns of a passive margin Quaternary section. A NE–SW transect of cores and seismic data in the southern Albemarle Embayment were analyzed using micropaleontologic (foraminifera, diatoms, pollen), sedimentologic, stratigraphic, and geochronologic data to reconstruct the paleoenvironmental evolution and paleoclimates in the nearly 90 m thick Quaternary section. The study area is a very low gradient Quaternary landscape that is cross-cut by several Pleistocene incised valleys; a Holocene barrier island complex forms its eastern margin. In the subsurface, the Albemarle Embayment is bordered to the north by the Norfolk Arch and to the south by the depositionally-constructed Cape Lookout High, which is positioned on the northern flank of the structural Carolina Platform. The Quaternary section overlies mid-Pliocene carbonates in three cores; the contact rises in elevation towards the Cape Lookout High. Fossils and sediment characteristics suggest a subtropical, shallow, high energy marine environment during the Pliocene. Overlying units include incomplete Pleistocene, clastic, transgressive-regressive (T-R) deposits. These have similar ages and stratigraphic signatures as the T-R cycles in the central and north-central Albemarle Embayment, although mid-Pleistocene deposits may be older in the southern region. The bulk of the early and mid-Pleistocene record consists of inner to mid-shelf sand and muddy sand. In contrast, late Pleistocene sands are of inner shelf origin, reflecting the infilling of the basin. Lowstand paleovalleys, with fluvial, wetland and estuarine fill, dissect the early, mid- and late Pleistocene marine units; their locations reflect antecedent topography. Holocene sediments were deposited in shoreface and barrier island environments. Quaternary foraminiferal assemblages in the southern Albemarle Embayment exhibit greater species richness than those in the central and north-central embayment reflecting the presence of a major biogeographic boundary at the same location as the modern biogeographic boundary at Cape Hatteras.
Keywords: Holocene

No iron fertilization in the equatorial Pacific Ocean during the last ice age - Costa, K. M.; McManus, J. F.; Anderson, R. F.; Ren, H.; Sigman, D. M.; Winckler, G.; Fleisher, M. Q.; Marcantonio, F.; Ravelo, A. C. (Nature, 2016)
The equatorial Pacific Ocean is one of the major high-nutrient, low-chlorophyll regions in the global ocean. In such regions, the consumption of the available macro-nutrients such as nitrate and phosphate is thought to be limited in part by the low abundance of the critical micro-nutrient iron1. Greater atmospheric dust deposition2 could have fertilized the equatorial Pacific with iron during the last ice age—the Last Glacial Period (LGP)—but the effect of increased ice-age dust fluxes on primary productivity in the equatorial Pacific remains uncertain3, 4, 5, 6. Here we present meridional transects of dust (derived from the 232Th proxy), phytoplankton productivity (using opal, 231Pa/230Th and excess Ba), and the degree of nitrate consumption (using foraminifera-bound δ15N) from six cores in the central equatorial Pacific for the Holocene (0–10,000 years ago) and the LGP (17,000–27,000 years ago). We find that, although dust deposition in the central equatorial Pacific was two to three times greater in the LGP than in the Holocene, productivity was the same or lower, and the degree of nitrate consumption was the same. These biogeochemical findings suggest that the relatively greater ice-age dust fluxes were not large enough to provide substantial iron fertilization to the central equatorial Pacific. This may have been because the absolute rate of dust deposition in the LGP (although greater than the Holocene rate) was very low. The lower productivity coupled with unchanged nitrate consumption suggests that the subsurface major nutrient concentrations were lower in the central equatorial Pacific during the LGP. As these nutrients are today dominantly sourced from the Subantarctic Zone of the Southern Ocean, we propose that the central equatorial Pacific data are consistent with more nutrient consumption in the Subantarctic Zone, possibly owing to iron fertilization as a result of higher absolute dust fluxes in this region7, 8. Thus, ice-age iron fertilization in the Subantarctic Zone would have ultimately worked to lower, not raise, equatorial Pacific productivity.
Keywords: Biogeochemistry; Palaeoceanography

Organic matter cycling across the sulfate-methane transition zone of the Santa Barbara Basin, California Borderland - Komada, Tomoko; Burdige, David J.; Li, Huan-Lei; Magen, édric; Chanton, Jeffrey P.; Cada, Abraham K. (Geochimica et Cosmochimica Acta, 2016)
Consumption of sulfate (SO42−) in the sulfate-methane transition zone (SMTZ) has often been considered to be due solely to anaerobic oxidation of methane (AOM). However, recent studies show SO42− fluxes into the SMTZ that exceed methane (CH4) fluxes, thereby challenging this conceptual model. Co-occurrence of organoclastic SO42− reduction (oSR) with AOM in the SMTZ has been hypothesized to be the cause for this flux imbalance, but conclusive evidence is lacking. To address this knowledge gap, we investigated organic matter cycling in the SMTZ of the organic-rich sediments of the Santa Barbara Basin, California Borderland, and examined the occurrence of oSR within this zone using bulk solute profiles and Δ14C and δ13C values of selected carbon pools. We also tested the hypothesis that the SMTZ acts as an oxidation front not just for CH4, but also for dissolved organic carbon (DOC) that is produced below the SMTZ and migrates upward. Mass balance calculations for the SMTZ based on reaction stoichiometry and Δ14C and δ13C values of associated carbon fluxes indicate that ∼35–45% of total SO42− reduction in the SMTZ occurs via oSR, with the remainder attributable to AOM. The δ13C value of net DOC production is distinct from that of the fraction of bulk POC undergoing degradation, suggesting that pore-water DOC represents a compositionally unique slice of the metabolizable POC pool. DOC diffusing upward at 450 cm is virtually free of 14C and contain low levels of short-chain organic acids. Radiocarbon mass balance shows that >30% of this pre-aged, and presumably refractory, DOC is removed from the pore waters within or immediately below the SMTZ. Although the SMTZ does not appear to be a major net DOC oxidation front, these results show that DOC dynamics provide unique insights into organic matter processing in these subsurface sediments.

Palaeoclimatic changes in Kveithola, Svalbard, during the Late Pleistocene deglaciation and Holocene: Evidences from microfossil and sedimentary records - Katia Carbonara; Karin Mezgec; Gabriella Varagona; Maria Elena Musco; Renata Giulia Lucchi; Giuliana Villa; Caterina Morigi; Romana Melis; Mauro Caffau (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract Climate changes are reflected in the Arctic ecosystem history over different timescales. We use a multi proxy-based approach for palaeoenvironmental and palaeoclimatic reconstructions, conducted on sediment cores, compared with summer insolation and Greenland ice core δ18O data in order to establish a framework for climate changes from Late Pleistocene to late Holocene. Our dataset includes the results compiled from a sediment core, collected on the middle slope of the Kveithola Trough Mouth Fan (South of Svalbard) during the \{CORIBAR\} cruise (2013). The studied core presents remarkable lithological and magnetic susceptibility similarities with cores recovered in the same area during the \{SVAIS\} (2007) and the OGS-EGLACOM cruise (2008), allowing the construction of the age model. The results indicate that during the last 14.5 cal ky \{BP\} advances and retreats of the Svalbard Barents Sea Ice Sheet were strictly linked to the interplay of Atlantic and Arctic water inflows to the study area. During the deglaciation, from the Last Glacial Maximum to the onset of the Holocene, the climate underwent a series of abrupt changes including the Bølling-Allerød warm interstadial and the Younger Dryas cold event. During the early Holocene, the investigated area was dominated by enhanced warm Atlantic water inflow, which was concomitant with summer insolation increase, characterizing the Holocene Thermal Maximum. Conversely, the late Holocene was governed by deteriorating climatic conditions, with predominant Arctic/Polar water inflow on the surface water masses off Western Svalbard, possibly associated with summer insolation decline due to orbital forcing.
Keywords: Clay minerals

Plankton biochronology for the last 772,000 years from the western South Atlantic Ocean - Felipe A.L. Toledo; Juliana P. Quadros; Edmundo Camillo Jr.; Ana Cláudia A. Santarosa; José-Abel Flores; Karen B. Costa (Marine Micropaleontology, 2016)
Abstract Calcareous microfossils have potential in the biostratigraphy of Pleistocene sediments and a clear relationship with paleoceanographic studies. Conversely, there are few quantitative biostratigraphic studies of chronologically-tuned events or sections in the western South Atlantic. In order to improve the stratigraphical framework for South Atlantic paleoceanographic studies, the present work attempts to review the last 772,000 years by carrying out a quantitative analysis of the calcareous nannofossil and planktonic foraminiferal assemblages by comparing them with a high resolution marine isotopic record (δ18O). This work is based on the analysis of two piston cores obtained from the continental slope of the Santos Basin in the Santos Drift, southeastern Brazilian Continental Margin. Twelve Pleistocene calcareous nannofossil events and twenty planktonic foraminifera events calibrated with oxygen isotopes and correlated with literature stratigraphies are discussed. This is the first calcareous plankton biochronology study for the last 772 kyr in the western South Atlantic Ocean. More studies in this region will help to establish a more precise biochronology for these calcareous microfossils. This study also presents six new biostratigraphic events of isotopically-caibrated planktonic foraminifera which can be used as markers in the western South Atlantic.
Keywords: Biochronology

Records of continental slope sediment flow morphodynamic responses to gradient and active faulting from integrated AUV and ROV data, offshore Palos Verdes, southern California Borderland - Katherine L. Maier; Daniel S. Brothers; Charles K. Paull; Mary McGann; David W. Caress; James E. Conrad (Marine Geology, 2016)
Abstract Variations in seabed gradient are widely acknowledged to influence deep-water deposition, but are often difficult to measure in sufficient detail from both modern and ancient examples. On the continental slope offshore Los Angeles, California, autonomous underwater vehicle, remotely operated vehicle, and shipboard methods were used to collect a dense grid of high-resolution multibeam bathymetry, chirp sub-bottom profiles, and targeted sediment core samples that demonstrate the influence of seafloor gradient on sediment accumulation, depositional environment, grain size of deposits, and seafloor morphology. In this setting, restraining and releasing bends along the active right-lateral Palos Verdes Fault create and maintain variations in seafloor gradient. Holocene down-slope flows appear to have been generated by slope failure, primarily on the uppermost slope (  100–200 m water depth). Turbidity currents created a low relief (< 10 m) channel, up-slope migrating sediment waves (λ =   100 m, h ≤ 2 m), and a series of depocenters that have accumulated up to 4 m of Holocene sediment. Sediment waves increase in wavelength and decrease in wave height with decreasing gradient. Integrated analysis of high-resolution datasets provides quantification of morphodynamic sensitivity to seafloor gradients acting throughout deep-water depositional systems. These results help to bridge gaps in scale between existing deep-sea and experimental datasets and may provide constraints for future numerical modeling studies.
Keywords: Fault

Relative sea-level change in northeastern Florida (USA) during the last ∼8.0 ka - Hawkes, Andrea D.; Kemp, Andrew C.; Donnelly, Jeffrey P.; Horton, Benjamin P.; Peltier, W. Richard; Cahill, Niamh; Hill, David F.; Ashe, Erica; Alexander, Clark R. (Quaternary Science Reviews, 2016)
An existing database of relative sea-level (RSL) reconstructions from the U.S. Atlantic coast lacked valid sea-level index points from Georgia and Florida. This region lies on the edge of the collapsing forebulge of the former Laurentide Ice Sheet making it an important location for understanding glacio-isostatic adjustment and the history of ice-sheet melt. To address the paucity of data, we reconstruct RSL in northeastern Florida (St. Marys) over the last ∼8.0 ka from samples of basal salt-marsh sediment that minimize the influence of compaction. The analogy between modern salt-marsh foraminifera and their fossil counterparts preserved in the sedimentary record was used to estimate paleomarsh surface elevation. Sample ages were determined by radiocarbon dating of identifiable and in-situ plant macrofossils. This approach yielded 25 new sea-level index points that constrain a ∼5.7 m rise in RSL during the last ∼8.0 ka. The record shows that no highstand in sea level occurred in this region over the period of the reconstruction. We compared the new reconstruction to Earth-ice models ICE 6G-C VM5a and ICE 6G-C VM6. There is good fit in the later part of the Holocene with VM5a and for a brief time in the earlier Holocene with VM6. However, there are discrepancies in model-reconstruction fit in the early to mid Holocene in northeastern Florida and elsewhere along the Atlantic coast at locations with early Holocene RSL reconstructions. The most pronounced feature of the new reconstruction is a slow down in the rate of RSL rise from approximately 5.0 to 3.0 ka. This trend may reflect a significant contribution from local-scale processes such as tidal-range change and/or change in base flow of the St. Marys River in response to paleoclimate changes. However, the spatial expression (local vs. regional) of this slow down is undetermined and corroborative records are needed to establish its geographical extent.
Keywords: Foraminifera; Georgia; Holocene; Salt marsh; St. Marys River

Seasonal variability of stable carbon isotopes (δ13CDIC) in the Skagerrak and the Baltic Sea: Distinguishing between mixing and biological productivity - Helena L. Filipsson; Daniel C. McCorkle; Andreas Mackensen; Joan M. Bernhard; Lars S. Andersson; Lars-Johan Naustvoll; Angela M. Caballero-Alfonso; Kjell Nordberg; Didrik S. Danielssen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract We documented the annual cycle of the carbon isotopic composition of dissolved inorganic carbon (δ13CDIC) in the water columns of the Skagerrak and Baltic Sea to obtain an increased understanding of the processes involved controlling the carbon isotopic distribution in shelf seas. The lowest δ13CDIC values (− 4.9‰) were found in the low-oxygen, brackish Baltic bottom water whereas the highest values (+ 1.8‰) were observed in the surface water of the Skagerrak during late summer. Photosynthesis drove the high δ13CDIC values (between 1.0 and 1.8‰) noted in the surface waters of both the Skagerrak and the Baltic. The δ13CDIC values below the halocline in the Baltic reflect mixing of brackish water and the more saline water from the Skagerrak, and foremost organic matter remineralization processes that release significant amounts of low-δ13C CO2. Similarly, in the stagnant fjord basins, little deep water exchange and the degradation of terrestrial and marine organic matter set the δ13C composition. Deep-water renewal in the fjord basins resulted in rapid increases of the δ13CDIC on the order of 1‰, whereas remineralization processes caused a decrease in δ13CDIC of 0.1–0.3‰ per month depending on location. The combined effects of water mixing and remineralization processes (estimated using apparent oxygen utilization (AOU) values) yielded the expression: δ13CDIC = 0.032 ∗ S − 0.01 ∗ \{AOU\} − 0.12 for the Baltic – Skagerrak region at water depths below the halocline.
Keywords: Time-series

Sedimentation, stratigraphy and physical properties of sediment on the Juan de Fuca Ridge - K.M. Costa; J.F. McManus; B. Boulahanis; S.M. Carbotte; G. Winckler; P.J. Huybers; C.H. Langmuir (Marine Geology, 2016)
Abstract Sedimentation near mid-ocean ridges may differ from pelagic sedimentation due to the influence of the ridges' rough topography on sediment deposition and transport. This study explores whether the near-ridge environment responds to glacial-interglacial changes in climate and oceanography. New benthic δ18O, radiocarbon, multi-sensor track, and physical property (sedimentation rates, density, magnetic susceptibility) data for seven cores on the Juan de Fuca Ridge provide multiple records covering the past 700,000 years of oceanographic history of the Northeast Pacific Ocean. Systematic variations in sediment density and coarse fraction correspond to glacial-interglacial cycles identified in benthic δ18O, and these observations may provide a framework for mapping the δ18O chronostratigraphy via sediment density to other locations on the Juan de Fuca Ridge and beyond. Sedimentation rates generally range from 0.5 to 3 cm/kyr, with background pelagic sedimentation rates close to 1 cm/kyr. Variability in sedimentation rates close to the ridge likely reflects remobilization of sediment caused by the high relief of the ridge bathymetry. Sedimentation patterns primarily reflect divergence of sedimentation rates with distance from the ridge axis and glacial-interglacial variation in sedimentation that may reflect carbonate preservation cycles as well as preferential remobilization of fine material.
Keywords: Oxygen isotope stratigraphy

Stability of peatland carbon to rising temperatures - Wilson, R. M.; Hopple, A. M.; Tfaily, M. M.; Sebestyen, S. D.; Schadt, C. W.; Pfeifer-Meister, L.; Medvedeff, C.; McFarlane, K. J.; Kostka, J. E.; Kolton, M.; Kolka, R.K.; Kluber, L. A.; et al. (Nature Communications, 2016)
Peatlands contain one-third of soil carbon (C), mostly buried in deep, saturated anoxic zones (catotelm). The response of catotelm C to climate forcing is uncertain, because prior experiments have focused on surface warming. We show that deep peat heating of a 2 m-thick peat column results in an exponential increase in CH4 emissions. However, this response is due solely to surface processes and not degradation of catotelm peat. Incubations show that only the top 20–30 cm of peat from experimental plots have higher CH4 production rates at elevated temperatures. Radiocarbon analyses demonstrate that CH4 and CO2 are produced primarily from decomposition of surface-derived modern photosynthate, not catotelm C. There are no differences in microbial abundances, dissolved organic matter concentrations or degradative enzyme activities among treatments. These results suggest that although surface peat will respond to increasing temperature, the large reservoir of catotelm C is stable under current anoxic conditions.

Tracing subarctic Pacific water masses with benthic foraminiferal stable isotopes during the \{LGM\} and late Pleistocene - Mea S. Cook; A. Christina Ravelo; Alan Mix; Ian M. Nesbitt; Nari V. Miller (Deep Sea Research Part II: Topical Studies in Oceanography, 2016)
Abstract As the largest ocean basin, the Pacific helps to set the global climate state, since its circulation affects mean ocean properties, air–sea partitioning of carbon dioxide, and the distribution of global oceanic poleward heat transport. There is evidence that during the Last Glacial Maximum (LGM) the subarctic Pacific contained a better-ventilated, relatively fresh intermediate water mass above  2000 m that may have formed locally. The source and spatial extent of this water mass is not known, nor do we know how formation of this water mass varied during Pleistocene glaciations with different orbital and ice sheet boundary conditions. Here we present a 0.5 My multi-species benthic stable isotope record from Site \{U1345\} (1008 m) on the northern Bering slope and a 1.0 My record from \{U1339\} (1868 m) from the Umnak Plateau in the southeastern basin. We find that the relatively well-ventilated low-δ18O intermediate water reaches 1000 m in the Bering Sea during MIS2, but that the hydrographic divide between this water mass and poorly-ventilated deep water was shallower than 1000 m for earlier glaciations. We also compare Bering Sea piston core and İODP\} Expedition 323 Uvigerina data from the Holocene and \{LGM\} with the modern hydrography, and to previously published profiles from the Okhotsk Sea and Emperor Seamounts. We find that the carbon and oxygen stable isotope signatures of well-ventilated water in the Bering and Okhotsk Seas are distinct, suggesting that there may have been intermediate water formation in both basins during the LGM.
Plio-Pleistocene Paleoceanography of the Bering Sea
Keywords: Ocean circulation

Tracing the intrusion of fossil carbon into coastal Louisiana macrofauna using natural 14C and 13C abundances - Wilson, Rachel M.; Cherrier, Jennifer; Sarkodee-Adoo, Judith; Bosman, Samantha; Mickle, Alejandra; Chanton, Jeffrey P. (Deep Sea Research Part II: Topical Studies in Oceanography, 2016)
The Deepwater Horizon oil spill released a large volume of 13C and radiocarbon depleted organic matter to the northern Gulf of Mexico. Evidence of petroleum-derived carbon entering the offshore planktonic foodweb, as well as widespread oiling of coastal areas documented in previous studies suggests that hydrocarbons could have entered the near shore foodweb. To test this hypothesis, we measured radiocarbon (Δ14C%) and stable carbon isotopes (δ13C) in an assortment of fish tissue, invertebrate tissue and shell samples collected within a year of the spill at seven sites from Louisiana to Florida USA across the northern Gulf of Mexico. We observed a west–east gradient with the most depleted radiocarbon values found in Terrebonne Bay, Louisana and increasingly enriched radiocarbon values in organisms collected at sites to the east. Depleted radiocarbon values as low as −10% in invertebrate soft tissue from Terrebonne suggest assimilation of fossil carbon (2.8±1.2%), consistent with the hypothesis that organic matter from petrochemical reservoirs released during the Deepwater Horizon spill entered the coastal food web to a limited extent. Further there was a significant correlation between radiocarbon and δ13C values in invertebrate tissue consistent with this hypothesis. Both oyster tissue and hard head catfish tissue collected in impacted areas of coastal Louisiana were significantly depleted in 14C and 13C relative to organisms collected in the unaffected Apalachicola Bay, Florida (p<0.014). Alternative explanations for these results include the influence of chronic hydrocarbon pollution along the western gulf coast or that the organisms ingest carbon derived from 14C depleted organic matter mobilized during the erosion of coastal marshes in southern Louisiana.

Unusually large tsunamis frequent a currently creeping part of the Aleutian megathrust - Witter, Robert C.; Carver, Gary A.; Briggs, Richard W.; Gelfenbaum, Guy; Koehler, Richard D.; La Selle, SeanPaul; Bender, Adrian M.; Engelhart, Simon E.; Hemphill-Haley, Eileen; Hill, Troy D. (Geophysical Research Letters, 2016)
Current models used to assess earthquake and tsunami hazards are inadequate where creep dominates a subduction megathrust. Here we report geological evidence for large tsunamis, occurring on average every 300–340 years, near the source areas of the 1946 and 1957 Aleutian tsunamis. These areas bookend a postulated seismic gap over 200 km long where modern geodetic measurements indicate that the megathrust is currently creeping. At Sedanka Island, evidence for large tsunamis includes six sand sheets that blanket a lowland facing the Pacific Ocean, rise to 15 m above mean sea level, contain marine diatoms, cap terraces, adjoin evidence for scour, and date from the past 1700 years. The youngest sheet and modern drift logs found as far as 800 m inland and >18 m elevation likely record the 1957 tsunami. Previously unrecognized tsunami sources coexist with a presently creeping megathrust along this part of the Aleutian Subduction Zone.

A 12,000-yr pollen record off Cape Hatteras — Pollen sources and mechanisms of pollen dispersion - Naughton, F.; Keigwin, L.; Peteet, D.; Costas, S.; Desprat, S.; Oliveira, D.; de Vernal, A.; Voelker, A.; Abrantes, F. (Marine Geology, 2015)
Integrating both marine and terrestrial signals from the same sediment core is one of the primary challenges for understanding the role of ocean–atmosphere coupling throughout past climate changes. It is therefore vital to understand how the pollen signal of a given marine record reflects the vegetation changes of the neighboring continent. The comparison between the pollen record of marine core JPC32 (KNR178JPC32) and available terrestrial pollen sequences from eastern North America over the last 12,170 years indicates that the pollen signature off Cape Hatteras gives an integrated image of the regional vegetation encompassing the Pee Dee river, Chesapeake and Delaware hydrographic basins and is reliable in reconstructing the past climate of the adjacent continent. Extremely high quantities of pollen grains included in the marine sediments off Cape Hatteras were transferred from the continent to the sea, at intervals 10,100–8800 cal yr BP, 8300–7500 cal yr BP, 5800–4300 cal yr BP and 2100–730 cal yr BP, during storm events favored by episodes of rapid sea-level rise in the eastern coast of US. In contrast, pollen grains export was reduced during 12,170–10,150 cal yr BP and 4200–2200 cal yr BP, during episodes of intense continental dryness and slow sea level rise episodes or lowstands in the eastern coast of US. The near absence of reworked pollen grains in core JPC32 contrasts with the high quantity of reworked material in nearby but deeper located marine sites, suggesting that the JPC32 record was not affected by the Deep Western Boundary Current (DWBC) since the end of the Younger Dryas and should be considered a key site for studying past climate changes in the western North Atlantic.

Assessment of branched GDGTs as temperature proxies in sedimentary records from several small lakes in southwestern Greenland - Colcord, Devon E.; Cadieux, Sarah B.; Brassell, Simon C.; Castañeda, Isla S.; Pratt, Lisa M.; White, Jeffrey R. (Organic Geochemistry, 2015)
This study of five small (<3.0 ha) lakes in southwestern Greenland examines the veracity of branched glycerol dialkyl glycerol tetraethers (br GDGTs) as a temperature proxy in lacustrine systems. The proximity (<5 km) of the lakes suggests that their temperature history, and thus their br GDGT records, should be similar. Distributions of br GDGTs in (i) surface sediments from all five lakes, (ii) 14C-dated sediment cores from two lakes (Upper and Lower EVV Lakes) and (iii) soil samples from the area surrounding the lakes were examined. The temporal records of br GDGT-based temperature for the two cores exhibited both similarities and major discrepancies. The differences between the paleotemperature records for the two lakes suggest that br GDGTs are not solely soil-derived, reflecting air temperature, but also indicate an additional br GDGT contribution from another source. Among the broader suite of lake sediments, there was a strong correlation (R2 0.987) between br GDGT-based surface sediment temperatures and measured summer bottom water temperatures for the four lakes with hypoxic/anoxic bottom waters, including Upper EVV Lake. The correlation suggests production of br GDGTs by anaerobic bacteria within the bottom water and/or sediment–water interface, reflecting environmental temperature for the individual lakes and augmenting the uniform, soil-derived signal. Hence, assessment of br GDGTs in Greenland lake sediments provides evidence for their origin from anaerobic autochthonous bacteria and indicates that interpretation of lacustrine br GDGT-based paleotemperature records requires contextual knowledge of individual lake systems and potential source(s) of sedimentary br GDGTs.

Beach ridges as paleoseismic indicators of abrupt coastal subsidence during subduction zone earthquakes, and implications for Alaska-Aleutian subduction zone paleoseismology, southeast coast of the Kenai Peninsula, Alaska - Kelsey, Harvey M.; Witter, Robert C.; Engelhart, Simon E.; Briggs, Richard; Nelson, Alan; Haeussler, Peter; Corbett, D. Reide (Megathrust Earthquakes and Sea-level Change: a Tribute to George Plafker, 2015)
The Kenai section of the eastern Alaska-Aleutian subduction zone straddles two areas of high slip in the 1964 great Alaska earthquake and is the least studied of the three megathrust segments (Kodiak, Kenai, Prince William Sound) that ruptured in 1964. Investigation of two coastal sites in the eastern part of the Kenai segment, on the southeast coast of the Kenai Peninsula, identified evidence for two subduction zone earthquakes that predate the 1964 earthquake. Both coastal sites provide paleoseismic data through inferred coseismic subsidence of wetlands and associated subsidence-induced erosion of beach ridges. At Verdant Cove, paleo-beach ridges record the paleoseismic history; whereas at Quicksand Cove, buried soils in drowned coastal wetlands are the primary indicators of paleoearthquake occurrence and age. The timing of submergence and death of trees mark the oldest earthquake at Verdant Cove that is consistent with the age of a well documented ∼900-year-ago subduction zone earthquake that ruptured the Prince William Sound segment of the megathrust to the east and the Kodiak segment to the west. Soils buried within the last 400–450 years mark the penultimate earthquake on the southeast coast of the Kenai Peninsula. The penultimate earthquake probably occurred before AD 1840 from its absence in Russian historical accounts. The penultimate subduction zone earthquake on the Kenai segment did not rupture in conjunction with the Prince William Sound to the northeast. Therefore the Kenai segment, which is presently creeping, can rupture independently of the adjacent Prince William Sound segment that is presently locked.

Carbon Isotope Concentrations in Stream Food Webs of the Arctic Network National Parks, Alaska, 2014-2016 - Carey, Michael P.; O'Donnell, Jonathan A.; Koch, Joshua C. (Alaska Science Center, U.S. Geological Survey, 2015)
This dataset includes information on the carbon samples that were collected from organic and mineral soils, streams, algae, invertebrates, and fish in the Arctic Network Parks.

Climatic and biotic thresholds of coral-reef shutdown - Toth, Lauren T.; Aronson, Richard B.; Cobb, Kim M.; Cheng, Hai; Edwards, R. Lawrence; Grothe, Pamela R.; Sayani, Hussein R. (Nature Climate Change, 2015)
Climate change is now the leading cause of coral-reef degradation and is altering the adaptive landscape of coral populations1, 2. Increasing sea temperatures and declining carbonate saturation states are inhibiting short-term rates of coral calcification, carbonate precipitation and submarine cementation3, 4, 5. A critical challenge to coral-reef conservation is understanding the mechanisms by which environmental perturbations scale up to influence long-term rates of reef-framework construction and ecosystem function6, 7. Here we reconstruct climatic and oceanographic variability using corals sampled from a 6,750-year core from Pacific Panamá. Simultaneous reconstructions of coral palaeophysiology and reef accretion allowed us to identify the climatic and biotic thresholds associated with a 2,500-year hiatus in vertical accretion beginning ~4,100 years ago8. Stronger upwelling, cooler sea temperatures and greater precipitation—indicators of La Niña-like conditions—were closely associated with abrupt reef shutdown. The physiological condition of the corals deteriorated at the onset of the hiatus, corroborating theoretical predictions that the tipping points of radical ecosystem transitions should be manifested sublethally in the biotic constituents9. Future climate change could cause similar threshold behaviours, leading to another shutdown in reef development in the tropical eastern Pacific.
Keywords: Climate-change ecology; Palaeoceanography; Palaeoclimate; Palaeoecology

Coastal evidence for Holocene subduction-zone earthquakes and tsunamis in central Chile - Dura, Tina; Cisternas, Marco; Horton, Benjamin P.; Ely, Lisa L.; Nelson, Alan R.; Wesson, Robert L.; Pilarczyk, Jessica E. (Quaternary Science Reviews, 2015)
The ∼500-year historical record of seismicity along the central Chile coast (30–34°S) is characterized by a series of ∼M 8.0–8.5 earthquakes followed by low tsunamis (<4 m) occurring on the megathrust about every 80 years. One exception is the AD 1730 great earthquake (M 9.0–9.5) and high tsunami (>10 m), but the frequency of such large events is unknown. We extend the seismic history of central Chile through a study of a lowland stratigraphic sequence along the metropolitan coast north of Valparaíso (33°S). At this site, higher relative sea level during the mid Holocene created a tidal marsh and the accommodation space necessary for sediment that preserves earthquake and tsunami evidence. Within this 2600-yr-long sequence, we traced six laterally continuous sand beds probably deposited by high tsunamis. Plant remains that underlie the sand beds were radiocarbon dated to 6200, 5600, 5000, 4400, 3800, and 3700 cal yr BP. Sediment properties and diatom assemblages of the sand beds—for example, anomalous marine planktonic diatoms and upward fining of silt-sized diatom valves—point to a marine sediment source and high-energy deposition. Grain-size analysis shows a strong similarity between inferred tsunami deposits and modern coastal sediment. Upward fining sequences characteristic of suspension deposition are present in five of the six sand beds. Despite the lack of significant lithologic changes between the sedimentary units under- and overlying tsunami deposits, we infer that the increase in freshwater siliceous microfossils in overlying units records coseismic uplift concurrent with the deposition of five of the sand beds. During our mid-Holocene window of evidence preservation, the mean recurrence interval of earthquakes and tsunamis is ∼500 years. Our findings imply that the frequency of historical earthquakes in central Chile is not representative of the greatest earthquakes and tsunamis that the central Chilean subduction zone has produced.
Keywords: Coastal hazards; Coastal paleoseismology; Diatom paleoecology; Prehistoric earthquakes; Tsunami Deposits

Early deglacial onset of southwestern Greenland ice-sheet retreat on the continental shelf - Winsor, Kelsey; Carlson, Anders E.; Welke, Bethany M.; Reilly, Brendan (QUATERNARY SCIENCE REVIEWS, 2015)
The Greenland ice sheet (GrIS) advanced onto the continental shelf during the last glacial period. While deglacial records for when the GrIS withdrew onto the modern coastline are relatively abundant, the timing of early GrIS retreat on the shelf is poorly constrained. Here we use planktic foraminiferal delta O-18, sediment grain size, sedimentation rates, and C-14 ages in southeastern Davis Strait core HU87033-008 to develop an early deglaciation chronology of the southwestern GrIS while on the continental shelf. Sedimentation rates, and especially silt and clay fractions, are high between similar to 20.5 and similar to 17.1 ka, suggesting that the southwestern GrIS margin was near or at the shelf break, where it released subglacially derived sediment-laden meltwater. A peak in sedimentation rates of similar to 110 cm ka(-1) between similar to 19.3 ka and similar to 18.6 ka, combined with an initial decrease in planktic delta O-18 of similar to 0.5 per mil, suggests an early deglacial pull back of the GrIS margin from the shelf break with a concurrent increase in surface ocean meltwater discharge. A subsequent planktic delta O-18 decrease of similar to 1.0 per mil combined with a drop in silt and clay sedimentation rates at 18-17 ka likely record further GrIS retreat inland from the shelf break. Terrestrial Be-10 surface exposure ages indicate that the GrIS margin remained on the continental shelf until similar to 11 ka, yet the cause of this subsequent ice-margin stability on the inner shelf is not known. Our new records provide the first evidence that the southwestern GrIS margin may have begun to deglaciate at the same time as other Northern Hemisphere ice sheets. As Labrador Sea water temperatures likely remained near glacial values until similar to 15 ka, we suggest that initial southwestern GrIS retreat was in response to rising global sea level from retreat of other ice sheets and/or the initial deglacial rise in boreal summer insolation. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Davis Strait; Deglaciation; Greenland; Retreat forcings; sea level; Sedimentation rate

The End of the Wietenberg Culture in the Light of New 14C dates and its Chronological Relation Towards the Noua Culture. - Ciugudean, Horia; Quinn, Colin P. (Bronze Age Chronology in the Carpathian Basin, 2015)
Keywords: Bronze Age; Bronze Age Chronology; Carpathian Basin; Noua culture; radiocarbon dates; Transylvania; Wietenberg culture

Holocene variability in the intensity of wind-gap upwelling in the tropical eastern Pacific - Toth, Lauren T.; Aronson, Richard B.; Cheng, Hai; Edwards, R. Lawrence (Paleoceanography, 2015)
Wind-driven upwelling in Pacific Panamá is a significant source of oceanographic variability in the tropical eastern Pacific. This upwelling system provides a critical teleconnection between the Atlantic and tropical Pacific that may impact climate variability on a global scale. Despite its importance to oceanographic circulation, ecology, and climate, little is known about the long-term stability of the Panamanian upwelling system or its interaction with climatic forcing on millennial time scales. Using a combination of radiocarbon and U-series dating of fossil corals collected in cores from five sites across Pacific Panamá, we reconstructed the local radiocarbon reservoir correction, ΔR, from ~6750 cal B.P. to present. Because the ΔR of shallow-water environments is elevated by upwelling, our data set represents a millennial-scale record of spatial and temporal variability of the Panamanian upwelling system. The general oceanographic gradient from relatively strong upwelling in the Gulf of Panamá to weak-to-absent upwelling in the Gulf of Chiriquí was present throughout our record; however, the intensity of upwelling in the Gulf of Panamá varied significantly through time. Our reconstructions suggest that upwelling in the Gulf of Panamá is weak at present; however, the middle Holocene was characterized by periods of enhanced upwelling, with the most intense upwelling occurring just after of a regional shutdown in the development of reefs at ~4100 cal B.P. Comparisons with regional climate proxies suggest that, whereas the Intertropical Convergence Zone is the primary control on modern upwelling in Pacific Panamá, the El Niño–Southern Oscillation drove the millennial-scale variability of upwelling during the Holocene.

Late Holocene glacial advance and ice shelf growth in Barilari Bay, Graham Land, west Antarctic Peninsula - Christ, Andrew J.; Talaia-Murray, Manique; Elking, Natalie; Domack, Eugene W.; Leventer, Amy; Lavoie, Caroline; Brachfeld, Stefanie; Yoo, Kyu-Cheul; Gilbert, Robert; Jeong, Sun-Mi; Petrushak, Stephen; Wellner, Julia; et al. (GEOLOGICAL SOCIETY OF AMERICA BULLETIN, 2015)
Three marine sediment cores were collected along the length of the fjord axis of Barilari Bay, Graham Land, west Antarctic Peninsula (65 degrees 55'S, 64 degrees 43'W). Multi-proxy analytical results constrained by high-resolution geochronological methods (Pb-210, radiocarbon, Cs-137) in concert with historical observations capture a record of Holocene paleoenvironmental variability. Our results suggest early and middle Holocene (>7022-2815 cal. {[}calibrated] yr B.P.) retreated glacial positions and seasonally open marine conditions with increased primary productivity. Climatic cooling increased sea ice coverage and decreased primary productivity during the Neoglacial (2815 to cal. 730 cal. yr B.P.). This climatic cooling culminated with glacial advance to maximum Holocene positions and expansion of a fjord-wide ice shelf during the Little Ice Age (LIA) (ca. 730-82 cal. yr B.P.). Seasonally open marine conditions were achieved and remnant ice shelves decayed within the context of recent rapid regional warming (82 cal. yr B.P. to present). Our findings agree with previously observed late Holocene cooling and glacial advance across the Antarctic Peninsula, suggesting that the LIA was a regionally significant event with few disparities in timing and magnitude. Comparison of the LIA Antarctic Peninsula record to the rest of the Southern Hemisphere demonstrates close synchronicity in the southeast Pacific and southern most Atlantic region but less coherence for the southwest Pacific and Indian Oceans. Comparisons with the Northern Hemisphere demonstrate that the LIA Antarctic Peninsula record was contemporaneous with pre-LIA cooling and sea ice expansion in the North Atlantic-Arctic, suggesting a global reach for these events.

Multiproxy record of monsoon variability from the Ganga Plain during 400–1200 A.D - Singh, Dhruv Sen; Gupta, Anil K.; Sangode, S. J.; Clemens, Steven C.; Prakasam, M.; Srivastava, Priyeshu; Prajapati, Shailendra K. (Updated Quaternary Climatic Research in parts of the Third Pole Selected papers from the HOPE-2013 conference, Nainital, India, 2015)
Understanding on the Indian Summer Monsoon (ISM) variability is chiefly based upon the marine proxies and a few continental records. The Ganga Plain, one of the most densely populated regions of the world marked by intensive cultivation of monsoon dependent crops and a rich cultural history, is not yet well understood in the context of monsoon variability. We present here a 400–1200 A.D. AMS radiocarbon dated record of Ropan Chhapra tal in the Central Ganga Plain using sedimentology, environmental magnetism, and stable isotope of oxygen for ISM variability. The environmental magnetic parameters (χlf, χARM, SIRM/χlf, S-Ratio, B(0)CR and HIRM) inferred antiferromagnetic mineralogy (hematite and/or goethite) independent of grain size variation during 400–900 A.D., depicting climate variability within warm humid to warm arid conditions favouring stronger ISM seasonality. Prevalence of ferrimagnetic mineralogy under less oxygenated conditions intermittently demonstrates an altered catchment regime or possibly in response to stronger winter monsoon. The higher δ18O values around 500, 580 and 740 A.D. indicate warm and arid conditions under weak ISM. The lower δ18O values around 480, 540 and 700 A.D. and from 900 to 1200 A.D. occur during warm and humid conditions indicating maximum intensity of the ISM. Increased silt content from 800 A.D. onwards is due to increased surface runoff in response to enhanced precipitation, and the higher clay percentage around 500, 580 and 740 indicates low-energy (ponding) conditions under weak ISM. The well sorted nature of sediment indicates consistency of the lacustrine environments under fairly uniform energy and constant bottom water conditions, under varied monsoonal intensity. Combinations of sediment textures and stable isotope indicate intense ISM at ∼480 and ∼540 A.D. with flooding around ∼700 A.D. and a weak monsoon at 580 and 740 A.D., with drought at 500 A.D. During ∼900–1200 A.D. the multiproxy record suggests strong summer monsoon synchronous with Medieval Warm Period (MWP), whereas after 1200 A.D. the weak monsoon phase coincides with the onset of the Little Ice Age (LIA).

Refined bomb radiocarbon dating of two iconic fishes of the Great Barrier Reef - Andrews, Allen H.; Choat, John H.; Hamilton, Richard J.; DeMartini, Edward E. (Marine and Freshwater Research, 2015)
PT: J; TC: 0; UT: WOS:000351621600003

Relative sea-level change in Connecticut (USA) during the last 2200 yrs - Kemp, Andrew C.; Hawkes, Andrea D.; Donnelly, Jeffrey P.; Vane, Christopher H.; Horton, Benjamin P.; Hill, Troy D.; Anisfeld, Shimon C.; Parnell, Andrew C.; Cahill, Niamh (Earth and Planetary Science Letters, 2015)
We produced a relative sea-level (RSL) reconstruction from Connecticut (USA) spanning the last ∼2200 yrs that is free from the influence of sediment compaction. The reconstruction used a suite of vertically- and laterally-ordered sediment samples ≤2 cm above bedrock that were collected by excavating a trench along an evenly-sloped bedrock surface. Paleomarsh elevation was reconstructed using a regional-scale transfer function trained on the modern distribution of foraminifera on Long Island Sound salt marshes and supported by bulk-sediment δ13C measurements. The history of sediment accumulation was estimated using an age-elevation model constrained by radiocarbon dates and recognition of pollution horizons of known age. The RSL reconstruction was combined with regional tide-gauge measurements spanning the last ∼150 yrs before being quantitatively analyzed using an error-in-variables integrated Gaussian process model to identify sea-level trends with formal and appropriate treatment of uncertainty and the temporal distribution of data. RSL rise was stable (∼1 mm/yr) from ∼200 BCE to ∼1000 CE, slowed to a minimum rate of rise (0.41 mm/yr) at ∼1400 CE, and then accelerated continuously to reach a current rate of 3.2 mm/yr, which is the fastest, century-scale rate of the last 2200 yrs. Change point analysis identified that modern rates of rise in Connecticut began at 1850–1886 CE. This timing is synchronous with changes recorded at other sites on the U.S. Atlantic coast and is likely the local expression of a global sea-level change. Earlier sea-level trends show coherence north of Cape Hatteras that are contrasted with southern sites. This pattern may represent centennial-scale variability in the position and/or strength of the Gulf Stream. Comparison of the new record to three existing and reanalyzed RSL reconstructions from the same site developed using sediment cores indicates that compaction is unlikely to significantly distort RSL reconstructions produced from shallow (∼2–3 m thick) sequences of salt-marsh peat.
Keywords: Atlantic Ocean; Foraminifera; Gulf Stream; Late Holocene; Salt marsh

Sedimentation Pulse in the NE Gulf of Mexico following the 2010 DWH Blowout - Brooks, Gregg R.; Larson, Rebekka A.; Schwing, Patrick T.; Romero, Isabel; Moore, Christopher; Reichart, Gert-Jan; Jilbert, Tom; Chanton, Jeff P.; Hastings, David W.; Overholt, Will A.; Marks, Kala P.; Kostka, Joel E.; et al. (PLOS ONE, 2015)
The objective of this study was to investigate the impacts of the Deepwater Horizon (DWH) oil discharge at the seafloor as recorded in bottom sediments of the DeSoto Canyon region in the northeastern Gulf of Mexico. Through a close coupling of sedimentological, geochemical, and biological approaches, multiple independent lines of evidence from 11 sites sampled in November/December 2010 revealed that the upper ~1 cm depth interval is distinct from underlying sediments and results indicate that particles originated at the sea surface. Consistent dissimilarities in grain size over the surficial ~1 cm of sediments correspond to excess 234Th depths, which indicates a lack of vertical mixing (bioturbation), suggesting the entire layer was deposited within a 4–5 month period. Further, a time series from four deep-sea sites sampled up to three additional times over the following two years revealed that excess 234Th depths, accumulation rates, and 234Th inventories decreased rapidly, within a few to several months after initial coring. The interpretation of a rapid sedimentation pulse is corroborated by stratification in solid phase Mn, which is linked to diagenesis and redox change, and the dramatic decrease in benthic formanifera density that was recorded in surficial sediments. Results are consistent with a brief depositional pulse that was also reported in previous studies of sediments, and marine snow formation in surface waters closer to the wellhead during the summer and fall of 2010. Although sediment input from the Mississippi River and advective transport may influence sedimentation on the seafloor in the DeSoto Canyon region, we conclude based on multidisciplinary evidence that the sedimentation pulse in late 2010 is the product of marine snow formation and is likely linked to the DWH discharge.

Single cell genomics indicates horizontal gene transfer and viral infections in a deep subsurface Firmicutes population - Labonte, Jessica M.; Field, Erin K.; Lau, Maggie; Chivian, Dylan; Van Heerden, Esta; Wommack, K. Eric; Kieft, Thomas L.; Onstott, Tullis C.; Stepanauskas, Ramunas (Frontiers in Microbiology, 2015)
A major fraction of Earth's prokaryotic biomass dwells in the deep subsurface, where cellular abundances per volume of sample are lower, metabolism is slower, and generation times are longer than those in surface terrestrial and marine environments. How these conditions impact biotic interactions and evolutionary processes is largely unknown. Here we employed single cell genomics to analyze cell-to-cell genome content variability and signatures of horizontal gene transfer (HGT) and viral infections in five cells of Candidatus Desulforudis audaxviator, which were collected from a three km-deep fracture water in the 2.9 Ga-old Witwatersrand Basin of South Africa. Between 0 and 32 % of genes recovered from single cells were not present in the original, metagenomic assembly of Desulforudis, which was obtained from a neighboring subsurface fracture. We found a transposable prophage, a retron, multiple clustered regularly interspaced short palindromic repeats (CRISPRs) and restriction-modification systems, and an unusually high frequency of transposases in the analyzed single cell genomes. This indicates that recombination, HGT and viral infections are prevalent evolutionary events in the studied population of microorganisms inhabiting a highly stable deep subsurface environment.
PT: J; TC: 0; UT: WOS:000352551600004

Source-age dynamics of estuarine particulate organic matter using fatty acid delta C-13 and Delta C-14 composition - McIntosh, Hadley A.; McNichol, Ann P.; Xu, Li; Canuel, Elizabeth A. (Limnology and Oceanography, 2015)
This study used a multiproxy approach to elucidate the source and age composition of estuarine particulate organic matter (POM) using bulk stable isotopes (C-13(POC)), fatty acid (FA) biomarkers, and compound specific isotopic analyses in surface waters along the Delaware River and Bay (Delaware Estuary, hereafter). C-13 values of FA (C-13(FA)) ranged more widely (-30.9 parts per thousand to -21.8 parts per thousand) than C-13(POC) (-27.5 parts per thousand to -23.5 parts per thousand), providing greater insight about POM sources along the estuary. C-13 values of C-16:0 phospholipid FA (primarily, aquatic sources) increased along the salinity gradient (-29.8 parts per thousand to -23.4 parts per thousand), while C-13(FA) values of long-chain neutral fatty acid (terrestrial sources) decreased (-28.6 parts per thousand to -30.9 parts per thousand). C-13(FA) values for C-18's FA indicated the importance of marsh-derived organic matter within Delaware Estuary. Compound specific radiocarbon analysis showed the heterogeneous age structure of FA associated with POM (FA(POM)). C-14 ages of FA ranged from modern (postbomb) to 1790BP; aged FA (120BP to 1700BP) derived primarily from the watershed, whereas modern FA were produced within Delaware Estuary. C-14 ages of short-chain FA (aquatic sources) reflected differences in the age of dissolved inorganic carbon along the estuary and had older C-14 ages at the river end-member. C-14 ages of FA from terrigenous sources were older than water and sediment residence times indicating this source derived from the watershed. This study is the first to document the complex age distribution of FA(POM) along the estuarine salinity gradient and shows that inorganic carbon sources, watershed inputs and autochthonous production contribute to variation in the ages of POM.
PT: J; TC: 0; UT: WOS:000351126500020

Using Natural Abundance Radiocarbon To Trace the Flux of Petrocarbon to the Seafloor Following the Deepwater Horizon Oil Spill - Chanton, Jeffrey; Zhao, Tingting; Rosenheim, Brad E.; Joye, Samantha; Bosman, Samantha; Brunner, Charlotte; Yeager, Kevin M.; Diercks, Arne R.; Hollander, David (Environmental Science & Technology, 2015)
In 2010, the Deepwater Horizon accident released 4.6–6.0 × 1011 grams or 4.1 to 4.6 million barrels of fossil petroleum derived carbon (petrocarbon) as oil into the Gulf of Mexico. Natural abundance radiocarbon measurements on surface sediment organic matter in a 2.4 × 1010 m2 deep-water region surrounding the spill site indicate the deposition of a fossil-carbon containing layer that included 1.6 to 2.6 × 1010 grams of oil-derived carbon. This quantity represents between 0.5 to 9.1% of the released petrocarbon, with a best estimate of 3.0–4.9%. These values may be lower limit estimates of the fraction of the oil that was deposited on the seafloor because they focus on a limited mostly deep-water area of the Gulf, include a conservative estimate of thickness of the depositional layer, and use an average background or prespill radiocarbon value for sedimentary organic carbon that produces a conservative value. A similar approach using hopane tracer estimated that 4–31% of 2 million barrels of oil that stayed in the deep sea settled on the bottom. Converting that to a percentage of the total oil that entered into the environment (to which we normalized our estimate) converts this range to 1.8 to 14.4%. Although extrapolated over a larger area, our independent estimate produced similar values.

What do benthic ? 13 C and ? 18 O data tell us about Atlantic circulation during Heinrich Stadial 1? - Oppo, Delia W.; Curry, William B.; McManus, Jerry F. (Paleoceanography, 2015)
Approximately synchronous with the onset of Heinrich Stadial 1 (HS1), δ13C decreased throughout most of the upper (~1000–2500 m) Atlantic, and at some deeper North Atlantic sites. This early deglacial δ13C decrease has been alternatively attributed to a reduced fraction of high-δ13C North Atlantic Deep Water (NADW) or to a decrease in the NADW δ13C source value. Here we present new benthic δ18O and δ13C records from three relatively shallow (~1450–1650 m) subpolar Northeast Atlantic cores. With published data from other cores, these data form a depth transect (~1200–3900 m) in the subpolar Northeast Atlantic. We compare Last Glacial Maximum (LGM) and HS1 data from this transect with data from a depth transect of cores from the Brazil Margin. The largest LGM-to-HS1 decreases in both benthic δ13C and δ18O occurred in upper waters containing the highest NADW fraction during the LGM. We show that the δ13C decrease can be explained entirely by a lower NADW δ13C source value, entirely by a decrease in the proportion of NADW relative to Southern Ocean Water, or by a combination of these mechanisms. However, building on insights from model simulations, we hypothesize that reduced ventilation due to a weakened but still active Atlantic Meridional Overturning Circulation also contributed to the low δ13C values in the upper North Atlantic. We suggest that the benthic δ18O gradients above ~2300 m at both core transects indicate the depth to which heat and North Atlantic deglacial freshwater had mixed into the subsurface ocean by early HS1.

Coastal response to late-stage transgression and sea-level highstand - Hein, C. J.; FitzGerald, D. M.; Thadeu de Menezes, J.; Cleary, W. J.; Klein, A. H. F.; Albernaz, M. B. (Geological Society of America Bulletin, 2014)
Coastal morphologic features associated with past shoreline transgressions and sea-level highstands can provide insight into the rates and processes associated with coastal response to the modern global rise in sea level. Along the eastern and southern Brazilian coasts of South America, 6000 years of sea-level fall have preserved late-stage transgressive and sea-level highstand features 1–4 m above present mean sea level and several kilome ters landward of modern shore-lines. GPS with real-time kinematics data, ground-penetrating radar, stratigraphy, and radiocarbon dating within a 2–3-km-wide river-associated strandplain in central Santa Catarina (southern Brazil) uncovered a diverse set of late-stage transgressive and high- stand deposits. Here, the highstand took the forms of (1) an exposed bedrock coast in areas of high wave energy and low sediment supply; (2) a 3.8-m-high transgressive barrier ridge where landward barrier migration was prohibited by the presence of shallow bedrock; and (3) a complete barrier-island complex containing a 5.2-m-high barrier ridge, washover deposits, a paleo-inlet, and a backbarrier lowland, formed in a protected cove with ample sediment supply from small local streams and the erosion of upland sediments. Similar signatures of the mid-Holocene highstand can be traced across all coastal Brazilian states. This study presents the first complete compilation of the diversity of these sedimentary sequences. They are broadly classified here as exposed bedrock coasts (type A), back barrier deposits (type B), transgressive barrier ridges (type C), and barrier-island complexes (type D), according to localized conditions of upland migration potential, wave exposure, and sediment supply. These Brazilian systems present a paradigm for understanding future coastal response to climate change and accelerated sea-level rise: the recognition of a minimum threshold sea-level-rise rate of ~2 mm yr–1 above which transgression proceeded too rapidly for the formation of these stable accretionary shoreline features demonstrates the nonlinearity of coastal response to sea-level change, and the site specificity of conditions associated with the formation of each highstand deposit type, even within a single small embayment, demonstrates the non-uniformity of that response.

Composition and origin of authigenic carbonates in the Krishna-Godavari and Mahanadi Basins, eastern continental margin of India - Teichert, B. M. A.; Johnson, J. E.; Solomon, E. A.; Giosan, L.; Rose, K.; Kocherla, M.; Connolly, E. C.; Torres, M. E. (Marine and Petroleum Geology, 2014)
The mineralogical and stable isotopic composition of authigenic carbonates from the Krishna-Godavari (KG) and Mahanadi Basin provide a deeper insight into the processes inducing carbonate formation in the sediments of the eastern continental margin of India in the Bay of Bengal. Authigenic carbonate cements, (micro) nodules, bioturbation casts and tubes from 12 core locations drilled during the Indian National Gas Hydrate Program (NGHP) Expedition 01 were investigated for this study. Three main processes responsible for authigenic carbonate precipitation are identified: organoclastic sulfate reduction, anaerobic oxidation of methane and methanogenesis. Evidence of vigorous methane seepage is indicated in carbonates recovered at Sites 7, 10, 12 (KG Basin) and 19 (Mahanadi Basin). These methane-derived carbonates display typical paragenetic carbonate mineralogies (aragonite, high-Mg calcite with >15 Mol% MgCO3, Ca-rich dolomite). Two separate horizons of methane derived-carbonates are correlated between 4 drill holes (up to ∼16 km apart). The upper horizon has been dated with 14C (40,100 – 51,600 a B.P. 1950) clearly indicating that methane seepage has been much more vigorous in the past possibly due to a glacial sea level lowstand.
AAy4wyTimes Cited:5Cited References Count:63

Decreased influence of Antarctic intermediate water in the tropical Atlantic during North Atlantic cold events - Huang, Kuo-Fang; Oppo, Delia W.; Curry, William B. (Earth and Planetary Science Letters, 2014)
Antarctic Intermediate Water (AAIW) is a key player in the global ocean circulation, contributing to the upper limb of the Atlantic Meridional Overturning Circulation (AMOC), and influencing interhemispheric heat exchange and the distribution of salinity, nutrients and carbon. However, the deglacial history of AAIW flow into the North Atlantic is controversial. Here we present a multicore-top neodymium isotope calibration, which confirms the ability of unclean foraminifera to faithfully record bottom water neodymium isotopic composition () values in their authigenic coatings. We then present the first foraminifera-based reconstruction of from three sediment cores retrieved from within modern AAIW, in the western tropical North Atlantic. Our records reveal similar glacial and interglacial contributions of AAIW, and a pronounced decrease in the AAIW fraction during North Atlantic deglacial cold episodes, Heinrich Stadial 1 (HS1) and Younger Dryas (YD). Our results suggest two separate phases of reduced fraction of AAIW in the tropical Atlantic during HS1, with a greater reduction during early HS1. If a reduction in AAIW fraction also reflects reduced AMOC strength, this finding may explain why, in many regions, there are two phases of hydrologic change within HS1, and why atmospheric CO2 rose more rapidly during early than late HS1. Our result suggesting less flow of AAIW into the Atlantic during North Atlantic cold events contrasts with evidence from the Pacific, where intermediate-depth records may indicate increased flow of AAIW into the Pacific during the these same events. Antiphased behavior between intermediate depths of the North Atlantic and Pacific implies that the flow of AAIW into Atlantic and Pacific seesawed during the last deglaciation.
Keywords: antarctic intermediate water; Atlantic meridional overturning circulation; deglacial variability; Nd isotopes; North Atlantic cold events

Deglacial ?18O and hydrologic variability in the tropical Pacific and Indian Oceans - Gibbons, Fern T.; Oppo, Delia W.; Mohtadi, Mahyar; Rosenthal, Yair; Cheng, Jun; Liu, Zhengyu; Linsley, Braddock K. (Earth and Planetary Science Letters, 2014)
Evidence from geologic archives suggests that there were large changes in the tropical hydrologic cycle associated with the two prominent northern hemisphere deglacial cooling events, Heinrich Stadial 1 (HS1; ∼19 to 15 kyr BP; kyr BP = 1000 yr before present) and the Younger Dryas (∼12.9 to 11.7 kyr BP). These hydrologic shifts have been alternatively attributed to high and low latitude origin. Here, we present a new record of hydrologic variability based on planktic foraminifera-derived δ18O of seawater (δ18Osw) estimates from a sediment core from the tropical Eastern Indian Ocean, and using 12 additional δ18Osw records, construct a single record of the dominant mode of tropical Eastern Equatorial Pacific and Indo-Pacific Warm Pool (IPWP) hydrologic variability. We show that deglacial hydrologic shifts parallel variations in the reconstructed interhemispheric temperature gradient, suggesting a strong response to variations in the Atlantic Meridional Overturning Circulation and the attendant heat redistribution. A transient model simulation of the last deglaciation suggests that hydrologic changes, including a southward shift in the Intertropical Convergence Zone (ITCZ) which likely occurred during these northern hemisphere cold events, coupled with oceanic advection and mixing, resulted in increased salinity in the Indonesian region of the IPWP and the eastern tropical Pacific, which is recorded by the δ18Osw proxy. Based on our observations and modeling results we suggest the interhemispheric temperature gradient directly controls the tropical hydrologic cycle on these time scales, which in turn mediates poleward atmospheric heat transport.
Keywords: Deglaciation; Eastern Equatorial Pacific; heat transport; Indo-Pacific; δ18O of seawater

Delta growth and river valleys: the influence of climate and sea level changes on the South Adriatic shelf (Mediterranean Sea) - Maselli, V.; Trincardi, F.; Asioli, A.; Ceregato, A.; Rizzetto, F.; Taviani, M. (Quaternary Science Reviews, 2014)
Incised valleys across continental margins represent the response of fluvial systems to changes in their equilibrium dynamics, mainly driven by base level fall forced by glacial–eustatic cycles. The Manfredonia Incised Valley formed during the last glacial sea level lowstand, when most of the southern Adriatic shelf was sub-aerially exposed but the outer shelf remained under water. The pronounced upstream deepening of the valley is ascribed to river incision of the MIS5e highstand coastal prism and related subaqueous clinoform under the influence of MIS5-4 sea level fluctuations, while the downstream shallowing and narrowing mainly reflects the impact of increased rates of sea level fall at the MIS3-2 transition on a flatter mid-outer shelf. Until 15 ka BP, the valley fed an asymmetric delta confined to the mid-outer shelf, testifying that continental and deep marine systems remained disconnected during the lowstand. Sea level rise reached the inner shelf during the Early Holocene, drowning the valley and leading to the formation of a sheltered embayment confined toward the land: at this time part of the incision remained underfilled with a marked bathymetric expression. This mini-basin was rapidly filled by sandy bayhead deltas, prograding from both the northern and southern sides of the valley. In this environment, protected by marine reworking and where sediment dispersal was less effective, the accommodation space was reduced and autogenic processes forced the formation of multiple and coalescing delta lobes. Bayhead delta progradations occurred in few centuries, between 8 and 7.2 ka cal BP, confirming the recent hypothesis that in this area the valley was filled during the formation of sapropel S1. This proximal valley fill, representing the very shallow-water equivalent of the cm-thick sapropel layers accumulated offshore in the deeper southern Adriatic basin, is of key importance in following the signature of the sapropel in a facies-tract ideally from the shoreline to the abyss.

Gas hydrate destabilization and methane release events in the Krishna–Godavari Basin, Bay of Bengal - Joshi, R. K.; Mazumdar, A.; Peketi, A.; Ramamurty, P. B.; Naik, B. G.; Kocherla, M.; Carvalho, Mary Ann; Mahalakshmi, P.; Dewangan, P.; Ramana, M. V. (Marine and Petroleum Geology, 2014)
Methane release events have been linked to global warming, alteration of the carbon cycle and influence on biota. However, unequivocal evidence of paleomethane release events are limited. We report several negative carbon stable isotope excursions in planktic and benthic foraminifera in a core (MD161-8) from the Krishna-Godavari (K–G) Basin, Bay of Bengal. The most negative δ13C spikes are recorded during the marine isotope stages MIS-4 and at the transition of MIS-5 to 4. Occurrence of highly 13C depleted (average δ13C = −48 ± 2.4‰ VPDB) authigenic high magnesian calcite are also reported within this time window from the core MD161-8. In the present work an unequivocal explanation for the observed 13C depletion in the marine planktic and benthic foraminifera is difficult to achieve solely from the optical/electron microscopy or C–O stable isotope ratio analyses due to possible influence of diagenetic alteration. We attribute the observed episodic methane expulsion events, as inferred from the negative δ13C excursions and earlier reports on the occurrence chemosynthetic bivalves and Mo concentration anomaly to the destabilization of the base of gas hydrate stability zone (BGHSZ). Sea level drop and shale tectonics induced focused fluid flow are the two possible causes of hydrate destabilization discussed here. Shale tectonics were possibly responsible for creating fault systems which acted as the conduit for gas flow through the sediment column and subsequent seepage. Shale and salt tectonics in the passive continental margins being a globally observed phenomenon, its role as an important driving force for enhanced methane emission needs detailed investigation to understand the climatic perturbations through geologic time. Additional evidence of methane emission from site MD161-15 further supports the link between shale tectonics and methane emission.
AAy4wyTimes Cited:2Cited References Count:97

The high-supply, current-dominated continental margin of southeastern South America during the late Quaternary - Lantzsch, Hendrik; Hanebuth, Till J. J.; Chiessi, Cristiano M.; Schwenk, Tilmann; Violante, Roberto A. (Quaternary Research, 2014)
The continental margin off the La Plata Estuary (SE South America) is characterized by high fluvial sediment supply and strong ocean currents. High-resolution sediment-acoustic data combined with sedimentary facies analysis, AMS-14C ages, and neodymium isotopic data allowed us to reconstruct late Quaternary sedimentary dynamics in relation to the two major sediment sources, the La Plata Estuary and the Argentine margin. Sediments from these two provinces show completely different dispersal patterns. We show that the northward-trending La Plata paleo-valley was the sole transit path for the huge volumes of fluvial material during lower sea levels. In contrast, material from the Argentine margin sector was transported northwards by the strong current system. Despite the large sediment volumes supplied by both sources, wide parts of the shelf were characterized by either persistent non-deposition or local short-term depocenter formation. The location and formation history of these depocenters were primarily controlled by the interplay of sea level with current strength and local morphology. The high sediment supply was of secondary importance to the stratigraphic construction, though locally resulting in high sedimentation rates. Thus, the shelf system off the La Plata Estuary can be considered as a hydrodynamic-controlled end-member.

Holocene sea-surface temperature variability in the Chilean fjord region - Caniupán, Magaly; Lamy, Frank; Lange, Carina B.; Kaiser, Jérôme; Kilian, Rolf; Arz, Helge W.; León, Tania; Mollenhauer, Gesine; Sandoval, Susana; De Pol-Holz, Ricardo; Pantoja, Silvio; Wellner, Julia; et al. (Quaternary Research, 2014)
Here we provide three new Holocene (11–0 cal ka BP) alkenone-derived sea surface temperature (SST) records from the southernmost Chilean fjord region (50–53°S). SST estimates may be biased towards summer temperature in this region, as revealed by a large set of surface sediments. The Holocene records show consistently warmer than present-day SSTs except for the past ~ 0.6 cal ka BP. However, they do not exhibit an early Holocene temperature optimum as registered further north off Chile and in Antarctica. This may have resulted from a combination of factors including decreased inflow of warmer open marine waters due to lower sea-level stands, enhanced advection of colder and fresher inner fjord waters, and stronger westerly winds. During the mid-Holocene, pronounced short-term variations of up to 2.5°C and a cooling centered at ~ 5 cal ka BP, which coincides with the first Neoglacial glacier advance in the Southern Andes, are recorded. The latest Holocene is characterized by two pronounced cold events centered at ~ 0.6 and 0.25 cal ka BP, i.e., during the Little Ice Age. These cold events have lower amplitudes in the offshore records, suggesting an amplification of the SST signal in the inner fjords.

Late Holocene sea- and land-level change on the U.S. southeastern Atlantic coast - Kemp, Andrew C.; Bernhardt, Christopher E.; Horton, Benjamin P.; Kopp, Robert E.; Vane, Christopher H.; Peltier, W. Richard; Hawkes, Andrea D.; Donnelly, Jeffrey P.; Parnell, Andrew C.; Cahill, Niamh (Marine Geology, 2014)
Late Holocene relative sea-level (RSL) reconstructions can be used to estimate rates of land-level (subsidence or uplift) change and therefore to modify global sea-level projections for regional conditions. These reconstructions also provide the long-term benchmark against which modern trends are compared and an opportunity to understand the response of sea level to past climate variability. To address a spatial absence of late Holocene data in Florida and Georgia, we reconstructed ~ 1.3 m of RSL rise in northeastern Florida (USA) during the past ~ 2600 years using plant remains and foraminifera in a dated core of high salt-marsh sediment. The reconstruction was fused with tide-gauge data from nearby Fernandina Beach, which measured 1.91 ± 0.26 mm/year of RSL rise since 1900 CE. The average rate of RSL rise prior to 1800 CE was 0.41 ± 0.08 mm/year. Assuming negligible change in global mean sea level from meltwater input/removal and thermal expansion/contraction, this sea-level history approximates net land-level (subsidence and geoid) change, principally from glacio-isostatic adjustment. Historic rates of rise commenced at 1850–1890 CE and it is virtually certain (P = 0.99) that the average rate of 20th century RSL rise in northeastern Florida was faster than during any of the preceding 26 centuries. The linearity of RSL rise in Florida is in contrast to the variability reconstructed at sites further north on the U.S. Atlantic coast and may suggest a role for ocean dynamic effects in explaining these more variable RSL reconstructions. Comparison of the difference between reconstructed rates of late Holocene RSL rise and historic trends measured by tide gauges indicates that 20th century sea-level trends along the U.S. Atlantic coast were not dominated by the characteristic spatial fingerprint of melting of the Greenland Ice Sheet.

Late Holocene sea- and land-level change on the U.S. southeastern Atlantic coast - Kemp, Andrew C.; Bernhardt, Christopher E.; Horton, Benjamin P.; Kopp, Robert E.; Vane, Christopher H.; Peltier, W. Richard; Hawkes, Andrea D.; Donnelly, Jeffrey P.; Parnell, Andrew C.; Cahill, Niamh (Marine Geology, 2014)
Late Holocene relative sea-level (RSL) reconstructions can be used to estimate rates of land-level (subsidence or uplift) change and therefore to modify global sea-level projections for regional conditions. These reconstructions also provide the long-term benchmark against which modern trends are compared and an opportunity to understand the response of sea level to past climate variability. To address a spatial absence of late Holocene data in Florida and Georgia, we reconstructed ~ 1.3 m of RSL rise in northeastern Florida (USA) during the past ~ 2600 years using plant remains and foraminifera in a dated core of high salt-marsh sediment. The reconstruction was fused with tide-gauge data from nearby Fernandina Beach, which measured 1.91 ± 0.26 mm/year of RSL rise since 1900 CE. The average rate of RSL rise prior to 1800 CE was 0.41 ± 0.08 mm/year. Assuming negligible change in global mean sea level from meltwater input/removal and thermal expansion/contraction, this sea-level history approximates net land-level (subsidence and geoid) change, principally from glacio-isostatic adjustment. Historic rates of rise commenced at 1850–1890 CE and it is virtually certain (P = 0.99) that the average rate of 20th century RSL rise in northeastern Florida was faster than during any of the preceding 26 centuries. The linearity of RSL rise in Florida is in contrast to the variability reconstructed at sites further north on the U.S. Atlantic coast and may suggest a role for ocean dynamic effects in explaining these more variable RSL reconstructions. Comparison of the difference between reconstructed rates of late Holocene RSL rise and historic trends measured by tide gauges indicates that 20th century sea-level trends along the U.S. Atlantic coast were not dominated by the characteristic spatial fingerprint of melting of the Greenland Ice Sheet.
Keywords: florida; Foraminifera; Glacio-isostatic adjustment Greenland fingerprint; Salt marsh

Maximum age and missing time in the vertebrae of sand tiger shark (Carcharias taurus): validated lifespan from bomb radiocarbon dating in the western North Atlantic and southwestern Indian Oceans - Passerotti, M. S.; Andrews, A. H.; Carlson, J. K.; Wintner, S. P.; Goldman, K. J.; Natanson, L. J. (Marine and Freshwater Research, 2014)
Bomb radiocarbon analysis of vertebral growth bands was used to validate lifespan for sand tiger sharks (Carcharias taurus) from the western North Atlantic (WNA) and southwestern Indian Oceans (SIO). Visual counts of vertebral growth bands were used to assign age and estimate year of formation (YOF) for sampled growth bands in eight sharks from the WNA and two sharks from the SIO. Carbon-14 results were plotted relative to YOF for comparison with regional Δ14C reference chronologies to assess the accuracy of age estimates. Results from the WNA validated vertebral age estimates up to 12 years, but indicated that ages of large adult sharks were underestimated by 11–12 years. Age was also underestimated for adult sharks from the SIO by 14–18 years. Validated lifespan for C. taurus individuals in the present study reached at least 40 years for females and 34 years for males. Findings indicated that the current age-reading methodology is not suitable for estimating the age of C. taurus beyond ~12 years. Future work should investigate whether vertebrae of C. taurus record age throughout ontogeny, or cease to be a reliable indicator at some point in time.
id: 2352

New cetacean ΔR values for Arctic North America and their implications for marine-mammal-based palaeoenvironmental reconstructions - Furze, Mark F. A.; Pieńkowski, Anna J.; Coulthard, Roy D. (Quaternary Science Reviews, 2014)
Radiocarbon-dated marine mammal remains from emergent Arctic coastlines have frequently been used to reconstruct Holocene sea-ice histories. The use of such reconstructions has hitherto been complicated by uncertain marine reservoir corrections precluding meaningful intercomparisons with data reported in calibrated or sidereal years. Based on an exhaustive compilation of previously published marine mammal radiocarbon dates (both live-harvested materials and subfossils) from the Canadian Arctic Archipelago (CAA), new, statistically-derived δ13C and ΔR values are provided. Average δ13C values are: −16.1 ± 1.1‰ (bone collagen; n = 193) for bowhead (Balaena mysticetus); −14.4 ± 0.5‰ (n = 44; dentine) for beluga (Delphinapterus leucas); −14.8 ± 1.9‰ (teeth and tusks; n = 18) and −18.0 ± 4.7‰ (n = 9; bone collagen) for walrus (Odobenus rosmarus). ΔR values are 170 ± 95 14C years for bowhead (n = 23) and 240 ± 60 14C years for beluga (n = 12). Scarce data preclude calculation of meaningful, statistically robust walrus ΔR. Using the new ΔR values, an expanded and revised database of calibrated bowhead dates (651 dates; many used in previous CAA sea-ice reconstructions) shows pronounced late Quaternary spatio-temporal fluctuations in bone abundance. Though broadly resembling earlier bowhead subfossil frequency data, analysis of the new expanded database suggests early- and mid-Holocene increases in whale abundance to be of longer duration and lower amplitude than previously considered. A more even and persistent spread of infrequent low-abundance remains during “whale free” intervals is also seen. The dominance of three eastern regions (Prince Regent Inlet & Gulf of Boothia; Admiralty Inlet; Berlinguet Inlet/Bernier Bay) in the CAA data, collectively contributing up to 88% of all subfossil remains in the mid-Holocene, is notable. An analysis of calibrated regional sea-level index points suggests that severance of the Admiralty Inlet-Gulf of Boothia marine channel due to isostatically-driven regression may have played a significant role in enhanced whale mortality during this interval. Comparisons between the newly calibrated bowhead data and other regional sea-ice proxy data further highlight spatial and temporal discrepancies, potentially due to regional asynchronicities and variable sensitivities in proxy response to climate and oceanographic forcing. However, the limited number of deglacial–postglacial marine records continues to hamper extensive intercomparisons between marine mammal and other proxy datasets. Nevertheless, an examination of assumptions inherent in linking bowhead subfossil frequencies, population densities, and sea-ice thickness and distribution, shows that such relationships are highly complex. Factors such as broad sea-ice preferences, variable mortality rates and causes, long distance carcass transport, variable coastline and basin/channel geometries, and changing emergence rates all complicate the correlation of whale bone abundance to sea-ice histories.

Organic matter transformation in the peat column at Marcell Experimental Forest: Humification and vertical stratification - Tfaily, Malak M.; Cooper, William T.; Kostka, Joel E.; Chanton, Patrick R.; Schadt, Christopher W.; Hanson, Paul J.; Iversen, Colleen M.; Chanton, Jeffrey P. (JOURNAL OF GEOPHYSICAL RESEARCH-BIOGEOSCIENCES, 2014)
We characterized peat decomposition at the Marcell Experimental Forest (MEF), Minnesota, USA, to a depth of 2m to ascertain the underlying chemical changes using Fourier transform infrared (FT IR) and C-13 nuclear magnetic resonance (NMR) spectroscopy) and related these changes to decomposition proxies C:N ratio, C-13 and N-15, bulk density, and water content. FT IR determined that peat humification increased rapidly between 30 and 75cm, indicating a highly reactive intermediate-depth zone consistent with changes in C:N ratio, C-13 and N-15, bulk density, and water content. Peat decomposition at the MEF, especially in the intermediate-depth zone, is mainly characterized by preferential utilization of O-alkyl-C, carboxyl-C, and other oxygenated functionalities with a concomitant increase in the abundance of alkyl- and nitrogen-containing compounds. Below 75cm, less change was observed but aromatic functionalities and lignin accumulated with depth. Significant correlations with humification indices, identified by FT IR spectroscopy, were found for C:N ratios. Incubation studies at 22 degrees C revealed the highest methane production rates, greatest CH4:CO2 production ratios, and significant O-alkyl-C utilization within this 30 and 75cm zone. Oxygen-containing functionalities, especially O-alkyl-C, appear to serve as excellent proxies for soil decomposition rate and should be a sensitive indicator of the response of the solid phase peat to increased temperatures caused by climate change and the field study manipulations that are planned to occur at this site. Radiocarbon signatures of microbial respiration products in deeper pore waters at the MEF resembled the signatures of more modern dissolved organic carbon rather than solid phase peat, indicating that recently photosynthesized organic matter fueled the bulk of subsurface microbial respiration. These results indicate that carbon cycling at depth at the MEF is not isolated from surface processes.
Keywords: FT-IR spectroscopy; humification; NMR spectroscopy; organic matter; peatlands; vertical stratification

Origin, composition, and transformation of dissolved organic matter in tropical peatlands - Gandois, L.; Teisserenc, R.; Cobb, A. R.; Chieng, H. I.; Lim, L. B. L.; Kamariah, A. S.; Hoyt, A.; Harvey, C. F. (Geochimica et Cosmochimica Acta, 2014)
Solid and dissolved organic matter (DOM) compositions were investigated in a pristine and a deforested tropical peat forest in Brunei Darussalam. A combination of elemental (%C, %N, C/N), isotopic (δ15N, δ13C, Δ14C), molecular (lignin phenol biomarkers) and optical (Specific UV Absorbance at 280 nm (SUVA280), fluorescence index (FI)) analyses were performed to characterize DOM in porewater and river water. The DOM composition was compared to vegetation and peat to assess DOM origin and transformations in the ecosystem. Significant relationships were observed between optical properties (SUVA280, FI) and bulk (Δ14C) and molecular (ratio of cinnamyl to vanillyl phenols, C/V) composition of DOM. The radiocarbon content of DOM shows that it is modern at both sites for both surface and deep (to 4.5 m) samples (Δ14C = 74.58 ± 8.53‰ at the pristine site and Δ14C = 87.84 ± 4.5‰ at the deforested site for the first 2 meters), indicating transport of young DOM to deeper layers. Stable carbon-13 content of vegetation, peat and DOM showed only slight fractionation and ranged from −32.2‰ to −28.3‰. Nitrogen showed a greater shift between ecosystem pools. Nitrogen-15 content was higher in the solid peat (δ15N = −0.92 ± 0.49‰ in the pristine site, δ15N = −1.22 ± 1.37‰ in the deforested site) than in DOM (δ15N = −4.2 ± 2.5‰ in the pristine site, δ15N = −4.1 ± 2.3‰ in the deforested site). This difference in δ15N is significantly correlated with the C/N values of peat and DOM and attributable to higher microbial degradation in the peat compared to DOM. Porewater DOM contains less lignin (λ8 = 1.10 ± 0.27 mg 100 mg dw−1 in the pristine site and λ8 = 1.38 ± 0.46 mg 100 mg dw−1 in the deforested site) than does the solid peat (λ8 = 5.66 ± 2.14 mg 100 mg dw−1 in the pristine site and λ8 = 10.29 ± 4.69 mg 100 mg dw−1 in the deforested site). All indicators of lignin degradation (P/(V + S), 3,5Bd/V, (Ad/Al)V, (Ad/Al)S) are significantly higher in DOM than in the solid peat. This shows that lignin can be processed rapidly in the porewater of upper layers of tropical peatlands. Logging activity affected the composition of organic matter at the deforested site. Higher lignin content (λ8) was observed in the solid peat, and the composition of DOM differed greatly in the deforested site: Δ14C, FI, 3,5Bd/V, (Ad/Al)V are significantly different from the pristine site. Thus it appears that the composition of DOM is more sensitive than the solid phase to the effects of land use change on organic matter dynamic in tropical peatlands.

Phylogeny and phylogeography of functional genes shared among seven terrestrial subsurface metagenomes reveal N-cycling and microbial evolutionary relationships - Lau, Maggie C. Y.; Cameron, Connor; Magnabosco, Cara; Brown, C. Titus; Schilkey, Faye; Grim, Sharon; Hendrickson, Sarah; Pullin, Michael; Lollar, Barbara Sherwood; Van Heerden, Esta; Kieft, Thomas L.; Onstott, Tullis C. (FRONTIERS IN MICROBIOLOGY, 2014)
Comparative studies on community phylogenetics and phylogeography of microorganisms living in extreme environments are rare. Terrestrial subsurface habitats are valuable for studying microbial biogeographical patterns due to their isolation and the restricted dispersal mechanisms. Since the taxonomic identity of a microorganism does not always correspond well with its functional role in a particular community, the use of taxonomic assignments or patterns may give limited inference on how microbial functions are affected by historical, geographical and environmental factors. With seven metagenomic libraries generated from fracture water samples collected from five South African mines, this study was carried out to (1) screen for ubiquitous functions or pathways of biogeochemical cycling of CH4, S, and N; (2) to characterize the biodiversity represented by the common functional genes; (3) to investigate the subsurface biogeography as revealed by this subset of genes; and (4) to explore the possibility of using metagenomic data for evolutionary study. The ubiquitous functional genes are NarV, NPD, PAPS reductase, NifH, NifD, NifK, NifE, and NifN genes. Although these eight common functional genes were taxonomically and phylogenetically diverse and distinct from each other, the dissimilarity between samples did not correlate strongly with geographical or environmental parameters or residence time of the water. Por genes homologous to those of Thermodesulfovibrio yellowstonii detected in all metagenomes were deep lineages of Nitrospirae, suggesting that subsurface habitats have preserved ancestral genetic signatures that inform the study of the origin and evolution of prokaryotes.
Keywords: evolution; functional genes; N-cycle; phylogenetics; phylogeny; phylogeography; terrestrial subsurface

Pre-aged plant waxes in tropical lake sediments and their influence on the chronology of molecular paleoclimate proxy records - Douglas, Peter M. J.; Pagani, Mark; Eglinton, Tim E.; Brenner, Mark; Hodell, David A.; Curtis, Jason H.; Ma, Keith; Breckenridge, Andy (Geochimica et Cosmochimica Acta, 2014)
Sedimentary records of plant-wax hydrogen (δDwax) and carbon (δ13Cwax) stable isotopes are increasingly applied to infer past climate change. Compound-specific radiocarbon analyses, however, indicate that long time lags can occur between the synthesis of plant waxes and their subsequent deposition in marginal marine sediments. The influence of these time lags on interpretations of plant-wax stable isotope records is presently unconstrained, and it is unclear whether such time lags also affect lacustrine sediments. We present compound-specific radiocarbon (14Cwax) data for n-alkanoic acid plant waxes (n-C26 to n-C30) from: 1) a sediment core from Lake Chichancanab, Yucatan Peninsula, Mexico, 2) soils in the Lake Chichancanab catchment, and 3) surface sediments from three other lakes in southeastern Mexico and northern Guatemala. 14Cwax ages in the surface sediments are consistently older than modern, and may be negatively correlated with mean annual precipitation and positively correlated with lake catchment area. 14Cwax ages in soils surrounding Lake Chichancanab increase with soil depth, consistent with deep, subsoil horizons being the primary source of lacustrine aged plant waxes, which are likely delivered to lake sediments through subsurface transport. Plant waxes in the Lake Chichancanab core are 350 to 1200 years older than corresponding ages of bulk sediment deposition, determined by 14C dates on terrestrial plant macrofossils in the core. A δDwax time series is in closer agreement with other regional proxy hydroclimate records when a plant-wax 14C age model is applied, as opposed to the macrofossil-based core chronology. Inverse modeling of plant-wax age distribution parameters suggests that plant waxes in the Lake Chichancanab sediment core derive predominantly from millennial-age soil carbon pools that exhibit relatively little age variance (< 200 years). Our findings demonstrate that high-temporal-resolution climate records inferred from stable isotope measures on plant waxes in lacustrine sediments may suffer from possible chronologic distortions as a consequence of long residence times of plant waxes in soils. They also underscore the importance of direct radiocarbon dating of these organic molecules.

Preferential burial of permafrost-derived organic carbon in Siberian-Arctic shelf waters - Vonk, Jorien E.; Semiletov, Igor P.; Dudarev, Oleg V.; Eglinton, Timothy I.; Andersson, August; Shakhova, Natalia; Charkin, Alexander; Heim, Birgit; Gustafsson, Örjan (JOURNAL OF GEOPHYSICAL RESEARCH-OCEANS, 2014)
The rapidly changing East Siberian Arctic Shelf (ESAS) receives large amounts of terrestrial organic carbon (OC) from coastal erosion and Russian-Arctic rivers. Climate warming increases thawing of coastal Ice Complex Deposits (ICD) and can change both the amount of released OC, as well as its propensity to be converted to greenhouse gases (fueling further global warming) or to be buried in coastal sediments. This study aimed to unravel the susceptibility to degradation, and transport and dispersal patterns of OC delivered to the ESAS. Bulk and molecular radiocarbon analyses on surface particulate matter (PM), sinking PM and underlying surface sediments illustrate the active release of old OC from coastal permafrost. Molecular tracers for recalcitrant soil OC showed ages of 3.4-13 C-14-ky in surface PM and 5.5-18 C-14-ky in surface sediments. The age difference of these markers between surface PM and surface sediments is larger (i) in regions with low OC accumulation rates, suggesting a weaker exchange between water column and sediments, and (ii) with increasing distance from the Lena River, suggesting preferential settling of fluvially derived old OC nearshore. A dual-carbon end-member mixing model showed that (i) contemporary terrestrial OC is dispersed mainly by horizontal transport while being subject to active degradation, (ii) marine OC is most affected by vertical transport and also actively degraded in the water column, and (iii) OC from ICD settles rapidly and dominates surface sediments. Preferential burial of ICD-OC released into ESAS coastal waters might therefore lower the suggested carbon cycle climate feedback from thawing ICD permafrost.
Keywords: biomarkers; carbon; permafrost; radiocarbon

Record of methane emissions from the West Svalbard continental margin during the last 23.500 yrs revealed by δ13C of benthic foraminifera - Panieri, Giuliana; James, Rachael H.; Camerlenghi, Angelo; Westbrook, Graham K.; Consolaro, Chiara; Cacho, Isabel; Cesari, Valentina; Cervera, Cristina Sanchez (Global and Planetary Change, 2014)
The values of δ13C in benthic foraminifera have been measured in a gas-hydrate-bearing sediment core collected from an area of active methane venting on the Vestnesa Ridge (West Svalbard continental margin) to reconstruct the local history of methane emissions over the past 23.500 yrs BP. The chronostratigraphic framework of the core has been derived from AMS 14C dates and biostratigraphic analysis. While foraminifera from some intervals have δ13C within the normal marine range (0 to − 1‰), five intervals are characterized by a much lower δ13C, as low as − 17.4‰. These intervals are interpreted to record the incorporation of 13C-depleted carbon in the presence of methane emissions at the seafloor during biomineralization of the carbonate foraminiferal tests and subsequent secondary mineralization. Methane emission events (MEE) occur from the Last Glacial Maximum (LGM) to the Holocene, with the most prominent one, in terms of δ13C depletion, predating the Bølling–Allerød Interstadial (GI-1 in the Greenland ice core record). The lack of correlation between the values of δ13C and δ18O, however, appears to preclude warming of bottom waters as the principal control on methane release. Rather, it seems likely that methane release is a consequence of episodicity in the supply of gas to the hydrate system and in the processes that enable methane gas to migrate through the hydrate stability field to the seabed, or of other geological processes still under debate.

Seafloor fault ruptures along the North Anatolia Fault in the Marmara Sea, Turkey: Link with the adjacent basin turbidite record - McHugh, Cecilia M. G.; Braudy, Nicole; Çağatay, M. Namik; Sorlien, Christopher; Cormier, Marie-Helene; Seeber, Leonardo; Henry, Pierre (Marine Geology, 2014)
The relation between seafloor fault ruptures and the generation of turbidity currents was investigated to better understand the structural growth of tectonic basins with direct implications for earthquake hazard assessment. This study focuses on the Holocene earthquake record of transtensional basins in the Marmara Sea, Turkey, that are associated with the North Anatolian Fault system. The physical and chemical composition of three 10 m-long cores recovered from the Central Basin was studied at high-resolution and turbidite–homogenite units were identified. Turbidite–homogenite units (T–H units) are complex deposits that consist of a sharp basal contact and multiple fining upward beds of sand to coarse silt, above. All are capped by a 25 cm to 75 cm thick layer of medium to fine silt. A chronology developed from radiocarbon and short-lived radioisotopes allowed the correlation of these T–H units to the historical record of earthquakes that in Turkey goes back 2000 years. We found that the best location to recover the most complete sedimentation record is in the deepest part of a basin or “depocenter” where T–H units constitute ~ 80% of the sediments. A very good correlation was established between T–H units in Central Basin and proximal inferred historic epicentres along the central Marmara segment of the North Anatolia Fault that occurred in 1343, 860, 740, and 557 AD, and two more distal earthquakes that occurred in 268 and 1963 (or possibly1964). These sedimentation events can then be referred to as “seismo-turbidites”. The results when compared to findings from other transform basins in Marmara Sea reveal a very good correlation between T–H units and historic ruptures. Most importantly, there is a strong correlation between the inferred locations of historical earthquakes and the preservation of turbidite–homogenite units in the basin adjacent to the inferred rupture. The 740 AD earthquake correlates with T–H units in Izmit Gulf and Central Basin and could represent a multi-segment rupture of the NAF. Generally, T–H units appear to be clustered through the Holocene sections, suggesting temporal earthquake clustering in the Marmara Sea region. Such clustering may account for the lack of T–H units and hence large ruptures through the Central Basin since 1343.

Sedimentary and faunal signatures of the post-glacial marine drowning of the Pontocaspian Gemlik “lake” (Sea of Marmara) - Taviani, M.; Angeletti, L.; Cagatay, M. N.; Gasperini, L.; Polonia, A.; Wesselingh, F. P. (Quaternary International, 2014)
A Late Pleistocene (Neoeuxinian) Pontocaspian fauna is documented from sediments cored at̴ ∼75 m present water depth in the shallow-silled (∼50 m) Gulf of Gemlik, Sea of Marmara. As determined by AMS-14C dating of Pontocaspian gastropods (15,860 ± 90 BP uncal.), the age of such fauna is consistent with known episodes of Caspian overflow into the Black Sea Basin (Early Hvalynian floods). The fossil mollusc fauna is relatively diverse (12 non-marine taxa), made up of neritid and hydrobioid gastropods, and dreissenid and lymnocardiine bivalves. The presence of hitherto poorly known Pontocaspian taxa in the Sea of Marmara, further documented by the record in Gulf of Gemlik, seems to document that the Neoeuxinian Sea extended south of the Bosporus in the latest Pleistocene. Further, they provide insight into the origin of the modern Black Sea Pontocaspian taxa. The Gemlik Neoeuxinian lacustrine-brackish fauna under scrutiny is the westernmost known expansion of the Pontocaspian domain during the Late Pleistocene. This distinct biogeographic faunal affinity, with all its eastbound implications in terms of landscape and seaway connections, came to an end with the abrupt marine inundation that accompanied the postglacial sea-level rise from the Mediterranean Sea.

Submarine Paleoseismology Along Populated Transform Boundaries: The Enriquillo-Plantain-Garden Fault, Canal du Sud, Haiti, and the North Anatolian Fault, Marmara Sea, Turkey - McHugh, Cecilia M. G.; Seeber, Leonardo; Cormier, Marie-Helene; Hornbach, Matthew (OCEANOGRAPHY, 2014)
Continental transform boundaries cross heavily populated regions and are associated with destructive earthquakes worldwide. The devastating 1999 Turkey earthquakes and the offshore 2010 Haiti earthquake emphasized the urgent need to study the submerged segments of continental transforms. In response, the rapidly evolving field of submarine paleoseismology is focusing its attention on understanding the relationships between sedimentation, seafloor ruptures, and earthquake recurrence intervals along submarine faults. In Canal du Sud, Haiti, the 2010 earthquake-triggered sedimentation events were documented from nearshore to the deep basin by measuring the excess Th-234 in sediment cores. This radioisotope, with a half-life of 24 days, tracked mass wasting, turbidites, turbidite-homogenite units, and a sediment plume that remained in the water column for at least two months after the earthquake. However, the turbidite units in Canal du Sud, Haiti, provide an incomplete record of the region's earthquake history, likely because sedimentation rates are too low for sedimentation events to be triggered by all earthquakes. In contrast, in the Marmara Sea basins, there is very good correlation between turbidites and the historical record of earthquakes dating back 2,000 years. The difference between these correlations is likely related to both sedimentation rates and particulars of the ruptures. Future research along the Enriquillo-Plantain-Garden fault in Haiti and along similar low sedimentation plate boundaries should focus on multiple fault segments in order to obtain complete earthquake recurrence histories.

Uplift and subsidence reveal a nonpersistent megathrust rupture boundary (Sitkinak Island, Alaska) - Briggs, Richard W.; Engelhart, Simon E.; Nelson, Alan R.; Dura, Tina; Kemp, Andrew C.; Haeussler, Peter J.; Corbett, D. Reide; Angster, Stephen J.; Bradley, Lee-Ann (Geophysical Research Letters, 2014)
We report stratigraphic evidence of land-level change and tsunami inundation along the Alaska-Aleutian megathrust during prehistoric and historical earthquakes west of Kodiak Island. On Sitkinak Island, cores and tidal outcrops fringing a lagoon reveal five sharp lithologic contacts that record coseismic land-level change. Radiocarbon dates, 137Cs profiles, computerized tomography scans, and microfossil assemblages are consistent with rapid uplift circa 290–0, 520–300, and 1050–790 cal yr B.P. and subsidence in A.D. 1964 and circa 640–510 cal yr B.P. Radiocarbon, 137Cs, and 210Pb ages bracketing a sand bed traced 1.5 km inland and evidence for sudden uplift are consistent with Russian accounts of an earthquake and tsunami in A.D. 1788. The mixed uplift and subsidence record suggests that Sitkinak Island sits above a nonpersistent boundary near the southwestern limit of the A.D. 1964 Mw 9.2 megathrust rupture.

Using Natural Abundance Radiocarbon To Trace the Flux of Petrocarbon to the Seafloor Following the Deepwater Horizon Oil Spill - Chanton, Jeffrey; Zhao, Tingting; Rosenheim, Brad E.; Joye, Samantha; Bosman, Samantha; Brunner, Charlotte; Yeager, Kevin M.; Diercks, Arne R.; Hollander, David (Environmental science & technology, 2014)
In 2010, the Deepwater Horizon accident released 4.6?6.0 ? 1011 grams or 4.1 to 4.6 million barrels of fossil petroleum derived carbon (petrocarbon) as oil into the Gulf of Mexico. Natural abundance radiocarbon measurements on surface sediment organic matter in a 2.4 ? 1010 m2 deep-water region surrounding the spill site indicate the deposition of a fossil-carbon containing layer that included 1.6 to 2.6 ? 1010 grams of oil-derived carbon. This quantity represents between 0.5 to 9.1% of the released petrocarbon, with a best estimate of 3.0?4.9%. These values may be lower limit estimates of the fraction of the oil that was deposited on the seafloor because they focus on a limited mostly deep-water area of the Gulf, include a conservative estimate of thickness of the depositional layer, and use an average background or prespill radiocarbon value for sedimentary organic carbon that produces a conservative value. A similar approach using hopane tracer estimated that 4?31% of 2 million barrels of oil that stayed in the deep sea settled on the bottom. Converting that to a percentage of the total oil that entered into the environment (to which we normalized our estimate) converts this range to 1.8 to 14.4%. Although extrapolated over a larger area, our independent estimate produced similar values.; In 2010, the Deepwater Horizon accident released 4.6?6.0 ? 1011 grams or 4.1 to 4.6 million barrels of fossil petroleum derived carbon (petrocarbon) as oil into the Gulf of Mexico. Natural abundance radiocarbon measurements on surface sediment organic matter in a 2.4 ? 1010 m2 deep-water region surrounding the spill site indicate the deposition of a fossil-carbon containing layer that included 1.6 to 2.6 ? 1010 grams of oil-derived carbon. This quantity represents between 0.5 to 9.1% of the released petrocarbon, with a best estimate of 3.0?4.9%. These values may be lower limit estimates of the fraction of the oil that was deposited on the seafloor because they focus on a limited mostly deep-water area of the Gulf, include a conservative estimate of thickness of the depositional layer, and use an average background or prespill radiocarbon value for sedimentary organic carbon that produces a conservative value. A similar approach using hopane tracer estimated that 4?31% of 2 million barrels of oil that stayed in the deep sea settled on the bottom. Converting that to a percentage of the total oil that entered into the environment (to which we normalized our estimate) converts this range to 1.8 to 14.4%. Although extrapolated over a larger area, our independent estimate produced similar values.

Validated age and growth estimates for Carcharhinus obscurus in the northwestern Atlantic Ocean, with pre- and post management growth comparisons - Natanson, Lisa J.; Gervelis, Brian J.; Winton, Megan V.; Hamady, Li Ling; Gulak, Simon J. B.; Carlson, John K. (Environmental Biology of Fishes, 2014)
Age and growth estimates for the dusky shark, Carcharhinus obscurus, were derived from vertebral centra collected in the northwestern Atlantic Ocean. Sample collection spanned the years prior to and following the implementation ofmanagementmeasures (1963– 2010). Growth was compared pre- and post- population depletion and pre- and post- management to investigate the possibility of density-mediated shifts in age and growth parameters over time. There was no evidence of difference between periods for either sex. Additionally, bomb radiocarbon dating was used to determine the periodicity of band pair formation. Results support the traditional interpretation of annual band pairs up to approximately 11 years of age. After this time, vertebral counts considerably underestimate true age. Maximum validated ages were estimated to be between 38 and 42 years of age (an increase of 15 to 19 years over the band count estimates), confirming longevity to at least 42 years of age. Growth curves estimated using only validated data were compared to those generated using band pair counts. Logistic growth parameters derived from validated vertebral length-at-age data were L∞=261.5 cm FL, Lo=85.5 cm, to=4.89 year and g=0.15 year−1 for the sexes combined. Revised estimates of age at maturity were 17.4 years for males and 17.6 years for females.
Keywords: Age and growth; bomb radiocarbon; Dusky shark; Elasmobranch; Validation; Vertebrae

After the lava flow: The importance of external soil sources for plant colonization of recent lava flows in the central Oregon Cascades, USA - Deligne, Natalia I.; Cashman, Katharine V.; Roering, Joshua J. (Geomorphology, 2013)
Effusive volcanic eruptions repave landscapes rapidly with lava flows, resetting broad areas of the underlying landscape and ecosystem. The unique physical properties of lava pose interesting challenges for ecologic recovery, as lava is dense, sterile, and generally inhospitable towards life. In this study we examine two sites of recent volcanism in the central Oregon Cascades, notable for the juxtaposition of barren exposed lava and mature forests on lava flows of the same or roughly the same age. We use a combination of LiDAR analyses, field observations, and soil characterization to examine soil and vegetation at these two sites, and find that the presence of an external sediment or soil source, particularly flood-borne deposits or syn- or post-eruptive tephra, greatly facilitates plant establishment, growth, and survival. The nature of the external sources of sediment or soil dictates the geographic extent of forests on these young lava flows: flood-borne deposits cover localized regions near river channels, while tephra can cover large regions. In general, our results suggest that external sources of soil provide a substrate for plants to grow in along with key nutrients and sufficient moisture retention. We conclude that external sources of soil source are key for the initial recovery following an effusive volcanic disturbance, in particular in temperate climates. Thus, unrelated geomorphic processes, such as past glaciations that provide local sources of mobile sediments, or concurrent volcanic processes, such as tephra production, dictate the presence or absence of forests on young lava flows.
id: 2321

Anatomy of the La Jolla Submarine Canyon system; offshore southern California - Paull, C. K.; Caress, D. W.; Lundsten, E.; Gwiazda, R.; Anderson, K.; McGann, M.; Conrad, J.; Edwards, B.; Sumner, E. J. (Marine Geology, 2013)
An autonomous underwater vehicle (AUV) carrying a multibeam sonar and a chirp profiler was used to map sections of the seafloor within the La Jolla Canyon, offshore southern California, at sub-meter scales. Close-up observations and sampling were conducted during remotely operated vehicle (ROV) dives. Minisparker seismic-reflection profiles from a surface ship help to define the overall geometry of the La Jolla Canyon especially with respect to the pre-canyon host sediments. The floor of the axial channel is covered with unconsolidated sand similar to the sand on the shelf near the canyon head, lacks outcrops of the pre-canyon host strata, has an almost constant slope of 1.0° and is covered with trains of crescent shaped bedforms. The presence of modern plant material entombed within these sands confirms that the axial channel is presently active. The sand on the canyon floor liquefied during vibracore collection and flowed downslope, illustrating that the sediment filling the channel can easily fail even on this gentle slope. Data from the canyon walls help constrain the age of the canyon and extent of incision. Horizontal beds of moderately cohesive fine-grained sediments exposed on the steep canyon walls are consistently less than 1.232 million years old. The lateral continuity of seismic reflectors in minisparker profiles indicate that pre-canyon host strata extend uninterrupted from outside the canyon underneath some terraces within the canyon. Evidence of abandoned channels and point bar-like deposits are noticeably absent on the inside bend of channel meanders and in the subsurface of the terraces. While vibracores from the surface of terraces contain thin (
id: 2302

Bomb radiocarbon dating of the endangered white abalone (Haliotis sorenseni): investigations of age, growth and lifespan - Andrews, Allen H.; Leaf, Robert T.; Rogers-Bennett, Laura; Neuman, Melissa; Hawk, Heather; Cailliet, Gregor M. (Marine and Freshwater Research, 2013)
Understanding basic life-history characteristics of white abalone (Haliotis sorenseni), such as estimated lifespan, is critical to making informed decisions regarding the recovery of this endangered species. All predictive modelling tools used to forecast the status and health of populations following restoration activities depend on a validated estimate of adult lifespan. Of the seven Haliotis species in California, white abalone is considered to have the highest extinction risk and was the first marine invertebrate listed as an endangered species under the Federal Endangered Species Act (ESA). Lifespan was previously estimated from observations of early growth; however, no study has generated ages for the largest white abalone. To address questions of age and growth, bomb radiocarbon (C-14) dating was used on shells from large white abalone. Measured bomb C-14 levels were compared to regional C-14 reference records to provide estimates of age, growth and lifespan. Bomb radiocarbon dating indicated that growth was variable among individuals, with a maximum estimated age of 27 years. The findings presented here provide support for previous age and growth estimates and an estimated lifespan near 30 years. These age data support the perception of a critical need for restoring the remnant aging and potentially senescent population.
id: 2351; PT: J; TC: 0; UT: WOS:000326166400004

Deciphering hemipelagites from homogenites through anisotropy of magnetic susceptibility. Paleoseismic implications (Sea of Marmara and Gulf of Corinth) - Campos, Corina; Beck, Christian; Crouzet, Christian; Demory, François; Van Welden, Aurélien; Eris, Kadir (Sedimentary Geology, 2013)
In closed marine basins and large lakes, gravity re-depositional processes often result in specific turbidites with two abruptly separated layers: a coarse graded lower term and an upper homogenous fine-grained term. An additional mixed term generally occurs in between, indicating to and from particle displacements. The later ones are related to oscillating bottom currents responsible for a high increase of the fine fraction segregation, within the reworked wasted mass. The whole sedimentary event is the association “homogenite + turbidite” (HmTu), which specific a settling condition area here characterized through Anisotropy of Magnetic Susceptibility (AMS). Homogenites's magnetic foliation appears anomalously high with respect to their expected state of compaction, and strikingly higher than hemipelagites's values. We applied this approach to Late Pleistocene/Holocene sediments from the Sea of Marmara and from the Gulf of Corinth. Grain-size and other magnetic parameters related to mineralogy are added to better assess the granular array influence on AMS. As HmTu is considered as often related to earthquake-triggering and tsunami/seiche effects, AMS appears as a useful tool for subaqueous paleoseismic investigations. First, it may evidence the signature of paleo-earthquakes; second, it permits to decipher hemipelagic intervals which are inferred to represent the time elapsed between two successive reworking events.

Evidence for a transgressive barrier within a regressive strandplain system: Implications for complex coastal response to environmental change - Hein, Christopher J.; FitzGerald, Duncan M.; Cleary, William J.; ALBERNAZ, MARCIO B.; De MENEZES, JOAO THADEU; Klein, Antonio H. da F. (Sedimentology, 2013)
Clastic, depositional strandplain systems have the potential to record changes in the primary drivers of coastal evolution: climate, sea-level, and the frequency of major meteorological and oceanographic events. This study seeks to use one such record from a southern Brazilian strandplain to highlight the potentially-complex nature of coastal sedimentological response to small changes in these drivers. Following a 2 to 4 m highstand at ca 5·8 ka in southern Brazil, falling sea-level reworked shelf sediment onshore, forcing coastal progradation, smoothing the irregular coastline and forming the 5 km wide Pinheira Strandplain, composed of ca 500 successive beach and dune ridges. Sediment cores, grab samples and >11 km of ground-penetrating radar profiles reveal that the strandplain sequence is composed of well-sorted, fine to very-fine quartz sand. Since the mid-Holocene highstand, the shoreline prograded at a rate of ca 1 to 2 m yr−1 through the deposition of a 4 to 6 m thick shoreface unit; a 1 to 3 m thick foreshore unit containing ubiquitous ridge and runnel facies; and an uppermost beach and foredune unit. However, the discovery of a linear, 100 m wide barrier ridge with associated washover units, a 3 to 4 m deep lagoon and 250 m wide tidal inlet within the strandplain sequence reveals a period of shoreline transgression at 3·3 to 2·8 ka during the otherwise regressive developmental history of the plain. The protected nature of Pinheira largely buffered it from changes in precipitation patterns, wave energy and fluvial sediment supply during the time of its formation. However, multiple lines of evidence indicate that a change in the rate of relative sea-level fall, probably due to either steric or ice-volume effects, may have affected this coastline. Thus, whereas these other potential drivers cannot be fully discounted, this study provides insights into the complexity of decadal-scale to millennial-scale coastal response to likely variability in sea-level change rates.

Export of submicron particulate organic matter to mesopelagic depth in an oligotrophic gyre - Close, H. G.; Shah, S. R.; Ingalls, A. E.; Diefendorf, A. F.; Brodie, E. L.; Hansman, R. L.; Freeman, K. H.; Aluwihare, L. I.; Pearson, A. (Proceedings of the National Academy of Sciences, 2013)
Sixty percent of the world ocean by area is contained in oligotrophic gyres [Longhurst A (1995) Prog Oceanog 36:77-16], the biomass of which is dominated by picophytoplankton, including cyanobacteria and picoeukaryotic algae, as well as picoheterotrophs. Despite their recognized importance in carbon cycling in the surface ocean, the role of small cells and their detrital remains in the transfer of particulate organic matter (POM) to the deep ocean remains disputed. Because oligotrophic marine conditions are projected to expand under current climate trends, a better understanding of the role of small particles in the global carbon cycle is a timely goal. Here we use the lipid profiles, radiocarbon, and stable carbon isotopic signatures of lipids from the North Pacific Subtropical Gyre to show that in the surface ocean, lipids from submicron POM (here called extra-small POM) are distinct from larger classes of suspended POM. Remarkably, this distinct extra-small POM signature dominates the total lipids collected at mesopelagic depth, suggesting that the lipid component of mesopelagic POM primarily contains the exported remains of small particles. Transfer of submicron material to mesopelagic depths in this location is consistent with model results that claim the biological origin of exported carbon should be proportional to the distribution of cell types in the surface community, irrespective of cell size [Richardson TL, Jackson GA (2007) Science 315:838-840]. Our data suggest that the submicron component of exported POM is an important contributor to the global biological pump, especially in oligotrophic waters.
Keywords: Biogeochemistry; biomarkers; carbon isotopes; Oceanography

First high-resolution marinopalynological stratigraphy of Late Quaternary sediments from the central part of the Bulgarian Black Sea area - Filipova-Marinova, Mariana; Pavlov, Danail; Coolen, Marco; Giosan, Liviu (Advancing Pleistocene and Holocene climate change research in the Carpathian-Balkan region, 2013)
Spores, pollen and dinoflagellate cysts of Late Pleistocene and Holocene sediments were analyzed from Giant Gravity Core 18 from the Black Sea continental slope, recovered from a water depth of 971 m. The investigated length of the core is 203.5 cm. It includes 3 lithological units: light grey clay, sapropels and coccolith-bearing ooze. The core was sampled at 5–10 cm intervals. Sampling of the interval 141.5–126 cm was carried out at every cm. AMS radiocarbon dating of bulk organic carbon was performed on 18 selected sediment layers. This chronological data allowed the first high-resolution pollen stratigraphy of Late Quaternary sediments from the western Black Sea area to be presented. The percentage spore–pollen diagram is divided into 6 local pollen assemblage zones. The trends in the vegetation dynamics and climate changes and the early history of migration of the majority of the arboreal taxa that nowadays occur in the Eastern Balkan Range were traced out. The palynological record suggests that open oak forests were spread in the Eastern Balkan Range at the beginning of the Holocene and shows early migration of the major temperate arboreal species such as Quercus, Ulmus, Tilia and Carpinus betulus. This vegetation palaeosuccession continues with the spreading of mixed oak forests from 8950 until 2620 cal. BP (8650 ± 40 until 3120 ± 35 14C BP) followed by destructive changes due to human impact and climate deterioration. A cooling of Holocene climate that is well known in the North Atlantic region as the “8200 yrs cold event” is identified for the first time in marine records from the Bulgarian Black Sea area. The assemblages of dinoflagellate cysts and acritarchs were investigated to provide a reconstruction of surface seawater salinity and surface seawater temperature changes. Two main dinoflagellate cyst assemblages, one dominated by fresh- to brackish water species such as Spiniferites cruciformis and Pyxidinopsis psilata and a subsequent one, that is characterized by euryhaline marine Mediterranean species such as Lingulodinium machaerophorum, Spiniferites belerius, Spiniferites bentorii, Operculodinium centrocarpum and acritarchs Cymatiosphaera globulosa testified a change in SSS from low salinity (
id: 2330

The Holocene onset in the southwestern South Atlantic - Pivel, M. A. G.; Santarosa, A. C. A.; Toledo, F. A. L.; Costa, K. B. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2013)
In this paper we present a paleoceanographic reconstruction of the southwestern South Atlantic for the past 13 kyr based on faunal and isotopic analysis of planktonic foraminifera from a high-resolution core retrieved at the South Brazil Bight continental slope. Our record indicates that oceanographic changes in the southwestern South Atlantic during the onset of the Holocene were comparable in strength to those that occurred during the Younger Dryas. Full interglacial conditions started abruptly after 8.2 kyr BP with a sharp change in faunal composition and surface hydrography (SST and SSS). Part of the observed events may be explained in terms of changes in thermohaline circulation while the other part suggests a dominant role of winds. Our data indicate that during the Early Holocene upwelling was significantly strengthened in the South Brazil Bight promoting high productivity and preventing the establishment of the typically interglacial menardiiform species. In general terms, oceanographic changes recorded by core KF02 occurred in synchrony with Antarctica's climate.
id: 2323

The Last Glacial: Insights from continuous coring on the New Jersey continental shelf - Christensen, Beth A.; Alexander, Clark; Goff, John A.; Turner, R. Jessica; Austin Jr, James A. (Marine Geology, 2013)
Sedimentation on the Pleistocene New Jersey (NJ) shelf is complex, and results from the interaction of processes chiefly driven by glacioeustatic change. Erosion, non-deposition, downcutting and infilling combine to produce a complicated set of reflectors and sedimentary units that are best interpreted in the shallow subsurface with the aid of high resolution seismic reflection profiling. The highly variable lithology on the shelf has historically been an impediment to significant core recovery in this challenging environment. Coring using the AHC-800 drilling system provided continuous downcore recovery at three sites on the outer shelf. The sites targeted fluvial incisions, channel fill and exposure surfaces associated with glacial lowstands. The exceptional cores were analyzed using an integrated approach. Textural and benthic foraminiferal data were evaluated to determine the environment of deposition and estimate paleodepth. Carbon dating of wood and shell material provides the temporal framework for interpretation and K–Ar dating of hornblende crystals provides insights into the source region of sediments. Our integrated analysis indicates the NJ shelf was a dynamic environment from at least 45 ka. Estimates of sea level from this study are consistent with other studies from the Pleistocene NJ Margin. The oldest sediments (> 36 k.y.) recovered by drilling came from below (Site 3) and above (Site 1) R, a time-transgressive regional unconformity. Best estimates are for formation of R on the mid shelf, between MIS3b and the MIS3b/a transition, ~ 45 ka, under neritic conditions. Channels were incised during late MIS2, between ~ 30 and 16 ka. Channel infill was focused in a narrow time frame, during latest MIS 2 (16–14 ka), shortly after the shoreline began to migrate landward. Rates of 1–2 cm/yr are consistent with modern fluvial/ estuarine sedimentation rates. Reinvigoration and infilling of the channels around 14 ka is associated with meltwater pulse 1A. We find no evidence at our study area for jökelhlaup deposition associated with the Intra-Allerød cold period ~ 13 ka. Regional deposition (channel infill and interfluvial regions) was underway by latest MIS2/early MIS1 as sea level transgressed the shelf. The uppermost sediments are of Holocene to Recent age and are routinely and likely rapidly reworked, eroded and mixed by shelf processes. The sediment source during MIS3, as determined by hornblende age dates, was bimodal. Older sediments were derived from the Reading Prong/NJ Highlands and younger sediments were sourced from along the Hudson River. Delivery to the study area was through a more southerly paleo-Hudson position that may have resulted in formation of the outer shelf wedge through deltaic sedimentation during at least MIS 3b–3a.
id: 2317

Maintenance of large deltas through channelization: Nature vs. humans in the Danube delta - Giosan, Liviu; Constantinescu, Stefan; Filip, Florin; Deng, Bing (Anthropocene, 2013)
Over the last half century, while the total sediment load of the Danube dramatically decreased due to dam construction on tributaries and its main stem, a grand experiment was inadvertently run in the Danube delta: the construction of a dense network of canals, which almost tripled the water discharge toward the interior of the delta plain. We use core-based and chart-based sedimentation rates and patterns to explore the delta transition from the natural to an anthropogenic regime, to understand the effects of far-field damming and near-field channelization, and to construct a conceptual model for delta development as a function sediment partition between the delta plain and the delta coastal fringe. We show that sediment fluxes increased to the delta plain due to channelization counteracting sea level rise. In turn, the delta coastal fringe was most impacted by the Danube's sediment load collapse. Furthermore, we suggest that morphodynamic feedbacks at the river mouth are crucial in trapping sediment near the coast and constructing wave-dominated deltas or lobes. Finally, we suggest that increased channelization that mimics and enhances natural processes may provide a simple solution for keeping other delta plains above sea level and that abandonment of wave-dominated lobes may be the most long term efficient solution for protecting the internal fluvial regions of deltas and provide new coastal growth downcoast.

A model for drowned terrestrial habitats with associated archeological remains in the northwestern Gulf of Maine, USA - Kelley, Joseph T.; Belknap, Daniel F.; Kelley, Alice R.; Claesson, Stefan H. (Marine Geology, 2013)
Marine geophysical techniques and geological measurement of sea-level change allow detailed mapping of seafloor archeological sites and development of models. In the northwestern Gulf of Maine, the lowstand of sea level is only at − 60 m depth, but a prolonged stasis during the late Quaternary sea-level rise, herein termed the slowstand, occurred between 11,500 and 7500 calibrated years before present (cal yr BP) at depths of 15–25 m. This slowdown caused substantial erosion of glacial deposits and formed terrestrial beaches, wetlands and lakes. These landforms attracted people, whose tools were later discovered during present day scallop-fishing activities. Our study areas at the Green Islands and Bass Harbor are within the lowstand and slowstand depth ranges, but at highly exposed and sheltered sites, respectively. The Green Islands site has lost most of its former terrestrial sediment and there is no longer any context for recovered artifacts. At the protected Bass Harbor site, the remains of eroded moraines are associated with drowned spits and a former lacustrine/estuarine basin. Cores at the Bass Harbor location encountered freshwater peat deposits and numerous shallow subtidal shell and plant fossils all deposited during the slowstand. The two most important controls on the preservation of terrestrial landforms and associated human artifacts in the northwestern Gulf of Maine are the rate of sea-level rise and degree of shelter of the site from waves.
id: 2285

Organic carbon export from the Greenland ice sheet - Bhatia, Maya P.; Das, Sarah B.; Xu, Li; Charette, Matthew A.; Wadham, Jemma L.; Kujawinski, Elizabeth B. (Geochimica et Cosmochimica Acta, 2013)
Glacial meltwater exports a unique type of organic carbon to marine systems, distinct from non-glacially derived riverine export, potentially capable of stimulating downstream marine primary productivity. Here, we describe for the first time the bulk-level dissolved organic carbon (DOC) and particulate organic carbon (POC) isotopic composition of glacial meltwater draining the Greenland ice sheet (GrIS). These data, in conjunction with an earlier study that investigated the molecular-level composition of GrIS dissolved organic matter, collectively describe the concentration, radiocarbon content, and lability of organic carbon in subglacial discharge from a land-terminating outlet glacier during a melt season. By scaling up our measurements across the ice sheet, we estimate that the annual DOC flux from the GrIS (0.08 Tg/y) is equivalent to that from a small Arctic river (discharge (Q) 200 km3/y). The DOC flux is derived primarily from beneath the glacier (subglacial) (>75%) in the early season, and from surface ice-melt (up to 100%) transmitting through the subglacial environment at the peak of the meltseason. The POC flux is primarily derived from the subglacial environment throughout the meltseason. The early season (low flow) glacier discharge contains higher DOC concentrations (0.5–4.1 mg L−1), and exports more enriched carbon (Δ14CDOC ∼ −250‰) compared to the peak season (high flow) discharge, when the concentrations are lower (0.1–0.6 mg L−1) and the Δ14C is more depleted (Δ14CDOC ∼ −400‰). Conversely, the POC export (1.4–13.2 mg L−1, Δ14CPOC ∼ −250‰) shows no temporal variation in either concentration or radiocarbon content throughout the meltseason. Dissolved ion loads in concomitant samples reflected the seasonal evolution of the subglacial drainage system, confirming the influence of subglacial hydrology on the composition of the bulk carbon pools. Based on this work, we conclude that (1) different mechanisms control the DOC and POC flux from glacial systems; (2) chemically-distinct DOC pools are accessed by seasonally-evolving hydrological flow-paths; and (3) the GrIS can deliver labile carbon, which may also be 14C-depleted, to downstream proglacial and marine environments.
id: 2276

Persistent export of 231Pa from the deep central Arctic Ocean over the past 35,000 years - Hoffmann, Sharon S.; McManus, Jerry F.; Curry, William B.; Brown-Leger, L. Susan (Nature, 2013)
The Arctic Ocean has an important role in Earth’s climate, both through surface processes1 such as sea-ice formation and transport, and through the production and export of waters at depth that contribute to the global thermohaline circulation2, 3. Deciphering the deep Arctic Ocean’s palaeo-oceanographic history is a crucial part of understanding its role in climatic change. Here we show that sedimentary ratios of the radionuclides thorium-230 (230Th) and protactinium-231 (231Pa), which are produced in sea water and removed by particle scavenging on timescales of decades to centuries, respectively4, record consistent evidence for the export of 231Pa from the deep Arctic and may indicate continuous deep-water exchange between the Arctic and Atlantic oceans throughout the past 35,000 years. Seven well-dated box-core records provide a comprehensive overview of 231Pa and 230Th burial in Arctic sediments during glacial, deglacial and interglacial conditions. Sedimentary 231Pa/230Th ratios decrease nearly linearly with increasing water depth above the core sites, indicating efficient particle scavenging in the upper water column and greater influence of removal by lateral transport at depth. Although the measured 230Th burial is in balance with its production in Arctic sea water, integrated depth profiles for all time intervals reveal a deficit in 231Pa burial that can be balanced only by lateral export in the water column. Because no enhanced sink for 231Pa has yet been found in the Arctic, our records suggest that deep-water exchange through the Fram strait may export 231Pa. Such export may have continued for the past 35,000 years, suggesting a century-scale replacement time for deep waters in the Arctic Ocean since the most recent glaciation and a persistent contribution of Arctic waters to the global ocean circulation.
Keywords: Marine chemistry; Palaeoceanography; Palaeoclimate

Quantifying overwash flux in barrier systems: An example from Martha's Vineyard, Massachusetts, USA - Carruthers, Emily A.; Lane, D. Philip; Evans, Rob L.; Donnelly, Jeffrey P.; Ashton, Andrew D. (Marine Geology, 2013)
Coastal barriers are particularly susceptible to the effects of accelerated sea-level rise and intense storms. Over centennial scales, barriers are maintained via overtopping during storms, which causes deposition of washover fans on their landward sides. Understanding barrier evolution under modern conditions can help evaluate the likelihood of future barrier stability. This study examines three washover fans on the undeveloped south shore of Martha's Vineyard using a suite of vibracores, ground penetrating radar, high resolution dGPS, and LiDAR data. From these data, the volumes of the deposits were determined and range from 2.1 to 2.4 × 104 m3. Two of these overwash events occurred during Hurricane Bob in 1991. The water levels produced by this storm have a calculated return interval of ~ 28 years, implying an onshore sediment flux of 2.4–3.4 m3/m/yr. The third washover was deposited by a nor'easter in January 1997, which has a water level return interval of ~ 6 years, suggesting a flux of 8.5 m3/m/yr. These onshore fluxes are smaller than the erosional flux of sediment resulting from shoreline retreat, suggesting that the barrier is not in long-term equilibrium, a result supported by the thinning of the barrier in recent years.
Keywords: barrier system; Coastal evolution; overwash flux; sea-level rise; storm impacts

Radiocarbon Dating of Basal Peats Supports Separation of Lake Superior from Lakes Michigan-Huron about 1250 years ago - Yu, Shi-Yong; Colman, Steven M.; Milne, Glenn A. (Earth and Planetary Science Letters, 2013)
Lake Superior represents an important component of the aquatic ecosystem in North America. Along its south shore, ongoing lake-level rise, accelerated erosion, and wetland loss are major environmental concerns to coastal communities. A better prediction of the future of this shore requires placing the instrumental lake-level records in a geological context. However, our knowledge of the late-Holocene history of the world's largest freshwater body remains fragmentary. Here we present a sedimentary record of late-Holocene relative lake-level changes by dating transgressive basal peats resting directly on a sandy substrate along a bathymetric gradient in Bark Bay Slough, Wisconsin. Our record shows a moderate lake-level rise at 1.4±0.2 mm/yr from about 2200 to 1250 cal yr BP as a result of relatively slow differential uplift of Bark Bay relative to the controlling outlet at Port Huron. The rise accelerated to 2.3±0.2 mm/yr at about 1250 cal yr BP when Sault Ste. Marie emerged as the controlling outlet, thereby separating Superior from Lakes Michigan–Huron and giving rise to the modern hydrographic regime of the upper Great Lakes. The timing of this event in our record is about 1000 yr later than that estimated in most previous studies, but our data complement and confirm the younger age of lake separation inferred using a different methodology. Our results not only provide pertinent information for hydrological regulation, navigation operation, and infrastructural design in the upper Great Lakes, but also provide insight into freshwater wetland succession on flooded coasts.

Reconstructing 7000 years of North Atlantic hurricane variability using deep-sea sediment cores from the western Great Bahama Bank - Toomey, Michael R.; Curry, William B.; Donnelly, Jeffrey P.; van Hengstum, Peter J. (Paleoceanography, 2013)
[1] Available overwash records from coastal barrier systems document significant variability in North Atlantic hurricane activity during the late Holocene. The same climate forcings that may have controlled cyclone activity over this interval (e.g., the West African Monsoon, El Niño–Southern Oscillation (ENSO)) show abrupt changes around 6000 yrs B.P., but most coastal sedimentary records do not span this time period. Establishing longer records is essential for understanding mid-Holocene patterns of storminess and their climatic drivers, which will lead to better forecasting of how climate change over the next century may affect tropical cyclone frequency and intensity. Storms are thought to be an important mechanism for transporting coarse sediment from shallow carbonate platforms to the deep-sea, and bank-edge sediments may offer an unexplored archive of long-term hurricane activity. Here, we develop this new approach, reconstructing more than 7000 years of North Atlantic hurricane variability using coarse-grained deposits in sediment cores from the leeward margin of the Great Bahama Bank. High energy event layers within the resulting archive are (1) broadly correlated throughout an offbank transect of multi-cores, (2) closely matched with historic hurricane events, and (3) synchronous with previous intervals of heightened North Atlantic hurricane activity in overwash reconstructions from Puerto Rico and elsewhere in the Bahamas. Lower storm frequency prior to 4400 yrs B.P. in our records suggests that precession and increased NH summer insolation may have greatly limited hurricane potential intensity, outweighing weakened ENSO and a stronger West African Monsoon—factors thought to be favorable for hurricane development.

Sea-level change during the last 2500 years in New Jersey, USA - Kemp, Andrew C.; Horton, Benjamin P.; Vane, Christopher H.; Bernhardt, Christopher E.; Corbett, D. Reide; Engelhart, Simon E.; Anisfeld, Shimon C.; Parnell, Andrew C.; Cahill, Niamh (Quaternary Science Reviews, 2013)
Relative sea-level changes during the last ∼2500 years in New Jersey, USA were reconstructed to test if late Holocene sea level was stable or included persistent and distinctive phases of variability. Foraminifera and bulk-sediment δ13C values were combined to reconstruct paleomarsh elevation with decimeter precision from sequences of salt-marsh sediment at two sites using a multi-proxy approach. The additional paleoenvironmental information provided by bulk-sediment δ13C values reduced vertical uncertainty in the sea-level reconstruction by about one third of that estimated from foraminifera alone using a transfer function. The history of sediment deposition was constrained by a composite chronology. An age–depth model developed for each core enabled reconstruction of sea level with multi-decadal resolution. Following correction for land-level change (1.4 mm/yr), four successive and sustained (multi-centennial) sea-level trends were objectively identified and quantified (95% confidence interval) using error-in-variables change point analysis to account for age and sea-level uncertainties. From at least 500 BC to 250 AD, sea-level fell at 0.11 mm/yr. The second period saw sea-level rise at 0.62 mm/yr from 250 AD to 733 AD. Between 733 AD and 1850 AD, sea level fell at 0.12 mm/yr. The reconstructed rate of sea-level rise since ∼1850 AD was 3.1 mm/yr and represents the most rapid period of change for at least 2500 years. This trend began between 1830 AD and 1873 AD. Since this change point, reconstructed sea-level rise is in agreement with regional tide-gauge records and exceeds the global average estimate for the 20th century. These positive and negative departures from background rates demonstrate that the late Holocene sea level was not stable in New Jersey.

Sedimentological and geomorphological imprints of Holocene tsunamis in southwestern Spain: An approach to establish the recurrence period - Ruiz, Francisco; Rodríguez-Vidal, Joaquín; Abad, Manuel; Cáceres, Luis M.; Carretero, María I.; Pozo, Manuel; Rodríguez-Llanes, José M.; Gómez-Toscano, Francisco; Izquierdo, Tatiana; Font, Eric; Toscano, Antonio (Continental Shelf Drowned Landscapes (INQUA-CMP and IGCP-526), 2013)
This paper reviews the sedimentological and geomorphological imprints of prehistoric and historical tsunamis in the four main estuaries of SW Spain. These imprints include beach erosion, filling of intertidal channels, deposition of bioclastic layers, washover fans and reworked aeolian sheets and the breaching of spits and tombolos. Most of these imprints were caused by the 218–209 BC and AD 1755 tsunamis, although evidence of other tsunamis has been identified. In these two events, effects on human populations were severe and diverse, such as human loss of life, changes in coastal settlements and international borders, damage to port infrastructure or flooding of marsh and inhabited areas. New radiocarbon reservoir data were included in order to obtain an approach to the recurrence period of these high-energy events (700–1000 years) in this area.

Separation of Lake Superior from Lakes Michigan–Huron about 1250 yr ago - Yu, Shi-Yong; Colman, Steven M.; Milne, Glenn A. (Earth and Planetary Science Letters, 2013)
Lake Superior represents an important component of the aquatic ecosystem in North America. Along its south shore, ongoing lake-level rise, accelerated erosion, and wetland loss are major environmental concerns to coastal communities. A better prediction of the future of this shore requires placing the instrumental lake-level records in a geological context. However, our knowledge of the late-Holocene history of the world's largest freshwater body remains fragmentary. Here we present a sedimentary record of late-Holocene relative lake-level changes by dating transgressive basal peats resting directly on a sandy substrate along a bathymetric gradient in Bark Bay Slough, Wisconsin. Our record shows a moderate lake-level rise at 1.4±0.2 mm/yr from about 2200 to 1250 cal yr BP as a result of relatively slow differential uplift of Bark Bay relative to the controlling outlet at Port Huron. The rise accelerated to 2.3±0.2 mm/yr at about 1250 cal yr BP when Sault Ste. Marie emerged as the controlling outlet, thereby separating Superior from Lakes Michigan–Huron and giving rise to the modern hydrographic regime of the upper Great Lakes. The timing of this event in our record is about 1000 yr later than that postulated in most previous studies. Our results not only provide pertinent information for hydrological regulation, navigation operation, and infrastructural design in the upper Great Lakes, but also provide insight into freshwater wetland succession on flooded coasts.
id: 2336

Surface production fuels deep heterotrophic respiration in northern peatlands - Elizabeth Corbett, J.; Burdige, David J.; Tfaily, Malak M.; Dial, Angela R.; Cooper, William T.; Glaser, Paul H.; Chanton, Jeffrey P. (Global Biogeochemical Cycles, 2013)
[1] Multiple analyses of dissolved organic carbon (DOC) from pore waters were conducted to define the processes that govern carbon balance in peatlands: (1) source, reactivity, and transport of DOC with respect to vegetation, peat, and age of carbon substrate, (2) reactivity of DOC with respect to molecular size, and (3) lability to photoxidation of surficial DOC. We found that surface organic production fuels heterotrophic respiration at depth in advection-dominated peatlands, especially in fens. Fen DOC was Δ14C enriched relative to the surrounding fen peat, and fen respiration products were similar to this enriched DOC indicating that DOC was the main microbial substrate. Bog DOC was more variable showing either enrichment in ∆14C at depth or ∆14C values that follow peat values. This variability in bogs is probably controlled by the relative importance of vertical transport of labile carbon substrates within the peat profile versus DOC production from bog peat. These results extended our set of observations to 10 years at one bog-fen pair and add two additional bog-fen pairs to our series of observations. Anaerobic incubations of peat, rinsed free of residual DOC, produced DOC and respiration products that were strikingly similar to the peat values in a bog and two fens. This result demonstrated conclusively that downward advection is the process responsible for the presence of modern DOC found at depth in the peat column. Fen DOC has lower C/N values and up to twice as much LMW (<1 kDa) DOC as bogs due to differences in organic inputs and greater microbial processing. Fluorescence irradiation experiments showed that fen DOC is more photolabile than bog DOC.

Transient stratification as the cause of the North Pacific productivity spike during deglaciation - Lam, Phoebe J.; Robinson, Laura F.; Blusztajn, Jerzy; Li, Camille; Cook, Mea S.; McManus, Jerry F.; Keigwin, Lloyd D. (Nature Geoscience, 2013)
During the Bølling–Allerød warm period of the last deglaciation, about 14 kyr ago, there was a strong and pervasive spike in primary productivity in the North Pacific Ocean1. It has been suggested that this productivity event was caused by an influx of the micronutrient iron from surrounding continental shelves as they were flooded by sea-level rise2. Here we test this hypothesis by comparing numerous proxies of productivity with iron flux and provenance measured from a core from the subarctic Pacific Ocean. We find no evidence for an abrupt deglacial pulse of iron from any source at the time of peak productivity. Instead, we argue that the deglacial productivity peak was caused by two stepwise events. First, deep convection during early deglaciation increased nutrient supply to the surface but also increased the depth of the mixed layer, which pushed surface production deeper in the water column and induced light limitation. A subsequent input of meltwater from northern American ice sheets then stratified the water column, which relieved light limitation while leaving the surface waters enriched in nutrients. We conclude that iron plays, at most, a secondary role in controlling productivity during the glacial and deglacial periods in the subarctic Pacific Ocean.
Keywords: Biogeochemistry; Marine biology; Marine chemistry; Palaeoceanography

An ~11,200 cal yr BP paleolimnological perspective for the archeological findings at Quartz Lake, Alaska - Wooller, M. J.; Kurek, J.; Gaglioti, B. V.; Cwynar, L. C.; Bigelow, N.; Reuther, J. D.; Gelvin-Reymiller, C.; Smol, J. P. (Journal of Paleolimnology, 2012)
Wetlands and lakes in the Tanana Valley, Alaska, have provided important resources for prehistoric humans who inhabited this region. We examine an ~11,200 cal yr BP record of environmental and paleolimnological changes from Quartz Lake in the middle Tanana Valley. Our data are also presented in the context of recent archaeological findings in the lake’s general vicinity that have 18 associated AMS 14C dates. We analyzed the stable-carbon and nitrogen isotope composition of total organic matter from the core, coupled with oxygen and carbon isotope analyses of Pisidiidae shells (fingernail clams), in addition to chironomid assemblage changes. Lacustrine sediments began to accumulate at ~11,200 cal yr BP. Initially, autochthonous production was low and allochthonous organic input was negligible between 11,000 and 10,500 cal yr BP, and were associated with relatively cool conditions at Quartz Lake at ~10,700 cal yr BP. After 10,500 cal yr BP, autochthonous production was higher coincident with a shift to chironomid assemblages dominated by taxa associated with warmer summer climates. A decrease in δ13C values of total organic carbon (TOC) and organic content of the sediment between 9,000 and 4,000 cal yr BP may indicate declining autochthonous primary production. This period ended with an abrupt (~7 ‰) decrease in the δ18O values from Pisidiidae shells at ~3,000 cal yr BP, which we hypothesize represented an episodic connection (flood) of the lake with flow from the nearby (~6 km) Tanana River. Our findings coincide with evidence for major flooding at other locations connected to the Tanana River and further afield in Alaska. From ~3,000 cal yr BP Quartz Lake subsequently appeared to become a relatively closed system, as indicated by the δ18OPisidiidae and δ13CPisidiidae data that are positively correlated and generally higher, which also correlates with a shift to moderately higher abundances of littoral chironomids. The cause of the transition to closed-basin conditions may have been geomorphic rather than climatic. This evidence of a progressively stronger evaporative influence on the lake’s closed hydrology after ~3,000 cal yr BP is consistent with our modern δ18O and δD water data from Quartz Lake that plot along a regional evaporative line we base on isotopic measurements from other local lakes and rivers.
id: 2134

Central Arctic paleoceanography for the last 50 kyr based on ostracode faunal assemblages - Poirier, Robert K.; Cronin, Thomas M.; Briggs Jr, William M.; Lockwood, Rowan (Marine Micropaleontology, 2012)
The paleoceanography of the central Arctic Ocean was reconstructed for the last 50 kyr (Marine Isotope Stages (MIS) 1–3) based on ostracode assemblages from 21 14C-dated sediment cores from the Mendeleev, Lomonosov, and Gakkel Ridges. Arctic sediments deposited during the Holocene interglacial period (MIS 1), the Bølling–Allerød, and larger interstadial Dansgaard–Oeschger (DO) events (3–4, 8, and 12) contain abundant Cytheropteron spp., Henryhowella asperrima, and Krithe spp. at intermediate/deep-depths (~ 1000 to 3000 m). These assemblages suggest a ventilated deep, Arctic Ocean water mass similar to the modern Arctic Ocean Deep Water (AODW) during these time periods. In contrast, sediment deposited during stadial events corresponding to Heinrich events 1, 2, 3, and 4, (also possibly the Younger Dryas; YD), contain abundant Polycope spp. (60–80%) suggesting a greater influence of the Atlantic Layer (AL) on the Arctic Intermediate Water (AIW) and AODW. Reduced sea-ice during the early Holocene, the last deglacial, and MIS 3 interstadials is indicated by the reoccurrence of Acetabulastoma arcticum, an epipelagic species that is parasitic on sea-ice dwelling amphipods. One hypothesis to explain these oceanographic changes during longer stadial events, particularly within the last glacial period (MIS 2), involves sluggish ocean circulation, thicker sea-ice cover, and a deeper halocline with ocean exchange between Greenland Sea and Arctic Ocean deep-water through the Fram Strait.
id: 2283

Chemical weathering and provenance evolution of Holocene–Recent sediments from the Western Indus Shelf, Northern Arabian Sea inferred from physical and mineralogical properties - Limmer, David R.; Köhler, Cornelia M.; Hillier, Stephen; Moreton, Steven G.; Tabrez, Ali R.; Clift, Peter D. (Marine Geology, 2012)
We present a multi-proxy mineral record based on X-ray diffraction and diffuse reflectance spectrophotometry analysis for two cores from the western Indus Shelf in order to reconstruct changing weathering intensities, sediment transport, and provenance variations since 13 ka. Core Indus-10 is located northwest of the Indus Canyon and exhibits fluctuations in smectite/(illite + chlorite) ratios that correlate with monsoon intensity. Higher smectite/(illite + chlorite) and lower illite crystallinity, normally associated with stronger weathering, peaked during the Early–Mid Holocene, the period of maximum summer monsoon. Hematite/goethite and magnetic susceptibility do not show clear co-variation, although they both increase at Indus-10 after 10 ka, as the monsoon weakened. At Indus-23, located on a clinoform just west of the canyon, hematite/goethite increased during a period of monsoon strengthening from 10 to 8 ka, consistent with increased seasonality and/or reworking of sediment deposited prior to or during the glacial maximum. After 2 ka terrigenous sediment accumulation rates in both cores increased together with redness and hematite/goethite, which we attribute to widespread cultivation of the floodplain triggering reworking, especially after 200 years ago. Over Holocene timescales sediment composition and mineralogy in two localities on the high-energy shelf were controlled by varying degrees of reworking, as well as climatically modulated chemical weathering.
id: 2271

Clay mineral variations in Holocene terrestrial sediments from the Indus Basin - Alizai, Anwar; Hillier, Stephen; Clift, Peter D.; Giosan, Liviu; Hurst, Andrew; VanLaningham, Sam; Macklin, Mark (Quaternary Research, 2012)
We employed X-ray diffraction methods to quantify clay mineral assemblages in the Indus Delta and flood plains since ~ 14 ka, spanning a period of strong climatic change. Assemblages are dominated by smectite and illite, with minor chlorite and kaolinite. Delta sediments integrate clays from across the basin and show increasing smectite input between 13 and 7.5 ka, indicating stronger chemical weathering as the summer monsoon intensified. Changes in clay mineralogy postdate changes in climate by 5–3 ka, reflecting the time needed for new clay minerals to form and be transported to the delta. Samples from the flood plains in Punjab show evidence for increased chemical weathering towards the top of the sections (6–
id: 2333

Climatic and environmental evolution of Lake Iznik (NW Turkey) over the last ∼4700 years - Ülgen, Umut Barış; Franz, Sven Oliver; Biltekin, Demet; Çağatay, M. Namik; Roeser, Patricia Angelika; Doner, Lisa; Thein, Jean (Temporal and spatial corridors of Homo sapiens sapiens population dynamics during the Late Pleistocene and Early Holocene, 2012)
Magnetic susceptibility, geochemistry, mineralogy and palynology of sediments from Lake Iznik in Northwestern Anatolia, Turkey, provide a 4700 year record of climatic trends and events. The measured proxies allow a reconstruction of variations in humid/dry periods and lake level changes. The Lake Iznik sedimentary sequence points to an oscillating trend of humid periods interrupted by rapid climate change (RCC) to arid periods. Especially abrupt lithologic and geochemical changes at 4.2 and 3.3 ka calBP may outline intense droughts, which extremely lowered the lake level. For the last 2000 years, the effects of the Roman warm period, Dark Age cold period, Medieval Warm Period and Little Ice Age are recorded within Lake Iznik sediments. Besides many similarities of local climatic periods with other records from the Eastern Mediterranean, there are also differences indicating the complex pattern of the climate in the region.
id: 2337

Composition and fate of gas and oil released to the water column during the Deepwater Horizon oil spill - Reddy, Christopher M.; Arey, J. Samuel; Seewald, Jeffrey S.; Sylva, Sean P.; Lemkau, Karin L.; Nelson, Robert K.; Carmichael, Catherine A.; McIntyre, Cameron P.; Fenwick, Judith; Ventura, G. Todd; Van Mooy, Benjamin A. S.; Camilli, Richard (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Quantitative information regarding the endmember composition of the gas and oil that flowed from the Macondo well during the Deepwater Horizon oil spill is essential for determining the oil flow rate, total oil volume released, and trajectories and fates of hydrocarbon components in the marine environment. Using isobaric gas-tight samplers, we collected discrete samples directly above the Macondo well on June 21, 2010, and analyzed the gas and oil. We found that the fluids flowing from the Macondo well had a gas-to-oil ratio of 1,600 standard cubic feet per petroleum barrel. Based on the measured endmember gas-to-oil ratio and the Federally estimated net liquid oil release of 4.1 million barrels, the total amount of C-1-C-5 hydrocarbons released to the water column was 1.7 x 10(11) g. The endmember gas and oil compositions then enabled us to study the fractionation of petroleum hydrocarbons in discrete water samples collected in June 2010 within a southwest trending hydrocarbon-enriched plume of neutrally buoyant water at a water depth of 1,100 m. The most abundant petroleum hydrocarbons larger than C-1-C-5 were benzene, toluene, ethylbenzene, and total xylenes at concentrations up to 78 mu gL(-1). Comparison of the endmember gas and oil composition with the composition of water column samples showed that the plume was preferentially enriched with water-soluble components, indicating that aqueous dissolution played a major role in plume formation, whereas the fates of relatively insoluble petroleum components were initially controlled by other processes.
id: 2247; PT: J; TC: 10; UT: WOS:000312605600028

Corrigendum to “Timing and duration of North American glacial lake discharges and the Younger Dryas climate reversal” [Quaternary Research 75 (2011) 541–551] - Rayburn, John A.; Cronin, Thomas M.; Franzi, David A.; Knuepfer, Peter L. K.; Willard, Debra A. (Quaternary Research, 2012)
id: 2156

Early stall of West Antarctic Ice Sheet advance on the eastern Ross Sea middle shelf followed by retreat at 27,500 14C yr BP - Bart, Philip J.; Cone, Amy N. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
Marine geological and geophysical data suggest that the West Antarctic Ice Sheet (WAIS) deposited three thick seismically-resolvable units in the eastern Ross Sea since the Last Glacial Maximum (LGM) but the chronology of these grounding events is debated. Existing ice-retreat chronologies for the eastern Ross Sea are considered suspect because nearly all have been developed using radiocarbon dating of acid-insoluble organics (AIO) from bulk sediment. We used a new strategy to isolate in situ forams from diamict sediment deposited at the middle-shelf grounding-zone wedge (GZW) — a subaqueous ice-marginal landform previously interpreted to represent deposition during the third grounding event since the LGM advance to the shelf edge. Here we present a synthesis of our new radiocarbon dates of foram tests and AIO with previously published radiocarbon dates. We propose that the WAIS's LGM advance in the eastern-Ross Sea sector reached the middle shelf circa 27,500 14C yr BP and that open-marine sedimentation began shortly thereafter. There is as of yet no clear explanation for why WAIS retreat in this sector of Antarctica apparently began prior to the peak of the last glacial cold period. A precipitation deficit, localized warm water intrusion, an ice dynamic response in the absence of climate forcing or another as of yet unknown forcing mechanism could be responsible.
id: 2170

ENSO Drove 2500-Year Collapse of Eastern Pacific Coral Reefs - Toth, L. T.; Aronson, R. B.; Vollmer, S. V.; Hobbs, J. W.; Urrego, D. H.; Cheng, H.; Enochs, I. C.; Combosch, D. J.; van Woesik, R.; Macintyre, I. G. (Science, 2012)
Cores of coral reef frameworks along an upwelling gradient in Panamá show that reef ecosystems in the tropical eastern Pacific collapsed for 2500 years, representing as much as 40% of their history, beginning about 4000 years ago. The principal cause of this millennial-scale hiatus in reef growth was increased variability of the El Niño–Southern Oscillation (ENSO) and its coupling with the Intertropical Convergence Zone. The hiatus was a Pacific-wide phenomenon with an underlying climatology similar to probable scenarios for the next century. Global climate change is probably driving eastern Pacific reefs toward another regional collapse.

Evaluation of sediment trace metal records as paleoproductivity and paleoxygenation proxies in the upwelling center off Concepción, Chile (36°S) - Muñoz, Praxedes; Dezileau, Laurent; Lange, Carina; Cardenas, Lissette; Sellanes, Javier; Salamanca, Marco A.; Maldonado, Antonio (Variability of the coastal upwelling and coastal transition zones off central-southern Chile, 2012)
This study analyzes the records of several trace metals sensitive to redox conditions in continental shelf sediments off Concepción, Chile (36°S). The continental margin off Concepción (36°S; 73°W) lies beneath an important upwelling center characterized by high primary production rates and, consequently, high fluxes of organic matter. In spring and summer, this material settles to the seafloor where it decays, producing periods of very low oxygen content in bottom waters (1 mL L−1). The goals of this study were to determine the input of trace metals to the sediment and to decipher how this information can be used to reveal variations in primary productivity or bottom oxygenation. Gravity cores collected at two stations – VG06-2 over the mid-shelf station (88 m water depth, upper boundary of the oxygen minimum zone) and VG06-3 over the outer shelf (120 m water depth, within the oxygen minimum zone) – were sampled for high resolution profiles (1 cm) of trace metals, biogenic opal, stable isotopes, and total organic carbon. The results suggest that the variability in the trace metal distribution on the continental shelf off Concepción is determined by redox conditions and the organic carbon flux to the bottom. Some sections of the sediment cores from the outer shelf showed appreciable authigenic enrichment of U, Cd, and Mo (EF: 5–10, 2–5, and 10–16 respectively) along with heavier values of δ15N, suggesting periods of suboxic conditions. During these periods, fluxes of organic material to the bottom were higher, as indicated by elevated TOC and opal contents. Alternating periods of higher and lower trace metal contents were not observed mid-shelf as they were on the outer shelf. Rather, the mid-shelf samples showed authigenic enrichment of U, Cd, and Mo (EF: 1–6, 4–5, and 10–20, respectively) throughout the core except in a 10-cm-thick gray layer. In general, authigenic enrichment of U, Mo, and Cd occurred at both sites, coincident with olive green layers in the cores. These layers were associated with periods of elevated primary productivity and suboxic conditions. Such periods did not seem to last as long as the oxygenated periods, which had higher inputs of refractive detrital material, coincident with the occurrence of distinct gray sediment layers.
id: 2154

Geologic methane seeps along boundaries of Arctic permafrost thaw and melting glaciers - Walter Anthony, Katey M.; Anthony, Peter; Grosse, Guido; Chanton, Jeffrey (Nature Geoscience, 2012)
Methane, a potent greenhouse gas, accumulates in subsurface hydrocarbon reservoirs, such as coal beds and natural gas deposits. In the Arctic, permafrost and glaciers form a ‘cryosphere cap’ that traps gas leaking from these reservoirs, restricting flow to the atmosphere. With a carbon store of over 1,200 Pg, the Arctic geologic methane reservoir is large when compared with the global atmospheric methane pool of around 5 Pg. As such, the Earth’s climate is sensitive to the escape of even a small fraction of this methane. Here, we document the release of 14C-depleted methane to the atmosphere from abundant gas seeps concentrated along boundaries of permafrost thaw and receding glaciers in Alaska and Greenland, using aerial and ground surface survey data and in situ measurements of methane isotopes and flux. We mapped over 150,000 seeps, which we identified as bubble-induced open holes in lake ice. These seeps were characterized by anomalously high methane fluxes, and in Alaska by ancient radiocarbon ages and stable isotope values that matched those of coal bed and thermogenic methane accumulations. Younger seeps in Greenland were associated with zones of ice-sheet retreat since the Little Ice Age. Our findings imply that in a warming climate, disintegration of permafrost, glaciers and parts of the polar ice sheets could facilitate the transient expulsion of 14C-depleted methane trapped by the cryosphere cap.
Keywords: Biogeochemistry; Cryospheric science

Late-Pleistocene to Holocene sedimentary fills of the Çınarcık Basin of the Sea of Marmara - Eriş, K. Kadir; Çağatay, Namık; Beck, Christian; Mercier de Lepinay, Bernard; Corina, Campos (Sedimentary Geology, 2012)
A giant RV Marion Dufresne piston core MD01-2425 recovered from the 1276 m-deep Çınarcık Basin of the Sea of Marmara documents characteristics of deep basin sedimentation influenced by large-scale gravity-controlled mass-wasting processes and associated turbidite deposition during the Late Pleistocene to Holocene. A visual lithological description of the core reveals twenty major seismoturbidite layers (> 20 cm thick), intercalated in hemipelagic-type fine-grained calcareous and slightly siliceous clays. The thickness and frequency of the sesimoturbidite layers deposited during the lacustrine period (prior to 12.3 cal ka BP) is much greater than during the Holocene marine period. The sedimentary processes during deposition of seismoturbidites in the basin have been determined in this study using a combination of grain-size parameters. Often the seismoturbidites show strong grain segregation with a sharp boundary between a coarse lower and a homogeneous upper part. The traction carpet deposits formed at the base of a turbulent suspension and were produced in the lower coarse-grained part, whereas the homogeneous upper part was deposited by uniform suspensions following bedload deposition.
id: 2309

Marine radiocarbon reservoir corrections (∆R) for Chesapeake Bay and the Middle Atlantic Coast of North America - Rick, Torben C.; Henkes, Gregory A.; Lowery, Darrin L.; Colman, Steven M.; Culleton, Brendan J. (Quaternary Research, 2012)
Radiocarbon dates from known age, pre-bomb eastern oyster (Crassostrea virginica) shells provide local marine reservoir corrections (∆R) for Chesapeake Bay and the Middle Atlantic coastal area of eastern North America. These data suggest subregional variability in ∆R, ranging from 148 ± 46 14C yr on the Potomac River to − 109 ± 38 14C yr at Swan Point, Maryland. The ∆R weighted mean for the Chesapeake's Western Shore (129 ± 22 14C yr) is substantially higher than the Eastern Shore (− 88 ± 23 14C yr), with outer Atlantic Coast samples falling between these values (106 ± 46 and 2 ± 46 14C yr). These differences may result from a combination of factors, including 14C-depleted freshwater that enters the bay from some if its drainages, 14C-depleted seawater that enters the bay at its mouth, and/or biological carbon recycling. We advocate using different subregional ∆R corrections when calibrating 14C dates on aquatic specimens from the Chesapeake Bay and coastal Middle Atlantic region of North America.
id: 2155

The Medieval Climate Anomaly in the Iberian Peninsula reconstructed from marine and lake records - Moreno, Ana; Pérez, Ana; Frigola, Jaime; Nieto-Moreno, Vanesa; Rodrigo-Gámiz, Marta; Martrat, Belén; González-Sampériz, Penélope; Morellón, Mario; Martín-Puertas, Celia; Corella, Juan Pablo; Belmonte, Ánchel; Sancho, Carlos; et al. (Quaternary Science Reviews, 2012)
Selected multi-proxy and accurately dated marine and terrestrial records covering the past 2000 years in the Iberian Peninsula (IP) facilitated a comprehensive regional paleoclimate reconstruction for the Medieval Climate Anomaly (MCA: 900–1300 AD). The sequences enabled an integrated approach to land–sea comparisons and, despite local differences and some minor chronological inconsistencies, presented clear evidence that the MCA was a dry period in the Mediterranean IP. It was a period characterized by decreased lake levels, more xerophytic and heliophytic vegetation, a low frequency of floods, major Saharan eolian fluxes, and less fluvial input to marine basins. In contrast, reconstruction based on sequences from the Atlantic Ocean side of the peninsula indicated increased humidity. The data highlight the unique characteristics of the MCA relative to earlier (the Dark Ages, DA: ca 500–900 years AD) and subsequent (the Little Ice Age, LIA: 1300–1850 years AD) colder periods. The reconstruction supports the hypothesis of Trouet et al. (2009), that a persistent positive mode of the North Atlantic Oscillation (NAO) dominated the MCA.
id: 2334

Paleoenvironmental changes on the northeastern and southwestern Black Sea shelves during the Holocene - Ivanova, Elena V.; Murdmaa, Ivar O.; Karpuk, Maria S.; Schornikov, Eugene I.; Marret, Fabienne; Cronin, Thomas M.; Buynevich, Ilya V.; Platonova, Elena A. (Quaternary International, 2012)
Four paleoceanographic events are distinguished during the Holocene based on changes in macro- and microfossil assemblages studied from three sediment cores (Ak 521, 522, 2571) from the outer northeast shelf and from core MAR02-45 situated on the southwest shelf of the Black Sea, west to the Bosphorus. The lithology and fossils were previously studied from cores Ak 521 and Ak 522 and MAR02-45. However, high resolution ostracod analyses from the AMS-14C dated core, Ak 2571, allowed for a revision of the taxonomy and paleoecological interpretation of this microfaunal group on the NE shelf. Downcore changes in the relative abundance of the polyhaline ostracods are found to be contemporaneous in all three cores from the NE shelf. As a result, centennial-millennial scale fluctuations of the bottom-water salinity are resolved in the area. A broader scale examination of paleoenvironmental changes between the NE and SW shelves is also made and the surface to bottom salinity gradient is discussed. An uncalibrated radiocarbon based chronology is used throughout this paper to facilitate comparison with the regional chronostratigraphy of marine transgression and regressions in the Black Sea. The calibrated ages corrected for the changes in reservoir age through the Holocene are also provided. The first paleoceanographic event is associated with the pulse of Mediterranean water previously established at about 9.8–9.3 ka BP. This event is clearly observed in the SW region but not on the NE shelf due to a hiatus in the longest core, Ak 521. The second event is represented on both the NE and SW shelves as a replacement of brackish benthic fauna and surface phytoplankton with marine ones between 8.4 and 6.9 ka BP, indicating a gradual increase in salinity. The third event is marked by opposing trends in surface and bottom-water salinity changes. On the NE shelf, bottom-water salinity rose to modern values by ∼ 6.5 ka BP and then decreased within the interval ∼6.4–5.3 ka BP as recorded by the ostracod assemblages. On the SW shelf, surface-water salinity reached modern values by 5.6 ka BP and remained constant until present day as inferred from the dinoflagellate cyst assemblages. The fourth event is marked by a recurring increase in bottom-water salinity to modern values indicated by the polyhaline ostracod assemblages at ∼ 5.3 ka BP in the NE region, after which only minor salinity fluctuations are observed.
id: 2123

Pre-Columbian fire regimes in lowland tropical rainforests of southeastern Peru - McMichael, C. H.; Correa-Metrio, A.; Bush, M. B. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
We document the fire history of the forests of a well-studied ecological research station (Los Amigos) in western Amazonia through soil charcoal analysis, and compare results with data from a nearby lake district known to have supported pre-Columbian human populations. We present novel methods of soil charcoal analysis that improve on its current limitations by accounting for variability in post-fire charcoal deposition, problematic age–depth relationships, and the presence of weathered or regionally-deposited charcoal particles that allow statistical comparisons of fire history characteristics between regions. The fire histories indicate that the research station experienced less intensive historical fire and pre-Columbian disturbance than the lake district. Dated charcoal particles indicated that while soil depth could not be used to predict fire age, fragments below 20 cm depth were generally older than 500 years. Frequent fires have not occurred in either region during the last 1000 years, but fire events in both regions were significantly synchronous from 1000 to 4000 cal. yr BP. The sampling design and methods that provide an ecologically and statistically valid avenue for comparing fire history characteristics between regions can be modified to suit other ecosystems. The results presented here establish confidence that the patterns and processes of the lowland tropical rainforests studied at Los Amigos are not affected by intense or recurrent historical fires. These data also suggest that forests of Madre de Dios, Peru are not post-successional remnants of a ‘cultural parkland’, as suggested by some Amazonian archeologists.
id: 2307

Radiocarbon evidence that carbon from the Deepwater Horizon spill entered the planktonic food web of the Gulf of Mexico - Chanton, J. P.; Cherrier, J.; Wilson, R. M.; Sarkodee-Adoo, J.; Bosman, S.; Mickle, A.; Graham, W. M. (ENVIRONMENTAL RESEARCH LETTERS, 2012)
The Deepwater Horizon (Macondo) oil spill released large volumes of oil and gas of distinct carbon isotopic composition to the northern Gulf of Mexico, allowing Graham et al (2010 Environ. Res. Lett. 5 045301) to use stable carbon isotopes (delta C-13) to infer the introduction of spilled oil into the planktonic food web. Surface ocean organic production and measured oil are separated by 5-7 parts per thousand in stable carbon isotope (delta C-13) space, while in radiocarbon (Delta C-14) space these two potential sources are separated by more than 1000 parts per thousand. Thus radiocarbon isotopes provide a more sensitive tracer by which to infer possible introduction of Macondo oil into the food web. We measured Delta C-14 and delta C-13 in plankton collected from within 100 km of the spill site as well as in coastal and offshore DIC (dissolved inorganic carbon or Sigma CO2) to constrain surface production values. On average, plankton values were depleted in C-14 relative to surface DIC, and we found a significant linear correlation between Delta C-14 and delta C-13 in plankton. Cumulatively, these results are consistent with the hypothesis that carbon released from the Deepwater Horizon spill contributed to the offshore planktonic food web. Our results support the findings of Graham et al (2010 Environ. Res. Lett. 5 045301), but we infer that methane input may be important.
Keywords: carbon isotope; Gulf oil spill; methane; petroleum hydrocarbon; radiocarbon

Radiocarbon evidence that carbon from the Deepwater Horizon spill entered the planktonic food web of the Gulf of Mexico - Chanton, J P; Cherrier, J; Wilson, R M; Sarkodee-Adoo, J; Bosman, S; Mickle, A; Graham, W M (Environmental Research Letters, 2012)
The Deepwater Horizon (Macondo) oil spill released large volumes of oil and gas of distinct carbon isotopic composition to the northern Gulf of Mexico, allowing Graham et al (2010 Environ. Res. Lett. 5 045301) to use stable carbon isotopes (δ13C) to infer the introduction of spilled oil into the planktonic food web. Surface ocean organic production and measured oil are separated by 5–7‰ in stable carbon isotope (δ13C) space, while in radiocarbon (Δ14C) space these two potential sources are separated by more than 1000‰. Thus radiocarbon isotopes provide a more sensitive tracer by which to infer possible introduction of Macondo oil into the food web. We measured Δ14C and δ13C in plankton collected from within 100 km of the spill site as well as in coastal and offshore DIC (dissolved inorganic carbon or ΣCO2) to constrain surface production values. On average, plankton values were depleted in 14C relative to surface DIC, and we found a significant linear correlation between Δ14C and δ13C in plankton. Cumulatively, these results are consistent with the hypothesis that carbon released from the Deepwater Horizon spill contributed to the offshore planktonic food web. Our results support the findings of Graham et al (2010 Environ. Res. Lett. 5 045301), but we infer that methane input may be important.

Refining the model of barrier island formation along a paraglacial coast in the Gulf of Maine - Hein, Christopher J.; FitzGerald, Duncan M.; Carruthers, Emily A.; Stone, Byron D.; Barnhardt, Walter A.; Gontz, Allen M. (Marine Geology, 2012)
Details of the internal architecture and local geochronology of Plum Island, the longest barrier in the Gulf of Maine, have refined our understanding of barrier island formation in paraglacial settings. Ground-penetrating radar and shallow-seismic profiles coupled with sediment cores and radiocarbon dates provide an 8000-year evolutionary history of this barrier system in response to changes in sediment sources and supply rates as well as variability in the rate of sea-level change. The barrier sequence overlies tills of Wisconsinan and Illinoian glaciations as well as late Pleistocene glaciomarine clay deposited during the post-glacial sea-level highstand at approximately 17 ka. Holocene sediment began accumulating at the site of Plum Island at 7–8 ka, in the form of coarse fluvial channel-lag deposits related to the 50-m wide erosional channel of the Parker River that carved into underlying glaciomarine deposits during a lower stand of sea level. Plum Island had first developed in its modern location by ca. 3.6 ka through onshore migration and vertical accretion of reworked regressive and lowstand deposits. The prevalence of southerly, seaward-dipping layers indicates that greater than 60% of the barrier lithosome developed in its modern location through southerly spit progradation, consistent with a dominantly longshore transport system driven by northeast storms. Thinner sequences of northerly, landward-dipping clinoforms represent the northern recurve of the prograding spit. A 5–6-m-thick inlet-fill sequence was identified overlying the lower stand fluvial deposit; its stratigraphy captures events of channel migration, ebb-delta breaching, onshore bar migration, channel shoaling and inlet infilling associated with the migration and eventual closure of the inlet. This inlet had a maximum cross-sectional area of 2800 m2 and was active around 3.5–3.6 ka. Discovery of this inlet suggests that the tidal prism was once larger than at present. Bay infilling, driven by the import of sediment into the backbarrier environment through tidal inlets, as well as minor sediment contribution from local rivers, led to a vast reduction in the bay tidal prism. This study demonstrates that, prior to about 3 ka, Plum Island and its associated marshes, tidal flats, and inlets were in a paraglacial environment; that is, their main source of sediment was derived from the erosion and reworking of glaciogenic deposits. Since that time, Plum Island has been in a state of dynamic equilibrium with its non-glacial sediment sources and therefore can be largely considered to be in a stable, “post-paraglacial” state. This study is furthermore the first in the Gulf of Maine to show that spit accretion and inlet processes were the dominant mechanisms in barrier-island formation and thus serves as a foundation for future investigations of barrier development in response to backbarrier infilling.
Keywords: barrier-island formation; ground-penetrating radar; inlet processes; inlet-fill sequence; paraglacial; spit accretion

Small-scale lacustrine drifts in Lake Champlain, Vermont - Manley, Patricia L.; Manley, T. O.; Hayo, Kathryn; Cronin, Thomas (Journal of Great Lakes Research, 2012)
High resolution CHIRP (Compressed High Intensity Radar Pulse) seismic profiles reveal the presence of two lacustrine sediment drifts located in Lake Champlain's Juniper Deep. Both drifts are positive features composed of highly laminated sediments. Drift B sits on a basement high while Drift A is built on a trough-filling acoustically-transparent sediment unit inferred to be a mass-transport event. These drifts are oriented approximately north–south and are parallel to a steep ridge along the eastern shore of the basin. Drift A, located at the bottom of a structural trough, is classified as a confined, elongate drift that transitions northward to become a system of upslope asymmetric mudwaves. Drift B is perched atop a structural high to the west of Drift A and is classified as a detached elongate drift. Bottom current depositional control was investigated using Acoustic Doppler Current Profilers (ADCPs) located across Drift A. Sediment cores were taken at the crest and at the edges of the Drift A and were dated. Drift source, deposition, and evolution show that these drifts are formed by a water column shear with the highest deposition occurring along its crest and western flank and began developing circa 8700–8800 year BP.
id: 2179

Stratigraphic evidence for an early Holocene earthquake in Aceh, Indonesia - Grand Pre, C.; Horton, B. P.; Kelsey, H. M.; Rubin, C. M.; Hawkes, A. D.; Daryono, M.; Rosenberg, G.; Culver, S. J. (Quaternary Science Reviews, 2012)
The Holocene stratigraphy of the coastal plain of the Aceh Province of Sumatra contains 6 m of sediment with three regionally consistent buried soils above pre-Quaternary bedrock or pre-Holocene unconsolidated sediment. Litho-, bio-, and chronostratigraphic analyses of the lower buried soil reveals a rapid change in relative sea-level caused by coseismic subsidence during an earlyHolocene megathrust earthquake. Evidence for paleoseismic subsidence is preserved as a buried mangrove soil, dominated by a pollen assemblage of Rhizophora and/or Bruguiera/Ceriops taxa. The soil is abruptly overlain by a thin tsunami sand. The sand contains mixed pollen and abraded foraminiferal assemblages of both offshore and onshore environments. The tsunami sand grades upward into mud that contains both well-preserved foraminifera of intertidal origin and individuals of the gastropod Cerithidea cingulata. Radiocarbon ages from the pre- and post-seismic sedimentary sequences constrain the paleoearthquake to 6500–7000 cal. yrs. BP. We use micro-and macrofossil data to determine the local paleoenvironment before and after the earthquake. We estimate coseismic subsidence to be 0.45 ± 0.30 m, which is comparable to the 0.6 m of subsidence observed during the 2004 Aceh–Andaman earthquake on Aceh’s west coast.
id: 2139

The application of foraminifera to reconstruct the rate of 20th century sea level rise, Morbihan Golfe, Brittany, France - Rossi, V.; Horton, B. P.; Corbett, D. R.; Leorri, E.; Perez-Belmonte, L.; Douglas, B. C. (Quaternary Research, 2011)
Foraminiferal assemblages preserved within salt-marsh sediment can provide an accurate and precise means to reconstruct relative sea level due to a strong relationship with elevation, which can be quantified using a transfer function. We collected a set of surface samples from two salt marshes in the Morbihan Golfe, France to determine foraminiferal distribution patterns. Dominant taxa included Jadammina macrescens, Trochammina inflata, Haplophragmoides spp. and Miliammina fusca. We developed a foraminifera-based transfer function using a modern training set of 36 samples and 23 species. The strong relationship between observed and predicted values (r(jack)(2) = 0.7) indicated that foraminiferal distribution is primarily controlled by elevation with respect to the tidal frame and precise reconstructions of former sea level are possible (RMSEP(jack) = 0.07 m). The application of the transfer function to a short salt-marsh core (0.32 m) allowed the reconstruction of former sea levels, which were placed in a chronological framework using short-lived radionuclides ((210)Pb and (137)Cs). The agreement between the foraminifera-based sea level curve and the Brest tide-gauge record confirms the reliability of transfer function estimates and the validity of this methodology to extend sea level reconstructions back into the pre-instrumental period. Both instrumental and microfossil records suggest an acceleration of sea level rise during the 20th century. (C) 2010 University of Washington. Published by Elsevier Inc. All rights reserved.
id: 1889; 713FR Times Cited:1 Cited References Count:71submittedY

Bomb-produced radiocarbon validation of growth-increment crossdating allows marine paleoclimate reconstruction - Kastelle, Craig R.; Helser, Thomas E.; Black, Bryan A.; Stuckey, Matthew J.; C. Gillespie, Darlene; McArthur, Judy; Little, Diana; D. Charles, Karen; Khan, Reziah S. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
The bivalve Pacific geoduck (Panopea generosa) has been used in the eastern North Pacific Ocean to create proxies for environmental factors such as temperature and oceanographic conditions. This type of research depends upon accurate age determination of Pacific geoducks, which historically was based on shell growth-increment counts. A recent study comparing age estimates generated by the dendrochronology (tree-ring science) procedure of crossdating to those estimated from growth-increment counts found a significant difference between the methods for geoduck older than 30 years. Compared to the traditional age determination method of counting growth increments, the crossdating method estimates a greater longevity in this species, with some individuals living in excess of 150 years. In the present study, the accuracy of each method was independently assessed using bomb-produced radiocarbon (14C) techniques. Specimens whose birth years were estimated to be within the era of the bomb-produced marine 14C increase and where the differences between ages estimated by the two methods were greatest were selected for 14C analysis. The difference between age estimates from traditional growth-increment counts and those from crossdating was evaluated using their respective 14C chronologies in comparisons to a reference chronology as a standard. The comparisons relied on Bayesian nonlinear models using Markov Chain Monte Carlo simulation. This method of analysis showed that with a 50% probability geoducks were aged correctly when using the crossdating method, compared to the growth increment counts which had a 50% probability of underestimating the age by 4 years. Therefore, the crossdated age estimates were found to be more accurate than increment counts. Furthermore, these results provide new confidence in using Pacific geoduck biochronologies for paleoclimate and paleoenvironmental reconstruction.
id: 2167

East–West similarities and differences in the surface and deep northern Arabian Sea records during the past 21 Kyr - Gupta, Anil K.; Mohan, K.; Sarkar, Sudipta; Clemens, Steven C.; Ravindra, Rasik; Uttam, Rajesh K. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
This study analyses monsoon proxy Globigerina bulloides from Ocean Drilling Program (ODP) Hole 723A (western Arabian Sea) and Hole ABP-25, 02 (northeastern Arabian Sea) as well as dominant benthic foraminifera, pteropods, total organic carbon (TOC), Inorganic Carbon (IC) and stable isotope values of benthic foraminifera from Hole ABP-25, 02 to understand summer monsoon-driven changes in the western and eastern Arabian Sea and their impacts on deep-sea ventilation during the past 21 Kyr. We have also combined published TOC data from ODP Hole 724B to understand if deep-sea conditions in the Arabian Sea were same throughout the region during the studied interval. The summer monsoon was generally weaker during cold intervals including the Last Glacial Maximum, the Younger Dryas and the Bond events of the Holocene. From 20 to 10 Kyr, the deep northeastern Arabian Sea was better oxygenated with less organic carbon supply except during 14–12.5 Kyr when TOC values increased, indicating a weaker summer monsoon and a weak oxygen minimum zone (OMZ). The TOC values and the abundance of the eutrophic benthic foraminiferal species Bulimina aculeata, Melonis barleeanum and Uvigerina peregrina increased during the late Holocene whereas well-oxygenated, low organic carbon benthic species Sphaeroidina bulloides as well as pteropods decreased, indicating an intense OMZ and an increased supply of refractory organic material to the Arabian Sea. It is important to note that although the surface response to monsoon variability was more or less similar in the western and northeastern Arabian Sea, the deep-sea conditions show a marked contrast in the two regions during the past 21 Kyr.
id: 2100

Fire history and human activities during the last 3300 cal yr BP in Spain's Central Pyrenees: The case of the Estany de Burg - Bal, Marie-Claude; Pelachs, Albert; Perez-Obiol, Ramon; Julia, Ramon; Cunill, Raquel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
The study of macroscopic charcoal particles from peat bogs has led to a better understanding of climate, vegetation and fire history, and human impacts. To determine the relationship between human activities and the role of fire events in vegetation change during the last 3300 cal yr BP, we present the results of a multi-proxy approach based on the analysis of sediment characteristics, sedimentary charcoal, organic matter and pollen, as well as historical sources. This multi-proxy research permits high resolution palaeoenvironmental and fire history reconstruction of a mountain area located in the southern central Pyrenees (Spain). In the Pyrenees, fire is typically attributed to human activities since the beginning of the Bronze Age and may be correlated with slash-and-burn cultivation, metallurgy and pasturing activities. The data indicate a good linkage between high fire signals and Poaceae and Cerealia pollen, which reveals the impact of agro-pastoral practices. This study also shows two periods, 2900–2650 cal yr BP and 1850–1550 cal yr BP, for which higher frequencies of fire occurred, suggested by high arboreal pollen (AP) concentrations, and confirming the need for arboreal biomass to sustain fires. From the beginning of the Middle Ages, it seems that a change occurred in the anthropogenic use of fire, from a tool for agro-pastoral forest clearance to a means of maintaining open spaces.
id: 2196

Geological legacy of storm erosion along a high-energy indented coastline: northern Santa Catarina, Brazil - Buynevich, I. V.; Klein, A. H. F.; FitzGerald, D. M.; Cleary, W. J.; Hein, C.; Veiga, F. A.; Angulo, R. J.; Asp, N. E.; Petermann, R. (Journal of Coastal Research, 2011)
Along moderate to high-energy sandy coasts of the world, periods of accretion are often punctuated by episodes of erosion and retreat. However documenting the legacy of such events in sand-dominated sequences remains a challenge. The present-day moderate-relief coastlines of Camboriú Peninsula (CP) and the adjacent Navegantes coastal plain in Santa Catarina, Brazil, exhibit a variety of geological features related to recent intense storms, such as the Santa Catarina cyclone of record (March 2004) and subsequent events. These systems offer an opportunity to assess the use of modern indicators of storm erosion as a guide to reconstructing their counterparts from the sedimentary record. The 0.5-2.0-km-long, headland-segmented, coarse-grained, reflective beaches of the Camboriú Peninsula contrast with a 10-km-long, fine-grained, dissipative beach of the Navegantes plain. Morphological indicators of erosion include steep dune and berm scarps, as well as ephemeral washout channels produced by rainfall-induced runoff. Where modified by subsequent deposition, these features can still be identified by their diagnostic reflection geometries and variable-angle truncations (disconformities) in highresolution ground-penetrating radar (GPR) images. In addition to morphological indicators of erosion, coastal sedimentary sequences contain distinct lithological anomalies. Heavy-mineral concentrations (HMCs) are easily identifiable in sediment cores and trenches and produce strong reflections on GPR images. Along Estaleiro Beach (CP), a buried disconformity was identified in GPR images beneath a road, approximately 25 m landward of the November 2004 storm scarp. Its geometry is similar to the recent scarp and its strong geophysical signal return is due to a magnetite-enriched horizon at a depth of 2.6 m. At the Navegantes strandplain, patchy thin layers enriched in fine-grained heavy minerals are common on a gently sloping intertidal beach and near the base of foredunes. Moreover, in the landward portion of the plain that developed during the past 2,000 years, the presence of truncated tangential-oblique reflections in GPR records and HMCs reaching 10-30 cm in thickness indicates past reworking of beach and dune sediments by a series of intense erosional episodes. Low-field magnetic susceptibility measurements of vibracores indicate values from thick HMC layers exceeding 1,000 (*10-5 SI) in contrast to 0−15 (*10-5 SI) for background quartz-rich sands. Given the relatively constant background fraction of heavy minerals in beach sands, the thickness and degree of concentration in HMCs can be used as proxies for the relative impact of high-energy events, including their duration and magnitude. Despite the apparent low preservation potential of these features on high-energy coasts, post-storm accretion and rapid progradation increase their chances of being removed from wave action.
id: 2125

Geological slip rates along the North Anatolian Fault in the Marmara region - Gasperini, Luca; Polonia, Alina; Çağatay, M. Namik; Bortoluzzi, Giovanni; Ferrante, Valentina (Tectonics, 2011)
Reliable piercing points on both sides of the Sea of Marmara enabled us to obtain an estimate of the slip-rate over time scales of 10-15 ka on different fault strands of the North Anatolian Fault (NAF) system. We analyzed geomorphic features in the gulfs of Izmit, Gemlik (Sea of Marmara) and Saros (NE Aegean Sea), which were passively displaced by the NAF strands after their abandonment related to the post-glacial sea level rise. Results for the main northern strand, consistently similar on both sides of the Marmara pull-apart, are in the order of 10 mm/yr, about one half of that expected from geodetic measurements and accepted plate-tectonic models. In the southern branch of the NAF, the estimated rate of similar to 4 mm/yr is only slightly higher than that given by geodetic models. Our findings have implications for both neo-tectonic reconstructions of the submerged portion of the NAF system, and fault interactions and seismic hazard estimates in the Marmara region. They suggest that, either the total Anatolia/Eurasia plate motion is more diffuse than previously reported, or geodetic data are not representative of the geological time-scale deformations. Moreover, they suggest that a significant amount of stress is accommodated along the southern strand of the NAF system, on which the last large (M approximate to 7) earthquakes dates back to 1419, 1855 and 1863 AD.
id: 2112; PT: J; TC: 0; J9: TECTONICS; UT: WOS:000296619700001

Late glacial to Holocene sea-level changes in the Sea of Marmara: new evidence from high-resolution seismics and core studies - Eriş, Kürşad Kadir; Cagatay, M. N.; Akcer, Sena; Gasperini, Luca; Mart, Yosi (Geo-Marine Letters, 2011)
The late glacial to Holocene sedimentary record of the northern shelf of the Sea of Marmara (SoM) has been documented by detailed seismo-, chrono-, and biostratigraphic analyses using sub-bottom (Chirp) profiles and sediment cores. During MIS 3 and the main part of MIS 2 (60-15 (14)C ka b.p.), disconnection from the Mediterranean and Black seas together with a dry climate resulted in a regression in the SoM, when the Sea was transformed into a brackish lake. The river incisions below 105 m water depth along the northern shelf took place during the last glacial maximum, when the lake level was modulated by stillstands at -98 and -93 m. The post-glacial freshwater transgressive stage of the Marmara 'Lake' occurred between 15 and 13.5 (14)C ka b.p., leading to a rise in water level to -85 m by 13.0 (14)C ka b.p., as evidenced by broad wave-cut terraces along the northern shelf. Since 12 (14)C ka b.p., high-frequency sea-level fluctuations have been identified at the SoM entrance to the Strait of A degrees stanbul (SoI). Thus, wave-cut terraces have been recorded at water depths of -76 and -71 m that, according to an age model for core MD04-2750, have ages of 11.5 and 10.5 (14)C ka b.p., respectively. Ancient shoreline at -65 m along the northern shelf presumably formed soon after the Younger Dryas (YD) at ca. 10.1 (14)C ka b.p. Moreover, there is compelling evidence of Holocene outflow from the Sea of Marmara to the Black Sea. At the SoM entrance to the SoI, the existence of bioherms on the reflector surface together with abundant Brizalina spathulata and Protoglobulimina pupoides in a core suggests a return to higher salinities due to strong Mediterranean water incursion into the SoM at similar to 8.8 (14)C ka b.p. This finding is consistent with earlier suggestions that, after the YD, the Black Sea was flooded by outflow from the SoM as a result of global sea-level rise.
id: 2113; PT: J; TC: 0; J9: GEO-MAR LETT; UT: WOS:000286334700001

Late Quaternary environmental change inferred from phytoliths and other soil-related proxies: Case studies from the central and southern Great Plains, USA - Cordova, Carlos E.; Johnson, William C.; Mandel, Rolfe D.; Palmer, Michael W. (Catena, 2011)
This study investigates stable carbon isotopes (delta(13)C), opal phytolith assemblages, burnt phytoliths, microscopic charcoal and Sporormiella spores from modern soils and paleosols in Kansas and Oklahoma. Grass and dicot phytoliths in combination with delta(13)C are used as proxies for reconstructing the structure of grasslands and woodlands. Burnt grass phytoliths and microscopic charcoal are evaluated as proxies for reconstructing paleofire incidence. Concentrations of the fungal spore Sporormiella are used as a proxy for assessing large herbivore activity. These proxies were tested on various modern grassland communities of the central and southern Great Plains, including areas with bison, cattle, and small herbivores, and areas under different fire frequencies. Opal phytolith assemblages and delta(13)C values show that before cal 11 ka, C(3) grasses and woody plants predominated in areas that today are dominated by C(4) grasses. The origin of the shortgrass prairie dates back to about cal 10 ka. The origin of the tallgrass prairie, however, is not clear as phytolith data show variable assemblages throughout the Holocene (mixed-grass, tallgrass, and tallgrass-woodland mosaic). Different proxies (burnt phytoliths vs. charcoal) reveal different fire frequencies, but it is apparent that microfossil evidence for fire incidence is closely related to the abundance of woody plants in the landscape. Before cal 12 ka, soils show somewhat elevated concentration of Spororrniella, but lower concentrations than the modern high-density bison and cattle grazing areas. Throughout the Holocene. Sporormiella frequencies are low, which suggests lower large ungulate densities and perhaps high mobility. (C) 2010 Elsevier B.V. All rights reserved.
id: 1992; PT: J; SI: SI; UT: WOS:000288642200002

Methane hydrate-bearing seeps as a source of aged dissolved organic carbon to the oceans - Pohlman, John W.; Bauer, James E.; Waite, William F.; Osburn, Christopher L.; Chapman, N. Ross (Nature Geoscience, 2011)
Marine sediments contain about 500-10,000 Gt of methane carbon(1-3), primarily in gas hydrate. This reservoir is comparable in size to the amount of organic carbon in land biota, terrestrial soils, the atmosphere and sea water combined(1,4), but it releases relatively little methane to the ocean and atmosphere(5). Sedimentary microbes convert most of the dissolved methane to carbon dioxide(6,7). Here we show that a significant additional product associated with microbial methane consumption is methane-derived dissolved organic carbon. We use Delta(14)C and delta(13)C measurements and isotopic mass-balance calculations to evaluate the contribution of methane-derived carbon to seawater dissolved organic carbon overlying gas hydrate-bearing seeps in the northeastern Pacific Ocean. We show that carbon derived from fossil methane accounts for up to 28% of the dissolved organic carbon. This methane-derived material is much older, and more depleted in (13)C, than background dissolved organic carbon. We suggest that fossil methane-derived carbon may contribute significantly to the estimated 4,000-6,000 year age of dissolved organic carbon in the deep ocean(8), and provide reduced organic matter and energy to deep-ocean microbial communities.
id: 2030; PT: J; UT: WOS:000285498600015

Micropaleontologic record of Quaternary paleoenvironments in the Central Albemarle Embayment, North Carolina, U.S.A - Culver, Stephen J.; Farrell, Kathleen M.; Mallinson, David J.; Willard, Debra A.; Horton, Benjamin P.; Riggs, Stanley R.; Thieler, E. Robert; Wehmiller, John F.; Parham, Peter; Snyder, Scott W.; Hillier, Caroline (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
To understand the temporal and spatial variation of eustatic sea-level fluctuations, glacio–hydro–isostacy, tectonics, subsidence, geologic environments and sedimentation patterns for the Quaternary of a passive continental margin, a nearly complete stratigraphic record that is fully integrated with a three dimensional chronostratigraphic framework, and paleoenvironmental information are necessary. The Albemarle Embayment, a Cenozoic regional depositional basin in eastern North Carolina located on the southeast Atlantic coast of the USA, is an ideal setting to unravel these dynamic, interrelated processes. Micropaleontological data, coupled with sedimentologic, chronostratigraphic and seismic data provide the bases for detailed interpretations of paleoenvironmental evolution and paleoclimates in the 90 m thick Quaternary record of the Albemarle Embayment. The data presented here come from a transect of cores drilled through a barrier island complex in the central Albemarle Embayment. This area sits in a ramp-like setting between late Pleistocene incised valleys. The data document the episodic infilling of the Albemarle Embayment throughout the Quaternary as a series of transgressive–regressive (T–R) cycles, characterized by inner shelf, midshelf, and shoreface assemblages, that overlie remnants of fluvial to estuarine valley-fill. Barrier island and marginal marine deposits have a low preservation potential. Inner to mid-shelf deposits of the early Pleistocene are overlain by similar middle Pleistocene shelf sediments in the south of the study area but entirely by inner shelf deposits in the north. Late Pleistocene marine sediments are of inner shelf origin and Holocene deposits are marginal marine in nature. Pleistocene marine sediments are incised, particularly in the northern half of the embayment by lowstand paleovalleys, partly filled by fluvial/floodplain deposits and in some cases, overlain by remnants of transgressive estuarine sediments. The shallowing through time of Quaternary sediments reflects the eastward progradational geometry of the continental shelf. The preservation potential of marginal marine deposits (barrier island, shoreface, backbarrier deposits) is not high, except in topographic lows associated with late Pleistocene paleovalleys and inlets because the current interglacial highstand has not yet reached its highest level. Given the documented increase in rate of relative sea-level rise in this region, shallow marine conditions are likely to return to the central Albemarle Embayment in the near future.
id: 2182

Pb isotopic variability in the modern-Pleistocene Indus River system measured by ion microprobe in detrital K-feldspar grains - Alizai, Anwar; Clift, Peter D.; Giosan, Liviu; VanLaningham, Sam; Hinton, Richard; Tabrez, Ali R.; Danish, Muhammad (Geochimica et Cosmochimica Acta, 2011)
The western Himalaya, Karakoram and Tibet are known to be heterogeneous with regard to Pb isotope compositions in K-feldspars, which allows this system to be used as a sediment provenance tool. We used secondary ion mass spectrometry to measure the isotopic character of silt and sand-sized grains from the modern Sutlej and Chenab Rivers, together with Thar Desert sands, in order to constrain their origin. The rivers show a clear Himalayan provenance, contrasting with grains from the Indus Suture Zone, but with overlap to known Karakoram compositions. The desert dunes commonly show 207Pb/204Pb and 206Pb/204Pb values that are much higher than those seen in the rivers, most consistent with erosion from Nanga Parbat. This implies at least some origin from the trunk Indus, probably reworked by summer monsoon winds from the SW, a hypothesis supported by bulk Nd and U–Pb zircon dating. Further data collected from Holocene and Pleistocene sands shows that filled and abandoned channels on the western edge of the Thar Desert were sourced from Himalayan rivers before and at 6–8 ka, but that after that time the proportion of high isotopic ratio grains rose, indicating increased contribution from the Thar Desert dunes prior to ∼4.5 ka when flow ceased entirely. This may be linked to climatic drying, northward expansion of the Thar Desert, or changes in drainage style including regional capture, channel abandonment, or active local Thar tributaries. Our data further show a Himalayan river channel east of the present Indus, close to the delta, in the Nara River valley during the middle Holocene. While this cannot be distinguished from the Indus it is not heavily contaminated by reworking from the desert. The Pb system shows some use as a provenance tool, but is not effective at demonstrating whether these Nara sediments represent a Ghaggar-Hakra stream independent from the Indus. Our study highlights an important role for eolian reworking of floodplain sediments in arid rivers such as the Indus.
id: 2171

The Posidonia oceanica marine sedimentary record: A Holocene archive of heavy metal pollution - Serrano, O.; Mateo, M. A.; Dueñas-Bohórquez, A.; Renom, P.; López-Sáez, J. A.; Martínez Cortizas, A. (Science of The Total Environment, 2011)
The study of a Posidonia oceanica mat (a peat-like marine sediment) core has provided a record of changes in heavy metal abundances (Fe, Mn, Ni, Cr, Cu, Pb, Cd, Zn, As and Al) since the Mid-Holocene (last 4470 yr) in Portlligat Bay (NW Mediterranean). Metal contents were determined in P. oceanica. Both, the concentration records and the results of principal components analysis showed that metal pollution in the studied bay started ca. 2800 yr BP and steadily increased until present. The increase in Fe, Cu, Pb, Cd, Zn and As concentrations since ca. 2800 yr BP and in particular during Greek (ca. 2680–2465 cal BP) and Roman (ca. 2150–1740 cal BP) times shows an early anthropogenic pollution rise in the bay, which might be associated with large- and short-scale cultural and technological development. In the last ca. 1000 yr the concentrations of heavy metals, mainly derived from anthropogenic activities, have significantly increased (e.g. from ~ 15 to 47 μg g− 1 for Pb, ~ 23 to 95 μg g− 1 for Zn and ~ 8 to 228 μg g− 1 for As). Our study demonstrates for the first time the uniqueness of P. oceanica meadows as long-term archives of abundances, patterns, and trends of heavy metals during the Late Holocene in Mediterranean coastal ecosystems.
id: 2098

Rapid Holocene coastal change revealed by high-resolution micropaleontological analysis, Pamlico Sound, North Carolina, USA - Grand Pre, Candace; Culver, Stephen J.; Mallinson, David J.; Farrell, Kathleen M.; Corbett, D. Reide; Horton, Benjamin P.; Hillier, Caroline; Riggs, Stanley R.; Snyder, Scott W.; Buzas, Martin A. (Quaternary Research, 2011)
Foraminiferal analyses of 404 contiguous samples, supported by diatom, lithologic, geochronologic and seismic data, reveal both rapid and gradual Holocene paleoenvironmental changes in an 8.21-m vibracore taken from southern Pamlico Sound, North Carolina. Data record initial flooding of a latest Pleistocene river drainage and the formation of an estuary 9000 yr ago. Estuarine conditions were punctuated by two intervals of marine influence from approximately 4100 to 3700 and 1150 to 500 cal yr BP. Foraminiferal assemblages in the muddy sand facies that accumulated during these intervals contain many well-preserved benthic foraminiferal species, which occur today in open marine settings as deep as the mid shelf, and significant numbers of well-preserved planktonic foraminifera, some typical of Gulf Stream waters. We postulate that these marine-influenced units resulted from temporary destruction of the southern Outer Banks barrier islands by hurricanes. The second increase in marine influence is coeval with increased rate of sea-level rise and a peak in Atlantic tropical cyclone activity during the Medieval Climate Anomaly. This high-resolution analysis demonstrates the range of environmental variability and the rapidity of coastal change that can result from the interplay of changing climate, sea level and geomorphology in an estuarine setting.
id: 2164

Rapid wetland expansion during European settlement and its implication for marsh survival under modern sediment delivery rates - Kirwan, M. L.; Murray, A. B.; Donnelly, J. P.; Corbett, D. R. (Geology, 2011)
Fluctuations in sea-level rise rates are thought to dominate the formation and evolution of coastal wetlands. Here we demonstrate a contrasting scenario in which land-use-related changes in sediment delivery rates drive the formation of expansive marshland, and vegetation feedbacks maintain their morphology despite recent sediment supply reduction. Stratigraphic analysis and radiocarbon dating in the Plum Island Estuary (Massachusetts, United States) suggest that salt marshes expanded rapidly during the eighteenth and nineteenth centuries due to increased rates of sediment delivery following deforestation associated with European settlement. Numerical modeling coupled with the stratigraphic observations suggests that existing marshland could survive, but not form under the low suspended sediment concentrations observed in the estuary today. These results suggest that many of the expansive marshes that characterize the modern North American coast are metastable relicts of high nineteenth century sediment delivery rates, and that recent observations of degradation may represent a slow return to pre-settlement marsh extent. In contrast to ecosystem management practices in which restoring pre-anthropogenic conditions is seen as a way to increase ecosystem services, our results suggest that widespread efforts to restore valuable coastal wetlands actually prevent some systems from returning to a natural state.
id: 846; 748TX Times Cited:2 Cited References Count:31under reviewY

Rare earth element geochemistry in the inner shelf of the East China Sea and its implication to sediment provenances - Xu, Fangjian; Li, Anchun; Li, Tiegang; Xu, Kehui; Chen, Shiyue; Qiu, Longwei; Cao, Yingchang (Journal of Rare Earths, 2011)
Gravity core EC2005, located in the mud wedge off the Zhejiang-Fujian coast in the inner shelf of the East China Sea (ECS), was analyzed for its lithology, grain size, rare earth elements (REE) and AMS14C dating. Results revealed high-resolution paleoenvironmental evolution and multiple switches of sediment provenances in the inner shelf of ECS. The lithology, grain size and REE concentrations of sediments varied significantly down the core. Mean grain size ranged from 8 to 121 μm, and the values of ΣREE were 152.8–227.9 μg/g. The chondrite- and shale-normalized REE patterns indicated their similarity to the terrigenous sediments in the study area. Between 17.3–12.3 ka BP the sediments in the inner shelf of ECS were mainly originated from local drainage basins. The source then gradually switched to the Yangtze River between 12.3 and 9.8 ka BP. Since about 10–9.8 ka BP, the sediments in the study area were dominantly derived from the Yangtze River. The continuous rising of sea level and formation of coastal current along the inner shelf played a key role in the switches of sediment provenances.
id: 2177

Rates and Mechanisms of Mineral Carbonation in Peridotite: Natural Processes and Recipes for Enhanced, in situ CO 2 Capture and Storage - Kelemen, Peter B.; Matter, Juerg; Streit, Elisabeth E.; Rudge, John F.; Curry, William B.; Blusztajn, Jerzy (Annual Review of Earth and Planetary Sciences, 2011)
Near-surface reaction of CO2-bearing fluids with silicate minerals in peridotite and basalt forms solid carbonate minerals. Such processes form abundant veins and travertine deposits, particularly in association with tectonically exposed mantle peridotite. This is important in the global carbon cycle, in weathering, and in understanding physical-chemical interaction during retrograde metamorphism. Enhancing the rate of such reactions is a proposed method for geologic CO2 storage, and perhaps for direct capture of CO2 from near-surface fluids. We review, synthesize, and extend inferences from a variety of sources. We include data from studies on natural peridotite carbonation processes, carbonation kinetics, feedback between permeability and volume change via reaction-driven cracking, and proposed methods for enhancing the rate of natural mineral carbonation via in situ processes ("at the outcrop") rather than ex situ processes ("at the smokestack").

Response of a marine-terminating Greenland outlet glacier to abrupt cooling 8200 and 9300 years ago - Young, ás E.; Briner, Jason P.; Axford, Yarrow; Csatho, Beata; Babonis, Greg S.; Rood, Dylan H.; Finkel, Robert C. (Geophysical Research Letters, 2011)
Long-term records of Greenland outlet-glacier change extending beyond the satellite era can inform future predictions of Greenland Ice Sheet behavior. Of particular relevance is elucidating the Greenland Ice Sheet's response to decadal- and centennial-scale climate change. Here, we reconstruct the early Holocene history of Jakobshavn Isbræ, Greenland's largest outlet glacier, using 10Be surface exposure ages and 14C-dated lake sediments. Our chronology of ice-margin change demonstrates that Jakobshavn Isbræ advanced to deposit moraines in response to abrupt cooling recorded in central Greenland ice cores ca. 8,200 and 9,300 years ago. While the rapid, dynamically aided retreat of many Greenland outlet glaciers in response to warming is well documented, these results indicate that marine-terminating outlet glaciers are also able to respond quickly to cooling. We suggest that short lag times of high ice flux margins enable a greater magnitude response of marine-terminating outlets to abrupt climate change compared to their land-terminating counterparts.

Response of Jakobshavn Isbrae, Greenland, to Holocene climate change - Young, N. E.; Briner, J. P.; Stewart, H. A. M.; Axford, Y.; Csatho, B.; Rood, D. H.; Finkel, R. C. (Geology, 2011)
Rapid fluctuations in the velocity of Greenland Ice Sheet (GIS) outlet glaciers over the past decade have made it difficult to extrapolate ice-sheet change into the future. This significant short-term variability highlights the need for geologic records of preinstrumental GIS margin fluctuations in order to better predict future GIS response to climate change. Using 10Be surface exposure ages and radiocarbon-dated lake sediments, we constructed a detailed chronology of ice-margin fluctuations over the past 10 k.y. for Jakobshavn Isbræ, Greenland's largest outlet glacier. In addition, we present new estimates of corresponding local temperature changes using a continuous record of insect (Chironomidae) remains preserved in lake sediments. We find that following an early Holocene advance just prior to 8 ka, Jakobshavn Isbræ retreated rapidly at a rate of ∼100 m yr−1, likely in response to increasing regional and local temperatures. Ice remained behind its present margin for ∼7 k.y. during a warm period in the middle Holocene with sustained temperatures ∼2 °C warmer than today, then the land-based margin advanced at least 2–4 km between A.D. 1500–1640 and A.D. 1850. The ice margin near Jakobshavn thus underwent large and rapid adjustments in response to relatively modest centennial-scale Holocene temperature changes, which may foreshadow GIS response to future warming.

Sea level controls sedimentation and environments in coastal caves and sinkholes - van Hengstum, Peter J.; Scott, David B.; Groecke, Darren R.; Charette, Matthew A. (Marine Geology, 2011)
Quaternary climate and sea-level research in coastal karst basins (caves, cenotes, sinkholes, blueholes, etc.) generally focuses on analyzing isotopes in speleothems, or associating cave elevations prior sea-level highstands. The sediments in coastal karst basins represent an overlooked source of climate and sea-level information in the coastal zone, but to accurately interpret these sediments first requires an understanding of the forcing mechanisms that emplace them. In this study, we hypothesize that coastal karst basins transition through vadose, littoral, anchialine, and finally into submarine environments during sea-level rise because groundwater and sea level oscillate in near synchrony in the coastal zone, causing each environment to deposit a unique sedimentary facies. To test this hypothesis, the stratigraphy in twelve sediment cores from a Bermudian underwater cave (Green Bay Cave) was investigated and temporally constrained with twenty radiocarbon dates. The results indicate that we recovered the first succession spanning the entire Holocene from an underwater cave (similar to 13 ka to present). The sediments were characterized with X-radiography, fossil remains, bulk organic matter, organic geochemistry (delta(13)C(org), C:N), and grain size analysis. Four distinct facies represent the four depositional environments: (i) vadose facies (>7.7 ka, calcite rafts lithofacies), (ii) littoral facies (7.7 to 7.3 ka: calcite rafts and mud lithofacies), (iii) anchialine facies (7.3 to 1.6 ka: slackwater and diamict lithofacies), and (iv) submarine facies (
id: 2058; PT: J; UT: WOS:000295104800003

Sources of n-alkanes in an urbanized estuary: Insights from molecular distributions and compound-specific stable and radiocarbon isotopes - Ahad, Jason M. E.; Ganeshram, Raja S.; Bryant, Charlotte L.; Cisneros-Dozal, Luz M.; Ascough, Philippa L.; Fallick, Anthony E.; Slater, Greg F. (Marine Chemistry, 2011)
Diagnostic molecular ratios and compound-specific 13C and 14C analyses were used to identify n-alkane sources in surface sediments collected along a transect from an urbanized estuary draining a peat-rich catchment (Tyne, UK). The most abundant homologues were generally C29 or C31, and the carbon preference index (CPI; 1.8 to 6.4) and average chain length (ACL; 28.5 to 29.5) of C25–C33 n-alkanes became progressively lower in samples closer to the mouth of estuary. δ13C signatures of C19–C31 n-alkanes ranged from − 37.1 to − 29.3‰ and in general became more depleted with increasing carbon number. Δ14C values for C21 (− 945 to − 738‰) were significantly more depleted compared to C29 (− 591 to − 65‰) and C31 (− 382 to − 96‰), pointing to a much higher component of fossil (i.e., 14C-free) carbon in the shorter homologue. The radiocarbon contents for these three n-alkanes decreased toward the North Sea, which in conjunction with an up to 4‰ seaward 13C-enrichment in C29 and C31 and seaward decreases in CPI and ACL pointed to petrogenic hydrocarbon contamination in lower estuarine sediments. Independent 13C and 14C mass balances used to calculate the relative proportions of modern (i.e., plant wax) and fossil (i.e., petrogenic) n-alkanes yielded similar results and demonstrated that mixing with marine-derived organic matter (OM) or microbial degradation during estuarine transport led to a seaward decline in modern, longer-chain homologues, resulting in an increasingly larger fossil carbon contribution toward the mouth of estuary. The ability to clearly distinguish anthropogenic from natural inputs suggests that compound-specific radiocarbon analysis can successfully delineate the age of terrigenous OM delivered to the coastal zone even near historically polluted systems such as the Tyne.
id: 2169

Stable isotope analysis of dog, fox, and human diets at a Late Holocene Chumash village (CA-SRI-2) on Santa Rosa Island, California - Rick, Torben C.; Culleton, Brendan J.; Smith, Carley B.; Johnson, John R.; Kennett, Douglas J. (Journal of Archaeological Science, 2011)
Stable carbon (δ13C) and nitrogen (δ15N) isotope analyses of dog (Canis familiaris), island fox (Urocyon littoralis), and human bone collagen from CA-SRI-2 (AD 130–1830) on Santa Rosa Island, California provide a proxy of diet and the relationships between humans and these animals. Carbon isotopic signatures indicate that Native Americans and their dogs at CA-SRI-2 subsisted almost exclusively on marine resources, while the island fox ate primarily terrestrial foods. Nitrogen isotopes and archaeofaunal remains indicate that humans and dogs also ate higher trophic level foods, including finfishes, marine mammals, and seabirds with smaller amounts of shellfish. The CA-SRI-2 island foxes appear to have eaten higher amounts of terrestrial foods, similar to the diets observed in modern fox populations. These data generally confirm the commensal relationship assumed to exist between domesticated dogs and people, but the carbon isotopic composition of dogs is enriched ∼2‰ compared to humans. We hypothesize that the difference in carbon isotopes between dogs and humans may have resulted from a higher consumption of C3 plants with lower δ13C values by humans, or less likely from the ingestion by dogs of significant amounts of bone collagen, which is enriched by ∼4‰ over associated muscle.
id: 2180

Timing and duration of North American glacial lake discharges and the Younger Dryas climate reversal - Rayburn, John A.; Cronin, Thomas M.; Franzi, David A.; Knuepfer, Peter L. K.; Willard, Debra A. (Quaternary Research, 2011)
Radiocarbon-dated sediment cores from the Champlain Valley (northeastern USA) contain stratigraphic and micropaleontologic evidence for multiple, high-magnitude, freshwater discharges from North American proglacial lakes to the North Atlantic. Of particular interest are two large, closely spaced outflows that entered the North Atlantic Ocean via the St. Lawrence estuary about 13,200–12,900 cal yr BP, near the beginning of the Younger Dryas cold event. We estimate from varve chronology, sedimentation rates and proglacial lake volumes that the duration of the first outflow was less than 1 yr and its discharge was approximately 0.1 Sv (1 Sverdrup = 106 m3 s−1). The second outflow lasted about a century with a sustained discharge sufficient to keep the Champlain Sea relatively fresh for its duration. According to climate models, both outflows may have had sufficient discharge, duration and timing to affect meridional ocean circulation and climate. In this report we compare the proglacial lake discharge record in the Champlain and St. Lawrence valleys to paleoclimate records from Greenland Ice cores and Cariaco Basin and discuss the two-step nature of the inception of the Younger Dryas.
id: 2184

Weathering the storm: Coastal subsistence and ecological resilience on Late Holocene Santa Rosa Island, California - Torben C, Rick (Shell Midden Research: An Interdisciplinary Agenda for the Quaternary and Social Sciences, 2011)
Archaeological research on California’s Channel Islands has significantly enhanced understanding of the diversity and variability of coastal hunter-gatherers and the shell middens these people left behind. On the Channel Islands, the Late Holocene was a time of substantial population growth, territoriality, and the emergence of social hierarchies. The role of marine and terrestrial climate change, population growth, human environmental impacts, and other variables in driving Late Holocene cultural and ecological developments is a subject of considerable debate. Analysis of faunal remains (especially finfish and shellfish), complemented by human skeletal and stable isotope analyses, from a massive shell midden and village complex (CA-SRI-2) on Santa Rosa Island provides insight into Late Holocene human responses to coastal resource stress and environmental change. Despite significant population growth, the emergence of social stratification, and increased pressure on local resources and ecosystems, these data demonstrate that there is significant continuity in the coastal resources Channel Island peoples exploited through time. These results document the long-term resilience and adaptability of coastal hunter-gatherers, the marine resources they harvested, and Channel Island ecosystems.
id: 2178

Aminostratigraphy of surface and subsurface Quaternary sediments, North Carolina coastal plain, USA - Wehmiller, J. F.; Thieler, E. R.; Miller, D.; Pellerito, V.; Keeney, V. B.; Riggs, S. R.; Culver, S.; Mallinson, D.; Farrell, K. M.; York, L. L.; Pierson, J.; Parham, P. R. (Quaternary Geochronology, 2010)
The Quaternary stratigraphy and geochronology of the Albemarle Embayment of the North Carolina (NC) Coastal Plain is examined using amino acid racemization (AAR) in marine mollusks, in combination with geophysical, lithologic, and biostratigraphic analysis of 28 rotasonic cores drilled between 2002 and 2006. The Albemarle Embayment is bounded by structural highs to the north and south, and Quaternary strata thin westward toward the Suffolk paleoshoreline, frequently referred to as the Suffolk Scarp. The Quaternary section is up to similar to 90 m thick, consists of a variety of estuarine, shelf, back-barrier, and lagoonal deposits, and has been influenced by multiple sea-level cycles. The temporal resolution of the amino acid racemization method is tested statistically and with the stratigraphic control provided by this geologic framework, and it is then applied to the correlation and age estimation of subsurface units throughout the region. Over 500 specimens (primarily Mercenaria and Mulinia) from the subsurface section have been analyzed using either gas chromatographic (GC) or reverse-phase liquid chromatographic (RPLC) techniques. The subsurface stratigraphic data are compared with AAR results from numerous natural or excavated exposures from the surrounding region, as well as results from NC beach collections, to develop a comprehensive aminostratigraphic database for the entire Quaternary record within the NC coastal system. Age mixing, recognized in the beach collections, is also seen in subsurface sections, usually where major seismic reflections or core lithology indicate the presence of stratigraphic discontinuities. Kinetic models for racemization are tested within the regional stratigraphic framework, using either radiocarbon or U-series calibrations or comparison with regional biostratigraphy. Three major Pleistocene aminozones [AZ2, AZ3, and AZ4] are found throughout the region, all being found in superposition in several cores. Each can be subdivided, yielding a total of at least eight stratigraphically and statistically distinct aminozones. Kinetic modeling, supplemented with local calibration, indicates that these aminozones represent depositional events ranging from similar to 80 ka to nearly 2 Ma. Three prominent seismic reflections are interpreted to represent the base of the early, middle, and late Pleistocene, respectively, roughly 2 Ma, 800 ka, and 130 ka. The large number of samples and the available stratigraphic control provide new insights into the capabilities and limitations of aminostratigraphic methods in assessing relative and numerical ages of Atlantic Coastal Plain Quaternary deposits. (C) 2009 Elsevier B.V. All rights reserved.
639btTimes Cited:19Cited References Count:82

Asphalt volcanoes as a potential source of methane to late Pleistocene coastal waters - Valentine, D. L.; Reddy, C. M.; Farwell, C.; Hill, T. M.; Pizarro, O.; Yoerger, D. R.; Camilli, R.; Nelson, R. K.; Peacock, E. E.; Bagby, S. C.; Clarke, B. A.; Roman, C. N.; et al. (Nature Geoscience, 2010)
Every year, natural petroleum seepage emits 0.2-2 Tg of oil to the ocean(1). Significant oil seepage can build large underwater mounds, consisting of tar deposits with morphologies similar to volcanic lava flows, known as asphalt volcanoes(2,3). Such events are typically accompanied by large fluxes of the greenhouse gas methane(4,5). Marine sediments from the Santa Barbara basin, California, contain a record of elevated methane concentrations(6), anoxia and tar deposition(7) during the Pleistocene epoch that had been attributed to dissolution of methane hydrates. However, the region is known to have exhibited oil seepage in the past(7). Here, we document the discovery of seven extinct asphalt volcanoes off the coast of southern California. The morphology of the deposits and geochemistry of samples taken from the two largest structures supports their classification as asphalt volcanoes, derived from a common source. We estimate that the two structures resulted from seepage of 0.07-0.4 Tg of oil, accompanied by the emission of 0.35-1.8 Tg of methane. Radiocarbon dating of carbonate deposits entrained with the asphalt indicates formation of the volcanoes between 44 and 31 kyr ago. The timing and volume of erupted hydrocarbons from the asphalt structures can explain some or all of the documented methane release and tar accumulation in the Santa Barbara basin during the Pleistocene.
id: 1866; Sp. Iss. SI 589XW Times Cited:0 Cited References Count:28; YY

Contrasting multiproxy reconstructions of surface ocean hydrography in the Agulhas Corridor and implications for the Agulhas Leakage during the last 345,000 years - Martinez-Mendez, Gema; Zahn, Rainer; Hall, Ian R.; Peeters, Frank J. C.; Pena, Leopoldo D.; Cacho, Isabel; Negre, Cesar (PALEOCEANOGRAPHY, 2010)
Planktonic delta(18)O and Mg/Ca-derived sea surface temperature (SST) records from the Agulhas Corridor off South Africa display a progressive increase of SST during glacial periods of the last three climatic cycles. The SST increases of up to 4 degrees C coincide with increased abundance of subtropical planktonic foraminiferal marker species which indicates a progressive warming due to an increased influence of subtropical waters at the core sites. Mg/Ca-derived SST maximizes during glacial maxima and glacial Terminations to values about 2.5 degrees C above full-interglacial SST. The paired planktonic delta(18)O and Mg/Ca-derived SST records yield glacial seawater delta(18)O anomalies of up to 0.8%, indicating measurably higher surface salinities during these periods. The SST pattern along our record is markedly different from a U(37)(K')-derived SST record at a nearby core location in the Agulhas Corridor that displays SST maxima only during glacial Terminations. Possible explanations are lateral alkenone advection by the vigorous regional ocean currents or the development of SST contrasts during glacials in association with seasonal changes of Agulhas water transports and lateral shifts of the Agulhas retroflection. The different SST reconstructions derived from U(37)(K') and Mg/Ca pose a significant challenge to the interpretation of the proxy records and demonstrate that the reconstruction of the Agulhas Current and interocean salt leakage is not as straightforward as previously suggested.

Deepwater Formation in the North Pacific During the Last Glacial Termination - Okazaki, Y.; Timmermann, A.; Menviel, L.; Harada, N.; Abe-Ouchi, A.; Chikamoto, M. O.; Mouchet, A.; Asahi, H. (Science, 2010)
Between ~17,500 and 15,000 years ago, the Atlantic meridional overturning circulation weakened substantially in response to meltwater discharges from disintegrating Northern Hemispheric glacial ice sheets. The global effects of this reorganization of poleward heat flow in the North Atlantic extended to Antarctica and the North Pacific. Here we present evidence from North Pacific paleo surface proxy data, a compilation of marine radiocarbon age ventilation records, and global climate model simulations to suggest that during the early stages of the Last Glacial Termination, deep water extending to a depth of ~2500 to 3000 meters was formed in the North Pacific. A switch of deepwater formation between the North Atlantic and the North Pacific played a key role in regulating poleward oceanic heat transport during the Last Glacial Termination.

Determination of Microbial Carbon Sources and Cycling during Remediation of Petroleum Hydrocarbon Impacted Soil Using Natural Abundance (14)C Analysis of PLFA - Cowie, Benjamin R.; Greenberg, Bruce M.; Slater, Gregory F. (Environmental science & technology, 2010)
In a petroleum impacted land-farm soil in Sarnia, Ontario, compound-specific natural abundance radiocarbon analysis identified biodegradation by the soil microbial community as a major pathway for hydrocarbon removal in a novel remediation system. During remediation of contaminated soils by a plant growth promoting rhizobacteria enhanced phytoremediation system (PEPS), the measured Delta(14)C of phospholipid fatty acid (PLEA) biomarkers ranged from -793 parts per thousand to -897 parts per thousand, directly demonstrating microbial uptake and utilization of petroleum hydrocarbons (Delta(14)C(PHC) = -1000 parts per thousand). Isotopic mass balance indicated that more than 80% of microbial PLEA carbon was derived from petroleum hydrocarbons (PHC) and a maximum of 20% was obtained from metabolism of more modern carbon sources. These PLFA from the contaminated soils were the most (14)C-depleted biomarkers ever measured for an in situ environmental system, and this study demonstrated that the microbial community in this soil was subsisting primarily on petroleum hydrocarbons. In contrast, the microbial community in a nearby uncontaminated control soil maintained a more modern. Delta(14)C signature than total organic carbon (Delta(14)C(PLFA) = +36 parts per thousand to -147 parts per thousand, Delta(14)C(TOC) = -148 parts per thousand), indicating preferential consumption of the most modern plant-derived fraction of soil organic carbon. Measurements of delta(13)C and Delta(14)C of soil CO(2) additionally demonstrated that mineralization of PHC contributed to soil CO(2) at the contaminated site. The CO(2) in the uncontaminated control soil exhibited substantially more modern Delta(14)C values, and lower soil CO(2) concentrations than the contaminated soils, suggesting increased rates of soil respiration in the contaminated soils. In combination, these results demonstrated that biodegradation in the soil microbial community was a primary pathway of petroleum hydrocarbon removal in the PEPS system. This study highlights the power of natural abundance radiocarbon for determining microbial carbon sources and identifying biodegradation pathways in complex remediation systems.
id: 2054; PT: J; UT: WOS:000275993700017

Drowned coastal deposits with associated archaeological remains from a sea-level "slowstand": Northwestern Gulf of Maine, USA - Kelley, Joseph T.; Belknap, Daniel F.; Claesson, Stefan (Geology, 2010)
Drowned terrestrial wetland environments, such as lakes, marshes, and beaches, were thought to be rare in formerly glaciated regions like the Gulf of Maine (United States). In the northwestern Gulf of Maine, postglacial relative sea-level changes include a "slowstand" between 11.5 ka and 7.5 ka, when the ocean rose
id: 1996; PT: J; UT: WOS:000279847900006

Environmental anomalies in the northeastern East China Sea during the last 3 000 years: implications for El Nino activity in the Holocene - Chang, Fengming; Li, Tiegang; Zhuang, Lihua; Yan, Jun (Chinese Journal of Oceanology and Limnology, 2010)
To reconstruct the productivity changes for the last 10 500 a in the northeastern East China Sea (ECS), biogenic compounds (such as carbonate, organic carbon and opal), marine micropaleontological fossils (planktonic foraminifera, benthic foraminifera, radiolarian and silicoflagellate) and the compositional characters of benthic foraminifera fauna analyses were carried out on a sediment core DOC082 obtained from the western slope of Okinawa Trough (29 degrees 13.93'N, 128 degrees 08.53' E; 1 128 m water depth). The long-term changes of biogenic and micropaleontological proxies display some similarities through the last 10 500 a, which show three different phases: lower values are recorded during the early and middle Holocene (before about 4 000 a BP), followed by an abrupt and remarkable increase at about 4 000 a BP, the late Holocene (after about 3 000 a BP) is characterized by continuously high values. The multi-proxy data of paleoproductivity and percents of benthic foraminifera genera (Uvigerina and Bulimina) show that during the early and middle Holocene (10 500-4 000 a BP) productivity was relatively low with a sudden and distinct increase at about 4 000 a BP, and the late Holocene (3 400-0 a BP) is marked by significantly higher productivity. Also, the radiolarian-based sea surface temperature (SST) records reveal a distinct decline in SST in the late Holocene after 3 200 a BP, very different from the early and middle Holocene. For the last 3 000 a, the enhanced biological productivity and distinctly lower SST indicate a major change of oceanographic conditions in the northeastern ECS. These marine environmental anomalies are consistent with other paleoclimatic records for the late Holocene in the Chinese continent and its surrounding regions. After analyzing the mechanisms of modern productivity and SST changes in the northeastern ECS, and based on the climatic anomalies in the Chinese continent and variations in the Kuroshio Current during modern El Nino periods, we suggest that the anomalous environmental conditions in the northeastern ECS may imply intensified El Nino activity during the late Holocene.
id: 1927; PT: J; UT: WOS:000275654100024

Evidence for size increase in an exploited mollusc: humped conch (Strombus gibberulus) at Chelechol ra Orrak, Palau from ca. 3000-0 BP - Giovas, Christina M.; Fitzpatrick, Scott M.; Clark, Meagan; Abed, Mira (JOURNAL OF ARCHAEOLOGICAL SCIENCE, 2010)
Past research has suggested that the humped conch (Strombus gibberulus), a species common in many prehistoric archaeological sites in the Pacific, declines in size and/or abundance over time. Explanations for this phenomenon largely revolve around the possibility that they were overharvested by human populations. In this study, we measured the length and width of over 1400 individual specimens of S. gibberulus shells recovered from the site of Chelechol ra Orrak in Palau, western Micronesia, in deposits dating from ca. 3000 BP to the present. Statistical analysis indicates that in contrast to previous reports, there is a significant size increase for this taxon through time which may be the result of a combination of anthropogenic and environmental factors. We discuss variables influencing mollusc size and suggest that, given the complexities of their interactions and the data limitations of archaeomalacological assemblages, unambiguous determination of the cause(s) of molluscan size change may not always be possible. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Anthropogenic impacts; Humped conch; Micronesia; Molluscs; Pacific Islands; Palau

FORAMINIFERAL RECORD OF CHANGES IN SUMMER MONSOON PRECIPITATION - Pivel, M. A. G.; Toledo, F. A. L.; Costa, K. B. (Revista Brasileira de Paleontologia, 2010)
Changes in the oxygen isotopic composition of the planktonic foraminifer Globigerinoides ruber and in the foraminifera faunal composition in a core retrieved from the southeastern Brazilian continental margin were used to infer past changes in the hydrological balance and monsoon precipitation in the western South Atlantic since the Last Glacial Maximum (LGM). The results suggest a first-order orbital (precessional) control on the South American Monsoon precipitation. This agrees with previous studies based on continental proxies except for LGM estimates provided by pollen records. The causes for this disagreement are discussed.
id: 1974

Freshwater Outburst from Lake Superior as a Trigger for the Cold Event 9300 Years Ago - Yu, Shi-Yong; Colman, Steven M.; Lowell, Thomas V.; Milne, Glenn A.; Fisher, Timothy G.; Breckenridge, Andy; Boyd, Matthew; Teller, James T. (Science, 2010)
Paleoclimate proxy records reveal a pervasive cooling event with a Northern Hemispheric extent similar to 9300 years ago. Coeval changes in the oceanic circulation of the North Atlantic imply freshwater forcing. However, the source, magnitude, and routing of meltwater have remained unknown. Located in central North America, Lake Superior is a key site for regulating the outflow of glacial meltwater to the oceans. Here, we show evidence for an similar to 45-meter rapid lake-level fall in this basin, centered on 9300 calibrated years before the present, due to the failure of a glacial drift dam on the southeast corner of the lake. We ascribe the widespread climate anomaly similar to 9300 years ago to this freshwater outburst delivered to the North Atlantic Ocean through the Lake Huron-North Bay-Ottawa River-St. Lawrence River valleys.
id: 1950; PT: J; UT: WOS:000278318600030

Highly episodic fire and erosion regime over the past 2,000 y in the Siskiyou Mountains, Oregon RID A-2851-2009 RID C-9214-2009 - Colombaroli, Daniele; Gavin, Daniel G. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Fire is a primary mode of natural disturbance in the forests of the Pacific Northwest. Increased fuel loads following fire suppression and the occurrence of several large and severe fires have led to the perception that in many areas there is a greatly increased risk of high-severity fire compared with presettlement forests. To reconstruct the variability of the fire regime in the Siskiyou Mountains, Oregon, we analyzed a 10-m, 2,000-y sediment core for charcoal, pollen, and sedimentological data. The record reveals a highly episodic pattern of fire in which 77% of the 68 charcoal peaks before Euro-American settlement cluster within nine distinct periods marked by a 15-y mean interval. The 11 largest charcoal peaks are significantly related to decadal-scale drought periods and are followed by pulses of minerogenic sediment suggestive of rapid sediment delivery. After logging in the 1950s, sediment load was increased fourfold compared with that from the most severe presettlement fire. Less severe fires, marked by smaller charcoal peaks and no sediment pulses, are not correlated significantly with drought periods. Pollen indicators of closed forests are consistent with fire-free periods of sufficient length to maintain dense forest and indicate a fire-triggered switch to more open conditions during the Medieval Climatic Anomaly. Our results indicate that over millennia fire was more episodic than revealed by nearby shorter tree-ring records and that recent severe fires have precedents during earlier drought episodes but also that sediment loads resulting from logging and road building have no precedent in earlier fire events.
id: 1951; PT: J; UT: WOS:000283749000034

Holocene changes in Proboscia diatom productivity in shelf waters of the north-western Antarctic Peninsula - Willmott, V.; Rampen, S. W.; Domack, E.; Canals, M.; Damste, J. S. S.; Schouten, S. (Antarctic Science, 2010)
Diatoms are important primary producers in present day Antarctic waters but their relative significance in the past is less clear. In this Study We used long-chain diols to reconstruct Proboscia diatom productivity in shelf waters of the western Antarctic Peninsula over the last 8500 yr. Biomarker lipid analysis revealed the presence of a suite of long-chain diols in the sediments, mainly comprising the C-28 and C-30 1,14-diol isomers derived from Proboscia diatoms and C-28 and C-30 1,13-diols derived from other unknown algae. The relative importance of Proboscia diatoms was assessed using the relative abundances of 1, 14-diols versus 1, 13-diols, which showed that Proboscia diatoms were relatively more abundant during the Late Holocene, suggesting that stronger upwelling of circumpolar waters Occurred at that time. The variations in the diol index strongly correlate with melt events in the Siple Dome ice core, Suggesting that the climatic processes responsible for changes in mean summer temperature, open marine influence and atmospheric cyclonic activity recorded at Siple Dome, also controlled the productivity of Proboscia diatoms on the western Antarctic Peninsula region.
id: 789; 559YJ Times Cited:0 Cited References Count:51Y

Investigating the influence of hydrogeomorphic setting on the response of lake sedimentation to climatic changes in the Uinta Mountains, Utah, USA - Corbett, Lee B.; Munroe, Jeffrey S. (Journal of Paleolimnology, 2010)
Reader Lake and Elbow Lake, two high-altitude lakes in the Uinta Mountains of Utah, are located approximately 2 km apart, at similar elevations, and within identical vegetation communities. Loss on ignition, carbon to nitrogen ratios, biogenic silica, and sediment grain size were analyzed throughout percussion cores retrieved from both lakes to construct continuous time series spanning 14 to ca. 2 ka BP. Given the proximity of the lakes, it is assumed that both were subjected to the same climatic forcing over this time. Accordingly, the first goal of this study was to consider these two multiproxy datasets in concert to yield an integrated paleoclimate record for this region. Close inspection of the records identified discrepancies indicating that the lakes responded to climate changes in different ways despite their proximity and similar setting. Clarifying these differences and understanding why the two lakes behaved differently at certain times was the second goal of this study. Overall, the paleoclimatic records document lake formation in the latest Pleistocene following glacier retreat. Buried glacier ice at the location of Reader Lake may have persisted through the Younger Dryas. Both lakes became biologically productive ca. 11.5 ka BP, and the first appearance of conifer needles indicates that trees had replaced alpine tundra in these watersheds by 10.5 ka BP. The interval from 10 to 6 ka BP was marked by a dramatic increase in precipitation, perhaps related to enhanced monsoonal circulation driven by the insolation maximum. The two lakes recorded this event in notably contrasting ways given their differing hydrogeomorphic settings. Precipitation decreased from 6 to 4 ka BP, and low water levels and drought conditions marked the interval from 4.0 to 2.7 ka BP. The integrated paleoclimate record developed from these cores provides a useful point of comparison with other records from the region. The differences between the records from these closely spaced lakes underscore the need to consider hydrogeomorphic setting when evaluating the suitability of a lake for a paleolimnological study.
id: 2013; PT: J; UT: WOS:000277939200023

Late-twentieth-century warming in Lake Tanganyika unprecedented since AD 500 - Tierney, Jessica E.; Mayes, Marc T.; Meyer, Natacha; Johnson, Christopher; Swarzenski, Peter W.; Cohen, Andrew S.; Russell, James M. (Nature Geoscience, 2010)
Instrumental observations suggest that Lake Tanganyika, the largest rift lake in East Africa, has become warmer, increasingly stratified and less productive over the past 90 years (refs 1,2). These trends have been attributed to anthropogenic climate change. However, it remains unclear whether the decrease in productivity is linked to the temperature rise(3,4), and whether the twentieth-century trends are anomalous within the context of longer-term variability. Here, we use the TEX(86) temperature proxy, the weight per cent of biogenic silica and charcoal abundance from Lake Tanganyika sediment cores to reconstruct lake-surface temperature, productivity and regional wildfire frequency, respectively, for the past 1,500 years. We detect a negative correlation between lake-surface temperature and primary productivity, and our estimates of fire frequency, and hence humidity, preclude decreased nutrient input through runoff as a cause for observed periods of low productivity. We suggest that, throughout the past 1,500 years, rising lake-surface temperatures increased the stratification of the lake water column, preventing nutrient recharge from below and limiting primary productivity. Our records indicate that changes in the temperature of Lake Tanganyika in the past few decades exceed previous natural variability. We conclude that these unprecedented temperatures and a corresponding decrease in productivity can be attributed to anthropogenic global warming, with potentially important implications for the Lake Tanganyika fishery.
id: 2043; PT: J; UT: WOS:000278134100019

Mid-Brunhes strengthening of the Indian Ocean Dipole caused increased equatorial East African and decreased Australasian rainfall - Gupta, Anil K.; Sarkar, Sudipta; De, Soma; Clemens, Steven C.; Velu, Angamuthu (Geophysical Research Letters, 2010)
The tropical Indian Ocean is an important component of the largest warm pool, marked by changes in sea surface temperatures and depths of thermocline and mixed layer in its western and eastern extremities leading to the development of a dipole mode - the Indian Ocean Dipole (IOD). A narrow band of westerlies (7 degrees N to 7 degrees S) sweep the equatorial Indian Ocean during the April - May and October - November transitions between the summer - and winter-monsoon seasons. These Indian Ocean equatorial westerlies (IEW) are closely related to the IOD, intensifying the upper ocean Eastward Equatorial current also known as Wyrtki jets. The strength of the IOD/IEW determines the moisture content in East Africa. A major decrease in the strength of the IEW (strengthening or positive mode of the IOD) during the mid-Brunhes epoch (similar to 300-250 Kyr BP) coincides with a wetter equatorial East Africa, a drier Australasia and a stronger Indian summer monsoon, indicating that the IOD/IEW play a significant role in driving climate change in East Africa, Australasia and South Asia. Citation: Gupta, A. K., S. Sarkar, S. De, S. C. Clemens, and A. Velu (2010), Mid-Brunhes strengthening of the Indian Ocean Dipole caused increased equatorial East African and decreased Australasian rainfall, Geophys. Res. Lett., 37, L06706, doi: 10.1029/2009GL042225.
id: 1966; PT: J; UT: WOS:000276025100002

Millennial-aged organic carbon subsidies to a modern river food web - Caraco, Nina; Bauer, James E.; Cole, Jonathan J.; Petsch, Steven; Raymond, Peter (Ecology, 2010)
Recent studies indicate that highly aged material is a major component of organic matter transported by most rivers. However, few studies have used natural (14)C to trace the potential entry of this aged material into modern river food webs. Here we use natural abundance (14)C, (13)C, and deuterium ((2)H) to trace the contribution of aged and contemporary organic matter to an important group of consumers, crustacean zooplankton, in a large temperate river (the Hudson River, New York, USA). Zooplankton were highly (14)C depleted (mean Delta(14)C = -240 parts per thousand) compared to modern primary production in the river or its watershed (Delta(14)C = -60 parts per thousand to +50 parts per thousand). In order to account for the observed (14)C depletion, zooplankton must be subsidized by highly aged particulate organic carbon. IsoSource modeling suggests that the range of the aged dietary subsidy is between similar to 57%, if the aged organic matter source was produced 3400 years ago, and similar to 21%, if the organic carbon used is >= 50 000 years in age, including fossil material that is millions of years in age. The magnitude of this aged carbon subsidy to river zooplankton suggests that modern river food webs may in some cases be buffered from the limitations set by present-day primary production.
id: 2032; PT: J; UT: WOS:000280153500022

Rapid Climatic Signal Propagation from Source to Sink in a Southern California Sediment-Routing System - Covault, J. A.; Romans, B. W.; Fildani, A.; McGann, M.; Graham, S. A. (Journal of Geology, 2010)
Terrestrial source areas are linked to deep-sea basins by sediment-routing systems, which only recently have been studied with a holistic approach focused on terrestrial and submarine components and their interactions. Here we compare an extensive piston-core and radiocarbon-age data set from offshore southern California to contemporaneous Holocene climate proxies in order to test the hypothesis that climatic signals are rapidly propagated from source to sink in a spatially restricted sediment-routing system that includes the Santa Ana River drainage basin and the Newport deep-sea depositional system. Sediment cores demonstrate that variability in rates of Holocene deep-sea turbidite deposition is related to complex ocean-atmosphere interactions, including enhanced magnitude and frequency of the North American monsoon and El Nino-Southern Oscillation cycles, which increased precipitation and fluvial discharge in southern California. This relationship is evident because, unlike many sediment-routing systems, the Newport submarine canyon-and-channel system was consistently linked to the Santa Ana River, which maintained sediment delivery even during Holocene marine transgression and highstand. Results of this study demonstrate the efficiency of sediment transport and delivery through a spatially restricted, consistently linked routing system and the potential utility of deep-sea turbidite depositional trends as paleoclimate proxies in such settings.
id: 875; 574IR Times Cited:0 Cited References Count:55Y

Regional seismic stratigraphy and controls on the Quaternary evolution of the Cape Hatteras region of the Atlantic passive margin, USA - Mallinson, D. J.; Culver, S. J.; Riggs, S. R.; Thieler, E. R.; Foster, D.; Wehmiller, J.; Farrell, K. M.; Pierson, J. (Marine Geology, 2010)
Seismic and core data, combined with amino acid racemization and strontium-isotope age data, enable the definition of the Quaternary stratigraphic framework and recognition of geologic controls on the development of the modern coastal system of North Carolina, U.S.A. Seven regionally continuous high amplitude reflections are defined which bound six seismic stratigraphic units consisting of multiple regionally discontinuous depositional sequences and parasequence sets, and enable an understanding of the evolution of this margin. Data reveal the progressive eastward progradation and aggradation of the Quaternary shelf. The early Pleistocene inner shelf occurs at a depth of ca. 20-40 m beneath the western part of the modern estuarine system (Pamlico Sound). A mid- to outer shelf lowstand terrace (also early Pleistocene) with shelf sand ridge deposits comprising parasequence sets within a transgressive systems tract, occurs at a deeper level (ca. 45-70 m) beneath the modern barrier island system (the Outer Banks) and northern Pamlico Sound. Seismic and foraminiferal paleoenvironmental data from cores indicate the occurrence of lowstand strandplain shoreline deposits on the early to middle Pleistocene shelf. Middle to late Pleistocene deposits occur above a prominent unconformity and marine flooding surface that truncates underlying units, and contain numerous filled fluvial valleys that are incised into the early and middle Pleistocene deposits. The stratigraphic framework suggests margin progradation and aggradation modified by an increase in the magnitude of sea-level fluctuations during the middle to late Pleistocene. expressed as falling stage, lowstand, transgressive and highstand systems tracts. Thick stratigraphic sequences occur within the middle Pleistocene section, suggesting the occurrence of high capacity fluvial point sources debouching into the area from the west and north. Furthermore, the antecedent topography plays a significant role in the evolution of the geomorphology and stratigraphy of this marginal system. (C) 2009 Elsevier B.V. All rights reserved.
id: 1862; 556RX Times Cited:0 Cited References Count:71Y

Search for a glacial-age (14)C-depleted ocean reservoir - Broecker, Wally; Clark, Elizabeth (Geophysical Research Letters, 2010)
Measurements of the radiocarbon age difference between mixed benthic foraminifera and several coexisting planktic entities were made in hopes of finding evidence for the existence of an isolated glacial-age abyssal ocean reservoir whose demise would explain the large drops in the (14)C to C ratio in atmosphere and surface ocean carbon which occurred during the period of deglaciation. Forty-six new radiocarbon results were obtained at seven depths covering the full range of glacial time (i.e., similar to 27 to 15 (14)C kyrs) from an equatorial Pacific sediment core at 4.4-km water depth. Even though age reversals for foraminifera (but not for coccoliths) at two of the eight depths and large age differences between G. sacculifer and three submixed-layer planktic species mar this data set, there remains little likelihood that such a reservoir existed. Citation: Broecker, W., and E. Clark (2010), Search for a glacial-age (14)C-depleted ocean reservoir, Geophys. Res. Lett., 37, L13606, doi: 10.1029/2010GL043969.
id: 1923; PT: J; UT: WOS:000280043800003

Shifting Perceptions of Sacred Spaces: Ceremonial Reuse of Maya Architecture and Monuments at San Bartolo, Guatemala - Craig, Jessica (University of Kansas, 2010)

The southern Svalbard Margin sedimentary system: preliminary results from EGLACOM cruise 2008 - Melis, R.; Lucchi, R. G.; Giorgetti, G.; Persico, D.; BÁRcena, M. A. A.; Caburlotto, A.; MacrÌ, P.; Villa, G.; Sagnotti, L.; Rebesco, M. (European Geosciences Union, General Assembly 2010, 2010)
id: 873

Submarine Mass Transport Within Monterey Canyon: Benthic Disturbance Controls on the Distribution of Chemosynthetic Biological Communities - Paull, C. K.; Schlining, B.; Ussler, W.; Lundste, E.; Barry, J. P.; Caress, D. W.; Johnson, J. E.; McGann, M. (Submarine mass movements and their consequences, 4th International Symposium:, 2010)
Documenting mass transport within Monterey Canyon and Fan has been a focus of remotely operated vehicle (ROV) observations, sampling, monitoring, and multibeam mapping studies. These efforts indicate that major mass transport events occur within upper Monterey Canyon (2 km water depths) and onto Monterey Fan for ~100 years. Simultaneous efforts to document the distribution of benthic taxa observed in the video records from 668 ROV dives conducted by the Monterey Bay Aquarium Research Institute (MBARI) provide a uniquely detailed record of the occurrence of chemosynthetic biological communities (CBC). The combined results of these studies provide an understanding of the relationship between disturbance caused by episodic mass wasting events and the distribution of CBC. CBC are common within the canyon's axis below ~2.5 km water depth, but have not been found within the canyon's axis at depths shallower than 2 km. Moreover, CBC occur on the canyon walls at essentially any depth, primarily within young (~hundreds of years old) slump scars. The distribution of CBC provides evidence about the disturbance history of the seafloor. Major mass transport events will destroy communities that lie in their path. Erosion associated with major mass transport events can create environments to support CBC by exposing methane-bearing strata. This can happen as a result of slumping events on the sidewalls of the canyon or where major gravity flow events have excavated the base of canyon walls. Once fresh strata are exposed, geochemical conditions to support CBC will persist for a few centuries. Because CBC are composed of slow-growing and long-lived organisms, it will take decades for these communities to be established. Their existence indicates that environmental stability has occurred over a similar time scale.
id: 879

Temperature and salinity changes in the deglacial North Atlantic - Benway, H.M.; McManus, J.F.; Oppo, D.W.; Cullen, J.F. (Quaternary Science Reviews, 2010)

Were last glacial climate events simultaneous between Greenland and France? A quantitative comparison using non-tuned chronologies RID E-4539-2011 RID A-2643-2010 - Blaauw, Maarten; Wohlfarth, Barbara; Christen, J. Andres; Ampel, Linda; Veres, Daniel; Hughen, Konrad A.; Preusser, Frank; Svensson, Anders (Journal of Quaternary Science, 2010)
Several large abrupt climate fluctuations during the last glacial have been recorded in Greenland ice cores and archives from other regions. Often these Dansgaard-Oeschger events are assumed to have been synchronous over wide areas, and then used as tie-points to link chronologies between the proxy archives. However, it has not yet been tested independently whether or not these events were indeed synchronous over large areas. Here, we compare Dansgaard-Oeschger-type events in a well-dated record from southeastern France with those in Greenland ice cores. Instead of assuming simultaneous climate events between both archives, we keep their age models independent. Even these well-dated archives possess large chronological uncertainties that prevent us from inferring synchronous climate events at decadal to multi-centennial time scales. If possible, comparisons between proxy archives should be based on independent, non-tuned time-scales. Copyright (C) 2009 John Wiley & Sons, Ltd.
id: 1986; PT: J; UT: WOS:000276090800014

Younger Dryas Event and formation of peat layers in the northern Yellow Sea - Li, Tiegang; Chang, Fengming; Yu, Xinke (Earth Science Frontiers, 2010)
Peat layer, which formed under the humid climatic conditions and during the stagnated phase of sea level changes, is an important vehicle for information of paleoenvironmental evolution. Results of study on four sections of peat layer from the northern Yellow Sea indicate that all of them are located on the mouth of Bohai Sea strait between 50 and 54 meters water depth. The AMS 14C ages of peat layer are in the range between 10650 and 10100 a BP, which are highly coincident with the age of the Younger Dryas event that was the most significant cold climatic event during the last deglacial warming and occurred between 11000 and 10000 14C a BP. This coincidence indicates that the formation of peat layers in the northern Yellow Sea may be closely correlated with the global impact of Younger Dryas event and can be regard as an evidence of the response of the northern Yellow Sea area to it. The mass appearance of peat layer implies that during the Younger Dryas event a few stagnated periods existed in the postglacial process of sea level rising, the sea level had reached the outside of Bohai Sea strait and may have lingered for about thousand years. The above results and records of pollen suggest that during the period from 10600 to 10200 14C a BP, the northern Yellow Sea was in a cold and humid environment. The humid condition in the northern Yellow Sea area during the Younger Dryas event was distinctly different from the most terrestrial and oceanic records of Younger Dryas event in the global, which shows distinctive effect of Younger Dryas event in different region, and it is irresponsible to diagnose the characteristics of response to Younger Dryas events in different regions based on a single dry and cold mode.
id: 1969
Keywords: northern Yellow Sea; peat layer; sea level; Younger Dryas Event

Abrupt mid-Holocene onset of centennial-scale climate variability on the Peru-Chile Margin - Chazen, C. R.; Altabet, M. A.; Herbert, T. D. (Geophysical Research Letters, 2009)
Understanding the natural climate variations in the eastern tropical Pacific (ETP) is crucial for predicting the evolution of the El Nino-Southern Oscillation (ENSO). Here we present the first continuous, decadal-resolution Holocene climate record from the Peru-Chile Margin, near the epicenter of the modern ENSO system. Geochemical proxies allow us to reconstruct sea surface temperature, phytoplankton productivity, and thermocline ventilation, variables that are tightly correlated to ENSO events today. Despite the observation that the mean state of all three variables did not change over the past 10,000 years, our data reveal a dramatic increase in climate variability near 5 ka; represented by prolonged periods (50-200 yrs) of climate extremes, which are absent in the early Holocene. These centennial-scale oscillations do not show typical El Nino-La Nina correlations between proxies. We therefore posit that a significant fraction of super-ENSO variance may originate outside the tropics, through processes that ventilate the ETP subsurface waters. Citation: Chazen, C. R., M. A. Altabet, and T. D. Herbert (2009), Abrupt mid-Holocene onset of centennial-scale climate variability on the Peru-Chile Margin, Geophys. Res. Lett., 36, L18704, doi:10.1029/2009GL039749.
id: 1890; 499OY Times Cited:0 Cited References Count:41Y

Age Validation of Freshwater Drum using Bomb Radiocarbon - Davis-Foust, S. L.; Bruch, R. M.; Campana, S. E.; Olynyk, R. P.; Janssen, J. (Transactions of the American Fisheries Society, 2009)
The ages of freshwater drum Aplodinotus grunniens have typically been estimated by counting the growth increments on their scales or otoliths, but the accuracy of these estimates has not been validated. We used accelerator mass spectrometry (AMS) bomb radiocarbon dating to validate age estimates from sagittal otoliths of freshwater drum from the Lake Winnebago system, Wisconsin. The freshwater drum Delta C-14 chronology from the AMS assay closely reflects the timing and shape of other bomb radiocarbon chronologies, thus validating the accuracy of otolith growth increments to at least age 52 +/- 2 years. The progression of a strong 1983 year-class, which was detected every year sampled over the course of the study (1986, 2003-2007), and indices of year-class abundance calculated from trawling assessments on Lake Winnebago (1986-2007) corroborated otolith ages. Age estimate comparisons between scales, anal spines, dorsal spines, and otoliths showed scales and spines to be completely unreliable as aging structures after age 2. Freshwater drum live to very old ages relative to most other Great Lakes fishes; our oldest specimen based on an otolith age estimate was 58 years old.
id: 802; 477EI Times Cited:1 Cited References Count:58Y

Bomb dating and age determination of skates (family Rajidae) off the eastern coast of Canada - McPhie, R. P.; Campana, S. E. (Ices Journal of Marine Science, 2009)
Recent declines in abundance of skates off the eastern coast of Canada have heightened the need for validated age and growth estimates in the region. In all, 502 winter (Leucoraja ocellata), little (Leucoraja erinacea), thorny (Amblyraja radiata), and smooth (Malacoraja senta) skate vertebral centra collected seasonally between 1999 and 2004 were sectioned using a mass processing method, then used to reconstruct growth in each species. Bomb rediocarbon (Delta C-14) analysis was used to provide evidence of annual band-pair deposition in thorny skates. Estimates of L-infinity from traditional von Bertalanffy growth models (VBGM) ranged from 60.6 cm (little skate) to 89.7 cm (thorny skate), and K estimates from 0.07 (thorny skate) to 0.19 (little skate). A modified two-parameter VBGM (L-MAX = 94.1 cm) fitted to winter skate lenght-at-age data yielded a value of K to 0.15. Maximum observed ages ranged from 12 (little skate) to 19 years in both winter and thorny skates. The year-specific incorporation of Delta C-14 milled from thorny and winter skate vertebral sections closely resembled shark-derived reference chronology values from the Northwest Atlantic. Pre-bomb Delta C-14 in a thorny skate collected in 1988 and aged at 23 years appeared to validate age interpretations and suggested that thorny skate reach an absolute age of at least 28 years, the oldest validated age reported for any species of batoid.
id: 1856; 421XR Times Cited:3 Cited References Count:82Y

Changes in sediment and organic carbon accumulation in a highly-disturbed ecosystem: The Sacramento-San Joaquin River Delta (California, USA) - Canuel, E. A.; Lerberg, E. J.; Dickhut, R. M.; Kuehl, S. A.; Bianchi, T. S.; Wakeham, S. G. (Marine Pollution Bulletin, 2009)
We used the Sacramento-San Joaquin River Delta CA (Delta, hereafter) as a model system for understanding how human activities influence the delivery of sediment and total organic carbon (TOC) over the past 50-60 years. Sediment cores were collected from sites within the Delta representing the Sacramento River (SAC), the San Joaquin River (SJR), and Franks Tract (FT), a flooded agricultural tract. A variety of anthropogenic tracers including (CS)-C-137, total DDE (Sigma DDE) and brominated diphenyl ether (BDE) congeners were used to quantify sediment accumulation rates. This information was combined with total organic carbon (TOC) profiles to quantify rates of TOC accumulation. Across the three sites, sediment and TOC accumulation rates were four to eight-fold higher prior to 1972. Changes in sediment and TOC accumulation were coincident with completion of several large reservoirs and increased agriculture and urbanization in the Delta watershed. Radiocarbon content of TOC indicated that much of the carbon delivered to the Delta is "pre-aged" reflecting processing in the Delta watershed or during transport to the sites rather than an input of predominantly contemporary carbon (e.g., 900-1400 years BP in surface sediments and 2200 yrs BP and 3610 yrs BP at the base of the SJR and FT cores, respectively). Together, these data suggest that human activities have altered the amount and age of TOC accumulating in the Delta since the 1940s. (C) 2009 Elsevier Ltd. All rights reserved.
id: 1845; Sp. Iss. SI 477XX Times Cited:1 Cited References Count:49Y

Coarse-grained sediment delivery and distribution in the Holocene Santa Monica Basin, California: Implications for evaluating source-to-sink flux at millennial time scales - Romans, B. W.; Normark, W. R.; McGann, M. M.; Covault, J. A.; Graham, S. A. (Geological Society of America Bulletin, 2009)
Utilizing accumulations of coarse-grained terrigenous sediment from deep-marine basins to evaluate the relative contributions of and history of controls on sediment flux through a source-to-sink system has been difficult as a result of limited knowledge of event timing. In this study, six new radiocarbon (C-14) dates are integrated with five previously published dates that have been recalibrated from a 12.5-m-thick turbidite section from Ocean Drilling Program (ODP) Site 1015 in Santa Monica Basin, offshore California. This borehole is tied to high-resolution seismic-reflection profiles that cover an 1100 km(2) area of the middle and lower Hueneme submarine fan and most of the basin plain. The resulting stratigraphic framework provides the highest temporal resolution for a thick-bedded Holocene turbidite succession to date, permitting an evaluation of source-to-sink controls at millennial (1000 yr) scales. The depositional history from 7 ka to present indicates that the recurrence interval for large turbidity-current events is relatively constant (300-360 yr), but the volume of sediment deposited on the fan and in the basin plain has increased by a factor of 2 over this period. Moreover, the amount of sand per event on the basin plain during the same interval has increased by a factor of 7. Maps of sediment distribution derived from correlation of seismic-reflection profiles indicate that this trend cannot be attributed exclusively to autogenic processes (e.g., progradation of depocenters). The observed variability in sediment accumulation rates is thus largely controlled by allogenic factors, including: (1) increased discharge of Santa Clara River as a result of increased magnitude and frequency of El Nino-Southern Oscillation (ENSO) events from ca. 2 ka to present, (2) an apparent change in routing of coarse-grained sediment within the staging area at ca. 3 ka (i.e., from direct river input to indirect, littoral cell input into Hueneme submarine canyon), and (3) decreasing rates of sea-level rise (i.e., rate of rise slowed considerably by ca. 3 ka). The Holocene history of the Santa Clara River-Santa Monica Basin source-to-sink system demonstrates the ways in which varying sediment flux and changes in dispersal pathways affect the basinal stratigraphic record.
id: 876; 478QZ Times Cited:1 Cited References Count:90Y

Coral growth rates from the Holocene Canada Honda fossil reef, Southwestern Dominican Republic: Comparisons with modern counterparts in high sedimentation settings - Cuevas, D. N.; Sherman, C. E.; Ramírez, W.; Hubbard, D. K. (Caribbean Journal of Science, 2009)
The Holocene Canada Honda fossil reef, located in southwestern Dominican Republic, provides a unique opportunity to examine a well-preserved fossil coral reef that thrived in a high-sedimentation environment between 9,000 to 5,000 years ago. Measurements of coral growth rates from the corals Montastraea faveolata and Siderastrea siderea were conducted and comparisons made with growth rate data of these same species from modern coral reefs throughout the Caribbean. Also, assessments of coral species abundance, morphology, age, and distribution, as well as reef sediment composition, were made to determine the paleoenvironment of reef accretion. This reef is characterized by a high relative abundance of sediment-tolerant coral species that have a tendency to form almost monospecific stands. Individual colonies have a propensity to grow as encrusting, dome-shaped, platy-like forms and specimens of Montastraea faveolata commonly contain bands of sediment incorporated into the skeleton. Calibrated radiocarbon ages of fossil corals range from 9,256 +/- 137 to 6,737 +/- 94.5 BP. Correlation of radiocarbon ages with well-established Holocene sea-level curves indicates that most corals on this reef developed at depths >15m. Measured growth rates in Siderastrea siderea (0.2-0.4 cm/yr) and Montastraea faveolata (0.09-0.44 cm/yr) are relatively low compared with growth rates from modern reef sites, indicating reduced light intensity caused by coral growth at depths greater than 15 m. Reef sediment is characterized by more than 85% carbonate material. A significant portion of the carbonate is allochtonous and was derived from nearby Neogene limestones. The reef was able to survive under high-sedimentation conditions because the high carbonate content of incoming terrigenous sediment would have allowed better light penetration and probable sporadic storms would provide intervening low-sedimentation periods during which reef corals could respond and grow back, keeping-up with sedimentation.
695voTimes Cited:0 Cited References Count:47
Keywords: australia; Belize; Caribbean; community; degradation; enriquillo valley; florida; great-barrier-reef; linear extension; montastraea-annularis; paluma shoals; record; siltation stress; skeletal extension; turbidity

DNA and lipid molecular stratigraphic records of haptophyte succession in the Black Sea during the Holocene - Coolen, M. J. L.; Saenz, J. P.; Giosan, L.; Trowbridge, N. Y.; Dimitrov, P.; Dimitrov, D.; Eglinton, T. I. (Earth and Planetary Science Letters, 2009)
Previous studies suggest that the coccolithophorid haptophyte Emiliania huxleyi entered the Black Sea similar to 3400 yrs ago and since then a coccolith ooze defined as Unit I has developed. Unit I sediments contain long-chain alkenones derived from E huxleyi whereas the alkenone distribution of the deeper coccolith-free sapropel (Unit II) is rather unusual. Alkenone-derived past sea surface temperature (SST) estimates suggest a large difference between Unit II and Unit I, which is likely a result of unusual biological precursors of the alkenones in Unit II. Here, we report a high-resolution stratigraphic analysis of ancient haptophyte DNA to establish the Holocene succession of haptophytes as sources of the alkenones in the Black Sea. Haptophytes related to brackish Isochrysis spp. were the initial sources of alkenones, and appeared immediately after the onset of sapropel deposition (similar to 7550 yrs before present [a BP]). As salinity increased, Isochrysis-related haptophytes were slowly replaced by a complex suite of huxleyi strains as sources of alkenones. Our paleogenetic data showed that E. huxleyi colonized the Black Sea shortly after the onset of sapropel deposition, similar to 4000 yrs earlier than previously recognized based on their preserved coccoliths. E. huxleyi strains were the most likely source of the previously reported abundant and unusual C-36 di-unsaturated "Black Sea alkenone". Strong haptophyte species and strain-specific effects were observed on the level of unsaturation of alkenones which resulted in spurious alkenone-derived SST estimates before 5250 a BP. In contrast, from similar to 5250 a BP onwards a relatively stable haptophyte assemblage dominated by a different suite of E. huxleyi strains yielded robust alkenone-SST values and indicated a gradual cooling from 19 degrees C to similar to 15 degrees C at the top of the record (similar to 450 a BP). Published by Elsevier B.V.
id: 1853; 487NY Times Cited:1 Cited References Count:78; YY

Evidence for calcification depth change of Globorotalia truncatulinoides between deglaciation and Holocene in the Western Atlantic Ocean - Cleroux, C.; Lynch-Stieglitz, J.; Schmidt, M. W.; Cortijo, E.; Duplessy, J. C. (Marine Micropaleontology, 2009)
Measurements of the delta O-18 in tests of planktonic and benthic foraminifera in the Florida Straits are used to reconstruct the properties of the water column through time over the last 12 ka (Lynch-Stieglitz et al., in press). The isotopic composition of the foraminifera largely reflects the vertical density gradient. We use this reconstruction and delta O-18 measurements on Globorotalia truncatulinoides in a nearby core to track the depth habitat of this species from the last deglaciation to 1.6 ka B.P. Around 9 ka, G. truncatulinoides was calcifying in much shallower water than during the late Holocene. The downward migration toward its modem habitat is a regional phenomenon over the western tropical Atlantic continental slope. The cause is still unclear but we hypothesize that the shallower calcification depth may be a response to the presence of glacial melt water or to circulation changes. This study points to the value of further study of the ecology, life cycle and calcification depth for G. truncatulinoides and other planktonic foraminifera that are used to reconstruct the history of the thermocline and upper water column structure. Published by Elsevier B.V.
id: 1883; 514BR Times Cited:0 Cited References Count:33Y

Fine-scale relief related to Late Holocene channel shifting within the floor of the upper Redondo Fan, offshore Southern California - Normark, William R.; Paull, Charles K.; Caress, David W.; Ussler Iii, William; Sliter, Ray (Sedimentology, 2009)
AbstractErosional and depositional bedforms have been imaged at outcrop scale in the upper Redondo Fan, in the San Pedro Basin of offshore Southern California in greater than or equal to 600 m water depths, using an Autonomous Underwater Vehicle developed by the Monterey Bay Aquarium Research Institute. The Autonomous Underwater Vehicle is equipped with multibeam and chirp sub-bottom sonars. Sampling and photographic images using the Monterey Bay Aquarium Research Institute Remotely Operated Vehicle Tiburon provide groundtruth for the Autonomous Underwater Vehicle survey. The 0.3 m vertical and 1.5 m lateral bathymetric resolution and 0.1 m sub-bottom profile resolution provide unprecedented detail of bedform morphology and structure. Multiple channels within the Redondo Fan have been active at different times during the Late Holocene (0 to 3000 yr bp). The currently active channel extending from Redondo Canyon makes an abrupt 90 degree turn at the canyon mouth before resuming a south-easterly course along the east side of the Redondo Fan. This channel is floored by sand and characterized by small steps generally
id: 2216; Source type: scholarlyjournals; Object type: Article; Object type: Feature; CSAUnique: OB-MD-0010477140; AccNum: 11022775; DOI: 10.1111/j.1365-3091.2009.01052.x; ISSN: 0037-0746; Peer Reviewed: true

Florida Straits density structure and transport over the last 8,000 years - Lynch-Stieglitz, J.; Curry, W. B.; Lund, D. C. (Paleoceanography, 2009)
id: 837; YY

Formal definition and dating of the GSSP (Global Stratotype Section and Point) for the base of the Holocene using the Greenland NGRIP ice core, and selected auxiliary records RID B-5560-2008 RID F-1111-2011 - Walker, Mike; Johnsen, Sigfus; Rasmussen, Sune Olander; Popp, Trevor; Steffensen, Jorgen-Peder; Gibbard, Phil; Hoek, Wim; Lowe, John; Andrews, John; Bjorck, Svante; Cwynar, Les C.; Hughen, Konrad; et al. (Journal of Quaternary Science, 2009)
The Greenland ice core from NorthGRIP (NGRIP) contains a proxy climate record across the Pleistocene-Holocene boundary of unprecedented clarity and resolution. Analysis of an array of physical and chemical parameters within the ice enables the base of the Holocene, as reflected in the first signs of climatic warming at the end of the Younger Dryas/Greenland Stadial 1 cold phase, to be located with a high degree of precision. This climatic event is most clearly reflected in an abrupt shift in deuterium excess values, accompanied by more gradual changes in delta(18)O, dust concentration, a range of chemical species, and annual layer thickness. A timescale based on multi-parameter annual layer counting provides an age of 11 700 calendar yr b2k (before AD 2000) for the base of the Holocene, with a maximum counting error of 99 yr. A proposal that an archived core from this unique sequence should constitute the Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period) has been ratified by the International Union of Geological Sciences. Five auxiliary stratotypes for the Pleistocene-Holocene boundary have also been recognised. Copyright (C) 2008 John Wiley & Sons, Ltd.
id: 1989; PT: J; UT: WOS:000262615700002

Growth and sexual maturity of the northern propellerclam (Cyrtodaria siliqua) in Eastern Canada, with bomb radiocarbon age validation - Kilada, R. W.; Campana, S. E.; Roddick, D. (Marine Biology, 2009)
The northern propellerclam Cyrtodaria siliqua is a common bycatch in the Arctic surfclam, Mactromeris polynyma fishery on Banquereau Bank in Eastern Canada. Samples of the propellerclam from this exploited fishery were used to determine the life history characteristics of the population. The age structure of the population is dominated by old animals to ages exceeding 100 years. We validated the age estimates for the propellerclam through analysis of bomb-produced radiocarbon in the shell growth increments deposited before, during and after the atmospheric atomic bomb testing periods of the 1950s and 1960s. Radiocarbon from shells with presumed birth dates between the late 1950s and 1970s clearly reflected the sharp increase in oceanic radiocarbon attributable to previous nuclear testing, indicating that age estimates based on shell increment counts are accurate. Estimates of von Bertalanffy growth parameters revealed that the growth rate of the population was relatively rapid for the first 20 years of life, slowing down to very low growth rates thereafter. Sexual maturity was estimated as being reached at 28.6 mm in length and 4.7 years in age. Size-weight morphometric relationships were also calculated.
id: 803; 413YA Times Cited:0 Cited References Count:45Y

Holocene sea-level changes along the North Carolina Coastline and their implications for glacial isostatic adjustment models - Horton, B. P.; Peltier, W. R.; Culver, S. J.; Drummond, R.; Engelhart, S. E.; Kemp, A. C.; Mallinson, D.; Thieler, E. R.; Riggs, S. R.; Ames, D. V.; Thomson, K. H. (Quaternary Science Reviews, 2009)
We have synthesized new and existing relative sea-level (RSL) data to produce a quality-controlled, spatially comprehensive database from the North Carolina coastline. The RSL database consists of 54 sea-level index points that are quantitatively related to an appropriate tide level and assigned an error estimate, and a further 33 limiting dates that confine the maximum and minimum elevations of RSL The temporal distribution of the index points is very uneven with only five index points older than 4000 cal a BP, but the form of the Holocene sea-level trend is constrained by both terrestrial and marine limiting dates. The data illustrate RSL rapidly rising during the early and mid Holocene from an observed elevation of -35.7 +/- 1.1 m MSL at 11062-10576 cal a BP to -4.2 m +/- 0.4 m MSL at 4240-3592 cal a BP. We restricted comparisons between observations and predictions from the ICE-5G(VM2) with rotational feedback Glacial Isostatic Adjustment (GIA) model to the Late Holocene RSL (last 4000 cal a BP) because of the wealth of sea-level data during this time interval. The ICE-5G(VM2) model predicts significant spatial variations in RSL across North Carolina, thus we subdivided the observations into two regions. The model forecasts an increase in the rate of sea-level rise in Region 1 (Albemarle, Currituck, Roanoke, Croatan, and northern Pamlico sounds) compared to Region 2 (southern Pamlico, Core and Bogue sounds, and farther south to Wilmington). The observations show Late Holocene sea-level rising at 1.14 +/- 0.03 mm year(-1) and 0.82 +/- 0.02 mm year(-1) in Regions 1 and 2, respectively. The ICE-5G(VM2) predictions capture the general temporal trend of the observations, although there is an apparent misfit for index points older than 2000 cal a BR It is presently unknown whether these misfits are caused by possible tectonic uplift associated with the mid-Carolina Platform High or a flaw in the CIA model. A comparison of local tide gauge data with the Late Holocene RSL trends from Regions 1 and 2 support the spatial variation in RSL across North Carolina, and imply an additional increase of mean sea level of greater than 2 mm year(-1) during the latter half of the 20th century; this is in general agreement with historical tide gauge and satellite altimetry data. (C) 2009 Elsevier Ltd. All rights reserved.
id: 814; Sp. Iss. SI 484ZD Times Cited:1 Cited References Count:108Y

Lake Sturgeon Age Validation using Bomb Radiocarbon and Known-Age Fish - Bruch, R. M.; Campana, S. E.; Davis-Foust, S. L.; Hansen, M. J.; Janssen, J. (Transactions of the American Fisheries Society, 2009)
Pectoral fin spines have been the accepted structure for estimating the age of various sturgeon species for nearly 100 years, though other structures have also been used (otoliths, pectoral girdle, scutes, and caudal fulcra). Accuracy of age estimates using any of these structures has not been validated, so we report the first use of bomb radiocarbon (C-14) assays to assess the validity of ages estimated using growth increments on pectoral fin spine and otolith frontal cross sections from lake sturgeon Acipenser fulvescens: we also assessed age estimates from pectoral fin spines of known-age lake sturgeon. Growth increments on pectoral fin spine cross sections underestimated true age of fish older than 14 years and error increased with age, whereas otoliths accurately estimated true age up to at least 52 years. Increment formation on pectoral fin spine and otolith cross sections from juvenile lake sturgeon (ages 2-11) was similar, although pectoral spines were clearer and easier to interpret. A power function (true age = [estimated age](1.054796), where estimated age was determined from pectoral spines; r(2) = 0.98) provides a means for correcting existing age estimates obtained from lake sturgeon pectoral fin spines.
id: 1855; 477EI Times Cited:1 Cited References Count:33Y

Late Pleistocene-Holocene evolution of the northern shelf of the Sea of Marmara - Cagatay, M. N.; Eris, K.; Ryan, W. B. F.; Sancar, U.; Polonia, A.; Akcer, S.; Biltekin, D.; Gasperini, L.; Gorur, N.; Lericolais, G.; Bard, E. (Marine Geology, 2009)
Chirp sub-bottom profiling, multibeam bathymetric mapping and a combination of faunal and isotopic analysis of molluscs and foraminifera in sediment cores on the northern shelf of the Sea of Marmara (SoM) provide evidence of sea-level excursions, water exchanges between the adjacent Mediterranean and Black Seas, and oscillating salinity over the last 160 ka bp. During the marine isotope stages MIS-2, MIS-3, MIS-4 and MIS-6 the SoM disconnected from the Mediterranean Sea and evolved into a lake. During MIS-1, MIS-5 and MIS-7, the SoM reconnected and became salty once again. Sapropels formed shortly after each invasion of Mediterranean saltwater observed in our cores. Concurrent suboxic-dysoxic conditions prevailed over quite shallow substrates on the shelf. Ancient shorelines are pervasive at -85 m on the northern shelf and in the region of Prince Islands coincident with the elevation of the modern bedrock sill in the Canakkale (Dardanelles) Strait. At times when global (eustatic) sea level dropped below this sill, the surface of the SoM stabilized at its outlet and freshened. Thus this particular shoreline is interpreted as the edge of the most recent SoM lake that existed from about 75 ka bp to 12 ka bp. The freshening is observed in very light (-6 parts per thousand) values of delta O-18 measured on freshwater molluscs and the complete absence of foraminifera. Two brief lacustrine episodes during MIS-5 suggest that the level of the Canakkale outlet might have been as shallow as -50 m in the past, a likelihood supported by submerged terraces along its margins bounding the modern central channel and the presence of an euryhaline biofacies in Unit L4.1 corresponding to MIS-5b. delta O-18 profiles and carbon-14 dating show that salinification of the SoM and the blossoming of bioherms evolved rapidly after the latest connection with the Mediterranean at 12 ka bp. However, freshening proceeded more slowly once the connection was severed. (C) 2009 Elsevier B.V. All rights reserved.
id: 1843; 500UN Times Cited:1 Cited References Count:80Y

Methane accumulation and release from deep peat: Measurements, conceptual models, and biogeochemical significance - Glaser, Paul H.; Chanton, Jeffrey P. (Carbon Cycling in Northern Peatlands, 2009)
Northern peatlands account for more than half the world's wetlands but are currently estimated to contribute only about a third of the total methane emissions from all wetlands. Increasing data on the dynamics of methane gas bubbles in peat deposits now suggest that these estimates may need to be scaled upward. Rates of methanogenesis may remain high in deep peat strata because of the downward transport of labile root exudates permitting the widespread production of gas bubbles. Recent investigations using an array of methods have reported free-phase gas volumes of 10–20% within both deep and shallow peat strata and episodic ebullition fluxes exceeding 35 g CH4 m−2 per event. Gas bubbles accumulate in overpressured pockets that episodically rupture in response to steep declines in atmospheric pressure or declining water tables. Although these ebullition fluxes are highly variable in both time and space, they appear to dominate the annual methane emissions from northern peatlands and represent a major and underappreciated element of the global methane cycle.
id: 1972
Keywords: Carbon cycle (Biogeochemistry)—Northern Hemisphere; Carbon sequestration—Northern Hemisphere; Greenhouse gases—Northern Hemisphere; Peatlands—Environmental aspects—Northern Hemisphere

Moderate rates of late Quaternary slip along the northwestern margin of the Basin and Range Province, Surprise Valley fault, northeastern California - Personius, Stephen F.; Crone, Anthony J.; Machette, Michael N.; Mahan, Shannon A.; Lidke, David J. (Journal of Geophysical Research-Solid Earth, 2009)
The 86-km-long Surprise Valley normal fault forms part of the active northwestern margin of the Basin and Range province in northeastern California. We use trench mapping and radiocarbon, luminescence, and tephra dating to estimate displacements and timing of the past five surface-rupturing earthquakes on the central part of the fault near Cedarville. A Bayesian OxCal analysis of timing constraints indicates earthquake times of 18.2 +/- 2.6, 10.9 +/- 3.2, 8.5 +/- 0.5, 5.8 +/- 1.5, and 1.2 +/- 0.1 ka. These data yield recurrence intervals of 7.3 +/- 4.1, 2.5 +/- 3.2, 2.7 +/- 1.6, and 4.5 +/- 1.5 ka and an elapsed time of 1.2 +/- 0.1 ka since the latest surface-rupturing earthquake. Our best estimate of latest Quaternary vertical slip rate is 0.6 +/- 0.1 mm/a. This late Quaternary rate is remarkably similar to long-term (8-14 Ma) minimum vertical slip rates (>0.4-0.5 +/- 0.3 mm/a) calculated from recently acquired seismic reflection and chronologic and structural data in Surprise Valley and the adjacent Warner Mountains. However, our slip rate yields estimates of extension that are lower than recent campaign GPS determinations by factors of 1.5-4 unless the fault has an unusually shallow (30 degrees-35 degrees) dip as suggested by recently acquired seismic reflection data. Coseismic displacements of 2-4.5 +/- 1 m documented in the trench and probable rupture lengths of 53-65 km indicate a history of latest Quaternary earthquakes of M 6.8-7.3 on the central part of the Surprise Valley fault.
id: 2021; PT: J; UT: WOS:000270058200001

Palaeoenvironmental changes from pollen record in deep sea core PC-1 from northern Okinawa Trough, East China Sea during the past 24 ka - Xu, HongYan; Chang, Fengming; Luo, YunLi; Sun, XiangJun (Chinese Science Bulletin, 2009)
A pollen record of core PC-1 from the northern Okinawa Trough, East China Sea (ECS), provides information on vegetation and climate changes since 24 cal. kaBP. A total of 103 samples were palynologically analyzed at 8 cm intervals with a time resolution of 230 a. Four pollen zones are recognized: zone I (812-715 cm, 24.2-21.1 cal. kaBP), zone II (715-451 cm, 21.1-15.2 cal. kaBP), zone III (451-251 cm, 15.2-10.8 cal. kaBP), zone IV (251-0 cm, 10.8-0.3 cal. kaBP), corresponding to Late MIS 3, Last Glacial Maximum (LGM), deglaciation and Holocene, respectively. The LGM is characterized by the dominance of herbs, mainly Artemisia, and high pollen influx, implying an open vegetation on the exposed continental shelf and a cool and dry climate. The deglaciation is a climate warming stage with Pinus percentage increased and Artemisia percentage decreased and a rapid sea-level rise. The Holocene is characterized by predominance of tree pollen with rapid increase in Castanea-Castanopsis indicating the development of mixed evergreen and deciduous broad-leaved forest and a warm, humid climate. Low pollen influx during the Holocene probably implies submergence of the continental shelf and retreat of the pollen source area. The vegetation indicated by pollen assemblage found in this upper zone is consistent with the present vegetation found in Kyushu, Japan. Originating from the humid mountain area of North Luzon of the Philippines, Tasmania and New Zealand, Phyllocladus with sporadic occurrence throughout PC-1 core probably suggests the influence of Palaeo-Kuroshio Current or intense summer monsoon. The observed changes in Pinus and Herbs percentage indicate fluctuations of the sea level, and high Pinus percentage corresponds to high sea level. Spectrum analysis of the pollen percentage record reveals many millennial-scale periodicities, such as periodicities of 6.8, 3.85 2.2, 1.6 ka.
id: 1931; PT: J; UT: WOS:000271175500023

Partitioning of organic matter in continental margin sediments among density fractions - Wakeham, S. G.; Canuel, E. A.; Lerberg, E. J.; Mason, P.; Sampere, T. P.; Bianchi, T. S. (Marine Chemistry, 2009)
Hydrodynamic processes sort and redistribute organic matter (OM) and minerals on continental margins. Density fractionations were conducted on sediments from diverse margins (Mexico margin, Gulf of Mexico, Mississippi River delta, Eel River margin) to investigate the nature, provenance and age of OM among density fractions. Mass. elemental (C and N), lignin, and surface area distributions, as well as stable carbon and radiocarbon isotopic compositions were measured, The lowest density fractions (2.5 g cm(-3)) were OC-poor (%OC -200 parts per thousand). Ratios of vanillic acid to vanillin (Ad/Al)v among lignin oxidation products increase with increasing particle density suggesting variable lignin sources or selective degradation of lignin among the different density fractions. (C) 2009 Elsevier B.V. All rights reserved.
id: 1844; 521ZI Times Cited:0 Cited References Count:99Y

Rapid Response of a Marine Mammal Species to Holocene Climate and Habitat Change - de Bruyn, Mark; Hall, Brenda L.; Chauke, Lucas F.; Baroni, Carlo; Koch, Paul L.; Hoelzel, A. Rus (Plos Genetics, 2009)
Environmental change drives demographic and evolutionary processes that determine diversity within and among species. Tracking these processes during periods of change reveals mechanisms for the establishment of populations and provides predictive data on response to potential future impacts, including those caused by anthropogenic climate change. Here we show how a highly mobile marine species responded to the gain and loss of new breeding habitat. Southern elephant seal, Mirounga leonina, remains were found along the Victoria Land Coast (VLC) in the Ross Sea, Antarctica, 2,500 km from the nearest extant breeding site on Macquarie Island (MQ). This habitat was released after retreat of the grounded ice sheet in the Ross Sea Embayment 7,500-8,000 cal YBP, and is within the range of modern foraging excursions from the MQ colony. Using ancient mtDNA and coalescent models, we tracked the population dynamics of the now extinct VLC colony and the connectivity between this and extant breeding sites. We found a clear expansion signal in the VLC population similar to 8,000 YBP, followed by directional migration away from VLC and the loss of diversity at similar to 1,000 YBP, when sea ice is thought to have expanded. Our data suggest that VLC seals came initially from MQ and that some returned there once the VLC habitat was lost, similar to 7,000 years later. We track the founder-extinction dynamics of a population from inception to extinction in the context of Holocene climate change and present evidence that an unexpectedly diverse, differentiated breeding population was founded from a distant source population soon after habitat became available.
id: 1914; PT: J; NR: 58; TC: 11; J9: PLOS GENET; PG: 11; GA: 486SZ; UT: WOS:000269219500031

Submarine canyon and fan systems of the California Continental Borderland - Normark, William R.; Piper, David J. W.; Romans, Brian W.; Covault, Jacob A.; Dartnell, Peter; Sliter, Ray W. (Geological Society of America Special Papers, 2009)
Late Quaternary turbidite and related gravity-flow deposits have accumulated in basins of the California Borderland under a variety of conditions of sediment supply and sea-level stand. The northern basins (Santa Barbara, Santa Monica, and San Pedro) are closed and thus trap virtually all sediment supplied through submarine canyons and smaller gulley systems along the basin margins. The southern basins (Gulf of Santa Catalina and San Diego Trough) are open, and, under some conditions, turbidity currents flow from one basin to another. Seismic-reflection profiles at a variety of resolutions are used to determine the distribution of late Quaternary turbidites. Patterns of turbidite-dominated deposition during lowstand conditions of oxygen isotope stages 2 and 6 are similar within each of the basins. Chronology is provided by radiocarbon dating of sediment from two Ocean Drilling Program sites, the Mohole test-drill site, and large numbers of piston cores. High-resolution, seismic-stratigraphic frameworks developed for Santa Monica Basin and the open southern basins show rapid lateral shifts in sediment accumulation on scales that range from individual lobe elements to entire fan complexes. More than half of the submarine fans in the Borderland remain active at any given position of relative sea level. Where the continental shelf is narrow, canyons are able to cut headward during sea-level transgression and maintain sediment supply to the basins from rivers and longshore currents during highstands. Rivers with high bedload discharge transfer sediment to submarine fans during both highstand and lowstand conditions.
id: 878; 10.1130/2009.2454(2.7)

Timing and magnitude of recent accelerated sea-level rise (North Carolina, United States) - Kemp, A. C.; Horton, B. P.; Culver, S. J.; Corbett, D. R.; van de Plassche, O.; Gehrels, W. R.; Douglas, B. C.; Parnell, A. C. (Geology, 2009)
We provide records of relative sea level since A. D. 1500 from two salt marshes in North Carolina to complement existing tide-gauge records and to determine when recent rates of accelerated sea-level rise commenced. Reconstructions were developed using foraminifera-based transfer functions and composite chronologies, which were validated against regional twentieth century tide-gauge records. The measured rate of relative sea-level rise in North Carolina during the twentieth century was 3.0-3.3 mm/a, consisting of a background rate of similar to 1 mm/a, plus an abrupt increase of 2.2 mm/a, which began between A. D. 1879 and 1915. This acceleration is broadly synchronous with other studies from the Atlantic coast. The magnitude of the acceleration at both sites is larger than at sites farther north along the U. S. and Canadian Atlantic coast and may be indicative of a latitudinal trend.
id: 829; 512AY Times Cited:15 Cited References Count:30Y

Using foraminifera to recognize former flood-tide deltas in the Holocene stratigraphic record: examples from the Outer Banks, North Carolina - Smith, C. G.; Culver, S. J.; Mallinson, D. J.; Riggs, S. R.; Corbett, D. R. (Stratigraphy, 2009)
id: 851

Validation of yellowedge grouper, Epinephelus flavolimbatus, age using nuclear bomb-produced radiocarbon - Cook, Melissa; Fitzhugh, Gary R.; Franks, James S. (ENVIRONMENTAL BIOLOGY OF FISHES, 2009)
Age validation and estimates of longevity of yellowedge grouper (Epinephelus flavolimbatus) from the Gulf of Mexico (GOM) are needed to inform fishery management decisions. Yellowedge grouper sagittal otoliths (n = 100) were collected, aged using conventional means, and cores were submitted for radiocarbon ((14)C) measurement. Radiocarbon values of yellowedge grouper otoliths were compared to established radiocarbon chronologies in the region to validate the age and ageing methodology of this species. The yellowedge grouper chronology displayed a similar sigmoidal trend as previously published chronologies. In addition to the core analysis, multiple areas on otolith sections from eight specimens were analyzed for Delta(14)C to validate age estimates for fish born prior to the (14)C increase. Our results indicate that yellowedge grouper live longer than previously reported (minimum of 40 years based on radiocarbon measurements). The validated ageing methodology supported an estimated maximum longevity of 85 years and established that yellowedge grouper have the longest lifespan currently known for any species of grouper in the GOM. Results also indicate a depth-age interaction in that material extracted from adult otolith sections assigned to post-bomb dates exhibited lower Delta(14)C values than cores (juvenile material) assigned to the same post-bomb dates. This finding is likely explained by lower (14)C levels reported from water masses at deeper depths (> 100 m) which are inhabited by adults.
Keywords: Age determination; Age validation; Gulf of Mexico; Longevity; RADIOCARBON ANALYSIS; Yellowedge grouper

Variations of terrigenous material discharges in the South Okinawa trough and its relation to the East Asian summer monsoon since the last millennium - Chen, Jinxia; Li, Tiegang; Qingyun, Nan (Journal of China University of Geosciences, 2009)
The top part of a giant IMAGE core MD05-2908 taken from the South Okinawa Trough was investigated for the sake of understanding the climate evolution in Donghai seacoast areas since the last millennium. Sporopollen and organic carbon isotope records of bulk sediments were used as proxies to trace the climate variations and terrigenous materials discharges. Time series were demarcated by 4 AMS 14 C dating ages. Comprehensive data of sporopollen and carbon isotopic composition, together with the paleoenvironmental records show that in the South Okinawa Trough the terrigenous material discharges fluctuated obviously for the past 1000 years. Three relatively high terrigenous material discharge periods, corresponding to 1100-1040 a BP, 960-880 a BP and 800-480 a BP respectively and two quite low terrigenous material discharge periods, namely, 1040-960 a BP and 480-230 a BP, can be identified from our records. In comparison with the stalagmite delta (super 13) C records(which were used to trace the East Asian Summer Monsoon) from Buddha Cave, Shaanxi Province, we found that the variations of terrigenous material discharges might be related closely to variations of the East Asian Summer Monsoon(EASM). Weaker EASM resulted in a convergence rain belt and longer residence time in the South China regions, which increased the efficiency of weathering and denudation of the source area. Moreover, increased rainfall enhanced the land runoff and as a result more terrigenous materials were transported to the South Okinawa Trough.
id: 1948; Source type: scholarlyjournals; Object type: Article; Copyright: GeoRef in Process, Copyright 2011, American Geosciences Institute. After editing and indexing, this record will be added to Georef.; CSAUnique: 600756-13; AccNum: 600756-13; ISSN: 1000-2383; Peer Reviewed: true

Vast laminated diatom mat deposits from the west low-latitude Pacific Ocean in the last glacial period - Zhai, Bin; Li, Tiegang; Chang, Fengming; Cao, QiYuan (Chinese Science Bulletin, 2009)
Diatoms are one of the predominant contributors to global carbon fixation by accounting for over 40% of total oceanic primary production and dominate export production. They play a significant role in marine biogeochemistry cycle. The diatom mat deposits are results of vast diatoms bloom. By analysis of diatom mats in 136 degrees 00'-140 degrees 00'E, 15 degrees 00'-21 degrees 00'N, Eastern Philippines Sea, we identified the species of the diatoms as giant Ethmodiscus rex (Wallich) Hendey. AMS (14)C dating shows that the sediments rich in diatom mats occurred during 16000-28600 a B.P., which means the bloom mainly occurred during the last glacial period, while there are no diatom mat deposits in other layers. Preliminary analysis indicates that Antarctic Intermediate Water (AAIW) expanded northward and brought silicate-rich water into the area, namely, silicon leakage processes caused the bloom of diatoms. In addition, the increase of iron input is one of the main reasons for the diatom bloom.
id: 1928; PT: J; UT: WOS:000272622100036

Was the Black Sea catastrophically flooded in the early Holocene? - Giosan, L.; Filip, F.; Constatinescu, S. (Quaternary Science Reviews, 2009)
A catastrophic flooding of the Black Sea basin was proposed to have occurred during its reconnection to the ocean in the early Holocene. Possible cultural consequences of the flood include the migration of Neolithic farmers from around the Black Sea towards central Europe as well as the creation of flood myths. Stratigraphic and paleo-geomorphologic information from Danube delta aided by radiocarbon ages on articulated mollusks constrain the level in the Black Sea before the marine reconnection to ca 30 m below the present sea level rather than 80 m or lower. If the flood occurred at all, the sea level increase and the flooded area during the reconnection were significantly smaller than previously proposed. (C) 2008 Elsevier Ltd. All rights reserved.
id: 866; 399HK Times Cited:0 Cited References Count:56; YY

Abrupt climate change and collapse of deep-sea ecosystems - Yasuhara, M.; Cronin, T. M.; deMenocal, P. B.; Okahashi, H.; Linsley, B. K. (Proceedings of the National Academy of Sciences of the United States of America, 2008)
We investigated the deep-sea fossil record of benthic ostracodes during periods of rapid climate and oceanographic change over the past 20,000 years in a core from intermediate depth in the northwestern Atlantic. Results show that deep-sea benthic community "collapses" occur with faunal turnover of up to 50% during major climatically driven oceanographic changes. Species diversity as measured by the Shannon-Wiener index falls from 3 to as low as 1.6 during these events. Major disruptions in the benthic communities commenced with Heinrich Event 1, the Inter-Allerod Cold Period (IACP: 13.1 ka), the Younger Dryas (YD: 12.9-11.5 ka), and several Holocene Bond events when changes in deep-water circulation occurred. The largest collapse is associated with the YD/IACP and is characterized by an abrupt two-step decrease in both the upper North Atlantic Deep Water assemblage and species diversity at 13.1 ka and at 12.2 ka. The ostracode fauna at this site did not fully recover until approximate to 8 ka, with the establishment of Labrador Sea Water ventilation. Ecologically opportunistic slope species prospered during this community collapse. Other abrupt community collapses during the past 20 ka generally correspond to millennial climate events. These results indicate that deep-sea ecosystems are not immune to the effects of rapid climate changes occurring over centuries or less.
id: 1884; 261KQ Times Cited:12 Cited References Count:71Y

Benthic foraminiferal faunal and isotopic changes as recorded in Holocene sediments of the northwest Indian Ocean - Gupta, Anil K.; Das, Moumita; Clemens, Steven C.; Mukherjee, Baidehi (Paleoceanography, 2008)
Historically, the Holocene has been considered an interval of relatively stable climate. However, recent studies from the northern Arabian Sea (Netherlands Indian Ocean Program 905) suggested high-amplitude climate shifts in the early and middle Holocene based on faunal and benthic isotopic proxy records. We examined benthic foraminiferal faunal and stable isotopic data from Ocean Drilling Program (ODP) Site 723 and total organic carbon data from ODP Site 724, Oman Margin (808 and 593 m water depths, respectively). At Site 723 the mid-Holocene shift in delta(18)O values of infaunal benthic species Uvigerina peregrina (1.4 parts per thousand) is 3 times larger than that of epifaunal benthic species Cibicides kullenbergi recorded at Site NIOP 905 off Somalia. However, none of the five other benthic species we measured at Hole 723A exhibits such a shift in delta(18)O. We speculate that the late Holocene delta(18)O decrease in U. peregrina represents species-specific changes in ecological habitat or food preference in response to changes in surface and deep ocean circulation. While the stable isotopic data do not appear to indicate a middle Holocene climatic shift, our total organic carbon and benthic faunal assemblage data do indicate that the early Holocene deep Arabian Sea was influenced by increased ventilation perhaps by North Atlantic Deep Water and/or Circumpolar Deep Water incursions into the Indian Ocean, leading to remineralization of organic matter and a relatively weak early Holocene oxygen minimum zone in the northwest Arabian Sea in spite of strong summer monsoon circulation.
id: 1964; PT: J; UT: WOS:000256362400001

Bomb radiocarbon chronologies in the Arctic, with implications for the age validation of lake trout (Salvelinus namaycush) and other Arctic species - Campana, S. E.; Casselman, J. M.; Jones, C. M. (Canadian Journal of Fisheries and Aquatic Sciences, 2008)
Radiocarbon generated by atmospheric testing of nuclear weapons (bomb radiocarbon) produced a strong signal with an abrupt onset in the 1950s, which serves as a dated marker for tracing oceanic circulation and confirming age in animals forming growth bands. Here, we report the first prebomb and postbomb radiocarbon chronologies for marine and freshwater environments in the Canadian Arctic, extend the radiocarbon chronology for the northwest Atlantic Ocean, and use the onset of the bomb signal to validate our age interpretations of lake trout (Salvelinus namaycush) in Arctic lakes. Both surface and deepwater Arctic chronologies became detectable on or around 1958, similar to the year of onset elsewhere in the world. In contrast, the freshwater Arctic chronology increased sharply in 1957, with a peak value sixfold higher than the adjacent marine environment. The radiocarbon content of the adult otolith core validated our age interpretation criteria for Arctic lake trout to an age of at least 50 years. Otolith growth in such slow-growing fish was so low as to be unresolvable under conventional examination with a dissecting microscope. With these new radiocarbon reference chronologies, age validation of a large number of Arctic organisms should now be possible.
id: 804; 285MD Times Cited:7 Cited References Count:41Y

Carbonate cycle and its control factors in Kuroshio source region during the last 190ka BP - Jingtao, Zhao; Chang, Fengming; Li, Tiegang; Qingyun, Nan; Li, Qing (Yanshi Xuebao = Acta Petrologica Sinica, 2008)
Two deep sea cores (Ph05-5, 16.05 degrees N, 124.34 degrees E, water depth 3382m and WP3:22.15 degrees N, 122.95 degrees E, water depth 2700m) retrieved from the Kuroshio source region of the western Philippine Sea were selected to carry out the CaCO
id: 1934; NO: Source type: scholarlyjournals; Object type: Article; Copyright: GeoRef in Process, Copyright 2011, American Geosciences Institute. After editing and indexing, this record will be added to Georef.; CSAUnique: 577070-23; AccNum: 577070-23; ISSN: 1000-0569; Peer Reviewed: true

Constraints on the Pleistocene chronology of sediments from the Lomonosov Ridge - O'Regan, M.; King, J.; Backman, J.; Jakobsson, M.; Palike, H.; Moran, K.; Heil, C.; Sakamoto, T.; Cronin, T. M.; Jordan, R. W. (Paleoceanography, 2008)
[1] Despite its importance in the global climate system, age-calibrated marine geologic records reflecting the evolution of glacial cycles through the Pleistocene are largely absent from the central Arctic Ocean. This is especially true for sediments older than 200 ka. Three sites cored during the Integrated Ocean Drilling Program's Expedition 302, the Arctic Coring Expedition ( ACEX), provide a 27 m continuous sedimentary section from the Lomonosov Ridge in the central Arctic Ocean. Two key biostratigraphic datums and constraints from the magnetic inclination data are used to anchor the chronology of these sediments back to the base of the Cobb Mountain subchron ( 1215 ka). Beyond 1215 ka, two best fitting geomagnetic models are used to investigate the nature of cyclostratigraphic change. Within this chronology we show that bulk and mineral magnetic properties of the sediments vary on predicted Milankovitch frequencies. These cyclic variations record "glacial'' and "interglacial'' modes of sediment deposition on the Lomonosov Ridge as evident in studies of ice-rafted debris and stable isotopic and faunal assemblages for the last two glacial cycles and were used to tune the age model. Potential errors, which largely arise from uncertainties in the nature of downhole paleomagnetic variability, and the choice of a tuning target are handled by defining an error envelope that is based on the best fitting cyclostratigraphic and geomagnetic solutions.
id: 868; 281YL Times Cited:22 Cited References Count:55; YY

Deglacial variability in the surface return flow of the Atlantic meridional overturning circulation - Came, R. E.; Oppo, D. W.; Curry, W. B.; Lynch-Stieglitz, J. (Paleoceanography, 2008)
[1] Benthic foraminiferal Cd/Ca from a Florida Current sediment core documents the history of the northward penetration of southern source waters within the surface return flow of the Atlantic meridional overturning circulation (AMOC). Cd seawater estimates (Cd-W) indicate that intermediate-depth southern source waters crossed the equator and contributed to the Florida Current during the Bolling-Allerod warm period of the last deglaciation, consistent with evidence of only a modest AMOC reduction compared to today. The Cd-W estimates also provide the first paleoceanographic evidence of a reduction in the influence of intermediate-depth southern source waters within the Florida Current during the Younger Dryas, a deglacial cold event characterized by a weak North Atlantic AMOC. Our results reveal a close correspondence between the northward penetration of intermediate-depth southern source waters and the influence of North Atlantic Deep Water, suggesting a possible link between intermediate-depth southern source waters and the strength of the Atlantic AMOC.
id: 838; 281YL Times Cited:4 Cited References Count:41; YY

Determination of biodiesel blending percentages using natural abundance radiocarbon analysis: Testing the accuracy of retail biodiesel blends - Reddy, C. M.; DeMello, J. A.; Carmichael, C. A.; Peacock, E. E.; Xu, L.; Arey, J. S. (Environmental Science & Technology, 2008)
Blends of biodiesel and petrodiesel are being used increasingly worldwide. Due to several factors, inaccurate blending of these two mixtures can occur. To test the accuracy of biodiesel blending, we developed and validated a radiocarbon-based method and then analyzed a variety of retail biodiesel blends. Error propagation analysis demonstrated that this method calculates absolute blend content with +/- 1% accuracy, even when real-world variability in the component biodiesel and petrodiesel sources is taken into account. We independently confirmed this accuracy using known endmembers and prepared mixtures. This is the only published method that directly quantifies the carbon of recent biological origin in biodiesel blends. Consequently, it robustly handles realistic chemical variability in biological source materials and provides unequivocal apportionment of renewable versus nonrenewable carbon in a sample fuel blend. Analysis of retail biodiesel blends acquired in 2006 in the United States revealed that inaccurate blending happens frequently. Only one out of ten retail samples passed the specifications that the United States Department of Defense requires for blends that are 20% biodiesel (v/v; referred to as B20).
id: 1864; 281JN Times Cited:3 Cited References Count:39; YY

Environmental Factors Controlling Community Structure, Morphology and Linear Extension of Mid-Holocene Reef Corals from Cañada Honda, Southwestern, Dominican Republic - Cuevas, D.; Sherman, C.; Ramírez, W.; Hubbard, D. (Proceedings of the 11th International Coral Reef Symposium, Ft. Lauderdale, Florida, 2008)
The Cañada Honda (CH) fossil coral reef, located in SW Dominican Republic, provides a unique opportunity to examine reef accretion in a high-sedimentation environment between 9.0-5.0 ky ago. Annual linear extension of fossil corals was determined for comparison with data from modern coral reefs. The reef is characterized by the high abundance of sediment-tolerant coral species, their tendency to form almost monospecific stands and grow as domes-cones with ragged margins. Also, colonies of Montastraea faveolata commonly contain bands of sediment incorporated within their skeletons. Calibrated radiocarbon ages of fossil corals range from 9,256±137 to 6,737±94.5 BP. Correlation with Holocene sea-level curves indicates that most corals on CH developed at depths greater than 15m. Growth rates varied from 0.09-0.44 cm/yr and suggest reduced light penetration caused by coral growth at such depths. Reef sediment is characterized by more than 85% carbonate material. A significant portion of the carbonate is allochtonous and was derived from nearby Neogene limestones. The reef was able to survive under these conditions because of the high carbonate content of incoming terrigenous sediment and that storms probably occurred sporadically providing intervening lowsedimentation periods during which reef corals could respond and grow back, “keeping-up” with sedimentation.
id: 1979
Keywords: Caribbean; Holocene; ICRS11; Lessons from the past; linear extension; siltation

Episodic reductions in bottom-water currents since the last ice age - Praetorius, S. K.; McManus, J. F.; Oppo, D. W.; Curry, W. B. (Nature Geoscience, 2008)
Past changes in the freshwater balance of the surface North Atlantic Ocean are thought to have influenced the rate of deep-water formation, and consequently climate(1,2). Although water-mass proxies are generally consistent with an impact of freshwater input on meridional overturning circulation(3), there has been little dynamic evidence to support this linkage. Here we present a 25,000 year record of variations in sediment grain size from south of Iceland, which indicates vigorous bottom-water currents during both the last glacial maximum and the Holocene period. Together with reconstructions of North Atlantic water-mass distribution, vigorous bottom currents suggest a shorter residence time of northern-source waters during the last glacial maximum, relative to the Holocene period. The most significant reductions in flow strength occur during periods that have been associated with freshening of the surface North Atlantic. The short-term deglacial oscillations in bottom current strength are closely coupled to changes in Greenland air temperature, with a minimum during the Younger Dryas cold reversal and a maximum at the time of rapid warming at the onset of the Holocene. Our results support a strong connection between ocean circulation and rapid climate change.
id: 1896; ISI Document Delivery No.: 331AG Times Cited: 9 Cited Reference Count: 34 Cited References: ALLEY RB, 1997, GEOLOGY, V25, P483 BARBER DC, 1999, NATURE, V400, P344 BARD E, 1994, EARTH PLANET SC LETT, V126, P275 BIANCHI GG, 1999, NATURE, V397, P515 BIANCHI GG, 1999, SEDIMENTOLOGY, V46, P1001 BOND G, 1992, NATURE, V360, P245 BOYLE EA, 1987, NATURE, V330, P35 BROECKER WS, 1989, GEOCHIM COSMOCHIM AC, V53, P2465 BROECKER WS, 1989, NATURE, V341, P318 CAME RE, 2007, GEOLOGY, V35, P315, DOI 10.1130/G23455A.1 CURRY WB, 2005, PALEOCEANOGRAPHY, V20, ARTN PA1017 DUPLESSY JC, 1980, NATURE, V286, P479 DUPLESSY JC, 1988, PALEOCEANOGRAPHY, V3, P343 ELLISON CRW, 2006, SCIENCE, V312, P1929, DOI 10.1126/science.1127213 FIRESTONE RB, 2007, P NATL ACAD SCI USA, V104, P16016, DOI 10.1073/pnas.0706977104 GHERARDI JM, 2005, EARTH PLANET SC LETT, V240, P710, DOI 10.1016/j.epsl.2005.09.061 GROOTES PM, 1993, NATURE, V366, P552 HALL IR, 2004, QUATERNARY SCI REV, V23, P1529, DOI 10.1016/j.quascirev.2004.04.004 KENNETT JP, 2007, EOS T AGU JOINT AS S, V88, UNSP PP41A05 KROOPNICK P, 1980, EARTH PLAN, V49, P469 LEGRAND P, 1995, PALEOCEANOGRAPHY, V10, P1011 MANABE S, 1995, NATURE, V378, P165 MCCARTNEY MS, 1996, OCEANUS, V39, P19 MCCAVE IN, 1995, NATURE, V374, P149 MCCAVE IN, 1995, PALEOCEANOGRAPHY, V10, P593 MCCAVE IN, 2006, GEOCHEM GEOPHY GEOSY, V7, P37 MCMANUS JF, 2004, NATURE, V428, P824 OPPO DW, 1993, SCIENCE, V259, P1148 ROHLING EJ, 2005, NATURE, V434, P975, DOI 10.1038/nature03421 RUDDIMAN WF, 1981, PALAEOGEOGR PALAEOCL, V35, P145 SARNTHEIN M, 1994, PALEOCEANOGRAPHY, V9, P209 TARASOV L, 2005, NATURE, V435, P662, DOI 10.1038/nature03617 WORTHINGTON LV, 1976, N ATLANTIC CIRCULATI YU EF, 1996, NATURE, V379, P689 Praetorius, Summer K. McManus, Jerry F. Oppo, Delia W. Curry, William B. Nature publishing group New york; YY

Evolution in upper water structure and paleoproductivity in the northern margin of the western pacific warm pool and its forcing mechanism during the last 190 ka B.P.-evidence from nannofossil, foraminifera and their isotope com position - Zhao, Jingtao; Li, Tiegang; Chang, Fengming; Jiang, Bo (Oceanologia et Limnologia Sinica, 2008)
id: 1932

The Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period) in the NGRIP ice core RID B-5560-2008 RID F-1111-2011 - Walker, Mike; Johnsen, Sigfu's; Rasmussen, Sune Olander; Steffensen, Jorgen-Peder; Popp, Trevor; Gibbard, Philip; Hoek, Wim; Lowe, John; Andrews, John; Bjorck, Svante; Cwynar, Les; Hughen, Konrad; et al. (Episodes, 2008)
The Greenland ice core from NorthGRIP (NGRIP) contains a proxy climate record across the Pleistocene-Holocene boundary of unprecedented clarity and resolution. Analysis of an array of physical and chemical parameters within the ice enables the base of the Holocene, as reflected in the first signs of climatic warming at the end of the Younger Dryas/Greenland Stadial 1 cold phase, to be located with a high degree of precision. This climatic event is most clearly reflected in an. abrupt shaft in deuterium excess values, accompanied by more gradual changes in delta(18)O, dust concentration, a range of chemical species, and annual layer thickness. A timescale based on multi-parameter annual layer counting provides an age of 11,700 yr b2k (before AD2000) for the base of the Holocene, with, an estimated 2 sigma uncertainty of 99 yr: It is proposed that an archived core from this unique sequence should constitute the Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period).
id: 1988; PT: J; CT: 17th Congress of the International-Union-for-Quaternary-Research; CY: JUL 28-AUG 03, 2007; CL: Cairns, AUSTRALIA; SP: Int Union Quaternary Res; UT: WOS:000258669100017

Growth analysis and age validation of a deepwater Arctic fish, the Greenland halibut (Reinhardtius hippoglossoides) - Treble, M. A.; Campana, S. E.; Wastle, R. J.; Jones, C. M.; Boje, J. (Canadian Journal of Fisheries and Aquatic Sciences, 2008)
The accuracy of age interpretations on a deep-sea, Arctic fish species, the Greenland halibut (Reinhardtius hippoglossoides) was tested using several age validation methods. Consistent annual growth increments were either not formed or not visible in either whole or sectioned otoliths from three fish marked with oxytetracyline and recaptured after 2-4 years at liberty. Bomb radiocarbon assays based on a local reference chronology indicated that both whole and sectioned otoliths underestimated age by 1-15 years, with an average of 6 years. Growth rates estimated using the tag recapture model GROTAG were consistent with growth rates based on the radiocarbon assays and were less than half that of previously reported growth rates. The failure of otolith sections to provide an accurate age is unusual, but may be symptomatic of very slow-growing species with unusually shaped otoliths. Greenland halibut living in the deep-sea, Arctic environment are slower growing and longer lived than previously suspected, suggesting that the age-structured basis for current fisheries management warrants careful examination. Our results highlight the importance of using rigorous tests of ageing accuracy for exploited species and confirm that such age validation methods can be applied successfully in challenging environments such as the deep sea or the Arctic.
id: 806; 322ER Times Cited:3 Cited References Count:56Y

Holocene erosion of the Lesser Himalaya triggered by intensified summer monsoon - Clift, P. D.; Giosan, L.; Biusztajn, J.; Campbell, I. H.; Allen, C.; Pringle, M.; Tabrez, A. R.; Danish, M.; Rabbani, M. M.; Alizai, A.; Carter, A.; Lueckge, A. (Geology, 2008)
Climate is one of the principal controls setting rates of continental erosion. Here we present the results of a provenance analysis of Holocene sediments from the Indus delta in order to assess climatic controls on erosion over millennial time scales. Bulk sediment Nd isotope analysis reveals a number of changes during the late Pleistocene and early Holocene (at 14-20,11-12 and 8-9 ka) away from erosion of the Karakoram and toward more sediment flux from the Himalaya. Radiometric Ar-Ar dating of muscovite and U-Pb dating of zircon sand grains indicate that the Lesser Himalaya eroded relatively more strongly than the Greater Himalaya as global climate warmed and the summer monsoon intensified after 14 ka. Monsoon rains appear to be the primary force controlling erosion across the western Himalaya, at least over millennial time scales. This variation is preserved with no apparent lag in sediments from the delta, but not in the deep Arabian Sea, due to sediment buffering on the continental shelf.
id: 800; 247YL Times Cited:7 Cited References Count:27; YY

Holocene multidecadal- to millennial-scale hydrologic variability on the South American Altiplano - Ekdahl, E. J.; Fritz, S. C.; Baker, P. A.; Rigsby, C. A.; Coley, K. (Holocene, 2008)
Precipitation on the South American Altiplano varies at a range of temporal scales. A long-term secular increase in moisture availability from the early/mid Holocene to the present, driven by increasing summer insolation resulting from precessional changes in the Earth's orbit, has been documented in earlier studies. However, higher frequency Holocene variability is not yet understood. Here we present high-resolution diatom assemblage data from two small Altiplano lakes, Lago Lagunillas and Lago Umayo, indicating changes in effective moisture in the southern tropical Andes at decadal, centennial and millennial timescales throughout the mid to late Holocene. A strong millennial-scale component, similar in pacing to periods of increased ice-rafted debris flux in the North Atlantic, is observed in both lake records, which suggests that regional precipitation and North Atlantic climate variability are coupled at these scales. The interpretation of the higher frequency variability is hampered by the small number of high-resolution continental and marine records for comparison.
id: 842; ISI Document Delivery No.: 341ZR Times Cited: 1 Cited Reference Count: 49 Ekdahl, Erik J. Fritz, Sherilyn C. Baker, Paul A. Rigsby, Catherine A. Coley, KirstinY

A Holocene paleotemperature record based on radiolaria from the northern Okinawa Trough (East China Sea) - Chang, Fengming; Li, Tiegang; Zhuang, Lihua; Yan, Jun (Quaternary International, 2008)
Using a radiolarian-based transfer function, mean annual sea surface temperature (SST) and seasonal temperature range are reconstructed through the last 10,500yrs in the northern Okinawa Trough. Down-core SST estimates reveal that throughout the Holocene the changes of mean annual SST display a three-step trend: (i) an early Holocene continuous warming between 10,500 and 8500yr BP which ends up with a abrupt cooling at about 8200yr BP; (ii) a relatively stable middle Holocene with high SST that lasted until 3200yr BP; and (iii) a late-Holocene distinct SST decline between 3200 and 500yr BP. This pattern is in agreement with the ice core and terrestrial paleoclimatic records in the Chinese continent and other regions of the world. Five cooling events with abrupt mean annual SST drops, which occur at similar to 300-600, 1400, 3100, 4600-5100 and 8200yr BP, are recognized during the last 10,500yrs. Comparison of our results with records of GISP2 ice core and marine sediment in North Atlantic region suggests these cooling events are strongly coupled, which implies a possible significant climatic correlation between high- and low-latitude areas. (C) 2007 Elsevier Ltd and INQUA. All rights reserved.
id: 1926; PT: J; UT: WOS:000257255700009

Increased terrestrial to ocean sediment and carbon fluxes in the northern chesapeake bay associated with twentieth century land alteration - Saenger, C.; Cronin, T. M.; Willard, D.; Halka, J.; Kerhin, R. (Estuaries and Coasts, 2008)
We calculated Chesapeake Bay (CB) sediment and carbon fluxes before and after major anthropogenic land clearance using robust monitoring, modeling and sedimentary data. Four distinct fluxes in the estuarine system were considered including (1) the flux of eroded material from the watershed to streams, (2) the flux of suspended sediment at river fall lines, (3) the burial flux in tributary sediments, and (4) the burial flux in main CB sediments. The sedimentary maximum in Ambrosia (ragweed) pollen marked peak land clearance (similar to 1900 A.D.). Rivers feeding CB had a total organic carbon (TOC)/total suspended solids of 0.24 +/- 0.12, and we used this observation to calculate TOC fluxes from sediment fluxes. Sediment and carbon fluxes increased by 138-269% across all four regions after land clearance. Our results demonstrate that sediment delivery to CB is subject to significant lags and that excess post-land clearance sediment loads have not reached the ocean. Post-land clearance increases in erosional flux from watersheds, and burial in estuaries are important processes that must be considered to calculate accurate global sediment and carbon budgets.
id: 812; 316CY Times Cited:1 Cited References Count:54Y

Interpreting sea surface temperature from strontium/calcium ratios in Montastrea corals: Link with growth rate and implications for proxy reconstructions - Saenger, C.; Cohen, A. L.; Oppo, D. W.; Hubbard, D. (Paleoceanography, 2008)
[1] We analyzed strontium/calcium ratios (Sr/Ca) in four colonies of the Atlantic coral genus Montastrea with growth rates ranging from 2.3 to 12.6 mm a(-1). Derived Sr/Ca-sea surface temperature (SST) calibrations exhibit significant differences among the four colonies that cannot be explained by variations in SST or seawater Sr/Ca. For a single coral Sr/Ca ratio of 8.8 mmol mol(-1), the four calibrations predict SSTs ranging from 24.0 degrees to 30.9 degrees C. We find that differences in the Sr/Ca-SST relationships are correlated systematically with the average annual extension rate (ext) of each colony such that Sr/Ca ( mmol mol(-1)) = 11.82 (+/- 0.13) - 0.058 (+/- 0.004) x ext ( mm a(-1)) - 0.092 (+/- 0.005) x SST (degrees C). This observation is consistent with previous reports of a link between coral Sr/Ca and growth rate. Verification of our growth-dependent Sr/Ca - SST calibration using a coral excluded from the calibration reconstructs the mean and seasonal amplitude of the actual recorded SST to within 0.3 degrees C. Applying a traditional, nongrowth-dependent Sr/Ca - SST calibration derived from a modern Montastrea to the Sr/Ca ratios of a conspecific coral that grew during the early Little Ice Age (LIA) ( 400 years B. P.) suggests that Caribbean SSTs were > 5 degrees C cooler than today. Conversely, application of our growth-dependent Sr/Ca - SST calibration to Sr/Ca ratios derived from the LIA coral indicates that SSTs during the 5-year period analyzed were within error (+/- 1.4 degrees C) of modern values.
id: 864; ISI Document Delivery No.: 333MS Times Cited: 3 Cited Reference Count: 49 Cited References: *DEP CONS CULT AFF, 1986, MAR WAT QUAL MEAS CH *NAT RES COUNC, 2006, SURF TEMP REC LAST 2 BEVINGTON PR, 1969, DATA REDUCTION ERROR, P56 BLACK DE, 2004, PALEOCEANOGRAPHY, V19, ARTN PA2022 BLACK DE, 2007, PALEOCEANOGRAPHY, V22, ARTN PA4204 CARDINAL D, 2001, CHEM GEOL, V176, P213 CARRICARTGANIVET JP, 2004, J EXP MAR BIOL ECOL, V302, P249, DOI 10.1016/j.jembe.2003.10.015 CHIANG JCH, 2002, J GEOPHYS RES-ATMOS, V107, ARTN 4004 COBB KM, 2003, EARTH PLANET SC LETT, V210, P91, DOI 10.1016/S0012-821X(03)00138-9 COHEN AL, 2004, GEOPHYS RES LETT, V31, ARTN L16310 COHEN AL, 2004, MAR ECOL-PROG SER, V271, P147 COHEN AL, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q12004 COHEN AL, 2007, GEOPHYS RES LETT, V34, ARTN L17706 CRONIN TM, 2003, GLOBAL PLANET CHANGE, V36, P17 DEVILLIERS S, 1995, SCIENCE, V269, P1247 DEVILLIERS S, 1999, EARTH PLANET SC LETT, V171, P623 FELIS T, 2004, NATURE, V429, P164, DOI 10.1038/nature02546 GABITOV RI, 2006, GEOCHIM COSMOCHIM S, V70, A187, DOI 10.1016/j.gca.2006.06.377 GAETANI GA, 2006, GEOCHIM COSMOCHIM AC, V70, P4617, DOI 10.1016/j.gca.2006.07.008 GOODKIN NF, 2005, PALEOCEANOGRAPHY, V20, ARTN PA4016 HAASESCHRAMM A, 2003, PALEOCEANOGRAPHY, V18, ARTN 1073 HAASESCHRAMM A, 2005, PALEOCEANOGRAPHY, V20, ARTN PA4015 HAUG GH, 2001, SCIENCE, V293, P1304 HENDY EJ, 2002, SCIENCE, V295, P1511 HERNANDEZGUERRA A, 2000, GEOPHYS RES LETT, V27, P3497 HODELL DA, 2005, QUATERNARY RES, V63, P109, DOI 10.1016/j.yqres.2004.11.004 HUBBARD DK, 2005, J SEDIMENT RES, V75, P97, DOI 10.2110/jsr.2005.009 HUGHEN KA, 2004, RADIOCARBON, V46, P1059 JONES PD, 2004, REV GEOPHYS, V42, ARTN RG2002 LEDER JJ, 1996, GEOCHIM COSMOCHIM AC, V60, P2857 LOUGH JM, 2004, PALAEOGEOGR PALAEOCL, V204, P115, DOI 10.1016/S0031-0182(03)00727-2 LUND DC, 2006, PALEOCEANOGRAPHY, V21, ARTN PA2009 MEIBOM A, 2006, GEOPHYS RES LETT, V33, ARTN L11608 MOHIUDDIN MM, 2004, DEEP-SEA RES PT I, V51, P1659, DOI 10.1016/j.dsr.2004.06.002 NYBERG J, 2002, PALAEOGEOGR PALAEOCL, V183, P25 OSTERMANN DR, 2000, PALEOCEANOGRAPHY, V15, P353 PFLAUMANN U, 2003, PALEOCEANOGRAPHY, V18, ARTN 1065 REYNAUD S, 2007, GEOCHIM COSMOCHIM AC, V71, P354, DOI 10.1016/j.gca.2006.09.009 REYNOLDS RW, 1994, J CLIMATE, V7, P929 ROSENTHAL Y, 1999, ANAL CHEM, V71, P3248 SCHMIDT MW, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q02P10 SMITH JM, 2006, PALEOCEANOGRAPHY, V21, ARTN PA1010 SWART PK, 2002, GEOCHEM GEOPHY GEOSY, V3, ARTN 8402 THUNELL RC, 1984, MICROPALEONTOLOGY, V30, P243 VELLINGA M, 2004, J CLIMATE, V17, P4498 WATANABE T, 2001, MAR GEOL, V173, P21 WEIL E, 1994, B MAR SCI, V55, P151 WINTER A, 2000, GEOPHYS RES LETT, V27, P3365 YOO JM, 1990, J PHYS OCEANOGR, V20, P831 Saenger, Casey Cohen, Anne L. Oppo, Delia W. Hubbard, Dennis Amer geophysical union Washington; YY

The last reconnection of the Marmara Sea (Turkey) to the World Ocean: A paleoceanographic and paleoclimatic perspective - McHugh, C. M. G.; Gurung, D.; Giosan, L.; Ryan, W. B. F.; Mart, Y.; Sancar, U.; Burckle, L.; Cagatay, M. N. (Marine Geology, 2008)
During the late glacial, marine isotope Stage 2, the Marmara Sea transformed into a brackish lake as global sea-level fell below the sill in the Dardanelles Strait. A record of the basin's reconnection to the global ocean is preserved in its sediments permitting the extraction of the paleoceanographic and paleoclimatic history of the region. The goal of this study is to develop a high-resolution record of the lacustrine to marine transition of Marmara Sea in order to reconstruct regional and global climatic events at a millennia] scale. For this purpose, we mapped the paleoshorelines of Marmara Sea along the northern, eastern, and southern shelves at Cekmece. Prince Islands, and Imrali, using data from multibeam bathymetry, high-resolution subbottom profiling (chirp) and ten sediment cores. Detailed sedimentologic, biostratigraphic (foraminifers, mollusk, diatoms), X-ray fluorescence geochemical scanning, and oxygen and carbon stable isotope analyses correlated to a calibrated radiocarbon chronology provided evidence for cold and city conditions prior to 15 ka BP, warm conditions of the Bolling-Allerod from similar to 15 to 13 ka BP, a rapid marine incursion at 12 ka BP, still stand of Marmara Sea and sediment reworking of the paleoshorelines during the Younger Dryas at similar to 11.5 to 10.5 ka BP, and development of strong stratification and influx of nutrients as Black Sea waters spilled into Marmara Sea at 9.2 ka BR Stable environmental conditions developed in Marmara Sea after 6.0 ka BP as sea-level reached its present shoreline and the basin floors filled with sediments achieving their present configuration. (C) 2008 Elsevier B.V. All rights reserved.
id: 801; 370ED Times Cited:4 Cited References Count:104; YY

Micropaleontologic record of late pliocene and quaternary paleoenvironments in the northern Albemarle embayment, North Carolina, USA - Culver, S. J.; Farrell, K. M.; Mallinson, D. J.; Horton, B. P.; Willard, D. A.; Thieler, E. R.; Riggs, S. R.; Snyder, S. W.; Wehmiller, J. F.; Bernhardt, C. E.; Hillier, C. (Palaeogeography Palaeoclimatology Palaeoecology, 2008)
Micropaleontological data provide a strong actualistic basis for detailed interpretations of Quaternary paleoenvironmental change. The 90 m-thick Quaternary record of the Albemarle Embayment in the mid-Atlantic coastal plain of the USA provides an excellent opportunity to use such an approach in a region where the details of Quaternary environmental change are poorly known. The foraminiferal record in nine cores from the northern Outer Banks, east of Albemarle Sound, North Carolina, indicates the deposition of subhorizontal, mostly open-marine early to late Pleistocene units unconformably upon a basement of late Pliocene reduced-oxygen, fine-grained, shelf-basin deposits. Pollen data record several warm-cool fluctuations within the early to mid-Pleistocene deposits. Diatom data indicate that some fresh and brackish-water units occur within the generally open-marine Pleistocene succession. A channel cut by the paleo-Roanoke River during the last glacial sea-level lowstand occurs in the northern part of the study area. Pollen indicates that the basal fluvial valley fill accumulated in cooler than modern climate conditions in the latest Pleistocene. Overlying silts and muds accumulated under cool climatic, estuarine conditions according to diatom and pollen data. Radiocarbon ages from the estuarine deposits indicate that the bulk of these sediments accumulated during the latest Pleistocene. The estuarine channel-fill deposits are overlain by Holocene open-marine sands deposited as the rising sea transgressed into the estuary approximately 8.5 to 9.0 kyr BR Within the barrier island drill cores of this study, fully marine sedimentation occurred throughout the Holocene. However, immediately west of the present barrier island, mid- to late Holocene estuarine deposits underlie the modern Albemarle Sound. The islands that currently form a continuous barrier across the mouth of Albemarle Sound have a complex history of Holocene construction and destruction and large portions of them may be less than 3 kyr old. The barrier island sands overlie open-marine sands of Colington Shoal in the north and to the south overlie fluvial and marine sand filling paleo-Roanoke tributary valleys. The Pleistocene sediments underlying the northern Outer Banks study area are mainly of open inner to midshelf origin. If, as is likely, sea level continues to rise, a return to such environmental conditions is likely in the near future. (c) 2008 Elsevier B.V. All rights reserved.
id: 815; 331MZ Times Cited:2 Cited References Count:79Y

Near constancy of the Pacific Ocean surface to mid-depth radiocarbon-age difference over the last 20 kyr - Broecker, W.; Clark, E.; Barker, S. (Earth and Planetary Science Letters, 2008)
Although C-13 to C-12 and cadmium to calcium ratios provide information regarding the distribution of deep water masses during late glacial time and during the period of deglaciation, our knowledge of the rate at which these water masses were ventilated comes mainly from the difference in radiocarbon-age between coexisting bottom- and surface-dwelling foraminifera. Paired benthic/planktonic foraminiferal radiocarbonage differences covering last 20 kyr in a high-deposition-rate western equatorial Pacific core, MD01-2386, from a water depth of 2.8 km show no significant climate-related variations over this period. This result is surprising for we would have expected a change in this age difference between the last glacial maximum (LGM) and the Holocene and also during the Mystery Interval (17.5-14.5 kyr ago) when the waters in a radiocarbon-depleted abyssal reservoir were presumably being mixed back into the remainder of the ocean. (C) 2008 Elsevier B.V. All rights reserved.
id: 770; 390GV Times Cited:2 Cited References Count:27Y

Northern hemisphere controls on tropical southeast African climate during the past 60,000 years - Tierney, Jessica E.; Russell, James M.; Huang, Yongsong; Damste, Jaap S. Sinninghe; Hopmans, Ellen C.; Cohen, Andrew S. (Science, 2008)
The processes that control climate in the tropics are poorly understood. We applied compound-specific hydrogen isotopes (delta D) and the TEX(86) (tetraether index of 86 carbon atoms) temperature proxy to sediment cores from Lake Tanganyika to independently reconstruct precipitation and temperature variations during the past 60,000 years. Tanganyika temperatures follow Northern Hemisphere insolation and indicate that warming in tropical southeast Africa during the last glacial termination began to increase similar to 3000 years before atmospheric carbon dioxide concentrations. delta D data show that this region experienced abrupt changes in hydrology coeval with orbital and millennial-scale events recorded in Northern Hemisphere monsoonal climate records. This implies that precipitation in tropical southeast Africa is more strongly controlled by changes in Indian Ocean sea surface temperatures and the winter Indian monsoon than by migration of the Intertropical Convergence Zone.
id: 2047; PT: J; UT: WOS:000259902300046

Oxygen and carbon isotope records of calcareous nannofossils from the west Philippine Sea during the last 190ka - Jingtao, Zhao; Li, Tiegang; Chang, Fengming; Li, Jun (Earth Science.Journal of China University of Geoscience, 2008)
The piston core Ph05-5 recovered from the West Philippine Sea(16.049 degrees N, 124.344 degrees E, water depth 3382m) was used to study the delta (super 18) O and delta (super 13) C variations of calcareous nannofossils. The delta (super 18) O values of calcareous nannofossils were obviously lower in Holocene and the last interglaciation than those in the last and the penultimate glaciation. During the last 190 ka the nannofossil delta (super 18) O values were positively correlated with those of planktonic and benthic foraminifera from the same core. But the average delta (super 18) O value of nannofossils was 0.431X10 (super -3) , higher than that of planktonic foraminifera Globigerinoides rubber, and was 0.410X10 (super -3) , lower than that of planktonic foraminifera Neogloboquadrina dutertrei. All the above three average delta (super 18) O values were much lower than those of benthic foraminifera Cibicides wullerstorfi. The change of nannofossil delta (super 13) C values showed similar trends with the absolute abundance of calcareous nannofossils in core Ph05-5, which also indicates the primary productivity variations in the West Philippine Sea. The primary productivity stayed at a stable but relatively low level at MIS 6 and MIS 5e.There was an abrupt rise at the beginning of MIS 5d for the primary productivity which retained high value until 25 ka BP. The primary productivity showed a slight decline during MIS 2 and MIS 1, but still higher than that of MIS 6 and MIS 5e.
id: 1933; NO: Source type: scholarlyjournals; Object type: Article; Copyright: GeoRef in Process, Copyright 2011, American Geosciences Institute. After editing and indexing, this record will be added to Georef.; CSAUnique: 570969-5; AccNum: 570969-5; ISSN: 1000-2383; Peer Reviewed: true
Keywords: 02D; 24; algae; biochemistry; C-13/C-12; carbon; Cenozoic; Foraminifera; Geochemistry; Holocene; Invertebrata; Isotope geochemistry; isotope ratios; isotopes; Last glacial maximum; microfossils; nannofossils; north pacific; Northwest Pacific; O-18/O-16; oxygen; Pacific Ocean; paleo-oceanography; Philippine Sea; Plantae; Pleistocene; productivity; Protista; Quaternary; Quaternary geology; Stable isotopes; upper Pleistocene; West Pacific

PALEOPRODUCTIVITY VARIATION AND ITS CORRELATION WITH CLIMATE CHANGES:AN APPROACH OF LONG-CHAIN ALKENONE - Nan, Q.; Li, T.; Chen, Jinxia; Yu, X.; Li, Q. (Quaternary Sciences, 2008)
The accurate reconstruction of paleoproductivity is critical for understanding the carbon cycle in the past and for predicting the fate of anthropogenic carbon in the future.Biomarkers in marine sediments are useful tools for paleoenvirionment study and have been used as proxies for total and specific phytoplankton group paleoproductivity.Based on 17 AMS14C age controlling points,we report here molecular abundance data for alkenone and organic carbon isotopic data for bulk samples from a giant piston core MD05-2908(24°48.04'N,122°29.35'E).The aim is to evaluate the paleoproductivity and interpret the climatic-induced controlling factors for the past 7000aB.P.The results showed that the paleoproductivity in the South Okinawa Trough(SOT)fluctuated frequently in the past 7000aB.P.By correlating with the Titanium records from Huguang Marr and Cariaco Basin,we found out that the paleoproductivity was largely controlled by the latitude migration of ITCZ.The rapid southward shift of the ITCZ might have caused longer staying of the rainfall front in the source supply area,thus,led to intensified erosion,brought increased terrigenous material into the ECS and SOT by fluvial the terrigenous materil delivers to the SOT.Terrigenous input on the one hand might have fertilized the sea surface of SOT and stimulated the production,but on the other hand might have diluted the signal of marine derived input to the sediments.The lower production periods in the SOT correlated well with those ice-drift episodes recorded in the high latitude Atlantic Ocean,suggesting the strong relationships between high and low latitude climate.
id: 1968
Keywords: Alkenone; ITCZ; paleoproductivity; SOT; the last 7000aB.P.

Quaternary paleoceanography of the central arctic based on Integrated Ocean Drilling Program Arctic Coring Expedition 302 foraminiferal assemblages - Cronin, T. M.; Smith, S. A.; Eynaud, F.; O'Regan, M.; King, J. (Paleoceanography, 2008)
The Integrated Ocean Drilling Program (IODP) Arctic Coring Expedition (ACEX) Hole 4C from the Lomonosov Ridge in the central Arctic Ocean recovered a continuous 18 m record of Quaternary foraminifera yielding evidence for seasonally ice-free interglacials during the Matuyama, progressive development of large glacials during the mid-Pleistocene transition (MPT) similar to 1.2-0.9 Ma, and the onset of high-amplitude 100-ka orbital cycles similar to 500 ka. Foraminiferal preservation in sediments from the Arctic is influenced by primary (sea ice, organic input, and other environmental conditions) and secondary factors (syndepositional, long-term pore water dissolution). Taking these into account, the ACEX 4C record shows distinct maxima in agglutinated foraminiferal abundance corresponding to several interglacials and deglacials between marine isotope stages (MIS) 13-37, and although less precise dating is available for older sediments, these trends appear to continue through the Matuyama. The MPT is characterized by nearly barren intervals during major glacials (MIS 12, 16, and 22-24) and faunal turnover (MIS 12-24). Abundant calcareous planktonic (mainly Neogloboquadrina pachyderma sin.) and benthic foraminifers occur mainly in interglacial intervals during the Brunhes and very rarely in the Matuyama. A distinct faunal transition from calcareous to agglutinated foraminifers 200-300 ka in ACEX 4C is comparable to that found in Arctic sediments from the Lomonosov, Alpha, and Northwind ridges and the Morris Jesup Rise. Down-core disappearance of calcareous taxa is probably related to either reduced sea ice cover prior to the last few 100-ka cycles, pore water dissolution, or both.
id: 813; 281VR Times Cited:10 Cited References Count:84Y

Radiocarbon evidence for the importance of surface vegetation on fermentation and methanogenesis in contrasting types of boreal peatlands - Chanton, J. P.; Glaser, P. H.; Chasar, L. S.; Burdige, D. J.; Hines, M. E.; Siegel, D. I.; Tremblay, L. B.; Cooper, W. T. (Global Biogeochemical Cycles, 2008)
We found a consistent distribution pattern for radiocarbon in dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and methane replicated across spatial and temporal scales in northern peatlands from Minnesota to Alaska. The (14)C content of DOC is relatively modern throughout the peat column, to depths of 3 m. In sedge-dominated peatlands, the (14)C contents of the products of respiration, CH(4) and DIC, are essentially the same and are similar to that of DOC. In Sphagnum- and woody plant-dominated peatlands with few sedges, however, the respiration products are similar but intermediate between the (14)C contents of the solid phase peat and the DOC. Preliminary data indicates qualitative differences in the pore water DOC, depending on the extent of sedge cover, consistent with the hypothesis that the DOC in sedge-dominated peatlands is more reactive than DOC in peatlands where Sphagnum or other vascular plants dominate. These data are supported by molecular level analysis of DOC by ultrahigh-resolution mass spectrometry that suggests more dramatic changes with depth in the composition of DOC in the sedge-dominated peatland pore waters relative to changes observed in DOC where Sphagnum dominates. The higher reactivity of DOC from sedge-dominated peatlands may be a function of either different source materials or environmental factors that are related to the abundance of sedges in peatlands.
id: 1949; PT: J; UT: WOS:000262041000002

Reply to Comment on "The timing and evolution of the post-glacial transgression across the Sea of Marmara shelf south of Istanbul" by Hiscott et al., Marine Geology 248, 228-236 - Eris, K. K.; Ryan, W. B. F.; Cagatay, M. N.; Lericolais, G.; Sancar, U.; Menot, G.; Bard, E. (Marine Geology, 2008)
In their comment Hiscott and co-authors adhere rigidly to ages and sources for sedimentary units in the subsurface of the Marmara shelf that they have previously reported in their publications from 2002 through 2007. This adherence is in spite of a superior age-depth model from our 13 m-long sediment core that penetrated deeply into the deposits under consideration and in disregard to the results of subsequent more-detailed and full-coverage mapping of the region under scrutiny. The age revisions are dismissed by the authors of the comment as representing sediments severely disturbed during coring. We rebut this criticism. The Bosporus source attributed by them to the sedimentary units sampled and dated by us appears to be driven by their conception that the Black Sea had a persistent outflow prior to its two-way connection with Marmara. Irrespective of whether the outflow was persistent, our reply shows that the drawing of the isopachs of the sedimentary units by Hiscott and coauthors was accomplished in a fashion to promote the Bosporus source hypothesis regardless of the geographic limits of their survey. The ages assigned to the units are equally indeterminate because the cores used by them have missing core tops of unknown lengths that are not discussed in their publications. Furthermore, the sub-bottom reflectors at the sites where the reflectors were calibrated to their only core without a missing top are actually hidden by the finite width of the bottom reflecting wavelet. (C) 2008 Elsevier B.V. All rights reserved.
id: 784; 377ZE Times Cited:0 Cited References Count:33Y

Subtropical Atlantic salinity variability and Atlantic meridional circulation during the last deglaciation - Carlson, A. E.; Oppo, D. W.; Came, R. E.; LeGrande, A. N.; Keigwin, L. D.; Curry, W. B. (Geology, 2008)
During the last deglaciation (ca. 21-10 ka), freshening of the North Atlantic surface likely caused reductions in Atlantic meridional overturning circulation (AMOC); the mechanisms related to AMOC recovery remain poorly understood. Here we present three new deglacial surface temperature and delta O-18(seawater) (delta O-18(sw)) reconstructions from the western subtropical North and South Atlantic. Similarities to tropical Caribbean and western Atlantic delta O-18(sw) records suggest that a salty surface water mass accumulated in the western Atlantic from 27 degrees S to 33 degrees N during periods of reduced AMOC. However, delta O-18(sw) decreases led deep AMOC resumption by hundreds of years. We suggest that the northward export of salt previously trapped in the western Atlantic resulted in the early establishment of a shallow overturning circulation that eventually culminated in deep AMOC resumption, implying that AMOC may constitute a self-limiting system.
id: 862; ISI Document Delivery No.: 381WN Times Cited: 5 Cited Reference Count: 32 Cited References: *CLIMAP PROJ MEMB, 1981, GEOL SOC AM MAP CHAR ANAND P, 2003, PALEOCEANOGRAPHY, V18, ARTN 1050 BENWAY HM, 2006, PALEOCEANOGRAPHY, V21, ARTN PA3008 BEVINGTON P, 2002, DATA REDUCTION ERROR BOYLE EA, 1987, NATURE, V330, P35 BROECKER WS, 1990, PALEOCEANOGRAPHY, V5, P469 CARLSON AE, 2007, P NATL ACAD SCI USA, V104, P6556, DOI 10.1073/pnas.0611313104 CLARK PU, 2004, SCIENCE, V304, P1141 GRIMM EC, 2006, QUATERNARY SCI REV, V25, P2197, DOI 10.1016/j.quascirev.2006.04.008 GROOTES PM, 1993, NATURE, V366, P552 KASPI Y, 2004, PALEOCEANOGRAPHY, V19, ARTN PA3004 KNORR G, 2003, NATURE, V424, P532, DOI 10.1038/nature01855 LEA DW, 2003, SCIENCE, V301, P1361 LEDUC G, 2007, NATURE, V445, P908, DOI 10.1038/nature05578 LEGRANDE AN, 2006, GEOPHYS RES LETT, V33, ARTN L12604 LEGRANDE AN, 2008, PALEOCEANOGRAPHY, V23, DOI 10.1029/2008PA001610 MCMANUS JF, 2004, NATURE, V428, P834, DOI 10.1038/nature02494 OPPO DW, 2007, GEOPHYS RES LETT, V34, ARTN L13701 PEETERS FJC, 2004, NATURE, V430, P661, DOI 10.1038/nature02785 PETERSON LC, 2000, SCIENCE, V290, P1947 ROBINSON LF, 2005, SCIENCE, V310, P1469, DOI 10.1126/science.1114832 RUHLEMANN C, 1999, NATURE, V402, P511 SCHMIDT GA, 2007, J GEOPHYS RES-ATMOS, V112, ARTN D10103 SCHMIDT MW, 2004, NATURE, V428, P160, DOI 10.1038/nature02346 SCHMIDT MW, 2006, NATURE, V443, P561, DOI 10.1038/nature05121 SCHMITZ WJ, 1995, REV GEOPHYS, V33, P151 SKINNER LC, 2006, QUATERNARY SCI REV, V25, P3312, DOI 10.1016/j.quascirev.2006.07.005 STOUFFER RJ, 2006, J CLIMATE, V19, P1365 THOMAS AL, 2006, EARTH PLANET SC LETT, V241, P493, DOI 10.1016/j.epsl.2005.11.031 WANG XF, 2004, NATURE, V432, P740, DOI 10.1038/nature03067 WEAVER AJ, 2003, SCIENCE, V299, P1709 WELDEAB S, 2006, EARTH PLANET SC LETT, V241, P699, DOI 10.1016/j.epsl.2005.11.012 Carlson, Anders E. Oppo, Delia W. Came, Rosemarie E. LeGrande, Allegra N. Keigwin, Lloyd D. Curry, William B. Geological soc amer, inc Boulder; YY

Terrigenous organic matter in sediments from the Fly River delta-clinoform system (Papua New Guinea) - Goñi, M. A.; Monacci, N.; Gisewhite, R.; Crockett, J.; Nittrouer, C.; Ogston, A.; Alin, S. R.; Aalto, R. (Journal of Geophysical Research-Earth Surface, 2008)
Although an inordinate fraction of the global sediment flux to the ocean occurs in tropical mountainous river margins, little is known regarding the sources and fate of organic matter in these systems. To address these knowledge gaps, the distribution and composition of organic matter in sediments from the Fly River delta-clinoform were examined in the context of the source-to-sink study of the Papuan Continuum. The significant contrasts in the texture of seabed sediments measured across the study area coincided with stark contrasts in concentration and composition of the sedimentary organic matter. Coarser sediments displayed significantly lower organic carbon and nitrogen contents, more enriched stable carbon and nitrogen compositions, lower lignin product yields, and distinctly different lignin and nonlignin product compositions than their fine-textured counterparts. Compositional differences were also measured between high-and low-density fractions of selected sediment samples. Subsurface sediments showed marked compositional variations that were predominantly associated with changes in the texture of the deposits. Most sediments were characterized by moderate carbon loadings (0.5-1.0 mg C m(-2)), although several samples from the outer topset region, an area of sediment bypass, were characterized by lower carbon loadings indicative of enhanced carbon losses. Overall, the organic matter in both surface and subsurface sediments appeared to have predominantly a terrigenous origin, with no evidence for dilution and/or replacement by marine carbon. The measured compositions were consistent with contributions from modern vascular plant detritus, aged soil organic matter, and very old or fossil organic matter devoid of recognizable biochemicals.
id: 826; 257VD Times Cited:8 Cited References Count:78Y

TRACING PAST CIRCULATION CHANGES IN THE WESTERN SOUTH ATLANTIC BASED ON PLANKTONIC FORAMINIFERA - Toledo, F. A. L.; Costa, K. B.; Pivel, M. A. G.; Campos, E. (Revista Brasileira de Paleontologia, 2008)
In this study, we traced past oceanographic changes in the southeastern Brazilian Continental Margin based on the ratio between two planktonic foraminifera species (Globigerina bulloides and Globigerinoides ruber), along a core located close to the transition between the tropical and subtropical biogeographic provinces. Each species is representative of a biogeographic province and has excluding ecological preferences. According to our interpretation, periods of low G. bulloides/G. ruber values would characterize a stronger influence of the warm, oligotrophic tropical water and, conversely, periods of high G. bulloides/G. ruber values correspond to a stronger influence of colder and nutrient-richer waters. Changes in the relative influence of the different water masses are strongly dependent on the regional wind field which affects the upper-level circulation mostly by the latitudinal displacement of the bifurcation of the South Equatorial Current which, in turn, has strong impacts on the Brazil Current’s strength and on the intensity of the upwelling regime in the study area. The analysis of the last 30 kyr record, suggests that productivity was highly increased both around the Last Glacial Maximum and the Younger Dryas event. In between these events, the record suggests that productivity was severely decreased during deglaciation. Also, our record suggests a gradual decrease in productivity from 11 kyr BP through the Holocene which can be explained by a progressively stronger Brazil Current resulting from a southward displacement of the Intertropical Convergence Zone. Our results are consistent with other studies providing estimates of changes in trade wind strength and in the extent of the climatic belts through time.
id: 1973

A validated description of age and growth of western Atlantic bluefin tuna (Thunnus thynnus) - Neilson, J. D.; Campana, S. E. (Canadian Journal of Fisheries and Aquatic Sciences, 2008)
Current stock assessments of western Atlantic bluefin tuna (Thunnus thymus) use age-structured population analyses, but the age assignment in the population model is made using all age-length relationship derived from mark and recapture studies largely completed during the 1970s. In our study, the deposition of bomb radiocarbon was used as a dated mark to validate age inferences of bluefin tuna and to compare the validated ages with those predicted from the age-length relationship. The results support the view that the age-length relationship currently in use for the assessment overestimates growth rate and the ultimate size of the fish. These findings have implications for the estimation of stock productivity and may negatively impact the rebuilding schedules established by fisheries managers.
id: 805; 348EN Times Cited:4 Cited References Count:12Y

Very high-resolution seismo-acoustic imaging of seagrass meadows (Mediterranean Sea): Implications for carbon sink estimates - Lo Iacono, C.; Mateo, M. A.; Gracia, E.; Guasch, L.; Carbonell, R.; Serrano, L.; Serrano, O.; Danobeitia, J. (Geophysical Research Letters, 2008)
Posidonia oceanica is a widespread coastal Mediterranean seagrass which accumulates in its subsurface large quantities of organic material derived from its roots, rhizomes and leaf sheaths embedded in sandy sediments. These organic deposits may be up to several meters thick as they accumulate over thousands of years forming the matte, whose high content in organic carbon plays a major role in the global ocean carbon cycle. In this study, very highresolution seismo-acoustic methods were applied to image the subsurface features of a P. oceanica seagrass meadow at Portlligat (Cadaque's, Girona, Spain), in the NW-Mediterranean Sea. Our findings yield fresh insights into the settling of the P. oceanica meadow in the study area, and define with unprecedented detail the potential volume occupied by the matte. A strong reflector, located from 4.3 to 11.7 m depth, was recognized in several seismo-acoustic profiles as the substratum on which P. oceanica first settled in the study area. A 3D bathymetric model of this substratum allowed us to reconstruct the Portlligat palaeo-environment prior to the settling of P. oceanica, which corresponded to a shallow coastal setting protected from the open sea. A core drilled in the meadow at Portlligat revealed the presence of a 6 m thick dense matte composed of medium to coarse sandy sediments mixed with plant debris and bioclasts. Radiocarbon datings revealed a constant accretion rate of the matte of about 1.1 m/kyr. Gravelly bioclastic deposits observed at the base of the core correspond to the base of the matte and gave a date of 5616 +/- 46 Cal yr BP. For the first time, very high-resolution marine geophysical techniques allowed us to accurately define the volume occupied by P. oceanica matte, which in the study area reaches up to almost 220,000 +/- 17,400 m(3). This result is an important step forward in our efforts to estimate the size of the carbon sink represented by P. oceanica meadows along the Mediterranean coasts significantly contributing to the biosphere carbon cycle.
id: 896; 351AE Times Cited:1 Cited References Count:14
Keywords: cycle

14C and 13C isotopic characterization of organic carbon in surface waters of the South Atlantic Bight - De Alteris, J. A.; Bauer, J. E.; Perkey, D. W.; Keesee, E. J.; Cai, W. J. (ASLO Aquatic Sciences Meeting, 2007)
id: 1026

A 28-ka history of sea surface temperature, primary productivity and planktonic community variability in the western Arabian Sea - Pourmand, Ali; Marcantonio, Franco; Bianchi, Thomas S.; Canuel, Elizabeth A.; Waterson, Elizabeth J. (Paleoceanography, 2007)
Uranium series radionuclides and organic biomarkers, which represent major groups of planktonic organisms, were measured in western Arabian Sea sediments that span the past 28 ka. Variability in the past strength of the southwest and northeast monsoons and its influence on primary productivity, sea surface temperature (SST), and planktonic community structure were investigated. The average alkenone-derived SST for the last glacial period was ∼3°C lower than that measured for the Holocene. Prior to the deglacial, the lowest SSTs coincide with the highest measured fluxes of organic biomarkers, which represent primarily a planktonic suite of diatoms, coccolithophorids, dinoflagellates, and zooplankton. We propose that intensification of winter northeast monsoon winds during the last glacial period resulted in deep convective mixing, cold SSTs and enhanced primary productivity. In contrast, postdeglacial (<17 ka) SSTs are warmer during times in which biomarker fluxes are high. Associated with this transition is a planktonic community structure change, in which the ratio of the average cumulative flux of diatom biomarkers to the cumulative flux of coccolithophorid biomarkers is twice as high during the deglacial and Holocene than the average ratio during the last glacial period. We suggest that this temporal transition represents a shift from a winter northeast monsoon-dominated (pre-17 ka) to a summer southwest monsoon-dominated (post-17 ka) wind system.

Age under-estimation in New Zealand porbeagle sharks (Lamna nasus): is there an upper limit to ages that can be determined from shark vertebrae? - Francis, M. P.; Campana, S. E.; Jones, C. M. (Marine and Freshwater Research, 2007)
Annual deposition of growth bands in vertebrae has been validated for many shark species, and is now widely regarded as the norm. However, vertebrae are part of the shark's axial skeleton, and band deposition may stop in old sharks when somatic growth ceases. We aged vertebral sections from New Zealand porbeagle sharks (Lamna nasus) under reflected white light and using X-radiographs. Bomb radiocarbon assays supported vertebral age estimates up to similar to 20 years, but not at older ages. The results suggest that older porbeagles were under-aged by as much as 50% from vertebral band counts, presumably because band width declined to a point where it became unresolvable. This has important implications for growth studies on other long-lived sharks. Estimated ages at sexual maturity were 8-11 years for males and 15-18 years for females, and longevity may be similar to 65 years. New Zealand and North Atlantic porbeagles differ in these parameters, and in length at maturity and maximum length, suggesting genetic isolation of the two populations.
id: 1857; 131AF Times Cited:5 Cited References Count:60Y

Amplitude and timing of temperature and salinity variability in the subpolar North Atlantic over the past 10 k.y. - Came, R. E.; Oppo, D. W.; McManus, J. F. (Geology, 2007)
Paired planktic foraminiferal δ18O and Mg/Ca data reveal trends of increasing temperatures (∼3 °C) and salinities in the subpolar North Atlantic over the course of the Holocene, which were punctuated by abrupt events. The trends likely reflect an insolation-forced northward retreat of the boundary between polar and North Atlantic subsurface waters. The superimposed variability does not appear to be periodic, but tends to recur within a broad millennial band. The records provide convincing evidence of open-ocean cooling (nearly 2 °C) and freshening during the 8.2 ka event, and suggest similar conditions at 9.3 ka. However, the two largest temperature oscillations in our record (∼2 °C) occurred during the past 4 k.y., suggesting a recent increase in temperature variability relative to the mid-Holocene, perhaps in response to neoglaciation, which began at about this time.
id: 983
Keywords: Björn Drift; Mg/Ca; Neogloboquadrina pachyderma dextral; Ocean Drilling Program Site 984; paleotemperature

Atlantic meridional overturning circulation during the Last Glacial Maximum - Lynch-Stieglitz, J.; Adkins, J. F.; Curry, W. B.; Dokken, T.; Hall, I. R.; Herguera, J. C.; Hirschi, J. J. M.; Ivanova, E. V.; Kissel, C.; Marchal, O.; Marchitto, T. M.; McCave, I. N.; et al. (Science, 2007)
The circulation of the deep Atlantic Ocean during the height of the last ice age appears to have been quite different from today. We review observations implying that Atlantic meridional overturning circulation during the Last Glacial Maximum was neither extremely sluggish nor an enhanced version of present-day circulation. The distribution of the decay products of uranium in sediments is consistent with a residence time for deep waters in the Atlantic only slightly greater than today. However, evidence from multiple water-mass tracers supports a different distribution of deep-water properties, including density, which is dynamically linked to circulation.
id: 1897; ISI Document Delivery No.: 153XD Times Cited: 46 Cited Reference Count: 61 Cited References: ADKINS JF, 1997, NATURE, V390, P154 ADKINS JF, 1999, RECONSTRUCTING OCEAN, P103 ADKINS JF, 2003, EARTH PLANET SC LETT, V216, P109, DOI 10.1016/S0012-821X(03)00502-8 BACON MP, 1982, J GEOPHYS RES, V87, P2045 BICKERT T, 2004, S ATLANTIC LATE QUAT, P671 BOYLE EA, 1982, SCIENCE, V218, P784 BROECKER W, 1988, RADIOCARBON, V30, P261 CHASE Z, 2002, EARTH PLANET SC LETT, V204, P215 CLARK PU, 2002, NATURE, V415, P863 CONKRIGHT ME, 2002, WORLD OCEAN ATLAS 20 CURRY WB, 1982, QUATERNARY RES, V18, P218 CURRY WB, 2005, PALEOCEANOGRAPHY, V20, ARTN PA1017 DUPIESSY JC, 1980, NATURE, V286, P479 DUPLESSY JC, 1988, PALEOCEANOGRAPHY, V3, P343 DUPLESSY JC, 1989, RADIOCARBON, V31, P493 ELDERFIELD H, 2006, EARTH PLANET SC LETT, V250, P633, DOI 10.1016/j.epsl.2006.07.041 EMILIANI C, 1955, J GEOL, V63, P538 GANACHAUD A, 2000, NATURE, V408, P453 GEBBIE G, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q11N07 GHERARDI JM, 2005, EARTH PLANET SC LETT, V240, P710, DOI 10.1016/j.epsl.2005.09.061 HALL IR, 2006, GEOPHYS RES LETT, V33, ARTN L16616 HALL MM, 1982, DEEP-SEA RES, V29, P339 HEWITT CD, 2003, CLIM DYNAM, V20, P203, DOI 10.1007/s00382-002-0272-6 HIRSCHI JJM, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q10N04 HUYBERS P, 2007, J PHYS OCEANOGR, V37, P394, DOI 10.1175/JPO3018.1 KEIGWIN LD, 2004, PALEOCEANOGRAPHY, V19, ARTN PA4012 KISSEL C, 1999, EARTH PLANET SC LETT, V171, P489 KITOH A, 2001, GEOPHYS RES LETT, V28, P2221 KUCERA M, 2005, QUATERNARY SCI REV, V24, P951, DOI 10.1016/j.quascirev.2004.07.014 KUMAR N, 1993, NATURE, V362, P45 LEGRAND P, 1995, PALEOCEANOGRAPHY, V10, P1011 LEGRANDE AN, 2006, P NATL ACAD SCI USA, V103, P837 LYNCHSTIEGLITZ J, 1999, PALEOCEANOGRAPHY, V14, P360 LYNCHSTIEGLITZ J, 2001, GEOCHEM GEOPHY GEOSY, V2, DOI 10.1029/2001GC000208 LYNCHSTIEGLITZ J, 2003, TREATISE GEOCHEMISTR, V6, P433 LYNCHSTIEGLITZ J, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q10N03 MANABE S, 1988, J CLIMATOL, V1, P841 MANGINI A, 1998, NATURE, V392, P347 MARCHAL O, 2000, PALEOCEANOGRAPHY, V15, P625 MARCHITTO TM, 2000, PALEOCEANOGRAPHY, V15, P299 MARCHITTO TM, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q12003 MAROTZKE J, 1999, J GEOPHYS RES-OCEANS, V104, P29529 MATSUMOTO K, 1999, PALEOCEANOGRAPHY, V14, P149 MCCAVE IN, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q10N05 MCMANUS JF, 2004, NATURE, V428, P834, DOI 10.1038/nature02494 MIX AC, 2001, QUATERNARY SCI REV, V20, P627 OTTOBLIESNER BL, 2006, J CLIMATE, V19, P2526 PAUL A, 2003, PALEOCEANOGRAPHY, V18, ARTN 1058 PIOTROWSKI AM, 2005, SCIENCE, V307, P1933, DOI 10.1126/science.1104883 ROBINSON LF, 2005, SCIENCE, V310, P1469, DOI 10.1126/science.1114832 ROEMMICH D, 1985, DEEP-SEA RES, V32, P619 SARNTHEIN M, 1994, PALEOCEANOGRAPHY, V9, P209 SCHMITTNER A, 2005, GLOBAL BIOGEOCHEM CY, V19, ARTN GB3004 SHACKLETON NJ, 1988, NATURE, V335, P708 SHIN SI, 2003, CLIM DYNAM, V20, P127, DOI 10.1007/s00382-002-0260-x STOMMEL H, 1961, TELLUS, V13, P224 STREETER SS, 1979, SCIENCE, V203, P168 VELLINGA M, 2002, CLIMATIC CHANGE, V54, P251 WUNSCH C, 2003, QUATERNARY SCI REV, V22, P371 YU EF, 1996, NATURE, V379, P689 ZHANG R, 2005, J CLIMATE, V18, P1853 Lynch-Stieglitz, Jean Adkins, Jess F. Curry, William B. Dokken, Trond Hall, Ian R. Herguera, Juan Carlos Hirschi, Joel J. -M. Ivanova, Elena V. Kissel, Catherine Marchal, Olivier Marchitto, Thomas M. McCave, I. Nicholas McManus, Jerry F. Mulitza, Stefan Ninnemann, Ulysses Peeters, Frank Yu, Ein-Fen Zahn, Rainer Amer assoc advancement science Washington; YY

The Environmental Anomalies in the Northeastern East China Sea during the Last 3000 Years: Implications for El Nino Activity in the Holocene - Chang, F.; Zhuang, L.; Li, T.; Yan, J.; Li, Q. (9th International Conference on Paleoceanography (ICP 9), 2007)
id: 1935; TY: CPAPER; NO: Source type: conferencepapers&proceedings; Object type: Conference Paper; CSAUnique: CPI-4728602; AccNum: 4728602(China)
Keywords: Donghai Sea; Holocene; Multidisciplinary; Paleo studies; Paleoenvironments; U 7000

Evolution and latitudinal diversity gradient: Speciation, extinction, and biogeography - Mittelbach, G. G.; Schemske, D. W.; Cornell, H. V.; Allen, A. P.; Brown, J. M.; Bush, M. B. (Ecology Letters, 2007)
id: 456

The Geographic, Geological and Oceanographic Setting of the Indus River - Inam, A.; Clift, P. D.; Giosan, L. (Large Rivers, 2007)
id: 867; Y

Holocene sea-level oscillations and environmental changes on the Eastern Black Sea shelf - Ivanova, E. V.; Murdmaa, I. O.; Chepalyga, A. L.; Cronin, T. M.; Pasechnik, I. V.; Levchenko, O. V.; Howe, S. S.; Manushkina, A. V.; Platonova, E. A. (Palaeogeography Palaeoclimatology Palaeoecology, 2007)
A multi-proxy study of four sediment cores from the Eastern (Caucasian) Black Sea shelf revealed five transgressive-regressive cycles overprinted on the general trend of glacioeustatic sea-level rise during the last 11,000 C-14 yr. These cycles are well represented in micro-and macrofossil assemblages, sedimentation rates, and gain size variations. The oldest recovered sediments were deposited in the Neoeuxinian semi-freshwater basin (similar to 10,500-9000 C-14 yr BP) and contain a Caspian-type mollusk fauna dominated by Dreissena rostriformis. Low delta O-18 and delta C-13 values are measured on this species. The first appearance of marine mollusks and ostracodes from the Mediterranean is established in this part of the Black Sea at similar to 8200 C-14 yr BP, i.e., about 1000-2000 yr later than the appearance of marine microfossils in the deeper part of the sea. The Early Holocene (Bugazian to Vityazevian) condensed section of shell and shelly mud sediments with at least two hiatuses represent a high-energy shelf-edge facies. It contains a transitional assemblage representing a mixture of Caspian and Mediterranean fauna. This pattern suggests a dual-flow regime via the Bosphorus after 8200 C-14 yr BR Caspian species disappear and oligolialine species decrease in abundance during the Vityazevian-Prekalamitian cycle. Later, during the Middle to Late Holocene, low sea-level stands are characterized by shell layers, whereas silty mud with various mollusk and ostracode assemblages rapidly accumulated during transgressions. Restricted mud accumulation, as well as benthic faunal composition and abundance, suggest high-energy and well-ventilated bottom water during low sea-level stands. A trend of O-18 enrichment in mollusk shells points to an increase in bottom-water salinity during the Vityazevian to Kalamitian transgressions (similar to 7000 to 5700 C-14 yr BP) due to a more open connection with the Mediterranean, while a pronounced increase in polyhaline species abundance is established during the Kalamitian to Djemetean transgressions (similar to 6400 to 2700 C-14 yr BP). However, the composition of the faunal assemblage indicates that bottom-water salinity never exceeded modem values of 18-20 psu. (c) 2006 Elsevier B.V. All rights reserved.
156gzTimes Cited:22Cited References Count:51

Human responses to Middle Holocene climate change on California's Channel Islands - Kennett, D. J.; Kennettb, J. P.; Erlandson, J. M.; Cannariato, K. G. (Quaternary Science Reviews, 2007)
High-resolution archaeological and paleoenvironmental records from California's Channel Islands provide a unique opportunity to examine potential relationships between climatically induced environmental changes and prehistoric human behavioral responses. Available climate records in western North America (7-3.8 ka) indicate a severe dry interval between 6.3 and 4.8 ka embedded within a generally warm and dry Middle Holocene. Very dry conditions in western North America between 6.3 and 4.8 ka correlate with cold to moderate sea-surface temperatures (SST) along the southern California Coast evident in Ocean Drilling Program (ODP) Core 893A/B (Santa Barbara Basin). An episode of inferred high marine productivity between 6.3 and 5.8 ka corresponds with the coldest estimated SSTs of the Middle Holocene, otherwise marked by warm/low productivity marine conditions (7.5-3.8 ka). The impact of this severe aridity on humans was different between the northern and southern Channel Islands, apparently related to degree of island isolation, size and productivity of islands relative to population, fresh water availability, and on-going social relationships between island and continental populations. Northern Channel Islanders seem to have been largely unaffected by this severe and phase. In contrast, cultural changes on the southern Channel Islands were likely influenced by the climatically induced environmental changes. We suggest that productive marine conditions coupled with a dry terrestrial climate between 6.3 and 5.8 ka stimulated early village development and intensified fishing on the more remote southern islands. Contact with people on the adjacent southern California Coast increased during this time with increased participation in a down-the-line trade network extending into the western Great Basin and central Oregon. Genetic similarities between Middle Holocene burial populations on the southern Channel Islands and modern California Uto-Aztecan populations suggest Middle Holocene movement of people at this time from southern California desert environs westward to the southern islands, a migration perhaps stimulated by increased continental aridity. (c) 2006 Elsevier Ltd. All rights reserved.
158ghTimes Cited:49Cited References Count:167

Late Holocene barrier island collapse; Outer Banks, North Carolina, USA - Culver, Stephen J.; Grand Pre, Candace A.; Mallinson, David J.; Riggs, Stanley R.; Corbett, D. Reide; Foley, Jennifer; Hale, Michael; Metger, Lauren; Ricardo, John; Rosenberger, Jeb; Smith, Christopher G.; Smith, Curtis W.; et al. (The Sedimentary Record, 2007)
We document here the threat of large scale destruction (collapse) of barrier islands based on the study of many cores taken along the Outer Banks and in Pamlico Sound, North Carolina.Around 1,100 cal yr BP, probably as the result of hurricane activity, portions of the southern Outer Banks must have collapsed to allow normal salinity waters to bathe southern Pamlico Sound for several hundred years. Such collapse could occur again during our current regime of global warming, rising sea level and increased tropical cyclone activity. The economic effect of barrier island break collapse on Outer Banks communities would be devastating.
id: 1887; ISSN: 1543-8740 Language: English References: 16; illus. incl. strat. col., geol. sketch map United States (USA) Latitude:N350000,N353000 Longitude:W0753000,W0760000
Keywords: 24, Quaternary geology; algae; assemblages; barrier islands; Cenozoic; changes; clastic sediments; cores; diatoms; erosion; Foraminifera; geologic hazards; Holocene; hurricanes; Invertebrata; landform evolution; lithofacies; littoral; microfossils; North Carolina; Outer Banks; Pamlico Sound; Plantae; preservation; Protista; Quaternary; salinity; sand; sea-level; sediments; United States; upper Holocene; Vibroseis

Late Holocene fine-grained sediments of the Balearic Abyssal Plain, Western Mediterranean Sea - Zuniga, D.; Garcia-Orellana, J.; Calafat, A.; Price, N. B.; Adatte, T.; Sanchez-Vidal, A.; Canals, M.; Sanchex-Cabeza, J. A.; Masque, P.; Fabres, J. (Marine Geology, 2007)
The Late Holocene fine-grained sedimentation in the deep central Balearic Abyssal Plain, Western Mediterranean Sea, has been studied after the analysis of high quality sediment cores from three multicoring stations, named A, B and C. The coring stations are 25 km apart from each other and form a triangle that is at the greatest distance from the nearest landmasses. The sediments consist of foraminifer-pteropod oozes (layers U1 and U4 from bottom to top), two pteropod oozes (U2 and U5) and a turbidite layer (U3). The same sequence has been identified in the three cores. The turbidite layer U3 that lies on top of U2 (C-14 AMS dated at 1814 cal yrs BP) ranges from 5 to I I cm thick and is clearly distinguished from the dominating hemipelagic sediments by colour variations, higher water content and the absence of planktonic foraminifer shells. Rather uniform values of organic carbon and nitrogen are also characteristic of the U3 turbidite unit, likely because of homogenisation during transport and emplacement. In addition, U3 unit shows higher contents of terrigenous elements such as K and Fe. Otherwise, the presence of zeolites in the turbidite layer supports the hypothesis of the Sardinian continental margin, where pyroclastic deposits are known, as the most likely source area for U3. Our results demonstrate the ability of turbidity currents originating on the margins surrounding the Balearic Abyssal Plain to reach the very centre of the basin during high sea level still stands as the present one. (c) 2006 Elsevier B.V. All rights reserved.
id: 624; 139VA Times Cited:6 Cited References Count:57

Late quaternary paleoseismology of the southern Steens fault zone, northern Nevada - Personius, Stephen F.; Crone, Anthony J.; Machette, Michael N.; Mahan, Shannon A.; Kyung, Jai Bok; Cisneros, Hector; Lidke, David J. (Bulletin of the Seismological Society of America, 2007)
The 192-km-long Steens fault zone is the most prominent normal fault system in the northern Basin and Range province of western North America. We use trench mapping and radiometric dating to estimate displacements and timing of the last three surface-rupturing earthquakes (E1-E3) on the southern part of the fault south of Denio, Nevada. Coseismic displacements range from 1.1 to 2.2 +/- 0.5 m, and radiometric ages indicate earthquake times of 11.5 +/- 2.0 ka (E3), 6.1 +/- 0.5 ka (E2), and 4.6 +/- 1.0 ka (E1). These data yield recurrence intervals of 5.4 +/- 2.1 k.y. between E3 and E2, 1.5 +/- 1.1 k.y. between E2 and E1, and an elapsed time of 4.6 +/- 1.0 k.y. since El. The recurrence data yield variable interval slip rates (between 0.2 +/- 0.22 and 1.5 +/- 2.3 mm/yr), but slip rates averaged over the past similar to 18 k.y. (0.24 +/- 0.06 mm/year) are similar to long-term (8.5-12.5 Ma) slip rates (0.2 +/- 0.1 mm/yr) measured a few kilometers to the north. We infer from the lack of significant topographic relief across the fault in Bog Hot Valley that the fault zone is propagating southward and may now be connected with a fault at the northwestern end of the Pine Forest Range. Displacements documented in the trench and a rupture length of 37 km indicate a history of three latest Quaternary earthquakes with magnitudes of M 6.6-7.1 on the southern part of the Steens fault zone.
id: 2022; PT: J; UT: WOS:000249930900021

North Atlantic intermediate depth variability during the Younger Dryas; evidence from benthic foraminiferal Mg/Ca and the GFDL R30 coupled climate model - Came, Rosemarie E.; Curry, William B.; Oppo, Delia W.; Broccoli, Anthony J.; Stouffer, Ronald J.; Lynch-Stieglitz, Jean (Geophysical Monograph, vol. 173, 2007)
id: 857; American Geophysical Union 2005 fall meeting, San Francisco, CA, United States, Dec 5-9, 2005 NSF grants OCE-0096495, ATM-0502428, OCE-0096472, OCE-0220776 and ATM-0501351 References: 72; illus.; Y
Keywords: 24, Quaternary geology; Atlantic Ocean; benthic environment; Cenozoic; chemical ratios; Foraminifera; Glaciation; Gulf of Mexico; ice cores; Invertebrata; isotope ratios; isotopes; Little Bahama Bank; Mg/Ca; microfossils; North Atlantic; O-18/O-16; oxygen; paleo-oceanography; paleobathymetry; paleosalinity; paleotemperature; Pleistocene; Protista; Quaternary; Stable isotopes; Straits of Florida; upper; upper Weichselian; Weichselian; Younger Dryas

Paleoecology and ecosystem restoration: case studies from Chesapeake Bay and the Florida Everglades - Willard, D. A.; Cronin, T. M. (Frontiers in Ecology and the Environment, 2007)
Climate extremes that cause droughts, floods, or large temperature fluctuations can complicate ecosystem restoration efforts focused on local and regional human disturbance. Restoration targets are often based primarily on monitoring data and modeling simulations, which provide information on species' short-term response to disturbance and environmental variables. Consequently, the targets may be unsustainable under the spectrum of natural variability inherent in the system or under future climate change. Increasingly, ecologists and restoration planners recognize the value of the long temporal perspective provided by paleoecological data. Advances in paleoclimatology, including better climate proxy methods and temporal resolution, contribute to our understanding of ecosystem response to anthropogenic and climatic forcing at all time scales. We highlight paleoecological research in the Chesapeake Bay and the Florida Everglades and summarize the resulting contributions to restoration planning. Integration of paleoecological, historic, monitoring, and modeling efforts will lead to the development of sustainable, adaptive management strategies for ecosystem restoration.
id: 811; 227MD Times Cited:5 Cited References Count:51Y

Paleoenvironmental change in the middle Okinawa Trough since the last deglaciation: Evidence from the sedimentation rate and planktonic foraminiferal record - Xiang, R.; Sun, Y. B.; Li, T. G.; Oppo, D. W.; Chen, M. H.; Zheng, F. (Palaeogeography Palaeoclimatology Palaeoecology, 2007)
Well-dated, high-resolution records of planktonic foraminifera and oxygen isotopes from two sediment cores, A7 and E017, in the middle Okinawa Trough reveal strong and rapid millennial-scale climate changes since similar to 18 to 17 thousand years before present (kyr B.P.). Sedimentation rate shows a sudden drop at similar to 11.2 cal. kyr B.P. due to a rapid rise of sea level after the Younger Dryas (YD) and consequently submergence of the large continental shelf on the East China Sea (ECS) and the retreat of the estuary providing sediment to the basin. During the last deglaciation, the relative abundance of warm and cold species of planktonic foraminifera fluctuates strongly, consistent with the timing of sea surface temperature (SST) variations determined from Mg/Ca measurements of planktonic foraminifera from one of the two cores. These fluctuations are coeval with climate variation recorded in the Greenland ice cores and North Atlantic sediments, namely Heinrich event 1 (H1), Bolling-Allerod (B/A) and YD events. At about 9.4 kyr B.P., a sudden change in the relative abundance of shallow to deep planktonic species probably indicates a sudden strengthening of the Kuroshio Current in the Okinawa Trough, which was synchronous with a rapid sea-level rise at 9.5-9.2 kyr B.P. in the ECS, Yellow Sea (YS) and South China Sea (SCS). The abundance of planktonic foraminiferal species, together with Mg/Ca based SST, exhibits millennial-scale oscillations during the Holocene, with 7 cold events (at about 1.7, 2.3-4.6, 6.2, 7.3, 8.2, 9.6, 10.6 cal. kyr BP) superimposed on a Holocene warming trend. This Holocene trend, together with centennial-scale SST variations superimposed on the last deglacial trend, suggests that both high and low latitude influences affected the climatology of the Okinawa Trough. (c) 2006 Elsevier B.V. All rights reserved.
134kzTimes Cited:48Cited References Count:62

Paleoseismology of the Nephi segment of the Wasatch fault zone, Juab County, Utah--Preliminary results from two large exploratory trenches at Willow Creek - Machette, M. N.; Crone, A. J.; Personius, S. F.; Dart, R. L.; Lidke, D. J.; Mahan, S. A.; Olig, S. S. (U. S. Geological Survey, 2007)
id: 1116; Investigations Map 2966, 2 oversize plates

Placing late Neanderthals in a climatic context RID A-5197-2008 - Tzedakis, P. C.; Hughen, K. A.; Cacho, I.; Harvati, K. (Nature, 2007)
Attempts to place Palaeolithic finds within a precise climatic framework are complicated by both uncertainty over the radiocarbon calibration beyond about 21,500 (14)C years BP(1) and the absence of a master calendar chronology for climate events from reference archives such as Greenland ice cores or speleothems(2). Here we present an alternative approach, in which (14)C dates of interest are mapped directly onto the palaeoclimate record of the Cariaco Basin by means of its (14)C series(3), circumventing calendar age model and correlation uncertainties, and placing dated events in the millennial-scale climate context of the last glacial period. This is applied to different sets of dates from levels with Mousterian artefacts, presumably produced by late Neanderthals, from Gorham's Cave in Gibraltar: first, generally accepted estimates of about 32,000 (14)C years BP for the upper-most Mousterian levels(4,5); second, a possible extended Middle Palaeolithic occupation until about 28,000 (14)C years BP(6); and third, more contentious evidence for persistence until about 24,000 (14)C years BP(6). This study shows that the three sets translate to different scenarios on the role of climate in Neanderthal extinction. The first two correspond to intervals of general climatic instability between stadials and interstadials that characterized most of the Middle Pleniglacial and are not coeval with Heinrich Events. In contrast, if accepted, the youngest date indicates that late Neanderthals may have persisted up to the onset of a major environmental shift, which included an expansion in global ice volume and an increased latitudinal temperature gradient. More generally, our radiocarbon climatostratigraphic approach can be applied to any 'snapshot' date from discontinuous records in a variety of deposits and can become a powerful tool in evaluating the climatic signature of critical intervals in Late Pleistocene human evolution.
id: 1991; PT: J; UT: WOS:000249394500047

Planktonic foraminifera, calcareous nannoplankton and ascidian variations during the last 25 kyr in the Southwestern Atlantic: A paleoproductivity signature? - Toledo, Filipe A. L.; Chachao, Mario; Costa, Karen B.; Pivel, Maria A. G. (Marine Micropaleontology, 2007)
id: 1061

Population dynamics, structure and per-recruit analysis of yellowedge grouper, Epinephelus flavolimbatus, from the northern Gulf of Mexico - Cook, M. (University of Southern Mississippi, 2007)

Quaternary depositional patterns and sea-level fluctuations, northeastern North Carolina - Parham, P. R.; Riggs, S. R.; Culver, S. J.; Mallinson, D. J.; Wehmiller, J. F. (Quaternary Research, 2007)
A detailed record of late Quaternary sea-level oscillations is preserved within the upper 45 in of deposits along an eight kin transect across Croatan Sound, a drowned tributary of the Roanoke/Albemarle drainage system, northeastern North Carolina. Drill-hole and seismic data reveal nine relatively complete sequences filling an antecedent valley comprised of discontinuous middle and early Pleistocene deposits. On interfluves, lithologically similar marine deposits of different sequences occur stacked in vertical succession and separated by ravinement surfaces. Within the paleo-drainage, marine deposits are separated by fluvial and/or estuarine sediments deposited during periods of lowered sea level. Foraminiferal and molluscan fossil assemblages indicate that marine facies were deposited in a shallow-marine embayment with open connection to shelf waters. Each sequence modifies or truncates portions of the preceding sequence or sequences. Sequence boundaries are the product of a combination of fluvial, estuarine, and marine erosional processes. Stratigraphic and age analyses constrain the ages of sequences to late Marine Isotope Stage (MIS) 6 and younger (similar to 140 ka to present), indicating multiple sea-level oscillations during this interval. Elevations of highstand deposits associated with late MIS 5 and MIS 3 imply that sea level was either similar to present during those times, or that the region may have been influenced by glacio-isostatic uplift and Subsidence. (c) 2006 University of Washington. All rights reserved.
131tvTimes Cited:18Cited References Count:56

Quaternary geology of the San Luis Basin, southern Colorado and Northern New Mexico--Rocky Mountain Section Friends of the Pleistocene Guidebook - Machette, M. N.; Coates, M. M.; Johnson, M. J. (U. S. Geological Survey Open-File Report 2007-1193, 2007)
id: 625

Quaternary glaciation and hydrologic variation in the South American tropics as reconstructed from the Lake Titicaca drilling project - Fritz, S. C.; Baker, P. A.; Seltzer, G. O.; Ballantyne, A.; Tapia, P.; Cheng, H.; Edwards, R. L. (Quaternary Research, 2007)
A 136-m-long drill core of sediments was recovered from tropical high-attitude Lake Titicaca, Bolivia-Peru, enabling a reconstruction of past climate that spans four cycles of regional glacial advance and retreat and that is estimated to extend continuously over the last 370,000 yr. Within the errors of the age model, the periods of regional glacial advance and retreat are concordant respectively with global glacial and interglacial stages. Periods of ice advance in the southern tropical Andes generally were periods of positive water balance, as evidenced by deeper and fresher conditions in Lake Titicaca. Conversely, reduced glaciation occurred during periods of negative water balance and shallow closed-basin conditions in the lake. The apparent coincidence of positive water balance of Lake Titicaca and glacial growth in the adjacent Andes with Northern Hemisphere ice sheet expansion implies that regional water balance and glacial mass balance are strongly influenced by global-scale temperature changes, as well as by precessional forcing of the South American summer monsoon. (c) 2007 University of Washington. All rights reserved.
id: 841; 227AJ Times Cited:9 Cited References Count:63Y

Radiocarbon age of late glacial deep water from the equatorial Pacific - Broecker, W.; Clark, E.; Barker, S.; Hajdas, I.; Bonani, G.; Moreno, E. (Paleoceanography, 2007)
Radiocarbon age differences for pairs of coexisting late glacial age benthic and planktic foraminifera shells handpicked from 10 sediment samples from a core from a depth of 2.8 km in the western equatorial Pacific are not significantly different from that of 1600 years calculated from measurements on prenuclear seawater. This places a lower limit on the depth of the interface for the hypothetical radiocarbon-depleted glacial age seawater reservoir required to explain the 190% drop in the (14)C/C for atmospheric CO(2), which occurred during the mystery interval (17.5 to 14.5 calendar years ago). These measurements restrict the volume of this reservoir to be no more than 35% that of the ocean. Further, (14)C measurements on a single Last Glacial Maximum age sample from a central equatorial Pacific core from a depth of 4.4 km water fail to reveal evidence for the required 5- to 7-kyr age difference between benthic and planktic foraminifera shells if the isolated reservoir occupied only one third of the ocean. Nor does the (13)C record for benthic forams from this abyssal core yield any evidence for the excess respiration CO(2) expected to be produced during thousands of years of isolation. Nor, as indicated by the presence of benthic foraminifera, was the dissolved oxygen used up in this abyssal water.
id: 413; 165MC Times Cited:10 Cited References Count:18

Radiocarbon age offsets of foraminifera resulting from differential dissolution and fragmentation within the sedimentary bioturbated zone - Barker, Stephen; Broecker, Wallace; Clark, Elizabeth; Hajdas, Irka (Paleoceanography, 2007)
Shells of coexisting species of planktonic foraminifera from the Ontong Java Plateau reveal radiocarbon age offsets of up to 2200 years. Similar offsets are found between fragments and whole shells of single species. Steady state modelling of dissolution and bioturbation within the sedimentary mixed layer predicts age differences of up to several kiloyears due to the interplay between differential dissolution and fragmentation of foraminifer shells and bioturbation. The observation that fragile foraminiferal shells are systematically older than those of more robust species is more difficult to explain. Mechanisms of chemical erosion, interface dissolution, and sediment redistribution are all apparently unable to explain this phenomenon. A possible solution is presented in which a particular species may be represented by two distinct classes of shells which are more or less robust. In this case, differential dissolution and fragmentation causes an increase in the mean age as the fragile class contributes less to the remaining intact shells. This study highlights the vulnerability of low sedimentation rate cores to the effects of dissolution and bioturbation.
id: 1920; PT: J; UT: WOS:000246308600002

Rapid sea level rise and ice sheet response to 8,200-year climate event - Cronin, T. M.; Vogt, P. R.; Willard, D. A.; Thunell, R.; Halka, J.; Berke, M.; Pohlman, J. (Geophysical Research Letters, 2007)
The largest abrupt climatic reversal of the Holocene interglacial, the cooling event 8.6 - 8.2 thousand years ago (ka), was probably caused by catastrophic release of glacial Lake Agassiz-Ojibway, which slowed Atlantic meridional overturning circulation (AMOC) and cooled global climate. Geophysical surveys and sediment cores from Chesapeake Bay reveal the pattern of sea level rise during this event. Sea level rose similar to 14 m between 9.5 to 7.5 ka, a pattern consistent with coral records and the ICE- 5G glacio-isostatic adjustment model. There were two distinct periods at similar to 8.9 - 8.8 and similar to 8.2 - 7.6 ka when Chesapeake marshes were drown as sea level rose rapidly at least similar to 12 mm yr(-1). The latter event occurred after the 8.6 - 8.2 ka cooling event, coincided with extreme warming and vigorous AMOC centered on 7.9 ka, and may have been due to Antarctic Ice Sheet decay.
id: 810; 225MA Times Cited:4 Cited References Count:32Y

Regional variability in the ages and reactivities of riverine dissolved and particulate organic matter exported to a temperate ocean margin - Bauer, J. E.; Raymond, P. A.; Cole, J. J.; Petsch, S. T.; Longworth, B. E.; Caraco, N. F.; Keesee, E. J. (ASLO Aquatic Sciences Meeting, 2007)
id: 477

Response of vegetation and fire to Little Ice Age climate change: regional continuity and landscape heterogeneity - Hotchkiss, S. C.; Calcote, R.; Lynch, E. A. (Landscape Ecology, 2007)
Late-Holocene climatic conditions in the upper Great Lakes region have changed sufficiently to produce significant changes in vegetation and fire regimes. The objective of this study was to determine how the vegetation mosaic and fire regimes on an oak (Quercus spp.)- and pine (Pines spp.)-dominated sand plain in northwestern Wisconsin responded to climatic changes of the past 1,200 years. We used pollen and charcoal records from a network of sites to investigate the range of natural variability of vegetation on a 1,500-km(2) landscape on the southern part of the sand plain. A major vegetation shift from jack pine (Pines banksiana) and red pine (P. resinosa) to increased abundance of white pine (P. strobus) occurred between 700 and 600 calendar years before present (cal yr BP), apparently corresponding to more mesic conditions regionally. A decrease in charcoal accumulation rate also occurred at most sites but was not synchronous with the vegetation change. At some sites there were further changes in vegetation and fire regimes occurring similar to 500-300 cal yr BP, but these changes were not as strong or unidirectional as those that occurred 700-600 cal yr BP. Our results suggest that both the composition and the distribution of vegetation of the southern part of the sand plain have been sensitive to relatively small climatic changes, and that the vegetation at the time of European settlement was a transitory phenomenon, rather than a long-term stable condition.
Suppl. 1239unTimes Cited:25Cited References Count:92

Salinity changes in the western tropical South Atlantic during the last 30 kyr - Toledo, F. A. L.; Costa, K. B.; Pivel, M. A. G. (Global and Planetary Change, 2007)
The hydrographic changes in the western tropical South Atlantic during the last 30 kyr were reconstructed based in the faunal and isotopic analyses of planktonic foraminifera of three cores taken along the Brazilian Continental Margin between 14 degrees S and 25 degrees S. The application of the SIMMAX-MAT method on faunal counts data provided the sea surface temperature estimates. Sea surface salinity estimates were based on the oxygen isotope composition of Globigerinoides ruber (white). Additionally, the abundance record of the planktonic foraminifera Globorotalia truncatulinoides (right) was used as a proxy for vertical mixing of surface waters. Sea surface temperature estimates suggest a relative stability of the area during the last 30 kyr. However, significant changes in the isotopic composition of G. ruber (white) suggest that the isotopic signal is dominated by the influence of sea surface salinity changes. The observed salinity changes are related to both the local hydrological balance and global circulation. Orbital forcing and sea surface salinity changes were responsible for considerable changes in the stability of the upper water column and consequently in the depth of the mixed layer, as indicated by the abundance record of G. truncatulinoides (right). (c) 2007 Elsevier B.V All rights reserved.
181bjTimes Cited:28Cited References Count:59

Sea level rise in Tampa Bay - Cronin, Thomas M.; Edgar, N. Terence; Brooks, Gregg; Hastings, David; Larson, Rebekka; Hine, Albert; Locker, Stanley; Suthard, Beau; Flower, Benjamin; Hollander, David; Wehmiller, John; Willard, Debra A.; et al. (Eos, Transactions, American Geophysical Union, 2007)
id: 1899; References: 14; illus. incl. geol. sketch map Latitude:N272700,N280200 Longitude:W0822200,W0825100Y

Strandplain evolution along the southern coast of Santa Caterina, Brazil - FitzGerald, D. M.; Cleary, W. J.; Buynevich, I. V.; Hein, C. J.; Kleins, A. H. F.; Asp, N.; Angulo, R. (Journal of Coastal Research, 2007)
id: 1099

Submarine canyon and fan systems of the California Continental Borderland, Chapter 3-7 - Normark, W. R.; Piper, D. J. W.; Romans, B. W.; Covault, J. A.; Dartnell, P.; Sliter, R. W. (Earth Science in the Urban Ocean: The Southern California Contental Borderlands, 2007)
id: 992

Terrestrial subsidies of aquatic metabolism and food webs: A turorial and review - Cole, J. J. (American Society of Limnology and Oceanography; Aquatic Science meeting, 2007)
69
id: 480

The timing and evolution of the post-glacial transgression across the Sea of Marmara shelf south of Istanbul - Eris, K. K.; Ryan, W. B. F.; Cagatay, M. N.; Sancar, U.; Lericolais, G.; Menot, G.; Bard, E. (Marine Geology, 2007)
High-resolution seismic reflection profiles and analyses of the sedimentary substrate at the Sea of Marmara (SoM) entrance to the Strait of Istanbul (Sol, Bosphorus) provide a detailed record of the transgression that took place after the SoM reconnected with the Mediterranean. The sediments progressively fill a paleo shelf valley that incised the margin from the Sol to the shelf break at the time of the pre-Holocene lowstand. We map seven seismic reflection units that can be confidently correlated to sediment cores by lithology and physical properties. Sediments in the cores are dated by radiocarbon methods. Early channel and levee deposits within the paleo valley belong to the Younger Dryas cold stage and record outflow from the Black Sea via the Sol. Small clinoform packages on the valley margin formed in proximity to climbing paleo shorelines. The elevations of these deposits conform to the sealevel history recorded in Barbados corals. The younger part of the succession includes a subaqueous prodelta sourced from the Kurbagalidere River. Its relatively young age when the Holocene sea had almost reached its modem level suggests that the thick progradational and aggradational clinoform development was primarily a response to sediment supply rather than the filling of expanding accommodation space. Our findings refute the hypothesis of Aksu et al. (Aksu, A.E., Hiscott, R.N., Mudie., P.J., Rochon, A., Kaminski, M.A., Abrojano, T., Yasar, D., 2002a. Persistent Holocene outflow fromn the Black Sea to the Eastern Mediterranean contradicts Noah's Flood hypothesis, GSA Today 10,(6), 3-7., Aksu, A.E., Hiscott, R.N., Kaminski, M.A., Mudie, P.J., Gillespie, H., Abrojano, T., Yasar, D., 2002b. Last glacial-Holocene paleoceanography of the Black Sea and Marmara Sea: stable isotopic, foraminiferal and coccolith evidence. Mar. Geol., 190, 119-149.) and Hiscott et al. (Hiscott, R.N., Aksu, A.E., Yasar, D., Kaminski, M.A., Mudie, P.J., Kostylev, V.E., MacDonald, J.C. Isler, F.I., Lord, A.R., 2002. Deltas south of the Bosphorus Strait record persistent Black Sea outflow to the Marmara Sea since similar to 10 ka, Mar. Geol., 190,95-118., Hiscott, R.N., Aksu, A.E., Mudie., P.J., Kaminski, M.A., Abrajano, T, Yasar, D., Rochon, A., 2007. The Marmara Sea gateway since similar to 16 ky BP: non-catastrophic causes of paleoceanographic events in the Black Sea at 8.4 and 7.15 ky BR In Yanko-Hombach,V, Gilbert, A.S., Dolukhanov, P.M. (Eds.), The Black Sea Flood Question, Springer, The Netherlands, 89-117.) that this deposit was supplied from the Sol and that its presence requires a persistent Black Sea outflow since 10 C-14 ka bp (not corrected from the reservoir age or calibrated). (c) 2007 Elsevier B.V All rights reserved.
210tuTimes Cited:36Cited References Count:52

Tropical Pacific - mid-latitude teleconnections in medieval times - Graham, N. E.; Hughes, M. K.; Ammann, C. M.; Cobb, K. M.; Hoerling, M. P.; Kennett, D. J.; Kennett, J. P.; Rein, B.; Stott, L.; Wigand, P. E.; Xu, T. Y. (Climatic Change, 2007)
Terrestrial and marine late Holocene proxy records from the western and central US suggest that climate between approximately 500 and 1350 A.D. was marked by generally arid conditions with episodes of severe centennial-scale drought, elevated incidence of wild fire, cool sea surface temperatures (SSTs) along the California coast, and dune mobilization in the western plains. This Medieval Climate Anomaly (MCA) was followed by wetter conditions and warming coastal SSTs during the transition into the "Little Ice Age" (LIA). Proxy records from the tropical Pacific Ocean show contemporaneous changes indicating cool central and eastern tropical Pacific SSTs during the MCA, with warmer than modern temperatures in the western equatorial Pacific. This pattern of mid-latitude and tropical climate conditions is consistent with the hypothesis that the dry MCA in the western US resulted (at least in part) from tropically forced changes in winter NH circulation patterns like those associated with modern La Nina episodes. We examine this hypothesis, and present other analyses showing that the imprint of MCA climate change appears in proxy records from widely distributed regions around the planet, and in many cases is consistent with a cool medieval tropical Pacific. One example, explored with numerical model results, is the suggestion of increased westerlies and warmer winter temperatures over northern Europe during medieval times. An analog technique for the combined use of proxy records and model results, Proxy Surrogate Reconstruction (PSR), is introduced.
160ufTimes Cited:125Cited References Count:151

Validated age, growth, and mortality estimates of the ocean quahog (Arctica islandica) in the western Atlantic - Kilada, R. W.; Campana, S. E.; Roddick, D. (Ices Journal of Marine Science, 2007)
The age structure of offshore (Sable Bank) and inshore (St Mary's Bay) populations of eastern Canadian ocean quahogs (Arctica islandica), and of a northwestern Iceland population, is investigated. Age estimates for eastern Canadian ocean quahogs were validated through analysis of bomb-produced C-14 in quahog shell growth increments deposited before, during, and after the atmospheric atomic bomb testing periods of the 1950s and 1960s. Delta 14C from shells with presumed birthdates between the late 1950s and 1970s clearly reflects the sharp increase in oceanic radiocarbon attributable to nuclear testing. The results validate our age interpretations of Sable Bank quahogs to an age of 45 y, and support longevity estimates of more than 200 y for the same population. Longevity calculations for the other populations exceeded 60 y. Von Bertalanffy growth parameters were estimated for the three populations, the growth rate of all three was relatively rapid for the first 20 - 30 y of life, but thereafter was very slow. The instantaneous rate of natural mortality (M), calculated using the age-frequency distribution of the unexploited populations, was estimated to be 0.03 and 0.10 for the Sable Bank and St Mary's Bay populations, respectively.
id: 807; 173HY Times Cited:6 Cited References Count:51Y

Absence of 14C in PM2.5 Emissions from Gasohol Combustion in Small Engines - Lewis, C. W.; Volkens, J.; Braddock, J. N.; Crews, W. S.; Lonneman, W. A.; McNichol, A. P. (Aerosol Science and Technology, 2006)
id: 1699

Anomalous radiocarbon ages for foraminifera shells - Broecker, W.; Barker, S.; Clark, E.; Hajdas, I.; Bonani, G. (Paleoceanography, 2006)
The causes for discordant radiocarbon results on multiple species of planktonic foraminifera from high-sedimentation-rate marine sediments are investigated. We have documented two causes for these anomalous results. One is the addition of secondary radiocarbon for which we have, to date, only one firm example. It involves an opal-rich sediment. The other is the incorporation of reworked material. Again, we have, to date, only one firm example. It involves a rapidly deposited ocean margin sediment. However, we have three other examples where reworking is the most likely explanation. On the basis of this study it is our conclusion that, where precise radiocarbon dating of high-deposition-rate marine sediment is required, a prerequisite is to demonstrate that concordant ages can be obtained on pairs of fragile and robust planktic shells. For sediment rich in opal, it is advisable to check for secondary calcite by comparing ages obtained on acid-leached samples with those on unleached samples.
id: 980; 041JB Times Cited:7 Cited References Count:7

Anthropogenic markers in the Holocene stratigraphic sequence of the Gulf of Trieste (northern Adriatic Sea) - Covelli, S.; Fontolan, G.; Faganeli, J.; Ogrinc, N. (Marine Geology, 2006)
The Gulf of Trieste is a shallow serni-enclosed marine basin in the northernmost part of the Adriatic Sea that has been affected by the relative rise in sea-level during the Holocene. The sedimentary sequences in three cores, ranging in length from 130 to 320 cm, were investigated through the variability in grain-size parameters, major (Al, Fe, S, N, Ca and Mg) and trace (Ti, Mn, Cr, Ni, Cu, Zn and Hg) elements, organic and inorganic C, delta C-13 and C-14 dating in order to obtain information on paleoenvironmental evolution and the historical development of heavy metal contamination. The potential sources of pollution are: urban sewage from nearly 400,000 inhabitants, industrial effluents, and 500 yr of Hg mining activity in the Idrija region (western Slovenia), located in the upper basin of the Isonzo river, the main freshwater input to the coastal zone. The conventional 14 C ages of bulk sedimentary OC in the basal part of the three cores were 9030 +/- 70 (GTI), 8270 +/- 50 (GT2) and 9160 +/- 120 (GT3) yr BP. An upward increase in highly negative delta C-13(org) values from the core bottoms indicates that lacustrine-swamp conditions in the study area were rapidly followed by a typical marine depositional environment. Cluster analysis performed on the geochemical data for all subsamples of the three cores identifies several groups with a clear stratigraphic meaning. Factor analysis of the data shows related element groups that can be interpreted as being related to, for instance, the natural contribution from alummosilicates and carbonates, from organic matter (peat) and the more recent anthropogenic "impact". Predicted natural linear relationships for metal-Al were obtained from the core subsamples and they can be used as a baseline to evaluate metal enrichments on a regional scale. Results show that more recent sediments in the central sector of the Gulf of Trieste are slightly enriched in Cu (max Enrichment Factor EF=2.1) and Zn (max EF=1.6), and noticeably contaminated by Hg (up to 23.32 mu g g(-1)) to a maximum depth of 90 cm and up to 60 times above the estimated regional background (0.13 mu g g(-1)). The Hg historical trend is well correlated with extraction activity at the Idrija mine, thus allowing indicative sedimentation rate estimation and tentative assessment of the rate of Hg accumulation in bottom sediments (from 1.77 to 31.49 mg m(-2) yr(-1) at the surface). The large inventory of Hg in the core GT2 appeared to be the result of proximity to the fluvial source, which is still active in supplying Hg to the coastal areas and makes the Gulf of Trieste one of the most Hg contaminated area in the whole Mediterranean basin. (c) 2006 Elsevier B.V. All rights reserved.
069seTimes Cited:37Cited References Count:61

Bioreactivity of estuarine dissolved organic matter: A combined geochemical and microbiological approach - McCallister, S. L.; Bauer, J. E.; Canuel, E. A. (Limnology and Oceanography, 2006)
An integrated multidisciplinary study utilizing geochemical and microbial ecological approaches was conducted to characterize the origins, chemical nature, and quantities of dissolved and particulate organic matter (OM) utilized by heterotrophic bacteria in a temperate estuary. C: N, stable isotope (delta C-13), and lipid biomarker analyses revealed differences in the inferred reactivity of autochthonous versus allochthonous OM sources. Isotopic comparison of OM size fractions and bacterial nucleic acids suggests that high-molecular-weight dissolved OM (DOM) is consistently linked to bacterial biomass synthesis along the estuarine salinity gradient. Polyunsaturated fatty acids (as percent of total fatty acids, FA) were a reliable predictor of DOM decomposition in bioassays, thus providing an indicator directly linking DOM reactivity to its composition. Significant positive correlations between FA diagnostic of bacterial sources and lipid biomarker compounds diagnostic of planktonic origin indicate a systematic bacterial response to autochthonous DOM sources along the estuarine continuum. These findings further suggest that, although the geochemical signature of algal-derived OM in the dissolved phase may appear quantitatively insignificant, this fraction may nevertheless represent a principal source of bioreactive OM to heterotrophic bacteria in estuarine waters.
040scTimes Cited:39 Cited References Count:32
Keywords: acids; bacteria; bay; bioavailability; carbon-isotope analysis; extraction; food webs; sediments

Bomb dating and age validation using the spines of spiny dogfish (Squalus acanthias) - Campana, S. E.; Jones, C.; McFarlane, G. A.; Myklevoll, S. (Environmental Biology of Fishes, 2006)
Bomb radiocarbon has previously been used to validate the age of large pelagic sharks based on incorporation into vertebrae. However, not all sharks produce interpretable vertebral growth bands. Here we report the first application of bomb radiocarbon as an age validation method based on date-specific incorporation into spine enamel. Our results indicate that the dorsal spines of spiny dogfish, Squalus acanthias, recorded and preserved a bomb radiocarbon pulse in growth bands formed during the 1960s with a timing which was very similar to that of marine carbonates. Using radiocarbon assays of spine growth bands known to have formed in the 1960s and 1970s as a dated marker, we confirm the validity of spine enamel growth band counts as accurate annual age indicators to an age of at least 45 year. Radiocarbon incorporation into northeast Atlantic dogfish spines occurred in similar years as those in the northwest Atlantic and northeast Pacific, although the amount of radiocarbon differed in keeping with the radiocarbon content of the different water masses. Published reports suggesting that Pacific dogfish are longer lived and slower growing than their Atlantic counterparts appear to be correct, and are not due to errors in interpreting the spine growth bands. Radiocarbon assays of fin spine enamel appears to be well suited to the age validation of sharks with fin spines which inhabit the upper 200 m of the ocean.
107bsTimes Cited:38Cited References Count:25

Bomb radiocarbon dating calibrates beluga (Delphinapterus leucas) age estimates - Stewart, R. E. A.; Campana, S. E.; Jones, C. M.; Stewart, B. E. (Canadian Journal of Zoology-Revue Canadienne De Zoologie, 2006)
The ages of many mammals are estimated by counting growth layers in tooth sections, yet validation of age estimation techniques using free-ranging mammals has been problematic. Contrary to age estimates for most other animals in which it is assumed that one bipartite growth increment forms annually, beluga whale (Delphinapterus leucas (Pallas, 1776)) age estimates have been calculated assuming that two growth layer groups (GLGs) form each year. Here we report the age validation for belugas based on date-specific incorporation of atomic bomb radiocarbon into tooth GLGs. Radiocarbon assays of dentinal layers formed in belugas harvested between 1895 and 2001 indicated that radiocarbon from atmospheric testing of nuclear weapons was incorporated into growing teeth and retained for the remaining life of the animal. Comparison of age determined by bomb radiocarbon with age determined by GLG counts indicated that GLGs form annually, not semiannually, and provide an accurate indicator of age for belugas up to at least 60 years old. Radiocarbon signatures of belugas were temporally and metabolically stable and were apparently derived more from the radiocarbon content of their prey than from water. Our understanding of many facets of beluga population dynamics is altered by the finding that this species lives twice as long as previously thought.
140vdTimes Cited:51Cited References Count:73

Carbon flux in seagrass ecosystems - Mateo, M. A.; Cebrián, J.; Dunton, K.; Mutchler, T. (Seagrasses: Biology, Ecology and Conservation., 2006)
id: 2006

Coherence between solar activity and the East Asian winter monsoon variability in the past 8000 years from Yangtze River-derived mud in the East China Sea - Xiao, S. B.; Li, A. C.; Liu, J. P.; Chen, M. H.; Xie, Q.; Jiang, F. Q.; Li, T. G.; Xiang, R.; Chen, Z. (Palaeogeography Palaeoclimatology Palaeoecology, 2006)
AMS(14)C dating and grain-size analysis for Core PC-6, located in the middle of a mud area on the inner shelf of the East China Sea (ECS), were used to rebuild the Holocene history of the East Asian winter monsoon (EAWM). The 7.5-m core recorded the history of environmental changes during the postglacial transgression. The core's mud section (the upper 450 cm) has been formed mainly by suspended sediment delivered from the Yangtze River mouth by the ECS Winter Coastal Current (ECSWCC) since 7.6 kyr BP. Using a mathematical method called "grain size vs. standard deviatioW', we can divide the Core PC-6's grain-size distribution into two populations at about 28 mu m. The fine population (< 28 mu m) is considered to be transported by the ECSWCC as suspended loads. Content of the fine population changes little and represents a stable sedimentary environment in accord with the present situation. Thus, variation of mean grain-size from the fine population would reflect the strength of ECSWCC, which is mainly controlled by the East Asian winter monsoon.Abrupt increasing mean grain size in the mud section is inferred to be transported by sudden strengthened ECSWCC, which was caused by the strengthened EAWM. Thus, the high resolution mean grain-size variation might serve as a proxy for reconstruction of the EAWM. A good correlation between sunspot change and the mean grain-size of suspended fine population suggests that one of the primary controls on centennial- to decadal-scale changes of the EAWM in the past 8 ka is the variations of sun irradiance, i.e., the EAWM will increase in intensity when the number of sunspots decreases. Spectral analyses of the mean grain-size time series of Core PC-6 show statistically significant periodicities centering on 2463, 1368, 128, 106, 100, 88-91, 7678, and 70-72 years. The EAWM and the East Asian summer monsoon (EASM) agree with each other well on these cycles, and the East Asian Monsoon (EAM) and the Indian Monsoon also share in concurrent cycles in Holocene, which are in accord with the changes of the sun irradiance. (c) 2005 Elsevier B.V. All rights reserved.
072kpTimes Cited:52Cited References Count:61

Deglaciation and Holocene climate change in the western Peruvian Andes - Weng, C. Y.; Bush, M. B.; Curtis, J. H.; Kolata, A. L.; Dillehay, T. D.; Binford, M. W. (Quaternary Research, 2006)
Pollen, charcoal, magnetic susceptibility, and bulk density data provide the first paleoecological record spanning the last 33,000 years from the western cordillera of the Peruvian Andes. Sparse super-puna vegetation existed before 30,000 cat yr B.P. around Lake Compuerta (3950 m elevation), prior to a sedimentary hiatus that lasted until c. 16,200 cat yr B.P. When sedimentation resumed, a glacial foreland or super-puna flora is represented in which Polylepis was a significant element. Glacial outwash, marked by high sedimentary magnetic susceptibility, increased from c. 16,200 cat yr B.P. and reached a peak at c. 13,200 cat yr B.P. Between c. 12,500 cat yr B.P. and 10,000 cat yr B.P., magnetic susceptibility was reduced. Vegetation shifts suggest a cool dry time, consistent with regional descriptions of the Younger Dryas event. Deglaciation resumes by 10,000 cat yr B.P. and the last ice is lost from the catchnient at similar to 7500 cat yr B.P. During the early Holocene warm and dry period between 10,000 and 5500 cat yr B.P., Alnus expanded in downslope forests. Alnus declined in abundance at 5500 cat yr B.P. when wetter and cooler conditions returned and human activity intensified. Maize (Zea mays) pollen first occurred in the core at similar to 2600 cat yr B.P., indicating a minimum age for local agriculture. An increase in Alnus pollen abundance at similar to 1000 cat yr B.P. could be due to human activity or perhaps due to a regional climate change associated with cultural turnover elsewhere in the Andes at this time. (c) 2006 University of Washington. All rights reserved.
058upTimes Cited:27Cited References Count:55

Determination of carbon dioxide, hydrographic and chemical parameters during the R/V Nathaniel B. Palmer cruise in the southern Indian Ocean (WOCE section S041) - Takahashi, R.; Millero, F. J.; Key, R. M.; Chipman, D.; Peltola, E.; Rubin, S.; Sweeney, C.; Sutherland, S. (2006)
id: 1053

Dissolved and particulate organic matter source-age characterization in the upper and lower Chesapeake Bay: A combined isotope and biochemical approach - Loh, A. N.; Bauer, J. E.; Canuel, E. A. (Limnology and Oceanography, 2006)
In order to characterize the sources and ages of organic matter contributing to river and estuarine outflow waters, the present study investigated Delta C-14 and delta C-13 signatures of the major operationally defined biochemical classes of ultrafiltered dissolved organic matter (UDOM) in conjunction with lipid biomarker and elemental compositions of UDOM and suspended particulate organic matter (POM) in the Chesapeake Bay. Freshwater (Susquehanna River) UDOM was dominated by a molecularly uncharacterized (MUC) fraction, followed by total carbohydrate (TCHO), total hydrolysable amino acid (THAA) and total lipid (TLE) components. In contrast, UDOM at the bay mouth (salinity similar to 22-24) was comprised mainly of TCHO, followed by MUC, THAA, and TLE. The Delta C-14 and delta C-13 signatures of both UDOM and its major biochemical classes indicate that Susquehanna DOM is derived in part from old allochthonous terrestrial sources, whereas young marine sources dominate at the bay mouth. In contrast to the other biochemical classes, lipophilic DOM at both sites was very old (similar to 5,000-7,000 years B.P.). In addition, factor analysis of lipid biomarker compounds revealed unique signatures for the UDOM and POM pools that imply disparate source and/or recycling properties as well as potential influences due to physical partitioning. Lipid biomarker compounds showed that although autochthonous riverine/estuarine sources dominated both the UDOM and POM pools, terrigenous lipids were elevated in the Susquehanna during high flow conditions. The presence of lipid biomarkers diagnostic of "fresh" algal material in UDOM further suggested its greater reactivity than POM. The observed biochemical and lipid biomarker compositions and isotopic signatures of UDOM and POM are consistent with previous findings suggesting that these two major organic matter pools have dissimilar reactivities and cycling times, and they derive from comparatively unique source-age materials in rivers and estuaries.
045nhTimes Cited:24 Cited References Count:37
Keywords: biomarkers; carbon; delta-c-13; lipid-composition; ocean; radiocarbon; river; san-francisco; sediments; variability

Do inland waters matter in the regional or global C balance: A review and turorial - Cole, J. J. (American Society of Limnology and Oceanography Summer Meeting, 2006)
id: 479

Elemental and isotopic characterization of organic matter and carbon in the South Atlantic bight, a net heterotrophic ocean margin - De Alteris, J.; Bauer, J. E.; Perkey, D. W.; Keesee, E. J.; Cai, W. J. (Ocean Sciences Meeting, 2006)
id: 481

Flooding of Bering Strait and Holocene climate in the Chukchi Sea - Keigwin, L. D.; Donnelly, J. P.; Cook, M. S.; Driscoll, N. W.; Brigham-Grette, J. (Geology, 2006)
id: 678

Foraminiferal and sedimentary record of Late Holocene barrier island evolution, Pea Island, North Carolina: The role of storm overwash, inlet processes, and anthropogenic modification - Culver, S. J.; Ames, D. V.; Corbett, D. R.; Mallinson, D. J.; Riggs, S. R.; Smith, C. G.; Vance, D. J. (Journal of Coastal Research, 2006)
Foraminiferal and sedimentary data, supplemented with geochemical dating and ground-penetrating radar transects, show that the barrier island at Pea Island National Wildlife Refuge just north of Rodanthe, North Carolina, has been dominated by a combination of inlet and overwash processes for at least 1000 years. The stratigraphic record of several vibracores does not preserve every, or even many, overwash events but, instead, is characterized by three to four fining-upward sequences. The last three commence with overwash sand or gravel that is overlain by a variety of finer-grained estuarine, inlet, and marsh deposits. The dynamic nature of this segment of the Outer Banks was muted in the late 1930s by construction of artificial barrier dune ridges, extensive planting of grass and shrubs, and construction of Highway 12 in 1953. Subsequently, the road and barrier dune ridge were rebuilt and relocated several times following storm events.
070tkTimes Cited:19Cited References Count:33

Gulf Stream density structure and transport during the past millennium - Lund, D. C.; Lynch-Stieglitz, J.; Curry, W. B. (Nature, 2006)
The Gulf Stream transports approximately 31 Sv (1 Sv = 10(6) m(3) s(-1)) of water and 1.3 x 10(15) W of heat into the North Atlantic ocean. The possibility of abrupt changes in Gulf Stream heat transport is one of the key uncertainties in predictions of climate change for the coming centuries. Given the limited length of the instrumental record, our knowledge of Gulf Stream behaviour on long timescales must rely heavily on information from geologic archives. Here we use foraminifera from a suite of high-resolution sediment cores in the Florida Straits to show that the cross-current density gradient and vertical current shear of the Gulf Stream were systematically lower during the Little Ice Age (ad approximately 1200 to 1850). We also estimate that Little Ice Age volume transport was ten per cent weaker than today's. The timing of reduced flow is consistent with temperature minima in several palaeoclimate records, implying that diminished oceanic heat transport may have contributed to Little Ice Age cooling in the North Atlantic. The interval of low flow also coincides with anomalously high Gulf Stream surface salinity, suggesting a tight linkage between the Atlantic Ocean circulation and hydrologic cycle during the past millennium.
Lund, David CLynch-Stieglitz, JeanCurry, William BengResearch Support, U.S. Gov't, Non-P.H.S.England2006/12/01 09:00Nature. 2006 Nov 30;444(7119):601-4.

Human Impacts on Rapa, French Polynesia - Kennett, D. J.; Anderson, A.; Prebble, M.; Conte, E.; Southon, J. (Antiquity, 2006)
id: 1020

Intra-shell radiocarbon variability in marine mollusks - Culleton, B. J.; Kennett, D. J.; Ingram, B. L.; Erlandson, J. M.; Southon, J. (Radiocarbon, 2006)
id: 1019

Late-Quaternary paleoenvironmental evolution of Lesina lagoon (sosuthern Italy) from subsurface data - Lucchi, Marianna Ricci; Fiorini, Flavia; Colalongo, Maria Luisa; Curzi, Pietro Vittorio (Sedimentary Geology, 2006)
Integrated sedimentological and micropaleontological (foraminifers and ostracods) analyses of two 55 m long borehole cores (S3 and S4) drilled in the subsurface of Lesina lagoon (Gargano promontory—Italy) has yielded a facies distribution characteristic of alluvial, coastal and shallow-marine sediments. Stratigraphic correlation between the two cores, based on strong similarity in facies distribution and AMS radiocarbon dates, indicates a Late Pleistocene to Holocene age of the sedimentary succession. Two main depositional sequences were deposited during the last 60-ky. These sequences display poor preservation of lowstand deposits and record two major transgressive pulses and subsequent sea-level highstands. The older sequence, unconformably overlying a pedogenized alluvial unit, consists of paralic and marine units (dated by AMS radiocarbon at about 45–50,000 years BP) that represent the landward migration of a barrier-lagoon system. These units are separated by a ravinement surface (RS1). Above these tansgressive deposits, highstand deposition is characterised by progradation of the coastal sediments. The younger sequence, overlying an unconformity of tectonic origin, is a 10 m-thick sedimentary body, consisting of fluvial channel sediments overlain by transgressive–regressive deposits of Holocene age. A ravinement surface (RS2), truncating the transgressive (lagoonal and back-barrier) deposits in core S4, indicates shoreface retreat and landward migration of the barrier/lagoon system. The overlying beach, lagoon and alluvial deposits are the result of mid-Holocene highstand sedimentation and coastal progradation.
id: 1060
Keywords: Foraminifers; Late Quaternary; Lesina lagoon (Italy); Ostracods; Sea-level changes

Meridional overturning circulation in the South Atlantic at the last glacial maximum - Lynch-Stieglitz, J.; Curry, W. B.; Oppo, D. W.; Ninneman, U. S.; Charles, C. D.; Munson, J. (Geochemistry Geophysics Geosystems, 2006)
The geostrophic shear associated with the meridional overturning circulation is reflected in the difference in density between the eastern and western margins of the ocean basin. Here we examine how the density difference across 30 degrees S in the upper 2 km of the Atlantic Ocean ( and thus the magnitude of the shear associated with the overturning circulation) has changed between the last glacial maximum and the present. We use oxygen isotope measurements on benthic foraminifera to reconstruct density. Today, the density in upper and intermediate waters along the eastern margin in the South Atlantic is greater than along the western margin, reflecting the vertical shear associated with the northward flow of surface and intermediate waters and the southward flowing North Atlantic Deep Waters below. The greater density along the eastern margin is reflected in the higher delta(18)O values for surface sediment benthic foraminifera than those found on the western margin for the upper 2 km. For the last glacial maximum the available data indicate that the eastern margin foraminifera had similar delta(18)O to those on the western margin between 1 and 2 km and that the gradient was reversed relative to today with the higher delta(18)O values in the western margin benthic foraminifera above 1 km. If this reversal in benthic foraminifera delta(18)O gradient reflects a reversal in seawater density gradient, these data are not consistent with a vigorous but shallower overturning cell in which surface waters entering the Atlantic basin are balanced by the southward export of Glacial North Atlantic Intermediate Water.
092siTimes Cited:17Cited References Count:46

Modern saltmarsh diatom distributions of the Outer Banks, North Carolina, and the development of a transfer function for high resolution reconstructions of sea level - Horton, B. P.; Corbett, R.; Culver, S. J.; Edwards, R. J.; Hillier, C. (Estuarine Coastal and Shelf Science, 2006)
We collected modern diatom samples from Currituck Barrier Island, Oregon inlet and Pea Island marshes, Outer Banks, North Carolina, USA, which have different salinity regimes due to their varying distances from a major barrier island inlet. Multivariate analyses separate the saltmarsh diatom assemblages into distinct elevational zones, dominated by differing abundances of polyhalobous, mesohalobous and oliohalobous taxa. suggesting that the distribution of saltmarsh diatoms is a direct function of elevation, with the most important controlling factors being the duration and frequency of subaerial exposure.We developed the first diatom-based transfer function for the east coast of North America to reconstruct former sea levels based upon the relationship between diatom assemblage and elevation. Results imply that this is possible to a precision of +/- 0.08 m, superior to most similar studies from temperate, mid-latitude environments. The transfer function is used to construct a relative sea-level curve from fossil assemblages from Salvo. North Carolina. These results suggest a sea-level rise of 0.7 m over the last c. 150 years, at an average of c. 3.7 mm year(-1). This is consistent with existing sea-level data, and illustrates the utility of the transfer function approach. (c) 2006 Elsevier Ltd. All rights reserved.
090jmTimes Cited:37Cited References Count:74

New evidence for remnant deposits recorded by columnar sediments in the shelf of the northern South China Sea - Xiao, S. B.; Chen, M. H.; Lu, J. (Marine Geology & Quaternary Geology, 2006)
id: 568

The North Anatolian fault in the Gulf of Izmit (Turkey): Rapid vertical motion in response to minor bends of a non-vertical continental transform - Cormier, M. H.; Seeber, L.; McHugh, C. M. G.; Polonia, A.; Cagatay, M. N.; Emre, O.; Gasperini, L.; Gorur, N.; Bortoluzzi, G.; Bonatti, E.; Ryan, W. B. F.; Newman, K. R. (Journal of Geophysical Research, 2006)
id: 532

Rapid sea-level rise and Holocene climate in the Chukchi Sea - Keigwin, L. D.; Donnelly, J. P.; Cook, M. S.; Driscoll, N. W.; Brigham-Grette, J. (Geology, 2006)
Three new sediment cores from the Chukchi Sea preserve a record of local paleoenvironment, sedimentation, and flooding of the Chukchi Shelf (similar to-50 m) by glacial-eustatic sea-level rise. Radiocarbon dates on foraminifera provide the first marine evidence that the sea invaded Hope Valley (southern Chukchi Sea, -53 m) as early as 12 ka. The lack of significant sediment accumulation since ca. 7 ka in Hope Valley, southeastern Chukchi Shelf, is consistent with decreased sediment supply and fluvial discharge to the shelf as deglaciation of Alaska concluded. Abundant benthic foraminifera from a site west of Barrow Canyon indicate that surface waters were more productive 4-6 ka, and this productivity varied on centennial time scales. An offshore companion to this core contains a 20 m record of the Holocene. These results show that carefully selected core sites from the western Arctic Ocean can have a temporal resolution equal to the best cores from other regions, and that these sites can be exploited for high-resolution studies of the paleoenvironment.
089zkTimes Cited:67Cited References Count:18

Rapid subsidence and sedimentation from oblique slip near a bend on the North Anatolian transform fault in the Marmara Sea, Turkey - Seer, L.; Cormier, M. H.; McHugh, C.; Emre, O.; Polonia, A.; Sorlien, C. (Geology, 2006)
id: 533

A revised late Holocene sea-level record for northern Massachusetts, USA - Connelly, J. P. (Journal of Coastal Research, 2006)
id: 497

Sedimentology, physical properties and age of mass transport deposits associated with the Marques de Pombal Fault, Southwest Portuguese Margin - Vizcaino, Alexis; Gracia, Eulalia; Pallas, Raimon; Garcia-Orellana, Jordi; Escutia, Carlota; Casas, David; Willmott, Veronica; Diez, Susana; Asioli, Alessandra; Danobeitia, Juanjo (Norwegian Journal of Geology, 2006)
id: 623

Sources and potential transformation of estuarine dissolved and particulate organic matter: a multi-tracer approach - McCallister, S. L.; Bauer, J. E.; Ducklow, H. W.; Canuel, E. A. (Organic Geochemistry, 2006)
id: 597

Submarine earthquake geology along the North Anatolia Fault in the Marmara Sea, Turkey: A model for transform basin sedimentation - McHugh, C. M. G.; Seeber, L.; Cormier, M. H.; Dutton, J.; Cagatay, N.; Polonia, A.; Ryan, W. B. F.; Gorur, N. (Earth and Planetary Science Letters, 2006)
The submerged portions of the North Anatolia Fault system beneath the Marmara Sea were studied with high-resolution multibeam bathymetry, subbottom profiling and sediment cores. The major objectives were to learn about the seismic and tectonic history of the fault from the stratigraphic record at a scale similar to paleoseismic studies on land and to develop tools for submarine earthquake geology that can be applied to fault-controlled basins in general. We focused on Holocene sediment in several Marmara Sea basins of different sizes. The approach was to test whether: (1) the depocenters of the larger basins contain a record of all historic Ms > 7 earthquakes within the Marmara Sea region; (2) the small transform basins record earthquakes that rupture through them; (3) vertical and strike-slip Holocene deformation can be quantified; and (4) the effects of an earthquake generally includes both primary structural features due to rupture of the sea floor, such as strata offset, scarps and tilting, as well as secondary effects due to shaking, such as mass-wasting and gravitational flows. We found evidence of earthquakes that we correlate with historic events in 181 AD, 740 AD, 1063 AD, 1343 AD, 1509 AD, 1766 AD, 1894 AD and 1912 AD. The geologic evidence is primarily from those basins adjacent to the rupture as inferred from historic data. This suggests that coseismic deformation of the sea floor along the rupture is a critical factor in the sedimentary record. We propose a qualitative sedimentation model that relates this coseismic deformation to mass-wasting of the slope, scour of the basin floor, seiche motions and homogenite deposition. Frequent earthquake activity sheds sediments from the flanks, contributes to the much thicker sediment on the basin floor and decreases the likelihood of sediment failures in response to normal marine gravity-driven processes. The surveying techniques and approaches used have therefore the potential of documenting earthquake ruptures of fault segments and to extend the earthquake record far before the known history, thus improving hazard evaluations and the fundamental understanding of earthquake process. (c) 2006 Elsevier B.V. All rights reserved.
085kgTimes Cited:55Cited References Count:98

Temporal and spatial complexity in post-glacial shelf sedimentation on the tectonically active, Poverty Bay continental margin of New Zealand - Orpin, A. R.; Alexander, C.; Carter, L.; Kuehl, S.; Walsh, J. P. (Continental Shelf Research, 2006)
id: 634

Two ecological shifts in Long Island Sound during the industrial period - Thomas, E.; Varekamp, J. C.; Mecray, E. L.; Buchholtzten-Brink, M. R. L.; Cooper, S.; Brinkhuis, H.; Sangioirgio, F. (Long Island Sound Research Center, 2006)
id: 751

Using packrat middens to assess how grazing influences vegetation change in Glen Canyon National Recreation Area, Utah - Fisher, J.; Cole, K. L.; Anderson, R. S. (USGS open-file report 2006-1183, 2006)
id: 1105

Variability in radiocarbon ages of biochemical compound classes of high molecular weight dissolved organic matter in estuaries - Wang, X. C.; Callahan, J.; Chen, R. F. (Estuarine Coastal and Shelf Science, 2006)
High molecular weight dissolved organic matter (HMW-DOM, > 1000 Da) represents a major fraction (> 30%) of dissolved organic carbon (DOC) in the ocean and thus plays an important role in the global biogeochemical cycling of carbon and many other elements. Its organic sources and formation mechanisms, however, are still not well understood especially in estuarine and coastal regions where multiple natural and anthropogenic sources contribute to total HMW-DOM. In this paper we report our measurements of natural radiocarbon (C-14) abundances and stable carbon isotope (C-13) compositions of the major biochemical compound classes: amino acids, carbohydrates and lipids separated from eight HMW-DOM samples collected from five US estuaries as part of our on-going study of sources, distribution and transport of chromophoric dissolved organic matter (CDOM) in estuarine and coastal waters. Distinct differences in both C-14 and C-13 values were found among the bulk HMW-DOM samples as well as the individual compound classes. Radiocarbon ages of the major compound classes varied by as much as 27,000 years in a single sample. The calculated average radiocarbon ages of the compound fractions of HMW-DOM indicate that the total lipid fraction is very "old", while the acid-insoluble fraction is slightly younger. Total amino acid and carbohydrate fractions, however, have relatively modern apparent C-14 ages. The significant variability in C-14 ages among the compound classes indicates not only multiple organic carbon sources but also different formation and turnover pathways controlling the cycling of different biochemical components of HMW-DOM in estuarine and coastal waters. (c) 2006 Elsevier Ltd. All rights reserved.
057ogTimes Cited:6Cited References Count:41

Variability in the character, age and reactivity of organic matter exported from rivers and estuaries to ocean margins - Bauer, J. E.; Cole, J. J.; Caraco, N. F.; Raymond, P. A.; Keesee, E. J.; Fernald, S.; Mull, K. (Ocean Sciences Meeting, 2006)
id: 476

Young Danube delta documents stable Black Sea level since the middle Holocene: Morphodynamic, paleogeographic, and archaeological implications - Giosan, L.; Donnelly, J. P.; Constantinescu, S.; Filip, F.; Ovejanu, I.; Vespremeanu-Stroe, A.; Vespremeanu, E.; Duller, G. A. T. (Geology, 2006)
New radiocarbon and optical dates show that the Holocene Danube delta started to build out of a Black Sea embayment similar to 5200 yr ago. Delta lobe development phases differ by as much as 5 k.y. from previously proposed ages. The new chronology allows for a better understanding of the Danube delta paleogeography, including the demise of Istria, the main ancient Greek-Roman city in the region. Prior reconstructions of sea level in the Black Sea inferred fluctuations to 15 m in range; however, stratigraphy of beach ridges in the delta shows that the relative Black Sea level for the past 5 k.y. was stable in the Danube delta region within -2 m and +1.5 of the current level. Hydroisostatic effects related to a proposed catastrophic reconnection of the Black Sea to the World Ocean in the early Holocene may have been responsible for the sea level reaching the highstand earlier than estimated by models. The new sea-level data suggest that submergence at several ancient settlements around the Black Sea may be better explained by local factors such as subsidence rather than by basin-wide sea-level fluctuations.
084aqTimes Cited:63Cited References Count:35

Carbon and nitrogen isotope compositions of organic matter in coastal marine sediments (the Gulf of Trieste, N Adriatic Sea): indicators of sources and preservation - Ogrinc, N.; Fontolan, G.; Faganeli, J.; Covelli, S. (Marine Chemistry, 2005)
Terrestrial organic carbon (OC) preserved in marine sediments is an important reservoir in the global carbon cycle, but remains poorly constrained. We determined the elemental and C- and N-isotopic compositions of organic material (OM) in surface sediments and sediment cores from the Gulf of Trieste (N Adriatic), an area characterized by relatively high riverine input. This multiple tracer approach permits evaluation of how sensitive each tracer is for constraining the terrestrial component of OM. Using the relevant terrestrial and marine OM end-members, we estimate that the terrestrial contribution ranges from about 90% at the mouth of the Isonzo River and decreases to <= 10% in the center of the Gulf. In the southern part of the Gulf, 32-44% of terrestrial OC is contributed from smaller rivers, while the delta(15)N values of OM reflect more effective nutrient utilization. Analyses of different size fractions show that smaller particles are consistently more organic-rich and tend to be transported further from the river mouth, depending on river discharge. In the size fraction 2-16 mu m, elemental ratios and delta(13)C(org) and delta(15)N isotopic signatures are consistent with a sedimentary OM pool dominated by bacterially derived biomass. Radiocarbon analyses of sedimentary OC yield depleted Delta(14)C values (-338.7 parts per thousand to -429.4 parts per thousand), indicating a significant fraction of relatively old OC. The natural abundance of C-13 and C-14 tracers suggests a two-component mixture of ancient and modem C in the sediments down to approximately 60 cm sub-bottom, with an estimated similar to 45% of sedimentary OC probably being derived from ancient sedimentary OC (kerogen). In addition, there is a significant change in the source of organic material downcore in these sediments which, along with geological evidence, indicate contributions from freshwater swamps typical of coastal lakes with intermittent connections to the sea (brackish) prior to similar to 9000 BP. Depth variations in a core from a salt marsh further indicate temporal variability of OM deposition and transformations in a changing brackish-marine environment in the past. (C) 2004 Elsevier B.V. All rights reserved.
934goTimes Cited:76Cited References Count:77

Carbon isotopes from fossil packrat pellets and elevational movements of Utah agave plants reveal the Younger Dryas cold period in Grand Canyon, Arizona - Cole, K. L.; Arundel, S. T. (Geology, 2005)
Carbon isotopes in rodent fecal pellets were measured on packrat (Neotoma spp.) middens from the Grand Canyon, Arizona. The pellet samples reflect the abundance of cold-intolerant C4 and Crassulacean acid metabolism (CAM) plant species relative to the predominant C3 vegetation in the packrat diet. The temporal sequence of isotopic results suggests a temperature decline followed by a sharp increase corresponding to the Boiling/ Allerod-Younger Dryas-early Holocene sequence. This pattern was then tested using the past distribution of Utah agave (Agave utahensis). Spatial analyses of the range of this temperature-sensitive CAM species demonstrate that its upper elevational limit is controlled by winter minimum temperature. Applying this paleotemperature proxy to the past ellevational limits of Utah agave suggests that minimum winter temperatures were similar to 8 degrees C below modern values during the Last Glacial Maximum, 4.5-6.5 degrees C below modern during the Bolling/Allerod, and 7.5-8.7 degrees C below modern during the early Younger Dryas. As the Younger Dryas terminated, temperatures warmed similar to 4 degrees C between ca. 11.8 ka and 11.5 ka. These extreme fluctuations in winter minimum temperature have not been generally accepted for terrestrial paleoecological records from the and southwestern United States, likely because of large statistical uncertainties of older radiocarbon results and reliance on proxies for summer temperatures, which were less affected.
960jfTimes Cited:22Cited References Count:26

Cross-formational flow and salinity sources inferred from a combined study of helium concentrations, isotopic ratios, and major elements in the Marshall aquifer, southern Michigan - Ma, L.; Castro, M. C.; Hall, C. M.; Walter, L. M. (Geochemistry Geophysics Geosystems, 2005)
Helium data and major ion chemistry are presented for the shallow Marshall aquifer in southern Michigan. This data set is subsequently analyzed in conjunction with major element data sets from deeper and shallower water levels previously collected in this area. He excesses and isotopic ratios suggest the presence of tritiogenic He-3 in young waters in the Marshall aquifer. He excesses in old groundwater samples are mostly of crustal origin although the presence of a significant mantle He component in some samples cannot be ruled out. He excesses in the Marshall aquifer are unusually high for such shallow depths ( <= 300 m) and reach over two and three orders of magnitude above those of air- saturated water ( ASW) for He-3 and He-4, respectively. He isotopes require a source external to the aquifer, partly supplied by underlying formations within the sedimentary sequence, partly from the crystalline basement. Calibration of He concentrations observed in the Marshall aquifer requires He fluxes of 1 x 10(-13) and 1.6 x 10(-6) cm(3) STP cm(-2) yr(-1) for He-3 and He-4, respectively. These He fluxes are far greater than those reported in other sedimentary basins around the world ( e. g., Paris Basin, Gulf Coast Basin) at similar and far greater depths. Such high He fluxes present at such shallow depths within the Michigan Basin strongly suggest the presence of a dominant vertical water flow component and further indicate that impact of recharge water at depth is minor. Upward cross- formational flow is also likely responsible for the extremely high salinities present in the shallow subsurface of the Michigan Basin. The observed positive correlation between helium and bromide strongly suggests that these two very distinct conservative tracers both originate at greater depths and further suggests that advection is the dominant transport mechanism within the basin. The occurrence of large- scale cross- formational flow is also consistent with the evolution displayed by the major ion chemistry throughout most of the sedimentary sequence, indicating that solutes from shallow levels carry the signature of deep formation brines.
973vwTimes Cited:18Cited References Count:63

The deglacial history of surface and intermediate water of the Bering Sea - Cook, M. S.; Keigwin, L. D.; Sancetta, C. A. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2005)
The lithology of deglacial sediments from the Bering Sea includes intervals of laminated or dysaerobic sediments. These intervals are contemporaneous with the occurrence of laminated sediments from the California margin and Gulf of California, which suggests widespread low-oxygen conditions at intermediate depths in the North Pacific Ocean. The cause could be reduced intermediate water ventilation, increased organic carbon flux, or a combination of the two. We infer abrupt decreases of planktonic foraminifer delta(18)O at 14,400 and 11,650 yr BP, which may be a combination of both freshening and warming. On the Shirshov Ridge, the abundance of sea-ice diatoms of the genus Nitzschia reach local maxima twice during the deglaciation, the latter of which may be an expression of the Younger Dryas. These findings expand the extent of the expression of deglacial millennial-scale climate events to include the northernmost Pacific. (c) 2005 Elsevier Ltd. All rights reserved.
995ksTimes Cited:51Cited References Count:52

Dissolved and particulate organic matter source-age characterization in river and estuarine outflow waters: a combined isotope and biochemical approach - Loh, A. N.; Bauer, J. E.; Canuel, E. A. (ASLO Summer Meeting, 2005)
id: 482

Evidence from the Northeastern Atlantic basin for variability in the rate of the meridional overturning circulation through the last deglaciation - Gherardi, J. M.; Labeyrie, L.; McManus, J. F.; Francois, R.; Skinner, L. C.; Cortijo, E. (Earth and Planetary Science Letters, 2005)
A first study from the subtropical western Atlantic, using Pa-231/Th-230 ratios as a kinematic proxy for deep water circulation, provided compelling evidence for a strong link between climate and the rate of Meridional Overturning Circulation (MOC) over the last deglaciation. However, these results warrant confirmation from additional locations and water depths because the interpretation of the sedimentary Pa-231/Th-230 ratio in terms of circulation vigor can be biased by variations in particle flux and composition. We have measured Pa-231/Th-230 in a core from the Iberian margin, in the Northeastern Atlantic basin, and have compared these new results to the data from the western Atlantic basin. We find that the reduction in the circulation during H1 and YD and the subsequent increases first recognized in the sediment deposited on Ben-nuda Rise are also evident in the eastern basin, in a totally different sedimentary regime, confirming that sedimentary Pa-231/Th-230 ratios record basin-wide changes in deep water circulation. However, some differences between the eastern and western records are also recognized, providing preliminary evidence to differentiate between renewal rates in the two North Atlantic basins and between shallower and deeper overturning. Our results suggest the possible existence of two sources of Glacial North Atlantic Intermediate Deep Water (GNAIW), one in the south Labrador Sea and another west of Rockall Plateau. Both sources contributed to the meridional overturning but the two had different sensitivity to meltwater from the Laurentide and the Fermoscandian ice sheets during the deglaciation. These results indicate that additional information on the geometry and strength of the ventilation of the deep Atlantic can be obtained by contrasting the evolution of sediment Pa-231/Th-230 in different sections of the Atlantic Ocean. (C) 2005 Elsevier B.V. All rights reserved.
995vhTimes Cited:93Cited References Count:69

Fluctuations in export productivity over the last century from sediments of a southern Chilean fjord (44 degrees S) - Sepulveda, J.; Pantoja, S.; Hughen, K.; Lange, C.; Gonzalez, F.; Munoz, P.; Rebolledo, L.; Castro, R.; Contreras, S.; Avila, A.; Rossel, P.; Lorca, G.; et al. (Estuarine Coastal and Shelf Science, 2005)
Here we present the first reconstruction of changes in surface primary production during the last century from the Puyuhuapi fjord in southern Chile, using a variety of parameters (diatoms, biogenic silica, total organic carbon, chlorins, and proteins) as productivity proxies. Two sediment cores from the head and the center of the fjord were analyzed and compared to gain insights on past changes in productivity in these two different depositional environments. Higher sedimentation rates found at the head of the fjord result from the combination of a shallower water column and a restricted circulation by the occurrence of a sill. Additionally, sediment mixing depths estimated from (210)Pb data suggest that suboxic conditions may dominate the bottom water and the sediment-water interface in this location.Productivity of the Puyuhuapi fjord during the last century was characterized by a constant increase from the late 19th century to the early 1980s, then decreased until the late 1990s, and then rose again to present-day values. The influence of rainfall on productivity was most noticeable during periods of low rainfall, which coincided with decreased overall productivity within the Puyuhuapi fjord. Simultaneous variations in productivity and rainfall in the study area suggest that marine productivity could respond to atmospheric-oceanic interactions at a local scale. At a regional scale, marine productivity of the area may be related to other large-scale processes such as the El Nino Southern Oscillation. (c) 2005 Elsevier Ltd. All rights reserved.
975sfTimes Cited:22Cited References Count:53

Geochemical and hydrogeological contrasts between shallow and deeper aquifers in two villages of Araihazar, Bangladesh: Implications for deeper aquifers as drinking water sources - Zheng, Y.; van Geen, A.; Stute, M.; Dhar, R.; Mo, Z.; Cheng, Z.; Horneman, A.; Gavrieli, I.; Simpson, H. J.; Versteeg, R.; Steckler, M.; Grazioli-Venier, A.; et al. (Geochimica et Cosmochimica Acta, 2005)
Sediment and groundwater profiles were compared in two villages of Bangladesh to understand the geochemical and hydrogeological factors that regulate dissolved As concentrations in groundwater. In both villages, fine-grained sediment layers separate shallow aquifers ( 50 ka ago and a groundwater age of thousands of years. In the other village (Bay), the sediment is
id: 604; 999UZ Times Cited:59 Cited References Count:49

Geochemical characteristics of recent 2 ka mud on the inner shelf of the East China Sea - Xiao, S. B.; Li, A. C.; Jiang, F.; Xu, F. J.; Zheng, F.; Chen, Z. (GEOCHIMICA, 2005)
The particle size of DD2 in the northern part of the muddy area along the continental margin of the East China Sea was analyzed. AMS 14 C age test and the main elements, trace elements The relationship between the content of each element and the particle size was discussed and analyzed. The relationship between them was discussed by R factor analysis. Studies have shown that nearly 2 ka to DD2 The majority of the main elements and trace elements in the pores are stable; the content of most of the elements with the grain size becomes increasing, while the content of Sr and SiO 2 The decreasing tendency of CaO, Na 2 O, Hf, Zr and Ti is poor in particle size. The results of factor analysis show that the chemical composition of DD2 pore can be It is divided into four kinds of combination types: the main characteristics of the distribution of elements in sediments are reflected, and the samples are not treated by salt beforehand to cause the combination of main elements and trace elements The Zr, Hf and Nb elements are enriched in the specific particle size components (silt), and the addition of calcareous biological components and the redistribution of elements during early diagenesis Wait. The results show that Rb, Cu, Ni, V, P, Sc, Fe 2 O 3 , Cr, K 2 O, Nb, Co, Th, Ti and Al 2 O 3 are relatively inactive elements in DD 2 pores, They can be compared with the modern Yangtze River, the Yellow River sediments, for genetic analysis. The Ti J Zr and Cr J Th ratios indicate that the pore deposits are mainly derived from the granitic Source area.
id: 570
Keywords: East China Sea continental shelf; factor analysis; geochemical characteristics; particle size

Glacial water mass geometry and the distribution of d 13 C of SCO 2 in the western Atlantic Ocean - Curry, W. B.; Oppo, D. W. (Paleoceanography, 2005)
id: 416

Holocene aminochronology and time-averaging fro Chesapeake Bay mulinia - Edwards, A. L.; Wehmiller, J. R.; Lockwood, R.; Kaufman, D.; Bright, J.; Cronin, T.; Willard, D. (Geological Society of America Abstracts with Programs, 2005)
id: 585

Holocene molluscan aminostratigraphy of Chesapeake Bay sediments - Edwards, A. L.; Lockwood, R.; Wehmiller, J.; Cronin, T.; Kaufman, D.; Bright, J. (Geological Society of America Abstracts with Programs, 2005)
id: 586

Holocene terebratulid brachiopods from the southern Brazilian Shelf (South Atlantic): Ecology, taphonomy, and time-averaging - Kowalewski, M.; Simoes, M. G.; Barbour-Wood, S. L.; Krause R.A, Jr.; Rodriguez, S. C.; Wehmiller, J. F.; Rodland, D. L.; Carroll, M. (Fifth International Brachiopod Congress, 2005)
id: 1171; Abstracts, p. 34-35

An investigation of accurate gas exchange measurements for determing a large river carbon isotope mass balance - Raymond, P. A.; McGillis, W. R.; Bauer, J. E.; Caraco, N. F.; Cole, J. J. (37th Liege International Colloquium on Gas Transfer at Water Survaces, 2005)
id: 490

Isolation and Characterization of a Genetically Tractable Photoautotrophic Fe(II)-Oxidizing Bacterium, Rhodopseudomonaspalustris Strain TIE-1 - Jiao, Yongqin; Kappler, Andreas; Croal, Laura R.; Newman, Dianne K. (Applied and Environmental Microbiology, 2005)
id: 1576

On the isolation of elemental carbon (EC) for micro-molar 14C accelerator mass spectrometry: development of a hybrid reference material for 14C-EC accuracy asssurance, and a critical evaluation of the thermal optical kinetic (TOK EC isolation procedure - Currie, L. A.; Kessler, J. D. (Atmospheric Chemistry and Physics, 2005)
id: 631

Late neogene and quaternary evolution of the northern Albermarle Embayment (mid-Atlantic continental margin, USA) - Mallinson, D.; Riggs, S.; Culver, S.; Thieler, R.; Foster, D. R.; Corbett, D. R.; Farrell, K.; J, Wehmiller (Marine Geology, 2005)
id: 1160

Long range transport of biomass aerosol to Greenland: Multi-spectroscopic investigation of particles deposited in the snow - Currie, L. A.; Kessler, J. D.; Fletcher, R. A.; Dibb, J. E. (Journal of Radioanalytical and Nuclear Chemistry, 2005)
Recent developments in radiometrics and mass spectrometry techniques for ultra-sensitive analysis of radionuclides in the marine environment are reviewed. In the radiometrics sector the dominant development has been the utilization of large HPGe detectors in underground laboratories with anti-cosmic or anti-Compton shielding for the analysis of short and medium-lived radionuclides in the environment. In the mass spectrometry sector, applications of inductively coupled plasma mass spectrometry (ICP-MS) and accelerator mass spectrometry (AMS) for the analysis of long-lived radionuclides in the environment are the most important recent achievements. The recent developments do not only considerably decrease the detection limits for several radionuclides (up to several orders of magnitude), but they also enable to decrease sample volumes so that sampling, e.g., of the water column can be much easier and more effective. A comparison of radiometrics and mass spectrometry results for the analysis of radionuclides in the marine environment shows a reasonable agreement - within quoted uncertainties, for wide range of activities and different sample matrices analyzed.
899oqTimes Cited:2Cited References Count:28

Long term calibration of the Noble gas temperature system in a shallow unconfined Pleistocene aquifer - Hall, C. M.; Castro, M. C.; Lohmann, K. C.; Ma, L. (Eos Trans. AGU Fall Meeting Supplement, 2005)
id: 438

Mid-Holocene hydrologic change and hypolimnion formation in Lake Erie - Clotts, R. A.; McCambridge, C. E.; Barrera, E.; Saylor, B. Z.; Palmer, D. F.; Coakley, J. P. (Journal of Great Lakes Research, 2005)
id: 688

Noble gases and stable isotopes in a shallow aquifer in southern Michigan: Implications for noble gas paleotemperature reconstructions for cool climates - Hall, C. M.; Castro, M. C.; Lohmann, K. C.; Ma, L. (Geophysical Research Letters, 2005)
Noble gas data from the Glacial Drift, the shallowest aquifer in southern Michigan confirm findings by Ma et al. (2004) that modern noble gas temperatures (NGTs) are systematically below the current mean annual air temperature (MAAT) which, in turn, is similar to the ground temperature of these recharge waters. By tracking noble gas concentrations as well as stable isotope ratios through an autumn, winter, spring and into summer, we show that although water in this aquifer is modern, noble gases do not track the atmosphere on a short time scale. Specifically, excess He-3 and He-4 indicate that the gas environment at the water table is integrating conditions over years or decades rather than weeks or months. Our results are interpreted using various NGT interpretational models and possible mechanisms for the production of low apparent NGTs are discussed.
968qnTimes Cited:26 Cited References Count:14
Keywords: water

One-year record of organic and elemental carbon in fine particles in downtown Beijing and Shanghai - Yang, F.; He, K.; Ye, B.; Chen, X.; Cha, L.; Cadle, S. H.; Chan, T.; Mulawa, P. A. (Atmospheric Chemistry and Physics, 2005)
Weekly PM2.5 samples were collected for one year ( 1999 - 2000) in Beijing and Shanghai and the carbonaceous species analyzed to investigate and compare their time series patterns and possible sources in the two biggest cities of China. Weekly carbonaceous concentrations varied in wide ranges with 8.6 - 59 mu g m(-3) for OC and 1.5-25.4 mu g m(-3) for EC in Beijing, and with 5.1 - 38.4 mu g m(-3) for OC and 2.3 - 13.0 mu g m(-3) for EC in Shanghai. Similar weekly and seasonal variations of OC and EC concentrations were found in each city though major combustion sources presented source-dependent emission characteristics and seasonal differences in emission amount for carbonaceous species. Both OC and EC maintained much higher concentrations in late fall through winter, probably due to enhanced emissions coupled with unfavorable meteorological conditions. In Beijing, the C-14 analysis of limited samples suggested there was a significant contribution ( 33 - 48%) of modern carbon to the total fine carbonaceous PM burden with higher fractions in the harvest seasons. The high mass ratios of excessive potassium to EC in both Beijing and Shanghai also indicated that biomass burning had important contribution to fine carbonaceous particles.
936dsTimes Cited:77Cited References Count:45

Organic matter inputs and metabolism in a large river estuary (the Hudson): Insights from natural abundance isotopes and whole system metabolism - Caraco, N. F.; Cole, J. J.; Raymond, P. A.; Bauer, J. E. (American Society of Limnology and Oceanography, 2005)
id: 478

Otolith science entering the 21st century - Campana, S. E. (Marine and Freshwater Research, 2005)
A review of 862 otolith-oriented papers published since the time of the 1998 Otolith Symposium in Bergen, Norway suggests that there has been a change in research emphasis compared to earlier years. Although close to 40% of the papers could be classifed as ‘annual age and growth’ studies, the remaining papers were roughly equally divided between studies of otolith microstructure, otolith chemistry and non-ageing applications. A more detailed breakdown of subject areas identified 15 diverse areas of specialisation, including age determination, larval fish ecology, population dynamics, species identification, tracer applications and environmental reconstructions. For each of the 15 subject areas, examples of representative studies published in the last 6 years were presented, with emphasis on the major developments and highlights. Among the challenges for the future awaiting resolution, the development of novel methods for validating the ages of deepsea fishes, the development of a physiologically-based otolith growth model, and the identification of the limits (if any) of ageing very old fish are among the most pressing.
id: 1044

Preliminary report on the archaeology and paleoecology of the Abalone Rocks Estuary, Santa Rosa Island, California - Rick, T. C.; Kennett, D. J.; Erlandson, J. M. (Proceedings of the Sixth California Islands Symposium, 2005)
id: 468

Recent 8 ka mud records of the East Asian Winter Monsoon from the inner shelf of the East China Sea - Xiao, S. B.; Li, A. C.; Chen, M. H.; Liu, J. P.; Jiang, F. G.; Li, T. G.; Xie, Q.; Xiang, R.; Chen, Z. (Earth Science - Journal of China University of Geosciences, 2005)
id: 569

Recent and modern marine erosion on the New Jersey outer shelf - Goff, J. A.; Austin, J. A.; Gulick, S.; Nordfjord, S.; Christensen, B.; Sommerfield, C.; Olson, H.; Alexander, C. (Marine Geology, 2005)
Recent chirp seismic reflection data combined with multibeam bathymetry, backscatter, and analysis of grab samples and short cores provide evidence of significant recent erosion on the outer New Jersey shelf. The timing of erosion is constrained by two factors: (1) truncation at the seafloor of what is interpreted to be the transgressive ravinement surface at the base of the surficial sand sheet, and (2) truncation of apparently moribund sand ridges along erosional swales oriented parallel to the primary direction of modem bottom flow and oblique to the strike of the sand ridges. These observations place the erosion in a marine setting, post-dating the passage of the shoreface ravinement and the evolution of sand ridges that form initially in the near shore environment. Also truncated by marine erosion are shallowly buried, fluvial channel systems, formed during the Last Glacial Maximum and filled during the transgression, and a regional reflector "R" that is > &SIM; 40 kyr. Depths of erosion range from a few meters to > 10 m. The seafloor within eroded areas is often marked by "ribbon" morphology, seen primarily in the backscatter data as areas of alternating high and low backscatter elongated in the direction of primary bottom flow. Ribbons are more occasionally observed in the bathymetry; where observed, crests exhibit low backscatter and troughs exhibit high backscatter. Sampling reveals that the high backscatter areas of the ribbons consist of a trimodal admixture of mud, sand and shell hash, with a bimodal distribution of abraded and unabraded sand grains and microfauna. The shell hash is interpreted to be an erosional lag, while the muds and unabraded grains are, in this non-depositional environment, evidence of recent erosion at the seafloor of previously undisturbed strata. The lower-backscatter areas of the ribbon morphology were found to be a well-sorted medium sand unit only a few 10's of cm thick overlying the shelly/muddy/sandy material. Concentrations of well-rounded gravels and cobbles were also found in eroded areas with very high backscatter, and at least one of these appears to be derived from the base of an eroded fluvial channel. Seafloor reworking over the transgressive evolution of the shelf appears to have switched from sand ridge evolution, which is documented to &SIM; 40 m water depth, to more strictly erosional modification at greater water depths. We suggest that this change may be related to the reduction with water depth in the effectiveness of sediment resuspension by waves. Resuspension is a critical factor in the grain size sorting during transport by bottom currents over large bedforms like sand ridges. Otherwise, we speculate, displacement of sand by unidirectional currents will erode the seafloor. © 2005 Elsevier B.V. All rights reserved.
925kdTimes Cited:42Cited References Count:53

Sedimentation and carbon burial on the northern California continental shelf: the signatures of land-use change - Leithold, E. L.; Perkey, D. W.; Blair, N. E.; Creamer, T. N. (Continental Shelf Research, 2005)
The burial of organic carbon (OC) on continental margins is strongly coupled to the supply and accumulation of inorganic mineral particles. It follows that carbon burial on the margins should be impacted by changes in riverine sediment delivery, yet these impacts have not been well documented. In this study, an similar to2000-year record of sedimentation and carbon burial on the continental shelf offshore from the Eel River in northern California was examined. The record reveals a 6-11-fold increase in the rate of sediment accumulation on the mid-shelf beginning about 1955, and a concomitant decrease in grain size and increase in flood-layer preservation. At the same time. the age of buried wood fragments abruptly decreased and their stable carbon isotopic composition became enriched in C-13. We argue that these changes can be explained largely as the result of altered land use in the Eel watershed during the past century and its impacts on shelf sediment dispersal processes.Sedimentary OC on the Eel shelf consists primarily of discrete wood fragments associated with coarse-silt- and sandsized particles, and of organic matter strongly bound to clay-sized mineral grains. The clay fraction is a particularly sensitive recorder of environmental change in the Eel system. Above the 1995 horizon, the clay fraction shows an abrupt decrease in OC concentration and loading (OC content normalized to particle surface area) attendant with the increased accumulation rate. Kerogen carbon constitutes a relatively constant proportion of the clay-associated OC throughout the similar to2000-year record. Increases in mass wasting and input of bedrock material following the onset of intensive industrial logging in the Eel watershed may have resulted in a lower loading of terrestrial plant OC in the clay fraction deposited after 1955 as suggested by isotopic mass balance calculations.The Eel River is representative of small mountainous watersheds worldwide that deliver a major portion of the sediment and carbon flux to the margins and that have been strongly impacted by land-use change during the past century. Our results suggest that such changes leave a distinctive mark in both the sedimentological and geochemical records preserved offshore. (C) 2004 Elsevier Ltd. All rights reserved.
894cyTimes Cited:29Cited References Count:109

On the sedimentological origin of downcore variations of bulk sedimentary nitrogen isotope ratios - Kienast, M.; Higginson, M. J.; Mollenhauer, G.; Eglinton, T. I.; Chen, M. T.; Calvert, S. E. (Paleoceanography, 2005)
The bulk sedimentary nitrogen isotopic composition of two cores from nearby sites on the northern slope of the South China Sea (Site 17940 and Ocean Drilling Program (ODP) Site 1144) differs by up to >2‰ during the last glacial period. Given their close proximity, both core sites are located in the same biogeographic zone and nutrient regime, and it is thus unlikely that this offset is due to a true gradient in surface ocean conditions. In an attempt to resolve this offset, we have investigated the possible effects of two sedimentological parameters that can affect bulk sedimentary δ15N, namely, the variable contribution of inorganic N to bulk N in the sediment and the grain-size dependence of bulk δ15N. We find that neither effect, singly or in combination, is sufficient to explain the significant δ15N offset between the two down-core records. By elimination the most likely explanation for the observed discrepancy is a different origin of both the organic and inorganic nitrogen at each site. This study adds to the growing body of evidence highlighting the complex nature and origin of the sedimentary components in sediment drifts, such as ODP Site 1144.
id: 1066

Source, timing and depositional environments of Paleochannel incision and infill on the New Jersey Shelf - Alexander, C.; Christensen, B.; Turner, J.; Goff, J.; Austin J.A, Jr.; Venherm, C.; Nordfjord, S.; Sommerfield, C.; Gulick, S.; Fulthorpe, C. (2005 National GSA Meeting, 2005)
id: 638

Status of the U. S. canary rockfish resource in 2005 - Methot, R.; Stewart, I. J. (Status of the Pacific Coast Groundfish Fishery Through 2005, Stock Assessment and Fishery Evaluation: Stock Assessments and Rebuilding Analyses, 2005)
id: 539

Submerged paleoshorelines in the southern and western Black Sea - implications for inundated prehistoric archaeological sites - Coleman, Dwight F.; Ballard, Robert D. (The Black Sea Flood Questions: Changes in Coastline, Climate, and Human Settlement, 2005)
id: 1058

Unusually high helium fluxes in the shallow Marshall aquifer in southern Michigan: implications for cross-formational flow and salinity sources - Ma, L.; Castro, M. C.; Hall, C. M.; Walter, L. M. (Eos Trans. AGU Fall Meeting Supplement, 2005)
id: 437

The 14C AMS system at the University of Georgia - Roberts, M. L.; Culp, R. A.; Dvoracek, D. K.; Hodgins, G. W. L.; Neary, M. P.; Noakes, J. E. (Nuclear Instruments and Methods in Physics Research, 2004)
id: 1809

The 14C AMS system at The University of Georgia - Roberts, M. L.; Culp, R. A.; Dvoracek, D. K.; Hodgins, G. W. L.; Neary, M. P.; Noakes, J. E. (Proceedings of the Ninth International Conference on Accelerator Mass Spectrometry, 2004)
The Center for Applied Isotope Studies at the University of Georgia has installed a compact 14C accelerator mass spectrometry (AMS) system manufactured by the National Electrostatics Corporation, Middleton, Wisconsin. The system utilizes a 134 sample ion source and a 500 kV Pelletron. In terms of cost and size, the new system is a significant advance over previous technology. Details and performance of the new system will be presented.
id: 2103

Alabama Gulf Coast groundwaters: 4He and 14C as groundwater-dating tools - Carey, Anne; Dowling, Carolyn B.; Poreda, Robert J. (Geology, 2004)
Analyses of 4He and 14C in groundwaters from a Miocene quartz aquifer on the Alabama Gulf Coast show the usefulness of 4He for dating these Holocene groundwaters. In this aquifer system of low alkalinities and low pHs, radiocarbon ages can be used without model correction. The groundwaters studied ranged from 42.3% to 95.5% modern carbon and yielded uncorrected ages of 375–6790 yr. Radiogenic 4He ages ranged from >50–7500 yr.
id: 1222
Keywords: 14C; 4He; age dating; Baldwin County Alabama; groundwater

Anthropogenic eutrophication of Long Island Sound: effects on diatom communities through time - Cooper, S. R.; Thomas, E.; Varekamp, J. C.; Sangiorgio, F. (7th Biennial Long Island Sound reserach conference proceedings, 2004)
id: 1181

Assessing sources and agesof organic matter supporting river and estuarine bacterial production: a multiple isotope (Delta14C, delta13C and delta15N) approach - McCallister, S. L.; Bauer, J. E.; Cherrier, J. C.; Ducklow, H. W. (Limnology and Oceanography, 2004)
id: 1153

Chronology of sediment deposition in Upper Klamath Lake, Oregon - Colman, S. M.; Bradbury, J. P.; McGeehin, J. P.; Holmes, C. W.; Sarna-Wojcicki, A. M.; Edgington, D. (Journal of Paleolimnology, 2004)
A combination of tephrochronology and 14C, 210Pb, and 137Cs measurements provides a robust chronology for sedimentation in Upper Klamath Lake during the last 45 000 years. Mixing of surficial sediments and possible mobility of the radio-isotopes limit the usefulness of the 137Cs and 210Pb data, but 210Pb profiles provide reasonable average sediment accumulation rates for the last 100–150 years. Radiocarbon ages near the top of the core are somewhat erratic and are too old, probably as a result of detrital organic carbon, which may have become a more common component in recent times as surrounding marshes were drained. Below the tops of the cores, radiocarbon ages in the center of the basin appear to be about 400 years too old, while those on the margin appear to be accurate, based on comparisons with tephra layers of known age.Taken together, the data can be combined into reasonable age models for each site. Sediments have accumulated at site K1, near the center of the basin, about 2 times faster than at site CM2, on the margin of the lake. The rates are about 0.10 and 0.05 cm/yr, respectively. The chronological data also indicate that accumulation rates were slower during the early to middle Holocene than during the late Holocene, consistent with increasing wetness in the late Holocene.
id: 182

Controls on the variability of organic matter and dissolved inorganic carbon ages in northeast U.S. rivers - Raymond, P. A.; Bauer, J. E.; Caraco, N. F.; Cole, J. J.; Longworth, B. E.; Petsch, S. T. (Marine Chemistry, 2004)
id: 967

Coupling instrumental and geological records of sea-level change: Evidence from southern New England of an increase in the rate of sea-level rise in the late 19th century - Donnelly, J. P.; Cleary, P.; Newby, P.; Ettinger, R. (Geophysical Research Letters, 2004)
We construct a high-resolution relative sea-level record for the past 700 years by dating basal salt-marsh peat samples above a glacial erratic in an eastern Connecticut salt marsh, to test whether or not the apparent recent acceleration in the rate of sea-level rise (SLR) is coeval with climate warming. The data reveal an average SLR rate of 1.0 +/- 0.2 mm/year from about 1300 to 1850 A. D. Coupling of the regional tide-gauge data (1856 to present) with this marsh-based record indicates that the nearly three-fold increase in the regional rate of SLR to modern levels likely occurred in the later half of the 19th century. Thus the timing of the observed SLR rate increase is coincident with the onset of climate warming, indicating a possible link between historic SLR increases and recent temperature increases.
806kkTimes Cited:94 Cited References Count:20
Keywords: accretion; cal yr ad; climate-ocean variations; connecticut; long-island sound; salt-marsh

Dating the rise of atmospheric oxygen - Bekker, A.; Holland, H. D.; Wang, P. L.; Rumble, D.; Stein, H. J.; Hannah, J. L.; Coetzee, L. L.; Beukes, N. J. (Nature, 2004)
Several lines of geological and geochemical evidence indicate that the level of atmospheric oxygen was extremely low before 2.45 billion years (Gyr) ago, and that it had reached considerable levels by 2.22 Gyr ago. Here we present evidence that the rise of atmospheric oxygen had occurred by 2.32 Gyr ago. We found that syngenetic pyrite is present in organic-rich shales of the 2.32-Gyr-old Rooihoogte and Timeball Hill formations, South Africa. The range of the isotopic composition of sulphur in this pyrite is large and shows no evidence of mass-independent fractionation, indicating that atmospheric oxygen was present at significant levels (that is, greater than 10(-5) times that of the present atmospheric level) during the deposition of these units. The presence of rounded pebbles of sideritic iron formation at the base of the Rooihoogte Formation and an extensive and thick ironstone layer consisting of haematitic pisolites and oolites in the upper Timeball Hill Formation indicate that atmospheric oxygen rose significantly, perhaps for the first time, during the deposition of the Rooihoogte and Timeball Hill formations. These units were deposited between what are probably the second and third of the three Palaeoproterozoic glacial events.
id: 1534; Bekker, A Holland, H D Wang, P-L Rumble, D 3rd Stein, H J Hannah, J L Coetzee, L L Beukes, N J England Nature. 2004 Jan 8;427(6970):117-20.

Decline of surface temperature and salinity in the western tropical Pacific Ocean in the Holocene epoch - Stott, L.; Cannariato, K.; Thunell, R.; Haug, G. H.; Koutavas, A.; Lund, S. (Nature, 2004)
In the present-day climate, surface water salinities are low in the western tropical Pacific Ocean and increase towards the eastern part of the basin. The salinity of surface waters in the tropical Pacific Ocean is thought to be controlled by a combination of atmospheric convection, precipitation, evaporation and ocean dynamics, and on interannual timescales significant variability is associated with the El Nino/Southern Oscillation cycles. However, little is known about the variability of the coupled ocean-atmosphere system on timescales of centuries to millennia. Here we combine oxygen isotope and Mg/Ca data from foraminifers retrieved from three sediment cores in the western tropical Pacific Ocean to reconstruct Holocene sea surface temperatures and salinities in the region. We find a decrease in sea surface temperatures of approximately 0.5 degrees C over the past 10,000 yr, whereas sea surface salinities decreased by approximately 1.5 practical salinity units. Our data imply either that the Pacific basin as a whole has become progressively less salty or that the present salinity gradient along the Equator has developed relatively recently.
Stott, LowellCannariato, KevinThunell, RobertHaug, Gerald HKoutavas, AthanasiosLund, SteveengResearch Support, U.S. Gov't, Non-P.H.S.England2004/09/03 05:00Nature. 2004 Sep 2;431(7004):56-9.

Deglacial sea surface temperatures of the western tropical Pacific: A new look at old coral - Cohen, A. L.; Hart, S. R. (Paleoceanography, 2004)
Using Secondary Ion Mass Spectrometry ( SIMS) ion microprobe techniques, we generated annual Sr/Ca cycles with subweekly resolution from chunks of Porites coral retrieved from a Tahiti barrier reef drill core (149degreesW, 17degreesS), representing the period 13,650 to 13,100 years B.P. The centers of pristine skeletal septa were selectively targeted with a 10 mum diameter ion beam spot, avoiding adjacent pore spaces occupied by secondary aragonite needles. Applying a Sr/Ca-sea surface temperature (SST) calibration equation derived from modern Tahiti Porites having the same low growth rate as the fossil specimens, we obtained SSTs similar to0.5degrees-1.5degreesC cooler during the Bolling-Allerod relative to the present day, with no significant change in seasonality. On the contrary, we estimate that analysis of bulk samples would yield excessively cool Sr/Ca-based SST estimates due to the occupation by secondary aragonite crystals of up to 50% of the skeletal pore space in the ancient samples. We find that growth rate effects on coral Sr/Ca further depress the apparent mean annual derived SSTs (by >3degreesC) and amplify the apparent seasonality by selectively enhancing wintertime cooling. Our microscale analysis of pristine skeleton and application of an appropriate growth-dependent calibration yield Sr/Ca-derived SSTs that are in good agreement with those derived from Mg/Ca ratios of calcitic foraminifera which indicate a continuous postglacial warming of the western tropical Pacific, in phase with the warming of the tropical Atlantic.
885czTimes Cited:30 Cited References Count:37
Keywords: bolling-allerod; climate-change; coral sr/ca; diagenesis; ion microprobe; last deglaciation; paleotemperature proxy; radiocarbon; record; sea surface temperature; sr/ca; strontium; symbiotic coral; trace-elements; tropical pacific

Enhanced marine productivity off western North America during warm climate intervals of the past 52 kyr - Ortiz, J. D.; O'Connell, S.; DelViscio, J.; Dean, W. E.; Carriquiry, J.; Marchitto, T. M.; Zheng, Y.; van Geen, A. (Geology, 2004)
id: 603

Eutrophication of western Long Island Sound - Thomas, E.; Varekamp, J. C.; Acosta, Z.; Thaler, B.; Cooper, S.; Sangiorgio, F. (GSA Annual Meeting, 2004)
id: 739

Evaluation of ocean carbon cycle models with data-based metrics - Matsumoto, K.; Sarmiento, J. L.; Key, R. M.; Aumont, O.; Bullister, J. L.; Caldeira, K.; Campin, J. M.; Doney, S. C.; Drange, H.; Dutay, J. C.; Follows, M.; Gao, Y.; et al. (Geophysical Research Letters, 2004)
New radiocarbon and chlorofluorocarbon-11 data from the World Ocean Circulation Experiment are used to assess a suite of 19 ocean carbon cycle models. We use the distributions and inventories of these tracers as quantitative metrics of model skill and find that only about a quarter of the suite is consistent with the new data-based metrics. This should serve as a warning bell to the larger community that not all is well with current generation of ocean carbon cycle models. At the same time, this highlights the danger in simply using the available models to represent the state-of-the-art modeling without considering the credibility of each model.
811adTimes Cited:110 Cited References Count:17
Keywords: anthropogenic co2; pacific-ocean; radiocarbon

Evidence of historical wet period deposits in central Long Island Sound: source and transport processes based on mercury profiles and sedimentology - Carey, D. A.; Varekamp, J. C. (7th biennial Long Island Sound research conference, Program and abstrracts, 2004)
id: 734

The evolution of the Earth surface sulfur reservoir - Canfield, D. E. (American Journal of Science, 2004)
The surface sulfur reservoir is in intimate contact with the mantle. Over long time scales, exchange with the mantle has influenced the surface reservoir size and possibly its isotopic composition. Processes delivering sulfur to the Earth surface from the mantle include volcanic outgassing, hydrothermal input, and ocean crust weathering. The sulfide fixed in ocean crust as a consequence of hydrothermal sulfate reduction, and subduction of sedimentary sulfides, represent return pathways of sulfur to the mantle. The importance of these different pathways in influencing the size of the surface sulfur reservoir depends on the particulars of ocean and atmosphere chemistry. During times of banded iron formation when the oceans contained dissolved iron, sulfide from submarine hydrothermal activity was precipitated on the seafloor and subsequently subducted back into the mantle and, therefore, had little impact on the surface sulfur reservoir size. With sulfidic ocean bottom water conditions, which may have occurred through long stretches of the Mesoproterozoic and Neoproterozoic, significant amounts of sulfide is subducted into the mantle. When the oceans are oxic, sulfide subduction is unimportant, and an additional source, ocean crust weathering, delivers sulfur to the Earth surface. Thus, under oxic conditions the surface environment accumulates sulfur, and probably has for most of the last 700 million years.Mass balance modeling suggests that the surface sulfur reservoir may have peaked in size in the early Mesoproterozoic, declined to a minimum in the Neoproterozoic, and increased to its present size through the Phanerozoic. The exchange of sulfur between the mantle and the surface environment can also influence the isotopic composition of the surface reservoir. Modeling shows that the subduction of S-34- depleted sulfur through the Mesoproterzoic could have significantly increased the average delta(34)S of the surface reservoir into the late Neoproterozoic. The preserved isotope record through the Neoproterozoic is well out of balance, with the average delta(34)S for sulfate and sulfide both exceeding the modem crustal average. This imbalance could be explained, at least partly, if the crustal average was more S-34-enriched than at present, as the modeling presented here suggests.
889sqTimes Cited:142Cited References Count:59

Flexible strategies for resource defense on the northern channel islands of California: An agent-based model - Kennett, D. J.; Clifford, R. (The Archaeology of Insularity: Examining the Past in Island Environments, 2004)
id: 470

H2-rich fluids from serpentinization: geochemical and biotic implications - Sleep, N. H.; Meibom, A.; Fridriksson, T.; Coleman, R. G.; Bird, D. K. (Proc Natl Acad Sci U S A, 2004)
Metamorphic hydration and oxidation of ultramafic rocks produces serpentinites, composed of serpentine group minerals and varying amounts of brucite, magnetite, and/or FeNi alloys. These minerals buffer metamorphic fluids to extremely reducing conditions that are capable of producing hydrogen gas. Awaruite, FeNi3, forms early in this process when the serpentinite minerals are Fe-rich. Olivine with the current mantle Fe/Mg ratio was oxidized during serpentinization after the Moon-forming impact. This process formed some of the ferric iron in the Earth's mantle. For the rest of Earth's history, serpentinites covered only a small fraction of the Earth's surface but were an important prebiotic and biotic environment. Extant methanogens react H2 with CO2 to form methane. This is a likely habitable environment on large silicate planets. The catalytic properties of FeNi3 allow complex organic compounds to form within serpentinite and, when mixed with atmospherically produced complex organic matter and waters that circulated through basalts, constitutes an attractive prebiotic substrate. Conversely, inorganic catalysis of methane by FeNi3 competes with nascent and extant life.
Sleep, N HMeibom, AFridriksson, ThColeman, R GBird, D KengResearch Support, U.S. Gov't, Non-P.H.S.2004/08/25 05:00Proc Natl Acad Sci U S A. 2004 Aug 31;101(35):12818-23. Epub 2004 Aug 23.

Holocene development of the Yellow River's subaqueous delta, North Yellow Sea - Liu, J. P.; Milliman, J. D.; Gao, S.; Cheng, P. (Marine Geology, 2004)
id: 650

A late Pleistocene-Holocene noble gas paleotemperature record in southern Michigan - Ma, L.; Castro, M. C.; Hall, C. M. (Geophysical Research Letters, 2004)
Noble gas temperatures (NGTs) and C-14 derived ages in groundwaters of the Michigan Basin reveal a ground temperature of similar to1degreesC toward the end of the Last Glacial Maximum (LGM) suggesting that groundwater recharge occurred under the Laurentide Ice Sheet (LIS) cover. In addition to the general warming observed since the LGM, the NGT record indicates an abrupt warming event between similar to12.8 and 11.1 kyrs BP, correlative to the Bolling-Allerod (BOA) warm phases. Ice-sheet-linked changes in freshwater delivery to the North Atlantic, together with changes in the North Atlantic Deep Water (NADW) circulation are possible causes of such abrupt climate shifts in northeastern US. Pleistocene waters yielding the lowest NGTs have the highest delta(18)O and deltaD values, suggesting an atmospheric circulation pattern distinct from today, with a stronger moisture component from the Gulf of Mexico, possibly due to the presence of the LIS which weakened the Pacific westerly flow.
881pcTimes Cited:31Cited References Count:24

Late-glacial climate as inferred from chironomid assemblages in lake sediments from Aroostook County, northeastern Maine - Chase, G. (University of Maine, 2004)

Long Island Sound: diatoms from sediment cores as part of environmental and ecological change studies, abstracts - Cooper, S. R.; Thomas, E.; Varekamp, J. C. (Mid-Atlantic ecology conference: sustainable landscapes, 2004)
id: 735

Mantle Samples Included in Volcanic Rocks: Xenoliths and Diamonds - Pearson, D. G.; Canil, D.; Shirey, S. B. (Treatise on Geochemistry, 2004)
id: 1575

New insights into the burial history of organic carbon on the early Earth - Bjerrum, C. J.; Canfield, D. E. (Geochemistry Geophysics Geosystems, 2004)
[1] The isotope record of organic matter and calcium carbonate is often used to infer the burial history of organic carbon through time. As organic carbon burial is widely held to control long-term oxygen production, the isotope record also relates to the production rates of oxygen on Earth. Current interpretations of the record suggest a long-term consistency in the proportion of total carbon buried as organic carbon (f ratio), with some important periods of much higher burial proportions. The isotope record is analyzed here with a new carbon isotope mass balance model, which considers submarine hydrothermal weathering of ocean crust as a significant removal pathway of inorganic carbon. With this model the f ratio is considerably reduced if isotopically depleted inorganic carbon is precipitated during hydrothermal weathering and if hydrothermal weathering dominates inorganic carbon removal from the surface environment. In contrast to previous calculations, our analysis of the carbon isotope record shows that organic carbon burial in the Archean accounted for only between 0% and 10% of the total carbon burial. These low burial proportions would have contributed to a slow accumulation of atmospheric oxygen in the Archean.
id: 1506; 846RU Times Cited:14 Cited References Count:44

Paleochannel incision and infill on the New Jersey shelf: timing, character and depositional environment - Alexander, C.; Christensen, C.; Goff, J.; Austin J.A, Jr.; Venherm, C.; Nordfjord, S.; Gulick, S.; Sommerfield, C.; Fulthorpe, C.; Schock, S. (2005 SE GSA Meeting, 2004)
id: 1120

Relations between environmental black carbon sorption and geochemical sorbent characteristics - Cornelissen, G.; Kukulska, Z.; Kalaitzidis, S.; Christanis, K.; Gustafsson, O. (Environmental Science & Technology, 2004)
Pyrogenic carbon particles in sediments (soot and charcoal, collectively termed "black carbon" or BC) appear to be efficient sorbents of many hydrophobic organic compounds, so they may play an important role in the fate and toxicity of these substances. To properly model toxicant sorption behavior, it is important to (i) quantify the magnitude of the role of BC in sorption and (ii) elucidate which geochemical BC characteristics determine the strength of environmental BC sorption. Sorption isotherms of d(10)-phenanthrene (d(10)-PHE) were determined over a wide concentration range (0.0003-20 mug/L), for five sediments with widely varying characteristics. From the sorption isotherms, we determined Freundlich coefficients of environmental BC sorption, K-F,BC(env). These varied from 10(4.7) to 10(5.5). From the data, it could be deduced that BC was responsible for 49-85% of the total d(10)-PHE sorption at a concentration of 1 ng/L. At higher concentrations, the importance of BC for the sorption process diminished to <20% at 1 mug/L and 0-1% at 1 mg/L. There were no significant relationships between BC sorption strength and the tested geochemical BC characteristics [the fraction of small (<38 mum) BC particles, the BC resistance to high-temperature oxidation, the fraction of biomass-derived BC, the native polycyclic aromatic hydrocarbon and total organic carbon contents]. Because of the limited variation in BC sorption strength with widely varying BC characteristics, the presented BC sorption coefficients may putatively be used as generic starting points for environmental modeling purposes.
834fgTimes Cited:90Cited References Count:48

The Remarkable Metrological History of Radiocarbon Dating [II] - Currie, L. A. (J Res Natl Inst Stand Technol, 2004)
This article traces the metrological history of radiocarbon, from the initial breakthrough devised by Libby, to minor (evolutionary) and major (revolutionary) advances that have brought (14)C measurement from a crude, bulk [8 g carbon] dating tool, to a refined probe for dating tiny amounts of precious artifacts, and for "molecular dating" at the 10 microg to 100 microg level. The metrological advances led to opportunities and surprises, such as the non-monotonic dendrochronological calibration curve and the "bomb effect," that gave rise to new multidisciplinary areas of application, ranging from archaeology and anthropology to cosmic ray physics to oceanography to apportionment of anthropogenic pollutants to the reconstruction of environmental history. Beyond the specific topic of natural (14)C, it is hoped that this account may serve as a metaphor for young scientists, illustrating that just when a scientific discipline may appear to be approaching maturity, unanticipated metrological advances in their own chosen fields, and unanticipated anthropogenic or natural chemical events in the environment, can spawn new areas of research having exciting theoretical and practical implications.
Currie, Lloyd Aeng2004/01/01 00:00J Res Natl Inst Stand Technol. 2004 Apr 1;109(2):185-217. doi: 10.6028/jres.109.013. Print 2004 Mar-Apr.

Sampling Mantle Heterogeneity through Oceanic Basalts: Isotopes and Trace Elements - Hofmann, A. W. (Treatise on Geochemistry, 2004)
id: 1525

Spatial variations in a condensed interval between estuarine and open-marine settings: Holocene Hudson River estuary and adjacent continental shelf - McHugh, C. M. G.; Pekar, S. F.; Christie-Blick, N.; Ryan, W. B. F.; Carbotte, S.; Bell, R. (Geology, 2004)
An interval of stratigraphic condensation extending for 300 km from the fluvially dominated Hudson River estuary to the adjacent continental shelf reveals stratal relationships within an unconformity-rellated depositional sequence that are commonly difficult to resolve in seismic reflection profiles and outcrop. High-resolution side-scan sonar and bathymetry, more than 100 sediment cores similar to2 m long, and radioisotope (C-14, Cs-137) age control show that much of the valley was filled by ca. 3 to 1 ka. The present rate of sediment accumulation averages 1 mm/yr, corresponding with a sea-level rise of similar to1.2 mm/yr relative to local bedrock. Condensation is manifested today by sedimentary bypass in most parts of the estuary and by the trapping of available sediment (1.2-5.6 x 10(5) t/yr [metric tons]) along narrow reaches and primarily in the vicinity of the estuarine turbidity maximum, a part of the estuary located upstream of the salinity intrusion similar to25 km from the mouth (3.0 x 10(5) t/yr). Shelf condensation is due to sediment starvation. The condensed interval merges updip with a nascent sequence boundary as the estuary reaches its final filling phase and downdip with the sequence boundary that developed at the Last Glacial Maximum. Delta progradation may take place as available shelf accommodation is filled, but such sediments are expected to be removed once sea level begins to fall. This sedimentation pattern, in which a condensed interval merges with different sequence boundaries, is consistent with the stratigraphic record of the Atlantic margin back to the Paleogene and may be typical of sediment-starved margins.
772lcTimes Cited:10Cited References Count:30

Stable carbon and nitrogen isotopic compositions of organic compound classes in high molecular weight dissolved organic matter from four U. S. estuaries - Wang, X. C.; Altabet, A. M.; Callahan, J.; Chen, R. F. (Geochimica et Cosmochimica Acta, 2004)
id: 515

Ventilation of the glacial deep Pacific Ocean - Broecker, W.; Barker, S.; Clark, E.; Hajdas, I.; Bonani, G.; Stott, L. (Science, 2004)
Measurements of the age difference between coexisting benthic and planktic foraminifera from western equatorial Pacific deep-sea cores suggest that during peak glacial time the radiocarbon age of water at 2-kilometers depth was no greater than that of today. These results make unlikely suggestions that a slowdown in deep-ocean ventilation was responsible for a sizable fraction of the increase of the ratio of carbon-14 (14C) to carbon in the atmosphere and surface ocean during glacial time. Comparison of 14C ages for coexisting wood and planktic foraminifera from the same site suggests that the atmosphere to surface ocean 14C to C ratio difference was not substantially different from today's.
Broecker, WallaceBarker, StephenClark, ElizabethHajdas, IrkaBonani, GeorgesStott, Lowelleng2004/11/13 09:00Science. 2004 Nov 12;306(5699):1169-72.

Western Long Island Sound: evidence from diatom studies of eutrophication and environmental change in the 19th centure - Cooper, S. R.; Thomas, E.; Varekamp, J. C.; Sangiorgio, F. (AERS fall meeting, 2004)
id: 736

1999 RV Melville Baja California cruise, on the preservation of laminated sediments along the western margin of North America - van Geen, A.; Zheng, Y.; Bernhard, J. M.; Cannariato, K. G.; Carriquiry, J.; Dean, E.; Eakins, B. W.; Ortiz, J. D.; Pike, J. (Paleoceanography, 2003)
id: 1102

Accumulation of biogenic and lithogenic material in the Pacific sector of the Southern Ocean during the past 40,000 years - Chase, Z.; Anderson, R. F.; Fleisher, M. Q.; Kubik, P. W. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2003)
The (230)Th-normalization technique was applied to surface sediments and down-core records from the Pacific sector of the Southern Ocean between 120degreesW and 170degreesW in order to reconstruct vertical rain rates, corrected for lateral redistribution of sediment. Preserved rain rates of opal, organic carbon and biogenic Ba all indicate that biological productivity south of the Antarctic Polar Front (APF) was much lower than today during the Last Glacial Maximum (LGM), probably in response to increased ice cover. However, by analogy with modern opal fluxes south of the ACC, we show that year-round ice cover is not a prerequisite for very low rates of opal accumulation. Available records from north of the APF indicate little to no change in opal export, in contrast to records from the Indian and Atlantic sectors, which show enhanced opal export north of the APF during the LGM. Glacial records from north of 66degreesS in the Pacific all show lithogenic fluxes that were greater than today, but significantly lower than lithogenic fluxes in the glacial Atlantic and Indian sectors. Together, these new records from the Pacific sector show that during the LGM the three basins of the Southern Ocean were significantly more differentiated than today. The observed inter-basin distribution of lithogenic fluxes and opal burial, and the presumed geographical distribution of increased dust input to the Southern Ocean during the LGM, are consistent with an Atlantic-Indian-Pacific gradient in the degree of iron-stimulated diatom productivity within the zone lying between the APF and the Subantarctic Front. Previous studies, which focused primarily on the Atlantic sector, may have overestimated the glacial increase in the strength of the biological pump in the Southern Ocean. (C) 2002 Elsevier Science Ltd. All rights reserved.
662agTimes Cited:82 Cited References Count:86
Keywords: antarctic circumpolar current; atmospheric co2; biological productivity; Deep-sea; interglacial changes; Last glacial maximum; marine-sediments; organic-carbon; pa-231/th-230 ratio; terrigenous sediment

Age determination, validation and growth of Grand Bank yellowtail flounder (Limanda ferruginea) - Dwyer, K. S.; Walsh, S. J.; Campana, S. E. (Ices Journal of Marine Science, 2003)
Yellowtail flounder (Limanda ferruginea) (Storer, 1839) on the Grand Bank off Newfoundland were traditionally aged using surface-read whole otoliths. Age determination of otoliths from recaptures of fish tagged in the early 1990s indicated that the traditional ageing technique was underestimating the ages of yellowtail flounder when compared with the time at liberty. Age comparisons between whole and thin-sectioned otoliths showed agreement in age readings up to 7 years; thereafter whole otoliths tended to give much lower ages than those estimated by thin sections. Length-frequency analysis of pelagic and demersal juveniles, captive rearing of juveniles and marginal increment analysis all corroborated age determination based on thin sections. Tag-recaptures and bomb radiocarbon assays validated age interpretations based on thin sections in young and old yellowtail flounder, respectively. Ages were validated up to 25 years for females and 21 years for males. However, because of increased narrowing of annuli in thin-sectioned otoliths from old fish, even thin sections may underestimate the true age of the fish. von Bertalanfly growth curve parameters (combined sexes) were L-infinity = 55.6 cm total length, K = 0.16 and t(0) = -0.003. These results challenge the conventional view that yellowtail flounder on the Grand Banks are a relatively fast growing, short-lived species. Crown Copyright (C) 2003 Published by Elsevier Ltd on behalf of International Council for the Exploration of the Sea. All rights reserved.
723jaTimes Cited:43Cited References Count:57

Analog for Holocene and future Climate? - McManus, J. F.; Oppo, D. W.; Cullen, J. L.; Healey, S. L. (Geophysical Monograph 137, Earth's Climate and Orbital Eccentricity: The Marine Isotope State 11 Questions, 2003)
id: 1166

Anthropogenically induced changes in sediment and biogenic silica fluxes in Chesapeake Bay - Colman, S. M.; Bratton, J. F. (Geology, 2003)
Sediment cores as long as 20 m, dated by C-14, Pb-210, and Cs-137 methods and pollen stratigraphy, provide a history of diatom productivity and sediment-accumulation rates in Chesapeake Bay. We calculated the flux of biogenic silica and total sediment for the past 1500 yr for two high-sedimentation-rate sites in the mesohaline section of the bay. The data show that biogenic silica flux to sediments, an index of diatom productivity in the bay, as well as its variability, were relatively low before European settlement of the Chesapeake Bay watershed. In the succeeding 300400 yr, the flux of biogenic silica has increased by a factor of 4 to 5. Biogenic silica fluxes still appear to be increasing, despite recent nutrient-reduction efforts. The increase in diatom-produced biogenic silica has been partly masked (in concentration terms) by a similar increase in total sediment flux. This history suggests the magnitude of anthropogenic disturbance of the estuary and indicates that significant changes had occurred long before the twentieth century.
632uhTimes Cited:47Cited References Count:35

Atlantic Ocean circulation during the Younger Dryas: Insights from a new Cd/Ca record from the western subtropical South Atlantic - Came, R. E.; Oppo, D. W.; Curry, W. B. (Paleoceanography, 2003)
[Benthic foraminiferal Cd/ Ca from an intermediate depth, western South Atlantic core documents the history of southward penetration of North Atlantic Intermediate Water ( NAIW). Cd seawater estimates ( Cd-W) for the last glacial are consistent with the production of NAIW and its export into the South Atlantic. At similar to 14.5 ka concurrently with the onset of the Bolling- Allerod to Younger Dryas cooling, the NAIW contribution to the South Atlantic began to decrease, marking the transition from a glacial circulation pattern to a Younger Dryas circulation. High Cd-W in both the deep North Atlantic and the intermediate South Atlantic imply reduced export of deep and intermediate water during the Younger Dryas and a significant decrease in northward oceanic heat transport. A modern circulation was achieved at similar to 9 ka, concurrently with the establishment of Holocene warmth in the North Atlantic region, further supporting a close linkage between deepwater variability and North Atlantic climate.
749rtTimes Cited:30Cited References Count:39

Calcium carbonate budget in the Atlantic Ocean based on water column inorganic carbon chemistry - Chung, S. N.; Lee, K.; Feely, R. A.; Sabine, C. L.; Millero, F. J.; Wanninkhof, R.; Bullister, J. L.; Key, R. M.; Peng, T. H. (Global Biogeochemical Cycles, 2003)
[1] Recent independent lines of evidence suggest that the dissolution of calcium carbonate (CaCO3) particles is substantial in the upper ocean above the calcite 100% saturation horizon. This shallow-water dissolution of carbonate particles is in contrast with the current paradigm of the conservative nature of pelagic CaCO3 at shallow water depths. Here we use more than 20,000 sets of carbon measurements in conjunction with CFC and C-14 data from the WOCE/JGOFS/OACES global CO2 survey to estimate in situ dissolution rates of CaCO3 in the Atlantic Ocean. A dissolution rate is estimated from changes in alkalinity as a parcel of water ages along an isopycnal surface. The in situ CaCO3 dissolution increases rapidly at the aragonite 100% saturation horizon. Estimated dissolution rates north of 40degreesN are generally higher than the rates to the south, which is partly attributable to the production of exported CaCO3 being higher in the North Atlantic than in the South Atlantic. As more CaCO3 particles move down the water column, more particles are available for in situ dissolution. The total water column CaCO3 dissolution rate in the Atlantic Ocean is determined on an annual basis by integrating estimated dissolution rates throughout the entire water column and correcting for alkalinity input of approximately 5.6 x 10(12) mol C yr(-1) from CaCO3-rich sediments. The resulting water column dissolution rate of CaCO3 for the Atlantic Ocean is approximately 11.1 x 10(12) mol C yr(-1). This corresponds to about 31% of a recent estimate (35.8 x 10(12) mol C yr(-1)) of net CaCO3 production by Lee [2001] for the same area. Our calculation using a large amount of high-quality water column alkalinity data provides the first basin-scale estimate of the CaCO3 budget for the Atlantic Ocean.
732egTimes Cited:44 Cited References Count:73
Keywords: alkalinity; anthropogenic co2; caco3 dissolution; calcium carbonate budget; chemical lysocline; Deep-sea; dioxide system; dissociation-constants; dissolution kinetics; dissolution of calcium carbonate; eastern north-atlantic; ocean carbon cycle; organic-carbon; pacific-ocean; saturation state of seawater

Emergence of Late Holocene sociopolitical complexity on Santa Rosa and San Miquel Islands - Kennett, D. J.; Conlee, C. A. (Catalist to Complexity: The Late Holocene Archaeology of the California Coast: Perspectives in California Archaeology, 2003)
id: 472

Eutrophication and carbon sources in Chesapeake Bay over the last 2700 yr: human impacts in context - Bratton, John F.; Colman, Steven M.; Seal, Robert R. (Geochimica et Cosmochimica Acta, 2003)
To compare natural variability and trends in a developed estuary with human-influenced patterns, stable isotope ratios (δ13C and δ15N) were measured in sediments from five piston cores collected in Chesapeake Bay. Mixing of terrestrial and algal carbon sources primarily controls patterns of δ13Corg profiles, so this proxy shows changes in estuary productivity and in delivery of terrestrial carbon to the bay. Analyses of δ15N show periods when oxygen depletion allowed intense denitrification and nutrient recycling to develop in the seasonally stratified water column, in addition to recycling taking place in surficial sediments. These conditions produced 15N-enriched (heavy) nitrogen in algal biomass, and ultimately in sediment. A pronounced increasing trend in δ15N of +4‰ started in about A.D. 1750 to 1800 at all core sites, indicating greater eutrophication in the bay and summer oxygen depletion since that time. The timing of the change correlates with the advent of widespread land clearing and tillage in the watershed, and associated increases in erosion and sedimentation. Isotope data show that the region has experienced up to 13 wet-dry cycles in the last 2700 yr. Relative sea-level rise and basin infilling have produced a net freshening trend overprinted with cyclic climatic variability. Isotope data also constrain the relative position of the spring productivity maximum in Chesapeake Bay and distinguish local anomalies from sustained changes impacting large regions of the bay. This approach to reconstructing environmental history should be generally applicable to studies of other estuaries and coastal embayments impacted by watershed development.
id: 541

Evolution of a habitable planet - Kasting, J. F.; Catling, D. (Annual Review of Astronomy and Astrophysics, 2003)
Giant planets have now been discovered around other stars, and it is only a matter of time until Earth-sized planets are detected. Whether any of these planets are suitable for life depends on their volatile abundances, especially water, and on their climates. Only planets within the liquid-water habitable zone (HZ) can support life on their surfaces and, thus, can be analyzed remotely to determine whether they are inhabited. Fortunately, current models predict that HZs are relatively wide around main-sequence stars not too different from our sun. This conclusion is based on studies of how our own planet has evolved over time. Earth's climate has remained conducive to life for the past 3.5 billion years or more, despite a large increase in solar luminosity, probably because of previous higher concentrations Of CO2 and/or CH4. Both these gases are involved in negative feedback loops that help to stabilize the climate. In addition to these topics, we also briefly discuss the rise of atmospheric O-2 and O-3, along with their possible significance as indicators of life on other planets.
742axTimes Cited:217Cited References Count:146

La colonisation et les fortifications de Rapa - Kennett, D. J.; Anderson, A. J.; Prebble, M.; Conte, E. (Bilan de la recherche archeologique en Polynesie francaise, 2003)
id: 471

Late-Holocene climate and ecosystem history from Chesapeake Bay sediment cores, USA - Willard, D. A.; Cronin, T. M.; Verardo, S. (Holocene, 2003)
Palaeoclimate records from late-Holocene sediments in Chesapeake Bay, the largest estuary in the USA, provide evidence that both decadal to centennial climate variability and European colonization had severe impacts on the watershed and estuary. Using pollen and dinoflagellate cysts as proxies for mid-Atlantic regional precipitation, estuarine salinity and dissolved oxygen (DO) during the last 2300 years, we identified four dry intervals, centred on AD 50 (P1/D1), AD 1000 (P2/D2), AD 1400 (P3) and AD 1600 (P4). Two centennial-scale events, P1/D1 and P2/D2, altered forest composition and led to increased salinity and DO levels in the estuary. Intervals P3 and P4 lasted several decades, leading to decreased production of pine pollen. Periods of dry mid-Atlantic climate correspond to 'megadroughts' identified from tree-ring records in the southeastern and central USA. The observed mid-Atlantic climate variability may be explained by changes in atmospheric circulation resulting in longer-term, perhaps amplified, intervals of meridional flow. After European colonization in the early seventeenth century, forest clearance for agriculture, timber and urbanization altered estuarine water quality, with dinoflagellate assemblages indicating reduced DO and increased turbidity.
650thTimes Cited:56Cited References Count:101

Late-Quaternary cold events recorded in the Southern Ocean sediments, Pacific Sector - Langone, L.; Capotondi, L.; Giglio, F.; Focaccia, P.; C, Morigi; Ravaioli, M. (Terra Antartica, 2003)
id: 1000

Palaeo-oceanography: Deepwater variability in the Holocene epoch - Oppo, D. W.; McManus, J. F.; Cullen, J. L. (Nature, 2003)
Oppo, Delia WMcManus, Jerry FCullen, James LengEngland2003/03/21 04:00Nature. 2003 Mar 20;422(6929):277.

The paleo environmental history of Long Island Sound, Abstract - Varekamp, J. C.; Thomas, E.; Buchholtz ten Brink, M. F.; Altabet, M.; Cooper, S. (Long Island Sound Lobster Research meeting, 2003)
id: 1178

A possible record of the Younger Dryas event in deep-sea sediments of the Southern Ocean (Pacific sector) - Morigi, C.; Capotondi, L.; Giglio, F.; Langone, L.; Brilli, M.; Turi, B.; Ravaioli, M. (Palaeogeography Palaeoclimatology Palaeoecology, 2003)
The oxygen isotope record combined with radiocarbon dating from two deep-sea cores collected along a transect between New Zealand and the Ross Sea are used to establish a reliable chronostratigraphy for the last 14 kyr. After an integrated geochemical and micropaleontological analysis in this timeframe we detected a cooling interval dated between 12.5 cal kyr BP and 11.4 cal kyr BP. The age control suggests that this event started 1.5 kyr after the onset of the Antarctic Cold Reversal previously observed in several Antarctic ice cores. We infer that the observed cool event corresponds to the Younger Dryas event defined in Northern Europe. This suggests that climate change recorded in this sector of the Southern Hemisphere still shows some synchronicity with Northern Hemisphere variations and that the decoupling of climate change between the two hemispheres likely occurred south of the Polar Front. (C) 2003 Elsevier B.V. All rights reserved.
723feTimes Cited:15Cited References Count:55

On the preservation of laminated sediments along the western margin of North America - van Geen, A.; Zheng, Y.; Bernhard, J. M.; Cannariato, K. G.; Carriquiry, J.; Dean, W. E.; Eakins, B. W.; Ortiz, J. D.; Pike, J. (Paleoceanography, 2003)
id: 1128

Quantitative estimates of time-averaging in terebratulidbrachiopod shell accumulations from a modern tropical shelf - Carroll, M.; Kowalewski, M.; Simoes, M. G.; Goodfriend, G. A. (Paleobiology, 2003)
Quantitative estimates of time-averaging in marine shellaccumulations available to date are limited primarily toaragonitic mollusk shells. We assessed time-averaging in Holoceneassemblages of calcitic brachiopod shells by direct dating ofindividual specimens of the terebratulid brachiopod Bouchardiarosea. The data were collected from exceptional (brachiopod-rich)shell assemblages, occurring surficially on a tropical mixedcarbonate-siliciclastic shelf (the Southeast Brazilian Bight, SWAtlantic), a setting that provides a good climatic andenvironmental analog for many Paleozoic brachiopod shell beds ofNorth America and Europe. A total of 82 individual brachiopodshells, collected from four shallow (5-25 m) nearshore (
id: 2231; Source type: scholarlyjournals; Object type: Article; Object type: Feature; CSAUnique: BONE5712965; AccNum: 5712965; DOI: 10.1043/0094-8373(2003)029(0381:QEOTIT)2.0.CO;2; ISSN: 0094-8373; Peer Reviewed: true

Sea-level changes and depositional environments in the Izmit Gulf, eastern Marmara Sea, during the late glacial-Holocene period - Cagatay, M. N.; Gorur, N.; Polonia, A.; Demirbag, E.; Sakinc, M.; Cormier, M. H.; Capotondi, L.; McHugh, C.; Emre, O.; Eris, K. (Marine Geology, 2003)
Offshore and onshore stratigraphic studies, together with high-resolution shallow seismic reflection profiling and multibeam bathymetric mapping, were carried out in the western and central part of the Izmit Gulf. These studies indicate that the Izmit Gulf was a lacustrine environment as part of the Marmara 'Lake' during the late glaciation and early deglaciation until similar to12 kyr BP, when the Marmara Basin was inundated by the Mediterranean waters. Correlation of C-14-dated onshore and offshore stratigraphic units in the Western Izmit Gulf indicates that generally coarse late glacial sediments overlie a marked erosional surface formed during the low water level of the Marmara 'Lake'. These coarse sediments are succeeded by 10.4-7 kyr BP old transgressive, and by late Holocene post-transgression mud units. The bathymetry and sub-bottom Chirp profiles clearly show that the paleoshoreline of the Gulf was located at -85 m, having been controlled by the bedrock sill depth of the Canakkale Strait. Another paleoshoreline observed at -65 m on the northern margin of the Western Izmit and Karamursel basins was probably formed during the Younger Dryas sea-level stillstand. The shelf areas during this time were colonized by bioherms, which were subsequently drowned and disappeared after a further rise of the sea level. The presence of a -65 in marine paleoshoreline in the Karamursel Basin indicates that the sill restricting this basin to the west was much deeper than its present -55 in level and was located further south. The Golcuk Basin, restricted by a -38 in sill to its west, was probably not flooded by marine waters until similar to9 kyr BP. (C) 2003 Published by Elsevier B.V.
749gpTimes Cited:52Cited References Count:30

Sedimentology and age control of late Quaternary New Jersey shelf deposits - Alexander, C.; Sommerfield, C.; Austin J.A, Jr.; Christensen, B.; Fulthorpe, C.; Goff, J.; Gulick, S.; Nordfjord, S.; Nielson, D.; Schock, S. (AGU Fall 2003 Meeting, 2003)
id: 636

Soil-productivity relationships and organic matter turnover in dry tropical forests of the Florida Keys - Ross, M. S.; Coultas, C. L.; Hsieh, Y. P. (Plant and Soil, 2003)
Soils and aboveground production in five types of upland forest in the Florida Keys were examined. Throughout the habitat gradient represented by these forest types, the soils were predominantly shallow and organic, forming in place directly on the limestone bedrock. However, the well-drained soils in the most productive broadleaved forests were deep enough to qualify as Histosols (Folists). Soils decreased in electrical conductivity and increased in nutrient content with increasing aboveground production. At 3-12 Mg ha(-1) yr(-1), production was within the range reported for dry tropical forests. Measured rates of decomposition were moderate or fast, and estimates of the organic C turnover of several soils based on their bomb radiocarbon signature were 100 years or less. In the face of these rapid turnover rates, we attribute the development of organic soils to the absence of mineral residues from weathering of the underlying limestone bedrock. Fast turnover of organic matter, and rapid and efficient cycling of nutrients are necessary to sustain the high production rates obtained on these shallow organic soils.
702ymTimes Cited:12Cited References Count:46

Suitability of glycerin-preserved otoliths for age validation using bomb radiocarbon - Campana, S. E.; Stanley, R. D.; Wischniowski, S. (Journal of Fish Biology, 2003)
The effect of glycerin storage on the bomb radiocarbon content of otoliths was determined experimentally. Storage in either pre- or post-bomb glycerin had no detectable effect on the bomb radiocarbon content of either pre- or post-bomb otoliths. Therefore bomb-dated age validation studies need not be restricted to freshly-collected samples or dry otoliths, implying that the large numbers of glycerin-archived otoliths around the world are suitable for age validation studies using bomb radiocarbon. (C) 2003 The Fisheries Society of the British Isles.
734gqTimes Cited:5Cited References Count:9

The 14C AMS system at the University of Georgia - Roberts, M. L.; Culp, R. A.; Dvoracek, D. K.; Hodgins, G. W. L.; Neary, M. P.; Noakes, J. E. (International Conference on Accelerator Mass Spectrometry, 2002)
id: 1684

A 4000-Year Lacustrine Record of Environmental Change in the Southern Maya Lowlands, Petén, Guatemala - Rosenmeier, Michael F.; Hodell, David A.; Brenner, Mark; Curtis, Jason H.; Guilderson, Thomas P. (Quaternary Research, 2002)
A 4000-yr sediment core record from Lake Salpetén, Guatemala, provides evidence for Maya-induced forest clearance and consequent soil erosion between ∼1700 cal yr B.C. and 850 cal yr A.D. Radiocarbon ages of wood, seeds, and charcoal support an age-depth model with average errors of ±110 cal yr. Relatively low carbonate δ18O values between 1300 and 400 cal yr B.C. coincide with pollen evidence for forest loss, consistent with increased surface and groundwater flow to the lake. Minimum δ18O values between 400 cal yr B.C. and 150 cal yr A.D. suggest a high lake level, as do 14C-dated aquatic gastropods as much as 7.5 m above the present lake stage. High lake levels resulted from reduced evaporation-to-precipitation ratios, increased hydrologic input caused by anthropogenic deforestation, or both. The Preclassic abandonment (150 A.D.) and Early Classic/Late Classic boundary (550 A.D.) are marked by relatively high δ18O values indicating reduced lake levels. Oxygen isotope composition increased further coincident with the Terminal Classic Maya demographic decline between 800 and 900 A.D. This period of high δ18O may have been caused by the greater aridity that has been documented in northern Yucatán lakes or by decreased hydrologic input to the lake as a consequence of forest recovery. Reduced soil erosion after 850 cal yr A.D. coincided with the Terminal Classic Maya demographic decline and permitted forest recovery and resumption of organic sedimentation.
id: 2106

Abundant brachiopods on a tropical, upwelling-influenced shelf (Southeast Brazilian Bight, South Atlantic - Kowalewski, M.; Simeos, M. G.; Carroll, M.; Rodland, D. L. (Palaios, 2002)
Rhynchonelliform brachiopods were diverse and often dominant benthos of tropical seas in the Paleozoic. In contrast, they are believed to be rare in open habitats of modern oceans, especially at low latitudes. This study documents numerous occurrences of rhynchonelliform brachiopods on a modern tropical shelf, particularly in areas influenced by upwelling. Extensive sampling of the outer shelf and coastal bays of the Southeast Brazilian Bight revealed dense populations of terebratulid brachiopods (>103 individuals / m2 of seafloor) between 24° and 26°S. On the outer shelf, brachiopods are more abundant than bivalves and gastropods combined. However, brachiopod diversity is low: only four species belonging to the genera Bouchardia, Terebratulina, Argyrotheca, and Platidia were identified among over 16000 examined specimens. Brachiopods occur preferentially on carbonate bottoms and include two substrate-related associations: Bouchardia (40–70% CaCO3 weight content) and Terebratulina-Argyrotheca (70–95% CaCO3). All four species display a broad bathymetric range that contrasts with a narrow depth tolerance postulated for many Paleozoic rhynchonelliforms. The most abundant populations occur in the depth range between 100 and 200 m, and coincide with zones of shelf-break upwelling, where relatively colder and nutrient-rich water masses of the South Atlantic Central Water are brought upward by cyclonic meanders of the South Brazil Current (a western boundary current that flows poleward along the coast of Brazil). This is consistent with previous biological and paleontological studies that suggest upwelling may play a role in sustaining brachiopod-dominated benthic associations. The presence of abundant brachiopods in the open habitats of the tropical shelf of the western South Atlantic contrasts with current understanding of their latitudinal distribution and points to major gaps in our knowledge of their present-day biogeography. The ecological importance of rhynchonelliform brachiopods in modern oceans and their role as producers of biogenic sedimentary particles may be underestimated.
id: 1416

The andesite aqueduct: prespectives on the evolution of intermediate magmatism in west-central (105-99 degrees W) Mexico - Carmichael, I. S. E. (Contributions to Mineralogy and Petrology, 2002)
id: 1588

Birth of the modern Chesapeake Bay estuary between 7.4 and 8.2 ka and implications for global sea-level rise - Bratton, John F.; Colman, Steven M.; Thieler, E. Robert; Seal, Robert R. (Geo-Marine Letters, 2002)
Two major pulses of sea-level rise are thought to have taken place since the last glacial maximum — meltwater pulses (mwp) 1A (12 cal ka) and 1B (9.5 cal ka). Between mwp 1B and about 6 cal ka, many of the complex coastal ecosystems which ring the world’s oceans began to form. Here we report data for rhenium, carbon isotopes, total organic carbon, and fossil oysters from Chesapeake Bay which span the transition from fresh to brackish water conditions in the bay in the mid-Holocene. These data constrain sea-level change and resulting environmental change in the bay. They indicate that the transition was rapid, and that it was produced by (1) a third pulse of rapid eustatic sea-level rise, or (2) a geometry of the prehistoric Chesapeake Bay basin which predisposed it to a nonlinear response to a steadily rising sea level. Similar nonlinear changes in vulnerable coastal environments are likely to take place in the future due to polar warming, regardless of the timing or rate of sea-level rise.
id: 540

Bomb dating and age determination of large pelagic sharks - Campana, S. E.; Natanson, L. J.; Myklevoll, S. (Canadian Journal of Fisheries and Aquatic Sciences, 2002)
Despite their notoriety and role as apex predators, the longevity of large pelagic sharks such as the porbeagle (Lamna nasus) and shortfin mako (Isurus oxyrinchus) is unknown. Vertebral growth bands provide an accurate indicator of age in young porbeagle, but age validation has never been reported for any large shark species past the age of sexual maturity. Here, we report the first application of bomb radiocarbon as an age validation method for long-lived sharks based on date-specific incorporation of radiocarbon into vertebral growth bands. Our results indicate that porbeagle vertebrae recorded and preserved a bomb radiocarbon pulse in growth bands formed during the 1960s. Through comparison of radiocarbon assays in young, known-age porbeagle collected in the 1960s with the corresponding growth bands in old porbeagle collected later, we confirm the validity of porbeagle vertebral growth band counts as accurate annual age indicators to an age of at least 26 years. The radiocarbon signatures of porbeagle vertebral growth bands appear to be temporally and metabolically stable and derived mainly from the radiocarbon content of their prey. Preliminary radiocarbon assays of shortfin mako vertebrae suggest that current methods for determining shortfin mako age are incorrect.
548ceTimes Cited:98Cited References Count:16

A Budget of Carbonate and Terrigenous Sediments, Hanalei Bay, Kauai, Hawaiian Islands - Calhoun, R. S.; Fletcher, C. H.; Harney, J. N. (Marine Geology, 2002)
The sediment budget of Hanalei Bay on the north shore of Kauai was calculated using sedimentological and geophysical methods. The calculations of the budget subsequently allowed an interpretation of the Holocene history of the bay. The bay sediments are easily separated into marine (carbonate) and terrigenous (siliciclastic) grains. Surficial sediments are dominated by carbonate grains (∼70%) of coralline algae, coral, and mollusc fragments as well as foraminifera, Halimeda, bryozoa, and echinoderm tests. However, siliciclastic grains (e.g. olivine, plagioclase, volcanic lithics) from the Hanalei River watershed draining shield volcanic highlands are the most common individual grain type (∼27%) and form a zone of high concentration from the mouth of the Hanalei River into the center of the bay. Flooding in the bay by the post-glacial sea-level rise began soon after 11.7 kyears. The resulting marine environment caused the net deposition of 45.5±1.5×106 m3 of sediment in the bay and approximately 33.7±11.2×106 m3 of sediment on the Hanalei coastal plain. The total volume of carbonate sediment stored in the bay and coastal plain is greater than the volume likely to have been produced exclusively within the bay during the same time. Calculations indicate that approximately 2490 m3 year−1 have been imported into the bay or coastal plain and deposited since 11,700 years ago. The majority of this sediment influx is likely delivered from the east by the strong tradewind-driven littoral currents that characterize Kauai's north shore. Net carbonate sediment deposition in Hanalei Bay peaked at a rate of 15,500 m3 year−1 between 5000 and 3000 years ago (when sea level may have been 2 m above present) diminishing to 3890 m3 year−1 from 1000 years ago to the present. This influx is likely to have played a significant role in the mid to late Holocene progradation of the Hanalei shoreline.
id: 105

Chemical and carbon isotopic evidence for the source and fate of dissolved organic matter in the northern Everglades - Wang, Y.; Hsieh, Y. P.; Landing, W. M.; Choi, Y. H.; Salters, V.; Campbell, D. (Biogeochemistry, 2002)
id: 616

Chemical composition and cycling of dissolved organic matter in the Mid-Atlantic Bight - Aluwihare, L. I.; Repeta, D. J.; Chen, R. F. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2002)
This study focuses on the chemical characterization of high molecular-weight dissolved organic matter (HMW DOM) isolated from the Middle Atlantic Bight in April 1994 and March 1996. Using proton nuclear magnetic resonance spectroscopy ((HNMR)-H-1) and monosaccharide analysis we compared both spatial and temporal variations in the chemical structure of HMW DOM across this region. Our analyses support the presence of at least two compositionally distinct components to HMW DOM. The major component is acyl polysaccharide (APS), a biopolymer rich in carbohydrates, acetate and lipid, accounting for between 50% and 80% of the total high molecular-weight dissolved organic carbon (HMW DOC) in surface samples. APS is most abundant in fully marine, surface-water samples, and is a product of autochthonous production. Organic matter with spectral properties characteristic of humic substances is the second major component of HMW DOM. Humic substances are most abundant (up to 49% of the total carbon) in samples collected from estuaries, near the coast, and in deep water, suggesting both marine and perhaps terrestrial sources. Radiocarbon analyses of neutral monosaccharides released by the hydrolysis of APS have similar and modern (average 71parts per thousand) Delta(14)C values. Radiocarbon data support our suggestion that these sugars occur as part of a common macromolecule, with an origin via recent biosynthesis. Preliminary radiocarbon data for total neutral monosaccharides isolated from APS at 300 and 750m show this fraction to be substantially enriched relative to total HMW DOC and DOC. The relatively enriched radiocarbon values of APS at depth suggest APS is rapidly transported into the deep ocean. (C) 2002 Elsevier Science Ltd. All rights reserved.
607kxTimes Cited:74Cited References Count:44

A Critical Evaluation of Interlaboratory Data on Total, Elemental, and Isotopic Carbon in the Carbonaceous Particle Reference Material, NIST SRM 1649a - Currie, L. A.; Benner, B. A., Jr.; Kessler, J. D.; Klinedinst, D. B.; Klouda, G. A.; Marolf, J. V.; Slater, J. F.; Wise, S. A.; Cachier, H.; Cary, R.; Chow, J. C.; Watson, J.; et al. (J Res Natl Inst Stand Technol, 2002)
Because of increased interest in the marine and atmospheric sciences in elemental carbon (EC), or black carbon (BC) or soot carbon (SC), and because of the difficulties in analyzing or even defining this pervasive component of particulate carbon, it has become quite important to have appropriate reference materials for intercomparison and quality control. The NIST "urban dust" Standard Reference Material((R)) SRM 1649a is useful in this respect, in part because it comprises a considerable array of inorganic and organic species, and because it exhibits a large degree of ((14)C) isotopic heterogeneity, with biomass carbon source contributions ranging from about 2 % (essentially fossil aliphatic fraction) to about 32 % (polar fraction). A primary purpose of this report is to provide documentation for the new isotopic and chemical particulate carbon data for the most recent (31 Jan. 2001) SRM 1649a Certificate of Analysis. Supporting this is a critical review of underlying international intercomparison data and methodologies, provided by 18 teams of analytical experts from 11 institutions. Key results of the intercomparison are: (1) a new, Certified Value for total carbon (TC) in SRM 1649a; (2) (14)C Reference Values for total carbon and a number of organic species, including for the first time 8 individual PAHs; and (3) elemental carbon (EC) Information Values derived from 13 analytical methods applied to this component. Results for elemental carbon, which comprised a special focus of the intercomparison, were quite diverse, reflecting the confounding of methodological-matrix artifacts, and methods that tended to probe more or less refractory regions of this universal, but ill-defined product of incomplete combustion. Availability of both chemical and (14)C speciation data for SRM 1649a holds great promise for improved analytical insight through comparative analysis (e.g., fossil/biomass partition in EC compared to PAH), and through application of the principle of isotopic mass balance.
Currie, L ABenner, B A JrKessler, J DKlinedinst, D BKlouda, G AMarolf, J VSlater, J FWise, S ACachier, HCary, RChow, J CWatson, JDruffel, E R MMasiello, C AEglinton, T IPearson, AReddy, C MGustafsson, OQuinn, J GHartmann, P CHedges, J IPrentice, K MKirchstetter, T WNovakow, TPuxbaum, HSchmid, Heng2002/01/01 00:00J Res Natl Inst Stand Technol. 2002 Jun 1;107(3):279-98. doi: 10.6028/jres.107.022. Print 2002 May-Jun.

Implications of environmental change for energy flow through natural systems: Freshwater wetlands and coastal zones - Chasar, L. (Florida State University, 2002)

Influence of Vegetation Change on Watershed Hydrology: Implications for Paleoclimatic Interpretation of Lacustrine d180 Records - Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H.; Martin, J. B.; Anselmetti, F. S.; Ariztegui, D.; Guilderson, T. P. (Journal of Paleolimnology, 2002)
id: 1386

Linking vertical advection and diet to juvenile salmon condition and parasite load: A study using 14C, 13C, and 15N - Casillas, E.; Rau, G. H.; al, et (Transactions, American Geophysical Union, 2002)
id: 1142

Oak, chestnut and fire: climatic and cultural controls of long-term forest dynamics in New England, USA - Foster, D. R.; Clayden, S.; Orwig, D. A.; Hall, B. (Journal of Biogeography, 2002)
Aim Despite decades of study we have limited insights into the nature of the pre-European landscape of the north-eastern USA and the forces and changes that shaped modern forest patterns. Information on such long-term forest dynamics would provide critical insights into the relationships among environmental change, land-use history and biotic responses and is greatly needed for conservation planning. To address these issues we used modern, historical, and palaeoecological approaches to reconstruct the 3500-year history of a New England upland region dominated by oak and (formerly) chestnut forests and to interpret the interactions among climate change, natural and human disturbance, and site factors in controlling vegetation patterns and dynamics at different spatial scales.Location The study focused on a broad upland ridge dominated by oak forests in the north-central Massachusetts town of New Salem. Detailed palaeoecological analyses were undertaken of wetland (Chamberlain Swamp) and lake (Lily Pond) basins in order to reconstruct local to regional scale vegetation dynamics, which were interpreted within the context of regional vegetation data from central Massachusetts.Methods Palaeoecological methods were used to reconstruct the vegetation, fire and land-use history of the local and subregional vegetation from the two basins and to place these in the context of regional information on vegetation and climate change based on other published data. Historical information including maps, archaeological and census data, and vegetation information were gathered for the landscape and areas surrounding the coring sites. Vegetation sampling in transects adjacent to the swamp coring area included tree cores for dendrochronological reconstructions.Results Stand, landscape and regional forest dynamics were most strongly driven by climate, notably an apparent cooling and increase in moisture availability c. 1500 yr BP, and European land-use activities commencing 260 yr BP. However, the abundance of oak and chestnut (fire-tolerant, sprouting species) and the distribution of hemlock (fire-intolerant) at a stand to landscape scale were also influenced by fire, which, in turn, varied with climate and human activity. Despite, or perhaps as a consequence of ongoing disturbance by fire and presumably windstorms in this hurricane-prone region, the pre-European period was marked by two 1000+ year periods of remarkably stable forest composition, separated by an abrupt compositional shift. In contrast, over the past 260 years the vegetation has changed rather continuously in response to human activity, producing stand, landscape and regional patterns that are novel as well as recent in origin.The results indicate that chestnut was a major component of some pre-European landscapes in New England, in part because of occasional fire, and that cultural and physical factors have interacted over millennia to control vegetation patterns and dynamics. Our analyses also suggest that the composition of low diversity forests can be remarkably stable over millennia. The range of ecological, cultural and management insights afforded by this study underscores the fundamental utility of very long-term research in science and policy development.
618gtTimes Cited:53Cited References Count:126

Ostracoda and paleoceanography - Cronin, T. M.; Boomer, I.; Dwyer, G. S.; Rodriguez-Lazaro, J. (American Geophysical Union Monograph - The Ostracoda: Applications in Quaternay Research, 2002)
id: 1473

Radiocarbon analysis, calibration and applications - Kromer, B.; Hughen, K. (Current methods in geochronology: Temporal resolution in geology, palaeontology, archaeoloty, and anthropology, 2002)
id: 326

Radiocarbon as a tool to apportion the sources of polycyclic aromatic hydrocarbons and black carbon in environmental samples - Reddy, C. M.; Pearson, A.; Xu, L.; McNichol, A. P.; Benner, B. A.; Wise, S. A.; Klouda, G. A.; Currie, L. A.; Eglinton, T. I. (Environmental Science & Technology, 2002)
To determine the relative inputs of polycyclic aromatic hydrocarbons (PAHs) and black carbon (BC) in environmental samples from the combustion of fossil fuels and biomass we have developed two independent analytical methods for determining the C-14 abundance of PAHs and BC. The 5730 yr half-life of C-14 makes it an ideal tracer for identifying combustion products derived from fossil fuels (C-14-free) versus those stemming from modern biomass (contemporary C-14). The C-14 abundance of PAHs in several environmental Standard Reference Materials was measured by accelerator mass spectrometry after extraction and then purification by high-performance liquid chromatography and preparative capillary gas chromatography. This method yields pure compounds that allow for a high degree of confidence in the C-14 results. The PAHs data were then used to compare and evaluate results from an operationally defined thermal oxidation method used to isolate a BC fraction. The C-14 compositions of PAHs and BC were very similar and suggest that the thermal oxidation method employed for isolating BC is robust and free from interferences by non-BC components. In addition, these data indicate that both the PAHs and the BC species derive mostly from fossil fuels and/or their combustion products.
541gfTimes Cited:133Cited References Count:59

Radiocarbon dating, chronologic framework, and changes in accumulation rates of Holocene estuarine sediments from Chesapeake Bay - Colman, S. M.; Baucom, P. C.; Bratton, J. F.; Cronin, T. M.; McGeehin, J. P.; Willard, D.; Zimmerman, A. R.; Vogt, P. R. (Quaternary Research, 2002)
Rapidly accumulating Holocene sediments in estuaries commonly are difficult to sample and date. In Chesapeake Bay, we obtained sediment cores as much as 20 m in length and used numerous radiocarbon ages measured by accelerator mass spectrometry methods to provide the first detailed chronologies of Holocene sediment accumulation in the bay. Carbon in these sediments is a complex mixture of materials from a variety of sources. Analyses of different components of the sediments show that total organic carbon ages are largely unreliable, because much of the carbon (including coal) has been transported to the bay from upstream sources and is older than sediments in which it was deposited. Mollusk shells (clams, oysters) and foraminifera appear to give reliable results, although reworking and burrowing are potential problems. Analyses of museum specimens collected alive before atmospheric nuclear testing suggest that the standard reservoir correction for marine samples is appropriate for middle to lower Chesapeake Bay. The biogenic carbonate radiocarbon ages are compatible with (210)Pb and (137)Cs data and pollen stratigraphy from the same sites.Post-settlement changes in sediment transport and accumulation is an important environmental issue in many estuaries, including the Chesapeake. Our data show that large variations in sediment mass accumulation rates occur among sites. At shallow water sites, local factors seem to control changes in accumulation rates with time. Our two relatively deep-water sites in the axial channel of the bay have different long-term average accumulation rates, but the history of sediment accumulation at these sites appears to reflect overall conditions in the bay. Mass accumulation rates at the two deep-water sites rapidly increased by about fourfold coincident with widespread land clearance for agriculture in the Chesapeake watershed.
517wpTimes Cited:57Cited References Count:33

Abrupt climate change and pre-Columbian cultural collapse - Brenner, M.; Hodell, D. A.; Curtis, J. H.; Rosenmeier, M.; Binford, M. W.; Abbott, M. B. (Interhemispheric Climate Linkages, 2001)
id: 1408

Amino acid composition and diagenesis in the shells of terebratulid brachiopod Bouchardia rosea (SW Atlantic) - Carroll, M.; Kowalewski, M.; Simeos, M. G.; Goodfriend, G. A. (Geological Society of America Abstracts with Programs, 2001)
id: 1417

Benthic remineralization and burial of biogenic SiO2, CaCO3, organic carbon, and detrital material in the Southern Ocean along a transect at 170oW - Sayles, F. L.; Martin, W. R.; Chase, Z.; Anderson, R. F. (Deep-Sea Res., 2001)
id: 276

Brachiopod shell taphonomy in subtropical siliciclastic environments: preliminary field results - Simoes, M. G.; Kowalewski, M.; Carroll, M.; Rodland, D. L.; Mello, L. H. C. (Reuniao Anal de Sociedade Brasileira de Paleontologia, Paleo-2001, 2001)
id: 281

Climate change in the circum-Caribbean (late Pleistocene-to-Present) and implications for regional biogeography - Curtis, J. H.; Brenner, M.; Hodell, D. A. (Biogeography of the West Indies: Patterns and Perspectives, 2nd Edition, 2001)
id: 265

Composition of hydrothermal vent microbial communities as revealed by analyses of signature lipids, stable carbon isotopes, and Aquificales cultures - Jahnke, Linda L.; Eder, Wolfgang; Huber, Robert; Hope, Janet M.; Hinrichs, Kai-Uwe; Hayes, John M.; Des Marais, David J.; Cady, Sherry L.; Summons, Roger E. (Applied and Environmental Microbiology, 2001)
id: 1783

Contribution of "old" carbon from natural marine hydrocarbon seeps to sedimentary and dissolved organic carbon pools in the Gulf of Mexico - Wang, X. C.; Chen, R. F.; Whelan, J.; Eglinton, L. (Geophysical Research Letters, 2001)
Natural radiocarbon (C-14) abundances and stable carbon isotope (delta C-13) compositions were measured for sediment total organic carbon (TOC), and total lipid fractions of sediments, bottom water, and hydrate-water collected from two hydrocarbon seepage sites in Green Canyon, Northern Gulf of Mexico to determine the contribution of "old" carbon from seeps to sediment TOC and dissolved organic carbon (DOC) pools. Our results indicate that 40-60% of the organic carbon preserved in the sediments and 30% of the DOC in the deep water above the seeps were seep-derived C-14-depleted organic carbon. This new evidence along with our previous studies suggest that natural marine hydrocarbon seepage could be a significant source contributing "old" carbon to the marine environment. Our findings suggest that the global importance and the long-term impact of this contribution to biogeochemical carbon cycling in the ocean need to be more thoroughly investigated.
467jmTimes Cited:20Cited References Count:25

Decadal record of climate variability spanning the last 700 years in the southern tropics of East Africa - Johnson, T. C.; Barry, S. L.; Chan, Y.; Wilkinson, P. (Geology, 2001)
id: 1477

Geometry, numerical models and revised slip rates for the Reelfoot blind thrust and truishear fault-propagation fold, New Medrid Seismic zone - Champion, J.; Mueller, K.; Tate, A.; Guccione, M. J. (Engineering Geology, 2001)
The geometry and structural relief of late Holocene sediments folded across the Reelfoot scarp are characterized with trench excavations, shallow borings, a digital elevation model (DEM) of topography and Reelfoot Lake (RL) bathymetry. Results suggest the scarp forms by heterogeneous shear in the forelimb of a fault-propagation fold. Seismic data and the accompanying structural analysis support the argument that the Reelfoot fault does not offset the surface, and that the Reelfoot scarp is a fold limb. Structural relief measured across the Reelfoot scarp is slightly higher than previous determinations and varies from 7 to 11 m along the western shoreline of RL. Numerical models based on trishear kinematics constrain growth of the Reelfoot monocline and indicate that the underlying Reelfoot thrust fault is steeply dipping. The shallowest portion of the central Reelfoot thrust segment dips 75° where the fault tip has propagated upward from 911 m to its current location 465 m beneath the surface. The models indicate that the shallowest section of the southern thrust segment in the Reelfoot thrust system dips even more steeply at 80° but has propagated upward only a few tens of meters to its present location 1016 m beneath the surface. The thrust is flatter at deeper levels based on the location of earthquake hypocenters. Strain across the Reelfoot scarp is partitioned into two or three separate fold scarps that collectively record a late Holocene fault slip rate of 3.9±0.1 mm/yr. The slip rate is based on 9 m of structural relief, the 2290±60 ybp age of folded sediment and a 75° dip for the fault. This implies a rate of horizontal contraction in the seismic zone of ∼1.0 mm/yr. This rate is strongly dependent on the dip of the thrust calculated by the structural analysis. The numerical models argue for reactivation of faults that previously offset Paleozoic strata.
id: 1381

Greenhouse warming and the impact of sea level rise on water resources on the coastal plain of the gulf coast, U.S.A - Carey, Anne (Annual PIs meeting of the DOE National Institute for Global Environmental Change Southeast Regional Center, 2001)
id: 344

The history of South American tropical precipitation for the past 25,000 years - Baker, P. A.; Seltzer, G. O.; Fritz, S. C.; Dunbar, R. B.; Grove, M. J.; Tapia, P. M.; Cross, S. L.; Rowe, H. D.; Broda, J. P. (Science, 2001)
Long sediment cores recovered from the deep portions of Lake Titicaca are used to reconstruct the precipitation history of tropical South America for the past 25,000 years. Lake Titicaca was a deep, fresh, and continuously overflowing lake during the last glacial stage, from before 25,000 to 15,000 calibrated years before the present (cal yr B.P.), signifying that during the last glacial maximum (LGM), the Altiplano of Bolivia and Peru and much of the Amazon basin were wetter than today. The LGM in this part of the Andes is dated at 21,000 cal yr B.P., approximately coincident with the global LGM. Maximum aridity and lowest lake level occurred in the early and middle Holocene (8000 to 5500 cal yr B.P.) during a time of low summer insolation. Today, rising levels of Lake Titicaca and wet conditions in Amazonia are correlated with anomalously cold sea-surface temperatures in the northern equatorial Atlantic. Likewise, during the deglacial and Holocene periods, there were several millennial-scale wet phases on the Altiplano and in Amazonia that coincided with anomalously cold periods in the equatorial and high-latitude North Atlantic, such as the Younger Dryas.
id: 369; Baker, P A Seltzer, G O Fritz, S C Dunbar, R B Grove, M J Tapia, P M Cross, S L Rowe, H D Broda, J P New York, N.Y. Science. 2001 Jan 26;291(5504):640-3.

Late quaternary climate and hydrology of tropical South America inferred from an isotopic and chemical model of Lake Titicaca, Bolivia and Peru - Cross, S. L.; Baker, P. A.; Seltzer, G. O.; Fritz, S. C.; Dunbar, R. B. (Quaternary Research, 2001)
A simple mass balance model provides insight into the hydrologic, isotopic, and chemical responses of Lake Titicaca to past climatic changes. Latest Pleistocene climate of the Altiplano is assumed to have been 20% wetter and 5 degreesC colder than today, based on previous modeling. Our simulation of lacustrine change since 15,000 cal yr B.P. is forced by these modeled climate changes. The latest Pleistocene Lake Titicaca was deep, fresh, and overflowing. The latest Pleistocene riverine discharge from the lake was about 8 times greater than the modern average, sufficient to allow the expansion of the great paleolake Tauca on the central Altiplano. The lake delta O-18 value averaged about -13 parts per thousand SMOW (the modern value is about -4.2 parts per thousand). The early Holocene decrease in precipitation caused Lake Titicaca to fall below its outlet and contributed to a rapid desiccation of paleolake Tauca. Continued evaporation caused the 100-m drop in lake level, but only a slight(1-2 parts per thousand) increase (relative to modern) in delta O-18 Of early Holocene lake waters. This Holocene lowstand level of nearly 100 m was most likely produced by a precipitation decrease, relative to modern, of about 40%, The lake was saline as recently as 2000 cal yr B.P. The timing of these hydrologic changes is in general agreement with calculated changes of insolation forcing of the South American summer monsoon, (C) 2001 University of Washington.
452lzTimes Cited:50Cited References Count:46

Metamorphic devolatilization of subducted oceanic metabasalts: implications for seismicity, arc magmatism and volatile recycling - Kerrick, D. M.; Connolly, J. A. D. (Earth and Planetary Science Letters, 2001)
Subducted oceanic metabasalts are believed to be a primary source of volatiles for are magmatism and fluid-induced seismicity. From phase equilibria computed for an average oceanic metabasalt we present a model for subduction zone devolatilization for pressures up to 6 GPa (similar to 180 km). Along high temperature geotherms complete dehydration occurs under forearcs, whereas dehydration does not occur along low temperature geotherms. For intermediate geotherms, major dehydration occurs under subarcs and provides a subjacent H2O source for are volcanism. Decarbonation is negligible along cold and intermediate geotherms and limited along high temperature geotherms. Because decarbonation is limited for all subducted carbonate-bearing lithologies, transfer of CO2 from subducted slabs to are magmas may be triggered by aqueous fluid infiltration. Metabasalt devolatilization could induce seismicity in forearcs (high temperature geotherms) and subarcs (intermediate geotherms); however, because of the lack of devolatilization, metabasalts would not be a fluid source for seismicity with low temperature geotherms. Along low temperature geotherms, limited devolatilization of subducted oceanic metabasalts and marine sediments in forearcs and subarcs provides a mechanism for return of volatiles to the deeper mantle. (C) 2001 Elsevier Science B.V. All rights reserved.
446xmTimes Cited:202Cited References Count:49

New records show pronounced changes in Arctic Ocean circulation and climate (cover article) - Darby, D.; Bischof, J.; Cutter, G.; de Vernal, A.; Hillaire-Marcel, C.; Dwyer, G.; McManus, J.; Polyak, L.; Osterman, L.; Poore, R. (EOS, Transactions, American Geophysical Union, 2001)
id: 332

Oceanic changes in the southern Pacific Ocean during the last deglaciation time, as recorded by planktic foraminifers and oxigen isotopes. --Extended abstract - Morigi, C.; Capotondi, L.; Giglio, F.; Langone, L.; Brilli, M.; Turi, B.; Ravaioli, M. (ANTOSTRAT Symposium on "The geologic record of the Antarctic ice sheet from drilling, coring and seismic studies", 2001)
id: 1428

Paleoceanographic changes in the Southern Ocean, during the last deglaciation time, as recorded by planktic foraminifers and oxygen isotopes--Poster - Morigi, C.; Capotondi, L.; Giglio, F.; Langone, L.; Turi, B.; Brilli, M.; Ravaioli, M. (ANTOSTRAT Symposium on "The geologic record of the Antarctic ice sheet from drilling, coring and seismic studies"--Poster, 2001)
id: 1424

Possible record of the yunger dryas event in sediments of the southern ocean (Pacific sector)--abstract - Morigi, C.; Capotondi, L.; Langone, L.; Giglio, F.; Ravaioli, M. (AUG, 2001)
id: 1427

Possible record of the yunger dryas event in sediments of the Southern Ocean (Pacific Sector)--Poster - Morigi, C.; Capotondi, L.; Langone, L.; Giglio, F.; Ravaioli, M. (AUG, 2001)
id: 1423

Proceedings of a Workshop on Alkenone-Based Paleoceanographic Indicators (Introduction to special issue of journal) - Eglinton, T. I.; Conte, M. H.; Eglinton, G.; Hayes, John M. (Geochem. Geophys. Geosyst., 2001)
id: 1739

Radiocarbon and stable carbon isotopic evidence for transport and transformation of DOC, DIC and CH4 in a northern Minnesota peatland - Chasar, L. S.; Chanton, J. P.; Glaser, P. H.; Siegel, D. I.; Rivers, J. S. (Global Biogeochemical Cycles, 2001)
id: 98

Time-Averaging in articulate brachiopod accumulations: A quantitative estimate of temporal resolution from a Holocene tropical shelf (Southern Brazil) - Carroll, M.; Kowalewski, M.; Simoes, M. G.; Goodfriend, G. A. (North American Paleontological Convention, Programs and Abstracts, 2001)
id: 1418

Tropical cooling and the isotopic composition of precipitation in general circulation model simullations of the ice age climate - Charles, C. D.; Rind, D.; Healy, R.; Webb, R. (Climate Dynamics, 2001)
id: 1716

Vegetation succession and carbon sequestration in a coastal wetland in northwestern Florida: evidence from carbon isotopes - Choi, Y.; Wang, Y.; Hsieh, Y. P.; Robinson, L. (Global Biogeochemical Cycles, 2001)
id: 267

Chesapeake Bay sedimentary record of Holocene climatic variability and human ecosystem disturbance - Cronin, T.; Willard, D.; Karlsen, A.; Ishman, S.; Verardo, S.; McGeehin, J.; Kerhin, R.; Holmes, C.; Colman, S. M.; Zimmerman, A. (Geology, 2000)
id: 184

Climate change in the northern American tropics since the last ice age: implications for environment and culture (Book Section) - Hodell, D. A.; Brenner, M.; Curtis, J. H. (Imperfect Balance: Landscape transformations in the Precolumbian Americas, 2000)
id: 198

Further evidence of abrupt Holocene drowning of the Black Sea shelf - Ballard, R. D.; Coleman, D. F.; Rosenberg, G. D. (Marine Geology, 2000)
A 1999 survey of the Black Sea continental shelf off the north central Turkish seaport of Sinop using a side-scan sonar, small remotely operated vehicles, and a series of dredge lowerings located, inspected and sampled an exposed high-energy paleoshoreline at a depth of 155 m. Radiocarbon dating of mollusk shells collected from this ancient beach revealed that the marine flooding of the Black Sea took place between 7460 and 6820 yr B.P. tall ages are reported in radiocarbon years, not calendar years, without correction for reservoir age or dendro-calibration) changing it from a lacustrine to marine environment. This relic surface remained in contact with the bottom waters of the Black Sea for a long period of time before being draped by a thin layer of sapropel mud. Wood samples recovered from this same location were very well preserved and yielded dates as old as 3580 yr B.P. (C) 2000 Elsevier Science B.V. All rights reserved.
380xeTimes Cited:71Cited References Count:8

Holocene and recent rates of sediment accumulation in southern Lake Michigan - Colman, S. M.; King, J. W.; Jones, G. A.; Reynolds, R. L.; Bothner, M. H. (Quaternary Science Reviews, 2000)
id: 183

Holocene climate in the western Great Lakes national parks and lakeshores: Implications for future climate change - Davis, M.; Douglas, C.; Calcote, R.; Cole, K. L.; Winkler, M. G.; Flakne, R. (Conservation Biology, 2000)
We reconstruct Holocene climate history (last 10,000 years) for each of the U.S. National Park Service units in the western Great Lakes region in order to evaluate their sensitivity to global warming. Annual precipitation, annual temperature, and July and January temperatures were reconstructed by comparing fossil pollen in lake sediment with pollen in surface samples, assuming that ancient climates were similar to modern climate near analogous surface samples. In the early Holocene, most of the parks experienced colder winters, warmer summers, and lower precipitation than today. An exception is Voyageurs National Park in northern Minnesota where, by 8000 years ago, January temperatures were higher than today. The combination of high mean annual temperature and lower precipitation at Voyageurs resulted in a dry period between 8000 and 5000 years ago, similar to the Prairie Period in regions to the south and west. A mid-Holocene warm-dry period also occurred at other northern and central parks but was much less strongly developed. In southern parks there was no clear evidence of a mid-Holocene warm-dry period. These differences suggest that global model predictions of a warm, dry climate in the northern Great Plains under doubled atmospheric CO2 may be more applicable to Voyageurs than to the other parks. The contrast in reconstructed temperatures at Voyageurs and Isle Royale indicates that the ameliorating effect of the Great Lakes on temperatures has been in effect throughout the Holocene and presumably will continue in the future, thus reducing the potential for species loss caused by future temperature extremes. Increased numbers of mesic trees at all of the parks in the late Holocene reflect increasing annual precipitation. This trend toward more mesic conditions began 6000 years ago in the south and 4000 years ago in the north and increased sharply in recent millennia at parks located today in lake-effect snow belts. This suggests that lake-effect snowfall is sensitive to continental-scale changes in climate and could be affected by future climate change. Plant and animal species sensitive to changes in the moisture regime could thus be endangered within the Great Lakes parks.
338uvTimes Cited:47Cited References Count:46

Lake Erie: The Impact of Mid-Holocene Flooding by Upper Great Lake Waters - Kempthorne, R. A.; Barrera, E.; Coakley, J. P.; Palmer, D. F. (EOS, Transactions, American Geophysical Union, 2000)
id: 248

A late Holocene pollen record from Torrey Pine State Reserve, California - Cole, K. L.; Wahl, Eugene (Quaternary Research, 2000)
id: 214

Lomas de ocupacion en los Llanos de Moxos (Book Section) - Erickson, Clark L. (La Arqueologia de las Tierras Bajas, 2000)
id: 180

Low-level (submicromole) environmental 14C metrology - Currie, L. A.; Kessler, J. D.; Marolf, J. V.; McNichol, A. P.; Stuart, D. R.; Donoghue, J. C. (Nucl. Instr. and Meth. in Phys. Res., 2000)
id: 1713

A New Estimate of the Holocene Lowstand Level of Lake Titicaca and Implications for Tropical Paleohydrology - Cross, S. C.; Baker, P. A.; Seltzer, G. O.; Fritz, S. C. (The Holocene, 2000)
id: 1339

Osmium isotopes demonstrate distal trnasport of contaminated sediments in Chesapeake Bay - Helz, G. R.; Adelson, J. M.; Miller, C. V.; Cornwell, J. C.; Hill, J. M.; Horan, M.; Walker, R. J. (Environmental Science Technology, 2000)
id: 1371

Paleoceanographic changes in the Southern Ocean (Pacific sector) during the last 14 Ka.--Poster - Morigi, C.; Capotondi, L.; Ravaioli, M.; Giglio, F.; Turi, B.; Brilli, M.; Langone, L. (Third International SO-JGOFS Symposium, 2000)
id: 1422

Particle mixing and sediment accumulation rates of Peconic Estuary sediments: A sediment accretion study in support of the Peconic Estuary Program (Report) - Cochran, J. K.; Hirschberg, D. J.; Amiel, D. (2000)
id: 1344

Postglacial and Late Holocene earthquakes on the Toe Jam strand of the Seattle fault, Bainbridge Island Washington - Nelson, A. R.; Johnson, S. Y.; Pezzopane, S. K.; Wells, R. E.; Kelsey, H. M.; Sherrod, B. L.; Koehler, R. D.; Bradley, L. A.; Bucknam, R. C.; LaPrade, W. T.; Cox, J. W.; Narwold, C. F. (Geological Society of America Abstracts with Programs, 2000)
id: 258

Quantitative estimates of time-averaging in articulate brachiopod accumulations from a Holocene tropical shelf (Southern Brazil) - Carroll, M.; Kowalewski, M.; Simoes, M. G.; Goodfriend, G. A. (Geological Society of America Abstracts with Programs, 2000)
id: 124

Quaternary Geology of Central Sheboygan County, Wisconsin, Thesis - Chapel, Dawn (University of Wisconsin, 2000)

Radiocarbon dates in China's Holocene Yangtze delta: record of sediment storage and reworking, not timing of deposition - Stanley, D. J.; Chen, Z. (Journal Coastal Res., 2000)
id: 230

Radiocarbon dating of Marion-Dufresne cores MD99-2204, 2207, and 2209, Chesapeake Bay - Colman, S. M.; Bratton, J. F.; Baucom, P. C. (Initial Report on IMAGES V Cruise of the Marion-Dufresne to the Chesapeake Bay June 20-22, 1999, 2000)
id: 1414

Un registro de 8,000 anos del paleoclima del noroeste de Yucatan, Mexico - Brenner, M.; Leyden, B. W.; Curtis, J. H.; Medina-Gonzalez, R. M.; Dahlin, B. H. (Revista de la Universidad Autonoma de Yucatan, 2000)
id: 264
Keywords: Ciencias de la atmósfera; Geología; México; Paleoclima; Península de Yucatán; Yucatán

A 0.5-million-year record of millennial-scale climate variability in the north atlantic - McManus, J. F.; Oppo, D. W.; Cullen, J. L. (Science, 1999)
Long, continuous, marine sediment records from the subpolar North Atlantic document the glacial modulation of regional climate instability throughout the past 0.5 million years. Whenever ice sheet size surpasses a critical threshold indicated by the benthic oxygen isotope (delta18O) value of 3.5 per mil during each of the past five glaciation cycles, indicators of iceberg discharge and sea-surface temperature display dramatically larger amplitudes of millennial-scale variability than when ice sheets are small. Sea-surface temperature oscillations of 1 degrees to 2 degreesC increase in size to approximately 4 degrees to 6 degreesC, and catastrophic iceberg discharges begin alternating repeatedly with brief quiescent intervals. The glacial growth associated with this amplification threshold represents a relatively small departure from the modern ice sheet configuration and sea level. Instability characterizes nearly all observed climate states, with the exception of a limited range of baseline conditions that includes the current Holocene interglacial.
McManusOppo Cullen eng 1999/02/12 03:03 Science. 1999 Feb 12;283(5404):971-5.

87Sr/86Sr, delta 18O evolution of Phanerozoic seawater - Veizer, Jan; Davin, Ala; Azmy, Karem; Bruckschen, Peter; Buhl, Dieter; Bruhn, Frank; Carden, Giles A. F.; Diener, Andreas; Ebneth, Stefan; Godderis, Yves; Jasper, Torsten; Korte, Christoph; et al. (Chemical Geology, 1999)
id: 1603

Assessment of a hard water dating problem in Wonder Lake, Denali National Park, Alaska - Child, J. C.; Werner, A. (Geographie Physique et Quatenaire, 1999)
id: 1383

Biogenic silica records from the BDP-93 drill site and adjacent areas of the Selenga Delta, Lake Baikal, Siberia - Colman, S. M.; Peck, J. A.; Hatton, J.; Karabanov, E. B.; King, J. W. (Journal of Paleolimnology, 1999)
id: 186

Carbon sequestration and vegetation succession in a coastal wetland in northwest Florida (abstract) - Choi, Y.; Wang, Y.; Hsieh, Y.; Robinson, L. (Spring meeting of American Geophysical Union, 1999)
id: 164

Climate change in the Lake Valencia Basin, Venezuela, approximately 12,600 yr BP to present - Curtis, J. H.; Brenner, M.; Hodell, D. A. (The Holocene, 1999)
id: 197

The distribution and carbon isotopic composition of dissolved organic matter in Florida Everglades (abstract) - Wang, Y.; Hsieh, Y. P.; Landing, W. M.; Salters, V.; Cooper, W.; Proctor, L. (The Sixth Symposium on Biogeochemistry of Wetlands, 1999)
id: 165

Evidence for Late Pleistocene-Holocene Intermediate-Water variability in the North Atlantic - McManus, J. F.; Oppo, D. W.; Curry, W.; Marchitto, T.; Cullen, J. L. (EOS, 1999)
id: 172

Fault slip rates in the modern new madrid seismic zone - Mueller, K.; Champion, J.; Guccione, M.; Kelson, K. (Science, 1999)
Structural and geomorphic analysis of late Holocene sediments in the Lake County region of the New Madrid seismic zone indicates that they are deformed by fault-related folding above the blind Reelfoot thrust fault. The widths of narrow kink bands exposed in trenches were used to model the Reelfoot scarp as a forelimb on a fault-bend fold; this, coupled with the age of folded sediment, yields a slip rate on the blind thrust of 6.1 +/- 0.7 mm/year for the past 2300 +/- 100 years. An alternative method used structural relief across the scarp and the estimated dip of the underlying blind thrust to calculate a slip rate of 4.8 +/- 0.2 mm/year. Geometric relations suggest that the right lateral slip rate on the New Madrid seismic zone is 1.8 to 2.0 mm/year.
MuellerChampion Guccione Kelson eng 1999/11/05 Science. 1999 Nov 5;286(5442):1135-8.

A geostrophic transport estimate for the Florida Current from the oxygen isotope composition of benthic foraminifera - Lynch-Stieglitz, J.; Curry, W. B.; Slowey, N. (Paleoceanography, 1999)
We present a new method for the quantitative reconstruction of upper ocean flows for during times in the past. For the warm (T>5 degrees C) surface ocean, density can be accurately reconstructed from calcite precipitated in equilibrium with seawater, as both of these properties increase with decreasing temperature and increasing salinity. Vertical density profiles can be reconstructed from the oxygen isotopic composition of benthic foraminifera. The net volume transport between two vertical density profiles can be calculated using the geostrophic method. Using benthic foraminifera from surface sediment samples from either side of the Florida Straits (Florida Keys and Little Bahama Bank), we reconstruct two vertical density profiles and calculate a volume transport of 32 Sv using this method. This agrees well with estimates from physical oceanographic methods of 30-32 Sv for the mean annual volume transport. We explore the sensitivity of this technique to various changes in the relationship between temperature and salinity as well as salinity and the oxygen isotopic composition of seawater.
198xcTimes Cited:81Cited References Count:45

Glacial modulation of rapid climate change during the last 0.5 million years - McManus, J. F.; Oppo, D. W.; Cullen, J. L. (PAGES newsletter, 1999)
id: 168

Holocene Environmental changes in the Lake Erie Basis - Kepthorne, R. A.; Barrera, E.; Coakley, J. P.; Tevesz, M. J. S.; Miller, B. B. (International Association for Great Lakes Research Program and Abstract, 1999)
id: 249

Interdisciplinary environmental project probes Chesapeake Bay down to the core - Cronin, T.; Colman, S. M.; Willard, D.; Kerhin, R.; Holmes, C.; Karlsen, A.; Ishman, S.; Bratton, J. (EOS, 1999)
id: 185

Isotopic and molecular fractionation in combustion; three routes to molecular marker validation, including direct molecular 'dating' (GC/AMS) - Currie, L. A.; Klouda, G. A.; Benner, B. A.; Garrity, K.; Eglinton, T. I. (Atmospheric Environment, 1999)
The identification of unique isotopic, elemental, and molecular markers for sources of combustion aerosol has growing practical importance because of the potential effects of fine particle aerosol on health, visibility and global climate. It is urgent, therefore, that substantial efforts be directed toward the validation of assumptions involving the use of such tracers for source apportionment. We describe here three independent routes toward carbonaceous aerosol molecular marker identification and validation: (1) tracer regression and multivariate statistical techniques applied to field measurements of mixed source, carbonaceous aerosols; (2) a new development in aerosol (14)C metrology: direct, pure compound accelerator mass spectrometry (AMS) by off-line GC/AMS ('molecular dating'); and (3) direct observation of isotopic and molecular source emissions during controlled laboratory combustion of specific fuels. Findings from the combined studies include. independent support for benzo(ghi)perylene as a motor vehicle tracer from the first (statistical) and second (direct 'dating') studies; a new indication, from the third (controlled combustion) study, of a relation between (13)C isotopic fractionation and PAH molecular fractionation, also linked with fuel and stage of combustion; and quantitative data showing the influence of both fuel type and combustion conditions on the yields of such species as elemental carbon and PAH, reinforcing the importance of exercising caution when applying presumed conservative elemental or organic tracers to fossil or biomass burning field data as in the first study. Published by Elsevier Science Ltd.
208duTimes Cited:38Cited References Count:31

Linking the 10Be continental record of Lake Baikal to marine and ice archives for the last 50 ka: Implication for the global dust-aerosol input - Aldahan, A.; Possnert, G.; Peck, J.; King, J.; Colman, S. (Geophysical Research Letters, 1999)
We present here a 10Be profile from the continental sediments of Lake Baikal (the world's largest fresh water lake), which, for the first time, shows the ≈ 40 ka 10Be enhancement and a pattern that strongly matches those from the marine and ice records for the last 50 ka. This finding provides a new horizon for global and regional correlation of continental archives. Additionally, our VADM-predicted 10Be production confirms and further strengthens a common global cause (geomagnetic field intensity) for the change in atmospheric 10Be over the last 50 ka. We also show that most of the 10Be inventory to the lake has been provided by riverine input, but with a significant addition from direct precipitation and dust-aerosol fallout. We estimate a higher dust-aerosol contribution of 10Be during the Holocene and interstadial stage 3 (22–50 ka) as compared with the glacial period (12–22 ka).
id: 1353

Measured and predicted sediment yield from a subtropical, heavy rainfall, steep-sided river basin: Hanalei, Kauai, Hawaiian Islands - Calhoun, R. S.; Fletcher, C. H. (Geomorphology, 1999)
To determine the sediment yield of the 54.4 km(2) Hanalei River basin, we employ three methods: (1) the Universal Soil Loss Equation (USLE), which uses natural characteristics of the basin such as the amount of rain, slope steepness and length values, and soil types to predict sediment erosion in a basin; (2) the thickness and calibrated radiocarbon age of fluvial deposits cored from the coastal plain; and (3) field measurements of suspended sediment in the river. Method 1 (USLE) provides a model prediction of sediment yield that we test with observational data of methods 2 and 3. Several curves, including one by the US Soil Conservation Service, predict a sediment delivery ratio (measured sediment yield: gross erosion) between approximately 15% and 50%. With 5260 +/- 2210 Mg (metric tons) yr(-1) of suspended sediment in the Hanalei River and 2300 +/- 700 Mg yr(-1) deposited on the coastal plain, however, the delivery of sediment in the Hanalei basin ranged between 45% and 101% of the maximum predicted USLE value (88 +/- 103 Mg km(-2) yr(-1)). This higher than predicted yield may be the result of mass movement. We are not able to differentiate, however, between erosion and mass movement as the principle agent of denudation. Our measurements indicate a total sediment yield of 140 +/- 55 Mg km(-2) yr(-1) for the Hanalei Valley. (C) 1999 Elsevier Science B.V. All rights reserved.
267flTimes Cited:14Cited References Count:37

Millennial-scale climate changes in ventilation of the thermocline, intermediate and deep waters of the glacial North Atlantic - Curry, W. B.; Marchitto, T. M.; McManus, J. F.; Oppo, D. W.; L, Laarkamp K. (Geophysical Monograph series, 1999)
id: 207

The North Atlantic's 1-2 kyr climate rhythm: Relation to Heinrich events, Dansgaard/Oeschger cycles and the Little Ice Age (Book Section) - Bond, G. C.; Showers, W.; Elliot, M.; Evans, M.; Lotti, R.; Hajdas, I.; Bonani, G.; Johnson, S. (Mechanisms of global climate change at mellennial time scales, 1999)
id: 216

The overturning circulation of the glacial Atlantic: A view from the top - Lynch-Stieglitz, J.; Curry, W. B.; Slowey, N.; Schmidt, G. A. (Reconstructing Ocean History: A Window into the Future, 1999)
id: 1364

The overturning circulation of the glacial Atlantic: A view from the top - Lynch-Stieglitz, J.; Curry, W. B.; Slowey, N. C. (Sixth International Conference on Paleoceanography, 1999)
id: 1337

Paleoceanographic changes in the Southern Ocean (Pacific Sector) during the last 14 ka.- -Abstract - Morigo, C.; Capotondi, L.; Ravaioli, M.; Giglio, F.; Turi, B.; Brilli, M.; Langone, L. (Third International SO-JGOFS Symposium, 1999)
id: 1426

Paleoclimate of Southwestern China for the past 50,000 yr inferred from lake sediment records - Hodell, D. A.; Brenner, M.; Kanfoush, S. L.; Curtis, J. H.; Stoner, J. S.; Song, X. L.; Yuan, W.; Whitmore, T. J. (Quaternary Research, 1999)
Long sediment cores (12.5 and 13.5 m) from two lakes in Yunnan Province were used to infer the paleoclimate of southwest China over the past 50,000 yr, During the Holocene and marine isotope stage (MIS 3), bio-induced carbonate precipitation and organic matter (OM) production was high, suggesting warm temperatures and high primary productivity. In contrast, sediment inorganic carbon (IC) and organic carbon (OC) concentrations were low in last glacial deposits from 38,000 to 12,000 cal yr B.P., indicating cool temperatures and low productivity. The 50,000-yr record has alternating peaks of carbonate and coarse-grain (>38 mu m) quartz that reflect warm, moist interglacial or interstadial conditions alternating with cold, dry glacial or stadial conditions, respectively. Spectral analysis of the carbonate and quartz signals reveals power concentrated at periods of 7200 and 8900 cal yr, respectively, that may reflect a nonlinear climate response to precessional forcing at a time of reduced eccentricity modulation (McIntyre and Molfino, 1996). Oxygen isotope values of calcite from Yunnan lake cores indicate the summer monsoon was weak during the last glaciation from 50,000 to 12,000 cal yr B.P. The summer monsoon intensified between 12,000 and 8000 cal yr B.P., but weakened gradually in response to insolation forcing during the mid-to-late Holocene. Our results support the Overpeck ef al. (1996) model that posits a weak summer monsoon during the last glaciation that responded nonlinearly to insolation forcing when its intensity was affected by Eurasian snow cover and ice-sheet extent. The summer monsoon intensified and responded linearly to seasonal insolation forcing in the Holocene when ice volume diminished. (C) 1999 University of Washington.
255ltTimes Cited:85Cited References Count:58

Paleoenvironments of Capitol Reef National Park reconstructed from fossil packrate middens - Cole, K. L.; Murray, L. K. (4th biennial Conference on Research on the Colorado Plateau, 1999)
id: 1369

Peat accumulation and succession following permafrost thaw in the boreal peatlands of Manitoba, Canada - Camill, P. (Ecoscience, 1999)
Permafrost thaw in boreal peatlands may be widespread as climate warms over the next century. Thaw will lead to dramatic changes in vegetation, and an understanding of the patterns and rates of succession following thaw is important for assessing future ecosystem changes, such as carbon accumulation and the likelihood of permafrost formation during climate warming. This paper describes the autogenic processes of peat accumulation and succession from recently thawed, aquatic Sphagnum communities to lawn and hummock Sphagnum communities favorable for permafrost formation. Peat cores were used to construct bulk density profiles in aquatic, lawn, and hummock habitats. Soil bulk density increased over time from the edges to the centers of thawed bogs. These changes corresponded to changes from aquatic to lawn/hummock communities. Macrofossils from Pb-210-dated peat cores were used to document historical changes to hummock communities. Succession to hummock communities capable of forming permafrost was less than 80 years. Picea mariana seedlings colonized emergent Sphagnum hummocks in collapse scars, which may lead to permafrost formation. However, permafrost formation in today's discontinuous permafrost landscape is unlikely during future climate warming because of limited tree establishment and shifting mean annual temperature isotherms.
299bzTimes Cited:22Cited References Count:55

Planktic foraminifera and oxygen isotope as proxies for paleoceanographic reconstruction in the Southern Ocean during the last deglacial time--Abstract - Morigi, C.; Capotondi, L.; Ravaioli, M.; Giglio, F.; Turi, B.; Brilli, M.; Frignani, M.; Langone, L. (Convegno Glaciologia e Paleoclima, 1999)
id: 1425

Spatial distribution of carbon and oxygen isotopes in laterally extensive carbonate-cemented layers: Implications for mode of growth and subsurface identification - Klein, J. S.; Mozley, P.; Campbell, A.; Cole, R. (Journal of Sedimentary Research, 1999)
Carbonate concretions and laterally extensive cemented layers are common features in the Prairie Canyon Member of the Mancos Shale at its type locality in western Colorado. Stable-isotope and petrographic data were obtained from these cemented zones in an attempt to determine: (1) how the cemented layers form, (2) whether or not they can be chemically correlated, and (3) if it is possible to differentiate them from concretions in the subsurface. The cement in both the layers and concretions consists of ferroan dolomite and lesser amounts of stoichiometric dolomite and ankerite. Samples for stable-isotope analysis were drilled from 10 grids, with a typical grid spacing of 10 cm x 10 cm, Gridded samples were obtained from two continuous cemented layers at several locations along the layers (2.3 m to 1.5 km apart on the same layer), and from isolated and stratabound concretions,Taken together, all the cements (regardless of spatial position) show a remarkably linear correlation (R-2 = 0.98) between delta(13)C and delta(18)O, Systematic center-to-edge decreases in both delta(13)C and delta(18)O occur in each of the cemented zones and are persistent over lateral intervals of at least 1.5 km, The cores of the cemented zones have positive delta(13)C values (up to > 10 parts per thousand PDB), which result from incorporation of C-13-enriched carbon during methanogenesis. The edges of the cemented zones have negative delta(13)C values (down to < -9 parts per thousand PDB), which suggests incorporation of C-13-depleted carbon from thermocatalytic decarboxylation reactions. Oxygen isotope paleothermometry indicates that precipitation may have started at moderate temperatures (similar to 25 degrees C) and ended at temperatures as high as 92 degrees C,The spatial distribution of the isotopic data in the cemented layers can be explained as resulting from the coalescence of stratabound concretions, followed by growth above and below the coalesced concretions. Such growth may have occurred in a complex: manner, in which early cements precipitated throughout the thickness of the layer but were more abundant in the core zone. Given the lateral persistence of the pattern of isotopic variation in the cemented layers, geochemical correlation of the layers may be possible in the subsurface. In addition, because laterally persistent cemented layers in the Prairie Canyon Member exhibit patterns of isotopic variation different from concretions (layers have a more asymmetrical vertical distribution), it should be possible to distinguish between the two styles of cementation from subsurface core data alone.
A157gxTimes Cited:36Cited References Count:39

The speciation and sources of dissolved phosphorus in the Everglades (Report) - Copper, W.; Hsieh, Y. P.; Landing, W. M.; Proctor, L.; Salters, V.; Wang, Y. (1999)
id: 1348

Terminal Proterozoic Mid-Shelf Benthic Microbial Mats in the Centralian Supervasin and their Environmental Significance - Logan, Graham A.; Calver, Clive R.; Gorjan, Paul; Summons, Roger E.; Hayes, John M.; Walter, Malcolm R. (Geochimica et Cosmochimica Acta, 1999)
id: 1734

Variability in shallow- and intermediate-water hydrography during the last climate cycle of the Quaternary - McManus, J. F.; Healey, S. L.; Oppo, D. W.; Curry, W. B. (EOS, 1999)
id: 170

Weaker Gulf Stream in the Florida straits during the last glacial maximum - Lynch-Stieglitz, J.; Curry, W. B.; Slowey, N. (Nature, 1999)
As it passes through the Florida Straits, the Gulf Stream consists of two main components: the western boundary flow of the wind-driven subtropical gyre and the northward-flowing surface and intermediate waters which are part of the 'global conveyor belt' compensating for the deep water that is exported from the North Atlantic Ocean(1), The mean flow through the Straits is largely in geostrophic balance and is thus reflected in the contrast in seawater density across the Straits(2). Here we use oxygen-isotope ratios of benthic foraminifera which lived along the ocean margins on the boundaries of the Florida Current during the Last Glacial Maximum to determine the density structure in the water and thereby reconstruct transport through the Straits using the geostrophic method-a technique which has been used successfully for estimating present-day flow(3). Our data suggest that during the Last Glacial Maximum, the density contrast across the Florida Straits was reduced, with the geostrophic flow, referenced to the bottom of the channel, at only about two-thirds of the modern value. If the wind-driven western boundary flow was not lower during the Last Glacial Maximum than today, these results indicate a significantly weaker conveyor-belt component of the Gulf Stream compared to present-day values. Whereas previous studies based on tracers suggested that deep waters of North Atlantic origin were not widespread during glacial times, indicating either a relatively weak or a shallow overturning cell, our results provide evidence that the overturning cell was indeed weaker during glacial times.
264pcTimes Cited:122Cited References Count:31

A 25,000-year tropical climate history from bolivian ice cores - Thompson, L. G.; Davis, M. E.; Mosley-Thompson, E.; Sowers, T. A.; Henderson, K. A.; Zagorodnov, V. S.; Lin, P.; Mikhalenko, V. N.; Campen, R. K.; Bolzan, J. F.; Cole-Dai, J.; Francou, B. (Science, 1998)
Ice cores that were recovered from the summit of Sajama mountain in Bolivia provide carbon-14-dated tropical records and extend to the Late Glacial Stage (LGS). Oxygen isotopic ratios of the ice decreased 5.4 per mil between the early Holocene and the Last Glacial Maximum, which is consistent with values from other ice cores. The abrupt onset and termination of a Younger Dryas-type event suggest atmospheric processes as the probable drivers. Regional accumulation increased during the LGS, during deglaciation, and over the past 3000 years, which is concurrent with higher water levels in regional paleolakes. Unlike polar cores, Sajama glacial ice contains eight times less dust than the Holocene ice, which reflects wetter conditions and extensive snow cover.
ThompsonDavis Mosley-Thompson Sowers Henderson Zagorodnov Lin Mikhalenko Campen Bolzan Cole-Dai Francou eng 1998/12/04 03:02 Science. 1998 Dec 4;282(5395):1858-64.

Controls of chemical and isotopic composition of Lake water, Peten, Guatemala and implications for Holocene climatic variability in Central America. Abstracts with Programs - Martin, J. B.; Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H. (Geological Society of America Annual Meeting, 1998)
id: 140

Early to middle Holocene climatic variability in Central America: evidence from lacustrine sediments in the Peten, Guatemala - Rosenmeier, M. F.; Hodel, D. A.; Martin, J. B.; Brenner, M.; Curtis, J. H. (EOS: Transactions American Geophysical Union, 1998)
id: 1209

Late Holocene climatic variability in Central America: evidence from lacustrine sediments in the Peten, Guatemala and implications for Maya cultural evolution; Procedings of the PEP 1 - Rosenmeier, M. F.; Hodell, D. A.; Martin, J. B.; Brenner, M.; Curtis, J. H. (PEP 1 (Pole-Equator-Pole, Paleoclimate of the Americas), 1998)
id: 141

Late Pleistocene Mammuthus primigenious from coastal mMaine - Hoyle, B. G.; Fisher, D. C.; Dorion, C. C.; Churchill, L. L.; W, Borns H., Jr.; Nelson, R. E. (33rd annual meeting, Geological Society of America, Northeastern Section, 1998)
id: 21

Millennial-scale changes in North Atlantic circulation since the last glaciation - Marchitto, T. M.; Curry, W. B.; Oppo, D. W. (Nature, 1998)
Ocean circulation is closely linked to climate change on glacial-interglacial and shorter timescales. Extensive reorganizations in the circulation of deep and intermediate-depth waters in the Atlantic Ocean have been hypothesized for both the last glaciation(1-6) and the subsequent Younger Dryas cold interval(3,6-10), but there has been little palaeoceanographic study of the subtropical gyres(11-13). These gyres are the dominant oceanic features of wind-driven circulation, and as such they reflect changes in climate and are a significant control on nutrient cycling and, possible, atmospheric CO2 concentrations. Here we present Cd/Ca ratios in the shells of benthic foraminifera from the Bahama banks that confirm previous suggestions(11,12) that nutrient concentrations in the North Atlantic subtropical gyre were much lower during the Last Glacial Maximum than they are today (up to 50% lower according to our data). These contrasting nutrient burdens imply much shorter residence times for waters within the thermocline of the Last Glacial Maximum. Below the glacial thermocline, nutrient concentrations were reduced owing to the presence of Glacial North Atlantic Intermediate Water. A high-resolution Cd/Ca record from an intermediate depth indicates decreased nutrient concentrations during the Younger Dryas interval as well, mirroring opposite changes at a nearby deep site(3,9). Together, these observations suggest that the formation of deep and intermediate waters-North Atlantic Deep Water and Glacial North Atlantic Intermediate Water, respectively-wax and wane alternately on both orbital and millennial timescales.
Zt988Times Cited:106Cited References Count:30

A multi-proxy study of Holocene environmental change in the Maya lowlands of Peten, Guatemala - Curtis, J. H.; Brenner, M.; Hodell, D. A.; Balser, R. A.; Islebe, G. A.; Hooghiemstra, H. (Journal of Paleolimnology, 1998)
We used multiple variables in a sediment core from Lake Peten-Itza, Peten, Guatemala, to infer Holocene climate change and human influence on the regional environment. Multiple proxies including pollen, stable isotope geochemistry, elemental composition, and magnetic susceptibility in samples from the same core allow differentiation of natural versus anthropogenic environmental changes. Core chronology is based on AMS (14)C measurement of terrestrial wood and charcoal and thus avoids the vagaries of hard-water-lake error. During the earliest Holocene, prior to similar to 9000 (14)C yr BP, the coring site was not covered by water and all proxies suggest that climatic conditions were relatively dry. Water covered the coring site by similar to 9000 (14)C yr BP, coinciding with filling of other lakes in Peten and farther north on the Yucatan Peninsula. During the early Holocene (similar to 9000 to similar to 6800 (14)C yr BP), pollen data suggest moist conditions, but high delta(18)O values are indicative of relatively high E/P. This apparent discrepancy may be due to a greater fractional loss of the lake's water budget to evaporation during the early stages of lake filling. Nonetheless, conditions were moist enough to support semi-deciduous lowland forest. Decrease in delta(18)O values and associated change in ostracod species at similar to 6800 (14)C yr BP suggest a transition to even moister conditions. Decline in lowland forest taxa beginning similar to 5780 (14)C yr BP may indicate early human disturbance. By similar to 2800 (14)C yr BP, Maya impact on the environment is documented by accelerated forest clearance and associated soil erosion. Multiple proxies indicate forest recovery and soil stabilization beginning similar to 1100 to 1000 (14)C yr BP, following the collapse of Classic Maya civilization.
Zj856Times Cited:92Cited References Count:96

A new model for Proterozoic ocean chemistry - Canfield, D. E. (Nature, 1998)
There was a significant oxidation of the Earth's surface around 2 billion years ago (2 Gyr)(1-4). Direct evidence for this oxidation comes, mostly, from geological records of the redox-sensitive elements Fe and U reflecting the conditions prevailing during weathering(1-3). The oxidation event was probably driven by an increased input of oxygen to the atmosphere arising from an increased sedimentary burial of organic matter between 2.3 and 2.0 Gyr(5). This episode was postdated by the final large precipitation of banded iron formations around 1.8 Gyr(1,2). It is generally believed that banded iron formations precipitated from an ocean whose bottom waters contained significant concentrations of dissolved ferrous iron, and that this sedimentation process terminated when aerobic bottom waters developed, oxidizing the iron and thus removing it from solution(1,2). In contrast, I argue here that anoxic bottom waters probably persisted until well after the deposition of banded iron formations ceased; I also propose that sulphide, rather than oxygen, was responsible for removing iron from deep ocean water. The sulphur-isotope record supports this hypothesis as it indicates increasing concentrations of oceanic sulphate, starting around 2.3 Gyr(6), leading to increasing rates of sulphide production by sulphate reduction. The increase in sulphide production became sufficient, around 1.8 Gyr,to precipitate the total flux of iron into the oceans. I suggest that aerobic deep-ocean waters did not develop until the Neoproterozoic era (1.0 to similar to 0.54 Gyr), in association with a second large oxidation of the Earth's surface. This new model is consistent with the emerging view of Precambrian sulphur geochemistry and the chemical events leading to the evolution of animals, and it is fully testable by detailed geochemical analyses of preserved deep-water marine sediments.
145klTimes Cited:530Cited References Count:29

North Atlantic gyre ventilation and intermediate water formation during the last glaciation and Younger Dryas - Marchitto, T. M.; Curry, W. B.; W, Oppo D. (Nature, 1998)
id: 208

Sea-level rise on eastern China's Yangtze delta - Chen, Z. Y.; Stanley, D. J. (Journal of Coastal Research, 1998)
The Yangtze delta is a densely populated, low-lying region highly vulnerable to flooding, high tides and typhoons. All previous studies indicated that relative sea level was higher from similar to 7500-4000 yrs. BP, then lowered and stabilized at about present msl during the past 3000 yrs. To the contrary, we find that sea level has been rising relative to the southern Yangtze delta plain based on new sea-level data derived from dated peats, reassessment of earlier sea-level curves and measurement of delta plain subsidence and analysis of prehistoric habitat bases from similar to 7000 to 3000 yrs. BP. Consequences of this relative rise include difficulty in expelling water from the low-lying delta plain to the coast and associated flood damage. Emplacement of the 3-Gorges Dam on the Yangtze will control flooding of the Yangtze river but decrease sediment accumulation on the delta plain that, in turn, is likely to accelerate saline inundation of this vital breadbasket.
Yt592Times Cited:46 Cited References Count:27
Keywords: delta flooding; Holocene; neolithic sites; peat; radiocarbon dates; relative sea level; sea-level curve; subsidence; taihu lake; yangtze delta

Three Holocene tephras identified in lacustrine sediment cores from the Wonder Lake area, Denali National Park and Preserve AK - Child, J. C.; Beget, J.; Werner, A. (Arctic and Alpine Research, 1998)
id: 235

Water-level changes in Lake Baikal, Siberia: Tectonics versus climate - Colman, S. M. (Geology, 1998)
id: 187

Yangtze delta inundation and the discontinuity between Neolithic and younger cultures, China - Stanley, D. J.; Chen, Z.; Song, J. (Geoarchaeology, 1998)
id: 228

Climate variation and the rise and fall of an Andean civilization - Binford, M. W.; Kolata, A. L.; Brenner, M.; Janusek, J. W.; Seddon, M. T.; Abbott, M.; Curtis, J. H. (Quaternary Research, 1997)
Paleolimnological and archaeological records that span 3500 years from Lake Titicaca and the surrounding Bolivian-Peruvian altiplano demonstrate that the emergence of agriculture (ca. 1500 B.C.) and the collapse of the Tiwanaku civilization (ca. A.D. 1100) coincided with periods of abrupt, profound climate change, The timing and magnitude of climate changes are inferred from stratigraphic evidence of lake-level variation recorded in C-14-dated lake-sediment cores. Paleolake levels provide estimates of drainage basin water balance. Archaeological evidence establishes spatial and temporal patterns of agricultural field use and abandonment. Prior to 1500 B.C., aridity in the altiplano precluded intensive agriculture. During a wetter period from 1500 B.C. to A.D. 1100, the Tiwanaku civilization and its immediate predecessors developed specialized agricultural methods that stimulated population growth and sustained large human settlements, A prolonged drier period (ca. A.D. 1100-1400) caused declining agricultural production, field abandonment, and cultural collapse. (C) 1997 University of Washington.
Wu887Times Cited:148Cited References Count:53

Determination of the radiocarbon ages of individual PAH extracted from urban aerosol and marine sediment - Pearson, A.; Eglinton, T. I.; McNichol, A. P.; Currie, L. A.; Schneider, R. J.; von Reden, K. F.; Benner, B. A.; Wise, S. A. (16th International Radiocarbon Conference, 1997)
id: 951

Late Quaternary climate, fire, and vegetation dynamics (Book Section) - Winkler, M. G. (Sediment Records of Biomass Burning and Global Change, 1997)
id: 134

Lignin phenols in sediments of Lake Baikal, Siberia: application to paleoenvironmental studies - Orem, W. H.; Colman, S. M.; Lerch, H. E. (Organic Geochemistry, 1997)
Sediments from three cores obtained from distinct depositional environments in Lake Baikal, Siberia were analyzed for organic carbon, total nitrogen and lignin phenol concentration and composition. Results were used to examine changes in paleoenvironmental conditions during climatic cycles of the late Quaternary (<125 ka). Average organic carbon, and total nitrogen concentrations, atomic C/N ratios and organic carbon accumulation rates were significantly higher in the Holocene compared with the late Pleistocene, reflecting overall warmer temperatures and increased runoff during the Holocene. A Holocene maximum in organic carbon was observed at about 6 ka, and may represent the warmest/wettest period of the Holocene. At one site (Academician Ridge) pronounced late Pleistocene maxima in organic carbon and biogenic silica were observed at about 80-85 ka, probably indicative of an interstadial period with enhanced aquatic productivity. Total sedimentary lignin phenol contents were generally lower in the late Pleistocene compared to the Holocene, but with several peaks in concentration during the late Pleistocene. These late Pleistocene peaks in total sedimentary lignin content (dated at about 80, 50 and 30 ka) directly precede or occur during peaks in sedimentary biogenic silica contents. These periods likely represent relatively warm interstadial times, with increased precipitation producing the observed increase in terrestrial runoff and aquatic productivity. Lignin phenol ratios (S/V, C/V and P/V) were used to examine changes in terrestrial vegetation type resulting from changes in paleoenvironmental conditions during the late Pleistocene. A degree of caution must be used in the interpretation of these ratios with regard to vegetation sources and paleoenvironmental conditions, because of potential compositional changes in lignin resulting from biodegradation. Nevertheless, results show that long glacial periods were characterized by terrestrial vegetation composed of a mix of non-woody angiosperm vegetation and minor gymnosperm forest. Shorter interstadial periods are defined by a change to dominant gymnosperm forest and were observed at about 80, 75, 63, 50 and 30 ka, ranging from about 2-6 kyr in duration. These interstadial periods of the late Pleistocene defined by lignin phenol ratios generally occur during longer periods of enhanced sedimentary biogenic silica content (about 10-15 ka in duration), providing corroborative evidence of these warm interstadial periods. (C) 1997 Elsevier Science Ltd.
Yq252Times Cited:29Cited References Count:61

Paleoclimatic implications of silicieous microfossil succession in late Quaternary sediments in Lake Baikal, Siberia - Julius, M. L.; Stoermer, E. F.; Colman, S. M.; Moore, T. C. (Journal of Paleolimnology, 1997)
id: 1354

Possible role of climate in the collapse of the Akkadian Empire: evidence from Gulf of Oman marine sediments - Cullen, H. (AGU Fall Meeting, 1997)
id: 1235

Preliminary paleoecology study of Salt Pond and Nauset Lagoon, Cape Cod National Seashore (Report) - Cole, K.; Winkler, M. G.; Sanford, P. R. (National Park Service, North Atlantic Region, 1997)
id: 131

Preliminary results of the first scientific drilling on Lake Baikal, Buguldeika site, southeastern Siberia - Colman, S.; Grachev, M.; Hearn, P.; Horie, S.; Kawai, T.; Kuzmin, M.; Logachov, N.; Fialkov, V.; Gorigljad, A.; Tomilov, B.; Khakhaev, B.; Kochikov, S.; et al. (Quaternary International, 1997)
The Baikal Drilling Project (BDP) is a multinational effort to investigate the paleoclimatic history and tectonic evolution of the Baikal sedimentary basin during the Late Neogene. In March 1993 the Baikal drilling system was successfuly deployed from a barge frozen into position over a topographic high, termed the Buguldeika saddle, in the southern basin of Lake Baikal. The BDP-93 scientific team, made up of Russian, American and Japanese scientists, successfully recovered the first long (>100 m) hydraulic piston cores from two holes in 354 m of water. High quality cores of 98 m (Hole 1) and 102 m (Hole 2), representing sedimentation over the last 500,000 years, were collected in 78 mm diameter plastic liners with an average recovery of 72% and 90%, respectively. Magnetic susceptibility logging reveals an excellent hole-to-hole correlation. In this report the scientific team describes the preliminary analytical results from BDP-93 hole 1 cores. Radiocarbon dating by accelerator mass spectrometry provides an accurate chronology for the upper portion of Hole 1. Detailed lithologic characteristics, rock magnetic properties and inorganic element distributions show a significant change to the depositional environment occuring at 50 m subbottom depth, approximately 250,000 BP. This change may be due to uplift and rotation of the horst block in the Buguldeika saddle. The sedimentary section above 50 m is pelitic with varve-like laminae, whereas the section below 50 m contains a high proportion of sand and gravel horizons often organized into turbidite sequences. Accordingly, high resolution seismic records reveal a change in sonic velocity at this depth. It is inferred that sedimentation prior to 250 ka BP was from the west via the Buguldeika river system. After 250 ka BP the Buguldeika saddle reflects an increase in hemipelagic sediments admired with fine-grained material from the Selenga River drainage basin, east of Lake Baikal. Variations in the spore-pollen assemblage, diatoms, biogenic silica content, rock magnetic properties, clay mineralogy and organic carbon in the upper 50 m of BDP-93-1 reveal a detailed record of climate change over approximately the last 250,000 years. These variables alternate in a pattern characteristic of glacial/interglacial climatic fluctuations. The present age model suggests that the climate signal recorded in Lake Baikal sediments is similar to Late Quaternary signals recorded in Chinese loess sections and in marine sediments. Copyright (C) 1996 INQUA/Elsevier Science Ltd
Vq100Times Cited:44 Cited References Count:29
Keywords: asia; tectonics

Productivity-induced sulphur enrichment of hydrocarbon-rich sediments from the Kimmeridge Clay Formation - Lallier-Verges, E.; Hayes, J. M.; Boussafir, M.; Zaback, D. A.; Tribovillard, N. P.; Connan, J.; Bertrand, P. (Chem Geol, 1997)
This work aims to highlight the relationship between primary productivity, sulphate reduction and organic carbon preservation in cyclic marine sediments from the Kimmeridge Clay Formation. A concomitant increase of the total sulphur content with the preserved organic content (TOC), shows the progressive supply of both metabolisable organic matter and resistant organic matter is linked to primary productivity. However, variations in sulphate reduction efficiency, based on elemental abundance and isotopic composition of sulphur, reveal that the proportion of metabolisable vs. resistant organic matter has varied along the cycles. This is interpreted in terms of the variation in organic delivery. Organic sulphur content is found to be proportional to the organic matter content, whereas concentrations of pyritic sulphur are constant at very high (> 10% TOC) values. This result is explained by a limitation of available iron for pyritisation at times of very high organic flux. Under such conditions, HS- in excess could be responsible for the early formation of organo-sulphur compounds and thus for the preservation of highly aliphatic (i.e. lipid-rich) organic matter.
Lallier-Verges, EHayes, J MBoussafir, MZaback, D ATribovillard, N PConnan, JBertrand, PengResearch Support, Non-U.S. Gov'tNetherlands1997/01/01 00:00Chem Geol. 1997;134:277-88.

Synchronous, high-frequency oscillations in tropical sea surface temperatures and North Atlantic Deep Water production during the last glacial cycle - Curry, W. B.; Oppo, D. W. (Paleoceanography, 1997)
Stable isotopic measurements of G. sacculifer and C. wuellerstorfi in a core from the western equatorial Atlantic imply that there are parallel, suborbital oscillations in surface water hydrography and deep water circulation occurring during oxygen isotope stages 2 and 3. Low values of G. sacculifer delta(18)O accompany high values of C. wuellerstorfi delta(13)C, linking warmer sea surface temperatures (SSTs) in the tropics with increased production of lower North Atlantic Deep Water (NADW). The amplitude of the delta(18)O oscillations is 0.6 parts per thousand (or 2 degrees-3 degrees C), which is superimposed on a glacial/interglacial amplitude of about 2.1 parts per thousand,. Using the G. sacculifer delta(18)O data, we calculate that surface waters were colder during stage 2 than calculated by CLIMAP [1976, 1981]. The longer-period (> 2 kyr) oscillations in air temperature recorded in the Greenland and Antarctic ice cores appear to correlate with oscillations in sea surface temperature in the equatorial Atlantic. The magnitude of these oscillations in tropical SST is too large to have resulted from changes in meridional heat transport caused by the global conveyor alone. The apparent synchroneity of equatorial SST and polar air temperature changes, as well as the amplitude of the SST changes at the equator, are consistent with the climate effects expected from changes in the atmosphere's greenhouse gas content (H(2)0(vapor), CO2, and CH4).
Wd891Times Cited:109Cited References Count:63

Western Great Lakes regional paleoenvironmental changes: island and inland contrasts - Winkler, M. G.; Sanford, P. R.; Cole, K. L.; Flakne, R. L. (Ecological Society of America Bulletin, 1997)
id: 1301

An 84-kyr paleomagnetic record from the sediments of Lake Baikal, Siberia - Peck, J. A.; King, J. W.; Colman, S. M.; Kravchinsky, V. A. (Journal of Geophysical Research-Solid Earth, 1996)
We have conducted a paleomagnetic study of sediment cores obtained from the Selenga prodelta region of Lake Baikal, Russia. This record, which spans approximately the last 84 kyr, contributes to a better understanding of the nature of geomagnetic field behavior in Siberia and is a useful correlation and dating tool. We demonstrate that the Lake Baikal sediments are recording variations in the geomagnetic field. The directional record displays secular variation behavior with a geomagnetic excursion at 20 ka and additional excursions appearing as large-amplitude secular variation at 41, 61, and 67 ka. Smoothing of the geomagnetic excursion behavior occurs in Lake Baikal sediments owing to the intermediate sedimentation rate (13 cm kyr(-1)). The Lake Baikal relative paleointensity record correlates to absolute paleointensity data for the last 10 kyr and to relative paleointensity records from the Mediterranean Sea and Indian Ocean for the last 84 kyr. This correlation suggests a strong global (i.e., dipole) component to these records and further supports the reliability of sediments as recorders of relative geomagnetic paleointensity. We show that a relative geomagnetic intensity stratigraphy has a potential resolution of 7 kyr by correlating continental and marine records. The geomagnetic intensity stratigraphy helps constrain the age of the difficult to date Lake Baikal sediments.
Ul090Times Cited:76Cited References Count:48

AMS radiocarbon analyses from Lake Baikal, Siberia: Challenges of dating sediments from a large, oligotrophic lake - Colman, S. M.; Jones, G. A.; Rubin, M.; King, J. W.; Peck, J. A.; Orem, W. H. (Quaternary Science Reviews, 1996)
A suite of 146 new accelerator-mass spectrometer (AMS) radiocarbon ages provides the first reliable chronology for late Quaternary sediments in Lake Baikal. In this large, highly oligotrophic lake, biogenic and authigenic carbonate are absent, and plant macrofossils are extremely rare. Total organic carbon is therefore the primary material available for dating. Several problems are associated with the TOC ages. One is the mixture of carbon sources in TOC, not all of which are syndepositional in age. This problem manifests itself in apparent ages for the sediment surface that are greater than zero. However, because most of the organic carbon in Lake Baikal sediments is algal (autochthonous) in origin, this effect is limited to about 1000+/-500 years, which can be corrected, at least for young deposits. The other major problem with dating Lake Baikal sediments is the very low carbon contents of glacial-age deposits, which makes them extremely susceptible to contamination with modern carbon. This problem can be minimized by careful sampling and handling procedures.The ages show almost an order of magnitude difference in sediment-accumulation rates among different sedimentary environments in Lake Baikal, from about 0.04 mm/year on isolated banks such as Academician Ridge, to nearly 0.3 mm/year in the turbidite depositional areas beneath the deep basin floors, such as the Central Basin. The new AMS ages clearly indicate that the dramatic increase in diatom productivity in the lake, as evidenced by increases in biogenic silica and organic carbon, began about 13 ka, in contrast to previous estimates of 7 ka for the age of this transition. Holocene net sedimentation rates may be less than, equal to, or greater than those in the late Pleistocene, depending on the site. This variability reflects the balance between variable terrigenous sedimentation and increased biogenic sedimentation during interglaciations. The ages reported here, and the temporal and spatial variation in sedimentation rates that they imply, provide opportunities for paleoenvironmental reconstructions at different time scales and resolutions. Published by Elsevier Science Ltd
Vp609Times Cited:112Cited References Count:29

Climate connections between the hemisphere revealed by deep sea sediment core ice core correlations - Charles, C. D.; LynchStieglitz, J.; Ninnemann, U. S.; Fairbanks, R. G. (Earth and Planetary Science Letters, 1996)
Correlation of Southern Ocean deep sea sediment core records with ice core records of polar climate delineates with unprecedented detail the relationship between high latitude climate and the ocean's thermohaline circulation over the last 80,000 years. Our observations suggest that, while North Atlantic Deep Water variability manifests itself clearly in Southern Ocean nutrient proxy records over periods as short as 500 yr, this deep water variability did not promote a direct link between climate variability in the high latitudes of the two hemispheres on millennial timescales. In particular, the proxy records indicate that, on average, northern hemisphere climate fluctuations lagged those of the southern hemisphere by 1500 yr.
Uz230Times Cited:201Cited References Count:33

Compound specific radiocarbon analysis as a tool to quantitatively apportion modern and fossil sources of polycyclic aromatic hydrocarbons in environmental matrices. - Eglinton, T. I.; Pearson, A.; McNichol, A. P.; Currie, L. A.; Benner, B. A.; Wise, S. A. (Abstracts of Papers of the American Chemical Society, 1996)
1Va915 Times Cited:0 Cited References Count:0

Direct U-Th dating of marine sediments from the two most recent interglacial periods - Slowey, N. C.; Henderson, G. M.; Curry, W. B. (Nature, 1996)
A KNOWLEDGE of the age of marine sediments is necessary to determine the timing of events and rates of processes in the marine realm, and the relationships among marine and other climatically sensitive records. The establishment of an accurate chronology for Pleistocene marine sediments beyond the range of radiocarbon dating (approximately the past 45 kyr) has therefore been a goal of palaeoceanographers for decades. Early attempts(1,2) based on measurements of the radionuclides Th-230 and Pa-231 mere beset with problems, and subsequent studies focused on tying fluctuations in marine sediment oxygen-isotope records to events such as the formation of col al reef terraces and changes in the Earth's magnetic polarity(3,4), and tuning the resultant chronologies to the Earth's orbitally driven insolation variations(5-8). But these chronologies (especially the age and duration of the last interglacial period) have been challenged by several studies(9-12), raising questions about the fundamental cause of Pleistocene climate fluctuations. Here we report the direct U-Th dating of aragonite-rich marine sediments from the Bahamas, and present an accurately dated marine oxygen-isotope record for the last two interglacials. We obtain dates of 120-127 kyr BP for the last interglacial and 189-190 kyr np for the late stage 7 interglacial. These dates are in accord with the general theory of orbitally forced climate fluctuations and demonstrate the potential of our direct-dating approach for developing an absolute chronology for the Pleistocene marine oxygen-isotope record.
Vh315Times Cited:39Cited References Count:40

East Asian monsoon variations; linkage to northern hemisphere millenniallll-scale climate oscillations - Oppo, D. W.; Deiner, L.; Curry, W. B.; Norris, R. D. (Supplement to EOS, 1996)
id: 56

Holocene climatic and human influences on lakes of the Yucatan Peninsula, Mexico: An interdisciplinary, palaeolimnological approach - Whitmore, T. J.; Brenner, M.; Curtis, J. H.; Dahlin, B. H.; Leyden, B. W. (Holocene, 1996)
We used palaeolimnological techniques to examine effects of Holocene climate change and human influence on lakes of the Yucatan Peninsula, Mexico. The three study lakes are located along a west-east transect that represents a gradient of increasing modern precipitation and density of former Maya settlement. At Lake Coba, an 880-cm sediment core yields a complete record of lacustrine sedimentation that began when the lake first filled similar to 8000 BP as groundwater level rose in response to rising sea level and increased precipitation. Diatom, ostracod, and delta(18)O evidence indicate that Lake Coba was initially shallow and saline. Coba, presently in the region of greatest rainfall, showed more episodic water-level changes than Lake San Jose Chulchaca or Lake Sayaucil. High lake level and fresh water were evident at 440 cm (similar to 2600 BP), followed by a decline in water levels and an increase in total ionic salinity to the present time. In a 613-cm core from Sayaucil, in the intermediate precipitation zone, total salinity was high between 600 and 400 cm (similar to 3050 and 2000 BP), followed by consistently higher water levels. Salinity was high in the lower portion of a 110-cm San Jose Chulchaca core (beginning similar to 1860 BP), followed by a gradual and consistent freshening of water to the present time.Trophic state changes and human influence on lakes were evaluated using diatom, delta(18)O, total P, sedimentary organic matter, and preliminary pollen data. Maximal human disturbance at Lake Coba, a densely settled Maya urban site, occurred during a deep-water event at 440 cm, followed by a decline in human influence and trophic state to the present time. Trophic state and linear sedimentation rates in Sayaucil increased significantly above 400 cm (after similar to 2000 BP), probably associated with initial Maya settlement near Xtojil and subsequent small-scale farming. Limnological disturbance may have preceded the period of maximal human occupation because initial land clearance and consequent soil erosion probably affected water quality substantially. San Jose Chulchaca lacks archaeological evidence of human occupation in the drainage, and shows gradual changes in trophic state not caused by human disturbance. With the exception of a C-14 date on wood from the base of the Coba core, C-14 dates and chronologies may be artificially old as a consequence of hard-water-lake error. Trophic state changes in the study lakes were generally consistent with known patterns of human settlement and population change. Late-Holocene water-level fluctuations were most pronounced in Lake Coba in eastern Yucatan, where modern rainfall is currently greatest, but lake level is generally lower than during much of the past. Lake level was relatively constant in Sayaucil in the central peninsula, whereas lake level in San Jose Chulchaca in the arid western portion of the peninsula increased gradually over time.
Vh189Times Cited:56Cited References Count:65

A Holocene vegetation history from lowland Guatemala - Islebe, G. A.; Hooghiemstra, H.; Brenner, M.; Curtis, J. H.; Hodell, D. A. (Holocene, 1996)
A 5.45-m core from Lake Peten-Irza, lowland Guatemala, contains a near-complete record of Holocene sedimentation. The age-depth relationship for the core is based on AMS C-14 dating of terrestrial wood fragments and provides a reliable chronology in this karst region where hard-water lake error has typically confounded sediment geochronology. In the basal part of the sequence, pollen of the Moraceae-Urticaceae group dominate, indicating the presence of widespread tropical forest during the early Holocene (c. 8600-5600 yr BP). Relative abundance of pollen of high forest taxa declined beginning as early as 5600 yr BP, indicating climatic drying or perhaps initial land clearance. Deforestation by prehistoric Mayan inhabitants is documented clearly in the pollen record beginning about 2000 pr BP (106 cal BC-122 cal Ao, 95.4%, 2 sigmas) by the appearance of disturbance taxa (e.g. Ambrosia and Poaceae) and presence of Zea. Forest regrowth occurred following the Classic Maya collapse, c. AD 900, as reflected by a relative increase in Moraceae-Urticaceae pollen.
Vh189Times Cited:103Cited References Count:44

Late holocene coastal plain stratigraphy and sea-level history at Hanalei, Kauai, Hawaiian islands - Calhoun, R. S.; Fletcher, C. H. (Quaternary Research, 1996)
Fluvial, marine, and mixed fluvial-marine deposition on the coastal plain of Hanalei Bay on the north shore of Kauai, Hawaii, records a middle- to late-Holocene fall of relative sea level. Radiocarbon dating of the regression boundary preserved in the stratigraphy of the coastal plain documents a seaward shift of the shoreline beginning at least 4800-4580 cal yr B.P. and continuing until at least 2160-1940 cal yr B.P. Marine sands stranded in the backshore and coastal plain environment are buried by fluvial floodplain and channel sands, silts, and muds. In places, erosion at the regression contact exposed older marine sands thus increasing the hiatus at the regression disconformity, The shoreline regression is best explained as the result of a fall in relative sea level. The age and elevation of the cored regression boundary at sites that have not been influenced by erosion are consistent with a middle-to late-Holocene highstand of relative sea level as predicted by geophysical models of whole Earth deformation related to deglaciation. (C) 1996 University of Washington.
Uf728Times Cited:21Cited References Count:35

Late Quaternary deep circulation in the western equatorial Atlantic (Book Section) - Curry, W. B. (The South Atlantic: Present and Past Circulation, 1996)
id: 1336

A long pollen record from lowland Amazonia: Forest and cooling in glacial times - Colinvaux, P. A.; DeOliveira, P. E.; Moreno, J. E.; Miller, M. C.; Bush, M. B. (Science, 1996)
A continuous pollen history of more than 40,000 years was obtained from a lake in the lowland Amazon rain forest. Pollen spectra demonstrate that tropical rain forest occupied the region continuously and that savannas or grasslands were not present during the last glacial maximum. The data suggest that the western Amazon forest was not fragmented into refugia in glacial times and that the lowlands were not a source of dust. Glacial age forests were comparable to modern forests but also included species now restricted to higher elevations by temperature, suggesting a cooling of the order of 5 degrees to 6 degrees C.
Vk748Times Cited:350Cited References Count:42

Neolithic migrations as a function of sea level-controlled topography in the Yangtze Delta, China - Stanley, D. J.; Chen, Zhongyuan (Geology, 1996)
id: 1282

One thousand years of change in the Great Lakes Region. A pilot project of the NBS Landscape Use History of North America (LUHNA) publ. electronically on the World Wide Web - Cole, K. L.; Davis, M. B.; Winkler, M. G. (1996)
id: 1323; http://www.nbs.gov/luhna/cole

Radiocarbon measurements of atmospheric volatile organic compounds: Quantifying the biogenic contribution - Klouda, G. A.; Lewis, C. W.; Rasmussen, R. A.; Rhoderick, G. C.; Sams, R. L.; Stevens, R. K.; Currie, L. A.; Donahue, D. J.; Jull, A. J. T.; Seila, R. L. (Environmental Science & Technology, 1996)
The radiocarbon (C-14) abundance of atmospheric volatile organic compounds (VOC) gives a quantitative estimate of contributions from biomass and fossil-mass sources, important information for effective regulation of ozone precursors. We report here details of a methodology to perform such measurements and the first exploratory C-14 results on VOC fractions separated from two composited urban tropospheric air samples, collected during the summer (1992) in Atlanta, GA. The upper limit of the percentage of VOC originating from biomass sources during the morning and evening hours in Atlanta were 9 and 17%, respectively, measurements reported at the 95% confidence level. However, due to the level of the process blank and its uncertainty, in both cases the percentage can be as low as zero. The results of these experiments, designed to (i) evaluate the entire [C-14]VOC measurement process and (ii) obtain reliable estimates of biogenic contributions to atmospheric VOC, emphasize how important controls are throughout this multi-step chemical process to ensure quality data.
Uc413Times Cited:26Cited References Count:25

Sedimentology of the Krakatau 1883 submarine pyroclastic deposits - Mandeville, C. W.; Carey, S.; Sigurdsson, H. (Bulletin of Volcanology, 1996)
The majority of tephra generated during the paroxysmal 1883 eruption of Krakatau volcano, Indonesia, was deposited in the sea within a 15-km radius of the caldera. Two syneruptive pyroclastic facies have been recovered in SCUBA cores which sampled the 1883 subaqueous pyroclastic deposit. The most commonly recovered facies is a massive textured, poorly sorted mixture of pumice and lithic lapilli-to-block-sized fragments set in a silty to sandy ash matrix. This facies is indistinguishable from the 1883 subaerial pyroclastic flow deposits preserved on the Krakatau islands on the basis of grain size and component abundances. A less common facies consists of well-sorted, planar-laminated to low-angle cross-bedded, vitric-enriched silty ash. Entrance of subaerial pyroclastic flows into the sea resulted in subaqueous deposition of the massive facies primarily by deceleration and sinking of highly concentrated, deflated components of pyroclastic flows as they traveled over water. The basal component of the deposit suggests no mixing with seawater as inferred from retention of the fine ash fraction, high temperature of emplacement, and lack of traction structures, and no significant hydraulic sorting of components. The laminated facies was most likely deposited from low-concentration pyroclastic density currents generated by shear along the boundary between the submarine pyroclastic flows and seawater. The Krakatau deposits are the first well-documented example of true submarine pyroclastic flow deposition from a modern eruption, and thus constitute an important analog for the interpretation of ancient sequences where subaqueous deposition has been inferred based on the facies characteristics of encapsulating sedimentary sequences.
Uk310Times Cited:57Cited References Count:59

Uranium-series disequilibrium, sedimentation, diatom frustules, and paleoclimate change in Lake Baikal - Edgington, D. N.; Robbins, J. A.; Colman, S. M.; Orlandini, K. A.; Gustin, M. P. (Earth and Planetary Science Letters, 1996)
The large volume of water, approximately one-fifth of the total surface fresh water on the planet, contained in Lake Baikal in southeastern Siberia is distinguished by having a relatively high concentration of uranium (ca. 2 nM), and, together with the surface sediments, an unusually high U-234/U-238 alpha activity ratio of 1.95. About 80% of the input of 234 uranium to the lake, with a U-234/U-238 ratio of 2.0, comes from the Selenga River, Profiles of uranium, as well as the extent of isotopic disequilibrium in a 9 m sediment core collected on Academic Ridge, generally show high values during interglacial periods corresponding to high diatom frustule numbers (DiFr) and biogenic silica (BSi) data that have been reported elsewhere. During glacial periods (low DiFr and BSi), uranium progeny (U-234 and Th-230) were in secular equilibrium with low concentrations of their parent U-238. Radionuclide distributions were interpreted in terms of a quantitative model allowing for adsorption of riverine inputs of uranium onto two classes of sedimenting particles with differing U-238/Th-232 ratios and uranium progeny in secular equilibrium. If the U-234/U-238 activity ratio of adsorbed uranium has remained constant, mean sedimentation rates can be independently estimated as 3.6 +/- 0.6 and 3.7 +/- 0.9 cm . kyr(-1) for the decay of U-234 and in-growth of Th-230, respectively. These rates are consistent with a mean rate of 3.76 cm . kyr(-1), calculated by optimization of the correspondence between adsorbed U-238 and delta(18)O in dated oceanic sediments, The adsorbed uranium apparently tracks variable river flow during interglacials and is drastically reduced during periods of glaciation. Evidently, uranium has not been significantly redistributed within Baikal sediments over at least the past 250 kyr and is a unique, biologically non-essential, tracer for climate-sensitive processes, which provide their own internal geochronometers, potentially useful for ages up to 1 Myr BP.
Uz230Times Cited:61Cited References Count:29

Continental climate response to orbital forcing from biogenic silica records in Lake Baikal, Siberia - Colman, S. M.; Peck, J. A.; B, Karabanov E.; Carter, S. J.; Bradbury, J. P.; King, J. W.; Williams, D. F. (Nature, 1995)
id: 1357

Developments at the NOSAMS Facility During 1995 - von Reden, K. F.; Cohen, G. J.; Dalton, M. J.; Peden, J. C.; Schneider, R. J. (Symposium of Northeastern Accelerator Personnel, 1995)
id: 1799

Glacial-Interglacial Differences in Circulation and Carbon Cycling within the Upper Western North-Atlantic - Slowey, N. C.; Curry, W. B. (Paleoceanography, 1995)
We investigated glacial-interglacial changes in the circulation and carbon cycling in the western North Atlantic subtropical gyre using hydrographic data and downcore records of the stable isotopic compositions of individual shells of Bahamian benthic foraminifera. Potential temperature-salinity-depth relations show that modern thermocline (similar to 200-1000 m) and deep (similar to 1000-2000 m) waters in the Providence Channels, Bahamas, originate in the Sargasso Sea and are typical of the subtropical gyre. Gradients in the stable isotopic compositions of late Holocene Planulina and Cibicidoides species from the bank margins (similar to 400 to 1500 m depth) reflect temperature, nutrient, and isotopic gradients of modern subtropical gyre waters. The difference between the delta(18)O of glacial maximum and late Holocene foraminifera is similar to 2.1 parts per thousand for the upper 900 m of the water column and similar to 1.6 parts per thousand for deeper waters, indicating that these waters were similar to 4 degrees C and similar to 2 degrees C cooler, respectively, during glacial time. The glacial temperature gradient (dT/dz) was similar to today, while the base of the thermocline was similar to 100 m shallower. These results differ significantly from our earlier results from multiple shell delta(18)O analyses, which implied upper thermocline waters were only similar to 1 degrees C cooler and dT/dz was greater during the glacial maximum. The difference occurs because bioturbation adversely affects multiple shell analyses of glacial-aged samples from shallow water depths. At all depths above 1500 m, foraminiferal delta(13)C are greater during the glacial maximum than the late Holocene by at least 0.1 to 0.2 parts per thousand (as much as 0.6 parts per thousand in the lower thermocline), indicating that nutrient concentrations throughout the thermocline were reduced and there was no oxygen minimum zone during the glacial maximum. This suggests greater, more uniform ventilation of the thermocline. Results of single and multiple shell delta(13)C analyses of glacial age foraminifera compare favorably because samples most affected by mixing correspond to water depths where the glacial-interglacial change of delta(13)C was small. Cooler upper ocean waters during the glacial maximum reflect cooler temperatures at the ocean surface where isopycnal surfaces outcrop, including large areas of the subtropical ocean. A shallower thermocline base is consistent with southward migration of the northern edge of the subtropical gyre or increased mode water production. Enhanced thermocline ventilation is consistent with more vigorous winds and all isopycnal surfaces outcropping in the area of Ekman downwelling.
Rm032Times Cited:80Cited References Count:86

North Atlantic Deep Water variability during stage 3 - Oppo, D. W.; Lehman, S. J.; Curry, J.; Lynch, Stieglitz; Fairbanks, R. G. (Eos, Transactions, American Geophysical Union, 1995)
id: 58

Possible Role of Climate in the Collapse of Classic Maya Civilization - Hodell, D. A.; Curtis, J. H.; Brenner, M. (Nature, 1995)
THE Maya civilization developed around 3,000 years ago in Mesoamerica, and after flourishing during the so-called Classic period, it collapsed around 750-900 AD(1). It has been speculated(2-6) that climate change may have played a part in this collapse. But efforts to reconstruct the last three millennia of Mesoamerican climate using palynological methods have met with equivocal success, because human-mediated deforestation has altered regional vegetation in ways that mimic climate shifts, making it difficult to discriminate between natural and anthropogenic changes(7-15). Here we use temporal variations in oxygen isotope and sediment composition in a 4.9-m sediment core from Lake Chichancanab, Mexico, to reconstruct a continuous record of Holocene climate change for the central Yucatan peninsula. The interval between 1,300 and 1,100 yr up (AD 800-1,000) was the driest of the middle to late Holocene epoch, and coincided with the collapse of Classic Maya civilization, This continuous climate proxy record thus provides evidence of climate deterioration in the Maya region during the terminal Classic period.
Rb101Times Cited:439Cited References Count:41

Radiocarbon Ages of Pre-Bomb Clams and the Hard-Water Effect in Lakes Michigan and Huron - Rea, D. K.; Colman, S. M. (Journal of Paleolimnology, 1995)
Five radiocarbon ages, all determined by accelerator mass spectrometry, have been obtained for two pre-bomb bivalves from Lake Michigan and one from Lake Huron. After correcting those ages for the fractionation of C-14 in calcite and for the radioactively inert CO2 in the atmosphere, we find residual ages, caused by the hard water effect, of about 250 years for Lake Michigan and 440 years for Lake Huron.
Rq668Times Cited:22Cited References Count:13

Tree Survival and Growth on Land Reclaimed in Accord with Public-Law-95-87 - Chaney, W. R.; Pope, P. E.; Byrnes, W. R. (Journal of Environmental Quality, 1995)
The objective of this study was to determine survival and growth of black walnut (Juglans nigra L.) and northern red oak (Quercus alba L.) 12 yr after planting on a surface-mined site in southern Indiana reclaimed according to specifications of Public Law 95-87, the Surface Mining Control and Reclamation Act of 1977. A stocking level adequate to meet the requirements for forest land use (1112 trees/ha, or 450 trees/acre) was attained only for black walnut and only if competing ground cover vegetation was controlled in the tree rows. Height of both tree species was significantly greater when ground cover vegetation was controlled during the first 2 yr, but the growth rate, approximately 10 cm/yr, was very slow.
Rj934Times Cited:17 Cited References Count:18

Automated Sample Processing at the National Ocean Sciences Ams Facility - Cohen, G. J.; Hutton, D. L.; Osborne, E. A.; vonReden, K. F.; Gagnon, A. R.; McNichol, A. P.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
The high throughput and high precision requirements for the NOSAMS facility have made it essential to automate many of the stages in sample processing. These automated procedures increase the sample capacity for the lab while reducing errors in sample preparation. Automation has also allowed sample histories to be recorded and saved in Sybase, a relational data base.
Nv547Times Cited:9Cited References Count:1

Biogenic Silica in Lake Baikal Sediments - Results from 1990-1992 American Cores - Carter, S. J.; Colman, S. M. (Journal of Great Lakes Research, 1994)
The Lake Baikal Paleoclimate Project is a joint Russian-American program established to study the paleoclimate of Central Asia. During three summer field seasons, duplicate Russian and American coves were taken at a number of sites in different sedimentary environments in the lake. Eight cores returned to the U.S. were quantitatively analyzed for biogenic silica using a single-step 5-hour alkaline leach, followed by dissolved silicon analysis by inductively-coupled-plasma atomic-emission spectroscopy. Sediments of Holocene age in these cores have biogenic silica maxima that range from about 15 to 80 percent. An underlying zone in each core with low biogenic-silica concentrations (0 to 5 percent) dates from the last glacial maximum. The transition from the last glaciation to the present interglaciation, recorded by biogenic silica, began about 13,000 years ago. Biogenic silica profiles from these cores appear to be a good measure of past diatom productivity and a useful basis for paleoclimatic interpretations.
Px453Times Cited:46 Cited References Count:20
Keywords: accumulation; Holocene; Lake Baikal; marine-sediments; opal; Paleoclimate; sediments; silica

Comparative-Study of Fe-C Bead and Graphite Target Performance with the National-Ocean-Science-Ams (Nosams) Facility Recombinator Ion-Source - Klinedinst, D. B.; McNichol, A. P.; Currie, L. A.; Schneider, R. J.; Klouda, G. A.; vonReden, K. F.; Verkouteren, R. M.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
An accelerator mass spectrometry (AMS) experiment was designed to investigate C-14 target performance for two target types over a range of isotopic concentrations and sample sizes, with a special focus on the ability to measure C-14 in environmental samples having only microgram amounts of carbon. The findings were positive, showing that precision, accuracy, and stability were adequate to determine C-14 to 1% or better in samples containing as little as 25 mug carbon. Satisfactory Poisson uncertainty and target stability were demonstrated down to a level of 7 mug carbon, but experimental data showed that accurate measurements at that level require detailed knowledge of blank variability and mass dependence of the modern carbon calibration factor.
Nv547Times Cited:23Cited References Count:13

Control and automation of the Accelerator Mass Spectrometry Facility at Woods Hole Oceanographic Institution - Cohen, G. C.; von Reden, K. F. (Symposium of Northeastern Accelerator Personnel, 1994)
id: 1649

Deglaciation, Lake Levels, and Meltwater Discharge in the Lake-Michigan Basin - Colman, S. M.; Clark, J. A.; Clayton, L.; Hansel, A. K.; Larsen, C. E. (Quaternary Science Reviews, 1994)
The deglacial history of the Lake Michigan basin, including discharge and routing of meltwater, is complex because of the interaction among (1) glacial retreats and re-advances in the basin (2) the timing of occupation and the isostatic adjustment of lake outlets and (3) the depositional and erosional processes that left evidence of past lake levels. In the southern part of the basin, a restricted area little affected by differential isostasy, new studies of onshore and offshore areas allow refinement of a lake-level history that has evolved over 100 years. Important new data include the recognition of two periods of influx of meltwater from Lake Agassiz into the basin and details of the highstands gleaned from sedimentological evidence. Major disagreements still persist concerning the exact timing and lake-level changes associated with the Algonquin phase, approximately 11,000 BP. A wide variety of independent data suggests that the Lake Michigan Lobe was thin, unstable, and subject to rapid advances and retreats. Consequently, lake-level changes were commonly abrupt and stable shorelines were short-lived. The long-held beliefs that the southern part of the basin was stable and separated from deformed northern areas by a hinge-line discontinuity are becoming difficult to maintain. Numerical modeling of the ice-earth system and empirical modeling of shoreline deformation are both consistent with observed shoreline tilting in the north and with the amount and pattern of modern deformation shown by lake-level gauges. New studies of subaerial lacustrine features suggest the presence of deformed shorelines higher than those originally ascribed to the supposed horizontal Glenwood level. Finally, the Lake Michigan region as a whole appears to behave in a similar manner to other areas, both local (other Great Lakes) and regional (U.S. east coast), that have experienced major isostatic changes. Detailed sedimentological and dating studies of field sites and additional development of geophysical models offer hope for reconciling the field data with our understanding of earth theology.
Qq080Times Cited:30Cited References Count:48

Glacial/interglacial slope sedimentation changes on the Pleistocene NJ margin, ODP Site 904A - Christensen, B. A.; Thunell, R.; Miller, K. G.; Smith, N.; Cockrell, K. (Eos, Transactions, American Geophysical Union, 1994)
id: 54

High resolution sediment changes on the Pleistocene NJ upper slope - Christensen, B. A.; Hoppie, B. W.; Miller, K. G.; Thunell, R. C.; Le, J. (Eos, Transactions, American Geophysical Union, 1994)
id: 53

Lake-Level History of Lake-Michigan for the Past 12,000 Years - the Record from Deep Lacustrine Sediments - Colman, S. M.; Forester, R. M.; Reynolds, R. L.; Sweetkind, D. S.; King, J. W.; Gangemi, P.; Jones, G. A.; Keigwin, L. D.; Foster, D. S. (Journal of Great Lakes Research, 1994)
Collection and analysis of an extensive set of seismic-reflection profiles and cores from southern Lake Michigan have provided new data that document the history of the lake basin for the past 12,000 years. Analyses of the seismic data, together with radiocarbon dating, magnetic, sedimentologic, isotopic, and paleontologic studies of core samples, have allowed us to reconstruct lake-level changes during this recent part of the lake's history.The post-glacial history of lake-level changes in the Lake Michigan basin begins about 11.2 ka with the fall from the high Calumet level, caused by the retreat of the Two Rivers glacier, which had blocked the northern outlet of the lake. This lake-level fall was temporarily reversed by a major influx of water from glacial Lake Agassiz (about 10.6 ka), during which deposition of the distinctive gray Wilmette Bed of the Lake Michigan Formation interrupted deposition of red glaciolacustrine sediment. Lake level then continued to fall, culminating in the opening of the North Bay outlet at about 10.3 ka. During the resulting Chippewa low phase, lake level was about 80 m lower than it is today in the southern basin of Lake Michigan. The rise of the early Holocene lake level, controlled primarily by isostatic rebound of the North Bay outlet, resulted in a prominent, planar, transgressive unconformity that eroded most of the shoreline features below present lake level. Superimposed on this overall rise in lake level, a second influx of water from Lake Agassiz temporarily raised lake levels an unknown amount about 9.1 ka. At about 7 ka, lake level may have fallen below the level of the outlet because of sharply drier climate. Sometime between 6 and 5 ka, the character of the lake changed dramatically, probably due mostly to climatic causes, becoming highly undersaturated with respect to calcium carbonate and returning primary control of lake level to the isostatically rising North Bay outlet. Post-Nipissing (about 5 ka) lake level has fallen about 6 m due to erosion of the Port Huron outlet, a trend around which occurred relatively small (+/- approximately 2 m), short-term fluctuations controlled mainly by climatic changes. These cyclic fluctuations are reflected in the sedimentological and sediment-magnetic properties of the sediments.
Nl348Times Cited:47 Cited References Count:29
Keywords: lake michigan; ostracodes; radiocarbon; sedimentology; sediments; southern

The limnological and climate history of Lake Michigan from ostracode, stable-isotope, and magnetic susceptibility records - Forester, R. M.; Colman, S. M.; Reynolds, R. L.; Jones, G. A.; Keigwin, L. D.; Foster, D. S. (Journal of Great Lakes Research, 1994)
id: 1358

Performance Characteristics of the 3-MV Tandetron AMS System at the National Ocean Sciences AMS Facility - von Reden, K. F.; Schneider, R. J.; Cohen, G. J.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B - Beam Interactions with Materials and Atoms, 1994)
id: 1619; PBS Record: 60; (03) KF Vonreden/Woods Hole Oceanog Inst/Natl Ocean Sci Accelerator/Mass Spectrometry Facil/Woods Hole, MA 02540 USA (42) English Article (44) NV547
Keywords: ACCELERATOR MASS-SPECTROMETER

A rock-magnetic record from Lake Baikal, Siberia: Evidence for Late Quaternary climate change - Peck, J. A.; King, J. W.; Colman, S. M.; Kravchinsky, V. A. (Earth and Planetary Science Letters, 1994)
id: 15

The Role of the Deep-Ocean in North-Atlantic Climate-Change between 70-Kyr and 130-Kyr Ago - Keigwin, L. D.; Curry, W. B.; Lehman, S. J.; Johnsen, S. (Nature, 1994)
THE suggestion(1) that changes in North Atlantic Deep Water (NADW) production are linked through surface heat flux to the atmospheric temperature over Greenland is supported by earlier indications(2,3) that NADW production decreased during glacial times, and by the subsequent finding(4-6) that it declined during the Younger Dryas cool period at the end of the last glaciation. Changes in North Atlantic surface temperatures have been found? to mirror high-frequency temperature changes recorded in Greenland ice cores over the past 80 kyr, but the connection to abyssal circulation has yet to be established, except for one or two isolated oscillations(8,9). Here we present carbon and oxygen isotope analyses of benthic foraminifera in a high-resolution North Atlantic deepsea sediment core for the period 70-130 kyr ago. These data allow us to reconstruct the history of NADW production, which shows a close correlation with Greenland climate variability for much of this time interval, suggesting that the climate influence of NADW variability was widespread. We see no evidence, however, for changes in NADW production during substage 5e (the Eemian interglacial period), in contrast with recent ice-core data(10) which suggest severe climate instability in Greenland during this time period. Our results may support suggestions, based on data from a second ice core, that this apparent instability is am artefact caused by ice flow(11). Alternatively, the Eemian climate instability may have had a different origin from the subsequent climate events.
Ph254Times Cited:159Cited References Count:32

A Sediment Budget for Southern Lake-Michigan - Source and Sink Models for Different Time Intervals - Colman, S. M.; Foster, D. S. (Journal of Great Lakes Research, 1994)
We have constructed a sediment budget for the southern Lake Michigan basin for sand and for mud during three time periods: the past 100, 5,000, and 10,000 years. For the modern (100-year) sediment budget, accountable sediment sources add up to 93 percent of the calculated sinks. The mud budget has a source deficit of about 40%, probably due to errors in mu&sand ratios and (or) to other sources not included in our model, especially erosion of the lake floor, which accompanies bluff recession. Two terms dominate the modem sediment-budget equation: (1) bluff erosion, which is an order of magnitude larger than either rivers or aerosols as a source, and (2) deposition in the deep basin, which is more than two orders of magnitude greater as a sink than suspended sediment transport out of the basin. About half of the sand derived from bluff erosion is deposited in the deep lake; the other half must be deposited in nearshore sand bodies, beaches, and dunes. Despite the uncertainties in our estimates of sediment sources and sinks, the attempt to reconstruct sediment budgets for time intervals of 100, 5,000, and 10,000 years leads to important insights about erosion and sedimentation processes. Bluff erosion is the dominant source of both sand and mud in the basin. The deep lake floor is the primary sink for mud, whereas both the deep lake and nearshore areas are important sinks for sand. On a long-term basis, rates of bluff erosion have progressively decreased and are apparently independent of anthropogenic effects. Rates of sediment accumulation in the lake basin mirror the decrease in rates of bluff erosion for prehistoric time, but have increased markedly since human settlement, probably because of anthropogenic effects on river and aerosolic inputs.
Nl348Times Cited:17 Cited References Count:29
Keywords: deposition; erosion; Holocene; lake michigan; sediment budget; sediments

Sources of Urban Contemporary Carbon Aerosol - Hildemann, L. M.; Klinedinst, D. B.; Klouda, G. A.; Currie, L. A.; Cass, G. R. (Environmental Science & Technology, 1994)
Emissions from the major sources of fine carbonaceous aerosol in the Los Angeles basin atmosphere have been analyzed to determine the amounts of the C-12 and C-14 isotopes present. From these measurements, an inventory of the fossil carbon and contemporary carbon particle emissions to the Los Angeles atmosphere has been created. In the winter, more than half of the fine primary carbonaceous aerosol emissions are from sources containing contemporary carbon, including fireplaces, charbroilers, paved road dust, cigarette smoke, and brake lining dust, while in the summer at least one-third of the carbonaceous particle emissions are contemporary. Using a mathematical model for atmospheric transport, predictions are made of the atmospheric fine particulate fossil carbon and contemporary carbon concentrations expected due to primary source emissions. Model predictions are in reasonable agreement with the measured radiocarbon content of the fine ambient aerosol samples. It is concluded that the high fraction of contemporary carbon measured historically in Los Angeles is not due to local emission sources of biogenic material; rather, it is due to a combination of local anthropogenic pollution sources and background marine aerosol advected into the city.
Pe258Times Cited:111Cited References Count:45

A synthesis of post-glacial diatom records from Lake Baikal - Bradbury, J. Platt; Bezrukova, Ye V.; Chernyaeva, G. P.; Colman, S. M.; Khursevich, G.; King, J. W.; Likoshway, Y. V. (Journal of Paleolimnology, 1994)
The biostratigraphy of fossil diatoms contributes important chronologic, paleolimnologic, and paleoclimatic information from Lake Baikal in southeastern Siberia. Diatoms are the dominant and best preserved microfossils in the sediments, and distinctive assemblages and species provide inter-core correlations throughout the basin at millennial to centennial scales, in both high and low sedimentation-rate environments. Distributions of unique species, once dated by radiocarbon, allow diatoms to be used as dating tools for the Holocene history of the lake. Diatom, pollen, and organic geochemical records from site 305, at the foot of the Selenga Delta, provide a history of paleolimnologic and paleoclimatic changes from the late glacial (15 ka) through the Holocene. Before 14 ka diatoms were very rare, probably because excessive turbidity from glacial meltwater entering the lake impeded productivity. Between 14 and 12 ka, lake productivity increased, perhaps as strong winds promoted deep mixing and nutrient regeneration. Pollen evidence suggests a cold shrub — steppe landscape dominated the central Baikal depression at this time. As summer insolation increased, conifers replaced steppe taxa, but diatom productivity declined between 11 and 9 ka perhaps as a result of increased summer turbidity resulting from violent storm runoff entering the lake via short, steep drainages. After 8 ka, drier, but more continental climates prevailed, and the modern diatom flora of Lake Baikal came to prominence. On Academician Ridge, a site of slow sedimentation rates, Holocene diatom assemblages at the top of 10-m cores reappear at deeper levels suggesting that such cores record at least two previous interglacial (or interstadial?) periods. Nevertheless, distinctive species that developed prior to the last glacial period indicate that the dynamics of nutrient cycling in Baikal and the responsible regional climatic environments were not entirely analogous to Holocene conditions. During glacial periods, the deep basin sediments of Lake Baikal are dominated by rapidly deposited clastics entering from large rivers with possibly glaciated headwaters. On the sublacustrine Academician Ridge (depth = 300 m), however, detailed analysis of the diatom biostratigraphy indicates that diastems (hiatuses of minor duration) and (or) highly variable rates of accumulation complicate paleolimnologic and paleoclimatic reconstructions from these records.
id: 16
Keywords: Climate change; diatoms; Holocene; Lake Baikal; paleolimnology; palynology

Two episodes of meltwater influx from glacial Lake Agassiz into the Lake Michigan basin: Contrasts in climatic and oceanographic effects - Colman, S. M.; Keigwin, L. D.; Forester, R. M. (Geology, 1994)
id: 189

Comparative study of Fe-C Bead vs. graphite target performance with the NOSAMS Facility recombinator ion source - Kleindinst, D. B.; McNichol, A. P.; Currie, L. A.; Jones, G. A.; Verkouteren, R. M.; von Reden, K. F.; Klouda, G. A.; Schneider, R. J. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 931

Laboratory automation at the National Ocean Sciences AMS Facility - Cohen, G. J.; Hutton, D. L.; von Reden, K. F.; Osborne, E. A.; McNichol, A. P.; Jones, G. A. (6th Internation Conference on Accelerator Mass Spectrometry, 1993)
id: 927

The National Ocean Sciences AMS Facility at Woods Hole Oceanographic Institution - Jones, G. A.; Schneider, R. J.; von Reden, K. F.; McNichol, A. P.; Gagnon, A. R.; Cohen, G. J.; Osborne, E. A.; Hutton, D. L.; Kessel, E. D.; Elder, K. L. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 930

Performance characteristics of the 3MV tandetron AMS system at the National Ocean Sciences AMS Facility - von Reden, K. F.; Schneider, R. J.; Cohen, G. J.; Jones, G. A. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 936

Radiocarbon ages from two submerged strandline features in the western Gulf of Maine and a sea-level curve for the northeastern Massachusetts coastal region - Oldale, R. N.; Colman, S. M.; Jones, G. A. (Quaternary Research, 1993)
id: 10

Radiocarbon dating of Lake Baikal sediments--A progress report - Colman, S. M.; Kuptsov, V. M.; Jones, G. A.; Carter, S. J. (Russian Geology and Geophysics, 1993)
id: 191

The AMS Accelerator at Woods Hole Oceanographic Institution - Schneider, R. J.; von Reden, K. F.; Cohen, G. J.; Jones, G. A. (Symposium of North Eastern Accelerator Personnel, 1992)
id: 1794

Climatic History and Darwinian Causes of High Amazonian Diversity - Colinvaux, P. (8th International Palynological Congress, Aix-en-Provence, France, 1992)
id: 904

Geochemistry of Precambrian carbonates: IV. Early Paleoproterozoic (2.25 +/-0.25 Ga) seawater - Veizer, J.; Clayton, K. R. N.; Hinton, R. W. (Geochimica et Cosmochimica Acta, 1992)
id: 1602

Initial Dating and Paleoenvironmental Results From Lake Baikal, Southeastern Siberia - Colman, S. M.; Karabanov, E. B.; Williams, D. F.; Hearn, P. P., Jr.; King, J. W.; Orem, W. H.; Bradbury, J. P.; Shanks, W. C., III; Jones, G. A.; Carter, S. J. (Abstracts With Programs of the American Quaternary Association, 1992)
id: 905

The National Ocean Sciences Accelerator Mass Spectrometer for Precision C-14 at Woods Hole Oceanographic Institution -- Status and new results - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P.; Cohen, G. J. (EOS, Transactions of the American Geophysical Union, 1992)
id: 926

The new National Ocean Sciences Accelerator Mass Spectrometer Facility at Woods Hole Oceanographic Institution-Progress and first results (Proceedings of the 14th International Radiocarbon Conference, 1991) - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P.; Cohen, G. J.; Purser, K. H. (Radiocarbon, 1992)
id: 1787

The new National Ocean Sciences Accelerator Mass Spectrometer Facility at Woods Hole Oceanographic Institution - Progress and First Results - von Reden, K. F.; Jones, G. A.; Schneider, R. J.; McNichol, A. P.; Cohen, G. J.; Purser, K. H. (14th International Radiocarbon Conference 1991, 1992)
id: 1618

The compressibility of silicate liquids containing Fe2O3 and the effect of composition, temperature, oxygen fugacity and pressure on their redox states - Kress, V. C.; Carmichael, I. S. E. (Contributions to Mineralogy and Petrology, 1991)
id: 1582

Quantification and characterization of porewater organic colloids - Chin, Y. P.; McNichol, A. P.; Gschwend, P. M. (Organic Substances and Sediments in Water. Processes and Analytical, 1991)
id: 1744